1,25-dihydroxyvitamin D3 inhibits corneal wound healing in an ex-vivo mouse model - Sel, Saadettin; Trau, Stefanie; Paulsen, Friedrich; Kalinski, Thomas; Stangl, Gabriele I.; Nass, Norbert (Graefes Archive For Clinical and Experimental Ophthalmology, 2016)
PURPOSE: Impaired healing of corneal injuries can result in ulceration and complete loss of vision, especially in the elderly. Such patients frequently also exhibit vitamin D insufficiency. 1,25-dihydroxyvitamin D3 is the active vitamin D metabolite. As it affects cell proliferation and inflammation, we herein aimed at elucidating its influence on corneal wound healing after alkali burn by using in vitro and ex vivo techniques. METHODS: mRNA abundance in human corneal epithelial cells in response to vitamin D3 was determined by RT-PCR. Corneal re-epithelialization after alkaline burn was analyzed using enucleated mouse eyes and fluorescein staining. RESULTS: Human corneal epithelial cells (HCEC) expressed the vitamin D receptor (VDR) and retinoid x receptor (RXR) and were responsive to 1,25- dihydroxyvitamin D3, as shown by induction of the 1,25- dihydroxyvitamin D3 responsive gene cyp-24A1 and slightly reduced abundance of IL-6 mRNA. However, no effect on cell vitality and migration was observed. In contrast, re-epithelialization of mouse corneas ex vivo was dose dependently inhibited by 1,25- dihydroxyvitamin D3. CONCLUSIONS: These data indicate that topically applied 1,25- dihydroxyvitamin D3 does not seem to be suitable for therapy of corneal lesions.
EVALuna2:35350

(1 -> 3)-beta-D-glucan and mannan guided early termination of antifungal therapy in ICU patients: a prospective randomized intervention study (REDUCE-AM) - Erb, T.; Mihai, Sidonia; Cipa, Franziska; Herbst, Larissa; Strauss, Richard; Castellanos, Ixchel; Lang, K.; Ganslmayer, Marion; Willam, Carsten; Rath, Anca; Diesch, Katharina; Held, Jürgen (MYCOSES, 2020)
CRIS-Team WoS Importer:2020-10-02

5-HT3A serotonin receptor in the gastrointestinal tract: the link between immune system and enteric nervous system in the digestive form of Chagas disease - De Oliveira, Jefferson Alvim; Freitas, Michelle A. R.; De Oliveira, Enio Chaves; Jabari, Samir; Brehmer, Axel; Morais Da Silveira, Alexandre Barcelos (Parasitology Research, 2019)
Chagas disease is caused by Trypanosoma cruzi and remains one of the most neglected diseases in Latin America. One of its clinical forms is Chagas megacolon. Despite being known for more than half a century, detailed causes are still obscure. Recent evidence indicates a close relationship between the immune system and the enteric nervous system in the etiology of chagasic megacolon pathology. It is believed that low expression of the 5-HT3A serotonin receptor on lymphocytes could be linked to megacolon development. To test this hypothesis, this work investigated the distribution of CD4, CD8, and CD20 lymphocytes and their 5-HT3A receptor expression. The results demonstrated that Chagas patients without megacolon present a higher expression of the 5-HT3A receptor in all analyzed lymphocytes compared with Chagas patients with megacolon. These data suggest that the high expression of this receptor may lead to immunomodulation and prevent the development of Chagas megacolon.
CRIS-Team WoS Importer:2019-04-09

(68)Ga]PSMA-HBED uptake mimicking lymph node metastasis in coeliac ganglia: an important pitfall in clinical practice - Krohn, Thomas; Verburg, Frederik A.; Pufe, Thomas; Neuhuber, Winfried; Vogg, Andreas; Heinzel, Alexander; Mottaghy, Felix M.; Behrendt, Florian F. (European Journal of Nuclear Medicine and Molecular Imaging, 2015)
To determine the frequency of seemingly pathological retroperitoneal uptake in the location of the coeliac ganglia in patients undergoing [(68)Ga]PSMA-HBED PET/CT.The study included 85 men with prostate cancer referred for [(68)Ga]PSMA-HBED PET/CT. The PET/CT scans were evaluated for the local finding in the prostate and the presence of lymph node metastases, distant metastases and coeliac ganglia. The corresponding standardized uptake values (SUV) were determined. SUVmax to background uptake (gluteal muscle SUVmean) ratios were calculated for the ganglia and lymph node metastases. Immunohistochemistry was performed on the ganglia.In 76 of the 85 patients (89.4%) at least one ganglion with tracer uptake was found. For the ganglia, SUVmax and SUVmax to background SUVmean ratios were 2.97 ± 0.88 and 7.98 ± 2.84 (range 1.57-6.38 and 2.83-30.6), respectively, and 82.8% of all ganglia showed an uptake ratio of >5.0. For lymph node metastases, SUVmax and SUVmax to background SUVmean ratios were 8.5 ± 7.0 and 23.31 ± 22.23 (range 2.06-35.9 and 5.25-115.8), respectively. In 35 patients (41.2%), no lymph node metastases were found but tracer uptake was seen in the ganglia. Immunohistochemistry confirmed strong PSMA expression in the ganglia.Coeliac ganglia show a relevant [(68)Ga]PSMA-HBED uptake in most patients and may mimic lymph node metastases.
EVALuna2:4151

ACCOMMODATION & PRESBYOPIA: MOVEMENTS OF THE ACCOMMODATIVE APPARATUS IN THE PRESENCE OF THE IRIS AND LENS - Croft, Mary Ann; Nork, T. Michael; Mcdonald, Jared P.; Heatley, Gregg A.; Lütjen-Drecoll, Elke; Kaufman, Paul L. (2017)
EVALuna2:35332

ACCOMMODATIVE APPARATUS: MOVEMENTS IN PHAKIC AND APHAKIC EYES, INTERCONNECTIONS WITH THE VITREOUS AND PRESBYOPIA - Croft, Mary Ann; Nork, T. Michael; Mcdonald, Jared; Heatley, Gregg A.; Lütjen-Drecoll, Elke; Kaufman, Paul L. (2016)
EVALuna2:35347

Accommodative movements of the choroid in the optic nerve head region of human eyes, and their relationship to the lens - Croft, Mary Ann; Peterson, John; Smith, Christopher; Kiland, Julie; Nork, T. Michael; Mcdonald, Jared P.; Katz, Alexander; Hetzel, Scott; Lütjen-Drecoll, Elke; Kaufman, Paul L. (Experimental Eye Research, 2022)
The ciliary muscle (CM) powers the accommodative response, and during accommodation the CM pulls the choroid forward in the region of the ora serrata. Our goal was to elucidate the accommodative movements of the choroid in the optic nerve region in humans and to determine whether these movements are related to changes in the lens dimensions that occur with aging, in the unaccommodated and accommodated state. Both eyes of 12 human subjects (aged 18–51 yrs) were studied. Homatropine (1 drop/5%) was used to relax the ciliary muscle (unaccommodated or “resting” eye) and pilocarpine was used to induce the maximum accommodative response (2 drops/4%) (accommodated eye). Images of the fundus and choroid were collected in the region of the optic nerve (ON) via Spectralis OCT (infrared and EDI mode), and choroidal thickness was determined. Ultrasound biomicroscopy (UBM; 50 MHz, 35 MHz) images were collected in the region of the lens/capsule and ciliary body. OCT and UBM images were collected in the resting and accommodated state. The unaccommodated choroidal thickness declined significantly with age (p = 0.0073, r = 0.73) over the entire age range of the subjects studied (18–51 years old). The choroidal thickness was significantly negatively correlated with lens thickness in the accommodated (p = 0.01) and the unaccommodated states (p = 0.005); the thicker the lens the thinner the choroid. Choroid movements around the optic nerve during accommodation were statistically significant; during accommodation the choroid both thinned and moved centrifugally (outward/away from the optic nerve head). The accommodative choroid movements did not decline significantly with age and were not correlated with accommodative amplitude. Measurement of the choroidal thickness is possible with the Spectralis OCT instrument using EDI mode and can be used to determine the accommodative changes in choroidal thickness. The choroidal thickness decreased with age and during accommodation. It may be that age-related choroidal thinning is due to changes in the geometry of the accommodative apparatus to which it is attached (i.e., ciliary muscle/lens complex) such that when the lens is thicker, the choroid is thinner. Accommodative decrease in choroidal thickness and stretch of the retina/choroid may indicate stress/strain forces in the region of the optic nerve during accommodation and may have implications for glaucoma.
CRIS-Team Scopus Importer:2022-09-16

Acknowledging the use of human cadaveric tissues in research papers: Recommendations from anatomical journal editors - Iwanaga, Joe; Singh, Vishram; Ohtsuka, Aiji; Hwang, Youngil; Kim, Hee Jin; Moryś, Janusz; Ravi, Kumar Satish; Ribatti, Domenico; Trainor, Paul A.; Sañudo, José Ramón; Apaydin, Nihal; Şengül, Gülgün; et al. (Clinical Anatomy, 2020)
Research within the anatomical sciences often relies on human cadaveric tissues. Without the good will of these donors who allow us to use their bodies to push forward our anatomical knowledge, most human anatomical research would come to a standstill. However, many research papers omit an acknowledgement to the donor cadavers or, as no current standardized versions exist, use language that is extremely varied. To remedy this problem, 19 editors-in-chiefs from 16 anatomical journals joined together to put together official recommendations that can be used by authors when acknowledging the donor cadavers used in their studies. The goal of these recommendations is to standardize the writing approach by which donors are acknowledged in anatomical studies that use human cadaveric tissues. Such sections in anatomical papers will not only rightfully thank those who made the donation but might also encourage, motivate, and inspire future individuals to make such gifts for the betterment of the anatomical sciences and patient care.
CRIS-Team Scopus Importer:2020-09-18
Keywords: anatomy; cadavers; dissection; medical ethics; recommendation; research

A common variant mapping to CACNA1A is associated with susceptibility to exfoliation syndrome - Aung, Tin; Ozaki, Mineo; Mizoguchi, Takanori; Allingham, R. Rand; Li, Zheng; Haripriya, Aravind; Nakano, Satoko; Uebe, Steffen; Harder, Jeffrey M.; Chan, Anita S. Y.; Lee, Mei Chin; Burdon, Kathryn P.; et al. (Nature Genetics, 2015)
Exfoliation syndrome (XFS) is the most common recognizable cause of open-angle glaucoma worldwide. To better understand the etiology of XFS, we conducted a genome-wide association study (GWAS) of 1,484 cases and 1,188 controls from Japan and followed up the most significant findings in a further 6,901 cases and 20,727 controls from 17 countries across 6 continents. We discovered a genome-wide significant association between a new locus (CACNA1A rs4926244) and increased susceptibility to XFS (odds ratio (OR) = 1.16, P = 3.36 × 10(-11)). Although we also confirmed overwhelming association at the LOXL1 locus, the key SNP marker (LOXL1 rs4886776) demonstrated allelic reversal depending on the ancestry group (Japanese: OR(A allele) = 9.87, P = 2.13 × 10(-217); non-Japanese: OR(A allele) = 0.49, P = 2.35 × 10(-31)). Our findings represent the first genetic locus outside of LOXL1 surpassing genome-wide significance for XFS and provide insight into the biology and pathogenesis of the disease.
EVALuna2:9286

A comprehensive multi-domain dataset for mitotic figure detection - Aubreville, Marc; Wilm, Frauke; Stathonikos, Nikolas; Breininger, Katharina; Donovan, Taryn A.; Jabari, Samir; Veta, Mitko; Ganz, Jonathan; Ammeling, Jonas; van Diest, Paul J.; Klopfleisch, Robert; Bertram, Christof A. (Scientific Data, 2023)
The prognostic value of mitotic figures in tumor tissue is well-established for many tumor types and automating this task is of high research interest. However, especially deep learning-based methods face performance deterioration in the presence of domain shifts, which may arise from different tumor types, slide preparation and digitization devices. We introduce the MIDOG++ dataset, an extension of the MIDOG 2021 and 2022 challenge datasets. We provide region of interest images from 503 histological specimens of seven different tumor types with variable morphology with in total labels for 11,937 mitotic figures: breast carcinoma, lung carcinoma, lymphosarcoma, neuroendocrine tumor, cutaneous mast cell tumor, cutaneous melanoma, and (sub)cutaneous soft tissue sarcoma. The specimens were processed in several laboratories utilizing diverse scanners. We evaluated the extent of the domain shift by using state-of-the-art approaches, observing notable differences in single-domain training. In a leave-one-domain-out setting, generalizability improved considerably. This mitotic figure dataset is the first that incorporates a wide domain shift based on different tumor types, laboratories, whole slide image scanners, and species.
CRIS-Team Scopus Importer:2023-08-04

Acriflavine-Functionalized Silica@Manganese Ferrite Nanostructures for Synergistic Radiation and Hypoxia Therapies - Eckenberger, Elisabeth; Raczka, Theodor; Neuhuber, Winfried; Distel, Luitpold; Klein, Stefanie (ACS Applied Bio Materials, 2023)
Mesoporous and nonmesoporous SiO2@MnFe2O4 nanostructures were loaded with the hypoxia-inducible factor-1 inhibitor acriflavine for combined radiation and hypoxia therapies. The X-ray irradiation of the drug-loaded nanostructures not only triggered the release of the acriflavine inside the cells but also initiated an energy transfer from the nanostructures to surface-adsorbed oxygen to generate singlet oxygen. While the drug-loaded mesoporous nanostructures showed an initial drug release before the irradiation, the drug was primarily released upon X-ray radiation in the case of the nonmesoporous nanostructures. However, the drug loading capacity was less efficient for the nonmesoporous nanostructures. Both drug-loaded nanostructures proved to be very efficient in irradiated MCF-7 multicellular tumor spheroids. The damage of these nanostructures toward the nontumorigenic MCF-10A multicellular spheroids was very limited because of the small number of nanostructures that entered the MCF-10A spheroids, while similar concentrations of acriflavine without nanostructures were toxic for the MCF-10A spheroids.
CRIS-Team Scopus Importer:2023-09-29
Keywords: drug delivery; hypoxia; magnetic mesoporous silica@MnFe2O4 nanoparticles; magnetic silica@MnFe2O4 nanoparticle acriflavine; multicellular tumor spheroids; radiation therapy

Activation of the trigeminal system as a likely target of SARS-CoV-2 may contribute to anosmia in COVID-19 - Meßlinger, Karl; Neuhuber, Winfried; May, Arne (Cephalalgia, 2021)
Clinical publications show consistently that headache is a common symptom in the coronavirus disease of 2019 (COVID-19). Several studies specifically investigated headache symptomatology and associated features in patients with COVID-19. The headache is frequently debilitating with manifold characters including migraine-like characteristics. Studies suggested that COVID-19 patients with headache vs. those without headache are more likely to have anosmia. We present a pathophysiological hypothesis which may explain this phenomenon, discuss current hypotheses about how the coronavirus SARS-CoV-2 enters the central nervous system and suggest that activation of the trigeminal nerve may contribute to both headache and anosmia in COVID-19.
CRIS-Team Scopus Importer:2021-08-27
Keywords: anosmia; Coronavirus disease; headache; olfactory; trigeminal

Acute colonic flexures: the basis for developing an artificial intelligence-based tool for predicting the course of colonoscopy - Wozniak, Slawomir; Pawlus, Aleksander; Grzelak, Joanna; Chobotow, Slawomir; Paulsen, Friedrich; Olchowy, Cyprian; Zaleska-Dorobisz, Urszula (Anatomical Science International, 2022)
Tortuosity of the colon is an important parameter for predicting the course of colonoscopy. Computed tomography scans of the abdominal cavity were performed in 224 (94 female, 130 male) adult subjects. The number of acute (angle not exceeding 90°) bends between adjacent colonic segments was noted and analyzed. Data were analyzed for correlation with gender, age, height and weight. An artificial intelligence algorithm was proposed to predict the course of colonoscopy. We determined the number of acute flexions in females to be 9.74 ± 2.5 (min–max: 4–15) and in males to be 8.7 ± 2.75 (min–max: 4–20). In addition, more acute flexions were found in women than in men and in older women (after 60 years) and men (after 80 years) than in younger ones. We found the greatest variability in the number of acute flexures in the sigmoid colon (0–9), but no correlation was found between the number of acute flexures and age, gender, height or BMI. In the transverse colon, older and female subjects had more flexures than younger and male subjects, respectively. Older subjects had more acute flexures in the descending colon than younger subjects. There are opportunities to use the number of acute flexures (4–7, 8–12, more than 12 flexures) to classify patients into appropriate risk categories for future incomplete colonoscopy. On this basis, we predicted troublesome colonoscopies in 14.9% female and in 6.1% male subjects.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Artificial intelligence; Colon; Colon flexures; CT scans

A deep learning-based histopathology classifier for Focal Cortical Dysplasia - Vorndran, Jörg; Neuner, Christoph; Coras, Roland; Hoffmann, Lucas; Geffers, Simon; Honke, Jonas; Herms, Jochen; Roeber, Sigrun; Hamer, Hajo; Brandner, Sebastian; Hartlieb, Till; Pieper, Tom; et al. (Neural Computing & Applications, 2023)
A light microscopy-based histopathology diagnosis of human brain specimens obtained from epilepsy surgery remains the gold standard to confirm the underlying cause of a patient’s focal epilepsy and further inform postsurgical patient management. The differential diagnosis of neocortical specimens in the realm of epilepsy surgery remains, however, challenging. Herein, we developed an open access, deep learning-based classifier to histopathologically assess whole slide microscopy images (WSI) and to automatically recognize various subtypes of Focal Cortical Dysplasia (FCD), according to the ILAE consensus classification update of 2022. We trained a convolutional neuronal network (CNN) with fully digitalized WSI of hematoxylin–eosin stainings obtained from 125 patients covering the spectrum of mild malformation of cortical development (mMCD), mMCD with oligodendroglial hyperplasia in epilepsy (MOGHE), FCD ILAE Type 1a, 2a and 2b using 414 formalin-fixed and paraffin-embedded archival tissue blocks. An additional series of 198 postmortem tissue blocks from 59 patients without neurological disorders served as control to train the CNN for homotypic frontal, temporal and occipital areas and heterotypic Brodmann areas 4 and 17, entorhinal cortex and dentate gyrus. Special stains and immunohistochemical reactions were used to comprehensively annotate the region of interest. We then programmed a novel tile extraction pipeline and graphical dashboard to visualize all areas on the WSI recognized by the CNN. Our deep learning-based classifier is able to compute 1000 × 1000 µm large tiles and recognizes 25 anatomical regions and FCD categories with an accuracy of 98.8% (F1 score = 0.82). Microscopic review of regions predicted by the network confirmed these results. This deep learning-based classifier will be made available as online web application to support the differential histopathology diagnosis in neocortical human brain specimens obtained from epilepsy surgery. It will also serve as blueprint to build a digital histopathology slide suite addressing all major brain diseases encountered in patients with surgically amenable focal epilepsy.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Classification; Convolutional neuronal network; Cortex; Deep learning; Digital pathology; Epilepsy; FCD1; FCD2; mMCD; MOGHE

Affinity Tag Coating Enables Reliable Detection of Antigen-Specific B Cells in Immunospot Assays - Koppert, Sebastian; Wolf, Carla; Becza, Noemi; Sautto, Giuseppe A.; Franke, Fridolin; Kürten, Stefanie; Ross, Ted M.; Lehmann, Paul; Kirchenbaum, Greg A. (Cells, 2021)
Assessment of humoral immunity to SARS-CoV-2 and other infectious agents is typically restricted to detecting antigen-specific antibodies in the serum. Rarely does immune monitoring entail assessment of the memory B-cell compartment itself, although it is these cells that engage in secondary antibody responses capable of mediating immune protection when pre-existing antibodies fail to prevent re-infection. There are few techniques that are capable of detecting rare antigen-specific B cells while also providing information regarding their relative abundance, class/subclass usage and functional affinity. In theory, the ELISPOT/FluoroSpot (collectively ImmunoSpot) assay platform is ideally suited for antigen-specific B-cell assessments since it provides this information at single-cell resolution for individual antibody-secreting cells (ASC). Here, we tested the hypothesis that antigen-coating efficiency could be universally improved across a diverse set of viral antigens if the standard direct (non-specific, low affinity) antigen absorption to the membrane was substituted by high-affinity capture. Specifically, we report an enhancement in assay sensitivity and a reduction in required protein concentrations through the capture of recombinant proteins via their encoded hexahistidine (6XHis) affinity tag. Affinity tag antigen coating enabled detection of SARS-CoV-2 Spike receptor binding domain (RBD)-reactive ASC, and also significantly improved assay performance using additional control antigens. Collectively, establishment of a universal antigen-coating approach streamlines characterization of the memory B-cell compartment after SARS-CoV-2 infection or COVID-19 vaccinations, and facilitates high-throughput immune-monitoring efforts of large donor cohorts in general.
CRIS-Team WoS Importer:2021-09-03

Age- and Sex-Dependent Changes of Intra-articular Cortical and Trabecular Bone Structure and the Effects of Rheumatoid Arthritis - Simon, David; Kleyer, Arnd; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Hueber, Axel; Haschka, Judith; Renner, Nina; Figueiredo, Camille; Neuhuber, Winfried; Buder, Thomas; Englbrecht, Matthias; et al. (Journal of Bone and Mineral Research, 2016)
The objective of this cross-sectional study was to define normal sex- and age-dependent values of intra-articular bone mass and microstructures in the metacarpal heads of healthy individuals by high-resolution peripheral quantitative computed tomography (HR-pQCT) and test the effect of rheumatoid arthritis (RA) on these parameters. Human cadaveric metacarpal heads were used to exactly define intra-articular bone. Healthy individuals of different sex and age categories and RA patients with similar age and sex distribution received HR-pQCT scans of the second metacarpal head and the radius. Total, cortical, and trabecular bone densities as well as microstructural parameters were compared between 1) the different ages and sexes in healthy individuals; 2) between metacarpal heads and the radius; and 3) between healthy individuals and RA patients. The cadaveric study allowed exact definition of the intra-articular (intracapsular) bone margins. These data were applied in measuring intra-articular and radial bone parameters in 214 women and men (108 healthy individuals, 106 RA patients). Correlations between intra-articular and radial bone parameters were good (r = 0.51 to 0.62, p < 0.001). In contrast to radial bone, intra-articular bone remained stable until age 60 years (between 297 and 312 mg HA/cm(3) ) but decreased significantly (p < 0.001) in women thereafter (237.5 ± 44.3) with loss of both cortical and trabecular bone. Similarly, RA patients showed significant (p < 0.001) loss of intra-articular total (263.0 ± 44.8), trabecular (171.2 ± 35.6), and cortical bone (610.2 ± 62.0) compared with sex- and age-adjusted controls. Standard sex- and age-dependent values for physiological intra-articular bone were defined. Postmenopausal state and RA led to significant decrease of intra-articular bone. © 2016 American Society for Bone and Mineral Research.
EVALuna:33251

Aged hind-limb clasping experimental autoimmune encephalomyelitis models aspects of the neurodegenerative process seen in multiple sclerosis - Cahill, Lindsay S.; Zhang, Monan Angela; Ramaglia, Valeria; Whetstone, Heather; Sabbagh, Melika Pahlevan; Yi, Tae Joon; Woo, Laura; Przybycien, Thomas S.; Moshkova, Marina; Zhao, Fei Linda; Rojas, Olga L.; Gomes, Josephine; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Experimental autoimmune encephalomyelitis (EAE) is the most common model of multiple sclerosis (MS). This model has been instrumental in understanding the events that lead to the initiation of central nervous system (CNS) autoimmunity. Though EAE has been an effective screening tool for identifying novel therapies for relapsing-remitting MS, it has proven to be less successful in identifying therapies for progressive forms of this disease. Though axon injury occurs in EAE, it is rapid and acute, making it difficult to intervene for the purpose of evaluating neuroprotective therapies. Here, we describe a variant of spontaneous EAE in the 2D2 T cell receptor transgenic mouse (2D2+ mouse) that presents with hind-limb clasping upon tail suspension and is associated with T cell-mediated inflammation in the posterior spinal cord and spinal nerve roots. Due to the mild nature of clinical signs in this model, we were able to maintain cohorts of mice into middle age. Over 9 mo, these mice exhibited a relapsing-remitting course of hind-limb clasping with the development of progressive motor deficits. Using a combined approach of ex vivo magnetic resonance (MR) imaging and histopathological analysis, we observed neurological progression to associate with spinal cord atrophy, synapse degradation, and neuron loss in the gray matter, as well as ongoing axon injury in the white matter of the spinal cord. These findings suggest that mild EAE coupled with natural aging may be a solution to better modeling the neurodegenerative processes seen in MS.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Multiple sclerosis model; Neurodegeneration; Progressive

Age-related posterior ciliary muscle restriction - A link between trabecular meshwork and optic nerve head pathophysiology - Croft, Mary Ann; Lütjen-Drecoll, Elke; Kaufman, Paul L. (Experimental Eye Research, 2017)
The ciliary muscle plays a major role in controlling both accommodation and outflow facility in primates. The ciliary muscle and the choroid functionally form an elastic network that extends from the trabecular meshwork all the way to the back of the eye and ultimately attaches to the elastic fiber ring that surrounds the optic nerve and to the lamina cribrosa through which the nerve passes. The ciliary muscle governs the accommodative movement of the elastic network. With age ciliary muscle mobility is restricted by progressively inelastic posterior attachments and the posterior restriction makes the contraction progressively isometric; placing increased tension on the optic nerve region. In addition, outflow facility also declines with age and limbal corneoscleral contour bows inward. Age-related loss in muscle movement and altered limbal corneoscleral contour could both compromise the basal function of the trabecular meshwork. Further, recent studies in non-human primates show that the central vitreous moves posteriorly all the way back to the optic nerve region, suggesting a fluid current and a pressure gradient toward the optic nerve. Thus, there may be pressure and tension spikes on the optic nerve region during accommodation and these pressure and tension spikes may increase with age. This constellation of events could be relevant to glaucomatous optic neuropathy. In summary, our hypothesis is that glaucoma and presbyopia may be literally linked to each other, via the choroid, and that damage to the optic nerve may be inflicted by accommodative intraocular pressure and choroidal tension "spikes", which may increase with age.
EVALuna2:35334

Aggregated neutrophil extracellular traps occlude Meibomian glands during ocular surface inflammation - Mahajan, Aparna; Hasíková, Lenka; Hampel, Ulrike; Grüneboom, Anika; Shan, Xiaomei; Herrmann, Irmgard; Garreis, Fabian; Bock, Felix; Knopf, Jasmin; Singh, Jeeshan; Mahajan, Siddharth; Leppkes, Moritz; et al. (Ocular Surface, 2021)
Purpose: Obstructive Meibomian gland dysfunction (MGD) is one of the leading causes of evaporative dry eye disease. Meibomian glands at the eyelid secrete lipids that prevent evaporation of the aqueous tear film. The pathogenesis of obstructive MGD is incompletely understood to date. Herein, we aim to investigate the pathogenesis of obstructive MGD using murine and human samples with various forms of ocular surface inflammation. Method: The presence of Neutrophil extracellular Traps (NETs) was detected with immunofluorescence analysis of ocular surface discharge and biopsy samples from patients with blepharitis. Tear fluid from patients with MGD and blepharitis were evaluated for the presence of inflammatory mediators using bead based immunoassay. Murine model of allergic eye disease (AED) was performed to investigate the role of NETs in MG occlusion. Results: we show that the ocular discharge from patients with blepharitis contains aggregated neutrophil extracellular traps (aggNETs). Furthermore, the ducts of human Meibomian glands affected by blepharitis were largely congested by aggNETs. Tear fluid from patients with MGD showed elevated neutrophil chemoattractants (C5a, IL6, IL8 and IL18). C5a and IL8 correlated with the degree of deficiency of tear fluid. In the murine model of allergic eye disease (AED), aggNETs accumulated in the MG leading to occlusion of their ducts and the retrograde pent-up of the fluid followed by acinar atrophy. Constraining aggNET formation by genetic or pharmacological inhibition of peptidyl arginine deiminase type 4 (PADI4) effectively reduced MG damage. Conclusion: We conclude that aggNETs occlude MG causing MGD after ocular surface inflammation.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Blepharitis; Meibomian gland dysfunction (MGD); Neutrophil extracellular traps (NETs); Occlusion

Alarin in different human intestinal epithelial cell types - Jabari, Samir; Schrödl, Falk; Kaser-Eichberger, Alexandra; Kofler, Barbara; Brehmer, Axel (Histochemistry and Cell Biology, 2019)
Alarin (AL), a new member of the galanin family, has been localized in various CNS regions, mainly in rodents. Among other effects, it modulates food intake. Therefore, we analyzed the immunohistochemical distribution pattern of AL in human intestinal epithelia. Cryosections of 12 human bowel samples were immunohistochemically double-stained for AL and α-defensin 5 (αD; first set). Two further sets of sections were quadruple-stained either (second set) for AL, chromogranin (CG), synaptophysin (SY), and somatostatin (SO) or (third set) for AL, CG, Peptide Y (PY), and 5-hydroxytryptamine (5-HT). Slides were digitized and quantitative analysis of co-localization rates was undertaken. Small bowel: most of AL-positive cells (56%) were αD-positive Paneth cells located within the base of the crypts (first set). In the second set, about 27% of AL-labeled cells were co-reactive for SY and CG, likely representing entero-endocrine cells. In the third set, the largest subpopulation of AL-positive cells was not co-reactive for other markers applied (89%); most of them were likely Paneth cells. Large bowel: co-localization of AL with αD was not detected (first set). In the second set, AL was frequently co-localized with the other three markers applied (68%). In the third set, AL was frequently co-localized with 5-HT and CG (31%) as well as with PY and 5-HT (22%). Due to its presence in various enteroendocrine as well as Paneth cells, AL may be involved in different physiological and pathological processes.
CRIS-Team Scopus Importer:2019-06-07
Keywords: Alarin; Enteroendocrine cells; Epithelial cells; Galanin family; Paneth cells

Altered Surfactant Protein Expression in Primary Acquired Nasolacrimal Duct Obstruction - Mohammad, Javed Ali; Bráuer, Lars; Schicht, Martin; Paulsen, Friedrich (Ophthalmic Plastic and Reconstructive Surgery, 2019)
PURPOSE: To investigate the presence and distribution patterns of 6 surfactant proteins in lacrimal drainage tissues of patients with primary acquired nasolacrimal duct (NLD) obstruction. METHODS: The presence and distribution of surfactant proteins (SP)-G and SP-H was first assessed in normal cadaveric lacrimal systems. The study was then performed in 10 samples of lacrimal sac and the respective NLDs obtained from patients suffering from primary acquired NLD obstruction who underwent either a dacryocystorhinostomy or a dacryocystectomy. The lacrimal sac samples were further divided into fundus and body, soon after their removal. Immunohistochemical labeling was performed for assessing the presence and distribution of SPs: SP-A, SP-B, SP-C, SP-D, SP-G/SFTA2, and SP-H/SFTA3. The results were then scored as positive or negative and the distribution pattern, if any, within the lacrimal sac and NLDs was assessed. Human lung tissues were used as controls. RESULTS: SP-H was demonstrated in the lining epithelia of the normal lacrimal drainage systems, whereas SP-G was uniformly negative. Immunohistochemical labeling revealed wide variations in the staining patterns of different SPs in different regions of the lacrimal sac and the NLD. SP-D and SP-G revealed uniformly negative immunoreactivity. Variable staining patterns were also noted between the superficial and basal layers of the lining epithelia. However, the goblet cells and intraepithelial mucous glands did not express any of the SPs. CONCLUSIONS: This study provides a proof of principle for the presence of SP-H and absence of SP-G in the normal lacrimal drainage systems. In cases of primary acquired nasolacrimal duct obstruction, there were alterations or loss of SP expression in the lining epithelia of the lacrimal sac and NLDs, reflecting their possible role in the etiopathogenesis of primary acquired nasolacrimal duct obstruction.In cases of primary-acquired nasolacrimal duct obstruction, the expression of multiple surfactant proteins was either deranged or lost in the lining epithelium of the lacrimal sac and nasolacrimal ducts.
CRIS-Team Scopus Importer:2019-11-15

A major review on disorders of the animal lacrimal drainage systems: Evolutionary perspectives and comparisons with humans - Mohammad, Javed Ali; Rehorek, Susan J.; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2019)
Purpose: To provide a systematic review of the literature on the disorders and management of the lacrimal drainage system (LDS) in few of the species of the animal kingdom. Methods: The authors performed a PubMed search of all articles that were published in English with specific reference to lacrimal drainage disorders in animals. Data captured include demographics, presentations, investigation, diagnoses and management modalities. Emphasis was also on anatomical differences, evolutionary perspectives and addressing the lacunae and potential directions for future research. Results: The lacrimal drainage system is a terrestrial adaptation in vertebrates. Evolutionary development of the LDS is closely linked to the Harderian gland and the vomeronasal organ. Variable differences in the clinical presentations and management of lacrimal drainage disorders (LDD) are noted in comparison to humans. These are secondary to unique structural and pathophysiological differences. Uniformity in usage and reporting of disease terminologies is required. Diagnostic challenges in clinical examination can be met with the development of customized lacrimal instruments. Contrast dacryocystorhinography is a very useful investigation in the diagnosis of LDD. Multiple bypass procedures like conjunctivorhinostomy, conjunctivobuccostomy and conjunctivomaxillosinosotomy have been described for nasolacrimal duct obstruction (NLDO). Advances of endoscopy and radiological techniques are paralleled by minimally invasive lacrimal interventions. The search for an ideal animal model for human LDS is far from over and the choice of the animal needs to be customized based on the research objectives. Conclusion: The lacrimal drainage system is an ancestral feature in tetrapod vertebrates and it is present, in some form or another, in most descendant species. The lacrimal drainage system has evolved considerably, adapting to the needs of the species. It is essential to understand the lacrimal drainage disorders of domestic animals so that the animal and human lacrimal sciences contribute more meaningfully to each other.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Animal; Dacryology; Disease; Lacrimal; Lacrimal sac; Nasolacrimal duct

A MINIMAL-INVASIVE METHOD TO RETRIEVE AND IDENTIFY ENTHESEAL TISSUE FROM PSORIATIC ARTHRITIS PATIENTS - Raimondo, Maria Gabriella; Pachowsky, Milena; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Soare, A.; Bräuer, Lars; Rech, Jürgen; Simon, David; Kleyer, Arnd; Schett, Georg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Analyzing the transmission of visible light through electrospun nanofibrous PCL scaffolds - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Nordic Polymer Days, Helsinki (Finland), 2021, 2021)

Anatomical and radiological features of the bone organization of the anterior part of the mandible - Vasil'ev, Yuriy; Paulsen, Friedrich; Dydykin, Sergey (Annals of Anatomy-Anatomischer Anzeiger, 2020)
Background: The classical anatomical representation of the lingual relief of the mental region of the mandible reflects the presence of geniohyoid as well as genioglossus attachment areas, which are divided into two or single areas. The International Anatomical Terminology (contains references to the presence of upper and lower spinae mentales, but the terminology does not reflect the content of these structures. The aim of this study was to examine and classify the lingual canals of the mental region. Materials and methods: Using a Sirona ORTHOPHOS XG 3D tomograph (isotropic voxel size 0.1 in high-resolution mode) and KaVo 3D eXam cone beam computed tomography, the mental region of the mandible was analyzed in 561 patients aged 18–75 years with regard to bone density and the occurrence of a canal opening on the lingual side of the mandible. In order to visualize the mental spine area, another 50 mandibles were analyzed, divided into two groups of 25 mandibels each: 25 native and 25 dry preparations. Results: By prevalence the following channel types were classified: in 33% type I (narrow); in 32% type II (double) and of these in 17.5% (convergent) and type IIb in 14.5% a type IIb subtype (non-convergent); in 14% type III (wide); in 12% type IV (hook-shaped) and in 9% type V (diverging channel), identifying three combined components: the system of channels of the superior and inferior mental spine, and the transversal intraosseous canal of the mental region of the mandible. Conclusions: Our anatomical and radiological approach allowed us to suggest a new classification of intraosseous organization of the anterior part of the human mandible. As a result of studying X-ray anatomical and anatomical-topographical, constitutional-based, structural features of the mandible, intraosseous structures of the anterior mandible were clarified and classified, which solve not only terminological disputes, but also are important clinical guidelines for bone surgery, prosthetics, traumatology, endodontic treatment, dental implantation and local anesthesia.
CRIS-Team Scopus Importer:2020-04-21
Keywords: Bone; Mandible; Mental spine; Terminology; X-ray

Anatomical study of all carpal and adjoining bones of the wrist using 3D CT reconstruction –Finding the ultimate biomechanical theory - Gill, Dominik; Lyer, Stefan; Alexiou, Christoph; Fried, Frederik; Buder, Thomas; Neuhuber, Winfried; Jacxsens, Matthijs; Horch, Raymund E.; Arkudas, Andreas (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Background: The complex interplay of single wrist bones acting in combination with their ligamentous connections is still not fully understood. In this regard various theories exist, divisible in columnar and ring/row theories. The object of this study was to examine the mobility of the individual carpal bones as well as the ulna and metacarpals relative to each other in wrists of cadaveric hands using CT scans. Methods: The regular wrist mobility of a total of 21 cadaveric hands was examined by CT imaging in neutral position, radial/ulnar abduction as well as wrist flexion and extension. The data were evaluated as 3D models by using a standardized global coordinate system and object coordinate systems. Rotation and translation of each carpal bone as well as radius/ulna and all metacarpal bones were evaluated. Results: The principal motion took place in the carpus between the radius and the proximal carpal row followed by the midcarpal joint and the carpometacarpal joints and not mainly between the individual bones of a row. The scaphoid moves out of its row aggregate mainly during flexion and adapts to the motion of the distal carpal row. The trapezium and first metacarpal bones play a specific role detached from the remaining bones. Conclusions: With this study, a better understanding of the motion of the individual bones of the carpus, the metacarpals and the radius/ulna is shown. The study supports the row theory, where most motion takes place between the individual rows and not between the carpal bones, leaving the scaphoid and the first ray in a special role between the rows.
CRIS-Team Scopus Importer:2022-03-18
Keywords: 3-dimensional Computed Tomography; Biomechanical Theory; Wrist

Anatomical variations of the biceps brachii insertion: a proposal for a new classification. - Szewczyk, B.; Paulsen, Friedrich; LaPrade, Robert F.; Borowski, A.; Zielinska, N.; Olewnik, (Folia Morphologica, 2023)
BACKGROUND: The biceps brachii (BB) muscle is one of the three muscles located in the anterior compartment of the arm. Its insertion consists of two parts. The first part - main tendon - attached in the radial tuberosity and the second part - lacertus fibrosus (LF) - in the fascia of the forearm flexors. The intention of research was to reveal the morphological diversity of the insertion of this muscle. Thanks to the results of this work, have been created a classification of the distal attachment of BB. The results of that research can be used to further develop surgical procedures in the given region. MATERIALS AND METHODS: Eighty (40 left, and 40 right, 42 female, 38 male) upper limbs fixed in 10% formalin solution were examined. RESULTS: We observed three types of the insertion of the BB. Type I was characterised by a single tendon and occurred most frequently in 78.75% of the examined limbs. The second most common type was type II which was characterised by a double tendon and was observed in 13.75% of all the limbs. The last and least common was type III which was characterised by three tendons and occurred in 7.5% of the examined limbs. Additionally, the type of LF was analysed. In 8 (10%) specimens it was absent, i.e. in 2 specimens with type II insertion and 6 specimens with type III (p = 0.0001). Therefore, it may be deduced that type III BB insertion tendon predisposes to LF deficiency. CONCLUSIONS: The BB tendon is characterised by high morphological variability. The new classification proposes three types of distal attachment: type I - one tendon; type II - two separated band-shaped tendons; type III - three separated band-shaped tendons. The presence of type III BB tendon predisposes to a lack of LF.
EVALuna2:515784
Keywords: biceps brachii; biceps brachii tendon; lacertus fibrosus; bicipital aponeurosis; new classification

Anatomical variations of the tibialis anterior tendon - Karauda, Piotr; Podgórski, Michał; Paulsen, Friedrich; Polguj, Michał; Olewnik, Łukasz (Clinical Anatomy, 2020)
Introduction: The tibialis anterior muscle originates from the medial part of the anterior compartment, from the upper two-thirds of the lateral surface of the tibia and the adjacent part of the interosseous membrane, and typically inserts to the medial cuneiform and first metatarsal bone. The goal of the study was to examine the insertion of the tibialis anterior tendon and create a classification in human fetuses. Materials and methods: Fifty spontaneously-aborted human fetuses (26 male, 24 female, 100 lower limbs), aged 18–38 weeks of gestation at death were examined. Results: The classification comprised five types of tibialis anterior tendon insertion. The most common was Type V (60%), which was characterized by a single tendon inserting onto the medial cuneiform bone. The second most frequent was Type I (19%), which was characterized by a tendon which split into two equal-sized parts that insert to the medial cuneiform bone and the base of the first metatarsal. The third was Type II (12%), which was characterized by a tendon splitting into two different-sized parts that inserted onto the medial cuneiform bone (larger component) and the base of the first metatarsal (smaller component). The fourth type was Type III (5%), which was also characterized by a tendon splitting into two different-sized parts that inserted onto the medial cuneiform bone (smaller component) and the base of the first metatarsal (larger component). Finally, Type VI (4%), the least frequent type, was characterized by a tendon splitting into three different-sized parts, inserting onto the medial cuneiform bone (the smallest component) and the base of the first metatarsal (the middle and larger component). Conclusion: The tibialis anterior muscle is characterized by high variability in the approach of its tendon to the foot, at least in fetuses. This is classified in the present study for the first time.
CRIS-Team Scopus Importer:2020-09-25
Keywords: anatomical variations; fetuses; new classification; tibialis anterior muscle; tibialis anterior tendon

Anatomical variations of the tibialis anterior tendon insertion: An updated and comprehensive review - Zielinska, Nicol; Tubbs, Richard Shane; Paulsen, Friedrich; Szewczyk, Bartłomiej; Podgórski, Michał; Borowski, Andrzej; Olewnik, Łukasz (Journal of Clinical Medicine, 2021)
The tibialis anterior muscle originates on the lateral condyle of the tibia, on the upper two-thirds of the lateral surface of this bone, on the anterior surface of the interosseous membrane and on the deep surface of the fascia cruris. The distal attachment is typically at the medial cuneiform and first metatarsal. However, the tibialis anterior tendon can vary morphologically in both adults and fetuses. Different authors have created new classification systems for it. The main aim of this review is to present condensed information about the tibialis anterior tendon based on the available literature. Another aim is to compare classification systems and the results of previous studies.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Diagnosis; Fetuses; New classification; Systematic review; Tendon rupture; Tibialis anterior muscle

Anatomy and blood supply of the sternum - Neuhuber, Winfried; Lyer, Stefan; Alexiou, Christoph; Buder, Thomas (Deep Sternal Wound Infections, 2017)
The sternum is a sword-shaped flat bone about 15-17 cm long in the adult (? Fig. 2.1) (Putz and Müller-Gerbi Benninghoff 2003; Williams and Warwick 1980). Its cranial part, the manubrium, connects to the corpus by a synchondrosis in 90% of adults; in the remaining 10% there is a bony fusion (synostosis).
CRIS-Team Scopus Importer:2022-06-27
Keywords: Alba; Corti; Iodine; Ster; Synostosis

Anatomy and physiology of the nasolacrimal ducts - Paulsen, Friedrich; Garreis, Fabian; Schicht, Martin; Bräuer, Lars; Ali, M. J.; Sel, Saadettin (HNO, 2016)
Ophthalmologists and interventional radiologists are not the only professionals for whom diseases of the efferent tear duct system occupy centre stage; this applies also to ENT specialists involving endonasal conservative or surgical treatment. On the basis of current knowledge and taking account of results yielded by own research in recent years and of clinical aspects, we here give an overview of basic knowledge on the anatomy and physiology of the nasolacrimal system. In doing so functional aspects regarding tear transport as well as embryological and pathophysiological issues are integrated.
EVALuna2:34492

Anatomy in times of pandemia – Impact on teaching and body donations - Tschernig, Thomas; Bechmann, Ingo; Meier, Carola; Paulsen, Friedrich; Waschke, Jens; Westermann, Jürgen; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2021)
CRIS-Team Scopus Importer:2021-09-03
Keywords: Anatomy; Body donations; Dissection courses; SARS-CoV-2; Teaching

Anatomy-related ratios predict colonoscopy incompleteness in similar examination conditions - Wozniak, Slawomir; Kempinski, Radoslaw; Grzelak, Joanna; Domagala, Zygmunt; Paulsen, Friedrich (Advances in Clinical and Experimental Medicine, 2020)
Background. Screening colonoscopy is one of the most popular modalities for screening and surveillance of colorectal cancer and other colon disorders.
CRIS-Team WoS Importer:2020-06-19

Anconeus epitrochlearis muscle (epitrochlearisanconeus muscle; Musculus epitrochleoanconeus) with cubital tunnel syndrome – a rare but relevant clinical entity - Grüner, Jasmin; Paulsen, Friedrich; Barth, Anna; Horch, Raymund E. (Annals of Anatomy-Anatomischer Anzeiger, 2023)
Background: Compression of the ulnar nerve at the elbow within the cubital tunnel is related to the anatomical structures and is generally believed to be caused by Osborne's ligament (also known as the cubital retinaculum). However, in rare cases an anatomical variation of the developmental peculiarity of a remaining anconeus epitrochlearis muscle may be responsible for the disease. Methods: We present a series of five cases in which an anconeus epitrochlearis muscle was found as the cause of illness. Results: All patients presented with typical symptoms of numbness and tingling in the hand and ulnar fingers, and recurring pain as well as weakness of the ulnar innervated muscles. With neurophysiologically confirmed diminished nerve conduction velocity and unsuccessful conservative treatment, surgical decompression revealed an anconeus epitrochlearis muscle as the reason of compression. Full symptom relief was achieved immediately after the procedure in all cases. Conclusions: This article strives to call attention to this entity when diagnosing ulnar nerve compression. Myectomy and medial epicondylectomy is the preferred treatment option in such cases.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Cubital tunnel syndrome; Musculus anconeus epitrochlearis; Musculus epitrochleoanconeus; Sulcus ulnaris

A new, highly precise measurement technology for the in vitro evaluation of the accuracy of digital imaging data - von Wilmowsky, Cornelius; Bergauer, Bastian; Nkenke, Emeka; Neukam, Friedrich Wilhelm; Neuhuber, Winfried; Lell, Michael; Keller, Andrea; Eitner, Stephan; Matta, Ragai-Edward (Journal of Cranio-Maxillofacial Surgery, 2015)
Three-dimensional radiological imaging data play an increasingly role in planning, simulation, and navigation in oral and maxillofacial surgery. The aim of this study was to establish a new, highly precise, in vitro measurement technology for the evaluation of the geometric accuracy down to the micrometric range of digital imaging data.A macerated human mandible was scanned optically with an industrial, non-contact, white light scanner, and a three-dimensional (3D) model was obtained, which served as a master model. The mandible was then scanned 10 times by cone beam computed tomography (CBCT), and the generated 3D surface bone model was virtually compared with the master model. To evaluate the accuracy of the CBCT scans, the standard deviation and the intraclass coefficient were determined.A total of 19 measurement points in 10 CBCT scans were investigated, and showed an average value of 0.2676 mm with a standard deviation of 0.0593 mm. The standard error of the mean was 0.0043 mm. The intraclass correlation coefficient (ICC) within the 10 CBCT scans was 0.9416.This highly precise measuring technology was demonstrated to be appropriate for the evaluation of the accuracy of digital imaging data, down to the micrometric scale. This method is able to exclude human measurement errors, as the software calculates the superimposition and deviation. Thus inaccuracies caused by measurement errors can be avoided. This method provides a highly precise determination of deviations of different CBCT parameters and 3D models for surgical, navigational, and diagnostic purposes. Thus, surgical procedures and the post-operative outcomes can be precisely simulated to benefit the patient.
EVALuna2:4148

A New Immortalized Human Lacrimal Gland Cell Line - Gleixner, Sophie; Zahn, Ingrid; Dietrich, Jana; Singh, Swati; Drobny, Alice; Schneider, Yanni; Schwendner, Raphael; Socher, Eileen; Blavet, Nicolas; Bräuer, Lars; Gostian, Antoniu-Oreste; Balk, Matthias; et al. (Cells, 2024)
The lacrimal gland is crucial for maintaining ocular health by producing the aqueous component of the tear film, which hydrates and nourishes the ocular surface. Decreased production of this component results in dry eye disease, a condition affecting over 250 million people worldwide. However, the scarcity of primary human material for studying its underlying mechanisms and the absence of a cell model for human lacrimal gland epithelial cells present significant challenges. Here, we describe the generation of immortalized human lacrimal gland cell lines through the introduction of an SV40 antigen. We successfully isolated and characterized three cell clones from a female lacrimal gland donor, confirming their epithelial identity through genomic and protein analyses, including PCR, RNAseq, immunofluorescence and cultivation in a 3D spheroid model. Our findings represent a significant advancement, providing improved accessibility to investigate the molecular pathogenesis mechanisms of dry eye disease and potential therapeutic interventions. We identified the expression of typical epithelial cell marker genes and demonstrated the cells’ capability to form 2D cell sheets and 3D spheroids. This establishment of immortalized human lacrimal gland cells with epithelial characteristics holds promise for future comprehensive studies, contributing to a deeper understanding of dry eye disease and its cellular mechanisms.<br
Keywords: lacrimal gland; epithelial cells; immortalized; cell line; dry eye; tears; tear secretion

A New Organotypic 3D Slice Culture of Mouse Meibomian Glands Reveals Impact of Melanocortins - Zahn, Ingrid; Garreis, Fabian; Schicht, Martin; Rötzer, Vera; Waschke, Jens; Liu, Yuqiuhe; Altersberger, Valerian; Paulsen, Friedrich; Dietrich, Jana (International Journal of Molecular Sciences, 2022)
The meibomian glands (MGs) within the eyelids produce a lipid-rich secretion that forms the superficial layer of the tear film. Meibomian gland dysfunction (MGD) results in excessive evaporation of the tear film, which is the leading cause of dry eye disease (DED). To develop a research model similar to the physiological situation of MGs, we established a new 3D organotypic slice culture (OSC) of mouse MGs (mMGs) and investigated the effects of melanocortins on exocrine secretion. Tissue viability, lipid production and morphological changes were analyzed during a 21-day cultivation period. Subsequently, the effects on lipid production and gene expression were examined after stimulation with a melanocortin receptor (MCR) agonist, α-melanocyte-stimulating hormone (α-MSH), and/or an MCR antagonist, JNJ-10229570. The cultivation of mMGs OSCs was possible without impairment for at least seven days. Stimulation with the MCR agonists induced lipid production in a dose-dependent manner, whereas this effect was tapered with the simultaneous incubation of the MCR antagonist. The new 3D OSC model is a promising approach to study the (patho-) physiological properties of MG/MGD while reducing animal studies. Therefore, it may accelerate the search for new treatments for MGD/DED and lead to new insights, such as that melanocortins likely stimulate meibum production.
CRIS-Team Scopus Importer:2022-12-23
Keywords: 3D cell culture model; dry eye disease; meibomian gland; meibomian gland dysfunction; melanocortin receptor; organotypic slice culture; vibratome; α-MSH

A novel natural GRAS-grade enteric coating for pharmaceutical and nutraceutical products - Khoder, Mouhamad; Schropp, Verena; Zeitler, Susanne; Pereira, Beatriz; Habashy, Rober; Royall, Paul G.; Wang, Julie Tzu Wen; Alhnan, Mohamed A. (International Journal of Pharmaceutics, 2020)
In this study, enteric coatings based exclusively on naturally occurring ingredients were reported. Alginate (Alg) and pectin (Pec) blends with or without naturally occurring glyceride, glycerol monostearate (GMS), were initially used to produce solvent-casted films. Incorporating GMS in the natural polymeric films significantly enhanced the acid-resistance properties in gastric medium. Theophylline tablets coated with Alg-Pec blends without GMS disintegrated shortly after incubation in gastric medium (pH 1.2), leading to a premature and complete release of theophylline. Interestingly, tablets coated with Alg-Pec blends that contain the natural glyceride (GMS) resisted the gastric environment for 2 h with minimal drug release (<5%) and disintegrated rapidly following introduction to the intestinal medium, allowing a fast and complete drug release. Furthermore, the coating system proved to be stable for six months under accelerated conditions. These findings are particularly appealing to nutraceutical industry as they provide the foundation to produce naturally-occurring GRAS based enteric coatings.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Code oil; Delayed-release; Enteric-coatings; Gastro-resistant; Nutraceuticals; Probiotics

Ansa cervicalis - A new classification approach - Shvedavchenko, Anatoly I.; Oganesyan, Marine V.; Hammer, Christian; Paulsen, Friedrich; Bakhmet, Anastasia A. (Annals of Anatomy-Anatomischer Anzeiger, 2019)
Normally, the inferior root of Ansa cervicalis passes around the internal jugular vein and runs in an anterior direction to meet the superior root ventral to the common carotid artery. However, anatomical variants of the Ansa cervicalis are as yet not well investigated and understood. To close this gap the present study was undertaken. The Ansa cervicalis was examined in 54 human formalin-fixed cadavers and preparations of the head and neck by conventional dissection. In 66% of the specimens the Ansa cervicalis displayed the typical course that was classified as "internal type" (located medial to the internal jugular vein inside the carotid sheath). The remaining 34% pertained to the "external type" of the Ansa cervicalis (lateral to the internal jugular vein). The distance of the Ansa cervicalis relative to the superior margin of the thyroid cartilage was measured in every specimen. The external type Ansa cervicalis was located significantly lower than the internal type relative to the superior margin of thyroid cartilage. Regarding its location relative to the internal jugular vein four variants of combinations of the external and internal types of Ansa cervicalis on the right and left sides were distinguished. Based on their distance from the superior margin of the thyroid cartilage three types of Ansa cervicalis were defined. (C) 2018 Elsevier GmbH. All rights reserved.
CRIS-Team WoS Importer:2019-04-18

Antibody cross-reactivity between casein and myelin-associated glycoprotein results in central nervous system demyelination - Chunder, Rittika; Weier, Alicia; Mäurer, Hannah; Luber, Nicolas; Enders, Michael; Luber, Gabriele; Heider, Thorsten; Spitzer, Alfred; Tacke, Sabine; Becker-Gotot, Janine; Kurts, Christian; Iyer, Radhika; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Significance Multiple sclerosis (MS) is the most prevalent autoimmune disease of the central nervous system (CNS), leading to irreversible deficits in young adults. Its pathophysiology is believed to be influenced by environmental determinants. As far back as the 1990s, it had been suggested that there is a correlation between the consumption of cow's milk and the prevalence of MS. Here, we not only demonstrate that a high percentage of MS patients harbor antibodies to bovine casein but also that antibody cross-reactivity between cow's milk and CNS antigens can exacerbate demyelination. Our data broaden the current understanding of how diet influences the etiology of MS and set the stage for combining personalized diet plans with disease-modifying treatment strategies.
CRIS-Team Scopus Importer:2022-03-11
Keywords: antibodies; casein; cross-reactivity; multiple sclerosis; myelin-associated glycoprotein

Antibody Levels Poorly Reflect on the Frequency of Memory B Cells Generated following SARS-CoV-2, Seasonal Influenza, or EBV Infection - Wolf, Carla; Köppert, Sebastian; Becza, Noémi; Kürten, Stefanie; Kirchenbaum, Greg A.; Lehmann, Paul V. (Cells, 2022)
The scope of immune monitoring is to define the existence, magnitude, and quality of immune mechanisms operational in a host. In clinical trials and praxis, the assessment of humoral immunity is commonly confined to measurements of serum antibody reactivity without accounting for the memory B cell potential. Relying on fundamentally different mechanisms, however, passive immunity conveyed by pre-existing antibodies needs to be distinguished from active B cell memory. Here, we tested whether, in healthy human individuals, the antibody titers to SARS-CoV-2, seasonal influenza, or Epstein–Barr virus antigens correlated with the frequency of recirculating memory B cells reactive with the respective antigens. Weak correlations were found. The data suggest that the assessment of humoral immunity by measurement of antibody levels does not reflect on memory B cell frequencies and thus an individual’s potential to engage in an anamnestic antibody response against the same or an antigenically related virus. Direct monitoring of the antigen-reactive memory B cell compartment is both required and feasible towards that goal.
CRIS-Team Scopus Importer:2022-12-02
Keywords: affinity maturation; antibody-mediated immunity; EBV; ELISPOT; FluoroSpot; immune monitoring; influenza; memory B cells; plasma cells; SARS-CoV-2

Anti-CD52 antibody treatment depletes B cell aggregates in the central nervous system in a mouse model of multiple sclerosis - Simon, Micha; Ipek, Rojda; Homola, Gyoergy A.; Rovituso, Damiano M.; Schampel, Andrea; Kleinschnitz, Christoph; Kürten, Stefanie (Journal of Neuroinflammation, 2018)
BACKGROUND: Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS) for which several new treatment options were recently introduced. Among them is the monoclonal anti-CD52 antibody alemtuzumab that depletes mainly B cells and T cells in the immune periphery. Considering the ongoing controversy about the involvement of B cells and in particular the formation of B cell aggregates in the brains of progressive MS patients, an in-depth understanding of the effects of anti-CD52 antibody treatment on the B cell compartment in the CNS itself is desirable. METHODS: We used myelin basic protein (MBP)-proteolipid protein (PLP)-induced experimental autoimmune encephalomyelitis (EAE) in C57BL/6 (B6) mice as B cell-dependent model of MS. Mice were treated intraperitoneally either at the peak of EAE or at 60 days after onset with 200 μg murine anti-CD52 vs. IgG2a isotype control antibody for five consecutive days. Disease was subsequently monitored for 10 days. The antigen-specific B cell/antibody response was measured by ELISPOT and ELISA. Effects on CNS infiltration and B cell aggregation were determined by immunohistochemistry. Neurodegeneration was evaluated by Luxol Fast Blue, SMI-32, and Olig2/APC staining as well as by electron microscopy and phosphorylated heavy neurofilament serum ELISA. RESULTS: Treatment with anti-CD52 antibody attenuated EAE only when administered at the peak of disease. While there was no effect on the production of MP4-specific IgG, the treatment almost completely depleted CNS infiltrates and B cell aggregates even when given as late as 60 days after onset. On the ultrastructural level, we observed significantly less axonal damage in the spinal cord and cerebellum in chronic EAE after anti-CD52 treatment. CONCLUSION: Anti-CD52 treatment abrogated B cell infiltration and disrupted existing B cell aggregates in the CNS.
EVALuna2:35209

Antiglaucoma EP2 Agonists: A Long Road That Led Somewhere - Woodward, David F.; Wang, Jenny W.; Stamer, W. Daniel; Lütjen-Drecoll, Elke; Krauss, Achim H-P; Toris, Carol B. (Journal of Ocular Pharmacology and Therapeutics, 2019)
For >2 decades, EP2 agonists have been the subject of antiglaucoma research and development by scientists in industry and academia around the world. The road has led to the recent approval of the first drug of this class. This article reviews the development of EP2 agonists from conception to clinical approval, discussing pharmacology, structure, biodistribution, therapeutics, and drug delivery. An extensive list of source references is provided for the reader's benefit.
CRIS-Team WoS Importer:2019-08-09

Anti-inflammatory effects of an autologous gold-based serum therapy in osteoarthritis patients - Feldt, Jessica; Donaubauer, Anna-Jasmina; Welss, Jessica; Schneider, Ulrich; Gaipl, Udo; Paulsen, Friedrich (Scientific Reports, 2022)
Osteoarthritis (OA) involves activation and recruitment of immune cells to affected joints, including the production of pro-inflammatory cytokines. Here, a gold-based autologous serum therapy is investigated for its effect on peripheral blood cell composition and cytokine levels in OA patients. From six OA patients serum and blood samples were collected before and after second therapy treatment for analysis of peripheral blood cell composition as well as cytokine levels compared to control samples. This therapy significantly downregulates CD4+ T cells and B cells in OA patients after second treatment compared to healthy controls. Monocytes are significantly upregulated in patients after second treatment Serum IL-9 and TNF-α levels are downregulated in patients after second treatment compared to healthy control serum. The activation status of immune cells was modulated after therapy in patients. Anti-inflammatory effects of the peripheral blood cell composition in OA patients can be seen after therapy treatment. After two treatments IL-9 and TNF-α are significantly downregulated in patient serum. Here, primary data of a new autologous therapy for OA treatment and its modulatory effects on cytokines are presented.
CRIS-Team Scopus Importer:2022-03-11

Antimicrobial Peptides as Endogenous Antibacterials and Antivirals at the Ocular Surface - Garreis, Fabian; Schicht, Martin; Paulsen, Friedrich (Springer Basel, 2016)
Ocular surface infections are a significant cause of blindness worldwide particularly in developing countries and are mainly caused by bacteria, fungal species, and parasites as well as by viruses. Staphylococcus epidermidis, Staphylococcus aureus, Streptococcus pneumonia, and Pseudomonas aeruginosa are reported to be the most common bacteria associated with keratitis where the most frequent viruses leading to ocular surface infection are herpes simplex, adenovirus, and vaccinia virus. The eye and its adnexa have evolved a bulk of defense strategies to prevent microbial invasion. These include important components of the innate defense system in form of classical antimicrobial compounds as well as members of the cationic antimicrobial peptide family, distinct surfactant proteins, and potential new candidate molecules contributing to antimicrobial protection. Several of them are studied at the ocular surface not only for their antimicrobial properties, but based on easy topical application possibilities for their potential therapeutic effects. As several reviews already summarized the current knowledge with regard to the eye, this chapter will only briefly recapitulate the current knowledge of antimicrobial compound expression in the eye and then will focus on infectious keratitis resulting from bacterial and viral infection. In addition, the potential of using such peptides as therapeutics for treating bacterial and viral ocular surface infections will be elucidated.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Herpes Simplex Virus Infection; Lacrimal Gland; Ocular Surface; Secretory Leukocyte Protease Inhibitor; Trefoil Factor Family

Antioxidants reduce TGF-beta2-induced gene expressions in human optic nerve head astrocytes - Yu, Alice L.; Welge-Lüssen, Ulrich-Christoph (Acta Ophthalmologica, 2013)
The goal of the present study was to investigate whether the antioxidants vitamin E, vitamin C and vitamin B1 can reduce the transforming growth factor-beta2 (TGF-?2)-induced gene expressions in cultured human optic nerve head (ONH) astrocytes.Cultured human ONH astrocytes were pretreated with different concentrations of vitamin E, vitamin C and vitamin B1 and then exposed to 1.0 ng/ml TGF-?2 for 24 hr. Expression of the heat shock proteins Hsp27 and ?B-crystallin, the extracellular matrix (ECM) component fibronectin and the ECM-modulating protein connective tissue growth factor (CTGF) was detected by immunohistochemistry or real-time PCR analysis.TGF-?2 increased the expression of Hsp27, ?B-crystallin, fibronectin and CTGF in human ONH astrocytes. Pretreatment with different concentrations of vitamin E, vitamin C and vitamin B1 reduced the TGF-?2-stimulated gene expressions.In cultured human ONH astrocytes, the TGF-?2-stimulated gene expressions could be reduced by pretreatment with vitamin E, vitamin C and vitamin B1. Therefore, the use of antioxidants in glaucomatous optic neuropathy might be a promising approach to prevent TGF-?2-induced cellular changes in ONH astrocytes.
EVALuna2:21127

A pair of non‐competing neutralizing human monoclonal antibodies protecting from disease in a SARS‐CoV‐2 infection model - Peter, Antonia Sophia; Roth, Edith; Schulz, Sebastian; Fraedrich, Kirsten; Steinmetz, Tobit; Damm, Dominik; Hauke, Manuela; Richel, Elie; Müller-Schmucker, Sandra; Habenicht, Katharina Marie; Eberlein, Valentina; Issmail, Leila; et al. (European Journal of Immunology, 2021)
TRIANNI mice carry an entire set of human immunoglobulin V region gene segments and are a powerful tool to rapidly isolate human monoclonal antibodies. After immunizing these mice with DNA encoding the spike protein of SARS-CoV-2 and boosting with spike protein, we identified 29 hybridoma antibodies that reacted with the SARS-CoV-2 spike protein. Nine antibodies neutralize SARS-CoV-2 infection at IC50 values in the subnanomolar range. ELISA-binding studies and DNA sequence analyses revealed one cluster of three clonally related neutralizing antibodies that target the receptor-binding domain and compete with the cellular receptor hACE2. A second cluster of six clonally related neutralizing antibodies bind to the N-terminal domain of the spike protein without competing with the binding of hACE2 or cluster 1 antibodies. SARS-CoV-2 mutants selected for resistance to an antibody from one cluster are still neutralized by an antibody from the other cluster. Antibodies from both clusters markedly reduced viral spread in mice transgenic for human ACE2 and protected the animals from SARS-CoV-2-induced weight loss. The two clusters of potent non-competing SARS-CoV-2 neutralizing antibodies provide potential candidates for therapy and prophylaxis of COVID-19. The study further supports transgenic animals with a human immunoglobulin gene repertoire as a powerful platform in pandemic preparedness initiatives.

A Positive Control for Detection of Functional CD4 T Cells in PBMC: The CPI Pool - Schiller, Annemarie; Zhang, Ting; Li, Ruliang; Duechting, Andrea; Sundararaman, Srividya; Przybyla, Anna; Kürten, Stefanie; Lehmann, Paul V. (Cells, 2017)
Testing of peripheral blood mononuclear cells (PBMC) for immune monitoring purposes requires verification of their functionality. This is of particular concern when the PBMC have been shipped or stored for prolonged periods of time. While the CEF (Cytomegalo-, Epstein-Barr and Flu-virus) peptide pool has become the gold standard for testing CD8 cell functionality, a positive control for CD4 cells is so far lacking. The latter ideally consists of proteins so as to control for the functionality of the antigen processing and presentation compartments, as well. Aiming to generate a positive control for CD4 cells, we first selected 12 protein antigens from infectious/environmental organisms that are ubiquitous: Varicella, Influenza, Parainfluenza, Mumps, Cytomegalovirus, Streptococcus, Mycoplasma, Lactobacillus, Neisseria, Candida, Rubella, and Measles. Of these antigens, three were found to elicited interferon (IFN)-γ-producing CD4 cells in the majority of human test subjects: inactivated cytomegalo-, parainfluenza-, and influenza virions (CPI). While individually none of these three antigens triggered a recall response in all donors, the pool of the three (the 'CPI pool'), did. One hundred percent of 245 human donors tested were found to be CPI positive, including Caucasians, Asians, and African-Americans. Therefore, the CPI pool appears to be suitable to serve as universal positive control for verifying the functionality of CD4 and of antigen presenting cells.
EVALuna2:35213

A proposal for a new classification of coracobrachialis muscle morphology - Szewczyk, Bartlomiej; Polguj, Michal; Paulsen, Friedrich; Podgorski, Michal; Duparc, Fabrice; Karauda, Piotr; Olewnik, Lukasz (Surgical and Radiologic Anatomy, 2021)
Introduction: The coracobrachialis muscle (CRM) originates from the apex of the coracoid process, in common with the short head of the biceps brachii muscle, and from the intermuscular septum. It inserts to the medial part of the humerus between the attachment of the medial head of the triceps brachii and the brachial muscle. Both the proximal and distal attachments of the CRM, as well as its relationship with the musculocutaneus nerve, demonstrate morphological variability. Material and methods: One hundred and one upper limbs (52 left, and 49 right) fixed in 10% formalin solution were examined. Results: Three main types, with subtypes, were identified. The most common was Type I (49.5), characterized by a single muscle belly with a classical origin from the coracoid process, medially and posteriorly to the tendon of the biceps brachii. Type II (42.6%), characterized by two heads, was divided into two subtypes (A-B) depending on its origin: Type IIA, where one head originated from the coracoid process posteriorly to the tendon of the biceps brachii and the second head from the short head of the biceps brachii, and Type IIB, in which both heads originated from the coracoid process; however, the superficial head fused with the insertion of a short head of the biceps brachii, while the deep head was directly originating. Finally, Type III (7.9%) was characterized by three heads: two originated from the coracoid process (superficial and deep), and the third from a short head of the biceps brachii. Two types of insertion and two types of musculocutaneous nerve (MCN) relative to CRM could be distinguished. Conclusion: An adapted classification is needed for all clinicians working in this area, as well as for anatomists. The CRM demonstrates morphological variability in both its proximal and distal attachments, as well as the variable course of the MCN relative to the CRM. What is known about this subject "and" What this study adds to existing knowledge: Not much is known about the variability of coracobrachialis muscle. The present paper introduces a completely new classification, both clinical and anatomical.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Coracobrachialis muscle; Coracobrachialis muscle; Median nerve; Musculocutaneous nerve; New classification

A proposal for a new classification of soleus muscle morphology - Olewnik, Łukasz; Zielinska, Nicol; Paulsen, Friedrich; Podgórski, Michał; Haładaj, Robert; Karauda, Piotr; Polguj, Michał (Annals of Anatomy-Anatomischer Anzeiger, 2020)
Introduction: The soleus muscle (SM) is located in the superficial posterior compartment of the leg, together with the gastrocnemius muscle (GM) and plantaris muscle. There is little information on the morphological variability (pennation) of the SM. The aim of the study is to characterize the variations in the morphology of the pennation of the SM and to create the first accurate classification. Material and methods: Eighty lower limbs (40 left, and 40 right) fixed in 10% formalin solution were examined. The morphology of the central tendon, medial and lateral aponeuroses was evaluated, together with the pennation angle. Results: In all cases, the soleus muscle was present. Four types could be distinguished based on muscle fibre morphology. In order of frequency: Type 1 – bipennate (43.75%); Type 4 – non-pennate (36.25%); Type 2 – unipennate (15%); Type 3 – multipennate (5%). No significant difference in type distribution was observed with regard to body side (p = 0.9018) or gender (p = 0.0844). Conclusion: The soleus muscle is characterized by high morphological variability. Based on the pennation angle, four types (1–4) of soleus muscle are distinguishable.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Anatomical variations; Pennation angle; Soleus muscle

A proposal for a new morphological classification of the popliteus muscle tendon with potential clinical and biomechanical significance - Olewnik, Lukasz; Laprade, Robert F.; Paulsen, Friedrich; Gonera, Bartosz; Kurtys, Konrad; Podgorski, Michal; Aragones, Paloma; Sanudo, J. Ramon; Polguj, Michal (Scientific Reports, 2021)
The purpose of this study was to characterize the morphological variations in the proximal attachments and create an accurate classification of the PPM for use in planning surgical procedures in this area, for evaluating radiological imaging and rehabilitation. One hundred and thirty-four lower limbs of body donors (52 woman and 82 man) fixed in 10% formalin solution were examined. The popliteus muscle was present in all 134 limbs. Four main types were identified with subtypes. The most common type was Type I (34.3%), characterized by a single tendon in the popliteus sulcus. Type II (30.6%) characterized by a main tendon in the popliteus sulcus and accessory bands. This type was divided into five subtypes (A–E) based on presence of specific accessory bands. Type III (15.3%) was characterized by two tendons in the popliteal sulcus. Type IV (19.4%) was characterized by two tendons in the popliteus sulcus and additional bands. This type was also divided into five subtypes (A–E) based on presence of specific accessory bands. The popliteofibular ligament was present in 90.3% of cases. A new classification based on a proximal attachment is proposed. The popliteus tendon is characterized by a very high morphological variability, which can affect posterolateral knee stability and the natural rotation of the tibia. Such a classification system may be useful for clinicians performing medical procedures within the knee joint, including orthopedic surgeons.
CRIS-Team Scopus Importer:2021-08-06

APTES-Terminated ultrasmall and iron-doped silicon nanoparticles as X-Ray dose enhancer for radiation therapy - Klein, Stefanie; Wegmann, Marc; Distel, Luitpold; Neuhuber, Winfried; Kryschi, Carola (Biochemical and Biophysical Research Communications, 2018)
Silicon nanoparticles with sizes between were synthesized through wet-chemistry procedures using diverse phase transfer reagents. On the other hand, the preparation of iron-doped silicon nanoparticles was carried out using the precursor Na4Si4 containing 5% Fe. Biocompatibility of all silicon nanoparticle samples was achieved by surface-stabilizing with (3-aminopropyl)triethoxysilane. These surface structures provided positive surface charges which facilitated electrostatic binding to the negatively charged biological membranes. The mode of interaction with membranes, being either incorporation or just attachment, was found to depend on the nanoparticle size. The smallest silicon nanoparticles (ca. 1.5 nm) were embedded in the mitochondrial membrane in MCF-7 cells. When interacting with X-rays these silicon nanoparticles were observed to enhance the superoxide formation upon depolarizing the mitochondrial membrane. X-ray irradiation of MCF-7 cells loaded with the larger silicon nanoparticles was shown to increase the intracellular singlet oxygen generation. The doping of the silicon nanoparticles with iron led to additional production of hydroxyl radicals via the Fenton reaction.
EVALuna2:35202

Are agonistic beta 2-adrenergic receptor autoantibodies present in normal tension glaucoma and secondary open-angle glaucoma? - Hohberger, Bettina; Mardin, Christian Y.; Hosari, Sami; Lämmer, Robert; Kunze, Rudolf; Juenemann, Anselm; Schlötzer-Schrehardt, Ursula; Wallukat, Gerd; Herrmann, Martin (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

A review on use of botulinum toxin for intractable lacrimal drainage disorders - Singh, Swati; Ali, Mohammad Javed; Paulsen, Friedrich (International Ophthalmology, 2018)
PURPOSE: To review the published literature on botulinum toxin (BTX) for epiphora secondary to refractory lacrimal drainage disorders. METHODS: The authors performed a Pub Med search of all articles published in English on BTX injection into lacrimal gland for epiphora secondary to lacrimal drainage disorders. Relevant cross-references were obtained from the resultant studies. Data reviewed included demographics, indications, dose of BTX, number of injections, transconjunctival or transcutaneous route, outcomes and complications. Animal experiments of BTX into lacrimal gland were included and analyzed separately. RESULTS: Botulinum toxin injection into lacrimal gland, in animal studies, has shown to reduce the tear volume significantly lasting for approximately a month without any histological changes. The major indications have been refractory canalicular obstructions and functional epiphora. The commonly used dose was 2.5 U. Outcomes in the few studies published are encouraging with transient ptosis being the most common complication. CONCLUSIONS: Botulinum toxin into the lacrimal gland is a minimally invasive alternative in cases of refractory epiphora secondary to lacrimal drainage disorders. In these subsets of patients, the reported concentrations, dosage and outcome measures are variable and need larger studies for standardization.
EVALuna2:35304

Articular cartilage chondrocytes express aromatase and use enzymes involved in estrogen metabolism - Schicht, Martin; Ernst, Jana; Nielitz, Andrea; Fester, Lars; Tsokos, Michael; Guddat, Saskia S.; Bräuer, Lars; Bechmann, Judith; Delank, Karl-Stefan; Wohlrab, David; Paulsen, Friedrich; Claassen, Horst (Arthritis Research & Therapy, 2014)
Sex hormones, especially estrogens, have been implicated in articular cartilage metabolism and the pathogenesis of postmenopausal osteoarthritis. The conversion by aromatase (CYP19A1) of androstenedione into estrone (E1) and of testosterone into 17?-estradiol (E2) plays a key role in the endogenous synthesis of estrogens in tissue.We analyzed the expression of aromatase (CYP19A1) in immortalized C-28/I2 and T/C-28a2 chondrocytes, as well as in cultured primary human articular chondrocytes and human articular cartilage tissue, by means of RT-PCR, Western blotting and immunohistochemistry. By means of quantitative RT-PCR and enzyme-linked immunosorbent assay, we also determined whether the aromatase inhibitor letrozole influences estrogen metabolism of cultured chondrocytes in immortalized C-28/I2 chondrocytes.Aromatase mRNA was detected in both immortalized chondrocyte cell lines, in cultured primary human chondrocytes, and in human articular cartilage tissue. By means of Western blot analysis, aromatase was detected at the protein level in articular cartilage taken from various patients of both sexes and different ages. Cultured primary human articular chondrocytes, C-28/I2 and T/C-28a2, and human articular cartilage tissue reacted with antibodies for aromatase. Incubation of C-28/I2 chondrocytes with 10?¹¹ M to 10??M letrozole as an aromatase inhibitor revealed significantly increased amounts of the mRNAs of the enzyme cytochrome P4501A1 (CYP1A1), which is involved in the catagen estrogen metabolism, and of the estrogen receptors ER-? and ER-?. Concomitantly, synthesis of estrone (E1) was significantly downregulated after incubation with letrozole.We demonstrate that human articular cartilage expresses aromatase at the mRNA and protein levels. Blocking of estrone synthesis by the aromatase inhibitor letrozole is counteracted by an increase in ER-? and ER-?. In addition, CYP1A1, an enzyme involved in catabolic estrogen metabolism, is upregulated. This suggests that articular chondrocytes use ERs functionally. The role of endogenous synthesized estrogens in articular cartilage health remains to be elucidated.
EVALuna2:4411

ASO Visual Abstract: Augmented Reality Surgery to Guide Head and Neck Cancer Re-resection: A Feasibility and Accuracy Study - Prasad, Kavita; Miller, Alexis; Sharif, Kayvon; Colazo, Juan M.; Ye, Wenda; Necker, Fabian; Baik, Fred; Lewis, James S.; Rosenthal, Eben; Wu, Jie Ying; Topf, Michael C. (Annals of Surgical Oncology, 2023)
CRIS-Team Scopus Importer:2023-07-21

Assessing the adherence behavior of glaucoma patients to topical eye drops - Welge-Lüssen, Ulrich-Christoph; Weise, Stefanie; Yu, Alice L. (Patient Preference and Adherence, 2015)
The goal of this study was to determine the adherence of glaucoma patients to their topical glaucoma medication. Furthermore, the relationships between the adherence behavior and the patients' demographic data, clinical characteristics, and their knowledge about glaucoma were evaluated.This was a prospective study of 123 patients with primary open-angle glaucoma who were given two standardized questionnaires. The first questionnaire at time point T1 comprised a knowledge assessment and the self-reported adherence measures Adherence to Refills and Medication Scale 2 (ARMS2), visual analogue scale for adherence (VAS-AD), and missed doses in the past 14 days. Two months later at time point T2, a second questionnaire reevaluated the adherence measures ARMS2, VAS-AD, and missed doses in the past 14 days.There was a good correlation among all the three adherence measures at T1 and T2. The mean values of ARMS2 were in the lower range, with 3.38 at T1 and 2.8 at T2. The VAS-AD detected that 18.5% of patients always took their eye drops correctly, and 77.9% of patients reported not to have missed a single dose in the past 14 days. There was no significant correlation between the patients' demographic data or knowledge about glaucoma and the adherence measures ARMS2 or VAS-AD. Among the clinical characteristics, only single-eye blindness showed a significant correlation with VAS-AD.In this study, no general relationships were found between medication adherence and the patients' demographic data, clinical characteristics, or knowledge about glaucoma. It may be assumed that more individualized strategies are required to optimize adherence behavior.
EVALuna2:21149

Assessment of antibody functional affinity using ImmunSpot (R) - Kirchenbaum, G. A.; Franke, Fridolin; Lehmann, P. V. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-05

Assessment of a preclinical dry eye model using ultrahigh-resolution optical coherence tomography - Pfister, Martin; Messner, Alina; Fischak, Corinna; Garreis, Fabian; Paulsen, Friedrich; Schutzenberger, Kornelia; Dos Santos, Valentin Aranha; Stegmann, Hannes; Garhofer, Gerhard; Schmetterer, Leopold; Werkmeister, Rene Marcel (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

A survey of pelvic types on computed tomography images - Vučinić, Nikola; Paulsen, Friedrich; Milinkov, Milan; Nikolić, Marijana Basta; Todorović, Snežana Tomašević; Knezi, Nikola; Nikolić, Uroš (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Background: In the medical literature several classifications of the pelvis according to its shape can be found. The most common classification distinguishes four general pelvis types: gynecoid, android, anthropoid and platypelloid. Natural childbirth may be significantly prolonged, difficult or even impossible if the pelvis shape is not in proportion to the size of the fetus. The objectives of our study were to calculate major diameters and conjugate diameters of the female bony pelvic ring and to determine the major pelvic types according to their shape. Based on the parameters obtained, we aimed to establish a relationship between some pelvic types and difficult childbirth. Methods: The study was prospective in design and included 54 female subjects of various ages who had been referred for computed tomography of the pelvis, as part of the diagnosis of an underlying condition. In each patient, five most important parameters in two planes were measured and the pelvic type was determined by using the brim index and a special formula for android type. All measurements were performed using the Vue PACS v 12.1.6.1005 program. The description of the pelvic inlet was used to confirm all pelvic types. Data on previous births were taken from the questionnaire filled out by the subjects during the radiological examination. Results: Gynecoid pelvic type was the most common in our sample (28 pelvises – 52%), followed by platypelloid type (11 pelvises – 20%), anthropoid type (8 pelvises – 15%) and finally android type (7 pelvises – 13%). There was a statistically significant difference in the diameter bispinous length (p < 0.05) between the platypelloid and anthropoid pelvic types. Pathological degree of stenosis was present in seven pelvises (the first degree in six pelvises and the second degree in one pelvis). The frequency of cesarean section was 31.82% and this technique was most frequently used in the subjects with a gynecoid pelvic type. The duration of natural labor ranged from 4 to 18 h. There was no statistically significant difference in the duration of labor between subjects with different pelvic types. Conclusions: Gynecoid pelvic type was present in more than half of our subjects. Although this type is considered ideal for labor, we have not established that it has a great influence on whether the labor will be performed naturally or by cesarean section, neither that it significantly affects the length of birth. The gross narrowing of the pelvic ring is present in non-gynecoid pelvic types. The data obtained will certainly be useful to the obstetrician when planning the labor and considering all the factors that may affect the course of birth.
CRIS-Team Scopus Importer:2022-04-29
Keywords: Computed tomography; Labor; Morphology; Pelvis; Types

Asymmetric Omphalopagus in a Triplet after In Vitro Fertilization: A Rare Case of Conjoined Twinning - Jabari, Samir; Carbon, Roman; Besendörfer, Manuel; Hartmann, Arndt; Rompel, Oliver; Hoerning, Andre; Söder, Stephan (Case Reports in Pediatrics, 2018)
Introduction: Asymmetric omphalopagus is a rare situation of conjoined twinning, in which a grossly defective twin is attached to the thorax and upper abdomen of the main twin. We describe a case of an asymmetric omphalopagus accompanied by a normal triplet after assisted reproductive technology (ART) and tried to further characterize the all aspects of the conjoined twins. Case Presentation: Perioperative diagnostic imaging was carried out followed by an autopsy to evaluate all aspects of the parasite accompanied by histological, immunohistochemical, and molecular biological evaluation. The parasite had well-developed lower extremities as well as upper extremities with a cleft hand syndrome. The sex was nondeterminable, but DNA fingerprinting revealed that both parasite and autosite are monozygotic, so are females. There was no sign of any axial skeleton or central nervous system. We found a rudimentary rectum with a nonpervious anus, a kidney, ureter, urinary bladder, and a blind-ending urethra. The blood supply of the parasite was connected to the vessel system of the autosite. Conclusions: To our knowledge, only two cases of parasitic omphalopagus after ART have been described to date. Altogether, 52 cases have been reported, and in most of them, the parasites were successfully separated.
EVALuna2:34614

Atrophy and Impaired Contraction of the Myoepithelial Cells in Lacrimal Glands of Sjogren's Syndrome Animal Models of Dry Eye Disease - Zoukhri, Driss; Hawley, Dillon; Tang, Xin; Zyrianova, Tatiana; Shah, Mihir; Janga, Srikanth Reddy; Letourneau, Alexandra; Schicht, Martin; Paulsen, Friedrich; Hamm-Alvarez, Sarah; Makarenkova, Helen P. (2018)
EVALuna2:35313

Augmented-Reality Surgery to Guide Head and Neck Cancer Re-resection: A Feasibility and Accuracy Study - Prasad, Kavita; Miller, Alexis; Sharif, Kayvon; Colazo, Juan M.; Ye, Wenda; Necker, Fabian; Baik, Fred; Lewis, James S.; Rosenthal, Eben; Wu, Jie Ying; Topf, Michael C. (Annals of Surgical Oncology, 2023)
Background: Given the complex three-dimensional (3D) anatomy of head and neck cancer specimens, head and neck surgeons often have difficulty relocating the site of an initial positive margin to perform re-resection. This cadaveric study aimed to determine the feasibility and accuracy of augmented reality surgery to guide head and neck cancer re-resections. Methods: This study investigated three cadaveric specimens. The head and neck resection specimen was 3D scanned and exported to the HoloLens augmented reality environment. The surgeon manually aligned the 3D specimen hologram into the resection bed. Accuracy of manual alignment and time intervals throughout the protocol were recorded. Results: The 20 head and neck cancer resections performed in this study included 13 cutaneous and 7 oral cavity resections. The mean relocation error was 4 mm (range, 1–15 mm) with a standard deviation of 3.9 mm. The mean overall protocol time, from the start of 3D scanning to alignment into the resection bed, was 25.3 ± 8.9 min (range, 13.2–43.2 min). Relocation error did not differ significantly when stratified by greatest dimension of the specimen. The mean relocation error of complex oral cavity composite specimens (maxillectomy and mandibulectomy) differed significantly from that of all the other specimen types (10.7 vs 2.8; p < 0.01). Conclusions: This cadaveric study demonstrated the feasibility and accuracy of augmented reality to guide re-resection of initial positive margins in head and neck cancer surgery.
CRIS-Team Scopus Importer:2023-05-19

Autoantibodies Activating the β2-Adrenergic Receptor Characterize Patients With Primary and Secondary Glaucoma - Hohberger, Bettina; Kunze, Rudolf; Wallukat, Gerd; Kara, Katja; Mardin, Christian Y.; Lämmer, Robert; Schlötzer-Schrehardt, Ursula; Hosari, Sami; Horn, Folkert; Munoz Becerra, Luis; Herrmann, Martin (Frontiers in Immunology, 2019)
Recently, agonistic autoantibodies (agAAb) activating the β2-adrenergic receptor were detected in primary open-angle glaucoma (POAG) or ocular hypertension (OHT) patients and were linked to intraocular pressure (IOP) (1). The aim of the present study was to quantify β2-agAAb in the sera of glaucoma suspects and patients with primary and secondary glaucoma. Patients with OHT (n = 33), pre-perimetric POAG (pre-POAG; n = 11), POAG (n = 28), and 11 secondary OAG (SOAG) underwent ophthalmological examinations including examinations with Octopus G1 perimetry and morphometry. Twenty-five healthy individuals served as controls. Serum-derived IgG samples were analyzed for β2-agAAb using a functional bioassay. The beat-rate-increase of spontaneously beating cultured neonatal rat cardiomyocytes was monitored with 1.6 beats/15 s as cut-off. None of the sera of normal subjects showed β2-agAAb. In POAG or OHT patients increased beating rates of 4.1 ± 2.2 beats/15 s, and 3.7 ± 2.8 beats/15 s were detected (p > 0.05). Glaucoma patients with (POAG) and without perimetric (pre-POAG) defects did not differ (pre-POAG 4.4 ± 2.6 beats/15 s, POAG 4.1 ± 2.0 beats/15 s, p > 0.05). Patients with SOAG yielded mean beating rates of 4.7 ± 1.7 beats/15 s (p > 0.05). β2-agAAb were seen in 73% of OHT, 82% of pre-POAG, 82% of POAG, and 91% SOAG patients (p < 0.001). Clinical data did not correlate with beating rate (p > 0.05). The robust β2-agAAb seropositivity in patients with OHT, pre-POAG, POAG, and SOAG suggest a primary common role for β2-agAAb starting early in glaucoma pathophysiology and turned out to be a novel marker identifying all patients with increased IOP independent of glaucoma stage and entity.
CRIS-Team Scopus Importer:2019-10-29
Keywords: autoantibodies; glaucoma; ocular hypertension; primary open-angle glaucoma; secondary open-angle glaucoma; β2-adrenergic receptor

Autoantibodies against central nervous system antigens in a subset of B cell-dominant multiple sclerosis patients - Kürten, Stefanie; Lanz, Tobias V.; Lingampalli, Nithya; Lahey, Lauren J.; Kleinschnitz, Christoph; Mäurer, Mathias; Schroeter, Michael; Braune, Stefan; Ziemssen, Tjalf; Ho, Peggy P.; Robinson, William H.; Steinman, Lawrence (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS), with characteristic inflammatory lesions and demyelination. The clinical benefit of cell-depleting therapies targeting CD20 has emphasized the role of B cells and autoantibodies in MS pathogenesis. We previously introduced an enzyme-linked immunospot spot (ELISpot)-based assay to measure CNS antigen-specific B cells in the blood of MS patients and demonstrated its usefulness as a predictive biomarker for disease activity in measuring the successful outcome of disease-modifying therapies (DMTs). Here we used a planar protein array to investigate CNS-reactive antibodies in the serum of MS patients as well as in B cell culture supernatants after polyclonal stimulation. Anti-CNS antibody reactivity was evident in the sera of the MS cohort, and the antibodies bound a heterogeneous set of molecules, including myelin, axonal cytoskeleton, and ion channel antigens, in individual patients. Immunoglobulin reactivity in supernatants of stimulated B cells was directed against a broad range of CNS antigens. A group of MS patients with a highly active B cell component was identified by the ELISpot assay. Those antibody reactivities remained stable over time. These assays with protein arrays identify MS patients with a highly active B cell population with antibodies directed against a swathe of CNS proteins.
CRIS-Team Scopus Importer:2020-09-18
Keywords: antibody; B cells; ELISpot; multiple sclerosis; myelin

Autohaemotherapy based on gelsolin (GSN) enrichment supports corneal wound closure and has an anti-inflammatory effect on the ocular surface - Feldt, Jessica; Schicht, Martin; Garreis, Fabian; Welss, Jessica; Schneider, Ulrich; Paulsen, Friedrich (2019)
EVALuna2:210793

B-Cell Activity Predicts Response to Glatiramer Acetate and Interferon in Relapsing-Remitting Multiple Sclerosis - Tacke, Sabine; Braune, Stefan; Rovituso, Damiano M.; Ziemssen, Tjalf; Lehmann, Paul; Dikow, Heidi; Bergmann, Arnfin; Kürten, Stefanie (Neurology, Neuroimmunology and Neuroinflammation, 2021)
Objective We investigated the predictive value of the enzyme-linked immunospot technique (ELISPOT) in identifying patients with relapsing-remitting multiple sclerosis (RRMS) who will respond to treatment with glatiramer acetate (GA) or interferon-beta (IFN-beta), based on the brain-reactive B-cell activity of peripheral blood cells. Methods In this retrospective, cross-sectional, real-world multicenter study, we identified patients with RRMS in the NeuroTransData MS registry and stratified them based on their documented treatment response (relapse-free in the first 12 months of treatment) to GA or IFN-beta. The GA group comprised 73 patients who responded to GA and 35 nonresponders. The IFN-beta group comprised 62 responders to IFN-beta and 37 nonresponders. Patients with previous or current therapy affecting B-cell activity were excluded. We polyclonally stimulated mononuclear cells from peripheral blood samples (collected after participant selection) and investigated brain-reactive B-cell activity after incubation on brain tissue lysate-coated ELISPOT plates. Validity metrics of the ELISPOT testing results were calculated (Python 3.6.8) in relation to the clinical responsiveness in the 2 treatment groups. Results The ELISPOT B-cell activity assay showed a sensitivity of 0.74, a specificity of 0.76, a positive predictive value of 0.78, a negative predictive value of 0.28, and a diagnostic OR of 8.99 in predicting clinical response to GA vs IFN-beta therapy in patients with RRMS. Conclusion Measurement of brain-reactive B-cell activity by ELISPOT provides clinically meaningful predictive probabilities of individual patients' treatment response to GA or IFN-beta. The assay has the potential to improve the selection of optimal first-line treatment for individual patients with RRMS. Classification of Evidence This study provides Class II evidence that in patients with RRMS, the brain reactivity of their peripheral-blood B cells predicts clinical response to GA and IFN-beta.
CRIS-Team WoS Importer:2021-06-18

B Cells and B Cell Blasts Withstand Cryopreservation While Retaining Their Functionality for Producing Antibody - Fecher, Philipp; Caspell, Richard; Naeem, Villian; Karulin, Alexey Y.; Kürten, Stefanie; Lehmann, Paul (Cells, 2018)
In individuals who have once developed humoral immunity to an infectious/foreign antigen, the antibodies present in their body can mediate instant protection when the antigen re-enters. Such antigen-specific antibodies can be readily detected in the serum. Long term humoral immunity is, however, also critically dependent on the ability of memory B cells to engage in a secondary antibody response upon re-exposure to the antigen. Antibody molecules in the body are short lived, having a half-life of weeks, while memory B cells have a life span of decades. Therefore, the presence of serum antibodies is not always a reliable indicator of B cell memory and comprehensive monitoring of humoral immunity requires that both serum antibodies and memory B cells be assessed. The prevailing view is that resting memory B cells and B cell blasts in peripheral blood mononuclear cells (PBMC) cannot be cryopreserved without losing their antibody secreting function, and regulated high throughput immune monitoring of B cell immunity is therefore confined to-and largely limited by-the need to test freshly isolated PBMC. Using optimized protocols for freezing and thawing of PBMC, and four color ImmunoSpot® analysis for the simultaneous detection of all immunoglobulin classes/subclasses we show here that both resting memory B cells and B cell blasts retain their ability to secrete antibody after thawing, and thus demonstrate the feasibility of B cell immune monitoring using cryopreserved PBMC.
EVALuna2:35210

B Cells in Multiple Sclerosis and Virus-Induced Neuroinflammation - Chunder, Rittika; Schropp, Verena; Kürten, Stefanie (Frontiers in Neurology, 2020)
Neuroinflammation can be defined as an inflammatory response within the central nervous system (CNS) mediated by a complex crosstalk between CNS-resident and infiltrating immune cells from the periphery. Triggers for neuroinflammation not only include pathogens, trauma and toxic metabolites, but also autoimmune diseases such as neuromyelitis optica spectrum disorders and multiple sclerosis (MS) where the inflammatory response is recognized as a disease-escalating factor. B cells are not considered as the first responders of neuroinflammation, yet they have recently gained focus as a key component involved in the disease pathogenesis of several neuroinflammatory disorders like MS. Traditionally, the prime focus of the role of B cells in any disease, including neuroinflammatory diseases, was their ability to produce antibodies. While that may indeed be an important contribution of B cells in mediating disease pathogenesis, several lines of recent evidence indicate that B cells are multifunctional players during an inflammatory response, including their ability to present antigens and produce an array of cytokines. Moreover, interaction between B cells and other cellular components of the immune system or nervous system can either promote or dampen neuroinflammation depending on the disease. Given that the interest in B cells in neuroinflammation is relatively new, the precise roles that they play in the pathophysiology and progression of different neuroinflammatory disorders have not yet been well-elucidated. Furthermore, the possibility that they might change their function during the course of neuroinflammation adds another level of complexity and the puzzle remains incomplete. Indeed, advancing our knowledge on the role of B cells in neuroinflammation would also allow us to tackle these disorders better. Here, we review the available literature to explore the relationship between autoimmune and infectious neuroinflammation with a focus on the involvement of B cells in MS and viral infections of the CNS.
CRIS-Team Scopus Importer:2020-11-27
Keywords: B cells; central nervous system; EBV; multiple sclerosis; neuroinflammation; viral infection

Biomechanical analysis of the cervical spine segment as a method for studying the functional and dynamic anatomy of the human neck - Ovsepyan, A. L.; Smirnov, A. A.; Pustozerov, E. A.; Mokhov, D. E.; Mokhova, E. S.; Trunin, E. M.; Dydykin, S. S.; Vasil'Ev, Yu. L.; Yakovlev, E. V.; Budday, Silvia; Paulsen, Friedrich; Zhivolupov, S. A.; et al. (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Background: Traditionally, dynamic and functional anatomy, in particular the dynamic anatomy of the neck, is studied on cadaveric material. However, the development of in vivo visualization technologies and in silico modeling has made it possible to expand these possibilities. Despite significant progress in the study of dynamic and functional anatomy of the neck by means of in silico methods, the issues of validating the developed models and taking into account the pronounced nonlinearity of soft tissues as well as local anisotropy remain open. The aim of this study was to develop a virtual dynamic anatomical model of the human neck and reproduce the dynamic processes in the cervical spine from this model using the finite element method. Materials and methods: Reverse engineering was used to generate a dynamic anatomical model of the neck from CT data (both male, 24 and 22 years old). Two segments of the cervical spine (C3-C5, C2-T1) were isolated from the resulting model for finite element analysis. Finite element mesh generation and contact interactions were performed using the HyperMesh software (Altair Engineering Inc, Troy, Michigan, USA). The anisotropic hyperelastic Holzapfel-Gasser-Ogden model was used to describe the material behavior of the fibrous rings of the disc. Material modeling and finite element analysis were performed using Abaqus CAE 6.14 software (Simulia, Johnston, Rhode Island, USA). Results: A technique for creating a virtual dynamic anatomical model of the neck was elaborated and implemented. The model includes 79 major anatomical structures of the neck segmented from radiological data. A finite element analysis of the cervical spine was performed. The results of finite element analysis of the C3-C5 segment under axial load were compared with in vitro data. The proposed model shows nonlinear deformation of the disc under static loading; the model predicted displacement values agree well with the experimental ones. The displacement of the С3-С5 central vertebra with an axial load of 800 N reaches a value of 0.65 mm. For the segment C2-T1, data on intradiscal pressure, stress plots and displacements during flexion were obtained. The maximum stress value of 10.036 MPa is observed in the C3-C4 disc. Conclusion: Simulation results using the proposed methodology are in good agreement with experimental data. The generated biomechanical models allow describing dynamic phenomena in the cervical spine and obtaining a wide range of quantitative properties of anatomical objects, which are otherwise inaccessible to classical methods for studying dynamic and functional anatomy.
Created from Fastlane, Scopus look-up
Keywords: Abaqus CAE; Finite element method (FEM); Functional anatomy of the neck; Holzapfel-Gasser-Ogden material model; Intervertebral disc; Neck biomechanics

Biomechanical efficacy of collagen crosslinking in porcine cornea using a femtosecond laser pocket - Wollensak, Gregor; Hammer, Christian; Spoerl, Eberhard; Klenke, Joerg; Skerl, Katrin; Zhang, Yao; Sel, Saadettin (Cornea, 2014)
The aim of this study was to assess the biomechanical efficacy of transepithelial collagen crosslinking using the femtosecond laser pocket technique compared with that using the standard crosslinking (CXL) technique.Forty ex vivo porcine eyes were divided into 4 groups with 10 samples each. Group 1 comprised the untreated controls. Group 2 was the standard CXL group with debridement, instillation of 0.1% riboflavin-dextran solution for 15 minutes before and every 5 minutes during the 30 minutes of irradiation with ultraviolet A (UVA) light of 370 nm and an irradiance of 3 mW/cm². Group 3 pertained to the femtolaser pocket control with an intrastromal pocket but without riboflavin/UVA. Group 4 was the femtolaser pocket CXL group with an intrastromal pocket of an 8-mm diameter at a 180-?m depth, riboflavin/dextran application for 15 minutes and subsequent exposure to UVA light for 30 minutes. Postoperatively, biomechanical stress-strain measurements were performed.In the standard CXL group, the stress at 10% strain was 207.8 ± 64.1 × 10 Pa (+79.45% vs. controls; P = 0.021) compared with 115.8 ± 20.8 × 10 Pa in the untreated control group; in the crosslinked femtolaser pocket group, it was 159.5 ± 30.4 × 10 Pa (+37.74%; P = 0.049), in the non-cross-linked femtolaser pocket group, it was 103.5 ± 17.3 × 10 Pa (-10.62%; P = 0.103). The Young modulus was 5.4 MPa (+100% vs. controls) in the standard CXL group, 3.7 MPa (+37.04%) in the crosslinked femtolaser pocket group, and 2.4 MPa (-11.12%) in the non-cross-linked femtolaser pocket group compared with 2.7 MPa in the untreated control group.The biomechanical effect of CXL using the femtolaser pocket technique is about 50% less pronounced than that after standard CXL. Future studies will show whether the efficacy of the technique can still be improved and whether the clinical effect is sufficient for stabilizing ectatic corneas.
EVALuna2:4404

Biomimetically-and hydrothermally-grown HAp nanoparticles as reinforcing fillers for dental adhesives - Wagner, Andrea; Belli, Renan; Stoetzel, Christian; Hilpert, Andrea; Mueller, Frank A.; Lohbauer, Ulrich (Journal of Adhesive Dentistry, 2013)
Purpose: Differently prepared hydroxyapatite (HAp) nanoparticles were incorporated into the adhesive solution of a commercial adhesive system in order to evaluate the effect on microtensile bond strength to dentin. Materials and Methods: HAp nanoparticles (20 to 70 nm) were prepared by different processes (biomimetic and hydrothermal) and incorporated into the adhesive of the Adper Scotchbond Multi-Purpose (SBMP) system at various concentrations. Control (unfilled) and experimental groups (filled) were applied onto flat mid-coronal human dentin. Composite crowns were built up and cut into beams with a cross-sectional area of 0.65 ± 0.05 mm2. Specimens were fractured in tension and examined with a scanning electron microscope (SEM) for fractographic analysis. Microtensile bond strength (µTBS) data were analyzed using a two-way ANOVA and modified LSD test at α= 0.05. Analysis of the nanofiller distribution and ultramorphological characterization of the interface was performed by transmission electron microscopy (TEM). Results: HAp nanoparticle incorporation into the adhesive of SBMP significantly influenced µTBS to dentin depending on the fillers and the concentration used. A significant increase of the mechanical strength was obtained for the adhesives containing 1% (wt/vol) biomimetic and 5% hydrothermal silanized HAp particles, while the other particle fractions did not influence µTBS significantly. 10% (wt/vol) HAp particles significantly lowered the µTBS irrespective of the particle type used. TEM micrographs revealed nanoparticle dispersion through the adhesive layer but no deposition on or penetration into the hybrid layer. Conclusions: HAp nanoparticle incorporation into SBMP increased bond strength to dentin by cohesively reinforcing the interface adhesive layer. At a concentration of 10% (wt/vol), nanofiller incorporation had a negative effect on bond strength. © 2013 by Quintessence Publishing Co Inc.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Adhesion; Biomimetic and hydrothermal HAp preparation; Dentin bonding; HAp; Nanoparticle filler; Silanization; Tensile bond strength

Blockade of the BK-a/beta 4 potassium ion channel reduces outflow facility in mice - Bertrand, Jacques Alexander; Sherwood, Joseph M.; Schicht, Martin; Lütjen-Drecoll, Elke; Selwood, David; Stamer, William D.; Overby, Darryl R. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Bone marrow cells and CD117-positive haematopoietic stem cells promote corneal wound healing - Sel, Saadettin; Schilling, Ulf M.; Nass, Norbert; Simm, Andreas; Garreis, Fabian; Knak, Matthias; Storsberg, Joachim; Kaiser, Maja; Kalinski, Thomas; Ehrich, Dirk; Bredehorn-Mayr, Timm; Paulsen, Friedrich (Acta Ophthalmologica, 2012)
Purpose: The present study was conducted to evaluate the therapeutic effects of topically applied bone marrow (BM) cells and CD117-positive haematopoietic stem (CD117(+)) cells on alkali-induced corneal ulcers. Methods: Bone marrow cells and CD117(+) cells were isolated from syngenic mice and labelled with an intracellular cell tracer. Defined corneal wounds were produced in 89 eyes of syngenic mice and allowed to partially heal in vivo for 6 hr. The alkali-burned eyes were enucleated 6 hr postinjury and randomly divided into three groups. Control group (33 eyes) was incubated with medium only. The treatment groups received either BM cells (30 eyes) or CD117(+) cells (26 eyes) suspended in medium. Re-epithelialization process of corneal defects was qualitatively and quantitatively assessed and statistically analysed. The corneas were examined by histological and immunohistochemical methods. Results: We found that the re-epithelialization of corneal wounds in both treatment groups was significantly accelerated as compared to the control group. During the follow-up period (85 hr), the corneal transparency was comparable in all groups. Morphological investigations of corneas from control and treatment group showed no evident differences in the phenotype of the regenerated epithelium. Additionally, corneas in the treatment groups were devoid of donor-derived BM cells and CD117(+) cells, respectively. Conclusions: This study provides evidence that topical application of BM cells or CD117(+) cells can be used to reconstruct corneal surfaces. Because neither BM cells nor CD117(+) cells were integrated into the corneal epithelium, we suggest that soluble factors could be responsible for the positive effect of BM cells and CD117(+) cells on corneal wound healing.
EVALuna2:4383

Bone marrow-derived myeloid progenitors in the leptomeninges of adult mice - Koeniger, Tobias; Bell, Luisa; Mifka, Anika; Enders, Michael; Hautnnann, Valentin; Mekala, Subba Rao; Kirchner, Philipp; Ekici, Arif Bülent; Schulz, Christian; Woersdoerfer, Philipp; Mencl, Stine; Kleinschnitz, Christoph; et al. (Stem Cells, 2020)
Although the bone marrow contains most hematopoietic activity during adulthood, hematopoietic stem and progenitor cells can be recovered from various extramedullary sites. Cells with hematopoietic progenitor properties have even been reported in the adult brain under steady-state conditions, but their nature and localization remain insufficiently defined. Here, we describe a heterogeneous population of myeloid progenitors in the leptomeninges of adult C57BL/6 mice. This cell pool included common myeloid, granulocyte/macrophage, and megakaryocyte/erythrocyte progenitors. Accordingly, it gave rise to all major myelo-erythroid lineages in clonogenic culture assays. Brain-associated progenitors persisted after tissue perfusion and were partially inaccessible to intravenous antibodies, suggesting their localization behind continuous blood vessel endothelium such as the blood-arachnoid barrier. Flt3Cre lineage tracing and bone marrow transplantation showed that the precursors were derived from adult hematopoietic stem cells and were most likely continuously replaced via cell trafficking. Importantly, their occurrence was tied to the immunologic state of the central nervous system (CNS) and was diminished in the context of neuroinflammation and ischemic stroke. Our findings confirm the presence of myeloid progenitors at the meningeal border of the brain and lay the foundation to unravel their possible functions in CNS surveillance and local immune cell production.
CRIS-Team Scopus Importer:2020-12-25
Keywords: hematopoietic; meninges; mouse; myeloid; progenitor

Bony contact in arthritic and healthy elbow joints. Studies in cadaveric specimens - Schneider, M. M.; Hollinger, B.; Nietschke, R.; Mueller, K.; Buder, Thomas; Zimmerer, A.; Burkhart, K. J. (Orthopäde, 2019)
BackgroundArthroscopic and open debridement arthroplasty for elbow arthrosis produce excellent results. Resection of the tip of the olecranon and coronoid, as well as debridement of the associated fossae, is frequently described as sufficient for restoring range of motion and reducing pain.ObjectivesThe purpose of this study was to demonstrate that medial and lateral osteophytes of the olecranon and the coronoid usually mark the first bony contact and may, therefore, restrict range of motion.Material and methods11fresh-frozen elbows were dissected. The fossae were coated with Optosil PPlus (C-silicone), and maximal flexion and extension was simulated. The distribution of C-silicone impressions was documented. 6/7donors were male. The mean age at the time of death was 82.ResultsOut of 11elbows, 4 exhibited arthritic changes. All arthritic elbows showed marginal osteophytes of the olecranon without characteristic dipping of the olecranon into its fossa. In 1/4cases, additional osteophytes at the side of the coronoid were detected (in comparison to 1/7in healthy elbows).ConclusionThe distribution of osteophytes in elbow arthrosis may be underestimated. Many clinicians describe aresection of the tip of the olecranon and the coronoid and debridement of the related fossa as sufficient. Our study supports the theory that marginal osteophytes, especially of the olecranon, should be resected during debridement arthroplasty, since the distribution of bony contact differs in arthritic and healthy elbows.
CRIS-Team WoS Importer:2019-02-27

C1q/TNF-Related Proteins 1, 6 and 8 Are Involved in Corneal Epithelial Wound Closure by Targeting Relaxin Receptor RXFP1 In Vitro - Nicolaus, Hagen; Klonisch, Thomas; Paulsen, Friedrich; Garreis, Fabian (International Journal of Molecular Sciences, 2023)
Inadequate wound healing of ocular surface injuries can lead to permanent visual impairment. The relaxin ligand-receptor system has been demonstrated to promote corneal wound healing through increased cell migration and modulation of extracellular matrix formation. Recently, C1q/tumor necrosis factor-related protein (CTRP) 8 was identified as a novel interaction partner of relaxin receptor RXFP1. Additional data also suggest a role for CTRP1 and CTRP6 in RXFP1-mediated cAMP signaling. However, the role of CTRP1, CTRP6 and CTRP8 at the ocular surface remains unclear. In this study, we investigated the effects of CTRP1, CTRP6, and CTRP8 on epithelial ocular surface wound closure and their dependence on the RXFP1 receptor pathway. CTRP1, CTRP6, and CTRP8 expression was analyzed by RT-PCR and immunohistochemistry in human tissues and cell lines derived from the ocular surface and lacrimal apparatus. In vitro ocular surface wound modeling was performed using scratch assays. We analyzed the effects of recombinant CTRP1, CTRP6, and CTRP8 on cell proliferation and migration in human corneal and conjunctival epithelial cell lines. Dependence on RXFP1 signaling was established by inhibiting ligand binding to RXFP1 using a specific anti-RXFP1 antibody. We detected the expression of CTRP1, CTRP6, and CTRP8 in human tissue samples of the cornea, conjunctiva, meibomian gland, efferent tear ducts, and lacrimal gland, as well as in human corneal, conjunctival, and meibomian gland epithelial cell lines. Scratch assays revealed a dose-dependent increase in the closure rate of surface defects in human corneal epithelial cells after treatment with CTRP1, CTRP6, and CTRP8, but not in conjunctival epithelial cells. Inhibition of RXFP1 fully attenuated the effect of CTRP8 on the closure rate of surface defects in human corneal epithelial cells, whereas the CTRP1 and CTRP6 effects were not completely suppressed. Conclusions: Our findings demonstrate a novel role for CTRP1, CTRP6, and CTRP8 in corneal epithelial wound closure and suggest an involvement of the relaxin receptor RXFP1 signaling pathway. This could be a first step toward new approaches for pharmacological and therapeutic intervention.
CRIS-Team Scopus Importer:2023-04-21
Keywords: C1q/TNF-related proteins; C1QTNF; corneal wound closure; CTRP1; CTRP6; CTRP8; lacrimal apparatus; ocular surface; relaxin receptor; RXFP1

Caffeic Acid, Quercetin and 5-Fluorocytidine-Functionalized Au-Fe3O4 Nanoheterodimers for X-ray-Triggered Drug Delivery in Breast Tumor Spheroids - Klein, Stefanie; Distel, Luitpold; Neuhuber, Winfried; Kryschi, Carola (Nanomaterials, 2021)
Au-Fe3O4 nanoheterodimers (NHD) were functionalized with the natural and synthetic anticancer drugs caffeic acid (CA), quercetin (Q) and 5-fluorocytidine (5FC). Their X-radiation dose-enhancing potential and chemotherapeutic efficacy for bimodal cancer therapy were investigated by designing multicellular tumor spheroids (MCTS) to in vitro avascular tumor models. MCTS were grown from the breast cancer cell lines MCF-7, MDA-MB-231, and MCF-10A. The MCF-7, MDA-MB-231 and MCF-10A MCTS were incubated with NHD-CA, NHD-Q, or NHD-5FC and then exposed to fractionated X-radiation comprising either a single 10 Gy dose, 2 daily single 5 Gy doses or 5 daily single 2 Gy doses. The NHD-CA, NHD-Q, and NHD-5FC affected the growth of X-ray irradiated and non-irradiated MCTS in a different manner. The impact of the NHDs on the glycolytic metabolism due to oxygen deprivation inside MCTS was assessed by measuring lactate secretion and glucose uptake by the MCTS. The NHD-CA and NHD-Q were found to act as X-radiation dose agents in MCF-7 MCTS and MDA-MB-231 MCTS and served as radioprotector in MCF-10A MCTS. X-ray triggered release of CA and Q inhibited lactate secretion and thereupon disturbed glycolytic reprogramming, whereas 5FC exerted their cytotoxic effects on both, healthy and tumor cells, after their release into the cytosol.
CRIS-Team WoS Importer:2021-06-11

Calbindin D28k-Immunoreactivity in Human Enteric Neurons - Zetzmann, Katharina; Strehl, Johanna; Geppert, Carol-Immanuel; Kürten, Stefanie; Jabari, Samir; Brehmer, Axel (International Journal of Molecular Sciences, 2018)
Calbindin (CALB) is well established as immunohistochemical marker for intrinsic primary afferent neurons in the guinea pig gut. Its expression by numerous human enteric neurons has been demonstrated but little is known about particular types of neurons immunoreactive for CALB. Here we investigated small and large intestinal wholemount sets of 26 tumor patients in order to evaluate (1) the proportion of CALB⁺ neurons in the total neuron population, (2) the colocalization of CALB with calretinin (CALR), somatostatin (SOM) and vasoactive intestinal peptide (VIP) and (3) the morphology of CALB+ neurons. CALB+ neurons represented a minority of myenteric neurons (small intestine: 31%; large intestine: 25%) and the majority of submucosal neurons (between 72 and 95%). In the submucosa, most CALB⁺ neurons co-stained for CALR and VIP (between 69 and 80%) or for SOM (between 20 and 3%). In the myenteric plexus, 85% of CALB+ neurons did not co-stain with the other markers investigated. An unequivocal correlation between CALB reactivity and neuronal morphology was found for myenteric type III neurons in the small intestine: uniaxonal neurons with long, slender and branched dendrites were generally positive for CALB. Since also other neurons displayed occasional CALB reactivity, this protein is not suited as an exclusive marker for type III neurons.
EVALuna2:34063

Calcitonin gene-related peptide: A marker for putative primary afferent neurons in the pig small intestinal myenteric plexus? - Wolf, Matthias; Schrödl, Falk; Neuhuber, Winfried; Brehmer, Axel (Anatomical Record-Advances in Integrative Anatomy and Evolutionary Biology, 2007)
For years, calcitonin gene-related peptide (CGRP) has been used as a marker peptide for Dogiel type II neurons, putative intrinsic primary afferent neurons, in the pig enteric nervous system. Recently, some studies showed CGRP-positive neurons displaying distinctly different shapes. The aims of this study were to evaluate (1) the proportion of myenteric type II neurons that contain CGRP and (2) the proportion of myenteric CGRP-positive neurons that display type II vs. non-type II morphologies and to conclude if this peptide could be suited as a marker for type II neurons. For this purpose, nine myenteric whole-mounts (each one from duodenum, jejunum, and ileum, respectively, derived from three pigs) were triple-immunostained for CGRP, neurofilaments (NF), and choline acetyl transferase (ChAT). Each whole-mount was evaluated twice. First, 50 NF-stained type II neurons were selected randomly and their coreactivities for CGRP and ChAT were observed. Second, 50 CGRP-positive neurons were located randomly and their NF morphology and ChAT coreactivity were observed. Altogether, 92% of all type II neurons investigated displayed CGRP immunoreactivity, whereas 94.9% of all CGRP-reactive neurons recorded displayed type II morphology. We observed three further shapes of CGRP-positive neurons: 7 type V neurons (all were ChAT-positive; mainly in the ileal whole-mounts), 6 type I-like neurons (all were ChAT-positive), and 14 type III-like neurons (mostly ChAT-negative; mainly in duodenal and jejunal specimens). We conclude that CGRP-antibodies can be used as markers for type II neurons in the pig small intestinal myenteric plexus in quantitative studies but it should be kept in mind that up to one-tenth of CGRP-reactive neurons may be non-type II neurons. In case of single cell evaluation, CGRP-immunoreactivity alone is not suited as a marker. In such cases additional, morphological analysis is necessary. © 2007 Wiley-Liss, Inc.
Keywords: Euteric nervous system; Gut; Innervation; Morphology; Neuron type

Calcium regulation by temperature-sensitive transient receptor potential channels in human uveal melanoma cells - Mergler, Stefan; Derckx, Raissa; Reinach, Peter S.; Garreis, Fabian; Boehm, Anna; Schmelzer, Lisa; Skosyrski, Sergej; Ramesh, Niraja; Abdelmessih, Suzette; Polat, Onur Kerem; Khajavi, Noushafarin; Riechardt, Aline Isabel (Cellular Signalling, 2014)
Uveal melanoma (UM) is both the most common and fatal intraocular cancer among adults worldwide. As with all types of neoplasia, changes in Ca(2+) channel regulation can contribute to the onset and progression of this pathological condition. Transient receptor potential channels (TRPs) and cannabinoid receptor type 1 (CB1) are two different types of Ca(2+) permeation pathways that can be dysregulated during neoplasia. We determined in malignant human UM and healthy uvea and four different UM cell lines whether there is gene and functional expression of TRP subtypes and CB1 since they could serve as drug targets to either prevent or inhibit initiation and progression of UM. RT-PCR, Ca(2+) transients, immunohistochemistry and planar patch-clamp analysis probed for their gene expression and functional activity, respectively. In UM cells, TRPV1 and TRPM8 gene expression was identified. Capsaicin (CAP), menthol or icilin induced Ca(2+) transients as well as changes in ion current behavior characteristic of TRPV1 and TRPM8 expression. Such effects were blocked with either La(3+), capsazepine (CPZ) or BCTC. TRPA1 and CB1 are highly expressed in human uvea, but TRPA1 is not expressed in all UM cell lines. In UM cells, the CB1 agonist, WIN 55,212-2, induced Ca(2+) transients, which were suppressed by La(3+) and CPZ whereas CAP-induced Ca(2+) transients could also be suppressed by CB1 activation. Identification of functional TRPV1, TRPM8, TRPA1 and CB1 expression in these tissues may provide novel drug targets for treatment of this aggressive neoplastic disease.
EVALuna2:4406

Calcium regulation by thermo- and osmosensing transient receptor potential vanilloid channels (TRPVs) in human conjunctival epithelial cells - Mergler, Stefan; Garreis, Fabian; Sahlmueller, Monika; Lyras, Ekaterini-Maria; Reinach, Peter S.; Dwarakanath, Abhilash; Paulsen, Friedrich; Pleyer, Uwe (Histochemistry and Cell Biology, 2012)
Transient receptor potential vanilloid (TRPV) channels respond to polymodal stresses to induce pain, inflammation and tissue fibrosis. In this study, we probed for their functional expression in human conjunctival epithelial (HCjE) cells and ex vivo human conjunctivas. Notably, patients suffering from dry eye syndrome experience the same type of symptomology induced by TRPV channel activation in other ocular tissues. TRPV gene and protein expression were determined by RT-PCR and immunohistochemistry in HCjE cells and human conjunctivas (body donors). The planar patch-clamp technique was used to record nonselective cation channel currents. Ca 2+ transients were monitored in fura-2 loaded cells. Cultivated HCjE cells and human conjunctiva express TRPV1, TRPV2, and TRPV4 mRNA. TRPV1 and TRPV4 localization was identified in human conjunctiva. Whereas the TRPV1 agonist capsaicin (CAP) (5-20 μM) -induced Ca 2+ transients were blocked by capsazepine (CPZ) (10 μM), the TRPV4 activator 4α-PDD (10 μM) -induced Ca 2+ increases were reduced by ruthenium-red (RuR) (20 μM). Different heating (<40°C or>43°C) led to Ca 2+ increases, which were also reduced by RuR. Hypotonic challenges of either 25 or 50% induced Ca 2+ transients and nonselective cation channel currents. In conclusion, conjunctiva express TRPV1, TRPV2, and TRPV4 channels which may provide novel drug targets for dry eye therapeutics. Their usage may have fewer side effects than those currently encountered with less selective drugs. © Springer-Verlag 2012.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Dry eye; Human conjunctiva; Intracellular Ca; Planar patch-clamp; TRPV channels

Calretinin and Somatostatin Immunoreactivities Label Different Human Submucosal Neuron Populations - Kustermann, Andreas; Neuhuber, Winfried; Brehmer, Axel (Anatomical Record-Advances in Integrative Anatomy and Evolutionary Biology, 2011)
In human myenteric plexus, calretinin (CALR) and somatostatin (SOM) coexist in Dogiel Type II neurons, which were considered as intrinsic primary afferent neurons in the guinea pig. The aims of this study were to test if also human submucosal neurons costain immunohistochemically for CALR and SOM and whether these or other neurons display Type II morphology. Two sets of submucosal wholemounts of small and large intestine from 29 patients (median age 65 years) were triple stained for CALR, SOM, and human neuronal protein Hu C/D (HU, a pan-neuronal marker) as well as for CALR, SOM, and peripherin (PER), respectively. Only exceptionally, neurons coreactive for both CALR and SOM were found. The three major groups of neurons were CALR-/HU-coreactive (CALR-neurons), SOM-/HU-coreactive (SOM-neurons), and HU-alone-positive neurons. We observed significantly more CALR-neurons in the external submucosal plexus (ESP) of all regions and more SOM-neurons in the internal submucosal plexus (ISP), although with substantial interindividual variations. Comparisons of small vs. large intestine revealed more SOM-neurons (ESP: 29% vs. 4%, ISP: 40% vs. 13%) but fewer CALR-neurons (ESP: 37% vs. 77%, ISP: 21% vs. 67%) in small intestine. Morphologically, CALR-neurons had multiple processes; in some cases, we identified multidendritic/uniaxonal neurons. In contrast, SOM-neurons had mostly only one process. The functions of both populations as possible primary afferent neurons, interneurons, secretomotor neurons, or vasomotor neurons are discussed. Future morphochemical distinction of these groups may reveal different subgroups. © 2011 Wiley-Liss, Inc.
Keywords: Chemical coding; Enteric nervous system; Gut; Innervation; Neuron type; Submucosal plexus

Cathepsin D Variants Associated With Neurodegenerative Diseases Show Dysregulated Functionality and Modified α-Synuclein Degradation Properties - Bunk, Josina; Prieto Huarcaya, Susy; Drobny, Alice; Dobert, Jan Philipp; Walther, Lina; Rose-John, Stefan; Arnold, Philipp; Zunke, Friederike (Frontiers in Cell and Developmental Biology, 2021)
Cathepsin D (CTSD) is a lysosomal protease important for the degradation of various substrates, including disease-associated proteins like α-synuclein (a-syn), amyloid precursor protein (APP) and tau, all of which tend to aggregate if not efficiently degraded. Hence, it is not surprising that genetic variants within the CTSD gene have been linked to neurodegenerative diseases, like Parkinson’s and Alzheimer’s disease (PD, AD), as well as the lysosomal storage disorder neuronal ceroid lipofuscinosis type-10 (NCL10). Although recent studies have shown the molecular dependence of substrate degradation via CTSD within autophagic pathways, only little is known about the precise role of lysosomal CTSD function in disease development. We here performed biochemical, cellular and structural analyses of eleven disease-causing CTSD point mutations found in genomic sequencing data of patients to understand their role in neurodegeneration. These CTSD variants were analyzed for cellular localization, maturation and enzymatic activity in overexpression analyses. Moreover, for PD-associated mutants, intracellular degradation of a-syn was monitored. In summary, our results suggest that NCL10-associated CTSD variants are significantly impaired in lysosomal maturation and enzymatic activity, whereas the AD- and PD-associated variants seemed rather unaffected, indicating normal maturation, and lysosomal presence. Interestingly, a PD-associated CTSD variant (A239V) exhibited increased enzymatic activity accompanied by enhanced a-syn degradation. By structural analyses of this mutant utilizing molecular dynamics simulation (MDS), we identified a structural change within a loop adjacent to the catalytic center leading to a higher flexibility and potentially accelerated substrate exchange rates. Our data sheds light onto the role of CTSD in disease development and helps to understand the structural regulation of enzymatic function, which could be utilized for targeted CTSD activation. Because of the degradative function of CTSD, this enzyme is especially interesting for therapeutic strategies tackling protein aggregates in neurodegenerative disorders.
CRIS-Team Scopus Importer:2021-03-12
Keywords: alpha-synuclein; cathepsin D; lysosomal degradation; lysosomes; molecular dynamics simulation; neuronal ceroid lipofuscinoses; Parkinson’s disease

Chagasic megacolon: Enteric neurons and related structures - Jabari, Samir; De Oliveira, Enio; Brehmer, Axel; Da Silveira, Alexandre B.M. (Histochemistry and Cell Biology, 2014)
Megacolon, the irreversible dilation of a colonic segment, is a structural sign associated with various gastrointestinal disorders. In its hereditary, secondary form (e.g. in Hirschsprung's disease), dilation occurs in an originally healthy colonic segment due to an anally located, aganglionic zone. In contrast, in chronic Chagas' disease, the dilated segment itself displays pathohistological changes, and the earliest and most prominent being found was massive loss of myenteric neurons. This neuron loss was partial and selective, i.e. some neurons containing neuronal nitric oxide synthase and/or vasoactive intestinal peptide (VIP) were spared from neuron death. This disproportionate survival of inhibitory neurons, however, did not completely correlate with the calibre change along the surgically removed, megacolonic segments. A better correlation was observed as to potentially contractile muscle tissue elements and the interstitial cells of Cajal. Therefore, the decreased densities of α-smooth muscle actin- and c-kit-immunoreactive profiles were estimated along resected megacolonic segments. Their lowest values were observed in the megacolonic zones itself, whereas less pronounced decreases were found in the non-dilated, transitional zones (oral and anal to dilation). In contrast to the myenteric plexus, the submucosal plexus displayed only a moderate neuron loss. Neurons co-immunoreactive for VIP and calretinin survived disproportionately. As a consequence, these neurons may have contributed to maintain the epithelial barrier and allowed the chagasic patients to survive for decades, despite their severe disturbance of colonic motility. Due to its neuroprotective and neuroeffectory functions, VIP may play a key role in the development and duration of chagasic megacolon. © 2014 The Author(s).
Keywords: Chagas; Enteric nervous system; Hirschsprung; Megacolon; Vasoactive intestinal peptide

Changes in tears and ocular structures involved in tear film formation in chemotherapy-induced polyneuropathy in mice - Welss, Jessica; Phunchago, Nichapa; Sisignano, Marco; Perumal, Natarajan; Grus, Franz; Feldt, Jessica; Lütjen-Drecoll, Elke; Paulsen, Friedrich (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Changes in the conjunctival bacterial flora of patients hospitalized in an intensive care unit - Sahin, Afsun; Yildirim, Nilgun; Gultekin, Saadet; Akgun, Yurdanur; Kiremitci, Abdurrahman; Schicht, Martin; Paulsen, Friedrich (Arquivos Brasileiros De Oftalmologia, 2017)
Purpose:: To identify the changes in aerobic conjunctival bacterial flora and to correlate culture results with physical health and the duration of patients' hospitalization in an intensive care unit (ICU). Methods:: Patients hospitalized in the ICU were included in this study. Conjunctival cultures from all patients were obtained using a standard technique on days 1, 3, 7, and 14. Swabs were plated on nonselective (blood agar) and enriched (chocolate agar) media within one hour. Visible colonies were isolated, and standard microbiological techniques were used to identify the bacteria. The frequency, identity, and correlation of culture results with patients' physical findings and the duration of hospitalization were determined. Results:: We obtained 478 cultures (day 1, 270; day 3, 156; day 7, 36; and day 14, 16) from 135 patients; 288 (60.2%) cultures were positive, and 331 microorganisms were isolated. The most frequently isolated microorganism from the cultures was coagulase-negative Staphylococcus species (n=210/331, 63.5%), and the others were Corynebacterium diphtheriae (n=52/331, 15.7%), S. aureus (n=26/331, 7.9%), gram-negative bacilli other than Pseudomonas (n=14/331, 4.2%), Neisseria species (n=8/331, 2.4%), Pseudomonas aeruginosa (n=6/331, 1.8%), Haemophilus influenzae (n=7/331, 2.1%), Acinetobacter species (n=6/331, 1.8%), and Streptococcus species (n=2/331, 0.6%). The frequency of positive cultures significantly increased (p<0.03) with time. Conclusions:: Prolonged hospitalization significantly predisposes to bacterial colonization. The colonization rate of S. aureus and Neisseria spp. increased significantly after one week.
EVALuna2:35342

Changes of Osteopontin in the Aqueous Humor of the DBA2/J Glaucoma Model Correlated with Optic Nerve and RGC Degenerations - Birke, Marco; Neumann, Carolin; Birke, Kerstin; Kremers, Jan; Scholz, Michael (Investigative Ophthalmology & Visual Science, 2010)
PURPOSE. To identify age-dependent regulated aqueous humor (AH) factors in DBA2/J (D2J) mice and to correlate them with optic nerve degeneration and intraocular pressure (IOP) by population and individual analysis.METHODS. AH samples of D2J mice aged 2 (n = 3), 7 (n = 5), and 10 months (n = 14) were analyzed by mouse cytokine antibody array. Ten-month samples were classified into eyes with (D2J+) or without (D2J-) optic neuropathy. Ten-month-old C57/B16 (B6; n = 13) and DBA2/Rj (D2Rj; n = 15) mice served as controls. IOP was recorded from 2 to 10 months. Individual AH osteopontin (OPN) was determined in 31 D2J eyes (10 months) and was correlated with optic neuropathy and IOP. OPN mRNA was detected by in situ hybridization. OPN blood plasma content of D2J and B6 was monitored from 8 to 10 months. Effect of OPN on cell survival in the ganglion cell layer (GCL) or metabolism was tested in ex vivo-cultured D2Rj eyes and murine neuronal precursors.RESULTS. In array analysis, OPN was detected in 10-month-old D2J mice only. They significantly differed between D2J- and D2J+ (P = 0.006). By Western blot analysis, a sevenfold OPN increase in D2J+ was determined compared with B6. Individual analysis confirmed the positive correlation of OPN with optic neuropathy. IOP was not correlated with OPN. OPN blood plasma contents steadily increased with age in D2J. OPN+ cells were detected within the ciliary body of D2J, and OPN+ RGCs were approximate to 30% reduced. OPN treatment inhibited cell degeneration within the GCL in ex vivo-cultured D2Rj eyes and increased the metabolic activity of neuronal precursor cells.CONCLUSIONS. OPN is an age-dependent increased AH factor associated with degeneration of the optic nerve in D2J mice. By modulating the metabolism of neuronal cells, deregulated levels of OPN could be involved in degenerative processes affecting RGCs or optic nerve axons in the D2J model. (Invest Ophthalmol Vis Sci. 2010; 51:5759-5767) DOI:10.1167/iovs.105558

Characterization of blood-brain barrier integrity in a B-cell-dependent mouse model of multiple sclerosis - Bell, Luisa; Koeniger, Tobias; Tacke, Sabine; Kuerten, Stefanie (Histochemistry and Cell Biology, 2019)
Recent studies with B-cell-depleting antibodies have demonstrated clinical success in the treatment of multiple sclerosis (MS) patients. While these antibodies efficiently target B cells in the blood, it is unclear how effective they are in the central nervous system (CNS), especially in the context of limited blood-brain barrier (BBB) permeability and the ongoing discussion on the relevance of B-cell aggregate formation in the brains of SP-MS patients. The aim of this study was to evaluate BBB integrity in the context of B-cell-dependent neuroinflammation in a mouse model of MS. C57BL/6 mice were actively immunized with either myelin oligodendrocyte glycoprotein peptide 35-55 to induce T-cell-dependent experimental autoimmune encephalomyelitis (EAE), or with the myelin basic protein-proteolipid protein fusion protein MP4 for additional B-cell dependence. BBB integrity was assessed using Evans Blue or fluorescein isothiocyanate-dextran injection, respectively, in combination with immunofluorescence staining for key components of the BBB. In both EAE models, tracer leakage into the CNS parenchyma was observed indicating BBB leakiness. Yet, intensity and distribution patterns of leakage differed between the two models. There was no difference in the severity of BBB damage comparing acute and chronic MP4-induced EAE, but the formation of B-cell aggregates was associated with local BBB impairment in this model. This study underscores that a leaky BBB is a characteristic feature of EAE, but it also suggests that extent and region specificity of BBB damage differs between individual EAE models that vary in the underlying immunopathology.
CRIS-Team WoS Importer:2019-06-18

Characterization of dry eye disease in a mouse model by optical coherence tomography and fluorescein staining - Messner, Alina; Fischak, Corinna; Pfister, Martin; Schuetzenberger, Kornelia; Garreis, Fabian; Paulsen, Friedrich; Stegmann, Hannes; Dos Santos, Valentin Aranha; Garhoefer, Gerhard; Schmetterer, Leopold; Werkmeister, Rene M. (Biomedical Optics Express, 2019)
A custom-built ultrahigh-resolution optical coherence tomography (UHR-OCT) system and fluorescein staining were employed tier investigation of a scopolamine induced dry eye mouse model. Acquired data was used to evaluate common and complementary findings of the two modalities. Central corneal thickness as measured by UHR-OCT increased significantly over the study period of 24 hours, from 89.0 +/- 3.57 mu m to 92.2 +/- 4.07 mu m. Both techniques were able to show corneal lesions with a large range of severity. Localized fluorescein staining was detected in 5% and diffuse staining in 45 % of cases where no epithelial damage was visible with OCT. However, OCT revealed stromal defects in 6% and endothelial defects in 18% of the cases, which could not be visualized via fluorescein staining. Thus, while fluorescein staining widely detected defects of the corneal surface in a mouse model of dry eye disease, OCT non-invasively revealed additional intimation about defect depth and involvement of particular layers. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-09-20

Characterization of Neurochemical Signature Alterations in the Enteric Nervous System in Autoimmune Encephalomyelitis - Kicherer, Julia; Weier, Alicia; Enders, Michael; Neuhuber, Winfried; Heider, Thorsten; Kürten, Stefanie (Applied Sciences, 2022)
To date, it has remained unclear whether gastrointestinal symptoms, which are frequently observed in patients with multiple sclerosis (MS), are accompanied by pathology of the enteric nervous system (ENS). Here, the neurotransmitter signature of ENS neurons and morphological alterations of interstitial cells of Cajal (ICCs) were studied in patients with MS and mice with experimental autoimmune encephalomyelitis (EAE), which is an animal model of MS. Immunohistochemical analysis was performed on colonic whole mounts from mice with EAE and on paraffin-embedded sections of intestinal tissue from patients with MS. Antibodies against neurotransmitters or their enzymes (including vasoactive intestinal peptide (VIP), neuronal nitric oxide synthase (nNOS), and choline acetyltransferase (ChAT)) were used in conjunction with pan-neuronal markers. In addition, the presence of anoctamin 1 (ANO1)-expressing ICCs was studied. ENS changes were observed in the myenteric plexus, but they were absent in the submucosal plexus of both EAE mice and patients with MS. There was a significant decrease in the percentage of ChAT-positive neurons in EAE mice as opposed to a trend toward an increase in patients with MS. Moreover, while ANO1 expression was decreased in EAE mice, patients with MS displayed a significant increase. Although additional studies are necessary to accomplish an in-depth characterization of ENS alterations in MS, our results imply that such alterations exist and may reveal novel insights into the pathophysiology of MS.
CRIS-Team WoS Importer:2022-07-08

Characterization of the Cancer-Associated Meprin Βeta Variants G45R and G89R - Gellrich, Antonin; Scharfenberg, Franka; Peters, Florian; Sammel, Martin; Helm, Ole; Armbrust, Fred; Schmidt, Frederike; Lokau, Juliane; Garbers, Christoph; Sebens, Susanne; Arnold, Philipp; Becker-Pauly, Christoph (Frontiers in Molecular Biosciences, 2021)
Meprin β is a metalloprotease associated with neurodegeneration, inflammation, extracellular matrix homeostasis, transendothelial cell migration, and cancer. In this study, we investigated two melanoma-associated variants of meprin β, both exhibiting a single amino acid exchange, namely, meprin β G45R and G89R. Based on the structural data of meprin β and with regard to the position of the amino acid exchanges, we hypothesized an increase in proteolytic activity in the case of the G45R variant due to the induction of a potential new activation site and a decrease in proteolytic activity from the G89R variant due to structural instability. Indeed, the G89R variant showed, overall, a reduced expression level compared to wild-type meprin β, accompanied by decreased activity and lower cell surface expression but strong accumulation in the endoplasmic reticulum. This was further supported by the analysis of the shedding of the interleukin-6 receptor (IL-6R) by meprin β and its variants. In transfected HEK cells, the G89R variant was found to generate less soluble IL-6R, whereas the expression of meprin β G45R resulted in increased shedding of the IL-6R compared to wild-type meprin β and the G89R variant. A similar tendency of the induced shedding capacity of G45R was seen for the well-described meprin β substrate CD99. Furthermore, employing an assay for cell migration in a collagen IV matrix, we observed that the transfection of wild-type meprin β and the G45R variant resulted in increased migration of HeLa cells, while the G89R variant led to diminished mobility.
CRIS-Team Scopus Importer:2021-10-29
Keywords: ADAM; APP; CD99; IL-6; meprin; metalloprotease; sheddase

Characterization of the innervation of the meibomian glands in humans, rats and mice - Bründl, Maximilian; Garreis, Fabian; Schicht, Martin; Dietrich, Jana; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2020)
Aim of the present study was to identify the nerve structures of meibomian glands in humans, rats and mice into sympathetic, parasympathetic and sensory parts as well as their topographical relation with regard to the gland architecture. The upper and lower eyelids of humans, rats and mice were examined by means of immunohistochemistry and indirect immunofluorescence. Specimen were investigated with antibodies against vesicular acetylcholine transporter (VAChT), tyrosine hydroxylase (TH), nitric oxide synthase (NOS), and calcitonin gene-related peptide (CGRP). For overview and general identification of the nervous structures, protein gene product 9.5 (PGP 9.5) was used. PGP-immunoreactive nerve fibers were detectable in the interstitium of the meibomian glands, especially in the neighborhood to the basement membrane of the acini. The axons were positive for CGRP, VAChT, TH and NOS. In addition, the fluorescence labeling also revealed isolated nerve endings surrounding the duct system of the glands, especially along the main duct and in adjacent blood vessels. The density of the innervation of the meibomian glands and the detection of various neuropeptides suggest an influence of the nervous system on the function of the glands. To what extent these may play a role in the modulation of glandular function and the pathogenesis of dry eye disease, or perhaps even represent a possible therapeutic approach, needs further investigation.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Innervation; Meibomian gland; Neurotransmitter; Ocular surface; Tear film

Characterization of the mucocutaneous junction of the human eyelid margin and meibomian glands with different biomarkers - Tektas, Ozan Yüksel; Yadav, Ajay; Garreis, Fabian; Schlötzer-Schrehardt, Ursula; Schicht, Martin; Hampel, Ulrike; Bräuer, Lars; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2012)
To investigate the morphology of the human eyelid margin and the presence of different cytokeratins, mucins and stem cell markers within the skin epithelium, mucocutaneous junction (MCJ) and palpebral conjunctiva.Eyelids of body donors were investigated histologically and ultrastructurally as well as by immunohistochemical methods using antibodies to cytokeratins 1, 4, 7, 8, 10, 13, 14, 15, and 19; mucins MUC1, MUC4, and MUC5AC and potential stem cell markers K15, BCRP/ABCG2, integrin ?1, and N-cadherin.The expression pattern of cytokeratins, mucins and stem cell markers varied across the different epithelia of the human eyelid. Within the MCJ, CK7, 15 and 19 were absent, whereas the epithelium reacted positive to antibodies to CK1, 4, 8, 10, 13 and 14. Reactivity was also observed for MUC1 and MUC4, but not for MUC5AC. No reactivity was determined for K15, BCRP/ABCG2 and integrin ?1 in the area of the MCJ epithelium but a strong reactivity was present for N-cadherin.The present immunohistochemical findings lead to a better characterization of the MCJ. Additionally, the knowledge of distribution of biomarkers like cytokeratins, mucins and stem cells can be useful in the investigation of MCJ disturbances which occur in several disorders of the meibomian glands and the lid epithelium in the course of dry eye syndrome and especially meibomian gland dysfunction.
EVALuna2:4382

ChAT and NOS in human myenteric neurons: Co-existence and co-absence - Beck, Martin; Schlabrakowski, Anne; Schrödl, Falk; Neuhuber, Winfried; Brehmer, Axel (Cell and Tissue Research, 2009)
Most myenteric neurons contain one of the two generating enzymes for major excitatory and inhibitory neurotransmitters: choline acetyltransferase (ChAT) or neuronal nitric oxide synthase (NOS). Two minor groups of myenteric neurons contain either both enzymes or neither. Our study had two aims: (1) to compare the proportions of neurons stained for ChAT and/or NOS in human small and large intestinal whole-mounts by co-staining with an antibody against the human neuronal protein Hu C/D (HU); (2) to characterize these neurons morphologically by co-staining with a neurofilament (NF) antibody. In small intestinal whole-mounts co-stained with HU, we counted more ChAT-positive (ChAT+) than NOS+ neurons (52% vs. 38%), whereas the large intestine exhibited fewer ChAT+ than NOS+ neurons (38% vs. 50%). Neurons co-reactive for both ChAT and NOS accounted for about 3% in both regions, whereas neurons negative for both enzymes accounted for 7% in the small intestine and 8% in the large intestine. Co-staining with NF revealed that, in both small and large intestine, ChAT+/NOS+ neurons were either spiny (type I) neurons or displayed smaller perikarya that were weakly or not NF-stained. Of all spiny neurons, almost one third was co-reactive for ChAT and NOS, whereas nearly two thirds were positive only for NOS. Neurons negative for both ChAT and NOS were heterogeneous in size and NF reactivity. Thus, neither the co-existence nor the co-absence of ChAT and NOS in human myenteric neurons is indicative for particular neuron types, with several qualitative and quantitative parameters showing a wide range of interindividual variability. © 2009 Springer-Verlag.
Keywords: Chemical code; Enteric nervous system; Gut; Human; Morphology; Neuronal NOS

Chemical coding of myenteric neurons with different axonal projection patterns in the porcine ileum - Jungbauer, Carsten; Lindig, Tobias; Schrödl, Falk; Neuhuber, Winfried; Brehmer, Axel (Journal of Anatomy, 2006)
The aim of this study was to perform an immunohistochemical characterization of two different myenteric neuron types of the pig displaying opposite axonal projections. These were type I neurons equipped with lamellar dendrites that projected mainly orally, and type VI neurons that displayed typical axonal dendrites and projected anally. Double immunostainings of longitudinal muscle/myenteric plexus wholemounts from ileal segments of four pigs were performed to visualize neurofilaments (NF) in combination with calcitonin gene-related peptide (CGRP), leu-enkephalin (ENK) and substance P (SP), respectively. Triple immunostainings of wholemounts, using antibodies against neuronal nitric oxide synthase (nNOS) and vasoactive intestinal peptide (VIP) as well as against VIP and galanin (GAL), were performed. We found that 78% of type I neurons immunoreacted to ENK, 21% to CGRP and 24% to SP. The NF-positive type I neurons co-reactive for one of the three above markers displayed mostly frayed outlines of both their somal contours and their broadened dendritic endings. By contrast, most of the non-coreactive type I neurons displayed rather sharply outlined somata and dendrites. No type I neuron immunoreacted to nNOS, VIP or GAL and none of the type VI NF-reactive neurons reacted to CGRP, ENK or SP. All type VI neurons investigated displayed immunoreactivity for nNOS, 92% of which were co-reactive for VIP. Co-reactivity for VIP and GAL was found in 69% of type VI neurons, 21% were positive for VIP but negative for GAL, 9% were negative for both GAL and VIP, and 1% were positive for GAL but negative for VIP. We conclude that there are two subpopulations of morphological type I neurons. One of these displays mainly oral projections and could not be further characterized in this study. The other, which may correspond to neurons innervating the longitudinal and circular muscle layers, were partly immunoreactive for ENK, CGRP and/or SP. Type VI neurons are immunoreactive for nNOS frequently co-localized with VIP and, partly, also GAL. These may be inhibitory motor neurons and are different from VIP/GAL-coreactive minineurons described earlier. © 2006 The Authors Journal compilation © 2006 Anatomical Society of Great Britain and Ireland.
Keywords: Chemical coding; Enteric nervous system; Gut; Innervation; Neuron type

Chemical coding of submucosal type V neurons in porcine ileum - Kapp, Sonja; Schrödl, Falk; Neuhuber, Winfried; Brehmer, Axel (Cells Tissues Organs, 2006)
In this study, we attempted to determine the proportion of type V neurons relative to the putative whole neuron population in the two submucosal plexuses of pigs identified by their neurofilament immunoreactivity. The total neuron number was estimated in cuprolinic blue (CB)/anti-Hu protein (HU) costained wholemounts as the sum of the number of CB+/HU+, CB+/HU- and CB-/HU+ neurons. In the external submucosal plexus (ESP), HU labelled 98.6% and CB 97.3% of neurons. In the internal submucosal plexus, HU labelled 98.3%, whereas CB only marked 92.5% of neurons. Furthermore, we investigated the chemical coding of submucosal type V neurons and searched for submucosal, non-type V neurons displaying the same chemical coding as the myenteric type V neurons described earlier, i.e. the colocalization of calcitonin gene-related peptide (CGRP) and somatostatin (SOM). In order to facilitate immunohistochemical detection of neuroactive peptides, ileal segments were pretreated with colchicine prior to fixation. Type V neurons in the ESP occurred either as single cells displaying one or few prominent dendrite(s) or within aggregates displaying a dendritic tangle. In this plexus, type V neurons amounted to between 0.9 and 1.6% of all CB-stained neurons. ESP type V neurons displayed immunoreactivities for choline acetyl transferase (95.8%) and leucine-enkephalin (73.9%). All type V neurons were negative for neuronal nitric oxide synthase. Fifty-eight percent of ESP CGRP/SOM co-immunoreactive neurons displayed type V morphology, whereas 42% were non-type V neurons. Thus, the chemical coding of ESP type V neurons is in principal similar to that of the myenteric type V neurons described earlier. In the internal submucosal plexus, we found no type V neurons. In this plexus, 0.2% of all neurons counterstained with HU displayed CGRP/SOM coreactivity. As had been observed earlier concerning the myenteric type V neurons, ESP type V neurons were also closely apposed by conspicuous accumulations of boutons reactive for the same markers as the neurons themselves. Although we cannot exclude that axons of CGRP/SOM-reactive enteric, non-type V or extrinsic neurons end synaptically on type V neurons, we suggest that the main synaptic input to type V neurons originates from other type V neurons. This presents an argument for an interneuronal role of type V neurons. Copyright © 2006 S. Karger AG.
Keywords: Chemical coding; Neuron type; Submucosal plexus

Chemokine and cytokine levels in osteoarthritis and rheumatoid arthritis synovial fluid - Hampel, Ulrike; Sesselmann, Stefan; Iserovich, Pavel; Sel, Saadettin; Paulsen, Friedrich; Sack, Robert (Journal of Immunological Methods, 2013)
To develop a method of the assay of chemokine and cytokine signaling in synovial fluid from patients suffering from osteoarthritis (OA) or rheumatoid arthritis (RA) and evaluate the effect of heterophilic antibodies on the reliability of the data.21 synovial fluid samples from OA and 16 synovial fluid samples from RA patients were analyzed using a unique 2 step dot sandwich ELISA based micro-well protein array designed to detect heterophilic antibody signaling in the presence or absence of an effective heterophilic blocking reagent with assays carried out for Eotaxin, hGROa, interleukin (IL)-8, IP10, MCP-1, MCP-2, MIG, RANTES, TARC and IL-6.Array analysis reveals that the selective presence of heterophilic antibodies interferes with the accurate assay of synovial fluid samples from a minority of RA patients but not OA synovia. Using a commercial blocking diluent OA and RA synovial fluids reveal significant differences in chemokine content (IL-6, Eotaxin, hGROa, MCP-2, MIG, TARC, IL-8, RANTES).Using a two-step assay protocol it is possible to readily detect inappropriate antibody signaling due to heterophilic antibodies and devise a protocol designed to eliminate this problem thereby more accurately quantify cytokines and chemokines specific to both RA and OA fluids. © 2013 Elsevier B.V.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Arthritis; Chemokine; Cytokine; ELISA; Heterophilic antibody; Interference

Chemotherapy-induced release of ADAM17 bearing EV as a potential resistance mechanism in ovarian cancer - Hugendieck, Gerrit; Lettau, Marcus; Andreas, Svenja; Neumann, Sabrina; Reinhardt, Natalie; Arnold, Philipp; Theilig, Franziska; Bastian, Lorenz; Rogmans, Christoph; Weimer, Jörg P.; Flörkemeier, Inken; Wesch, Daniela; et al. (Journal of Extracellular Vesicles, 2023)
Ovarian cancer (OvCa) is the gynaecological disorder with the poorest prognosis due to the fast development of chemoresistance. We sought to connect chemoresistance and cancer cell-derived extracellular vesicles (EV). The mechanisms of how chemoresistance is sustained by EV remained elusive. One potentially contributing factor is A Disintegrin and Metalloprotease 17 (ADAM17)—itself being able to promote chemoresistance and inducing tumour cell proliferation and survival via the Epidermal Growth Factor Receptor (EGFR) pathway by shedding several of its ligands including Amphiregulin (AREG). We now demonstrate that upon chemotherapeutic treatment, proteolytically active ADAM17 is released in association with EV from OvCa cells. In terms of function, we show that patient-derived EV induce AREG shedding and restore chemoresistance in ADAM17-deficient cells. Confirming that ADAM17-containing EV transmit chemoresistance in OvCa, we propose that ADAM17 levels (also on EV) might serve as an indicator for tumour progression and the chemosensitivity status of a given patient.
CRIS-Team Scopus Importer:2023-08-25
Keywords: ADAM17; ascites; chemoresistance; extracellular vesicles; ovarian cancer

Chest CT Cinematic Rendering of SARS-CoV-2 Pneumonia - Necker, Fabian N.; Scholz, Michael (Radiology, 2022)
The SARS-CoV-2 pandemic has spread rapidly throughout the world since its first reported infection in Wuhan, China. Despite the introduction of vaccines for this viral infection, there remains a significant public health risk to the population as this virus continues to mutate. While it remains unknown if these new mutations will evade the current vaccines, there is a possibility that we may be living with this infection for many years to come as it becomes endemic. Cinematic rendering of CT images is a new way to show the three-dimensionality of the various densities of different pneumonia-affected lung tissues contained in volumetric CT data. We show an example of a patient with polymerase chain reaction-positive SARS-CoV-2 pneumonia using this new technique in the Figure (Figure). This case is from the RSNA International COVID-19 Open Radiology Database (RICORD) data set (1–3). It shows the typical presentation of SARS-CoV-2 pneumonia with ground-glass subpleural opacities that are clearly seen in both parts of the Figure and in the Movie (online). The higher attenuation of lung tissue filled with fluid results in these areas appearing patchy or spongy.
CRIS-Team Scopus Importer:2022-06-10

CILIARY MUSCLE AND CILIARY PROCESS' AREA: AGING CHANGES VERSUS LENS DIMENSIONS AT REST AND DURING ACCOMMODATION - Croft, Mary Ann; Nork, T. Michael; Mcdonald, Jared P.; Heatley, Gregg A.; Lütjen-Drecoll, Elke; Kaufman, Paul L. (2018)
EVALuna2:35311

Cinematic Rendering in anatomical teaching - a new tool for lecturers and students - Scholz, Michael (JOURNAL OF ANATOMY, 2020)
CRIS-Team WoS Importer:2020-04-24

Cinematic Rendering in Anatomy: A Crossover Study Comparing a Novel 3D Reconstruction Technique to Conventional Computed Tomography - Binder, Johannes; Scholz, Michael; Ellmann, Stephan; Uder, Michael; Grützmann, Robert; Krautz, Christian; Weber, Georg (Anatomical Sciences Education, 2020)
Integration of medical imaging into preclinical anatomy courses is already underway in many medical schools. However, interpretation of two-dimensional grayscale images is difficult and conventional volume rendering techniques provide only images of limited quality. In this regard, a more photorealistic visualization provided by Cinematic Rendering (CR) may be more suitable for anatomical education. A randomized, two-period crossover study was conducted from July to December 2018, at the University Hospital of Erlangen, Germany to compare CR and conventional computed tomography (CT) imaging for speed and comprehension of anatomy. Sixteen students were randomized into two assessment sequences. During each assessment period, participants had to answer 15 anatomy-related questions that were divided into three categories: parenchymal, musculoskeletal, and vascular anatomy. After a washout period of 14 days, assessments were crossed over to the respective second reconstruction technique. The mean interperiod differences for the time to answer differed significantly between the CR-CT sequence (-204.21 +/- 156.0 seconds) and the CT-CR sequence (243.33 +/- 113.83 seconds;P < 0.001). Overall time reduction by CR was 65.56%. Cinematic Rendering visualization of musculoskeletal and vascular anatomy was higher rated compared to CT visualization (P P = 0.003), whereas CT visualization of parenchymal anatomy received a higher scoring than CR visualization (P < 0.001). No carryover effects were observed. A questionnaire revealed that students consider CR to be beneficial for medical education. These results suggest that CR has a potential to enhance knowledge acquisition and transfer from medical imaging data in medical education.
CRIS-Team WoS Importer:2020-07-17

Cinematic rendering to improve visualization of supplementary and ectopic teeth using CT datasets - Willershausen, Ines; Necker, Fabian; Kloeckner, Roman; Seidel, Corinna Lesley; Paulsen, Friedrich; Gölz, Lina; Scholz, Michael (Dentomaxillofacial Radiology, 2023)
OBJECTIVES: Ectopic, impacted, and supplementary teeth are the number one reason for cross-sectional imaging in pediatric dentistry. The accurate post-processing of acquired data sets is crucial to obtain precise, yet also intuitively understandable three-dimensional (3D) models, which facilitate clinical decision-making and improve treatment outcomes. Cinematic rendering (CR) is anovel visualization technique using physically based volume rendering to create photorealistic images from DICOM data. The aim of the present study was to tailor pre-existing CR reconstruction parameters for use in dental imaging with the example of the diagnostic 3D visualization of ectopic, impacted, and supplementary teeth. METHODS: CR was employed for the volumetric image visualization of midface CT data sets. Predefined reconstruction parameters were specifically modified to visualize the presented dental pathologies, dentulous jaw, and isolated teeth. The 3D spatial relationship of the teeth, as well as their structural relationship with the antagonizing dentition, could immediately be investigated and highlighted by separate, interactive 3D visualization after segmentation through windowing. RESULTS: To the best of our knowledge, CR has not been implemented for the visualization of supplementary and ectopic teeth segmented from the surrounding bone because the software has not yet provided appropriate customized reconstruction parameters for dental imaging. When employing our new, modified reconstruction parameters, its application presents a fast approach to obtain realistic visualizations of both dental and osseous structures. CONCLUSIONS: CR enables dentists and oral surgeons to gain an improved 3D understanding of anatomical structures, allowing for more intuitive treatment planning and patient communication.
CRIS-Team Scopus Importer:2023-05-05
Keywords: 3D visualization; CBCT; CT; dental anatomy; dental radiology; volume rendering

Circadian Rhythm of VIP in Chicken Intrinsic Choroidal Neurons - Hohberger, Bettina; Lessberger, Carmen; Hermann, Franz; Zenkel, Matthias; Bergua, Antonio; Neuhuber, Winfried (2016)
EVALuna2:184249

Circumpunctal nevus - Ali, Mohammad Javed; Paulsen, Friedrich (Saudi Journal of Ophthalmology, 2018)
CRIS-Team Scopus Importer:2022-08-05

Citrate-coated superparamagnetic iron oxide nanoparticles enable a stable non-spilling loading of t cells and their magnetic accumulation - Boosz, Philipp; Pfister, Felix; Stein, René; Friedrich, Bernhard; Fester, Lars; Band, Julia; Mühlberger, Marina; Schreiber, Eveline; Lyer, Stefan; Dudziak, Diana; Alexiou, Christoph; Janko, Christina (Cancers, 2021)
T cell infiltration into a tumor is associated with a good clinical prognosis of the patient and adoptive T cell therapy can increase anti-tumor immune responses. However, immune cells are often excluded from tumor infiltration and can lack activation due to the immune-suppressive tumor microenvironment. To make T cells controllable by external forces, we loaded primary human CD3+ T cells with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONs). Since the efficacy of magnetic targeting depends on the amount of SPION loading, we investigated how experimental conditions influence nanoparticle uptake and viability of cells. We found that loading in the presence of serum improved both the colloidal stability of SPIONs and viability of T cells, whereas stimulation with CD3/CD28/CD2 and IL-2 did not influence nanoparticle uptake. Further-more, SPION loading did not impair cytokine secretion after polyclonal stimulation. We finally achieved 1.4 pg iron loading per cell, which was both located intracellularly in vesicles and bound to the plasma membrane. Importantly, nanoparticles did not spill over to non-loaded cells. Since SPION-loading enabled efficient magnetic accumulation of T cells in vitro under dynamic condi-tions, we conclude that this might be a good starting point for the investigation of in vivo delivery of immune cells.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Adoptive T cell transfer; Immune therapy; Magnetic targeting; Nanomedicine; Solid tumor; Superparamagnetic iron oxide nanoparticles (SPIONs); Targeted transport

Classification of human enteric neurons - Brehmer, Axel (Histochemistry and Cell Biology, 2021)
Major advances in our understanding of the functional heterogeneity of enteric neurons are driven by the application of newly developed, innovative methods. In contrast to this progress, both animal and human enteric neurons are usually divided into only two morphological subpopulations, "Dogiel type II" neurons (with several long processes) and "Dogiel type I" neurons (with several short processes). This implies no more than the distinction of intrinsic primary afferent from all other enteric neurons. The well-known chemical and functional diversity of enteric neurons is not reflected by this restrictive dichotomy of morphological data. Recent structural investigations of human enteric neurons were performed by different groups which mainly used two methodical approaches, namely detecting the architecture of their processes and target-specific tracing of their axonal courses. Both methods were combined with multiple immunohistochemistry in order to decipher neurochemical codes. This review integrates these morphological and immunohistological data and presents a classification of human enteric neurons which we believe is not yet complete but provides an essential foundation for the further development of human gastrointestinal neuropathology.
CRIS-Team WoS Importer:2021-07-23

Class switch towards non-inflammatory, spike-specific IgG4 antibodies after repeated SARS-CoV-2 mRNA vaccination - Irrgang, Pascal; Gerling, Juliane; Kocher, Katharina; Lapuente, Dennis; Steininger, Philipp; Habenicht, Katharina Marie; Wytopil, Monika; Beileke, Stephanie; Schäfer, Simon; Zhong, Jahn; Ssebyatika, George; Krey, Thomas; et al. (Science immunology, 2022)
RNA vaccines are efficient preventive measures to combat the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. High levels of neutralizing SARS-CoV-2 antibodies are an important component of vaccine-induced immunity. Shortly after the initial two mRNA vaccine doses, the immunoglobulin G (IgG) response mainly consists of the proinflammatory subclasses IgG1 and IgG3. Here, we report that several months after the second vaccination, SARS-CoV-2–specific antibodies were increasingly composed of noninflammatory IgG4, which were further boosted by a third mRNA vaccination and/or SARS-CoV-2 variant breakthrough infections. IgG4 antibodies among all spike-specific IgG antibodies rose, on average, from 0.04% shortly after the second vaccination to 19.27% late after the third vaccination. This induction of IgG4 antibodies was not observed after homologous or heterologous SARS-CoV-2 vaccination with adenoviral vectors. Single-cell sequencing and flow cytometry revealed substantial frequencies of IgG4-switched B cells within the spike-binding memory B cell population [median of 14.4%; interquartile range (IQR) of 6.7 to 18.1%] compared with the overall memory B cell repertoire (median of 1.3%; IQR of 0.9 to 2.2%) after three immunizations. This class switch was associated with a reduced capacity of the spike-specific antibodies to mediate antibody-dependent cellular phagocytosis and complement deposition. Because Fc-mediated effector functions are critical for antiviral immunity, these findings may have consequences for the choice and timing of vaccination regimens using mRNA vaccines, including future booster immunizations against SARS-CoV-2.<br

Clinical and immunological benefits of full primary COVID-19 vaccination in individuals with SARS-CoV-2 breakthrough infections: A prospective cohort study in non-hospitalized adults - Prelog, Martina; Jeske, Samuel D.; Asam, Claudia; Fuchs, Andre; Wieser, Andreas; Gall, Christine; Wytopil, Monika; Müller-Schmucker, Sandra; Beileke, Stephanie; Goekkaya, Mehmet; Kling, Elisabeth; Geldmacher, Christof; et al. (Journal of Clinical Virology, 2024)
Background: SARS-CoV-2 variants of concern (VOC) may result in breakthrough infections (BTIs) in vaccinated individuals. The aim of this study was to investigate the effects of full primary (two-dose) COVID-19 vaccination with wild-type-based SARS-CoV-2 vaccines on symptoms and immunogenicity of SARS-CoV-2 VOC BTIs. Methods: In a longitudinal multicenter controlled cohort study in Bavaria, Germany, COVID-19 vaccinated and unvaccinated non-hospitalized individuals were prospectively enrolled within 14 days of a PCR-confirmed SARS-CoV-2 infection. Individuals were visited weekly up to 4 times, performing a structured record of medical data and viral load assessment. SARS-CoV-2-specific antibody response was characterized by anti-spike-(S)- and anti-nucleocapsid-(N)-antibody concentrations, anti-S-IgG avidity and neutralization capacity. Results: A total of 300 individuals (212 BTIs, 88 non-BTIs) were included with VOC Alpha or Delta SARS-CoV-2 infections. Full primary COVID-19 vaccination provided a significant effectiveness against five symptoms (relative risk reduction): fever (33 %), cough (21 %), dysgeusia (22 %), dizziness (52 %) and nausea/vomiting (48 %). Full primary vaccinated individuals showed significantly higher 50 % inhibitory concentration (IC50) values against the infecting VOC compared to unvaccinated individuals at week 1 (269 vs. 56, respectively), and weeks 5–7 (1,917 vs. 932, respectively) with significantly higher relative anti-S-IgG avidity (78% vs. 27 % at week 4, respectively). Conclusions: Full primary COVID-19 vaccination reduced symptom frequencies in non-hospitalized individuals with BTIs and elicited a more rapid and longer lasting neutralization capacity against the infecting VOC compared to unvaccinated individuals. These results support the recommendation to offer at least full primary vaccination to all adults to reduce disease severity caused by immune escape-variants.
CRIS-Team Scopus Importer:2023-12-29
Keywords: Antibodies; Breakthrough infection; COVID-19 symptoms; SARS-CoV-2; Vaccine effectiveness; Viral load

Clinical relevance of systematic phenotyping and exome sequencing in patients with short stature - Hauer, Nadine; Popp, Bernt; Schoeller, Eva; Schuhmann, Sarah; Heath, Karen E.; Hisado-Oliva, Alfonso; Klinger, Patricia; Kraus, Cornelia; Trautmann, Udo; Zenker, Martin; Zweier, Christiane; Wiesener, Antje; et al. (Genetics in Medicine, 2018)
PurposeShort stature is a common condition of great concern to patients and their families. Mostly genetic in origin, the underlying cause often remains elusive due to clinical and genetic heterogeneity.MethodsWe systematically phenotyped 565 patients where common nongenetic causes of short stature were excluded, selected 200 representative patients for whole-exome sequencing, and analyzed the identified variants for pathogenicity and the affected genes regarding their functional relevance for growth.ResultsBy standard targeted diagnostic and phenotype assessment, we identified a known disease cause in only 13.6% of the 565 patients. Whole-exome sequencing in 200 patients identified additional mutations in known short-stature genes in 16.5% of these patients who manifested only part of the symptomatology. In 15.5% of the 200 patients our findings were of significant clinical relevance. Heterozygous carriers of recessive skeletal dysplasia alleles represented 3.5% of the cases.ConclusionA combined approach of systematic phenotyping, targeted genetic testing, and whole-exome sequencing allows the identification of the underlying cause of short stature in at least 33% of cases, enabling physicians to improve diagnosis, treatment, and genetic counseling. Exome sequencing significantly increases the diagnostic yield and consequently care in patients with short stature.
EVALuna2:34628

Co-expression pattern of neuronal nitric oxide synthase and two variants of choline acetyltransferase in myenteric neurons of porcine ileum - Brehmer, Axel; Schrödl, Falk; Neuhuber, Winfried; Tooyama, Ikuo; Kimura, Hiroshi (Journal of Chemical Neuroanatomy, 2004)
Cholinergic enteric neurons were demonstrated immunohistochemically so far by using antibodies staining the common choline acetyltransferase (cChAT) in neurons of the central nervous system. The results of staining in the enteric nervous system of various species were, however, not satisfactory. We describe here findings obtained with a newly raised antibody against a peripheral variant of choline acetyltransferase (pChAT) in myenteric neurons of the pig small intestine. Triple labelling for pChAT/cChAT/neuronal nitric oxide synthase (nNOS) revealed 19.7% of 1664 neurons (within 40 ganglia) to be immunoreactive exclusively for pChAT whereas 29.6% were positive for cChAT alone and 18.8% were reactive only for nNOS. Colocalization of pChAT and cChAT was found in 22.4%, of pChAT and nNOS in 8.1% and of cChAT and nNOS in 1.4%. All three markers were simultaneously found in only 1 of 1664 neurons. To investigate the presence and possible colocalization of the above markers within morphologically defined neuron types, triple labelling of cChAT or nNOS with pChAT and a neurofilament (NF) antibody pool was applied and the coexpression patterns of pChAT and cChAT as well as of pChAT and nNOS in 120 neurons of each type were recorded. All type I, II, IV and V neurons displayed immunoreactivity either for one or both cholinergic markers. These neuron types were considered to be cholinergic. All type VI neurons, a descending neuron population, were negative for cChAT but positive for nNOS. However, 95% were immunoreactive for both pChAT and nNOS. The physiological significance of the possible co-existence of acetylcholine and nitric oxide within type VI neurons remains to be clarified. It is concluded that the pChAT and cChAT antibodies used here recognize partly different populations of enteric neurons in the pig. Thus, for total immunohistochemical characterization of cholinergic enteric neurons both forms of choline acetyltransferase have to be considered. © 2003 Elsevier B.V. All rights reserved.
Keywords: Acetylcholine; Cholinergic; Innervation; Intestine; Morphology; Nitrergic; Peripheral ChAT

Combination of BMP2 and MSCs Significantly Increases Bone Formation in the Rat Arterio-Venous Loop Model - Bührer, Gregor; Balzer, Amelie; Arnold, Isabel; Beier, Justus; Körner, Carolin; Bleiziffer, Oliver; Brandl, Andreas; Weis, Christian; Horch, Raymund E.; Kneser, Ulrich; Arkudas, Andreas (Tissue Engineering - Part A, 2015)

Common genetic determinants of intraocular pressure and primary open-angle glaucoma - Van Koolwijk, Leonieke M. E.; Ramdas, Wishal D.; Ikram, M. Kamran; Jansonius, Nomdo M.; Pasutto, Francesca; Hysi, Pirro G.; Macgregor, Stuart; Janssen, Sarah F.; Hewitt, Alex W.; Viswanathan, Ananth C.; Ten Brink, Jacoline B.; Hosseini, S. Mohsen; et al. (PLoS Genetics, 2012)
Intraocular pressure (IOP) is a highly heritable risk factor for primary open-angle glaucoma and is the only target for current glaucoma therapy. The genetic factors which determine IOP are largely unknown. We performed a genome-wide association study for IOP in 11,972 participants from 4 independent population-based studies in The Netherlands. We replicated our findings in 7,482 participants from 4 additional cohorts from the UK, Australia, Canada, and the Wellcome Trust Case-Control Consortium 2/Blue Mountains Eye Study. IOP was significantly associated with rs11656696, located in GAS7 at 17p13.1 (p=1.4×10(-8)), and with rs7555523, located in TMCO1 at 1q24.1 (p=1.6×10(-8)). In a meta-analysis of 4 case-control studies (total N = 1,432 glaucoma cases), both variants also showed evidence for association with glaucoma (p=2.4×10(-2) for rs11656696 and p=9.1×10(-4) for rs7555523). GAS7 and TMCO1 are highly expressed in the ciliary body and trabecular meshwork as well as in the lamina cribrosa, optic nerve, and retina. Both genes functionally interact with known glaucoma disease genes. These data suggest that we have identified two clinically relevant genes involved in IOP regulation.
EVALuna2:9127

Common genetic variants associated with open-angle glaucoma - Ramdas, Wishal D.; Van Koolwijk, Leonieke M. E.; Lemij, Hans G.; Pasutto, Francesca; Cree, Angela J.; Thorleifsson, Gudmar; Janssen, Sarah F.; Jacoline, Ten Brink; Amin, Najaf; Rivadeneira, Fernando; Wolfs, Roger C. W.; Walters, G. Bragi; et al. (Human Molecular Genetics, 2011)
Open-angle glaucoma (glaucoma) is a major eye disorder characterized by optic disc pathology. Recent genome-wide association studies identified new loci associated with clinically relevant optic disc parameters, such as the optic disc area and vertical cup-disc ratio (VCDR). We examined to what extent these loci are involved in glaucoma. The loci studied include ATOH7, CDC7/TGFBR3 and SALL1 for optic disc area, and CDKN2B, SIX1, SCYL1/LTBP3, CHEK2, ATOH7 and DCLK1 for VCDR. We performed a meta-analysis using data from six independent studies including: the Rotterdam Study (n= 5736), Genetic Research in Isolated Populations combined with Erasmus Rucphen Family study (n= 1750), Amsterdam Glaucoma Study (n= 296) and cohorts from Erlangen and Tübingen (n= 1363), Southampton (n= 702) and deCODE (n= 36 151) resulting in a total of 3161 glaucoma cases and 42 837 controls. Of the eight loci, we found significant evidence (P= 1.41 × 10(-8)) for the association of CDKN2B with glaucoma [odds ratio (OR) for those homozygous for the risk allele: 0.76; 95% confidence interval (CI): 0.70-0.84], for the role of ATOH7 (OR: 1.28; 95% CI: 1.12-1.47) and for SIX1 (OR: 1.20; 95% CI: 1.10-1.31) when adjusting for the number of tested loci. Furthermore, there was a borderline significant association of CDC7/TGFBR3 and SALL1 (both P= 0.04) with glaucoma. In conclusion, we found consistent evidence for three common variants (CDKN2B, ATOH7 and SIX1) significantly associated with glaucoma. These findings may shed new light on the pathophysiological protein pathways leading to glaucoma, and point to pathways involved in the growth and development of the optic nerve.
EVALuna2:9086

Common trunk of the internal thoracic artery, inferior thyroid artery and thyrocervical trunk from the subclavian artery: a rare arterial variant - Westrych, Karolina; Ruzik, Kacper; Zielinska, Nicol; Paulsen, Friedrich; Georgiev, Georgi P.; Olewnik, Lukasz; Labetowicz, Piotr (Surgical and Radiologic Anatomy, 2022)
Purpose In this article, we describe a complex and rare variant of the common trunk arising as a branch of the subclavian artery. This description highlights the clinical relevance of such a variation for medical practice. Methods A routine dissection was carried out on an adult 74-year-old female cadaver. After identification and preparation of the common trunk, measurements and photographs were taken. Results The dissection revealed a common trunk arising from the first part of the left subclavian artery. It divided into the left internal thoracic artery, the inferior thyroid artery, and the thyrocervical trunk. Further on, the branches of the thyrocervical trunk supplied blood to the trapezius muscle, the longus colli muscle and the supraspinatus muscle. Conclusion For the first time, we report the specific appearance of a common trunk from the left subclavian artery that includes the origin of the left internal thoracic artery, inferior thyroid artery, and thyrocervical trunk. Knowledge of the different variations of subclavian branches is essential because of the high frequency with which this region is involved in diagnostic and surgical procedures.
CRIS-Team WoS Importer:2022-07-15

COMPARATIVE ANALYSIS OF INTEGRIN ALPHA 8 EXPRESSION AND ITS LIGANDS FIBRONECTIN AND OSTEOPONTIN IN HUMAN, RAT AND MOUSE PLACENTA - Fahlbusch, Fabian; Herdl, Sebastian; Volkert, Gudrun; Marek, Ines; Menendez-Castro, Carlos; Nögel, Stephanie; Rübner, Matthias; Hübner, Hanna; Hartner, Andrea; Rascher, Wolfgang (2016)
EVALuna2:33461

Comparative anatomy of nitrergic intrinsic choroidal neurons (ICN) in various avian species - Schrödl, Falk; De Stefano, M. Egle; Reese, Sven; Brehmer, Axel; Neuhuber, Winfried (Experimental Eye Research, 2004)
Intrinsic choroidal neurons (ICN) represent a peculiar feature of eyes in higher primates and birds. They account for up to 2000 in human and duck eyes but are virtually absent or rare in all other mammalian species investigated so far. It has been suggested that ICN are involved in regulation of ocular blood supply, hence influencing intraocular pressure, and changes in choroidal thickness, thus influencing accommodation. The present study was undertaken in order to compare differences in various avian species with respect to ICN as well as to provide data on some avian species relevant for experimental ophthalmic research, i.e. chicken and quail. Choroids from 12 avian species were processed for NADPH-diaphorase histochemistry or, in some cases, neuronal nitric oxide synthase immunocytochemistry. ICN were quantified and normalized to mean choroidal area. Three choroids of each galliformes (i.e. chicken, quail, turkey) and anseriformes (i.e. Muscovy duck, Mallard duck, goose) were rastered in squares of 1 mm and x/y coordinates were transferred into a 3D-diagram with the amount of ICN represented in the z-axis. ICN were detected in all species investigated. They were predominantly small cells with soma diameters of 20-30 μm. In turkey, and to a lesser amount in chicken, a subpopulation of ICN with somal diameters of up to 70 μm was observed. Highest mean cell counts were found in goose (6195.4; turkey 3558.4; chicken 1681.4; Muscovy duck 785.4; Mallard duck 640.8; quail 440.2). Normalized to choroidal area, highest mean cell counts were (per mm): 12.62 in goose, 4.42 in both chicken and turkey, 2.86 in quail, 2.66 in Mallard duck and 1.89 in Muscovy duck. In galliformes, ICN were found to be accumulated temporo-cranial, while in anseriformes they were arranged in a more belt-like fashion, passing from cranio-nasal to temporo-caudal. Our results show that besides Muscovy duck, other avian species appear as suitable models for further functional experiments on ICN. The temporo-cranial accumulation of ICN in galliformes and the belt-like arrangement in anseriformes may reflect special functional requirements in regions of high visual acuity. © 2003 Elsevier Ltd. All rights reserved.
Keywords: Accommodation; Eye; Neuronal nitric oxide synthase; Non-vascular smooth muscle; Vascular innervation; VIP

Comparative anatomy of the human and canine efferent tear duct system impact of mucin MUC5AC on lacrimal drainage - Hirt, Roman; Tektas, Ozan Yüksel; Carrington, Stephen D.; Arnett, Richard; Fitzpatrick, Eamonn; Knipping, Stephan; Paulsen, Friedrich (Current Eye Research, 2012)
Purpose: To investigate the histomorphology of the canine tear drainage system and to show the distribution of mucin MUC5AC within the tissue. Methods: Conjunctiva and tear drainage systems of 19 long-nosed dogs were investigated histologically and ultrastructurally. The tissues were stained with eight different antibodies reactive against less glycosylated and highly-glycosylated MUC5AC. Results were compared with findings in human tissue received from 12 body donors. Results: Except for a distinctly longer nasolacrimal duct and several accessory openings of the duct into the nasal cavity, the morphology of the canine tear drainage system is very similar to that of humans. MUC5AC in less-and highly-glycosylated forms was present in the conjunctival tissue of dogs as well of humans. Within the tear sac and the nasolacrimal duct only less-glycosylated MUC5AC could be found in dogs and in human. Conclusions: These findings demonstrate that the canine tear drainage system is very similar to its human equivalent. In particular the distribution of MUC5AC, supposed to play an important role within the pathogenesis of dry eye syndrome (DES), is the same as in humans. Therefore the canine model seems to be an appropriate model for further DES research. © 2012 Informa Healthcare USA, Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Canine; Dry eye syndrome; MUC5AC; Mucin; Nasolacrimal duct; Tears

Comparative Characterization of Human Meibomian Glands, Free Sebaceous Glands, and Hair-Associated Sebaceous Glands Based on Biomarkers, Analysis of Secretion Composition, and Gland Morphology - Liu, Yuqiuhe; Butovich, Igor A.; Garreis, Fabian; Zahn, Ingrid; Scholz, Michael; Gaffling, Simone; Jabari, Samir; Dietrich, Jana; Paulsen, Friedrich (International Journal of Molecular Sciences, 2024)
Meibomian gland dysfunction (MGD) is one of the main causes of dry eye disease. To better understand the physiological functions of human meibomian glands (MGs), the present study compared MGs with free sebaceous glands (SGs) and hair-associated SGs of humans using morphological, immunohistochemical, and liquid chromatography—mass spectrometry (LCMS)-based lipidomic approaches. Eyelids with MGs, nostrils, lips, and external auditory canals with free SGs, and scalp with hair-associated SGs of body donors were probed with antibodies against cytokeratins (CK) 1, 8, 10, and 14, stem cell markers keratin 15 and N-cadherin, cell–cell contact markers desmoglein 1 (Dsg1), desmocollin 3 (Dsc3), desmoplakin (Dp), plakoglobin (Pg), and E-cadherin, and the tight junction protein claudin 5. In addition, Oil Red O staining (ORO) was performed in cryosections. Secretions of MGs as well as of SGs of nostrils, external auditory canals, and scalps were collected from healthy volunteers, analyzed by LCMS, and the data were processed using various multivariate statistical analysis approaches. Serial sections of MGs, free SGs, and hair-associated SGs were 3D reconstructed and compared. CK1 was expressed differently in hair-associated SGs than in MGs and other free SGs. The expression levels of CK8, CK10, and CK14 in MGs were different from those in hair-associated SGs and other free SGs. KRT15 was expressed differently in hair-associated SGs, whereas N-cadherin was expressed equally in all types of glands. The cell–cell contact markers Dsg1, Dp, Dsc3, Pg, and E-cadherin revealed no differences. ORO staining showed that lipids in MGs were more highly dispersed and had larger lipid droplets than lipids in other free SGs. Hair-associated SGs had a smaller number of lipid droplets. LCMS revealed that the lipid composition of meibum was distinctively different from that of the sebum of the nostrils, external auditory canals, and scalp. The 3D reconstructions of the different glands revealed different morphologies of the SGs compared with MGs which are by far the largest type of glands. In humans, MGs differ in their morphology and secretory composition and show major differences from free and hair-associated SGs. The composition of meibum differs significantly from that of sebum from free SGs and from hair-associated SGs. Therefore, the MG can be considered as a highly specialized type of holocrine gland that exhibits all the histological characteristics of SGs, but is significantly different from them in terms of morphology and lipid composition.
CRIS-Team Scopus Importer:2024-04-05
Keywords: cell–cell contacts; cytokeratins; dry eye disease; meibomian gland dysfunction; meibomian glands; meibum; sebaceous glands; sebum; stem cell markers

Comparative Immunogenicity of COVID-19 Vaccines in a Population-Based Cohort Study with SARS-CoV-2-Infected and Uninfected Participants - Peterhoff, David; Einhauser, Sebastian; Beileke, Stephanie; Niller, Hans Helmut; Günther, Felix; Schachtner, Michael; Asbach, Benedikt; Steininger, Philipp; Tenbusch, Matthias; Peter, Antonia Sophia; Gessner, Andre; Burkhardt, Ralph; et al. (Vaccines, 2022)
To assess vaccine immunogenicity in non-infected and previously infected individuals in a real-world scenario, SARS-CoV-2 antibody responses were determined during follow-up 2 (April 2021) of the population-based Tirschenreuth COVID-19 cohort study comprising 3378 inhabitants of the Tirschenreuth county aged 14 years or older. Seronegative participants vaccinated once with Vaxzevria, Comirnaty, or Spikevax had median neutralizing antibody titers ranging from ID50 = 25 to 75. Individuals with two immunizations with Comirnaty or Spikevax had higher median ID50s (of 253 and 554, respectively). Regression analysis indicated that both increased age and increased time since vaccination independently decreased RBD binding and neutralizing antibody levels. Unvaccinated participants with detectable N-antibodies at baseline (June 2020) revealed a median ID50 of 72 at the April 2021 follow-up. Previously infected participants that received one dose of Vaxzevria or Comirnaty had median ID50 to 929 and 2502, respectively. Individuals with a second dose of Comirnaty given in a three-week interval after the first dose did not have higher median antibody levels than individuals with one dose. Prior infection also primed for high systemic IgA levels in response to one dose of Comirnaty that exceeded IgA levels observed after two doses of Comirnaty in previously uninfected participants. Neutralizing antibody levels targeting the spike protein of Beta and Delta variants were diminished compared to the wild type in vaccinated and infected participants.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Comirnaty; Immunogenicity; Neutralizing anti-bodies; Population-based cohort; SARS-CoV-2; Spikevax; Vaccination; Variants of concern VoC; Vaxzevria

Comparative studies of different types of osteosynthesis on the human corpse preparation in bilateral antero-lateral flail chest - Grupp, Sina; Fürst, Veronika; Buder, Thomas; Fichte, Alexander; Krinner, Sebastian; Carbon, Roman T.; Hennig, Friedrich; Langenbach, Andreas; Schulz-Drost, Stefan (Injury-International Journal of the Care of the Injured, 2017)
Bilateral flail chest injuries are challenging in treatment and comparatively often require an operative stabilization of the anterior chest wall to re-establish normal physiological conditions of the chest wall in shape and statics. Various procedures have been described which are technically sophisticated for the surgeon. Consequently there is an increasing interest in potentials of operative care and their effectiveness on the anterolateral chest wall.12 Human cadavers were prepared and the natural Sternum Position (NP) was marked. A digital probe was fixed to the sternum at the height of the 4th intercostal space in order to measure and compare the stability of the thorax. Readings were taken of the sternal displacement at 1-5cm sagittal distance from NP in starting conditions and from every combination of materials. Serial osteotomies were performed on 2 locations on ribs 2-8 to induce bilateral flail chest. Afterwards the stabilization was achieved with different implants: RESULTS: The osteotomies lead to a subsidence of the sternum occurred to almost 75 mm from NP which corresponds to a maximal unstable situation. The unstable chest wall showed substantially more stabilization through the use of locking plates. Our materialcombinations showed a stability of up to 60% of normal. The more ribs were treated osteosynthetically, the higher the stability of the chest wall.Locking plate fixation offers anatomically realignment of the ribs whereas metal strut support only lifts up the chest wall, but could not provide realignment of the dislocated ribs.
EVALuna2:15857

Comparison of cytokine/chemokine levels in aqueous humor of primary open-angle glaucoma patients with positive or negative outcome following trabeculectomy - Gajda-Deryło, Beata; Stahnke, Thomas; Struckmann, Stephan; Warsow, Gregor; Birke, Kerstin; Birke, Marco T.; Hohberger, Bettina; Rejdak, Robert; Fuellen, Georg; Jünemann, Anselm G. (Bioscience Reports, 2019)
We aimed to identify differences in cytokine/chemokine levels in the aqueous humor (AH) of primary open-angle glaucoma (POAG) patients who suffered from scarring, compared with POAG patients with no scarring after trabeculectomy surgery. Identification of differently expressed cytokines and chemokines may help to understand scarring and fibrotic processes following trabeculectomy, and to make predictions for the outcome of fistulating surgery in the future. Furthermore, the identification of cell signaling pathways involved in fibrosis offers the opportunity for a more specific antifibrotic therapy with reduced side effects, and an improvement in long-term surgical outcome.Eight samples of AH were collected during trabeculectomy surgery and commercially available cytokine/chemokine arrays were used. Specific, differently expressed proteins (cytokines/chemokines) in AH samples from patients with positive and negative surgery outcomes were detected. These proteins were classified based on their known profibrotic, inflammatory, adhesive, and apoptotic properties. Transforming growth factor β (TGF-β) and vascular endothelial growth factor (VEGF) were among the most important profibrotic cytokines that we detected. Differences in the fold change of protein expression were highly significant between patients after successful and failed trabeculectomy surgery, and these were processed and visualized using ExprEssence software.This pilot study revealed differences in concentrations of cytokines/chemokines in AH between the two examined groups of patients. Our findings suggest that a positive outcome from trabeculectomy is strongly related to an inhibition of the fibrosis process.
CRIS-Team Scopus Importer:2019-05-21
Keywords: bioinformatics; ophthalmology; protein expression

Comparison of enteric neuronal morphology as demonstrated by DiI-tracing under different tissue-handling conditions - Brehmer, Axel; Schrödl, Falk; Neuhuber, Winfried; Hens, Jurgen; Timmermans, Jean-Pierre (Anatomy and Embryology, 1999)
The aim of this study was to determine locations and morphologies of enteric neutrons innervating the small intestinal mucosa of the pig after application of the carbocyanine tracer DiI onto a single villus. The tissue was processed in two ways: incubation (1) of fixed material (postmortem tracing) for several months and (2) of living specimens within organotypic culture in vitro for several days (supravital tracing). In both procedures DiI-labelled neurons were found in the three ganglionated plexuses, the internal and external submucous plexus as well as the myenteric plexus. Postmortem tracing revealed different neuronal morphologies. Adendritic type II neurons were present in all three plexuses, type IV neurons with short, scarcely branched, polarly emerging dendrites were mainly found in the myenteric plexus and small dendritic neurons were mainly present in the internal submucous plexus. The latter may correspond to minineurons hitherto described only immunohistochemically, Tracing within tissue culture showed somata of neurons and, partly, proximal segments of processes to be labelled. Subsequent immunohistochemistry using general neuronal markers revealed some neurons to be adendritic type II neurons, Visualization of dendrites was less clear, hampering an accurate morphological classification of dendritic neurons. Our results suggest that neurons of all ganglionated enteric nerve plexuses of the pig participate in the innervation of the mucosa, and that postmortem tracing revealed enteric neuronal morphology more clearly than supravital tracing. Since the former method cannot be applied for deciphering the chemical coding of enteric neurons, combination of both methods will extend our knowledge of the morphological substrate for the intrinsic neuronal microcircuits in the gastrointestinal tract.
Keywords: Enteric nervous system; Innervation; Intestine; Mucosa; Pig

Complex mechanical behavior of human articular cartilage and hydrogels for cartilage repair - Weizel, A.; Distler, Thomas; Schneidereit, Dominik; Friedrich, Oliver; Bräuer, Lars; Paulsen, Friedrich; Detsch, Rainer; Boccaccini, Aldo R.; Budday, Silvia; Seitz, H. (Acta Biomaterialia, 2020)
The mechanical behavior of cartilage tissue plays a crucial role in physiological mechanotransduction processes of chondrocytes and pathological changes like osteoarthritis. Therefore, intensive research activities focus on the identification of implant substitute materials that mechanically mimic the cartilage extracellular matrix. This, however, requires a thorough understanding of the complex mechanical behavior of both native cartilage and potential substitute materials to treat cartilage lesions. Here, we perform complex multi-modal mechanical analyses of human articular cartilage and two surrogate materials, commercially available ChondroFillerliquid, and oxidized alginate-gelatin (ADA-GEL) hydrogels. We show that all materials exhibit nonlinearity and compression-tension asymmetry. However, while hyaline cartilage yields higher stresses in tension than in compression, ChondroFillerliquid and ADA-GEL exhibit the opposite trend. These characteristics can be attributed to the materials’ underlying microstructure: Both cartilage and ChondroFillerliquid contain fibrillar components, but the latter constitutes a bi-phasic structure, where the 60% nonfibrillar hydrogel proportion dominates the mechanical response. Of all materials, ChondroFillerliquid shows the most pronounced viscous effects. The present study provides important insights into the microstructure-property relationship of cartilage substitute materials, with vital implications for mechanically-driven material design in cartilage engineering. In addition, we provide a data set to create mechanical simulation models in the future.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Human articular cartilage; Hydrogels; Mechanical testing; Microstructure; Tissue engineering

Complex reinnervation pattern after unilateral renal denervation in rats - Rodionova, Kristina; Fiedler, Christian; Günther, Franziska; Grouzmann, Eric; Neuhuber, Winfried; Fischer, Michael; Ott, Christian; Linz, Peter; Freisinger, Wolfgang; Heinlein, Sonja; Schmidt, Stefan; Schmieder, Roland; et al. (American Journal of Physiology-Regulatory Integrative and Comparative Physiology, 2016)
Renal denervation (DNX) is a treatment for resistant arterial hypertension. Efferent sympathetic nerves regrow, but reinnervation by renal afferent nerves has only recently been shown in the renal pelvis of rats after unilateral DNX. We examined intrarenal perivascular afferent and sympathetic efferent nerves after unilateral surgical DNX. Tyrosine hydroxylase (TH), CGRP, and smooth muscle actin were identified in kidney sections from 12 Sprague-Dawley rats, to distinguish afferents, efferents, and vasculature. DNX kidneys and nondenervated kidneys were examined 1, 4, and 12 wk after DNX. Tissue levels of CGRP and norepinephrine (NE) were measured with ELISA and mass spectrometry, respectively. DNX decreased TH and CGRP labeling by 90% and 95%, respectively (P < 0.05) within 1 wk. After 12 wk TH and CGRP labeling returned to baseline with a shift toward afferent innervation (P < 0.05). Nondenervated kidneys showed a doubling of both labels within 12 wk (P < 0.05). CGRP content decreased by 72% [3.2 ± 0.3 vs. 0.9 ± 0.2 ng/gkidney; P < 0.05] and NA by 78% [1.1 ± 0.1 vs. 0.2 ± 0.1 pmol/mgkidney; P < 0.05] 1 wk after DNX. After 12 wk, CGRP, but not NE, content in DNX kidneys was fully recovered, with no changes in the nondenervated kidneys. The use of phenol in the DNX procedure did not influence this result. We found morphological reinnervation and transmitter recovery of afferents within 12 wk after DNX. Despite morphological evidence of sympathetic regrowth, NE content did not fully recover. These results suggest a long-term net surplus of afferent influence on the DNX kidney may be contributing to the blood pressure lowering effect of DNX.
EVALuna2:3840

Computational decomposition reveals reshaping of the SARS‐CoV‐2–ACE2 interface among viral variants expressing the N501Y mutation - Socher, Eileen; Conrad, Marcus; Heger, Lukas; Paulsen, Friedrich; Sticht, Heinrich; Zunke, Friederike; Arnold, Philipp (Journal of Cellular Biochemistry, 2021)
Variants of concern of the SARS-CoV-2 virus with an asparagine-to-tyrosine substitution at position 501 (N501Y) in the receptor-binding domain (RBD) show enhanced infectivity compared to wild-type, resulting in an altered pandemic situation in affected areas. These SARS-Cov-2 variants comprise the two Alpha variants (B.1.1.7, United Kingdom and B.1.1.7 with the additional E484K mutation), the Beta variant (B.1.351, South Africa), and the Gamma variant (P.1, Brazil). Understanding the binding modalities between these viral variants and the host cell receptor ACE2 allows to depict changes, but also common motifs of virus–host cell interaction. The trimeric spike protein expressed at the viral surface contains the RBD that forms the molecular interface with ACE2. All the above-mentioned variants carry between one and three amino acid exchanges within the interface-forming region of the RBD, thereby altering the binding interface with ACE2. Using molecular dynamics (MD) simulations and decomposition of intermolecular contacts between the RBD and ACE2, we identified phenylalanine 486, glutamine 498, threonine 500, and tyrosine 505 as important interface-forming residues across viral variants. However, especially the N501Y exchange increased contact formation for this residue and also induced some local conformational changes. Comparing here, the in silico generated B.1.1.7 RBD–ACE2 complex with the now available experimentally solved structure reveals very similar behavior during MD simulation. We demonstrate, how computational methods can help to identify differences in conformation as well as contact formation for newly emerging viral variants. Altogether, we provide extensive data on all N501Y expressing SARS-CoV-2 variants of concern with respect to their interaction with ACE2 and how this induces reshaping of the RBD–ACE2 interface.

Concise report: a minimal-invasive method to retrieve and identify entheseal tissue from psoriatic arthritis patients - Pachowsky, Milena; Raimondo, Maria Gabriella; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Vogg, Mario; Saad, Mina saad aziz; Simon, David; Rech, Jürgen; Soare, Alina; Bräuer, Lars; et al. (Annals of the Rheumatic Diseases, 2022)
Objectives To establish a minimally invasive biopsy technique for the analysis of entheseal tissue in patients with psoriatic arthritis (PsA). Methods Human cadavers were used for establishing the technique to retrieve tissue from the lateral humeral epicondyle enthesis (cadaveric biopsies). After biopsy, the entire enthesis was surgically resected (cadaveric resections). Biopsies and resections were assessed by label-free second harmonic generation (SHG) microscopy. The same technique was then applied in patients with PsA with definition of entheseal tissue by SHG, staining of CD45+immune cells and RNA extraction. Results Entheseal biopsies from five cadavers allowed the retrieval of entheseal tissue as validated by the analysis of resection material. Microscopy of biopsy and resection sections allowed differentiation of entheseal, tendon and muscle tissue by SHG and definition of specific intensity thresholds for entheseal tissue. In subsequent entheseal biopsies of 10 PsA patients: the fraction of entheseal tissue was high (65%) and comparable to cadaveric biopsies (68%) as assessed by SHG microscopy. Furthermore, PsA biopsies showed immune cell infiltration and sufficient retrieval of RNA for further molecular analysis. Conclusion Entheseal biopsy of the lateral epicondyle is feasible in patients with PsA allowing reliable retrieval of entheseal tissue and its identification by SHG microscopy.
CRIS-Team WoS Importer:2022-05-13

Cone beam CT imaging of the paranasal region with a multipurpose X-ray system-image quality and radiation exposure - Ohlmeyer, Sabine; Saake, Marc; Buder, Thomas; May, Matthias; Uder, Michael; Wüst, Wolfgang (Applied Sciences, 2020)
Besides X-ray and fluoroscopy, a previously introduced X-ray scanner offers a 3D cone beam option (Multitom Rax, Siemens Healthcare). The aim of this study was to evaluate various scan parameters and post-processing steps to optimize image quality and radiation exposure for imaging of the parasinus region. Four human cadaver heads were examined with different tube voltages (90-121 kV), dose levels (DLs) (278-2180 nGy) and pre-filtration methods (none, Cu 0.2 mm, Cu 0.3 mm and Sn 0.4 mm). All images were reconstructed in 2 mm slice thickness with and without a metal artifact reduction algorithm in three different kernels. In total, 80 different scan protocols and 480 datasets were evaluated. Image quality was rated on a 5-point Likert scale. Radiation exposure (mean computed tomography volume index (CTDIvol) and effective dose) was calculated for each scan. The most dose-effective combination for the diagnosis of sinusitis was 121 kV/DL of 278/0.3 mm copper (CTDIvol 1.70 mGy, effective dose 77 μSv). Scan protocols with 121 kV/DL1090/0.3 mm copper were rated sufficient for preoperative sinus surgery planning (CTDIvol 4.66 mGy, effective dose 212 μSv). Therefore, sinusitis and preoperative sinus surgery planning can be performed in diagnostic image quality at low radiation dose levels with a multipurpose X-ray system.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Computed tomography; DVT; Medical imaging; Parasinus region; Sinusitis; Three-dimensional; X-ray

Consensus recommendations for trabecular meshwork cell isolation, characterization and culture - Keller, Kate E.; Bhattacharya, Sanjoy K.; Borras, Theresa; Brunner, Thomas M.; Chansangpetch, Sunee; Clark, Abbott F.; Dismuke, W. Michael; Du, Yiqin; Elliott, Michael H.; Ethier, C. Ross; Faralli, Jennifer A.; Freddo, Thomas F.; et al. (Experimental Eye Research, 2018)
Cultured trabecular meshwork (TM) cells are a valuable model system to study the cellular mechanisms involved in the regulation of conventional outflow resistance and thus intraocular pressure; and their dysfunction resulting in ocular hypertension. In this review, we describe the standard procedures used for the isolation of TM cells from several animal species including humans, and the methods used to validate their identity. Having a set of standard practices for TM cells will increase the scientific rigor when used as a model, and enable other researchers to replicate and build upon previous findings.
EVALuna2:35317

Constitutive expression of HCA(2) in human retina and primary human retinal pigment epithelial cells - Yu, Alice L.; Birke, Kerstin; Lorenz, Reinhard L.; Welge-Lüssen, Ulrich-Christoph (Current Eye Research, 2014)
HCA2, a receptor of ?-hydroxybutyrate and niacin, has recently been described in mouse retina and immortalized human retinal pigment epithelial (RPE) cell lines. As HCA2 might be a pharmacologic target, e.g. in diabetic retinopathy, we studied its expression in human retina and primary human RPE cells.Paraffin sections of human retina and primary human RPE cells were obtained from human donor eyes. Expression of HCA2 in human retina was investigated by immunohistochemistry of paraffin sections and by RT-PCR. HCA2 expression in primary human RPE cells was examined by immunocytochemistry and by Western-blot analysis.Positive immunohistochemical staining for HCA2 was found in paraffin sections of human retina, and positive immunocytochemical staining for HCA2 in primary human RPE cells. RT-PCR analysis detected mRNA expression of HCA2 in human retina. The expression of HCA2 protein was found in primary human RPE cells.Based on these results, HCA2 appears to be constitutively expressed in human retina and in primary human RPE cells. Although its functional role is still unknown, HCA2 may be potentially involved in the pathogenesis of various retinopathies and may offer a new therapeutic target.
EVALuna2:21027

Contribution of LTi and T(H)17 cells to B cell aggregate formation in the central nervous system in a mouse model of multiple sclerosis - Schropp, Verena; Rohde, Joern; Rovituso, Damiano M.; Jabari, Samir; Bharti, Richa; Kürten, Stefanie (Journal of Neuroinflammation, 2019)
BackgroundIn a subgroup of patients suffering from progressive multiple sclerosis (MS), which is an inflammation-mediated neurodegenerative disease of the central nervous system (CNS), B cell aggregates were discovered within the meninges. Occurrence of these structures was associated with a more severe disease course and cortical histopathology. We have developed the B cell-dependent MP4-induced experimental autoimmune encephalomyelitis (EAE) as a mouse model to mimic this trait of the human disease. The aim of this study was to determine a potential role of lymphoid tissue inducer (LTi) and T(H)17 cells in the process of B cell aggregate formation in the MP4 model.MethodsWe performed flow cytometry of cerebellar and splenic tissue of MP4-immunized mice in the acute and chronic stage of the disease to analyze the presence of CD3(-)CD5(-)CD4(+)RORt(+) LTi and CD3(+)CD5(+)CD4(+)RORt(+) T(H)17 cells. Myelin oligodendrocyte glycoprotein (MOG):35-55-induced EAE was used as B cell-independent control model. We further determined the gene expression profile of B cell aggregates using laser capture microdissection, followed by RNA sequencing.ResultsWhile we were able to detect LTi cells in the embryonic spleen and adult intestine, which served as positive controls, there was no evidence for the existence of such a population in acute or chronic EAE in neither of the two models. Yet, we detected CD3(-)CD5(-)CD4(-)RORt(+) innate lymphoid cells (ILCs) and T(H)17 cells in the CNS, the latterespecially in the chronic stage of MP4-induced EAE. Moreover, we observed a unique gene signature in CNS B cell aggregates compared to draining lymph nodes of MP4-immunized mice and to cerebellum as well as draining lymph nodes of mice with MOG:35-55-induced EAE.ConclusionThe absence of LTi cells in the cerebellum suggests that other cells might take over the function as an initiator of lymphoid tissue formation in the CNS. Overall, the development of ectopic lymphoid organs is a complex process based on an interplay between several molecules and signals. Here, we propose some potential candidates, which might be involved in the formation of B cell aggregates in the CNS of MP4-immunized mice.
CRIS-Team WoS Importer:2019-06-18

Corneal tissue interactions of a new 345 nm ultraviolet femtosecond laser - Hammer, Christian M.; Petsch, Corinna; Klenke, Joerg; Skerl, Katrin; Paulsen, Friedrich; Kruse, Friedrich; Seiler, Theo; Menzel-Severing, Johannes (Journal of Cataract and Refractive Surgery, 2015)
To assess the suitability of a new 345 nm ultraviolet (UV) femtosecond laser for refractive surgery.Department of Ophthalmology, University of Erlangen-Nürnberg, Erlangen, Germany.Experimental study.Twenty-five porcine corneas were used for stromal flap or lamellar bed creation (stromal depth, 150 ?m) and 15 rabbit corneas for lamellar bed creation near the endothelium. Ultraviolet femtosecond laser cutting-line morphology, gas formation, and keratocyte death rate were evaluated using light and electron microscopy and compared with a standard infrared (IR) femtosecond laser. Endothelial cell survival was examined after application of a laser cut near the endothelium.Flaps created by the UV laser were lifted easily. Gas formation was reduced 4.2-fold compared with the IR laser (P = .001). The keratocyte death rate near the interface was almost doubled; however, the death zone was confined to a region within 38 ?m ± 10 (SD) along the cutting line. Histologically and ultrastructurally, a distinct and continuous cutting line was not found after UV femtosecond laser application if flap lifting was omitted and standard energy parameters were used. Instead, a regular pattern of vertical striations, presumably representing self-focusing induced regions of optical tissue breakdown, were identified. Lamellar bed creation with standard energy parameters 50 ?m from the endothelium rendered the endothelial cells intact and viable.The new 345 nm femtosecond laser is a candidate for pending in vivo trials and future high-precision flap creation, intrastromal lenticule extraction, and ultrathin Descemet-stripping endothelial keratoplasty.Mr. Klenke and Ms. Skerl were paid employees of Wavelight GmbH when the study was performed. Dr. Seiler is a scientific consultant to Wavelight GmbH. No other author has a financial or proprietary interest in any material or method mentioned.
EVALuna2:21240

Correction to: The specific DNA methylation landscape in focal cortical dysplasia ILAE type 3D (Acta Neuropathologica Communications, (2023), 11, 1, (129), 10.1186/s40478-023-01618-6) - Wang, Dan Dan; Katoch, Mitali; Jabari, Samir; Blumcke, Ingmar; Blumenthal, David B.; Lu, De Hong; Coras, Roland; Wang, Yu Jiao; Shi, Jie; Zhou, Wen Jing; Kobow, Katja; Piao, Yue Shan (Acta Neuropathologica Communications, 2024)
Following publication of the original article [1], the authors identified errors in the reference list and citations. Due to a technical error a wrong article version for the references and citations was used. The original article [1] has been corrected.
CRIS-Team Scopus Importer:2024-04-05

Correlated morphological and chemical phenotyping in myenteric type V neurons of porcine ileum - Brehmer, Axel; Schrödl, Falk; Neuhuber, Winfried (Journal of Comparative Neurology, 2002)
The study was aimed at the immunohistochemical characterization of myenteric Stach type V neurons of the pig ileum that were not included in the widely used Dogiel classification. So far, this conspicuous population has been defined morphologically on the basis of silver-impregnated specimens only. By using neurofilament immunohistochemistry, type V neurons that occur singly or in aggregates could be identified unequivocally and could be distinguished from other smoothly contoured myenteric neurons, i.e., type II and type IV. Double-labeling immunohistochemistry revealed a number of potentially neuroactive substances or their synthesizing enzymes to be present in type V neurons. Choline acetyltransferase immunoreactivity (-ir) was found in all type V neurons, whereas neuronal nitric oxide synthase was detected in none. Leu-enkephalin-ir was found within 92.3%, somatostatin (SOM)-ir within 91.1%, calcitonin gene-related peptide (CGRP)-ir within 80.6% and metenkephalin-ir within 74.7% of type V neurons. Triple-labeling immunohistochemistry was applied to address the question of a specific chemical coding for myenteric type V neurons. In contrast to other combinations of neuroactive substances/enzymes that were found in both type V and other, nontype V neurons, SOM/CGRP-ir was the only combination observed exclusively within type V neurons. Both substances were colocalized in 79.3% of type V neurons. This colocalization discriminates four-fifths of the type V neurons chemically from both type II neurons (CGRP positive, SOM negative) and type IV neurons (CGRP negative, SOM positive), which both share, at first glance, a similar morphology with type V neurons. These results further support the concept of a close correlation between morphologically defined neuronal type and chemical coding and, it is likely, also function in the enteric nervous system of larger mammals. © 2002 Wiley-Liss, Inc.
Keywords: Cytoskeleton; Gut; Innervation; Neuropeptides; Plexus

Corrigendum to “Functional anatomy of the vagus system: How does the polyvagal theory comply?” [Biological Psychology 174 (2022) 108425] (Biological Psychology (2022) 174, (S0301051122001685), (10.1016/j.biopsycho.2022.108425)) - Neuhuber, Winfried; Berthoud, Hans Rudolf (Biological Psychology, 2023)
In the published version on page 5, subchapter 5.1 Heart and large arteries, right column, the paper by Booth et al. (2021) was erroneously quoted as describing DMX cardiac neurons conducting at about B-fiber speed. However, these authors only described DMX neurons in general and not specifically cardiac neurons. Thus, the term “cardiac” should be deleted in lines 7 and 9. Also, in line 7, conduction speed should be 6 m/s.
CRIS-Team Scopus Importer:2023-04-28

Corrigendum to "Recombinant expression of surfactant protein H (SFTA3) in Escherichia coli" [Ann. Anat. 208C (2016) 129-134] - Schröder, Henrik; Sollfrank, L.; Paulsen, Friedrich; Bräuer, Lars; Schicht, Martin (Annals of Anatomy-Anatomischer Anzeiger, 2017)
EVALuna2:34488

Cor Triatriatum Sinistrum Combined with Changes in Atrial Septum and Right Atrium in a 60-Year-Old Woman - Claassen, Horst; Busch, Christian; May, Matthias; Schicht, Martin; Scholz, Michael; Schulze, Marko; Paulsen, Friedrich; Wree, Andreas (Medicina, 2021)
Background and Objectives: A rare case of cor triatriatum sinistrum in combination with anomalies in the atrial septum and in the right atrium of a 60-year-old female body donor is described here. Materials and Methods: In addition to classical dissection, ultrasound and magnetic resonance imaging, computer tomography and cinematic rendering were performed. In a reference series of 59 regularly formed hearts (33 men, 26 women), we looked for features in the left and right atrium or atrial septum. In addition, we measured the atrial and ventricular wall thickness in 15 regularly formed hearts (7 men, 8 women). Results: In the case described, the left atrium was partly divided into two chambers by an intra-atrial membrane penetrated by two small openings. The 2.5 cm-high membrane originated in the upper level of the oval fossa and left an opening of about 4 cm in diameter. Apparently, the membrane did not lead to a functionally significant flow obstruction due to the broad intra-atrial communication between the proximal and distal chamber of the left atrium. In concordance with this fact, left atrial wall thickness was not elevated in the cor triatriatum sinistrum when compared with 15 regularly formed hearts. In addition, two further anomalies were found: 1. the oval fossa was deepened and arched in the direction of the left atrium; 2. the right atrium showed a membrane-like structure at its posterior and lateral walls, which began at the lower edge of the oval fossa. It probably corresponds to a strongly developed eustachian valve (valve of the inferior vena cava). Conclusions: The case described suggests that malformations in the development of the atrial septum and in the regression of the valve of the right sinus vein are involved in the pathogenesis of cor triatriatum sinistrum.
CRIS-Team WoS Importer:2021-09-10

Cruciate Ligament Cell Sheets Can Be Rapidly Produced on Thermoresponsive poly(glycidyl ether) Coating and Successfully Used for Colonization of Embroidered Scaffolds - Zahn, Ingrid; Stoebener, Daniel David; Weinhart, Marie; Goegele, Clemens; Breier, Annette; Hahn, Judith; Schroepfer, Michaela; Meyer, Michael; Schulze-Tanzil, Gundula (Cells, 2021)
Anterior cruciate ligament (ACL) cell sheets combined with biomechanically competent scaffolds might facilitate ACL tissue engineering. Since thermoresponsive polymers allow a rapid enzyme-free detachment of cell sheets, we evaluated the applicability of a thermoresponsive poly(glycidyl ether) (PGE) coating for cruciate ligamentocyte sheet formation and its influence on ligamentocyte phenotype during sheet-mediated colonization of embroidered scaffolds. Ligamentocytes were seeded on surfaces either coated with PGE or without coating. Detached ligamentocyte sheets were cultured separately or wrapped around an embroidered scaffold made of polylactide acid (PLA) and poly(lactic-co-epsilon-caprolactone) (P(LA-CL)) threads functionalized by gas-phase fluorination and with collagen foam. Ligamentocyte viability, protein and gene expression were determined in sheets detached from surfaces with or without PGE coating, scaffolds seeded with sheets from PGE-coated plates and the respective monolayers. Stable and vital ligamentocyte sheets could be produced within 24 h with both surfaces, but more rapidly with PGE coating. PGE did not affect ligamentocyte phenotype. Scaffolds could be colonized with sheets associated with high cell survival, stable gene expression of ligament-related type I collagen, decorin, tenascin C and Mohawk after 14 d and extracellular matrix (ECM) deposition. PGE coating facilitates ligamentocyte sheet formation, and sheets colonizing the scaffolds displayed a ligament-related phenotype.
CRIS-Team WoS Importer:2021-05-14

Curvature-dependent shear bond strength of different attachment materials for orthodontic lingual indirect bonding - Jungbauer, Rebecca; Al-Burghol, Paul; Rosentritt, Martin; Kirschneck, Christian; Proff, Peter; Paulsen, Friedrich; Hammer, Christian (Scientific Reports, 2021)
To evaluate the shear bond strength (SBS) of different attachment materials used for lingual bonding, the influence of artificial aging and the radii of curvature of the enamel surface on SBS, 192 third molars were photographed to determine the radius of curvature of the oral surface. After phosphoric acid etching a cylindrical test piece was bonded to the oral enamel using a mold that was filled with a chemically curing (Maximum Cure, Transbond IDB Premix) or a dual-curing (Nexus NX3, RelyX Unicem2) attachment material. SBS was tested after 24 h, 500 thermal cycles or 90 days at 37 °C with a universal testing machine. Computed tomography scans were performed to determine the bonded surface and calculate SBS. Values ranged from 8.3 to 20.9 MPa. RelyX Unicem2 showed the highest SBS values at baseline, 500 thermal cycles and after 90 days (p < 0.001). Ninety days of wet storage significantly reduced SBS of Maximum Cure (p = 0.028). The radius of curvature correlated positively with SBS (rs = 0.204, p = 0.005). The SBS of all attachment materials was sufficient for clinical use, even after artificial aging. RelyX Unicem2 showed almost twice as high SBS values as the other attachment materials.
CRIS-Team Scopus Importer:2021-08-27

CXCR4 and CXCR7 Mediate TFF3-Induced Cell Migration Independently From the ERK1/2 Signaling Pathway - Dieckow, Julia; Brandt, Wolfgang; Hattermann, Kirsten; Schob, Stefan; Schulze, Ute; Mentlein, Rolf; Ackermann, Philipp; Sel, Saadettin; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2016)
PURPOSE: Trefoil factor family (TFF) peptides, and in particular TFF3, are characteristic secretory products of mucous epithelia that promote antiapoptosis, epithelial migration, restitution, and wound healing. For a long time, a receptor for TFF3 had not yet been identified. However, the chemokine receptor CXCR4 has been described as a low affinity receptor for TFF2. Additionally, CXCR7, which is able to heterodimerize with CXCR4, has also been discussed as a potential TFF2 receptor. Since there are distinct structural similarities between the three known TFF peptides, this study evaluated whether CXCR4 and CXCR7 may also act as putative TFF3 receptors. METHODS: We evaluated the expression of both CXCR4 and CXCR7 in samples of human ocular surface tissues and cell lines, using RT-PCR, immunohistochemistry, and Western blot analysis. Furthermore, we studied possible binding interactions between TFF3 and the receptor proteins in an x-ray structure-based modeling system. Functional studies of TFF3-CXCR4/CXCR7 interaction were accomplished by cell culture-based migration assays, flow cytometry, and evaluation of activation of the mitogen-activated protein (MAP) kinase signaling cascade. RESULTS: We detected both receptors at mRNA and protein level in all analyzed ocular surface tissues, and in lesser amount in ocular surface cell lines. X-ray structure-based modeling revealed CXCR4 and CXCR7 dimers as possible binding partners to TFF3. Cell culture-based assays revealed enhanced cell migration under TFF3 stimulation in a conjunctival epithelial cell line, which was completely suppressed by blocking CXCR4 and/or CXCR7. Flow cytometry showed increased proliferation rates after TFF3 treatment, while blocking both receptors had no effect on this increase. Trefoil factor family 3 also activated the MAP kinase signaling cascade independently from receptor activity. CONCLUSIONS: Dimers CXCR4 and CXCR7 are involved in TFF3-dependent activation of cell migration, but not cell proliferation. The ERK1/2 pathway is activated in the process, but not influenced by CXCR4 or CXCR7. These results implicate a dependence of TFF3 activity as to cell migration on the chemokine receptors CXCR4 and CXCR7 at the ocular surface.
EVALuna2:35355

Cytokine-dependent ELAM-1 induction and concomitant intraocular pressure regulation in porcine anterior eye perfusion culture - Birke, Marco; Birke, Kerstin; Lütjen-Drecoll, Elke; Schlötzer-Schrehardt, Ursula; Hammer, Christian (Investigative Ophthalmology & Visual Science, 2011)
To demonstrate the capacity of interleukin (IL)-1 to simultaneously lower intraocular pressure (IOP) and induce trabecular ELAM-1 expression in one experiment and to test for IL-6 accordingly and evaluate the role of transforming growth factor (TGF)-?2 as an IL-1 antagonist.Forty-two porcine eyes were subjected to trabecular meshwork (TM) perfusion with IL-1?, -1?, or -6 for 48 hours. Twelve of the IL-1?-treated eyes also received TGF-?2 for the final 24-hour period. Polymerase chain reaction and Western blot analyses of ELAM-1 expression were then performed on harvested TM samples. mRNA regulation of IL-1?, IL-1?, IL-6, TGF-?2, and P-selectin (SELP) was determined.IL-1? and -1? treatment augmented outflow facility approximately threefold while inducing ELAM-1. IL-6 perfusion neither changed IOP nor induced ELAM-1. IL-1?/TGF-?2 double treatment significantly counteracted the IL-1-induced IOP decrease and markedly reduced the degree of ELAM-1 mRNA upregulation from 22.3- to 3.1-fold, and ELAM-1 protein from 1.9- to 1.2-fold. IL-1? mRNA was upregulated 5.3-, 3.3-, and 5.5-fold after perfusion with IL-1?, -1?, and -1?/TGF-?2, respectively. The respective values for IL-6 mRNA were 2.0-, 2.1- and 2.4-fold. Expression of IL-1? and TGF-?2 mRNA remained unchanged. IL-6 perfusion had no discernible regulatory effect.Simultaneous demonstration of IL-1's lowering of IOP and inducing trabecular ELAM-1 was achieved for the first time in one experiment, and its possible implications in the pathogenesis of glaucoma was further emphasized. The involvement of an autocrine feedback loop was confirmed in the porcine system. TGF-?2 constitutes a potent IL-1 antagonist for IOP and ELAM-1 regulation.
EVALuna2:21022

Dacryocystography: From theory to current practice - Singh, Swati; Mohammad, Javed Ali; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2019)
Purpose: To provide a review and an update on dacryocystography (DCG) and its relevance in the current era. Methods: The authors performed a PubMed search of all articles published in English on DCG, digital subtraction-DCG (DS-DCG), computed tomographic DCG (CT-DCG) and magnetic resonance-DCG (MR-DCG). Data analyzed include the indications, techniques, interpretations, complication and limitations. Results: Dacryocystography has been used for illustrating the morphological and functional aspects of the lacrimal drainage system (LDS). Subtraction DCG provides the precise location of the alterations and acceptably delineates stenosis or an obstruction. Transit time for contrast into the nose varies widely across the studies. Low osmolality iodinated contrast media are tolerated well for DS-DCG and CT-DCG. However, normal saline either mixed with lidocaine or alone provided similar image quality as obtained with gadolinium for MR-DCG. CT-DCG provides useful information in complex orbitofacial trauma and lacrimal tumors. MR-DCG allows better 3D visualization of the LDS and dynamic functional evaluation. Sensitivity of CT-DCG and MR-DCG are mostly similar in identifying an LDS obstruction. Conclusion: Various forms of DCGs can provide additional information to evaluate patients with maxillo-facial trauma, functional epiphora, suspected lacrimal sac diverticula, partial nasolacrimal duct obstruction, and lacrimal drainage tumors. Canaliculi and the membranous part of the nasolacrimal duct are not yet visualized in detail and further focused studies with advanced techniques are required.
CRIS-Team Scopus Importer:2019-05-02
Keywords: CT-DCG; Dacryocystography; Epiphora; Lacrimal; MR dacryocystography; MR-DCG; Subtraction dacryocystography

Dacryolithogenesis or Dacryolithiasis-The Story So Far. - Ali, Mohammad Javed; Heichel, Jens; Paulsen, Friedrich (Ophthalmic Plastic and Reconstructive Surgery, 2024)
The term dacryoliths refers to the concretions found within the lacrimal system. When the term dacryoliths is unspecified, it usually refers to the noninfectious dacryoliths commonly isolated from the lacrimal sac and the nasolacrimal duct. More often, they are diagnosed incidentally during a dacryocystorhinostomy, and the reported incidence among all dacryocystorhinostomy surgeries is 5.7% to as high as 18%. Dacryolithiasis is a complex process occurring within the lacrimal system, and current evidence suggests a multifactorial etiology. The sequence of events can be summarized broadly into 4 stages: stage of susceptibility, stage of initiation/trigger, stage of development, and stage of maintenance. The triggering event is the breach of the lacrimal sac or nasolacrimal duct epithelium, resulting in microtrauma with blood leakage. The blood clots act as a nidus for subsequent sequential laying of mucopeptides, cellular debris present locally, debris washed from the ocular surface, and extraneous agents in tears. This process is aided by altered rheology and composition of the tear film. After the formation of dacryoliths, extracellular neutrophil traps usually form on the surface, which help to maintain the dacryoliths (which do not dissolve). This review highlights and discusses the possible sequence of events during dacryolithiasis.
EVALuna2:545148

Danger: High Voltage-The Role of Voltage-Gated Calcium Channels in Central Nervous System Pathology - Schampel, Andrea; Kürten, Stefanie (Cells, 2017)
Voltage-gated calcium channels (VGCCs) are widely distributed within the central nervous system (CNS) and presumed to play an important role in the pathophysiology of a broad spectrum of CNS disorders including Alzheimer's and Parkinson's disease as well as multiple sclerosis. Several calcium channel blockers have been in clinical practice for many years so that their toxicity and side effects are well studied. However, these drugs are primarily used for the treatment of cardiovascular diseases and most if not all effects on brain functions are secondary to peripheral effects on blood pressure and circulation. While the use of calcium channel antagonists for the treatment of CNS diseases therefore still heavily depends on the development of novel strategies to specifically target different channels and channel subunits, this review is meant to provide an impulse to further emphasize the importance of future research towards this goal.
EVALuna2:35214

DAPK loss in colon cancer tumor buds: implications for migration capacity of disseminating tumor cells - Ivanovska, Jelena; Zlobec, Inti; Forster, Stefan; Karamitopoulou, Eva; Dawson, Heather; Koelzer, Viktor Hendrik; Agaimy, Abbas; Garreis, Fabian; Söder, Stephan; Laqua, William; Lugli, Alessandro; Hartmann, Arndt; et al. (Oncotarget, 2015)
Defining new therapeutic strategies to overcome therapy resistance due to tumor heterogeneity in colon cancer is challenging. One option is to explore the molecular profile of aggressive disseminating tumor cells. The cytoskeleton-associated Death-associated protein kinase (DAPK) is involved in the cross talk between tumor and immune cells at the invasion front of colorectal cancer. Here dedifferentiated tumor cells histologically defined as tumor budding are associated with a high risk of metastasis and poor prognosis. Analyzing samples from 144 colorectal cancer patients we investigated immunhistochemical DAPK expression in different tumor regions such as center, invasion front, and buds. Functional consequences for tumor aggressiveness were studied in a panel of colon tumor cell lines using different migration, wound healing, and invasion assays. DAPK levels were experimentally modified by siRNA transfection and overexpression as well as inhibitor treatments. We found that DAPK expression was reduced towards the invasion front and was nearly absent in tumor buds. Applying the ECIS system with HCT116 and HCT116 stable lentiviral DAPK knock down cells (HCTshDAPK) we identified an important role for DAPK in decreasing the migratory capacity whereas proliferation was not affected. Furthermore, the migration pattern differed with HCTshDAPK cells showing a cluster-like migration of tumor cell groups. DAPK inhibitor treatment revealed that the migration rate was independent of DAPK's catalytic activity. Modulation of DAPK expression level in SW480 and DLD1 colorectal cancer cells significantly influenced wound closure rate. DAPK seems to be a major player that influences the migratory capability of disseminating tumor cells and possibly affects the dynamic interface between pro- and anti-survival factors at the invasion front of colorectal cancer. This interesting and new finding requires further evaluation.
EVALuna2:4438

Deep femoral artery: A new point of view based on cadaveric study - Claassen, Horst; Schmitt, O.; Schulze, M.; Wree, A. (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Introduction: In diagnostic angiographic procedures, the knowledge of arterial variations in the femoral artery (FA), deep femoral artery (DFA) and lateral and medial circumflex femoral arteries (LCFA, MCFA) has a great impact. Material and methods: The frequency of branching patterns of these arteries was investigated in 111 thighs of body donors. Gender and side differences were analyzed statistically. Results: The median distance of separation of the DFA from the FA in relation to the inguinal ligament (IL) was 3.29 cm. High origins (1−2 cm below IL) and middle origins (3−5 cm below IL) of the DFA were found in an equal distribution of 39.3% and 41.1%, respectively. Low origins (6−10 cm below IL) were rare (19.6%) but showed a tendential significance toward expression in males (p = 0.096). The origin of the LCFA from the FA (19.8%) or DFA (70.2%) are in line with the findings of other groups. The origin of the MCFA from FA (14.4%) or DFA (74.7%) showed that circumflex femoral arteries arose mostly from DFA. A trifurcation of the FA into the DFA, LCFA and MCFA was only observed in 9.9% and, therefore, less frequently than reported by others. Branches of the femoral nerve (FN) passed mostly anterior (46.4%) or anterior and posterior (47.8%) to the LCFA. The rare constellation of branches of FN passing only posterior to the LCFA (5.8%) showed a tendential significance to left side expression (p = 0.084). Conclusions: Taken together, this is the first classification of the median distance of separation of the DFA from the FA in relation to the IL in three defined groups. The knowledge of DFA branching pattern is essential for recent therapy options of cardiac diseases using a femoral artery access: transcatheter aortic valve replacement, catheter-based miniaturized ventricular assist device and veno-arterial extracorporal membrane oxygenation. The variant topography of the branches of FN in relation to LCFA should be kept in mind when harvesting an anterolateral thigh flap.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Arterial variation; Branching pattern; Femoral arteries; Femoral nerve; Thigh

Deficiency in X-linked inhibitor of apoptosis protein promotes susceptibility to microbial triggers of intestinal inflammation - Strigli, Anne; Gopalakrishnan, Shreya; Zeissig, Yvonne; Basic, Marijana; Wang, Jun; Schwerd, Tobias; Doms, Shauni; Peuker, Kenneth; Hartwig, Jelka; Harder, Juergen; Hoenscheid, Pia; Arnold, Philipp; et al. (Science immunology, 2021)
Inflammatory bowel disease (IBD) is characterized by inappropriate immune responses to the microbiota in genetically susceptible hosts, but little is known about the pathways that link individual genetic alterations to microbiotadependent inflammation. Here, we demonstrated that the loss of X-linked inhibitor of apoptosis protein (XIAP), a gene associated with Mendelian IBD, rendered Paneth cells sensitive to microbiota-, tumor necrosis factor (TNF)-, receptor-interacting protein kinase 1 (RIPK1)-, and RIPK3-dependent cell death. This was associated with deficiency in Paneth cell-derived antimicrobial peptides and alterations in the stratification and composition of the microbiota. Loss of XIAP was not sufficient to elicit intestinal inflammation but provided susceptibility to pathobionts able to promote granulomatous ileitis, which could be prevented by administration of a Paneth cell-derived antimicrobial peptide. These data reveal a pathway critical for host-microbial cross-talk, which is required for intestinal homeostasis and the prevention of inflammation and which is amenable to therapeutic targeting.
CRIS-Team WoS Importer:2021-12-03

Delayed Activation Kinetics of Th2- and Th17 Cells Compared to Th1 Cells - Duechting, Andrea; Przybyla, Anna; Kürten, Stefanie; Lehmann, Paul V. (Cells, 2017)
During immune responses, different classes of T cells arise: Th1, Th2, and Th17. Mobilizing the right class plays a critical role in successful host defense and therefore defining the ratios of Th1/Th2/Th17 cells within the antigen-specific T cell repertoire is critical for immune monitoring purposes. Antigen-specific Th1, Th2, and Th17 cells can be detected by challenging peripheral blood mononuclear cells (PBMC) with antigen, and establishing the numbers of T cells producing the respective lead cytokine, IFN-γ and IL-2 for Th1 cells, IL-4 and IL-5 for Th2, and IL-17 for Th-17 cells, respectively. Traditionally, these cytokines are measured within 6 h in flow cytometry. We show here that 6 h of stimulation is sufficient to detect peptide-induced production of IFN-γ, but 24 h are required to reveal the full frequency of protein antigen-specific Th1 cells. Also the detection of IL-2 producing Th1 cells requires 24 h stimulation cultures. Measurements of IL-4 producing Th2 cells requires 48-h cultures and 96 h are required for frequency measurements of IL-5 and IL-17 secreting T cells. Therefore, accounting for the differential secretion kinetics of these cytokines is critical for the accurate determination of the frequencies and ratios of antigen-specific Th1, Th2, and Th17 cells.
EVALuna2:35215

DEMODEX FOLLICULORUM IN PATIENTS WITH MILD TO SEVERE DRY EYE - Jacobi, Christina; Kurz, Julia; Paulsen, Friedrich; Juenemann, Anselm G. M. (2018)
EVALuna2:35308

Dendritic hypertrophy of Stach type VI neurons within experimentally altered ileum of pigs - Brehmer, Axel; Frieser, Markus; Graf, Michael; Radespiel-Tröger, Martin; Göbel, Dieter; Neuhuber, Winfried (Autonomic Neuroscience-Basic & Clinical, 2001)
Myenteric neurons were investigated morphometrically to answer the question if type-specific somal hypertrophy of type VI neurons in mechanically stressed ileum of pigs, which was known from an earlier study, is correlated with an increased dendritic arborization, that is, with dendritic hypertrophy. Muscular hypertrophy was induced in the ileum of two juvenile pigs by narrowing the gut circumference (mechanical stenosis) and by reversing a loop of ileum which results in an antiperistaltic segment (functional stenosis), respectively. After a survival time of 6 weeks, wholemounts from the pre- and poststenotic ileal regions, from the antiperistaltic segment as well as from an age matched control animal, were silver impregnated. Dendritic parameters of Stach types IV and VI neurons were recorded using a computer-aided morphometric program and analysed statistically. Type IV neurons showed no change of dendritic parameters, neither within control nor within stenosed ileal segments. In contrast, the type VI neurons displayed increased dendritic parameters within zones of muscular hypertrophy such as total dendritic length, numbers of dendrites, of dendritic branching points and of dendritic endings. We suggest that type VI neurons may participate as descending nitrergic interneurons or motorneurons in the control of muscular function, thus, undergoing plastic changes in case of experimental muscular hypertrophy. Type IV neurons which are involved in the regulation of mucosal processes were not affected by muscular hypertrophy. © 2001 Elsevier Science B.V.
Keywords: Enteric nervous system; Gut; Innervation; Morphology; Plasticity; Stenosis

Descending-sigmoid colon flexure – An important but surprisingly ignored landmark - Wozniak, Slawomir; Pawlus, Aleksander; Grzelak, Joanna; Chobotow, Slawomir; Paulsen, Friedrich; Olchowy, Cyprian; Zaleska-Dorobisz, Urszula (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Background: In invasive examinations of the colon, e.g. colonoscopy, the tortuosity of the colon is a crucial factor for successful completion of the procedure. If adjacent segments of the colon bend at acute angles (under 90°), endoscopy may become difficult and troublesome. Methods: We retrospectively enroled 227 individuals (96 female, 131 male) who underwent abdominopelvic computed tomography examination. For inclusion, subjects were required to have a negative history for colonic disease and abdominopelvic surgery. We measured the angle between the descending colon and the proximal part of the sigmoid (in degrees). In addition, the position of the descending-sigmoid flexure was assessed in relation to the left anterior superior iliac spine, the median plane, and anterior aspect of the 5th lumbar vertebra (in mm). The study protocol was reviewed and approved by the local ethics committee. Results: We visualised the descending-sigmoid flexure in all 227 subjects. In one third of cases, the flexure formed an angle smaller than/or 90°. In females, this landmark (mean ± standard deviation) was located 30.2 ± 8.4 mm from the left anterior superior iliac spine, 88.6 ± 14.2 mm from the median plane, and 115.4 ± 21.4 mm from the anterior aspect of the 5th lumbar vertebra. In males, the dimensions were: 32.1 ± 12.8 mm, 97.6 ± 15.8 mm, and 123.9 ± 22.9 mm, respectively. This landmark distance remained constant from the left anterior superior iliac spine regardless of subject age, height and weight. The other measured distances were related to age, height, weight or BMI. Conclusions: The descending-sigmoid flexure is an important landmark in large intestine morphology situated approximately width of two fingers (3 cm) from the left anterior superior iliac spine and one hand width (9–10 cm) from the median plane. In approximately one third of the subjects, the flexure formed an angle of less than/or 90°, which can cause a problem during colonoscopy.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Colosigmoid junction; Descending-sigmoid flexure; Large intestine; Large intestine flexures

Detection of intrinsic cholinergic system in the human lacrimal drainage system: evidence and potential implications - Mohammad, Javed Ali; Glöckner, Mareile; Schicht, Martin; Bräuer, Lars; Paulsen, Friedrich (Graefes Archive For Clinical and Experimental Ophthalmology, 2018)
PURPOSE: To investigate the presence and distribution of epithelial and non-epithelial cholinergic system and cholinergic brush cells in the human lacrimal drainage system. METHODS: The study was performed on fresh frozen human cadaveric samples of the lacrimal drainage system. Immunohistochemistry was performed for assessing the presence and distribution of cholinergic brush cell proteins-villin, acetylcholine synthesizing enzyme, choline acetyltransferase (ChAT); vesicular acetylcholine transporter (VAChT); components of canonical taste transduction signaling cascade, phospholipase C β2 (PLCβ2), and transient receptor potential cation channel, subfamily M, and member 5 (TRPM5). In addition, immunoreactivity to carbonic anhydrase 4 (CA4) was assessed. The immunoreactivity was scored as positive or negative and the distribution patterns in the canaliculi, lacrimal sac, and nasolacrimal duct were investigated. In addition, ultrastructural analysis was performed to ascertain the presence of brush cells by means of scanning electron microscopy (SEM). RESULTS: Villin revealed immunoreactivity in the superficial epithelial cells of lacrimal sac and nasolacrimal ducts. Positive immunoreactivity was also found for ChAT, VAChT, TRPM5, and PLCβ2. ChAT expression was limited to the superficial epithelial layers of the lacrimal sac epithelium. TRPM5 and PLCβ2 were expressed on the cell membranes, cytoplasm, and basolateral surfaces of the lacrimal sac epithelium and also showed strong expression in the submucosal glandular acinar cells. VAChT showed strong expression in the canaliculus and lacrimal sac and was expressed on the surface of the superficial epithelial cells and the submucosal glandular acinar cells and lining of the blood vessels. There was a uniformly negative immunoreactivity for CA4. SEM revealed single epithelial cells with dense tuft of rigid apical microvilli in the lacrimal sac and nasolacrimal ducts. CONCLUSIONS: This study provides a proof of principle for the presence of an intrinsic epithelial cholinergic mechanism in the lacrimal drainage system.
EVALuna2:35303

Detection of neuron-derived pathological alpha-synuclein in blood - Kluge, Annika; Bunk, Josina; Schaeffer, Eva; Drobny, Alice; Xiang, Wei; Knacke, Henrike; Bub, Simon; Lueckstaedt, Wiebke; Arnold, Philipp; Lucius, Ralph; Berg, Daniela; Zunke, Friederike (Brain, 2022)
To date, no reliable clinically applicable biomarker has been established for Parkinson's disease. Our results indicate that a long anticipated blood test for Parkinson's disease may be realized. Following the isolation of neuron-derived extracellular vesicles of Parkinson's disease patients and non-Parkinson's disease individuals, immunoblot analyses were performed to detect extracellular vesicle-derived alpha-synuclein. Pathological alpha-synuclein forms derived from neuronal extracellular vesicles could be detected under native conditions and were significantly increased in all individuals with Parkinson's disease and clearly distinguished disease from the non-disease state. By performing an alpha-synuclein seeding assay these soluble conformers could be amplified and seeding of pathological protein folding was demonstrated. Amplified alpha-synuclein conformers exhibited beta-sheet-rich structures and a fibrillary appearance. Our study demonstrates that the detection of pathological alpha-synuclein conformers from neuron-derived extracellular vesicles from blood plasma samples has the potential to evolve into a blood-biomarker of Parkinson's disease that is still lacking so far. Moreover, the distribution of seeding-competent alpha-synuclein within blood exosomes sheds a new light of pathological disease mechanisms in neurodegenerative disorders.
CRIS-Team WoS Importer:2022-07-01
Keywords: α-synuclein; Parkinson’s disease; biomarker; neuron-derived extracellular vesicles; seeding assay

Detection of surfactant proteins A, B, C, and D in human nasal mucosa and their regulation in chronic rhinosinusitis with polyps - Schicht, Martin; Knipping, Stephan; Hirt, Roman; Beileke, Stephanie; Sel, Saadettin; Paulsen, Friedrich; Bräuer, Lars (American Journal of Rhinology & Allergy, 2013)
Backround: The nasal mucosa is characterized by a multirow high prismatic ciliated epithelium representing the first barrier of the immune defense system against microbial and other environmental pathogenic influences. A number of nonspecific defense mechanisms, including the presence of lactoferrin, peroxidases, proteases, interferons, and lysozymes in nasal secretions, act to counter inflammatory processes. The surfactant proteins (SPs) known from the lungs are important components of the innate immune system. They also influence the rheology of fluids and reduce the surface tension of gas-fluid interphases. The objective of this study was to investigate the protein expression of all four SPs. A specific aim was detection and characterization of SP-C, which had previously not been confirmed in human nasal mucosa. Methods: The expression of mRNA for SP-A, -B, -C and -D was investigated using reverse transcriptase polymerase chain reaction on samples of both healthy nasal mucosa and nasal mucosa altered by inflammatory processes (allergic rhinitis and chronic rhinosinusitis). The distribution of all four proteins was determined with monoclonal antibodies using Western blot analysis as well as immunohistochemical methods. Results: The results show that all four SPs, including SP-C not detected before this, are nasal mucosa components. A shift was also observed in the expression behavior of the SP-A, -B, and -D in nasal mucosa with inflammatory changes. Conclusion: Based on these results, SPs appear to have an important function in immunologic and rheological process of the nasal mucosa and support the prospective therapeutic use of liposomal nasal sprays. Copyright © 2013, OceanSide Publications, Inc., U.S.A.
CRIS-Team Scopus Importer:2022-08-05

Determination of sex dimorphisms of the thickness of the hard palate in adolescence using computed tomography: Pilot study - Aleshkina, Olga; Suetenkov, Dmitriy; Dydykin, Sergey; Vasil'ev, Yuriy; Paulsen, Friedrich; Firsova, Irina; Bikbaeva, Tatiana; Polkovova, Irina (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Background: In addition to traditional craniometric techniques, computer craniometry has been used in recent decades, including stereometric methods, which make it possible to determine the microanatomical spatial relationships and dimensional features of various structures of the skull, in particular the thickness of the inert palate of the maxilla. Aim: Determination of the gender-specific variability of the thickness of the bony palate at the age of 18–20 years using CT. Material and methods: The material of the pilot study were 40 computed tomograms of young males and females aged 18–20 years. The method of computer craniometry was used to measure the thickness of the bony palate in sagittal projection taking into account the gender. A graphic raster map was created to identify the palatal areas, then analyze their thickness and determine the safe zones for the mini dental implants. Results: In young males and females (18–20 years) the thickness of the bony palate decreases at different levels from front to back and from the median suture to the alveolar process. The greatest thickness of the bony palate corresponds to its anterior third and reliably predominates in young males at all levels compared to young females. In the middle and posterior third palate, the averages do not show gender differences and their variation is insignificant. Conclusions: The greatest thickness of the bony palate can be used as the most favorable zone for the fixation of orthodontic mini dental implants. The variability in the thickness of the bony palate should be considered when selecting the most optimal zones and depth of mini-implant placement.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Adolescence; Bone palate; Mini dental implants; Orthodontic mini-screws

Developmental change in the gene-expression of transient receptor potential melanostatin channel 3 (TRPM3) in murine lacrimal gland - Kanewska, Anna; Ito, Masataka; Karasawa, Yoko; Inada, Makoto; Garreis, Fabian; Paulsen, Friedrich; Takeuchi, Masaru (2018)
EVALuna2:35312

Developmental change in the gene expression of transient receptor potential melastatin channel 3 (TRPM3) in murine lacrimal gland - Kanewska, A.; Ito, M.; Karasawa, Y.; Inada, M.; Garreis, Fabian; Paulsen, Friedrich; Takeuchi, M. (Annals of Anatomy-Anatomischer Anzeiger, 2020)
Transient receptor potential (TRP) channels are cation channels with ubiquitous expression. Various TRP channels are functionally active at the ocular surface and are involved in tear secretion and multiple inflammatory processes. So far, the impact of TRP channels regarding the development of the lacrimal gland (LG) is unclear. While investigating TRP channels in the LG, the TRPM3 channel presented itself as a promising candidate to play a role in the development and functioning of the LG. Therefore, Trpm3 expression was analyzed in different embryonic and postembryonic LGs. Thus, gene expression of TRPM channels including Trpm2, Trpm3, Trpm4 and Trpm6 was analyzed by quantitative RT-PCR in murine LGs at different developmental stages. Localization of TRPM3 in LGs was examined by immunohistochemistry. Primary LG epithelial cells (LGEC) and mesenchymal cells (MC) from newborn mice were cultured (either separately or collectively) for three days, and Trpm3 expression was analyzed in LGEC and MC. As a result, gene expression of Trpm2, Trpm4 and Trpm6 showed no significant difference in LGs in the different stages of development. However, Trpm3 gene expression was significantly higher in the embryonic stage than in the postnatal stage with the peak at E18. Postnatal, Trpm3 expression significantly decreased up to 28-fold until two years of age. Immunohistochemistry for TRPM3 revealed apical membranous expression in the excretory ducts, as well as in the acini of up to P7 old mice. Trpm3 expression in LGEC were significantly higher than that of MC. Our results indicate that Trpm3 expression in murine LG is age-dependent and peaks at age E18. Its expression is localized in the apical membrane of the glandular epithelium. However, its functional role still requires additional study in the LG.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Development; Lacrimal gland; Ocular surface; Ophthalmology; TRP channels

Development and Correlation of Work-Related Behavior and Experience Patterns, Burnout and Quality of Life in Medical Students from their Freshmanship to the First State Examination - Scholz, Michael; Neumann, Carolin; Steinmann, Cornelia; Hammer, Christian; Schröder, Antje; Essel, Nicole; Paulsen, Friedrich; Burger, Pascal H. M. (Psychotherapie Psychosomatik Medizinische Psychologie, 2015)
Symptoms of burnout are common among medical students. Although they usually start with a good health status, their condition deteriorates over the course of their studies. In our study ESTRELLAS we examined 530 medical students in the preclinical semesters with validated psychological questionnaires. The longer the students were studying, the more showed risky working habits. Cognitive and emotional burnout symptoms increased coincidentally in their intensity, whereas the mental quality of life continuously deteriorated. Medical students' cognitive and emotional burnout symptoms are constantly increasing from the beginning of their studies. Contemporaneously, the mental quality of life is deteriorating. This might be based on a drastic change towards risky working habits. We suggest to actively work against this process to keep our motivated students and prospective physi-cians productive and in good mental health.
EVALuna2:4431

Development and Initial Validation of a New Endoscopic Training Model for Advanced Endoscopic Procedures - The HEAT International Endoscopy Study - Neumann, Helmut; Buder, Thomas; Loeffler, Silke; Rath, Timo; Naegel, Andreas; Neuhuber, Winfried (2016)
EVALuna2:184251

Development of depression and deterioration in quality of life in German dental medical students in preclinical semesters - Burger, P. H. M.; Neumann, Carolin; Ropohl, A.; Paulsen, Friedrich; Scholz, Michael (Annals of Anatomy-Anatomischer Anzeiger, 2016)
PURPOSE: Early intervention to counter mental disorders during the course of studies in dentistry is indicated in view of the pronounced prevalence of burnout in this student collective. To assess the proportion of students in whom these risk states can be quantified in measurable parameters for concrete mental disorders, we conducted surveys among students of dental medicine during the first 2.5 years of their studies. METHODS: We surveyed a total of 163 students of dental medicine in their first 5 semesters of study. Standardized, validated psychological questionnaires on depressive symptoms (Beck Depression Inventory; BDI-II) and mental and physical quality of life (Short Form Survey; SF-12) were used in the survey, with per-semester participant quotas of around 90%. RESULTS: Regarding depression, the students were within the range of the normal populace at the beginning of the 1st semester. Symptoms of depression then became more pronounced with every succeeding semester. In the fifth semester, the average levels determined were equivalent to a depression with a clinical treatment indication. Hardly any change was registered for physical wellbeing in the quality of life questionnaire. The mental sum scores, however, reflected dramatic downturns in quality of life. Highly significant correlations between the parameters described here - depressivity and mental quality of life - were observed in all semesters. CONCLUSION: The participating students begin their course of studies at the level of the average populace for the symptoms surveyed, then develop, on average, a clinically manifest depression after 2.5 years. The personal experience of a deterioration of mental quality of life appears to be crucial in the phenomena observed.
EVALuna2:35352

Diagnosis of Proximal Hamstring Injuries Diagnostik von proximalen Hamstring-Verletzungen - Schroeter, S.; Heiß, Rafael; Hammer, Christian; Grim, C.; Engelhardt, M.; Hotfiel, T. (Sport-Orthopädie, Sport-Traumatologie, 2022)
Injuries and overload to the hamstring muscles are frequently observed in recreational and high-performance athletes. The proximal hamstring muscle complex is in a highly vulnerable region that is likely to sustain injury in several disciplines. Proximal hamstring injuries (PHI) are responsible for a substantial loss of training and competition days. A precise and targeted diagnostic approach is essential to provide a correct assessment of injury severity. In general, a careful anamnesis and thorough clinical examination with inspection, palpation, and functional testing provide substantial information about the extent and severity of injury. Imaging of muscle tissue is essential to confirm precise diagnosis for providing further assessment of the degree of damage or differential diagnosis. Understanding the specific tasks in the diagnosis of PHI requires knowledge of functional anatomy, injury, and pathophysiological mechanisms as well as examination and imaging techniques. The present work provides a structured overview of the diagnostic work-up of PHI, emphasizing structured examination and imaging techniques to enable reliable diagnosis and rapid treatment decisions.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Diagnosis; MRI; Muscle injuries; Sports injuries; Ultrasound

Diameters of umbilical and portal veins and ductus venosus in the human foetuses after 20 weeks of gestation in an ultrasound examination - Wozniak, Slawomir; Florjanski, Jerzy; Piatek, Aleksandra; Tomialowicz, Marek; Zazga, Maria; Szymocha, Marcin; Domagala, Zygmunt; Kurc-Darak, Bozena; Davies, D. Ceri; Paulsen, Friedrich (JOURNAL OF ANATOMY, 2021)
CRIS-Team WoS Importer:2021-02-12

Differential activity of transcription factor Sox9 in early and adult oligodendroglial progenitor cells - Hassel, Lisa; Fröb, Franziska; Küspert, Melanie; Hillgärtner, Simone; Arnold, Philipp; Huang, Wenhui; Kirchhoff, Frank; Wegner, Michael (Glia, 2023)
The high-mobility-group domain-containing transcription factor Sox9 confers glial competence to neuroepithelial precursors in the developing central nervous system and is an important determinant of astroglial and oligodendroglial specification. In oligodendroglial cells, it remains expressed in oligodendrocyte progenitor cells (OPCs) of the developing nervous system, but is shut off in differentiating oligodendrocytes as well as in OPCs that persist in the adult nervous system. To better understand the role of Sox9 in OPCs, we generated mouse models that allowed oligodendroglial expression of a Sox9 transgene during development or in the adult. With transgene expression beginning in the last trimester of pregnancy, the number of OPCs increased dramatically, followed by comparable gains in the number of pre-myelinating and myelinating oligodendrocytes as assessed by marker gene expression. This argues that Sox9 boosts oligodendrogenesis during ontogenetic development at all stages, including terminal oligodendrocyte differentiation. When Sox9 transgene expression started in the adult, many transgene-expressing OPCs failed to maintain their progenitor cell identity and instead converted into myelinating oligodendrocytes. As infrequent and inefficient differentiation of adult OPCs is one of the main obstacles to effective remyelination in demyelinating diseases such as Multiple Sclerosis, increased Sox9 levels in adult OPCs may substantially increase their remyelination capacity.
CRIS-Team Scopus Importer:2023-04-21
Keywords: glia; HMG; myelin; oligodendrocyte; Sox; Sry

Differential effects of FTY720 on the B cell compartment in a mouse model of multiple sclerosis - Bail, Kathrin; Notz, Quirin; Rovituso, Damiano M.; Schampel, Andrea; Wunsch, Marie; Koeniger, Tobias; Schropp, Verena; Bharti, Richa; Scholz, Claus-Juergen; Foerstner, Konrad U.; Kleinschnitz, Christoph; Kuerten, Stefanie (Journal of Neuroinflammation, 2017)
BACKGROUND: MP4-induced experimental autoimmune encephalomyelitis (EAE) is a mouse model of multiple sclerosis (MS), which enables targeted research on B cells, currently much discussed protagonists in MS pathogenesis. Here, we used this model to study the impact of the S1P1 receptor modulator FTY720 (fingolimod) on the autoreactive B cell and antibody response both in the periphery and the central nervous system (CNS). METHODS: MP4-immunized mice were treated orally with FTY720 for 30 days at the peak of disease or 50 days after EAE onset. The subsequent disease course was monitored and the MP4-specific B cell/antibody response was measured by ELISPOT and ELISA. RNA sequencing was performed to determine any effects on B cell-relevant gene expression. S1P1 receptor expression by peripheral T and B cells, B cell subset distribution in the spleen and B cell infiltration into the CNS were studied by flow cytometry. The formation of B cell aggregates and of tertiary lymphoid organs (TLOs) was evaluated by histology and immunohistochemistry. Potential direct effects of FTY720 on B cell aggregation were studied in vitro. RESULTS: FTY720 significantly attenuated clinical EAE when treatment was initiated at the peak of EAE. While there was a significant reduction in the number of T cells in the blood after FTY720 treatment, B cells were only slightly diminished. Yet, there was evidence for the modulation of B cell receptor-mediated signaling upon FTY720 treatment. In addition, we detected a significant increase in the percentage of B220+ B cells in the spleen both in acute and chronic EAE. Whereas acute treatment completely abrogated B cell aggregate formation in the CNS, the numbers of infiltrating B cells and plasma cells were comparable between vehicle- and FTY720-treated mice. In addition, there was no effect on already developed aggregates in chronic EAE. In vitro B cell aggregation assays suggested the absence of a direct effect of FTY720 on B cell aggregation. However, FTY720 impacted the evolution of B cell aggregates into TLOs. CONCLUSIONS: The data suggest differential effects of FTY720 on the B cell compartment in MP4-induced EAE.
EVALuna2:35216

Differentiation Patterns of Immortalized Human Meibomian Gland Epithelial Cells in Three-Dimensional Culture - Asano, Nagayoshi; Hampel, Ulrike; Garreis, Fabian; Schröder, Antje; Schicht, Martin; Hammer, Christian; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2018)
Purpose: To establish a simplified three-dimensional (3D) meibomian gland culture model using a meibomian gland epithelial cell (HMGEC) line that might be a useful tool to gain deeper insights into meibomian gland dysfunction. For this purpose, 3D differentiation patterns and growth characteristics of HMGECs were studied on various membranes/scaffolds as well as in hanging drops. Methods: Several types of inserts consisting of different materials (Millicell-HA, Millicell-PCF, ThinCert, and Alvetex) as well as hanging drop culture were analyzed. Culture conditions were optimized employing exposure to air (air-lift) and different cell culture media for a maximum of 28 days. To characterize cell differentiation in the developed 3D model, the expression pattern of cytokeratins was investigated by immunohistochemistry. Sudan III staining was performed for detection of lipid formation and transmission electron microscopy (TEM) was used for ultrastructural analysis. Results: Only Alvetex scaffolds and the hanging drop method revealed satisfactory results with regard to 3D culture. Continuous use of proliferation medium (serum-free keratinocyte medium containing epidermal growth factor and bovine pituitary extract) and air-lift were important steps for HMGEC differentiation in 3D culture. However, HMGECs only reached a differentiating state and never became mature or hypermature. When cultured in hanging drops, HMGECs showed serum-induced keratinization processes. Conclusions: HMGECs have the capability to differentiate in a long-term 3D culture, especially when adapted to an air-rich environment. However, even in the 3D format, HMGECs only reach a state of differentiating meibocytes.
EVALuna2:35318

Different Patterns of Cartilage Mineralization Analyzed by Comparison of Human, Porcine, and Bovine Laryngeal Cartilages - Claassen, Horst; Schicht, Martin; Fleiner, Bernd; Hillmann, Ralf; Hoogeboom, Sebastian; Tillmann, Bernhard; Paulsen, Friedrich (Journal of Histochemistry & Cytochemistry, 2017)
Laryngeal cartilages undergo a slow ossification process during aging, making them an excellent model for studying cartilage mineralization and ossification processes. Pig laryngeal cartilages are similar to their human counterparts in shape and size, also undergo mineralization, facilitating the study of cartilage mineralization. We investigated the processes of cartilage mineralization and ossification and compared these with the known processes in growth plates. Thyroid cartilages from glutaraldehyde-perfused male minipigs and from domestic pigs were used for X-ray, light microscopic, and transmission electron microscopic analyses. We applied different fixation and postfixation solutions to preserve cell shape, proteoglycans, and membranes. In contrast to the ossifying human thyroid cartilage, predominantly cartilage mineralization was observed in minipig and domestic pig thyroid cartilages. The same subset of chondrocytes responsible for growth plate mineralization is also present in thyroid cartilage mineralization. Besides mineralization mediated by matrix vesicles, a second pattern of cartilage mineralization was observed in thyroid cartilage only. Here, the formation and growth of crystals were closely related to collagen fibrils, which served as guide rails for the expansion of mineralization. It is hypothesized that the second pattern of cartilage mineralization may be similar to a maturation of mineralized cartilage after initial matrix vesicles-mediated cartilage mineralization.
EVALuna2:35331

Different treatment settings of Granulocyte-Colony Stimulating Factor and their impact on T cell-specific immune response in experimental stroke - Dietel, Barbara; Cicha, Iwona; Achenbach, Stephan; Kollmar, Rainer; Garlichs, Christoph; Tauchi, Miyuki (Immunology Letters, 2014)
Cerebral ischemia is associated with infectious complications due to immunosuppression and decreased T lymphocyte activity. G-CSF, which has neuroprotective properties, is known to modulate inflammatory processes after induced stroke. The aim of our study was to investigate the impact of G-CSF in experimental stroke and to compare two different modes of treatment, focusing on circulating T lymphocytes.Cerebral ischemia was induced in Wistar rats by occlusion of the middle cerebral artery, followed by reperfusion after 1h. G-CSF was applied either as a single dose 30 min after occlusion, or daily for seven days. Silver staining was used to determine infarct size. T lymphocytes in the peripheral blood were measured before and 7 days after induced cerebral ischemia by flow cytometry. In addition, migration of CD3-expressing T lymphocytes into the brain was investigated by immunohistochemistry.Both single dose and daily treatment with G-CSF significantly reduced infarct size. A significant improvement of neurological outcome was only observed after single application of G-CSF. While a decrease in peripheral T lymphocytes was detected seven days after induced stroke, no reduction was observed in the G-CSF-treated groups. Apart from that, G-CSF significantly reduced the number of brain migrated T lymphocytes in both treatment settings as compared to vehicle.A single dose of G-CSF exerted neuroprotective effects in ischemic stroke, which were less pronounced after daily G-CSF application. Both treatment strategies inhibited stroke-induced reduction of T lymphocytes in peripheral blood, which may have contributed to the reduction of infarct size.
EVALuna2:12004

Digital pathology imaging and computer-aided diagnostics as a novel tool for standardization of evaluation of aganglionic megacolon (Hirschsprung disease) histopathology - Schilling, Florian; Geppert, Carol-Immanuel; Strehl, Johanna; Hartmann, Arndt; Kürten, Stefanie; Brehmer, Axel; Jabari, Samir (Cell and Tissue Research, 2018)
Based on a recently introduced immunohistochemical panel (Bachmann et al. 2015) for aganglionic megacolon (AM), also known as Hirschsprung disease, histopathological diagnosis, we evaluated whether the use of digital pathology and 'machine learning' could help to obtain a reliable diagnosis. Slides were obtained from 31 specimens of 27 patients immunohistochemically stained for MAP2, calretinin, S100β and GLUT1. Slides were digitized by whole slide scanning. We used a Definiens Developer Tissue Studios as software for analysis. We configured necessary parameters in combination with 'machine learning' to identify pathological aberrations. A significant difference between AM- and non-AM-affected tissues was found for calretinin (AM 0.55% vs. non-AM 1.44%) and MAP2 (AM 0.004% vs. non-AM 0.07%) staining measurements and software-based evaluations. In contrast, S100β and GLUT1 staining measurements and software-based evaluations showed no significant differences between AM- and non-AM-affected tissues. However, no difference was found in comparison of suction biopsies with resections. Applying machine learning via an ensemble voting classifier, we achieved an accuracy of 87.5% on the test set. Automated diagnosis of AM by applying digital pathology on immunohistochemical panels was successful for calretinin and MAP2, whereas S100β and GLUT1 were not effective in diagnosis. Our method suggests that software-based approaches are capable of diagnosing AM. Our future challenge will be the improvement of efficiency by reduction of the time-consuming need for large pre-labelled training data. With increasing technical improvement, especially in unsupervised training procedures, this method could be helpful in the future.
EVALuna2:35208

Direct Detection of T- and B-Memory Lymphocytes by ImmunoSpot® Assays Reveals HCMV Exposure that Serum Antibodies Fail to Identify - Terlutter, Fredrik; Caspell, Richard; Nowacki, Tobias M.; Lehmann, Alexander; Li, Ruliang; Zhang, Ting; Przybyla, Anna; Kürten, Stefanie; Lehmann, Paul V. (Cells, 2018)
It is essential to identify donors who have not been infected with human cytomegalovirus (HCMV) in order to avoid transmission of HCMV to recipients of blood transfusions or organ transplants. In the present study, we tested the reliability of seronegativity as an indicator for the lack of HCMV exposure in healthy human blood donors. Eighty-two HCMV seronegative individuals were identified, and their peripheral blood mononuclear cells (PBMC) were tested in ImmunoSpot® assays for the presence of HCMV-specific T- and B-memory lymphocytes. Eighty-two percent (67 of 82) of these HCMV seronegative individuals featured at least one memory cell that was lineage specific for HCMV, with the majority of these subjects possessing CD4+ and CD8+ T cells, as well as B cells, providing three independent lines of evidence for having developed immunity to HCMV. Only 15 of these 82 donors (18%) showed neither T- nor B-cell memory to HCMV, consistent with immunological naïveté to the virus. The data suggest that measurements of serum antibodies frequently fail to reveal HCMV exposure in humans, which may be better identified by direct detection of HCMV-specific memory lymphocytes.
EVALuna2:35211

Distribution, morphology and projections of nitergic and non-nitrergic submucosal neurons in the pig small intestine - Brehmer, Axel; Stach, Werner; Krammer, Heinz-Jürgen; Neuhuber, Winfried (Histochemistry and Cell Biology, 1998)
Sequential nitric oxide synthase immunohistochemistry and nicotinamide adenine dinucleotide phosphate diaphorase (NADPHd) histochemistry in pig small intestinal wholemounts revealed a complete colocalisation of the two nitrergic markers in submucous neurons. The external submucous plexus (ESP) contained nitrergic neurons throughout. In the internal submucous plexus (ISP) we found a moderate number of nitrergic neurons in the duodenum, while they were rare in the jejunum and nearly absent in the ileum. Combined NADPHd histochemistry and silver impregnation showed morphological ESP type III and VI neurons to be NADPHd positive whereas ESP type II, IV and V neurons were NADPHd negative. Axons of ESP type III, IV and VI neurons were often observed to enter interconnecting strands directed abluminally. ESP type II neurons projected mainly to the ISP. In special silver-impregnated wholemounts containing both external muscle layers and the abluminal part of the submucous layer, i.e. the myenteric plexus and the ESP, the great majority of impregnated axons within the interconnecting strands were observed to run between both plexuses and did not enter the circular muscle layer. We conclude that ESP type III and VI neurons are nitrergic while ESP type II, IV and V neurons are non-nitrergic. Furthermore, we assume that ESP type III, IV and VI neurons may represent a submucosal input to the myenteric plexus.

Distribution of Young's modulus in porcine corneas after riboflavin/UVA-induced collagen cross-linking as measured by atomic force microscopy - Seifert, Jan; Hammer, Christian; Rheinlaender, Johannes; Sel, Saadettin; Scholz, Michael; Paulsen, Friedrich; Schaeffer, Tilman E. (PLoS ONE, 2014)
Riboflavin/UVA-induced corneal collagen cross-linking has become an effective clinical application to treat keratoconus and other ectatic disorders of the cornea. Its beneficial effects are attributed to a marked stiffening of the unphysiologically weak stroma. Previous studies located the stiffening effect predominantly within the anterior cornea. In this study, we present an atomic force microscopy-derived analysis of the depth-dependent distribution of the Young's modulus with a depth resolution of 5 µm in 8 cross-linked porcine corneas and 8 contralateral controls. Sagittal cryosections were fabricated from every specimen and subjected to force mapping. The mean stromal depth of the zone with effective cross-linking was found to be 219 ± 67 µm. Within this cross-linked zone, the mean Young's modulus declined from 49 ± 18 kPa at the corneal surface to 46 ± 17 kPa, 33 ± 11 kPa, 17 ± 5 kPa, 10 ± 4 kPa and 10 ± 4 kPa at stromal depth intervals of 0-50 µm, 50-100 µm, 100-150 µm, 150-200 µm and 200-250 µm, respectively. This corresponded to a stiffening by a factor of 8.1 (corneal surface), 7.6 (0-50 µm), 5.4 (50-100 µm), 3.0 (100-150 µm), 1.6 (150-200 µm), and 1.5 (200-250 µm), when compared to the Young's modulus of the posterior 100 µm. The mean Young's modulus within the cross-linked zone was 20 ± 8 kPa (2.9-fold stiffening), while it was 11 ± 4 kPa (1.7-fold stiffening) for the entire stroma. Both values were significantly distinct from the mean Young's modulus obtained from the posterior 100 µm of the cross-linked corneas and from the contralateral controls. In conclusion, we were able to specify the depth-dependent distribution of the stiffening effect elicited by standard collagen cross-linking in porcine corneas. Apart from determining the depth of the zone with effective corneal cross-linking, we also developed a method that allows for atomic force microscopy-based measurements of gradients of Young's modulus in soft tissues in general.
EVALuna2:4408

DNA methylation-based classification of malformations of cortical development in the human brain - Jabari, Samir; Kobow, Katja; Pieper, Tom; Hartlieb, Till; Kudernatsch, Manfred; Polster, Tilman; Bien, Christian G.; Kalbhenn, Thilo; Simon, Matthias; Hamer, Hajo; Roessler, Karl; Feucht, Martha; et al. (Acta Neuropathologica, 2022)
Malformations of cortical development (MCD) comprise a broad spectrum of structural brain lesions frequently associated with epilepsy. Disease definition and diagnosis remain challenging and are often prone to arbitrary judgment. Molecular classification of histopathological entities may help rationalize the diagnostic process. We present a retrospective, multi-center analysis of genome-wide DNA methylation from human brain specimens obtained from epilepsy surgery using EPIC 850 K BeadChip arrays. A total of 308 samples were included in the study. In the reference cohort, 239 formalin-fixed and paraffin-embedded (FFPE) tissue samples were histopathologically classified as MCD, including 12 major subtype pathologies. They were compared to 15 FFPE samples from surgical non-MCD cortices and 11 FFPE samples from post-mortem non-epilepsy controls. We applied three different statistical approaches to decipher the DNA methylation pattern of histopathological MCD entities, i.e., pairwise comparison, machine learning, and deep learning algorithms. Our deep learning model, which represented a shallow neuronal network, achieved the highest level of accuracy. A test cohort of 43 independent surgical samples from different epilepsy centers was used to test the precision of our DNA methylation-based MCD classifier. All samples from the test cohort were accurately assigned to their disease classes by the algorithm. These data demonstrate DNA methylation-based MCD classification suitability across major histopathological entities amenable to epilepsy surgery and age groups and will help establish an integrated diagnostic classification scheme for epilepsy-associated MCD.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Brain development; Cortical malformation; Deep learning; Epigenetic; Epilepsy

DNA methyltransferase 3A controls intestinal epithelial barrier function and regeneration in the colon - Fazio, Antonella; Bordoni, Dora; Kuiper, Jan W. P.; Weber-Stiehl, Saskia; Stengel, Stephanie T.; Arnold, Philipp; Ellinghaus, David; Ito, Go; Tran, Florian; Messner, Berith; Henning, Anna; Bernardes, Joana P.; et al. (Nature Communications, 2022)
Genetic variants in the DNA methyltransferase 3 A (DNMT3A) locus have been associated with inflammatory bowel disease (IBD). DNMT3A is part of the epigenetic machinery physiologically involved in DNA methylation. We show that DNMT3A plays a critical role in maintaining intestinal homeostasis and gut barrier function. DNMT3A expression is downregulated in intestinal epithelial cells from IBD patients and upon tumor necrosis factor treatment in murine intestinal organoids. Ablation of DNMT3A in Caco-2 cells results in global DNA hypomethylation, which is linked to impaired regenerative capacity, transepithelial resistance and intercellular junction formation. Genetic deletion of Dnmt3a in intestinal epithelial cells (Dnmt3aΔIEC) in mice confirms the phenotype of an altered epithelial ultrastructure with shortened apical-junctional complexes, reduced Goblet cell numbers and increased intestinal permeability in the colon in vivo. Dnmt3aΔIEC mice suffer from increased susceptibility to experimental colitis, characterized by reduced epithelial regeneration. These data demonstrate a critical role for DNMT3A in orchestrating intestinal epithelial homeostasis and response to tissue damage and suggest an involvement of impaired epithelial DNMT3A function in the etiology of IBD.
CRIS-Team Scopus Importer:2022-11-04

Does formalin fixation influence MSCT/CBCT accuracy? - Seidel, Anna; Bergauer, Bastian; Lell, Michael; Buder, Thomas; von Wilmowsky, Cornelius; Dach, Eva; Wichmann, Manfred; Matta, Ragai-Edward (Surgical and Radiologic Anatomy, 2017)
PURPOSE: Advanced imaging modalities, such as multi-slice computed tomography (MSCT) and cone beam computed tomography (CBCT), greatly facilitate diagnostic medicine. In radiological research, it is important to know how accurately a scanned object is visualized, and whether the methodology leads to image distortion. The objective of this study was to evaluate whether formalin fixation impacted the accuracy of virtual 3D bone models generated via CBCT and MSCT using a software-based evaluation method that excluded human measurement errors. METHODS: A head specimen, with and without formalin preservation, was subjected to MSCT and CBCT scans using the manufacturers' predefined scanning protocols. Digital models of the lower jaw were constructed and superimposed with a master model generated based on optical scanning with an industrial non-contact scanner. Means and standard deviations were calculated to assess accuracy, and a t test was used for comparisons between the fixed and unfixed specimens. RESULTS: The extent of discrepancy between the fixed and unfixed specimens was analyzed using a total of 200 points (n = 200) in each specimen state. The mean deviation between states was 0.01 mm for MSCT (at both 80 and 140 kV). Mean values from CBCT at 0.4 voxel did not differ between states. CONCLUSIONS: Our results suggest that formalin fixation of an anatomical specimen does not substantially affect the accuracy of a three-dimensional image generated with CBCT and MSCT. Thus, fixed specimen can be used in future investigations of 3D models without concerns regarding the accuracy.
EVALuna2:32833

Does vagus nerve stimulation influence pregnancy outcomes? - Sabers, Anne; Buchgreitz, Line; Neuhuber, Winfried (Brain Stimulation, 2018)
EVALuna2:35203

Donor-related risk factors and preoperative recipient-related risk factors for graft failure - Yu, Alice L.; Kaiser, Michaela; Schaumberger, Markus; Messmer, Elisabeth; Kook, Daniel; Welge-Lüssen, Ulrich-Christoph (Cornea, 2014)
The aim of this study was to evaluate the outcome of penetrating keratoplasties, at the University Eye Hospital, Ludwig-Maximilians-University, Munich, Germany, using organ-cultured donor corneas and to identify preoperative risk factors, which may influence the event of graft failure.In this study, 377 medical records of patients, who underwent penetrating keratoplasty between 2001 and 2011, were reviewed. Organ-cultured donor corneas were obtained from the eye bank, Ludwig-Maximilians-University, Munich, Germany. Donor-related and preoperative recipient-related risk factors for graft failure were analyzed by univariate and multivariate analyses.Graft failure occurred in 26% of patients. The following preoperative factors were significantly associated with graft failure by multivariate analyses: high donor age, low donor endothelial cell density, high patient age, indications of infectious keratitis, acute perforation of noninfectious keratitis, prior graft failure, chemical burn, trauma, glaucoma-associated corneal decompensation, high-risk graft indications, corneal edema, anterior chamber lens, diabetes mellitus, atopy, and autoimmune diseases.This study demonstrated a success rate of 74%, which is consistent with previous studies. Various preoperative recipient-related factors seem to influence the outcome of penetrating keratoplasties, whereas few donor-related factors have a significant association with graft failure.
EVALuna2:21201

Dynamics of humoral and cellular immune responses after homologous and heterologous SARS-CoV-2 vaccination with ChAdOx1 nCoV-19 and BNT162b2 - Vogel, Emanuel; Kocher, Katharina; Priller, Alina; Cheng, Cho Chin; Steininger, Philipp; Liao, Bo Hung; Körber, Nina; Willmann, Annika; Irrgang, Pascal; Held, Jürgen; Moosmann, Carolin; Schmidt, Viviane; et al. (EBioMedicine, 2022)
Background: Vaccines are an important means to overcome the SARS-CoV-2 pandemic. They induce specific antibody and T-cell responses but it remains open how well vaccine-induced immunity is preserved over time following homologous and heterologous immunization regimens. Here, we compared the dynamics of humoral and cellular immune responses up to 180 days after homologous or heterologous vaccination with either ChAdOx1-nCoV-19 (ChAd) or BNT162b2 (BNT) or both. Methods: Various tests were used to determine the humoral and cellular immune response. To quantify the antibody levels, we used the surrogate neutralization (sVNT) assay from YHLO, which we augmented with pseudo- and real virus neutralization tests (pVNT and rVNT). Antibody avidity was measured by a modified ELISA. To determine cellular reactivity, we used an IFN-γ Elispot, IFN-γ/IL Flurospot, and intracellular cytokine staining. Findings: Antibody responses significantly waned after vaccination, irrespective of the regimen. The capacity to neutralize SARS-CoV-2 – including variants of concern such as Delta or Omicron – was superior after heterologous compared to homologous BNT vaccination, both of which resulted in longer-lasting humoral immunity than homologous ChAd immunization. All vaccination regimens induced stable, polyfunctional T-cell responses. Interpretation: These findings demonstrate that heterologous vaccination with ChAd and BNT is a potent alternative to induce humoral and cellular immune protection in comparison to the homologous vaccination regimens. Funding: The study was funded by the German Centre for Infection Research (DZIF), the European Union's “Horizon 2020 Research and Innovation Programme" under grant agreement No. 101037867 (VACCELERATE), the “Bayerisches Staatsministerium für Wissenschaft und Kunst” for the CoVaKo-2021 and the For-COVID projects and the Helmholtz Association via the collaborative research program “CoViPa”. Further support was obtained from the Federal Ministry of Education and Science (BMBF) through the “Netzwerk Universitätsmedizin”, project “B-Fast” and “Cov-Immune”. KS is supported by the German Federal Ministry of Education and Research (BMBF, 01KI2013) and the Else Kröner-Stiftung (2020_EKEA.127).
CRIS-Team Scopus Importer:2022-10-21
Keywords: antibody avidity; BNT162b2; ChAdOx1-nCoV-19; COVID-19; Heterologous vaccination; long-term; maintenance; SARS-CoV-2; T cell immunity; vaccine

Dynamic study of the finger interphalangeal joint volar plate—motion analysis with magnetic resonance cinematography and histologic comparison - Lutter, Christoph; Kürten, Stefanie; Geppert, Carol-Immanuel; Mittelmeier, Wolfram; Klinder, Annett; Söder, Stephan; Roemer, Frank; Uder, Michael; Janka, Rolf Matthias; Bayer, Thomas (Skeletal Radiology, 2023)
Objective: We aimed to further improve knowledge about volar plate (VP) motion of the finger proximal interphalangeal joint (PIP), by analyzing the dynamic VP shape during a full range of finger flexion using magnetic resonance cinematography of the fingers (MRCF), and to compare the results with anatomical cross sections from cadaver specimens. Materials and methods: The dynamic sagittal VP shape was visualized with MRCF in a total number of 23 healthy volunteers. The length, angle, and thickness as well as the contact length of the VP to the PIP joint base were measured. Statistical analysis included t-test or rank-sum testing. Anatomical cross sections with differing degrees of PIP joint flexion were obtained from 12 cadaver specimens (fingers) for comparison. Results: Significant positive correlations between PIP joint flexion angle and VP area, length, depth and the VP contact length were found. This matched histologically to fiber rearrangements especially within the loose third VP layer. Conclusion: Our study analyzed the full range of motion dynamic VP shape of the PIP joint using MRCF. This contributes to a more precise understanding of the complex interaction of the VP with the PIP joint and may facilitate evaluation of clinical cases such as VP avulsion or pulley rupture.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Dislocation; Injury; Microsurgery; MRI; Ultrasound

DYNC2LI1 mutations broaden the clinical spectrum of dynein-2 defects - Keßler, Kristin; Wunderlich, Ina; Uebe, Steffen; Falk, Nathalie; Gießl, Andreas; Brandstätter, Johann Helmut; Popp, Bernt; Klinger, Patricia; Ekici, Arif Bülent; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Scientific Reports, 2015)
Skeletal ciliopathies are a heterogeneous group of autosomal recessive osteochondrodysplasias caused by defects in formation, maintenance and function of the primary cilium. Mutations in the underlying genes affect the molecular motors, intraflagellar transport complexes (IFT), or the basal body. The more severe phenotypes are caused by defects of genes of the dynein-2 complex, where mutations in DYNC2H1, WDR34 and WDR60 have been identified. In a patient with a Jeune-like phenotype we performed exome sequencing and identified compound heterozygous missense and nonsense mutations in DYNC2LI1 segregating with the phenotype. DYNC2LI1 is ubiquitously expressed and interacts with DYNC2H1 to form the dynein-2 complex important for retrograde IFT. Using DYNC2LI1 siRNA knockdown in fibroblasts we identified a significantly reduced cilia length proposed to affect cilia function. In addition, depletion of DYNC2LI1 induced altered cilia morphology with broadened ciliary tips and accumulation of IFT-B complex proteins in accordance with retrograde IFT defects. Our results expand the clinical spectrum of ciliopathies caused by defects of the dynein-2 complex.
EVALuna2:9281

E-Cadherin Is Important for Meibomian Gland Function as Revealed by a New Human ex Vivo Slice Culture Model - Rötzer, Vera; Melega, Francesca; Garreis, Fabian; Paulsen, Friedrich; Waschke, Jens (American Journal of Pathology, 2019)
Meibomian glands within the eyelid are important for the maintenance of the integrity and health of the ocular surface. Patients with the blistering skin disease pemphigus vulgaris (PV), which is caused by autoantibodies against desmosomal cadherins, often have dry eye disease. Therefore, we studied the regulation of cell cohesion in human meibomian gland epithelial cells (HMGECs). During serum-induced differentiation for 1 to 6 days, HMGECs drastically enhanced intercellular cohesion, whereas lipid production did not change. The expression profiles of the desmosomal PV antigens desmoglein (Dsg) 3 and 1 but not of the adherens junction component E-cadherin (Ecad) was dependent on the presence of serum. Surprisingly, after 1 day but not after 6 days of serum-induced differentiation, an inhibitory antibody against Ecad drastically reduced intercellular cohesion and blocked lipid production of HMGECs. In contrast, antibodies against desmosomal cadherins, including human and mouse pemphigus autoantibodies, had no effect on monolayer integrity and lipid production. Because lipid production was unaltered in meibomian glands from Dsg3-deficient mice, we established an ex vivo slice culture model of human eyelids to allow studies in a more physiologic environment. Here, the inhibitory antibody against Ecad but not a Dsg3-specific PV antibody interfered with stimulated lipid production. Together, these data demonstrate that cell cohesion is maintained differently in meibomian gland cells and indicate that Ecad is important for meibomian gland function.
CRIS-Team Scopus Importer:2019-08-02

Effect of a calcitonin gene-related peptide-binding L-RNA aptamer on neuronal activity in the rat spinal trigeminal nucleus - Fischer, Michael; Schmidt, Jakob; Koulchitsky, Stanislav; Klussmann, Sven; Vater, Axel; Meßlinger, Karl (Journal of Headache and Pain, 2018)
BACKGROUND: Calcitonin gene-related peptide (CGRP) plays a major role in the pathogenesis of migraine and other primary headaches. Spinal trigeminal neurons integrate nociceptive afferent input from trigeminal tissues including intracranial afferents, and their activity is thought to reflect facial pain and headache in man. CGRP receptor inhibitors and anti-CGRP antibodies have been demonstrated to be therapeutically effective in migraine. In parallel, CGRP receptor inhibition has been shown to lower spinal trigeminal neuron activity in animal models of meningeal nociception. METHODS: In a rat model of meningeal nociception, single cell activity of neurons in the spinal trigeminal nucleus with meningeal afferent input was recorded to test a further pharmacological approach, scavenging CGRP with a CGRP-binding L-RNA oligonucleotide, the L-aptamer NOX-C89. Cumulative ascending doses of NOX-C89 were intravenously infused. RESULTS: Spontaneous activity of spinal trigeminal neurons did not change after 0.05 mg/kg NOX-C89, however, after additional infusion of 0.5 mg/kg and 5 mg/kg NOX-C89, spontaneous activity was dose-dependently reduced. Identical doses of a control L-aptamer had no effect. This pharmacological effect of NOX-C89 was observed 10-25 min after infusion, but no difference was detected in the period 0-5 min. For comparison, the previously investigated CGRP receptor antagonist olcegepant had reduced activity within 5 min after infusion. Alongside the reduced spontaneous activity, after infusion of NOX-C89 the heat-induced neuronal activity was abolished. CONCLUSIONS: Scavenging CGRP by mirror-image RNA aptamers provides further evidence that this approach can be used to control spinal trigeminal activity.
EVALuna2:35775

Effect of intermittent shear stress on corneal epithelial cells using an in vitro flow culture model - Hampel, Ulrike; Garreis, Fabian; Burgemeister, Fabian; Eßel, Nicole; Paulsen, Friedrich (Ocular Surface, 2018)
PURPOSE: The aim of this study was to establish and to evaluate an in vitro model for culturing human telomerase-immortalized corneal epithelial (hTCEpi) cells under adjustable medium flow mimicking the movements of the tear film on the ocular surface. METHODS: Using an IBIDI pump system, cells were cultured under unidirectional, continuous or oscillating, discontinuous medium flow. Cell surface and cytoskeletal architecture were investigated by scanning electron microscopy and immunofluorescence. Gene expression of e-cadherin, occludin, tight junction protein (TJP), desmoplakin, desmocollin and mucins was investigated by real-time PCR. Protein expression of desmoplakin, TJP, occludin and e-cadherin was analyzed by western blot and localization was detected by immunofluorescence. Rose bengal staining was used to assess mucin (MUC) barrier integrity. MUC1, -4 and -16 proteins were localized by immunofluorescence. RESULTS: Medium flow-induced shear stress dramatically changed cellular morphology of hTCEpi. Cells subjected to discontinuous shear stress displayed the typical flattened, polygonal cell shape of the superficial layer of stratified squamous epithelia. Cell surfaces showed less bulging under shear stress and less extracellular gaps. The mRNA expression of E-cadherin, occludin and TJP were increased under oscillatory medium flow. Desmoplakin and occludin protein were upregulated under oscillatory shear stress. Stress fiber formation was not aligned to flow direction. MUC1, -4, and -16 protein were localized under all culture conditions, a regulation on mRNA expression was not detectable. Rose Bengal uptake was diminished under unidirectional conditions. CONCLUSION: Our findings suggest that shear stress as it occurs at the ocular surface during blinking exerts marked effects on corneal epithelial cells, such as changes in cellular morphology and expression of cell junctions. The described model may be useful for in vitro investigations of ocular surface epithelia as it represents a much more physiologic reproduction of the in vivo situation than the commonly applied static culture conditions.
EVALuna2:35314

Effect of Tff3 Deficiency and ER Stress in the Liver - Šešelja, Kate; Bazina, Iva; Welss, Jessica; Schicht, Martin; Paulsen, Friedrich; Bijelić, Nikola; Rođak, Edi; Horvatić, Anita; Gelemanović, Andrea; Mihalj, Martina; Baus Lončar, Mirela (International Journal of Molecular Sciences, 2019)
Endoplasmic reticulum (ER) stress, a cellular condition caused by the accumulation of unfolded proteins inside the ER, has been recognized as a major pathological mechanism in a variety of conditions, including cancer, metabolic and neurodegenerative diseases. Trefoil factor family (TFFs) peptides are present in different epithelial organs, blood supply, neural tissues, as well as in the liver, and their deficiency has been linked to the ER function. Complete ablation of Tff3 expression is observed in steatosis, and as the most prominent change in the early phase of diabetes in multigenic mouse models of diabesity. To elucidate the role of Tff3 deficiency on different pathologically relevant pathways, we have developed a new congenic mouse model Tff3-/-/C57BL6/N from a mixed background strain (C57BL6/N /SV129) by using a speed congenics approach. Acute ER stress was evoked by tunicamycin treatment, and mice were sacrificed after 24 h. Afterwards the effect of Tff3 deficiency was evaluated with regard to the expression of relevant oxidative and ER stress genes, relevant proinflammatory cytokines/chemokines, and the global protein content. The most dramatic change was noticed at the level of inflammation-related genes, while markers for unfolded protein response were not significantly affected. Ultrastructural analysis confirmed that the size of lipid vacuoles was affected as well. Since the liver acts as an important metabolic and immunological organ, the influence of Tff3 deficiency and physiological function possibly reflects on the whole organism.
CRIS-Team Scopus Importer:2019-09-17
Keywords: ER stress; liver; proinflammatory cytokines; trefoil peptide 3; tunicamycin

Effect of Topical 5-Fluorouracil on Lacrimal Drainage System: Histopathological Evidence from Animal Experiments and Potential Clinical Implications - Singh, Swati; Trakos, Nikolaos; Ali, Mohammad Javed (Ophthalmic Plastic and Reconstructive Surgery, 2023)
Purpose: The purpose of this study is to investigate the histopathological changes in the lacrimal drainage system of rabbits following the application of 1% topical 5-fluorouracil (5-FU) for 4 weeks. Methods: Ten eyes of 10 healthy New Zealand white rabbits were subjected to topical instillation of 1% (10 mg/mL) 5-FU, 1 drop 4 times a day for 4 weeks. Rabbits underwent a detailed ocular examination including eyelids, ocular surface, punctal, peri-punctal changes, and nasolacrimal duct patency at baseline and after 4 weeks of 5-FU. The rabbits were then sacrificed, and the eyelid, conjunctiva, lacrimal gland, and the entire lacrimal drainage system were retrieved for histopathological analysis as per standard protocols. Results: Clinically demonstrable peripunctal changes and canalicular stenosis were noted in 6 (60%, 6/10) rabbits. Two of these (20%, 2/10) had additional complete regurgitation of clear fluid, indicating a nasolacrimal duct obstruction. The remaining 4 (40%, 4/10) clinically did not demonstrate lacrimal drainage changes and were patent on irrigation. The conjunctiva showed focal loss of goblet cells in several areas. Significant changes were noted in the canalicular, lacrimal sac, and the nasolacrimal duct tissues in the form of epithelial hyperplasia, subepithelial inflammation, edema, dilated and congested vessels, and fibrosis. The lacrimal gland, eyelid tissue (excluding tarsal conjunctiva), and cornea showed no significant histopathological changes. Conclusions: Clinical and histopathological changes were noted in the lacrimal drainage system of rabbits subjected to topical 5-FU application. These findings can have potential clinical implications for patients receiving 5-FU therapy.
CRIS-Team Scopus Importer:2023-06-02

Effects of a Fully Humanized Type II Anti-CD20 Monoclonal Antibody on Peripheral and CNS B Cells in a Transgenic Mouse Model of Multiple Sclerosis - Tacke, Sabine; Chunder, Rittika; Schropp, Verena; Urich, Eduard; Kürten, Stefanie (International Journal of Molecular Sciences, 2022)
Successful therapy with anti-CD20 monoclonal antibodies (mAbs) has reinforced the key role of B cells in the immunopathology of multiple sclerosis (MS). This study aimed to determine the effects of a novel class of anti-CD20 mAbs on vascular and extravascular central nervous system (CNS)-infiltrating B cells in experimental autoimmune encephalomyelitis (EAE), an animal model of MS. Male hCD20xhIgR3 mice and wild-type C57BL/6 (B6) mice were immunized with human myelin oligodendrocyte glycoprotein (MOG)1–125 to induce EAE. While hCD20xhIgR3 mice were injected intravenously with an anti-human CD20 mAb (5 mg/kg) (rituximab (a type I anti-CD20 mAb) or obinutuzumab (a type II anti-CD20 mAb), B6 mice received the anti-mouse CD20 antibody 18B12. Neither mAb affected clinical disease or serum antibody levels. Obinutuzumab and rituxi-mab had an impact on splenic and CNS-infiltrated B cells with slightly differential depletion effi-cacy. Additionally, obinutuzumab had beneficial effects on spinal cord myelination. B cell depletion rates in the 18B12/B6 model were comparable with those observed in obinutuzumab-treated hCD20xhIgR3 mice. Our results demonstrate the usefulness of anti-CD20 mAbs for the modulation of B cell-driven peripheral immune response and CNS pathology, with type II antibodies potentially being superior to type I in the depletion of tissue-infiltrating B cells.
CRIS-Team Scopus Importer:2022-03-25
Keywords: B cells; CD20; Experimental autoimmune encephalomyelitis; Multiple sclerosis; Obinutuzumab; Rituximab

Efficacy of aflibercept (EYLEA®) on inhibition of human VEGF in vitro - Schicht, Martin; Hesse, Karen; Schröder, Henrik; Naschberger, Elisabeth; Lamprecht, W.; Garreis, Fabian; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2017)
Pathological formation of blood vessels plays a key role in the growth and metastasis of tumors and also in several serious ophthalmological diseases such as wet age-related macular degeneration (AMD) or diabetic retinopathy. In AMD treatment, aflibercept (tradename EYLEA®) is used to deactivate the underlying pathological neovascularisation. Aflibercept is a recombinant fusion protein which binds to vascular endothelial growth factor (VEGF) receptors, thereby inhibiting VEGF pathway activation. VEGF is one of the most important angiogenesis factors.This analysis investigates lasting efficacy of aflibercept in vitro for later application as therapeutic agent against macular degeneration (AMD).VEGF-ELISA assays were performed to investigate binding affinities at different aflibercept concentrations. The impact of VEGF on the proliferation of human umbilical vein endothelial cells (HUVEC) was investigated using proliferation assays. Moreover, time-dependent kinetic studies were performed to analyze different aflibercept storage durations with regard to its inhibitory capabilities on human VEGF.Our results reveal that aflibercept significantly lowers the amount of unbound VEGF as well as the proliferation rate of HUVEC. Moreover, in contrast to specifications given by the manufacturer, aflibercept retains its full inhibitory effect up to at least 120h after transference from the original vial into the injection syringe.
EVALuna2:15305

Electron Microscopic Features of Canalicular Concretions - Mohammad, Javed Ali; Heichel, Jens; Singh, Swati; Paulsen, Friedrich (Ophthalmic Plastic and Reconstructive Surgery, 2020)
PURPOSE: The aim of this study was to examine electron microscopic features of canalicular concretions obtained from patients with canaliculiths. METHODS: Canalicular concretions were obtained from 10 patients diagnosed as canaliculiths and were immediately fixed for ultrastructural analysis. Surface structure and transmission electron microscopical sections were studied. Multiple longitudinal and transverse ultrathin sections were obtained at different levels and all were studied using standard protocols of scanning electron microscopy and transmission electron microscopy. RESULTS: Three different types of canalicular concretions were noted; predominantly coccoid and bacilloid, predominantly filamentous, and mixed varieties. The surfaces and the cut sections showed typical and distinctive features for each of the concretion types. The filamentous subtypes were common accounting for 50% (5/10) of all canalicular concretions. The surface of predominantly filamentous concretions revealed typical honeycomb patterns, the walls and base of which were formed by definitive and peculiar arrangement of Actinomyces. Transmission electron microscopy confirmed the findings of scanning electron microscopy and demonstrated typical structural features of Actinomyces and some other bacteria undergoing binary fission. The most interesting feature was the lack of immune cells and blood products within the substance of canalicular concretions as compared with the mucopeptide concretions. CONCLUSIONS: Ultrastructural features of canalicular concretions reveal 3 distinct microbial subtypes and opens up avenues toward better understanding of the etiopathogenesis of canaliculiths and possible structural resistance to host defenses or antibiotics.
CRIS-Team Scopus Importer:2020-09-25

Electron microscopic features of the lacrimal sac mucopeptide concretions - Mohammad, Javed Ali; Schicht, Martin; Heichel, Jens; Nadimpalli, Siva Kumar; Paulsen, Friedrich (Graefes Archive For Clinical and Experimental Ophthalmology, 2018)
PURPOSE: The aim of this study was to examine the ultrastructural features of the mucopeptide concretions obtained from the lacrimal sac. METHODS: Mucopeptide concretions obtained from the lacrimal sacs of 10 patients during a dacryocystorhinostomy were immediately fixed for electron microscopic analysis. The surfaces were studied separately and longitudinal and transverse ultra-thin sections were obtained at different levels and all were studied using the standard protocols of scanning electron microscopy (SEM) and transmission electron microscopy (TEM). RESULTS: Mucopeptide concretions based on their extent take the shape of the lacrimal sac and nasolacrimal duct. The external surfaces and cut sections show mostly areas of homogenous deposits with occasional intervening heterogenic areas. Two distinct types of craters were noted, mostly in the heterogeneous areas. The core of the concretions was made up of extensive networks of fibril like tangles filled predominantly with granular material and red blood cells with occasional presence of granulocytes and epithelial cells. Numerous vacuoles and fissures appear to be more of artifacts than any metabolic process. No organic fibers of fungal filaments were noted within the concretions. There was no evidence of any bacterial biofilms other than few focal areas of scattered bacteria. Possible events in the development of mucopeptide concretions have been hypothesized based on the ultrastructural findings. CONCLUSION: Ultrastructural features of mucopeptide concretions from the lacrimal sac help in better understanding of their etiopathogenesis and tissue interactions. Further exploration of different stages of a concretion is needed to understand the potential factors that trigger its genesis and evolution.
EVALuna2:35315

Electrophysiological deficits in the retina of the DBA/2J mouse - Scholz, Michael; Kremers, Jan; et al. (Documenta Ophthalmologica, 2009)
The DBA/2J (D2J) is a genetic mouse model for glaucomatous neurodegeneration because the animals develop anatomical and functional retinal deficits that partially can be correlated with elevated intraocular pressure (IOP). The IOP starts to increase at an age of about 6 months as a result of morphological changes within the anterior eye segment, e.g., pigment dispersion and iris synechiae. The purpose of the present study was to investigate how ERG responses change in individuals at different ages in D2J mice and to compare these changes with normal aging effects in pigmented C57/B6 (B6) mice. IOP was measured in awake, non-sedated D2J and B6 mice with a rebound tonometer. At ages between 2-3 and 10 months, scotopic flash ERGs were measured five times with about 2 months' intervals. In addition, light adapted flicker ERGs were recorded. Our data show that the D2J shows lower flicker ERG responses than the B6 mice already at an age of 2-3 months. Dark adapted flash ERG responses are not decreased at this age. In both mouse strains the ERG responses decrease as a function of age, but there is a stronger decrease in the D2J mice. The data of flicker ERGs suggest the presence of early functional deficits in the D2J retina that possibly have a post-receptoral origin. The scotopic flash ERG reveals a functional deficit that occurs at a later stage and that possibly is IOP dependent. But, the deficits appear at an age at which the IOP is still lower than in the B6 mouse, indicating that other factors play an additional role. © 2009 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2009.med.AI.LAIPDL.electr
Keywords: DBA/2J mouse; Electroretinography; Flash ERG; Flicker ERG; Glaucoma; Intraocular pressure

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (30th Annual Conference of the European Society for Biomaterials, Dresden (Deutschland), 2019, 2019)

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas A. (16th Biennial - Bayreuther Polymer Symposium, 2019)

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (16th Bayreuther Polymer Symposium, Bayreuth (Deutschland), 2019., 2019)

Electrospun PCL-Collagen nanofiber membranes as substitute for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Nordic Polymer Days, Trondheim (Norwegen),, 2019)

Electrospun PCL-Collagen nanofiber membranes as substitute for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (The Association for Research in Vision and Ophthalmology (ARVO), 2019)

Embryological approach to the morphology of the ligamentum mucosum of the human knee joint - Gonera, B.; Borowski, A.; Zielinska, N.; Palac, W.; Paulsen, Friedrich; Olewnik, L. (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Purpose: The ligamentum mucosum is a ligamentous structure within the synovial layer of the knee joint capsule. It usually arises from the infrapatellar fat pad and is inserted into the intercondylar notch of the femur. In recent years, more attention has been paid to this structure because of its clinical significance. Despite the growing attention, the complex morphology of the ligamentum mucosum has led to many misunderstandings among the scientists and clinicians. Therefore, the main objective of this study was to characterize the morphology of the ligamentum mucosum and its attachment points, classify it, and evaluate its prevalence. Methods: Classical anatomical dissection was performed on 70 lower limbs of human fetuses fixed in 10% formalin solution. Morphology was carefully assessed, and morphometric measurements were performed. The types revealed were classified. Results: The ligamentum mucosum was present in 100% of all 70 specimens examined. Two types were detected. Type I (65.71%) - "cord-like". This type was the most common and is characterized by a single longitudinal ligament. The proximal attachment of the ligamentum mucosum was located in the middle of the infrapatellar fat, and the distal attachment was at the tip of the intercondylar notch. Type II (34.29%) - "vertical septum". This type is less common, but its morphology is much more complex compared to type I. It is wider and thicker than type I. Proximally, it is attached to the infrapatellar fat pad and distally through the entire intercondylar notch down to the anterior surface of the anterior cruciate ligament. It divides the joint cavity into medial and lateral sides. Conclusion: The ligamentum mucosum exhibits high morphologic variability, and the view that it is a vestigial remnant of the embryologic development of the knee should be reconsidered. We have proposed an anatomical classification of its types in human fetuses, which is a valuable addition to existing knowledge and will hopefully change the approach of clinicians and scientists.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Anatomical variations; Fetuses; Ligamentum mucosum; New classification

Encapsulation of hydrophobic drugs in shell-by- shell coated nanoparticles for radio—and chemotherapy—an in Vitro study - Klein, Stefanie; Luchs, Tobias; Leng, Andreas; Distel, Luitpold; Neuhuber, Winfried; Hirsch, Andreas (Bioengineering, 2020)
Our research objective was to develop novel drug delivery vehicles consisting of TiO2 and Al2O3 nanoparticles encapsulated by a bilayer shell that allows the reversible embedment of hydrophobic drugs. The first shell is formed by covalent binding of hydrophobic phosphonic acid at the metal oxide surface. The second shell composed of amphiphilic sodium dodecylbenzenesulfonate emerges by self-aggregation driven by hydrophobic interactions between the dodecylbenzene moiety and the hydrophobic first shell. The resulting double layer provides hydrophobic pockets suited for the intake of hydrophobic drugs. The nanoparticles were loaded with the anticancer drugs quercetin and 7-amino-4-methylcoumarin. Irradiation with X-rays was observed to release the potential anticancer drugs into the cytoplasm. In Michigan Cancer Foundation (MCF)-10 A cells, quercetin and 7-amino-4-methylcoumarin acted as antioxidants by protecting the non-tumorigenic cells from harmful radiation effects. In contrast, these agents increased the reactive oxygen species (ROS) formation in cancerous MCF-7 cells. Quercetin and 7-amino-4-methylcoumarin were shown to induce apoptosis via the mitochondrial pathway in cancer cells by determining an increase in TUNEL-positive cells and a decrease in mitochondrial membrane potential after irradiation. After X-ray irradiation, the survival fraction of MCF-7 cells with drug-loaded nanoparticles considerably decreased, which demonstrates the excellent performance of the double-layer stabilized nanoparticles as drug delivery vehicles.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Al; Chemotherapy; Drug delivery; Quercetin; Radiotherapy; Shell-by-shell nanoparticles; TiO

Enhancement of Outflow Facility in the Murine Eye by Targeting Selected Tight-Junctions of Schlemm's Canal Endothelia - Tam, Lawrence C. S.; Reina-Torres, Ester; Sherwood, Joseph M.; Cassidy, Paul S.; Crosbie, Darragh E.; Lütjen-Drecoll, Elke; Flügel-Koch, Cassandra; Perkumas, Kristin; Humphries, Marian M.; Kiang, Anna-Sophia; O'Callaghan, Jeffrey; Callanan, John J.; et al. (Scientific Reports, 2017)
The juxtacanalicular connective tissue of the trabecular meshwork together with inner wall endothelium of Schlemm's canal (SC) provide the bulk of resistance to aqueous outflow from the anterior chamber. Endothelial cells lining SC elaborate tight junctions (TJs), down-regulation of which may widen paracellular spaces between cells, allowing greater fluid outflow. We observed significant increase in paracellular permeability following siRNA-mediated suppression of TJ transcripts, claudin-11, zonula-occludens-1 (ZO-1) and tricellulin in human SC endothelial monolayers. In mice claudin-11 was not detected, but intracameral injection of siRNAs targeting ZO-1 and tricellulin increased outflow facility significantly. Structural qualitative and quantitative analysis of SC inner wall by transmission electron microscopy revealed significantly more open clefts between endothelial cells treated with targeting, as opposed to non-targeting siRNA. These data substantiate the concept that the continuity of SC endothelium is an important determinant of outflow resistance, and suggest that SC endothelial TJs represent a specific target for enhancement of aqueous movement through the conventional outflow system.
EVALuna2:35337

Enteric co-innervation of striated muscle in the esophagus: still enigmatic? - Neuhuber, Winfried; Wörl, Jürgen (Histochemistry and Cell Biology, 2016)
The existence of a distinct ganglionated myenteric plexus between the two layers of the striated tunica muscularis of the mammalian esophagus has represented an enigma for quite a while. Although an enteric co-innervation of vagally innervated motor endplates in the esophagus has been suggested repeatedly, it was not possible until recently to demonstrate this dual innervation. Twenty-two years ago, we were able to demonstrate that motor endplates in the rat esophagus receive dual innervation from both vagal nerve fibers originating in the brain stem and from varicose enteric nerve fibers originating in the myenteric plexus. Meanwhile, a considerable amount of data has been gathered on enteric co-innervation and its occurrence in the esophagus of a variety of species including humans, its neurochemistry, spatial relationships on motor endplates, ontogeny and possible functional roles. These data underline the significance of this newly discovered innervation component, although its function in vivo is still largely unknown. The aim of this review, which is an update of our previous paper (Worl and Neuhuber in Histochem Cell Biol 123(2):117-130. doi:10.1007/s00418-005-0764-7, 2005a), is to summarize the current knowledge about enteric co-innervation of esophageal striated muscle and to provide some hints as to its functional significance.
EVALuna2:184248

Enteroglial cells act as antigen-presenting cells in chagasic megacolon - Da Silveira, Alexandre B.M.; De Oliveira, Enio; Neto, Salustiano D.; Luquetti, Alejandro O.; Fujiwara, Ricardo T.; Oliveira, Rodrigo C.; Brehmer, Axel (Human Pathology, 2011)
Chagas disease is one of the most serious parasitic diseases of Latin America, with a social and economic impact far outweighing the combined effects of other parasitic diseases such as malaria, leishmaniasis, and schistosomiasis. In the chronic phase of this disease, the destruction of enteric nervous system components leads to megacolon development. Besides neurons, the enteric nervous system is constituted by enteric glial cells, representing an extensive but relatively poorly described population within the gastrointestinal tract. Several lines of evidence suggest that enteric glial cells represent an equivalent of central nervous system astrocytes. Previous data suggest that enteric glia and neurons are active in the enteric nervous system during intestinal inflammatory and immune responses. To evaluate whether these cells act as antigen-presenting cells, we investigated the expression of molecules responsible for activation of T cells, such as HLA-DR complex class II and costimulatory molecules (CD80 and CD86), by neurons and enteric glial cells. Our results indicate that only enteric glial cells of chagasic patients with megacolon express HLA-DR complex class II and costimulatory molecules, and hence they present the attributes necessary to act as antigen-presenting cells. © 2011 Elsevier Inc. All rights reserved.
Keywords: CD80; CD86; Chagas disease; Chagasic megacolon; HLA-DR complex class II

Entheseal Biopsy Approach: An Ultrasound-guided Method for Retrieval of Entheseal Tissue from Psoriatic Arthritis Patients - Raimondo, Maria Gabriella; Pachowsky, Milena; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Vogg, Mario; Saad, Mina saad aziz; Simon, David; Rech, Jürgen; Soare, Alina; Bräuer, Lars; et al. (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

Enzymes of urea synthesis are expressed at the ocular surface, and decreased urea in the tear fluid is associated with dry-eye syndrome - Jaeger, Kristin; Kielstein, Heike; Dunse, Matthias; Nass, Norbert; Paulsen, Friedrich; Sel, Saadettin (Graefes Archive For Clinical and Experimental Ophthalmology, 2013)
Purpose: The present study aims at determining whether enzymes of urea synthesis are expressed in the human lacrimal gland and in tissues of ocular surface (conjunctiva, cornea), to give evidence for the hypothesis that urea can be locally formed from ocular tissues and is important for the composition of the tear fluid. Methods: The presences of enzymes (arginase 1, 2 and agmatinase) that directly contribute to the formation of urea were investigated in the lacrimal gland and tissues of ocular surface by RT-PCR and immunohistochemistry. We collected tear fluid, aqueous humour, and blood samples from a total of 38 subjects, and tear fluid samples from a total of 78 subjects, with and without dry-eye syndrome (DES, keratoconjunctivitis sicca), and determined the urea concentration. Results: The enzymes arginase 1, 2 and agmatinase were expressed in all tissues examined except for arginase 1, which was not expressed in the cornea. There was no correlation of urea concentration in tear fluid with aqueous humour and blood plasma (r = 0.13, p = 0.58 and r = 0.45, p = 0.05 respectively). However, correlation of urea concentration between aqueous humour and blood plasma was highly significant (r = 0.7, p = 0.0001). The concentration of urea in the tear fluid of patients with DES compared to healthy control group was significantly reduced (p < 0.0001). Conclusion: Enzymes that are directly involved in the formation of urea are expressed in ocular tissues. This may imply that in the ocular surface is a well-coordinated system of enzymes that can produce urea which might be independent of external urea supply. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Agmatinase; Arginase 1 and 2; Dry eye syndrome; Meibomian gland disease; Urea

Epithelial cell types and their proposed roles in maintaining the mucosal barrier in human chagasic-megacolonic mucosa - Koch, Christian; Da Silveira, Alexandre B. M.; De Oliveira, Enio C.; Quint, Karl; Neuhuber, Winfried; Brehmer, Axel; Jabari, Samir (Histochemistry and Cell Biology, 2017)
Patients suffering from chagasic megacolon must have an intact mucosal barrier as they survive this chronic disease for decades. A key structure of the mucosal barrier are epithelial cells. Vasoactive-intestinal-peptide (VIP)-positive nerve fibres are involved in influencing, e.g., epithelial cell proliferation, mucus secretion (e.g., mucin 2 and trefoil factor 3 of goblet cells) and inflammation or autoimmunity, all putative and/or known factors altered in chagasic megacolon. We analyzed qualitatively and quantitatively goblet cells, their specific markers, such as mucin 2 (MUC2) and trefoil factor 3 (TFF3) and enterocytes, the relation of VIP-immunoreactive nerve fibres to the epithelia, the distribution of gelsolin, a protein involved in chronic inflammation processes in the epithelia, and the proliferation rate of epithelial cells by combined 4',6-diamidino-2-phenylindole (DAPI) and phosphohistone-H3 (PHH3) staining. Goblet cells were the dominating epithelial cell type. They accounted for 38.4% of all epithelial cells in controls and changed to 58.9% in the megacolonic parts. In contrast to the overall expression in goblet cells of control epithelia, TFF3 was confined to goblet cells at the base of the crypts whereas MUC2 was found only in luminal goblet cells. Gelsolin-positive goblet cells were predominantly recognized within the controls. Finally, the mean value of mitosis increased from 1.5% within the controls up to 2.6% in the anal parts of the chagasic sepcimens. Taken together, increased cell proliferation, preponderance of goblet cells, differential MUC 2, and TFF 3 expression might all be factors maintaining an intact mucosal barrier within chagasic megacolon.
EVALuna2:35224

Epithelial-mesenchymal transition in the lacrimal gland morphogenesis, damage and repair - Singh, Swati; Brabletz, Simone; Arnold, Philipp; Schicht, Martin; Paulsen, Friedrich (Ocular Surface, 2023)
Epithelial-mesenchymal transition (EMT) constitutes an important pathway in organ fibrosis seen in the lungs, liver, eye, and salivary glands. This review summarizes the EMT observed within the lacrimal gland during its development, tissue damage and repair along with possible translational implications. Existing animal and human studies have reported the increased expression of EMT regulators i.e., transcription factors like Snail, TGF-β1 within the lacrimal glands, and a possible role of reactive oxygen species, which might be initiating the cascade of EMT. In these studies, EMT is typically detected by reduced E-cadherin expression in the epithelial cells and increased Vimentin and Snail expression within the lacrimal glands' myoepithelial or ductal epithelial cells. Other than specific markers, electron microscopic evidence of disrupted basal lamina, increased collagen deposition, reorganised cytoskeleton of myoepithelial cells also indicated EMT. Very few studies have shown myoepithelial cells to be the cells transitioning into mesenchymal cells with increased extracellular matrix deposition within the lacrimal glands. EMT in animal models seemed reversible as glands got repaired after damage with IL-1α injection or duct ligation and transiently used the EMT as a means for tissue repair. The EMT cells also expressed nestin, a marker for progenitor cells in a rabbit duct ligation model. However, lacrimal glands of ocular graft versus host disease and IgG4 dacryoadenitis demonstrate irreversible acinar atrophy along with signs of EMT-fibrosis, reduced E-cadherin, and increased Vimentin and Snail expression. Future studies exploring the molecular mechanisms of EMT and thereby developing targeted therapies capable of transforming the mesenchymal cells into epithelial cells or blocking the EMT might help in the restoration of the lacrimal gland function.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Dry eye disease; EMT; Epithelial-mesenchymal transition; Lacrimal gland; Ocular surface; Tear film

Epithelial-mesenchymal transition of the retinal pigment epithelium causes choriocapillaris atrophy - Ohlmann, Andreas; Scholz, Michael; Koch, Marcus; Tamm, Ernst R. (Histochemistry and Cell Biology, 2016)
Epithelial-to-mesenchymal transition (EMT) of the retinal pigment epithelium (RPE) is commonly observed at sites of choroidal neovascularization in patients suffering from age-related macular degeneration. To learn in an experimental model how RPE EMT affects the biology of the choroidal vasculature, we studied transgenic mice (βB1-TGF-β1) with ocular overexpression of transforming growth factor-β1 (TGF-β1). RPE EMT was detectable at postnatal day (P)1 and included marked structural and functional alterations such as loss of the outer blood-retina barrier and reduced mRNA expression of the RPE-characteristic molecules Rlbp1, Rpe65, Rbp1 and Vegfa. Moreover, vascular endothelial growth factor (VEGF) was not detectable by immunohistochemistry at the RPE/choroid interface, while RPE cells stained intensely for α-smooth muscle actin. The choriocapillaris, the characteristic choroidal capillary network adjacent to the RPE, developed normally and was not obviously changed in embryonic transgenic eyes but was absent at P1 indicating its atrophy. At around the same time, photoreceptors stopped to differentiate and photoreceptor apoptosis was abundant in the second week of life. Structural changes were also seen in the retinal vasculature of transgenic animals, which did not form intraretinal vessels, and the hyaloid vasculature, which did not regress. In addition, the amounts of retinal HIF-1α and its mRNA were markedly reduced. We conclude that high amounts of active TGF-β1 in the mouse eye cause transdifferentiation of the RPE to a mesenchymal phenotype. The loss of epithelial differentiation leads to the diminished synthesis of RPE-characteristic molecules including that of VEGF. Lack of RPE-derived VEGF causes atrophy of the choriocapillaris, a scenario that disrupts photoreceptor differentiation and finally results in photoreceptor apoptosis. Lack of retinal vessel formation and of hyaloid vessel regression might be caused by the decrease in the metabolic requirements of the neuroretina leading to low amounts of retinal HIF-1α. In summary, our data indicate that failure of RPE differentiation may well precede and cause atrophy of the choriocapillaris. In contrast, RPE EMT is not sufficient to cause choroidal neovascularization.
EVALuna2:35344

Epithelial X-Box Binding Protein 1 Coordinates Tumor Protein p53-Driven DNA Damage Responses and Suppression of Intestinal Carcinogenesis - Welz, Lina; Kakavand, Nassim; Hang, Xiang; Laue, Georg; Ito, Go; Silva, Miguel Gomes; Plattner, Christina; Mishra, Neha; Tengen, Felicitas; Ogris, Christoph; Jesinghaus, Moritz; Wottawa, Felix; et al. (Gastroenterology, 2022)
BACKGROUND & AIMS: Throughout life, the intestinal epithelium undergoes constant self-renewal from intestinal stem cells. Together with genotoxic stressors and failing DNA repair, this self-renewal causes susceptibility toward malignant transformation. X-box binding protein 1 (XBP1) is a stress sensor involved in the unfolded protein response (UPR). We hypothesized that XBP1 acts as a signaling hub to regulate epithelial DNA damage responses. METHODS: Data from The Cancer Genome Atlas were analyzed for association of XBP1 with colorectal cancer (CRC) survival and molecular interactions between XBP1 and p53 pathway activity. The role of XBP1 in orchestrating p53-driven DNA damage response was tested in vitro in mouse models of chronic intestinal epithelial cell (IEC) DNA damage (Xbp1/H2b(fl/fl), Xbp1(Delta IEC), H2b(Delta IEC), H2b/Xbp1(Delta IEC)) and via orthotopic tumor organoid transplantation. Transcriptome analysis of intestinal organoids was performed to identify molecular targets of Xbp1-mediated DNA damage response. RESULTS: In The Cancer Genome Atlas data set of CRC, low XBP1 expression was significantly associated with poor overall survival and reduced p53 pathway activity. In vivo, H2b/Xbp1(Delta IEC) mice developed spontaneous intestinal carcinomas. Orthotopic tumor organoid transplantation revealed a metastatic potential of H2b/Xbp1(Delta IEC)-derived tumors. RNA sequencing of intestinal organoids (H2b/Xbp1(fl/fl), H2b(Delta IEC), H2b/Xbp1(Delta IEC), and H2b/p53(Delta IEC)) identified a transcriptional pro-gram downstream of p53, in which XBP1 directs DNA-damage-inducible transcript 4-like (Ddit4l) expression. DDIT4L inhibits mechanistic target of rapamycin-mediated phosphorylation of 4E-binding protein 1. Pharmacologic mechanistic target of rapamycin inhibition suppressed epithelial hyperproliferation via 4E-binding protein 1. CONCLUSIONS: Our data suggest a crucial role for XBP1 in coordinating epithelial DNA damage responses and stem cell function via a p53-DDIT4L-dependent feedback mechanism.
CRIS-Team WoS Importer:2021-12-31

Ergebnisse der Sicca-Forschungsförderung 2016 - Musayeva, A; Gericke, A; Jäger, Franziska; Paulsen, Friedrich; Braun, M; Fabry, Ben; Braun, R; Pauly, Diana; Holtmann, C; Geerling, Gerd; Goldblum, David; Horwath-Winter, Jutta; et al. (Ophthalmologe, 2020)
The Sicca-Förderpreis (Dry Eye Award) supports the development of scientific research on the pathogenesis, diagnostics, and treatment of dry eye and ocular surface diseases. It is awarded after a limited call for proposals in German-speaking countries, written application and selection of the award winner after evaluation by a jury of ophthalmologists working in basic and clinical science. In this article examples of the results of funded projects of the Sicca-Förderpreis 2016 are cursorily described, which were presented at the Ophthalmological Academy of Germany 2019 (Augenärztliche Akademie Deutschland 2019) and therefore provide an insight into current scientific developments. The role of muscarinic receptors and those of urea in the pathogenesis of dry eye as well as the (missing) correlation of tear film stability, viscosity and surface tension are highlighted. A project on the early detection of ocular involvement in graft versus host disease and the idea of treating meibomian gland dysfunction with eyelid surgery techniques are also groundbreaking. The outlined projects represent the potential for further substantial developments in the understanding, diagnostics and treatment of dry eye; however, their long-term clinical relevance still needs to be established.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Eyelid tension; Graft versus host disease; Muscarinic receptor; Tear film stability; Urea

Erratum to: Flat midsubstance of the anterior cruciate ligament with tibial "C"-shaped insertion site - Siebold, Rainer; Schuhmacher, Peter; Fernandez, Francis; Smigielski, Robert; Fink, Christian; Brehmer, Axel; Kirsch, Joachim (Knee Surgery Sports Traumatology Arthroscopy, 2014)

Estimates and determinants of sars-cov-2 seroprevalence and infection fatality ratio using latent class analysis: The population-based tirschenreuth study in the hardest-hit german county in spring 2020 - Wagner, Ralf; Peterhoff, David; Beileke, Stephanie; Günther, Felix; Berr, Melanie; Einhauser, Sebastian; Schütz, Anja; Niller, Hans Helmut; Steininger, Philipp; Knöll, Antje; Tenbusch, Matthias; Maier, Clara; et al. (Viruses, 2021)
SARS-CoV-2 infection fatality ratios (IFR) remain controversially discussed with implications for political measures. The German county of Tirschenreuth suffered a severe SARS-CoV-2 outbreak in spring 2020, with particularly high case fatality ratio (CFR). To estimate seroprevalence, underreported infections, and IFR for the Tirschenreuth population aged ≥14 years in June/July 2020, we conducted a population-based study including home visits for the elderly, and analyzed 4203 participants for SARS-CoV-2 antibodies via three antibody tests. Latent class analysis yielded 8.6% standardized county-wide seroprevalence, a factor of underreported infections of 5.0, and 2.5% overall IFR. Seroprevalence was two-fold higher among medical workers and one third among current smokers with similar proportions of registered infections. While seroprevalence did not show an age-trend, the factor of underreported infections was 12.2 in the young versus 1.7 for ≥85-year-old. Age-specific IFRs were <0.5% below 60 years of age, 1.0% for age 60–69, and 13.2% for age 70+. Senior care homes accounted for 45% of COVID-19-related deaths, reflected by an IFR of 7.5% among individuals aged 70+ and an overall IFR of 1.4% when excluding senior care home residents from our computation. Our data underscore senior care home infections as key determinant of IFR additionally to age, insufficient targeted testing in the young, and the need for further investigations on behavioral or molecular causes of the fewer infections among current smokers.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Antibodies; CLIA; ELISA; Infection fatality ratio; Latent class analysis; SARS-CoV-2; Senior care homes; Seroprevalence; Smoking; Underreported infections

Estimation of age at onset of linear enamel hypoplasia. New calculation tool, description and comparison of current methods - Dabrowski, Pawel; Kulus, Michal Jerzy; Furmanek, Miroslaw; Paulsen, Friedrich; Grzelak, Joanna; Domagala, Zygmunt (Journal of Anatomy, 2021)
Enamel Hypoplasia (EH) is known to be a useful indicator for wide range of detrimental factors in early childhood in past populations, such as nutritional disturbances, mechanical trauma, disease, metabolic, and/or genetic disorders. EH may be divided into three categories: pits, grooves, and lines, where the last two are referred to as “Linear Enamel Hypoplasia” (LEH). The regularity of enamel formation allows retrospective determination of the age of LEH formation. The current article reviews and compares the best-known methods used to estimate age at LEH formation and provides a new computational tool. Growth curves for canines and incisors were developed based on tooth growth tables by previous authors. Optimal models were selected using the Akaike Information Criterion. A Microsoft Excel spreadsheet was created to calculate age at LEH formation using the most common methods. All method results were compared with an archaeological sample (44 teeth of 18 individuals from an early modern cemetery from Wrocław, Poland) and a theoretical model. The results of the methods were compared pairwise with Bland-Altman plots. The current article provides a quick and easy-to-use tool for analyzing LEH chronology and comparing the results of different methods. As shown by the Bland-Altman plots, most methods provide approximately consistent results for LEHs formed at around 2–3 years of age. However, LEHs formed particularly early or late are more prone to discrepancies between different methods. Comparison of the age at LEH formation obtained by different methods should be done carefully - and the new LEH calculation tool with optimized equations provided in this publication can facilitate this process.
CRIS-Team Scopus Importer:2021-06-11
Keywords: enamel hypoplasia; mathematical modeling; physiological stress

Etiopathogenesis of lacrimal sac mucopeptide concretions: insights from cinematic rendering techniques - Mohammad, Javed Ali; Scholz, Michael; Singh, Swati; Heichel, Jens; Paulsen, Friedrich (Graefes Archive For Clinical and Experimental Ophthalmology, 2020)
Background/aim: To investigate the structural features following the cinematic rendering of lacrimal sac mucopeptide concretions (MPC). Methods: The study was performed on five mucopeptide concretions obtained from the lacrimal sac during dacryocystorhinostomy. All the concretions were imaged using special protocols of CT scans to obtain ultra-thin slices. Cinematic rendering (CR) techniques (Siemens Healthineers AG, Erlangen, Germany) were utilized to allow real-time computation of the interaction of photons and scanned patient images using the Monte Carlo path tracing algorithms. The CR algorithms facilitated volumetric reconstruction of the mucopeptide concretions to visualize the texture and inner structures. Each concretion could be sliced and viewed at 100-μm intervals. False color display and the use of different transfer functions were utilized to display variable densities of the concretions in color during visualization. Images obtained by virtual camera were further analysed to assess the structural features. Results: The 3D cinematic rendered images of MPC showed uniform structural consistency on the surface and minimal heterogeneity from the surface up to the core. As the image slicing occurs towards the core, a well-defined structure of grossly different consistency (nidus) from the rest of the MPC was noted. This area was usually located in the paracentral region and constitutes approximately < 10% of the entire area. If a color display was assigned to the internal structure of the MPC, most of it appears to be compact and dense but the density reduces in the periphery of the nidus and delineates it well. Further structural enhancements with the 3D cinematic rendering in some MPCs demonstrate occasional 1–2 more areas with similar features as that of nidus. Conclusions: 3D CR is a useful modality to study the internal structure of MPC. The CR findings also provide further evidence to support the earlier etiopathogenesis theory based on ultrastructural and immunohistochemistry features.
CRIS-Team Scopus Importer:2020-06-26
Keywords: 3D; Concretion; Dacryolith; Lacrimal; Lacrimal sac; Mucopeptide

Etiopathogenesis of Primary Acquired Nasolacrimal Duct Obstruction: What We Know and What We Need to Know - Mohammad, Javed Ali; Paulsen, Friedrich (Ophthalmic Plastic and Reconstructive Surgery, 2019)
PURPOSE: To provide a systematic review of the literature on the etiopathogenesis of primary acquired nasolacrimal duct obstruction (PANDO). METHODS: The authors performed a PubMed search of all articles published in English with specific reference to etiopathogenesis of PANDO or associations of PANDO. Data captured include demographics, study techniques, hypothesis, presumed or confirmed interpretations with regards to pathogenesis, mechanisms, or pathways. Specific emphasis was laid on addressing the lacunae and potential directions for future research. RESULTS: Numerous factors are believed to contribute to the etiopathogenesis of PANDO. The basic pathogenesis involves inflammation, vascular congestion, mucosal edema, fibrosis, obstruction, and stasis. Bony nasolacrimal duct diameter does not appear to play a significant role. There is no convincing data to substantiate nose as the site of disease origin and nasal factors appear to be comorbidities. Hormonal mechanisms are more evidence-based but can only partly explain the pathogenesis. Vascular theories are based on the behavior of perilacrimal cavernous bodies, their autonomic control, and additional structural changes in the helical patterns of connective tissue fiber arrangements. Repeated vascular malfunction leading to structural epithelial and subepithelial changes currently appears to be the most evidence-based and accepted theory. Tear proteomics holds a promise in decoding the etiopathogenesis of PANDO, at least in part. CONCLUSIONS: The etiopathogenesis of PANDO appears to be multifactorial. Hormonal microenvironments, vascular factors, and tear proteomics are promising candidates for further work. There is a need for focused work by Clinician-Scientists and the answers can have far reaching clinical implications.
CRIS-Team Scopus Importer:2019-09-17

Evaluation of a 345 nm Femtosecond Laser for Corneal Surgery with Respect to Intraocular Radiation Hazard - Menzel-Severing, Johannes; Petsch, Corinna; Tourtas, Theofilos; Polisetti, Naresh; Klenke, Joerg; Skerl, Katrin; Wuellner, Christian; Donitzky, Christof; Kruse, Friedrich; Kremers, Jan; Hammer, Christian (PLoS ONE, 2015)
We report our findings from a preclinical safety study designed to assess potential side effects of corneal ultraviolet femtosecond laser treatment on lens and retina.Refractive lenticules (-5 dpt) with a diameter of 6 mm were created in the right cornea of eight Dutch Belted rabbits. Radiant exposure was 0.5 J/cm² in two animals and 18 J/cm² in six animals. The presence of lens opacities was assessed prior to and up to six months following laser application using Scheimpflug images (Pentacam, Oculus) and backscatter analysis (Opacity Lensmeter 702, Interzeag). Ganzfeld flash and flicker electroretinogram (ERG) recordings were obtained from both eyes prior to and up to six weeks following laser application. At the study endpoint, retinas were examined by light microscopy.Independent of energy dose applied, no cataract formation could be observed clinically or with either of the two objective methods used. No changes in ERG recordings over time and no difference between treated and untreated eye were detected. Histologically, retinal morphology was preserved and retinal pigment epithelium as well as photoreceptor inner and outer segments appeared undamaged. Quantitative digital image analysis did not reveal cell loss in inner or outer nuclear layers.Our analysis confirms theoretical considerations suggesting that ultraviolet femtosecond laser treatment of the cornea is safe for intraocular tissues. Transmitted light including stray light induces no photochemical effects in lens or retina at energy levels much higher than required for the clinical purpose. These conclusions cannot be applied to eyes with pre-existing retinal damage, as these may be more vulnerable to light.
EVALuna2:4434

Evaluation of angiogenesis of bioactive glass in the arteriovenous loop model - Arkudas, Andreas; Balzer, Amelie; Bührer, Gregor; Arnold, Isabel; Hoppe, Alexander; Detsch, Rainer; Newby, Phillipa; Fey, Tobias; Greil, Peter; Horch, Raymund E.; Boccaccini, Aldo R.; Kneser, Ulrich (Tissue Engineering - Part C: Methods, 2013)
In this study, the angiogenetic effect of sintered 45S5 Bioglass (R) was quantitatively assessed for the first time in the arteriovenous loop (AVL) model. An AVL was created by interposition of a venous graft from the contralateral side between the femoral artery and vein in the medial thigh of eight rats. The loop was placed in a Teflon isolation chamber and was embedded in a sintered 45S5 Bioglass (R) granula matrix filled with fibrin gel. Specimens were investigated 3 weeks postoperatively by means of microcomputed tomography, histological, and morphometrical techniques. All animals tolerated the operations well. At 3 weeks, both microcomputed tomography and histology demonstrated a dense network of newly formed vessels originating from the AVL. All constructs were filled with cell-rich, highly vascularized connective tissue around the vascular axis. Analysis of vessel diameter revealed constant small vessel diameters, indicating immature new vessel sprouts. This study shows for the first time axial vascularization of a sintered 45S5 Bioglass (R) granula matrix. After 3 weeks, the newly generated vascular network already interfused most parts of the scaffolds and showed signs of immaturity. The intrinsic type of vascularization allows transplantation of the entire construct using the AVL pedicle.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.evalua

Evaluation of central corneal thickness after cataract surgery, penetrating keratoplasty and long-term soft contact lens wear - Sel, Saadettin; Trau, Stefanie; Knak, Matthias; Kalinski, Thomas; Kaiser, Delia; Kruse, Friedrich; Huchzermeyer, Cord; Duncker, Gernot I. W.; Paulsen, Friedrich; Auffarth, Gerd U.; Nass, Norbert (Contact Lens and Anterior Eye, 2013)
The aim of this study was to compare central corneal thickness (CCT) between corneas of normal healthy eyes (cNHE), corneas of eyes that had undergone cataract surgery by clear corneal phacoemulsification with implantation of an intracapsular intraocular lens (cIOL), corneal grafts after penetrating keratoplasty (gPK) and corneas of long-term soft contact lens wearers (cCL).The study design was a consecutive cross-sectional trial. CCT was measured using rotating Scheimpflug camera (Pentacam, software version 1.16r04) in 80 cNHE, 79 cIOL, 46 gPK and 78 cCL. Analysis of variance (one-way ANOVA) was performed to compare differences of mean values between these four groups. Pearson's or Spearman's correlation coefficient (r) was determined between CCT value and age, follow up time after penetrating keratoplasty (timePK) or contact lens wearing time (timeCL).Means of CCT measurements were comparable between cNHE (mean CCT±standard deviation, 554±36?m), cIOL (551±40?m) and gPK (534±52?m) as determined by one-way ANOVA. Mean CCT values in cCL (537±37?m) were statistically significantly lower in comparison to cNHE (p=0.026, 95% CI=1.43-31.44). There was no linear correlation between age and CCT values of cNHE and cIOL (p=0.841, r=-0.031 and p=0.931, r=0.011, respectively). No linear relationship was determined between CCT values of cCL and timeCL (p=0.315, r=-0.125). CCT values of gPK did not correlate with timePK (p=0.738, r=0.054).The data reported here indicate that in the same statistical model among CCT values of cNHE, cIOL and gPK only long-term soft contact lenses (CL) wearer have significantly lower CCT measurements.
EVALuna2:4398

Evaluation of intraocular pressure elevation after multiple injections of intravitreal ranibizumab - Yu, Alice L.; Seidensticker, Florian; Schaumberger, Markus; Welge-Lüssen, Ulrich-Christoph; Wolf, Armin (Clinical Ophthalmology, 2014)
We wanted to determine whether multiple injections of intravitreal ranibizumab was associated with an elevated intraocular pressure (IOP) in patients treated for neovascular age-related macular degeneration (AMD).This retrospective study examined 53 patients with neovascular AMD treated with multiple injections of intravitreal ranibizumab. The main outcome measure was the difference in IOP between the frequently-treated study eyes (>=15 injections) and the unfrequently-treated fellow control eyes (<= five injections). Patients were divided into three study groups: group I (35 patients with 15 to 19 injections); group II (15 patients with 20 to 29 injections); and group III (three patients with >=30 injections). The IOP was measured by Goldmann applanation tonometry 4 weeks after the last injection of intravitreal ranibizumab. For statistical analysis, the IOP was then correlated with the number of ranibizumab injections.Among the frequently-treated study eyes, the mean IOP was 13.68±2.91 mmHg (range, 8 to 20 mmHg). The unfrequently-treated fellow control eyes had a mean IOP of 13.45±3.09 mmHg (range, 9 to 25 mmHg). There was no significant correlation of the IOP difference between the study and control eyes with the number of ranibizumab injections (correlation coefficient 0.77; P=0.583). For each of groups I, II, and III, the difference in mean IOP between the study and control eyes was nonsignificant (P>0.05). There was also no significant association of the IOP difference between the study and control eyes with the number of ranibizumab injections for each group (P=0.391).Our study did not find an increased IOP in frequently-ranibizumab-treated eyes when compared to unfrequently-treated fellow control eyes. Further studies with a greater sample size are needed to evaluate whether an increased number of ranibizumab injections is associated with IOP changes.
EVALuna2:21197

Evaluation of surfactant proteins A, B, C, and D in articular cartilage, synovial membrane and synovial fluid of healthy as well as patients with osteoarthritis and rheumatoid arthritis - Hartjen, Nadine; Bräuer, Lars; Reiss, Beate; Claassen, Horst; Beileke, Stephanie; Garreis, Fabian; Hoogeboom, Sebastian; Tsokos, Michael; Etzold, Saskia; Mueller-Hilke, Brigitte; Gelse, Kolja; Mueller, Thomas; et al. (PLoS ONE, 2018)
OBJECTIVE: Surfactant Proteins (SPs) are well known from lung and form, along with phospholipids, a surface-active-layer at the liquid-air-interface of the alveolar lining. They play a major protective role by lowering surface tension, activating innate and adaptive immune defense at the lung mucosal interface, especially during infection. We analyzed the regulation of SPs in human and mouse articular chondrocytes, synoviocytes, and synovial fluid under healthy and inflammatory conditions, as well as in tissues of patients suffering from osteoarthritis and rheumatoid arthritis. METHODS: Immunohistochemistry, RT-PCR, qRT-PCR, ELISA, Western blotting were performed in cell cultures and tissue samples to determine localization, regulation, and concentration of SPs. RESULTS: All four SPs, were expressed by healthy human and mouse articular chondrocytes and synoviocytes and were also present in synovial fluid. Treatment with inflammatory mediators like IL-1β and TNF-α led to short-term upregulation of individual SPs in vitro. In tissues from patients with osteoarthritis and rheumatoid arthritis, protein levels of all four SPs increased significantly compared to the controls used. CONCLUSION: These results show the distribution and amount of SPs in tissues of articular joints. They are produced by chondrocytes and synoviocytes and occur in measurable amounts in synovial fluid. All four SPs seem to be differently regulated under pathologic conditions. Their physiological functions in lowering surface tension and immune defense need further elucidation and make them potential candidates for therapeutic intervention.
EVALuna2:35305

Evolutionary conserved networks of human height identify multiple Mendelian causes of short stature - Hauer, Nadine; Popp, Bernt; Taher, Leila; Vogl, Carina; Dhandapany, Perundurai S.; Büttner, Christian; Uebe, Steffen; Sticht, Heinrich; Ferrazzi, Fulvia; Ekici, Arif Bülent; De Luca, Alessandro; Klinger, Patricia; et al. (European journal of human genetics, 2019)
Height is a heritable and highly heterogeneous trait. Short stature affects 3% of the population and in most cases is genetic in origin. After excluding known causes, 67% of affected individuals remain without diagnosis. To identify novel candidate genes for short stature, we performed exome sequencing in 254 unrelated families with short stature of unknown cause and identified variants in 63 candidate genes in 92 (36%) independent families. Based on systematic characterization of variants and functional analysis including expression in chondrocytes, we classified 13 genes as strong candidates. Whereas variants in at least two families were detected for all 13 candidates, two genes had variants in 6 (UBR4) and 8 (LAMA5) families, respectively. To facilitate their characterization, we established a clustered network of 1025 known growth and short stature genes, which yielded 29 significantly enriched clusters, including skeletal system development, appendage development, metabolic processes, and ciliopathy. Eleven of the candidate genes mapped to 21 of these clusters, including CPZ, EDEM3, FBRS, IFT81, KCND1, PLXNA3, RASA3, SLC7A8, UBR4, USP45, and ZFHX3. Fifty additional growth-related candidates we identified await confirmation in other affected families. Our study identifies Mendelian forms of growth retardation as an important component of idiopathic short stature.
CRIS-Team Scopus Importer:2019-05-24

Examining the role of the surfactant family member SFTA3 in interneuron specification - Chen, Christopher Y.; Anderson, Nickesha C.; Becker, Sandy; Schicht, Martin; Stoddard, Christopher; Bräuer, Lars; Paulsen, Friedrich; Grabel, Laura (PLoS ONE, 2018)
The transcription factor NKX2.1, expressed at high levels in the medial ganglionic eminence (MGE), is a master regulator of cortical interneuron progenitor development. To identify gene candidates with expression profiles similar to NKX2.1, previous transcriptome analysis of human embryonic stem cell (hESC)-derived MGE-like progenitors revealed SFTA3 as the strongest candidate. Quantitative real-time PCR analysis of hESC-derived NKX2.1-positive progenitors and transcriptome data available from the Allen Institute for Brain Science revealed comparable expression patterns for NKX2.1 and SFTA3 during interneuron differentiation in vitro and demonstrated high SFTA3 expression in the human MGE. Although SFTA3 has been well studied in the lung, the possible role of this surfactant protein in the MGE during embryonic development remains unexamined. To determine if SFTA3 plays a role in MGE specification, SFTA3-/- and NKX2.1 -/- hESC lines were generated using custom designed CRISPRs. We show that NKX2.1 KOs have a significantly diminished capacity to differentiate into MGE interneuron subtypes. SFTA3 KOs also demonstrated a somewhat reduced ability to differentiate down the MGE-like lineage, although not as severe relative to NKX2.1 deficiency. These results suggest NKX2.1 and SFTA3 are co-regulated genes, and that deletion of SFTA3 does not lead to a major change in the specification of MGE derivatives.
EVALuna2:35300

Exercise Dependent Changes in Periosteal Femur Perfusion - Schroeter, S.; Rueter, L.; Heiß, Rafael; Hammer, Christian; Lutter, C.; Hoppe, M. W.; Grim, C.; Engelhardt, M.; Hotfiel, T. (Sport-Orthopädie, Sport-Traumatologie, 2022)
Background: Contrast-enhanced ultrasound (CEUS) has been shown to be a valid measurement tool for evaluating microvascular blood flow. Until now, the assessment of periosteal tissue has been insufficiently validated, and a procedure has not yet been standardized for this purpose. The aim of the present study was to investigate periosteal femur perfusion in the context of cycling exercise by means of CEUS and to evaluate the feasibility and reliability of this method. Material and Methods: Seventeen healthy athletes were recruited as study participants for the evaluation of periosteal femur perfusion (FP) and vastus intermedius muscle (VI) by CEUS (bolus dosage of 2.7 ml contrast agent, Sonovue, Bracco, Italy). Data were acquired from participants under resting conditions (T0) and immediately after standardized cycling exercise (T1, 20 min, 70% of maximum capacity). Peak enhancement (PE), the wash-in rate (WiR), the wash-in area under the curve (WiAUC), and the wash-in perfusion index (WiPI) were determined by software-based mapping quantification (Vuebox, Bracco, Italy). Intra- and interrater reliability were assessed among three different measurement time points and two investigators. Results: After exercise, a significant perfusion increase in the femur periosteum of 101.8% (PE; p = 0.003), 176.7% (WiR; p = 0.02), 93% (WiAUC; p< 0.001) and 116.2% (WiPI; p< 0.001) was observed in all measurement parameters compared to the resting conditions. For the VI, the increase was 110.9% (PE; p = 0.003), 221.3% (WiR; p< 0.001), 49.1% (WiAUC; p = 0.03), and 120.4% (WiPI; p< 0.001). Intrarater reliability showed measurement errors of 3.2–3.4% (PE), 5.0–5.1% (WiR), 4.5–4.1% (WiAUC), and 4.5–6.1% (WiPI). Interrater reliability presented measurement errors that ranged from 5.0–7.0% for T0 and 3.3–5.5% for T1. Conclusions: Lower limb exercise with a moderate load (ergometer cycling) significantly enhanced perfusion in healthy athletes within the FP and VI. Our data support the implementation of moderate exercise if enhanced tissue circulation is required. The findings from this study show that performing CEUS on the FP is a valuable diagnostic modality with high intra- and interrater reliability.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Bone metabolism; CEUS; Contrast-enhanced ultrasound; Femur; Microcirculation; Periosteal perfusion

Experimental hypertrophy of myenteric neurones in the pig: A morphometric study - Brehmer, Axel; Göbel, Dieter; Frieser, Markus; Graf, Michael; Radespiel-Tröger, Martin; et al. (Neurogastroenterology and Motility, 2000)
Muscular hypertrophy in the ileum of two pigs aged 6 weeks was induced using two different surgical techniques, narrowing of the gut circumference (mechanical stenosis) and segmental reversal of an ileal loop which results in a persistent antiperistalsis of that segment (functional stenosis). These pigs were sacrificed 5-6 weeks postoperatively. Cross sections through the gut wall at various distances from the operation sites revealed marked muscular hypertrophy in the pre-stenotic regions and in the reversed segment. Whole mounts from pre- and post- stenotic, as well as reversed ileal regions, were silver-impregnated. The corresponding ileal region of a third, nonoperated pig served as control. Using a computer-aided morphometric device, somal areas of five morphological neurone types were measured at various distances orally and anally from the operation sites and along the control ileum. Values between hypertrophic and nonhypertrophic zones as well as between two corresponding zones of nonoperated ileum were compared statistically. Along the control ileum, values revealed no differences in soma sizes. Within the experimentally altered material, somal areas of type VI neurones showed marked hypertrophy related to the sites of muscular hypertrophy whereas the other types remained constant throughout (II, IV in segmental reversal) or showed slightly larger somal areas within the post-stenotic, nonhypertrophied zones (I, V, IV in stenosis). Additionally, within the reversed segment, neuronal perikarya of type I, II, IV and V neurones were larger as compared to the neighbouring regions. However, this enlargement of perikarya within the reversed segment may not be correlated with muscular hypertrophy but rather with the transections of intramural axons before reversing this segment. The results suggest that morphologically distinct neurone types may play different roles within the mechanically stressed small intestine and possibly also in the coordination of normal muscular function.

Exploring the phenotypical spectrum of BRD4 defects - Hauer, Nadine; Vogl, C.; Popp, Bernt; Buettner, C.; Uebe, S.; Sticht, Heinrich; Ekici, Arif Bülent; Klinger, Patricia; Kraus, Cornelia; Krumbiegel, M.; Wiesener, A.; Dörr, Helmuth-Günther; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Expression analysis of ADAM17 during mouse eye development - Sel, Saadettin; Kalinski, Thomas; Enssen, Isabelle; Kaiser, Maja; Nass, Norbert; Trau, Stefanie; Wollensak, Gregor; Bräuer, Lars; Jaeger, Kristin; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2012)
ADAM17 (a disintegrin and metallopeptidase domain 17) is crucial for eye morphogenesis. In this study we analysed the expression pattern of ADAM17 during mouse eye development. ADAM17 expression in adult retina was examined using the reverse transcription-polymerase chain reaction (RT-PCR) and verification of the RT-PCR products by DNA sequencing. Immunohistochemistry was performed to evaluate the ADAM17 expression pattern in mouse eyes at developmental stages of embryonic day (E) 12, E14, E16, E18, postnatal day (P) 0, P1, P4, P7, P14, P 30 and P175 (adult). We detected ADAM17 mRNA in adult retina tissue. ADAM17 protein was expressed in non-pigmented ciliary epithelial cells and in retinal vessels from P7 onwards during eye development. In corneal epithelial cells and endothelium, ADAM17 protein was present from P14 onwards. Although, mice in which the functional ADAM17 gene is significantly reduced develop multiple eye malformations, the expression of ADAM17 is not ubiquitous over the entire eye. Its expression pattern during development suggests that not only TNF-alpha but additional membrane-anchored substrates of ADAM17 play an important role in eye formation.
EVALuna2:4384

Expression and Localization of Lung Surfactant Proteins in Human Testis - Beileke, Stephanie; Claassen, Horst; Wagner, Walter; Matthies, Cord; Ruf, Christian; Hartmann, Arndt; Garreis, Fabian; Paulsen, Friedrich; Schicht, Martin; Bräuer, Lars (PLoS ONE, 2015)
Surfactant proteins (SPs) have been described in various tissues and fluids including tissues of the nasolacrimal apparatus, airways and digestive tract. Human testis have a glandular function as a part of the reproductive and the endocrine system, but no data are available on SPs in human testis and prostate under healthy and pathologic conditions.The aim of the study was the detection and characterization of the surfactant proteins A, B, C and D (SP-A, SP-B, SP-C, SP-D) in human testis. Additionally tissue samples affected by testicular cancer were investigated.Surfactant proteins A, B, C and D were detected using RT-PCR in healthy testis. By means of Western blot analysis, these SPs were detected at the protein level in normal testis, seminoma and seminal fluid, but not in spermatozoa. Expression of SPs was weaker in seminoma compared to normal testicular tissue. SPs were localized in combination with vimentin immunohistochemically in cells of Sertoli and Leydig.Surfactant proteins seem to be inherent part of the human testis. By means of physicochemical properties the proteins appear to play a role during immunological and rheological process of the testicular tissue. The presence of SP-B and SP-C in cells of Sertoli correlates with their function of fluid secretion and may support transportation of spermatozoa. In seminoma the expression of all SP's was generally weaker compared to normal germ cells. This could lead to a reduction of immunomodulatory and rheology processes in the germ cell tumor.
EVALuna2:4444

Expression and Regulation of S100 Fused-Type Protein Hornerin at the Ocular Surface and Lacrimal Apparatus - Garreis, Fabian; Jahn, Janine; Wild, Katharina; Abrar, Daniel; Schicht, Martin; Schroeder, Jens-Michael; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2017)
Purpose: The S100 fused-type proteins hornerin (HRNR) and filaggrin-2 (FLG2) are members of the epidermal differentiation complex, which is involved in terminal differentiation of keratinocytes via cornification as well as maintenance of the epidermal antimicrobial barrier. We investigated the expression and possible regulation of HRNR and FLG2 at the ocular surface and in the lacrimal apparatus. Methods: Tissues of the lacrimal apparatus and ocular surface were analyzed systematically by means of RT-PCR, immunohistochemistry, and immuntransmission electron microscopy (iTEM) for their ability to express and produce HRNR and FLG2. In addition, inducibility and regulation of HRNR were studied in cultivated human corneal (HCE), conjunctival (HCjE), as well as meibomian gland (HMGEC) epithelial cell line by real-time RT-PCR. Results: RT-PCR, immunohistochemistry, and iTEM revealed constitutive expression of HRNR in the epithelium of cornea, conjunctiva, nasolacrimal ducts, and acinus cells of lacrimal and meibomian glands. HRNR also was detected in tears of healthy volunteers. No expression of FLG2 could be detected in tissue samples of the ocular surface and lacrimal apparatus. Real-time RT-PCR revealed a decreased HRNR gene expression after challenge with proinflammatory cytokines and supernatants of Escherichia coli and Pseudomonas aeroginosa in HCE cells, whereas HCjE cells revealed no changes. In HMGECs serum-induced differentiation and application of all-trans retinoic acid significantly increased HRNR gene expression. Conclusions: The data suggest that HRNR, but not FLG2, is a component of the ocular surface and lacrimal apparatus, including meibomian glands. HRNR seems to contribute to the maintenance of the epithelial barrier at the ocular surface and, thus, also may be involved in ocular surface diseases.
EVALuna2:35323

Expression of Low Affinity Nerve Growth Factor Receptor p75 in Classic Bladder Exstrophy - Promm, Martin; Otto, Wolfgang; Weber, Florian; Goetz, Stefanie; Burger, Maximilian; Mueller, Karolina; Rubenwolf, Peter; Neuhuber, Winfried; Roesch, Wolfgang H. (Frontiers in Pediatrics, 2021)
Successful primary closure of classic bladder exstrophy (BE) is crucial for development of bladder capacity and voided continence. It is universally agreed that an intensive pain management including the use of caudal epidural anesthesia is an essential cornerstone for the outcome of this complex surgery. Whether and to what extent pain is caused by structural or functional changes is not yet known. The nerve growth factor (NGF) is regarded as a marker for pain in different bladder disorders. This prospective study investigated the role of histological alterations and NGF in patients with BE including 34 patients with BE and 6 patients with congenital vesicoureterorenal reflux (VUR) who served as controls. Between January 2015 and April 2020 transmural bladder biopsies were taken from the posterior bladder wall during delayed primary bladder closure. The samples were stained for histological evaluation and subjected to immunohistochemistry to analyze NGFR p75. Differences in histological alterations were examined with Fisher's exact test, and Mann-Whitney-U-test was used to compare the NGFR p75 staining intensity between patients with BE and controls. Patients with BE showed significantly more often acute inflammation (p < 0.001), squamous metaplasia (p = 0.002), and cystitis glandularis (p = 0.005) as well as NGFR p75 in the urothelium (p = 0.003) than patients with VUR. A limitation of this study is the small number of participants due to the rare disease entity. Similar to other painful bladder disorders, pain transmission in BE after intitial closure may in part be facilitated by elevated NGF signaling through its receptor.
CRIS-Team Scopus Importer:2021-03-19
Keywords: bladder exstrophy; hyperalgesia; immunohistochemistry; nerve growth factor; pain

Expression of recombinant surfactant protein SFTA3 in the human kidney cell line HEK 293T - Schröder, Henrik; Fischer, Ronny; Sollfrank, L.; Paulsen, Friedrich; Bräuer, Lars; Schicht, Martin (Annals of Anatomy-Anatomischer Anzeiger, 2017)
Pulmonary surfactant is broadly known to keep the lung dry, clean and open by lowering the surface tension of the fluid-film that lines the alveoli. The surfactant's protein component, the so called surfactant proteins (SPs), make up a multifunctional protein family. In addition to the four "classical" surfactant proteins (SP-A, SP-B, SP-C and SP-D), which possess immunologic as well as surfactant regulatory properties, two novel putative surfactant proteins (SFTA2 and SFTA3) have recently been described. Neither of them shows sequential nor structural similarity with the already known surfactant proteins. However, bioinformatic analyses as well as first molecular-biological studies reveal properties that have already been described for known surfactant proteins. In our present work we introduce a technique to synthesize, purify and stabilize recombinant SFTA3 derived from the human embryonic kidney cell line HEK 293T. This will provide investigators with a valuable source of further examination and characterization of this fascinating novel member of the surfactant protein family.
EVALuna2:34489

Expression of Surfactant Proteins in the Human Canaliculus: Evidence and Potential Insights Into the Tear Flow Dynamics - Mohammad, Javed Ali; Kumar, Nadimpalli Siva; Bräuer, Lars; Paulsen, Friedrich; Schicht, Martin (Ophthalmic Plastic and Reconstructive Surgery, 2018)
PURPOSE: To investigate the presence and distribution patterns of 6 surfactant proteins (SPs) in the human lacrimal canaliculus. METHODS: The study was performed on fresh frozen cadaveric samples of canaliculi. Immunohistochemical labeling was performed for assessing the presence and distribution of SP: SP-A, SP-B, SP-C, SP-D, SP-G/SFTA2, and SP-H/SFTA3. Immunofluorescence double staining was performed using the respective fluorescein-conjugated antibodies and the results were scored as positive or negative and the distribution pattern within the canalicular system was assessed. Western blot analysis was performed on the protein content which was resolved by reducing 15% sodium dodecyl sulfate-polyacrylamide electrophoresis and bands were studied following staining with primary and secondary antibodies. Human lung tissues were used as controls. RESULTS: Fluorescence double staining with 4,6-diamidino 2-pheynlindole and SPs showed strong immunostaining for SP-A, SP-B, SP-C, SP-D, and SP-H/SFTA3. The positive immunofluorescence was noticed across all the layers of the epithelium but not the subepithelial structures. The expression was noted on the surfaces and superficial cytoplasm of the superficial and deep epithelial cells. There was no expression of SP-G/SFTA2 across the canalicular system. Western blot analysis of the proteins confirmed and concurred with the immunofluorescence findings. CONCLUSIONS: This study provides a proof of principle for the presence of SPs known from lungs in the canalicular system and hypothesizes their possible functions and also their potential role in the tear flow dynamics between the ocular surface and the lacrimal drainage system.
EVALuna2:35301

Extracellular matrix alterations in late-onset Fuchs' corneal dystrophy - Weller, Julia M.; Zenkel, Matthias; Schlötzer-Schrehardt, Ursula; Bachmann, Björn; Tourtas, Theofilos; Kruse, Friedrich (Investigative Ophthalmology & Visual Science, 2014)
To characterize the alterations of extracellular matrix proteins in Descemet's membranes (DM) of patients with late-onset Fuchs' corneal dystrophy (FCD) and to differentiate them from nonspecific alterations in pseudophakic bullous keratopathy (PBK).Human DM-endothelial cell complexes were obtained from patients with late-onset FCD (n = 40), PBK (n = 6), and control eyes (n = 5). Gene expression profiles of endothelial cells were compared using a commercial real-time PCR array and quantitative real-time PCR assays for confirmation of differentially expressed genes. A total of 24 extracellular matrix proteins were also localized in cryosections of corneal specimens from FCD (n = 10), PBK (n = 4), and control eyes (n = 5) by immunohistochemistry.Polymerase chain reaction array analysis revealed a significant upregulation of 27 out of 84 extracellular matrix-related genes including collagens, proteoglycans, glycoproteins, cell adhesion molecules, and matrix metalloproteinases in FCD specimens as compared to normal controls, which could be partly confirmed and quantified by real-time PCR. Comparative analysis of FCD and PBK specimens showed a significant and consistent FCD-specific upregulation of collagen types I, III, and XVI; fibronectin; agrin; clusterin; transforming growth factor beta-induced (TGFBI); and integrin ?4 (3- to 18-fold, P < 0.05). Immunohistochemistry revealed an increased labeling of collagen (types III, VII, XV, XVI), agrin, fibulin-2, TGFBI, versican, and clusterin in the DM of FCD specimens compared to PBK specimens.The findings provide evidence for a specific upregulation, production, and deposition of collagen types III and XVI, agrin, TGFBI, and clusterin in late-onset FCD and thus point to the importance of matrix alterations in the pathophysiology of FCD.
EVALuna2:21180

Factors affecting the use of antioxidant supplements in patients with late AMD - Yu, Alice L.; Paul, Tobias; Schaumberger, Markus; Welge-Lüssen, Ulrich-Christoph (Clinical Ophthalmology, 2014)
The purpose of this study was to assess the use of oral antioxidant supplements in patients with late age-related macular degeneration (AMD) and to identify influencing factors that may affect the use of such supplements.The study included 47 patients with late AMD. Using a questionnaire, the patients were asked for their demographic, ophthalmologic, and systemic data, their source of recommendation of antioxidant use for AMD, and/or their reasons for nonuse. The demographic, ophthalmologic, and systemic information was correlated with use or nonuse of oral antioxidant supplements for AMD.Sixty-eight percent (32/47) of patients took antioxidant supplements for AMD and 32% (15/47) of patients did not. There were no statistically significant differences in demographic, ophthalmologic, and systemic parameters between patients with late AMD who used supplements and those who did not. Two thirds of patients with late AMD (66%, 31/47) reported being recommended oral antioxidant supplements for AMD by their ophthalmologist. Patients who did not use antioxidant supplements either did not obtain any recommendation or did not believe in their benefits.This study shows that most patients with late AMD use antioxidant supplements despite the recommendation to do so being missing in the Age-Related Eye Disease Study. Our study emphasizes the importance of seeking further therapeutic options for patients with late AMD.
EVALuna2:21199

Factors influencing self-reported use of antioxidant supplements in patients with age-related macular degeneration - Yu, Alice L.; Paul, Tobias; Schaumberger, Markus; Welge-Lüssen, Ulrich-Christoph (Current Eye Research, 2014)
Abstract Aim: The goals of the present study were to evaluate the current use and accuracy of dose-taking prescription among patients with age-related macular degeneration (AMD) and to detect potential factors influencing the use or non-use of oral antioxidant supplements.This is a cross-sectional questionnaire-based study of 65 patients with AMD of Age-Related Eye Disease Study (AREDS) category 3 (intermediate AMD) or category 4 (unilateral advanced AMD). Self-report data were obtained from a structural clinical interview in clinic. The patients were asked questions regarding their demographic, ophthalmologic and systemic data, their source of recommendation for antioxidant supplement use and/or their reasons for non-use. Afterwards, this information was correlated with the use or non-use of antioxidant supplements. Statistical analyses were conducted using a series of Mann-Whitney U-tests and Fisher's exact tests.There were 55.4% (36 of 65) of the patients reporting antioxidant supplement use for AMD and 44.6% (29 of 65) with no supplement use. However, only 56.7% (17 of 30) took the recommended dose on label. There were significantly more female patients taking supplements than male patients (p = 0.010). A statistically significant correlation was also found between supplement use and the number of visits to an ophthalmologist per year (p = 0.037). The main reason for antioxidant supplement non-use was the missing awareness of the availability of antioxidant supplements.Despite the recommendation of oral antioxidant supplements in the ARED Study for patients with AMD of category 3 or 4, only about half of these patients took the supplements in this study. Identifying the factors, which influenced the decision against supplement use, may help to better support patients in the prevention of severe vision loss caused by AMD.
EVALuna2:21196

Feasibility of Clinical Hypnosis for Test Anxiety in First-Year Medical Students - Hammer, Christian; Scholz, Michael; Bischofsberger, Larissa; Paulsen, Friedrich; Burger, Pascal H. M. (International Journal of Clinical and Experimental Hypnosis, 2020)
The purpose of this pilot study was to characterize test anxiety among first-year medical students at the University of Erlangen-Nürnberg and to test clinical hypnosis as a possible intervention. The “Prüfungsangstfragebogen,” a shortened and revised German version of the Test Anxiety Inventory, was used to estimate test anxiety. It was administered 3 times: at the commencement of winter term 2017/18 and 2 days prior to each of 2 mandatory oral anatomy exams. The test-anxiety categories emotionality, worry, interference, and lack of confidence were evaluated. The effect of clinical hypnosis on test anxiety was estimated. The global test anxiety and lack of confidence scores were reduced significantly over time in the group that underwent clinical hypnosis but not in the control group. Direct comparisons of hypnosis vs. control group yielded no statistically significant differences in the test anxiety scores.
CRIS-Team Scopus Importer:2020-08-28

FERM domain–containing protein 6 identifies a subpopulation of varicose nerve fibers in different vertebrate species - Beck, Josefa; Kressel, Michael (Cell and Tissue Research, 2020)
FERM domain–containing protein 6 (FRMD6) is a member of the FERM protein superfamily, which is evolutionary highly conserved and has recently been identified as an upstream regulator of the conserved growth-promoting Hippo signaling pathway. In clinical studies, the FRMD6 gene is correlated with high significance to Alzheimer’s disease and cognitive impairment implicating a wider role of this protein in the nervous system. Scare data are available on the localization of endogenous FRMD6 in neural tissues. Using a FRMD6-directed antiserum, we detected specific immunoreactivity in varicose nerve fibers in the rat central and peripheral nervous system. FRMD6-immunoreactive (-ir) neurons were found in the sensory ganglia of cranial nerves, which were marked by a pool of labeled cytoplasmic granules. Cross-species comparative studies detected a morphologically identical fiber population and a comparable fiber distribution in tissues from xenopus and human cranial nerves and ganglia. In the spinal cord, FRMD6-ir was detectable in the terminal endings of primary afferent neurons containing substance P (SP). In the rat diencephalon, FRMD6-ir was co-localized with either SP- or arginine vasopressin–positive fibers in Broca’s diagonal band and the lateral septum. Dense fiber terminals containing both FRMD6-ir and growth hormone-releasing hormone were found in the median eminence. The intimate association of FRMD6 with secretory vesicles was investigated in vitro. Induction of exocytotic vesicles in cultured cells by ectopic expression of the SP precursor molecule preprotachykinin A led to a redistribution and co-localization of endogenous FRMD6 with secretory granules closely mimicking the observations in tissues.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Alzheimer’s disease; Expanded; FERM domain; FRMD6; Willin

Fetal sigmoid colon mesentery made visible by routine ultrasound in the first and second trimester of pregnancy - Wozniak, Slawomir; Zazga, Maria; Kurc-Darak, Bozena; Tomialowicz, Marek; Paulsen, Friedrich; Florjanski, Jerzy (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Background: Ultrasound is a routine procedure performed during pregnancy to monitor the status of the human fetus, including the development of the digestive tract. The aim of this publication was to determine the shape of the fetal sigmoid colon mesentery during the first and second trimester of pregnancy by means of ultrasound. Methods: The study was performed in 45 pregnant women (age: 36.4 years on average, range 25–45) during a routine ultrasound examination. The fetuses were between 12 and 22 weeks of pregnancy. The shape of the fetal sigmoid colon mesentery was analyzed. Results: We visualized the triangular shape of the mesentery in all 45 cases. A prevalence of scalene or isosceles acute triangles was found in both trimesters. At the 12−13 weeks we observed 5 different forms of mesenteric triangles – the scalene or isosceles acute triangles appeared at 33.3% and 28.6%, respectively. The obtuse scalene was present in 23.8 %. In the 2nd trimester (20−22 weeks) 4 types were found, among them 37.5 % acute scalene and 33.3 % acute isosceles. Conclusions: The fetal sigmoid colon mesentery can be visualized from the 12th week of pregnancy. The triangular shape of the sigmoid colon mesentery is easy to follow during routine ultrasound examinations.
CRIS-Team Scopus Importer:2021-02-19
Keywords: Fetal development; Fetal ultrasound; Human fetal sigmoid colon mesentery

Fine structural distinction between ganglia of the outer and inner submucosal plexus in porcine small intestine - Brehmer, Axel; Stach, Werner; Addicks, Klaus (Acta Anatomica, 1994)
Ultrastructural differences between ganglia of the plexus submucosus internus (Meissner; PSI) and plexus submucosus externus (Schabadasch; PSE) are described. Comparison revealed a different glia index (ratio glia per neuron) between the PSE (3:1) and the PSI (1:1), the arrangement of PSI neurons in compartments and the appearance of broad membrane-to-membrane appositions inside the compartments of the PSI. Structural and immunohistochemical differences between the two plexuses are discussed. In general, PSE neurons show a wider variety in size and shape than most of the PSI neurons.
Keywords: Enteric nervous system; Glia index; Pig; Small intestine; Submucosal nerve plexuses; Ultrastructure

Flat midsubstance of the anterior cruciate ligament with tibial "C"-shaped insertion site - Siebold, Rainer; Schuhmacher, Peter; Fernandez, Francis; Smigielski, Robert; Fink, Christian; Brehmer, Axel; Kirsch, Joachim (Knee Surgery Sports Traumatology Arthroscopy, 2015)
This anatomical cadaver study was performed to investigate the flat appearance of the midsubstance shape of the anterior cruciate ligament (ACL) and its tibial "C"-shaped insertion site.The ACL midsubstance and the tibial ACL insertion were dissected in 20 cadaveric knees (n = 6 fresh frozen and n = 14 paraffined). Magnifying spectacles were used for all dissections. Morphometric measurements were performed using callipers and on digital photographs.In all specimens, the midsubstance of the ACL was flat with a mean width of 9.9 mm, thickness of 3.9 mm and cross-sectional area of 38.7 mm(2). The "direct" "C"-shaped tibial insertion runs from along the medial tibial spine to the anterior aspect of the lateral meniscus. The mean width (length) of the "C" was 12.6 mm, its thickness 3.3 mm and area 31.4 mm(2). The centre of the "C" was the bony insertion of the anterior root of the lateral meniscus overlayed by fat and crossed by the ACL. No posterolateral (PL) inserting ACL fibres were found. Together with the larger "indirect" part (area 79.6 mm(2)), the "direct" one formed a "duck-foot"-shaped footprint.The tibial ACL midsubstance and tibial "C"-shaped insertion are flat and are resembling a "ribbon". The centre of the "C" is the bony insertion of the anterior root of the lateral meniscus. There are no central or PL inserting ACL fibres. Anatomical ACL reconstruction may therefore require a flat graft and a "C"-shaped tibial footprint reconstruction with an anteromedial bone tunnel for single bundle and an additional posteromedial bone tunnel for double bundle.
EVALuna2:4153

Flat Panel Detector Computed Tomography-Guided Placement of External Ventricular Drains Using the BrainLAB Headband and Precalibrated Disposable Stylet Instrument: A Cadaveric Feasibility Study - Feulner, Julian; Lang, Stefan; Buder, Thomas; Struffert, Tobias; Buchfelder, Michael; Brandner, Sebastian (World Neurosurgery, 2018)
BACKGROUND: The standard freehand method for the insertion of external ventricular drains (EVDs) is associated with high rates of incorrect placement. Use of neuronavigation has been shown to reduce the rates of inaccurately positioned EVDs. We present a novel neuronavigation-based approach for EVD placement using flat panel detector computed tomography (FDCT) imaging. METHODS: Four cadaveric heads were used for neuronavigated placement of EVDs using the BrainLAB reference headband in combination with laser surface registration and the precalibrated disposable stylet. In 2 cases, conventional multislice CT imaging was performed to reference neuronavigation. In the other 2 cases, preprocedural imaging was performed with FDCT. After inserting the EVDs, all heads were examined again with the identical imaging method as used before the procedure, followed by evaluation of catheter position. RESULTS: Our data demonstrate that FDCT imaging provides adequate image quality for referencing neuronavigation and performing navigated neurosurgery. All EVDs showed an optimal position in the ipsilateral frontal horn. Use of a BrainLAB reference headband combined with laser surface registration and the precalibrated disposable stylet affords the advantage of not requiring rigid fixation in a clamp. CONCLUSIONS: Our presented method is fast, accurate, and easy to use. Furthermore, this study is the first to demonstrate that navigated neurosurgery can be performed on the basis of FDCT imaging.
EVALuna2:212791

Flexor tendon repair with a polytetrafluoroethylene (PTFE) suture material - Polykandriotis, Elias; Besrour, Foued; Arkudas, Andreas; Ruppe, Florian; Zetzmann, Katharina; Bräuer, Lars; Horch, Raymund E. (Archives of Orthopaedic and Trauma Surgery, 2019)
BackgroundThere is a consensus that after a flexor tendon repair an aggressive rehabilitation protocol with early active motion can improve functional outcome, provided that the combination of material and suturing technique can meet the higher biomechanic demands. Bearing this in mind we evaluated a polytetrafluoroethylene (PTFE) suture (SERAMON((R)), Serag-Wiessner) as a possible material for flexor tendon repair.Materials and methods40 flexor tendons were harvested from fresh cadaveric upper extremities. 3-0 and 5-0 strands were used both in the polypropylene (PPL) as well as in the PTFE group. In the first phase of the study, we evaluated knotting properties and mechanical characteristics of the suture materials themselves. In the second phase, a 2-strand Kirchmayr-Kessler suture technique was applied for a core suture of a flexor tendon (n=16). In the third phase, we performed a tendon repair including an epitendinous running suture with 5-0 PPL or 5-0 PTFE material (n=22). One way ANOVA tests were performed.ResultsThe linear loading strength of single strand knotted PPL 3-0 was 19.870.59N. The linear loading strength of knotted PTFE 3-0 was 32.47 +/- 1.67N. For PPL 3-0 maximum linear strength was achieved with five knots, for PTFE 3-0 with eight knots. When a Kirchmayr-Kessler core-only repair was performed, then in the PPL group the loading strength of the repaired tendon was 30.74 +/- 9.77N. In the PTFE group the loading strength was 23.74 +/- 5.6N (p=0.10). However, all repairs in the PTFE group failed due to cheese wiring. When a Kirchmayr-Kessler core and epitendinous repair technique was used, then in the PPL group the loading strength of the repaired tendon was 49.90 +/- 16.05N. In the PTFE group the loading strength was 73.41 +/- 19.81N (p=0.006).Conclusion p id=Par4 PTFE demonstrates superior strength properties in comparison to PPL for flexor tendon repairs. However, standard 2 strand techniques have proved inadequate to bear the higher biomechanic demands.
CRIS-Team WoS Importer:2019-03-08

"Flexures and bends of the large intestine: Current terminology and a suggestion to simplify it" - Wozniak, Slawomir; Quondamatteo, Fabio; Paulsen, Friedrich (Journal of Anatomy, 2022)
There are a number of inconsistencies in the description of the bends of the colon down to the anus. This is historically based on the fact that anatomists saw the colon in its position in the abdominal cavity down to the pelvis and thus from the "outside" and also described it in this way. This view is still useful in clinical practice today (e.g. for the abdominal surgeons). For the greater part of clinicians, however, the view has shifted due to modern endoscopy. This allows examiners to see the terminal section of the intestine and the colon from the "inside". To accommodate both "ways of looking" in terms of modern medicine, we have been guided by today's clinical needs, and here we attempt to reconcile these with the historically evolved anatomical terms to create a nomenclature that meets all the needs of students, anatomists and clinicians looking at the large intestine from the inside and outside. With this in mind, we propose to speak of colic flexures (right colic flexure = RCF = hepatic flexure, flexura coli sinistra; left colic flexure = LCF = splenic flexure, flexura coli dextra; descending-sigmoid flexure = DSF; sigmoid-rectum flexure = SRF) for the colon (colon). For the rectum (rectum), we suggest the term bend (superior, intermediate and inferior) when viewed in the frontal plane, the term curvature (sacral curvature; anorectal curvature = perineal curvature) when viewed in the sagittal plane.
CRIS-Team WoS Importer:2022-12-23

Focused practice of lacrimal drainage disorders - Mohammad, Javed Ali; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2019)
CRIS-Team Scopus Importer:2019-05-02

Fresh and cryopreserved amniotic membrane secrete the trefoil factor family peptide 3 that is well known to promote wound healing - Schulze, Ute; Hampel, Ulrike; Sel, Saadettin; Goecke, Tamme W.; Thaele, Volker; Garreis, Fabian; Paulsen, Friedrich (Histochemistry and Cell Biology, 2012)
Amniotic membrane (AM) is often used for the treatment of ocular surface ulcerations and other corneal defects. Trefoil factor family (TFF) peptide 3 is produced by conjunctival goblet cells, participates in tear film physiology and has also been shown to be involved in ocular surface restitution after corneal injury. In the present study, we questioned whether AM also might be a source of TFF3 and if yes whether the secretion rate of TFF3 is changed by proinflammatory cytokines or by cryoconservation of AM. By means of RT-PCR, the mRNA expression of all three known TFF peptides could be detected in AM. Immunohistochemistry on paraffin-embedded sections localized TFF3 protein and also TFF2 in AM cells and Western blot analysis revealed TFF3 protein in AM. Stimulation experiments with proinflammatory cytokines and subsequent TFF3 ELISA measurements revealed that the secretion rate of fresh or cryoconserved AM was not significantly changed. The results indicate that TFF peptides are produced by AM. TFF3 may contribute to ocular surface wound healing after AM transplantation, but its production by AM is not further inducible by proinflammatory stimuli. Cryopreservation has no effect on the secretion rate of TFF3 supporting the use of cryopreserved AM for transplantation.
EVALuna2:4370

From freshmanship to the first "Staatsexamen"–increase of depression and decline in sense of coherence and mental quality of life in advanced medical students - Burger, Pascal H. M.; Tektas, Ozan Yüksel; Paulsen, Friedrich; Scholz, Michael (Psychotherapie Psychosomatik Medizinische Psychologie, 2014)
Psychiatric disorders (Burnout, depression, anxiety disorders) are common among medical students with a distinctly higher prevalence compared to the general public. Although medi-cal students show a normal health status at the beginning of their university study period, a deterioration of these aspects in higher semesters is evident and continues when they become residents. In our study ESTRELLAS we examined 530 medical students in the preclinical semesters (1st-4th) before their first "Staatsexamen" with validated psychological questionnaires for depression, anxiety, quality of life and sense of coherence. Students in their 1st semester show normal values like the general public. During the 4 semesters a slow and continuous rise of depressive symptoms and anxiety was detected. Quality of life and sense of coherence constantly deteriorated. An increase of physical symptoms was not detected. In the 4th semester the number of depressive students had already doubled. The development of worsening psychological problems and resulting psychiatric disorders seems to be a continuous process, starting with the beginning of the medical studies and growing continuously during the preclinical semesters. Effect-ive strategies for coping with distress should be integrated in the medical curriculum at universities from the very first semester on. Relaxation techniques could thus be an opportunity.
EVALuna2:4432

From Lysosomal Storage Disorders to Parkinson's Disease – Challenges and Opportunities - Mächtel, Rebecca; Boros, Fanni Annamaria; Dobert, Jan; Arnold, Philipp; Zunke, Friederike (Journal of Molecular Biology, 2023)
Lysosomes are specialized organelles with an acidic pH that act as recycling hubs for intracellular and extracellular components. They harbour numerous different hydrolytic enzymes to degrade substrates like proteins, peptides, and glycolipids. Reduced catalytic activity of lysosomal enzymes can cause the accumulation of these substrates and loss of lysosomal integrity, resulting in lysosomal dysfunction and lysosomal storage disorders (LSDs). Post-mitotic cells, such as neurons, seem to be highly sensitive to damages induced by lysosomal dysfunction, thus LSDs often manifest with neurological symptoms. Interestingly, some LSDs and Parkinson's disease (PD) share common cellular pathomechanisms, suggesting convergence of aetiology of the two disease types. This is further underlined by genetic associations of several lysosomal genes involved in LSDs with PD. The increasing number of lysosome-associated genetic risk factors for PD makes it necessary to understand functions and interactions of lysosomal proteins/enzymes both in health and disease, thereby holding the potential to identify new therapeutic targets. In this review, we highlight genetic and mechanistic interactions between the complex lysosomal network, LSDs and PD, and elaborate on methodical challenges in lysosomal research.
CRIS-Team Scopus Importer:2023-03-24
Keywords: lysosomal enzymes; lysosomal storage disorder; lysosome; neurodegeneration; Parkinson's disease

From Submerged Cultures to 3D Cell Culture Models: Evolution of Nasal Epithelial Cells in Asthma Research and Virus Infection - Aydin, Malik; Naumova, Ella A.; Bellm, Aliyah; Behrendt, Ann Kathrin; Giachero, Federica; Bahlmann, Nora; Zhang, Wenli; Wirth, Stefan; Paulsen, Friedrich; Arnold, Wolfgang H.; Ehrhardt, Anja (Viruses, 2021)
Understanding the response to viral infection in the context of respiratory diseases is of significant importance. Recently, there has been more focus on the role of the nasal epithelium in disease modeling. Here, we provide an overview of different submerged, organotypic 3D and spheroid cell culture models of nasal epithelial cells, which were used to study asthma and allergy with a special focus on virus infection. In detail, this review summarizes the importance, benefits, and disadvantages of patient-derived cell culture models of nasal- and bronchial epithelial cells, including a comparison of these cell culture models and a discussion on why investigators should consider using nasal epithelial cells in their research. Exposure experiments, simple virus transduction analyses as well as genetic studies can be performed in these models, which may provide first insights into the complexity of molecular signatures and may open new doors for drug discovery and biomarker research.
CRIS-Team Scopus Importer:2021-03-26
Keywords: 3D cell culture; air–liquid-interface; asthma; bronchial epithelial cells; culture techniques; epithelial cells; nasal epithelial cells; spheroids; submerged; virus

Frontline Science: Aggregated neutrophil extracellular traps prevent inflammation on the neutrophil-rich ocular surface - Mahajan, Aparna; Grüneboom, Anika; Petru, Lenka; Podolska, Malgorzata; Kling, Lasse; Maueröder, Christian; Dahms, Florian; Christiansen, Silke; Günter, Lochnit; Krenn, Veit; Jünemann, Anselm; Bock, Felix; et al. (Journal of Leukocyte Biology, 2019)
Eye rheum is a physiological discharge, which accumulates at the medial angle of the healthy eye soon after opening in the morning. Microscopic evaluation of eye rheum revealed the presence of viable neutrophils, bacteria, epithelial cells, and particles, aggregated by neutrophil extracellular traps. We observed that in the evening, during eye closure, high C5a recruited neutrophils to the tear film and activated them. In this hypoxic area rich in CO 2 , neutrophils fight microbial aggressors by degranulation. Immediately after eye opening, the microenvironment of the ocular surface changes, the milieu gets normoxic, and loss of CO 2 induces subtle alkalinization of tear film. These conditions favored the formation of neutrophil extracellular traps (NETs) that initially covers the ocular surface and tend to aggregate by eyelid blinking. These aggregated neutrophil extracellular traps (aggNETs) are known as eye rheum and contain several viable neutrophils, epithelial cells, dust particles, and crystals packed together by NETs. Similar to aggNETs induced by monosodium urate crystals, the eye rheum shows a robust proteolytic activity that degraded inflammatory mediators before clinically overt inflammation occur. Finally, the eye rheum passively floats with the tear flow to the medial angle of the eye for disposal. We conclude that the aggNETs-based eye rheum promotes cleaning of the ocular surface and ameliorates the inflammation on the neutrophil-rich ocular surfaces.
CRIS-Team Scopus Importer:2019-05-02
Keywords: degranulation; eye rheum; inflammation; NETs; neutrophils; resolution; serine protease

Functional anatomy of the syrinx of the chukar partridge (Galliformes: Alectoris chukar) as a model for phonation research - Erdogan, Serkan; Sagsoz, Hakan; Paulsen, Friedrich (Anatomical Record-Advances in Integrative Anatomy and Evolutionary Biology, 2015)
The phonation process of vertebrates is influenced by the material characteristics of the participating structures, ranging from molecular to macroscopic dimensions. Good animal models for phonation research are still lacking. Due to easy availability and relatively simple structure, the syrinx of birds might serve as a good animal model for this purpose. Our aim was therefore to determine structural features of the syrinx and obtain insights into its mucus layer characteristics. Epithelium and glands were analyzed using histological, histochemical, and immunohistochemical methods and conclusions were drawn on the use of the syrinx as a model for phonation research by comparing the epithelium and its mucus characteristics to human laryngeal secretions. Ten adult partridges were analyzed. The tympanum of the syrinx developed from the last two tracheal cartilages, whereas the caudal part of the syrinx was formed from eight pieces of bronchial cartilages. The tracheal and bronchial epithelia and the pessulus of the syrinx were lined by pseudo-stratified columnar epithelium in which goblet cells and intraepithelial glands were localized. Collagen fibers were distributed in the lamina propria of all parts of the syringeal mucosa. Elastic fibers in the membranes of the syrinx showed evident distribution. All glandular epithelial cells and goblet cells were positive for neutral, acidic and carboxylated mucins were dominant in particular. Epithelium and glands revealed positive reactivity with antibodies to the mucins MUC1, MUC2, and MUC5AC. Of these, MUC2 and MUC5AC were dominant. The syrinx of partridge can serve as a good ex vivo model for phonation research.
EVALuna2:4440

Functional anatomy of the vagus system – Emphasis on the somato-visceral interface - Neuhuber, Winfried; Berthoud, Hans Rudolf (Autonomic Neuroscience-Basic & Clinical, 2021)
Due to its pivotal role in autonomic networks, the vagus attracts continuous interest from both basic scientists and clinicians. In particular, recent advances in vagus nerve stimulation strategies and their application to pathological conditions beyond epilepsy provide a good opportunity to recall basic features of vagal peripheral and central anatomy. In addition to the “classical” vagal brainstem nuclei, i.e., dorsal motor nucleus, nucleus ambiguus and nucleus tractus solitarii, the spinal trigeminal and paratrigeminal nuclei come into play as targets of vagal afferents. On the other hand, the nucleus of the solitary tract receives and integrates not only visceral but also somatic afferents. Thus, the vagus system participates significantly in what may be defined as “somato-visceral interface”.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Auricular nerves; Dorsal motor nucleus; Nucleus ambiguus; Nucleus tractus solitarii; Paratrigeminal nucleus; Vagus nerve stimulation

Functional anatomy of the vagus system: How does the polyvagal theory comply? - Neuhuber, Winfried; Berthoud, Hans -Rudolf (Biological Psychology, 2022)
Due to its pivotal role in autonomic networks and interoception, the vagus attracts continued interest from both basic scientists and therapists of various clinical disciplines. In particular, the widespread use of heart rate variability as an index of autonomic cardiac control and a proposed central role of the vagus in biopsychological concepts, e.g., the polyvagal theory, provide a good opportunity to recall basic features of vagal anatomy. In addition to the “classical” vagal brainstem nuclei, i.e., dorsal motor nucleus, nucleus ambiguus and nucleus tractus solitarii, the spinal trigeminal and paratrigeminal nuclei come into play as targets of vagal afferents. On the other hand, the nucleus of the solitary tract receives and integrates not only visceral but also somatic afferents.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Central connections; Dorsal motor nucleus; Nucleus ambiguus; Nucleus tractus solitarii; Polyvagal theory

Functionalization of carbon nanotubes enables non-covalent binding and intracellular delivery of small interfering RNA for efficient knock-down of genes - Krajcik, Rastislav; Jung, Adrian; Hirsch, Andreas; Neuhuber, Winfried; Zolk, Oliver (Biochemical and Biophysical Research Communications, 2008)

Functional Protective Effects of Long-Term Memantine Treatment in the DBA/2J Mouse. - Atorf, Jenny; Scholz, Michael; Garreis, Fabian; Lehmann, Julia; Bräuer, Lars; Kremers, Jan (Documenta Ophthalmologica, 2013)
Purpose: To analyse the effects of long-term memantine treatment on the retinal physiology and morphology of DBA/2J mice. Methods: DBA/2J (D2J) mice received i.p. injections of the NMDA receptor antagonist memantine, which protects neurons from abnormally elevated glutamate levels, twice a day over a period of 7 months. At the age of 2, 6 and 10 months, the intraocular pressure (IOP) and electroretinograms (ERGs) were measured in all treated D2J mice, in untreated D2J controls and in C57Bl/6 (B6) wild-type mice. After the last measurement at the age of 10 months, the mice were killed and the retinae and the optic nerves were analysed morphologically. Results: The IOP increased with age in both D2J and B6 mice with a larger increase in the D2J strain. IOPs were not influenced by memantine treatment. The response amplitude of the scotopic flash ERG decreased with age in the D2J strain. This amplitude decrease, particularly that of the b-wave, was smaller in treated D2J mice. The retinae of treated D2J mice exhibited less peripheral degeneration of cone photoreceptors, and optic nerve neuropathy was less frequent. Conlcusions: Application of the NMDA receptor antagonist memantine diminished retinal neurodegeneration in the D2J mice and had a protective effect on the b-wave amplitude of the scotopic flash ERG. This protection may occur secondarily as memantine primarily acts on retinal ganglion cells. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-03-09:Pub.2013.med.AI.LAIPDL.functi
Keywords: DBA/2J mouse; Electroretinography; Memantine; Neurodegeneration

Functional Relevance of the Interaction between Human Cyclins and the Cytomegalovirus-Encoded CDK-Like Protein Kinase pUL97 - Schütz, Martin; Steingruber, Mirjam; Socher, Eileen; Müller, Regina; Wagner, Sabrina; Kögel, Merle; Sticht, Heinrich; Marschall, Manfred (Viruses, 2021)
The replication of human cytomegalovirus (HCMV) is characterized by a complex network of virus–host interaction. This involves the regulatory viral protein kinase pUL97, which represents a viral cyclin-dependent kinase ortholog (vCDK) combining typical structural and functional features of host CDKs. Notably, pUL97 interacts with the three human cyclin types T1, H and B1, whereby the binding region of cyclin T1 and the region conferring oligomerization of pUL97 were both assigned to amino acids 231–280. Here, we addressed the question of whether recombinant HCMVs harboring deletions in this region were impaired in cyclin interaction, kinase functionality or viral replication. To this end, recombinant HCMVs were generated by traceless BACmid mutagenesis and were phenotypically characterized using a methodological platform based on qPCR, coimmunoprecipitation, in vitro kinase assay (IVKA), Phos-tag Western blot and confocal imaging analysis. Combined data illustrate the following: (i) infection kinetics of all three recombinant HCMVs, i.e., ORF-UL97 ∆231–255, ∆256–280 and ∆231–280, showed impaired replication efficiency compared to the wild type, amongst which the largest deletion exhibited the most pronounced defect; (ii) specifically, this mutant ∆231–280 showed a loss of interaction with cyclin T1, as demonstrated by CoIP and confocal imaging; (iii) IVKA and Phos-tag analyses revealed strongly affected kinase activity for ∆231–280, with strong impairment of both autophosphorylation and substrate phosphorylation, but less pronounced impairments for ∆231–255 and ∆256–280; and (iv) a bioinformatic assessment of the pUL97–cyclin T1 complex led to the refinement of our current binding model. Thus, the results provide initial evidence for the functional importance of the pUL97–cyclin interaction concerning kinase activity and viral replication fitness.<br
Keywords: human cytomegalovirus; virus-encoded kinase pUL97; viral CDK ortholog; interaction with human cyclin T1; replication-impaired viral mutants; defects in pUL97 activities; pUL97–cyclin functional importance

Fungal interface keratitis by Candida orthopsilosis following deep anterior lamellar keratoplasty - Wessel, Julia M.; Bachmann, Björn; Meiller, Ralph; Kruse, Friedrich (BMJ Case Reports, 2013)
A 39-year-old male patient underwent uncomplicated deep anterior lamellar keratoplasty due to keratoconus. On day 5 after surgery, small whitish infiltrates developed in the corneal interface. The diagnosis of fungal keratitis was made when the culture medium of the graft grew Candida after the surgical intervention. Despite intensive antimycotic treatment and irrigation of the interface, the infiltrates persisted and eventually enlarged. Therefore, revision surgery with penetrating keratoplasty was performed. Microbiological analysis showed Candida orthopsilosis in the culture of the excised graft button. Histopathological staining of the excised graft showed periodic acid-Schiff-positive and Grocott methenamine silver-positive clusters of yeast between Descemet's membrane and the deep corneal stroma with focal perforations through Descemet's membrane. The treatment of mycotic keratitis caused by C orthopsilosis is challenging. Antimycotic treatment was unsuccessful in this case. Progression of the keratitis and perforation of Descemet's membrane suggest that early surgical intervention by penetrating keratoplasty is required.
EVALuna2:21124

Ganglioglioma with adverse clinical outcome and atypical histopathological features were defined by alterations in PTPN11/KRAS/NF1 and other RAS-/MAP-Kinase pathway genes - Hoffmann, Lucas; Coras, Roland; Kobow, Katja; López-Rivera, Javier A.; Lal, Dennis; Leu, Costin; Najm, Imad; Nürnberg, Peter; Herms, Jochen; Harter, Patrick N.; Bien, Christian G.; Kalbhenn, Thilo; et al. (Acta Neuropathologica, 2023)
Exome-wide sequencing studies recently described PTPN11 as a novel brain somatic epilepsy gene. In contrast, germline mutations of PTPN11 are known to cause Noonan syndrome, a multisystem disorder characterized by abnormal facial features, developmental delay, and sporadically, also brain tumors. Herein, we performed a deep phenotype-genotype analysis of a comprehensive series of ganglioglioma (GG) with brain somatic alterations of the PTPN11/KRAS/NF1 genes compared to GG with common MAP-Kinase signaling pathway alterations, i.e., BRAFV600E. Seventy-two GG were submitted to whole exome sequencing and genotyping and 84 low grade epilepsy associated tumors (LEAT) to DNA-methylation analysis. In 28 tumours, both analyses were available from the same sample. Clinical data were retrieved from hospital files including disease onset, age at surgery, brain localization, and seizure outcome. A comprehensive histopathology staining panel was available in all cases. We identified eight GG with PTPN11 alterations, copy number variant (CNV) gains of chromosome 12, and the commonality of additional CNV gains in NF1, KRAS, FGFR4 and RHEB, as well as BRAFV600E alterations. Histopathology revealed an atypical glio-neuronal phenotype with subarachnoidal tumor spread and large, pleomorphic, and multinuclear cellular features. Only three out of eight patients with GG and PTPN11/KRAS/NF1 alterations were free of disabling-seizures 2 years after surgery (38% had Engel I). This was remarkably different from our series of GG with only BRAFV600E mutations (85% had Engel I). Unsupervised cluster analysis of DNA methylation arrays separated these tumours from well-established LEAT categories. Our data point to a subgroup of GG with cellular atypia in glial and neuronal cell components, adverse postsurgical outcome, and genetically characterized by complex alterations in PTPN11 and other RAS-/MAP-Kinase and/or mTOR signaling pathways. These findings need prospective validation in clinical practice as they argue for an adaptation of the WHO grading system in developmental, glio-neuronal tumors associated with early onset focal epilepsy.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Brain; DNA methylation; Epilepsy; Seizure; Summary plots

Gender as an underestimated factor in mental health of medical students - Burger, P. H. M.; Scholz, Michael (Annals of Anatomy-Anatomischer Anzeiger, 2018)
BACKGROUND: In Germany, currently two out of three medical students are female. Several studies corroborate that medical students show a significantly higher prevalence of stress-related mental disorders than the population in general. AIMS: We aimed to evaluate, if gender has an influence on the distribution of mental stress parameters and learning style among male and female medical students. METHODS: We investigated a total of 758 students of the medical faculty at the University of Erlangen-Nuernberg, Germany, using standardized and validated psychological questionnaires on depressive symptoms (BDI-II), burnout (BOSS-II) and quality of life (SF-12). In addition, we screened the students for their learning styles according to Kolb. RESULTS: Out of 723 participants who declared their gender, 57.8% were female and 37.6% were male. Female students showed significantly higher values for depressiveness as well as for emotional and cognitive burnout, whereas the mental quality of life was significantly lower. A considerably higher percentage of male students with a converging or an accommodating learning style were found in comparison to their female fellows. CONCLUSIONS: We postulate that an adaptation of the medical curriculum content to the investigated factors may contribute to a higher mental stability and less stress-related symptoms in medical students.
EVALuna2:35320

Gibt es eine neue Kopfspeicheldrüse? – Eher nicht! - Guntinas-Lichius, Orlando; Ihrler, Stephan; Freesmeyer, Martin; Guehne, Falk; Kluge, Regine; Bräuer, Lars; Iro, Heinrich; Paulsen, Friedrich; Dietz, Andreas; Bechmann, Ingo (Laryngo-Rhino-Otologie, 2020)
In October 2020, the lay press, but also some medical journals and websites reported the putative discovery of a new salivary gland in the nasopharynx based on prostate-specific membrane antigen positron emission tomography computed tomography (PSMA-PET/CT) examinations. As an interdisciplinary group from the fields of anatomy, pathology, nuclear medicine and otorhinolaryngology, we come to the view that an accumulation of minor salivary glands has been described here. Minor salivary glands in the nasopharynx and in the peritubar region have been described at least since 1866. The current description in PSMA-PET/CT does not justify the definition of a new, independent salivary gland. The PSMA-PET/CT could, however, be suitable to better protect salivary glands in the nasopharynx when planning radiation therapy. This should be evaluated in clinical trials.
CRIS-Team Scopus Importer:2020-12-04

Gold-based blood serum treatment promotes wound closure of corneal epithelial cell defects in primary in vitro experiments - Feldt, Jessica; Welss, Jessica; Schneider, Ulrich; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Background: Wound healing disorders characterised by impaired or delayed reepithelialisation are a serious medical problem. In the present study, we show that gold-based blood serum therapy is a suitable therapeutic approach and shows a supportive effect in wound closure of human corneal epithelial cells (HCE) in primary in vitro experiments. Methods: For this purpose, blood from healthy individuals was incubated without (S.Ctrl) or with gold-microparticles (S.Therapy) for 24 h. Prior to human epithelial cell stimulation (HCE), the gold particles were removed and the serum was diluted in DMEM (10 % or 30 %). Both groups of serum were compared after injury. HCE were cultured and injured (corneal in vitro wound model) and then stimulated with S.Ctrl or S.Therapy. Results: Treatment with serum from a gold-based serum therapy (S.Therapy) shows a supportive effect on wound healing in HCE cells in vitro. In addition, gold therapy supports the secretion of important cytokines normally associated with ocular surface wound healing (IL-1β, IL-6, TNF-α and TGF-β) in HCE cells. Conclusions: Therapy with gold-based blood serum significantly promotes the secretion and expression of cytokines and growth factors in HCE cells in vitro. Further preclinical experiments are necessary to demonstrate the influence of this therapy on HCE cells for possible clinical application on the human ocular surface and to prove its function also in poorly healing corneal lesions.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Autohaemotherapy; Corneal wound healing; Gold therapy; Human corneal epithelial cells

GPR40 Activation Abolishes Diabetes-Induced Painful Neuropathy by Suppressing VEGF-A Expression - Königs, Vanessa; Pierre, Sandra; Schicht, Martin; Welss, Jessica; Hahnefeld, Lisa; Rimola, Vittoria; Lütjen-Drecoll, Elke; Geisslinger, Gerd; Scholich, Klaus (Diabetes, 2022)
G-protein-coupled receptor 40 (GPR40) is a promising target to support glucose-induced insulin release in patients with type 2 diabetes. We studied the role of GPR40 in the regulation of blood-nerve barrier integrity and its involvement in diabetes-induced neuropathies. Because GPR40 modulates insulin release, we used the streptozotocin model for type 1 diabetes, in which GPR40 functions can be investigated independently of its effects on insulin release. Diabetic wild-type mice exhibited increased vascular endothelial permeability and showed epineural microlesions in sciatic nerves, which were also observed in naïve GPR40-/- mice. Fittingly, expression of vascular endothelial growth factor-A (VEGF-A), an inducer of vascular permeability, was increased in diabetic wild-type and naïve GPR40-/- mice. GPR40 antagonists increased VEGF-A expression in murine and human endothelial cells as well as permeability of transendothelial barriers. In contrast, GPR40 agonists suppressed VEGF-A release and mRNA expression. The VEGF receptor inhibitor axitinib prevented diabetes-induced hypersensitivities and reduced endothelial and epineural permeability. Importantly, the GPR40 agonist GW9508 reverted established diabetes-induced hypersensitivity, an effect that was blocked by VEGF-A administration. Thus, GPR40 activation suppresses VEGF-A expression, thereby reducing diabetes-induced blood-nerve barrier permeability and reverting diabetes-induced hypersensitivities.
CRIS-Team Scopus Importer:2022-04-22

Granulocyte colony-stimulating factor does not promote neurogenesis after experimental intracerebral haemorrhage - Kallmünzer, Bernd; Tauchi, Miyuki; Schlachetzki, Johannes; Machold, Kristin; Schmidt, Ariana; Winkler, Jürgen; Schwab, Stefan; Kollmar, Rainer (International Journal of Stroke, 2014)
Hematopoietic growth factors have been suggested to induce neuroprotective and regenerative effects in various animal models of cerebral injury. However, the pathways involved remain widely unexplored.This study aimed to investigate effects of local and systemic administration of granulocyte colony-stimulating factor on brain damage, functional recovery, and cerebral neurogenesis in an intracerebral haemorrhage whole blood injection model in rats.Eight-week-old male Wistar rats (n = 100) underwent induction of striatal intracerebral haemorrhage by autologous whole blood injection or sham procedure and were randomly assigned to either (a) systemic treatment with granulocyte colony-stimulating factor (60 ?g/kg) for five-days; (b) single intracerebral injection of granulocyte colony-stimulating factor (60 ?g/kg) into the cavity; or (c) application of vehicle for five-days. Bromodeoxyuridine-labelling and immunohistochemistry were used to analyze proliferation and survival of newly born cells in the sub-ventricular zone and the hippocampal dentate gyrus. Moreover, functional deficits and lesion volume were assessed until day 42 after intracerebral haemorrhage.Differences in lesion size or hemispheric atrophy between granulocyte colony-stimulating factor-treated and control groups did not reach statistical significance. Neither systemic, nor local granulocyte colony-stimulating factor administration induced neurogenesis within the dentate gyrus or the sub-ventricular zone. The survival of newborn cells in these regions was prevented by intracerebral granulocyte colony-stimulating factor application. A subtle benefit in functional recovery at day 14 after intracerebral haemorrhage induction was observed after granulocyte colony-stimulating factor treatment.There was a lack of neuroprotective or neuroregenerative effects of granulocyte colony-stimulating factor in the present rodent model of intracerebral haemorrhage. Conflicting results from functional outcome assessment require further research.
EVALuna2:22279

Gut-brain communication and obesity: understanding functions of the vagus nerve - Berthoud, Hans-Rudolf; Albaugh, Vance L.; Neuhuber, Winfried (Journal of Clinical Investigation, 2021)
Given the crucial role of the gastrointestinal tract and associated organs in handling nutrient assimilation and metabolism, it has long been known that its communication with the brain is important for the control of ingestive behavior and body weight regulation. It is also clear that gut-brain communication is bidirectional and utilizes both rapid neural and slower humoral mechanisms and pathways. However, progress in understanding these mechanisms and leveraging them for the treatment of obesity and metabolic disease has been hindered by the enormous dimension of the gut mucosa, the complexity of the signaling systems, and lack of specific tools. With the ascent of modern neurobiological technology, our understanding of the role of vagal afferents in gut-brain communication has begun to change. The first function-specific populations of vagal afferents providing nutritional feedback as well as feed-forward signals have been identified with genetics-guided methodology, and it is hoped that extension of the methodology to other neural communication pathways will follow soon. Currently, efficient clinical leveraging of gut-brain communication to treat obesity and metabolic disease is limited to a few gut hormones, but a more complete understanding of function-specific and projection-specific neuronal populations should make it possible to develop selective and more effective neuromodulation approaches.
CRIS-Team WoS Importer:2021-06-04

Heterologous prime–boost vaccination with ChAdOx1 nCoV-19 and BNT162b2 - Tenbusch, Matthias; Schumacher, Sofie; Vogel, Emanuel; Priller, Alina; Held, Jürgen; Steininger, Philipp; Beileke, Stephanie; Irrgang, Pascal; Brockhoff, Ronja; Salmanton-García, Jon; Tinnefeld, Kathrin; Mijocevic, Hrvoje; et al. (Lancet Infectious Diseases, 2021)
CRIS-Team Scopus Importer:2021-09-10

High-Energy X-Ray Talbot-Lau Radiography of a Human Knee - Horn, Florian; Gelse, Kolja; Jabari, Samir; Hauke, Christian; Käppler, Sebastian; Ludwig, Veronika; Meyer, Pascal; Michel, Thilo; Mohr, Jürgen; Pelzer, Georg; Rieger, Jens; Riess, Christian; et al. (Physics in Medicine and Biology, 2017)
Keywords: dark-field; high-energy; chondrocalcinosis; x-ray imaging; phase-contrast; TalbotLau imaging

Higher Infection Risk among Health Care Workers and Lower Risk among Smokers Persistent across SARS-CoV-2 Waves-Longitudinal Results from the Population-Based TiKoCo Seroprevalence Study - Guenther, Felix; Einhauser, Sebastian; Peterhoff, David; Wiegrebe, Simon; Niller, Hans Helmut; Beileke, Stephanie; Steininger, Philipp; Burkhardt, Ralph; Kuechenhoff, Helmut; Gefeller, Olaf; Überla, Klaus; Heid, Iris M.; et al. (International Journal of Environmental Research and Public Health, 2022)
SARS-CoV-2 seroprevalence was reported as substantially increased in medical personnel and decreased in smokers after the first wave in spring 2020, including in our population-based Tirschenreuth Study (TiKoCo). However, it is unclear whether these associations were limited to the early pandemic and whether the decrease in smokers was due to reduced infection or antibody response. We evaluated the association of occupation and smoking with period-specific seropositivity: for the first wave until July 2020 (baseline, BL), the low infection period in summer (follow-up 1, FU1, November 2020), and the second/third wave (FU2, April 2021). We measured binding antibodies directed to SARS-CoV-2 nucleoprotein (N), viral spike protein (S), and neutralizing antibodies at BL, FU1, and FU2. Previous infection, vaccination, smoking, and occupation were assessed by questionnaires. The 4181 participants (3513/3374 at FU1/FU2) included 6.5% medical personnel and 20.4% current smokers. At all three timepoints, new seropositivity was higher in medical personnel with ORs = 1.99 (95%-CI = 1.36-2.93), 1.41 (0.29-6.80), and 3.17 (1.92-5.24) at BL, FU1, and FU2, respectively, and nearly halved among current smokers with ORs = 0.47 (95%-CI = 0.33-0.66), 0.40 (0.09-1.81), and 0.56 (0.33-0.94). Current smokers compared to never-smokers had similar antibody levels after infection or vaccination and reduced odds of a positive SARS-CoV-2 result among tested. Our data suggest that decreased seroprevalence among smokers results from fewer infections rather than reduced antibody response. The persistently higher infection risk of medical staff across infection waves, despite improved means of protection over time, underscores the burden for health care personnel.
CRIS-Team WoS Importer:2023-01-13

Highly Conserved Interaction Profiles between Clinically Relevant Mutants of the Cytomegalovirus CDK-like Kinase pUL97 and Human Cyclins: Functional Significance of Cyclin H - Schütz, Martin; Müller, Regina; Socher, Eileen; Wangen, Christina; Full, Florian; Wyler, Emanuel; Wong, Diana D.; Scherer, Myriam; Stamminger, Thomas; Chou, Sunwen; Rawlinson, William D.; Hamilton, Stuart T.; et al. (International Journal of Molecular Sciences, 2022)
The complex host interaction network of human cytomegalovirus (HCMV) involves the regulatory protein kinase pUL97, which represents a viral cyclin-dependent kinase (CDK) ortholog. pUL97 interacts with the three human cyclin types T1, H, and B1, whereby the binding region of cyclin T1 and the pUL97 oligomerization region were both assigned to amino acids 231-280. We further addressed the question of whether HCMVs harboring mutations in ORF-UL97, i.e., short deletions or resistance-conferring point mutations, are affected in the interaction with human cyclins and viral replication. To this end, clinically relevant UL97 drug-resistance-conferring mutants were analyzed by whole-genome sequencing and used for genetic marker transfer experiments. The recombinant HCMVs indicated conservation of pUL97–cyclin interaction, since all viral UL97 point mutants continued to interact with the analyzed cyclin types and exerted wild-type-like replication fitness. In comparison, recombinant HCMVs UL97 Δ231-280 and also the smaler deletion Δ236-275, but not Δ241-270, lost interaction with cyclins T1 and H, showed impaired replication efficiency, and also exhibited reduced kinase activity. Moreover, a cellular knock-out of cyclins B1 or T1 did not alter HCMV replication phenotypes or pUL97 kinase activity, possibly indicating alternative, compensatory pUL97–cyclin interactions. In contrast, however, cyclin H knock-out, similar to virus deletion mutants in the pUL97–cyclin H binding region, exhibited strong defective phenotypes of HCMV replication, as supported by reduced pUL97 kinase activity in a cyclin H-dependent coexpression setting. Thus, cyclin H proved to be a very relevant determinant of pUL97 kinase activity and viral replication efficiency. As a conclusion, the results provide evidence for the functional importance of pUL97–cyclin interaction. High selective pressure on the formation of pUL97–cyclin complexes was identified by the use of clinically relevant mutants<br

High-Throughput GLP-Capable Target Cell Visualization Assay for Measuring Cell-Mediated Cytotoxicity - Welter, Anna; Sundararaman, Srividya; Li, Ruliang; Zhang, Ting; Karulin, Alexey Y.; Lehmann, Alexander; Naeem, Villian; Roen, Diana R.; Kürten, Stefanie; Lehmann, Paul V. (Cells, 2018)
One of the primary effector functions of immune cells is the killing of virus-infected or malignant cells in the body. Natural killer (NK) and CD8 effector T cells are specialized for this function. The gold standard for measuring such cell-mediated cytolysis has been the chromium release assay, in which the leakage of the radioactive isotope from damaged target cells is being detected. Flow cytometry-based single cell analysis of target cells has recently been established as a non-radioactive alternative. Here we introduce a target cell visualization assay (TVA) that applies similar target cell staining approaches as used in flow cytometry but based on single cell computer image analysis. Two versions of TVA are described here. In one, the decrease in numbers of calcein-stained, i.e., viable, target cells is assessed. In the other, the CFSE/PI TVA, the increase in numbers of dead target cells is established in addition. TVA assays are shown to operate with the same sensitivity as standard chromium release assays, and, leaving data audit trails in form of scanned (raw), analyzed, and quality-controlled images, thus meeting requirements for measuring cell-mediated cytolysis in a regulated environment.
EVALuna2:35212

Historical Profiling of Dry Eye Patients - Potential Trigger Factors and Comorbidities - Posa, Andreas; Sel, Saadettin; Dietz, Richard; Sander, Ralph; Paulsen, Friedrich; Bräuer, Lars; Hammer, Christian (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose Dry eye syndrome (DES) is one of the most common diseases of the ocular surface. Affected persons suffer from different subjective complaints, with sometimes severe impairment in the quality of life. The aetiology and pathogenesis are multifactorial, multifaceted, and not yet fully understood. The present study is intended to provide deeper insights into possible triggering factors and correlating comorbidities.Materials and Methods In German ophthalmological practices, 306 persons (174 women, 132 men, age: 18 - 87 years) were interviewed by questionnaire on concomitant diseases and possible further triggering factors. DES was diagnosed by an ophthalmologist in 170 cases. The statistical comparative analysis between persons with and without DES was carried out using the chi-squared test (SPSS statistical software).Results DES occurred with significantly (p < 0.05) increased frequency in women over 40 years of age, as well as in persons exposed to screen work, air conditioning, persons with chronic ocular inflammation, myomas (hysterectomy), dry skin, arterial hypertonicity in need of medication, cardiac arrhythmias, fatty liver, gastric ulcer, appendicitis, cholecystectomy, depression, hyperlipidaemia, hyperuricaemia, osteoporosis, and nephrolithiasis.Conclusion Some of the known comorbidities and DES risk factors, e.g., computer work or depression, were confirmed. In contrast, the higher prevalence of hyperlipidaemia, hyperuricaemia, osteoporosis, nephrolithiasis, and fibroids among DES patients has not previously been reported. Additional studies should be performed on causal connections between DES and specific comorbidities.
CRIS-Team WoS Importer:2023-05-05

Horner's Muscle or Horner-Duverney's Muscle - Mohammad, Javed Ali; Paulsen, Friedrich (Ophthalmic Plastic and Reconstructive Surgery, 2020)
CRIS-Team Scopus Importer:2020-03-24

House dust mite exposure causes increased susceptibility of nasal epithelial cells to adenovirus infection - Aydin, Malik; Naumova, Ella A.; Paulsen, Friedrich; Zhang, Wenli; Gopon, Felix; Theis, Christian; Lutz, Sören; Ehrke-Schulz, Eric; Arnold, Wolfgang H.; Wirth, Stefan; Ehrhardt, Anja (Viruses, 2020)
Adenovirus (AdV) infections in the respiratory tract may cause asthma exacerbation and allergic predisposition, and the house dust mite (HDM) may aggravate virus-induced asthma exacerbations. However, the underlying mechanisms of whether and how AdV affects asthmatic patients remains unclear. To address this question, we investigated nasal epithelial cells (NAEPCs) derived from a pediatric exacerbation study cohort for experimental analyses. We analyzed twenty-one different green-fluorescent protein- and luciferase-tagged AdV types in submerged 2D and organotypic 3D cell culture models. Transduction experiments revealed robust transduction of AdV type 5 (AdV5) in NAEPCs, which was associated with an increased uptake of AdV5 in the presence of HDM. In healthy and asthmatic NAEPCs exposed to HDM before infection, we observed a time- and dose-dependent increase of AdV5 uptake associated with upregulation of entry receptors for AdV5. Furthermore, electron microscopic and histologic analyses of 3D cell cultures revealed an impairment of the respiratory cilia after HDM exposition. This ex vivo pilot study shows the impact of AdV infection and HDM exposition in a primary cell culture model for asthma.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Adenovirus; Allergy; Asthma; CAR; CD46; House dust mite; Pathogenesis

How do leg press exercises comply with limited weight bearing? - Wild, Linda; Carl, Hans-Dieter; Golditz, Tobias; Swoboda, Bernd; Hotfiel, Thilo (Physical Therapy in Sport, 2016)
To investigate foot loadings in different leg press settings with respect to a possible graduation of weight bearing (WB).Case series.Assessing plantar force values by means of dynamic pedobarography taken place in orthopaedic departments' rehab center.15 healthy students (9 men and 6 women, age 23 ± 2, weight 75 ± 6 kg) were recruited as participants from the medical faculty.Peak force values from normal gait (referred to as 100%) and single and double leg presses (SLP, DLP) with resistances of 10 kg, 20 kg and 40 kg, obtained with pedobarographic insoles.Performing DLP produced foot loadings (N) of 37 ± 15 with 10 kg, 91 ± 29 with 20 kg and 203 ± 27 with 40 kg, equal to 5%, 12% and 26% of full WB. SLP result in force values of 195 ± 32 with 10 kg, 308 ± 34 with 20 kg and 516 ± 45 with 40 kg, corresponding to 25%, 40% and 67% baseline.Leg press exercises can be performed in accordance with a given limitation of foot loading. Above mentioned conditions allow a graduation from 5% to 67% of full WB.
EVALuna2:10908

Human Lacrimal Drainage System Reconstruction, Recanalization, and Regeneration - Ali, Mohammad Javed; Paulsen, Friedrich (Current Eye Research, 2020)
Purpose: This review examines the broad contexts of the reconstructive and recanalization strategies of the human lacrimal drainage system.Materials and methods: A PubMed search was performed using individually and combination of the terms "lacrimal," "reconstruction", "recanalization," "canaliculus," "canalicular," "stenosis," "obstruction," "block," "drainage," "disorder," "disease," "nasolacrimal duct (NLD)," "endoscopy," "dacryoendoscopy," "trauma," "laceration," "stents," "repair," "tubes," "tear," "eyelid," "Sisler," "trephine," and "trephination". Selections from these lists were the basis of examination of reconstruction and recanalization strategies of multiple lacrimal disorders and their outcomes.Results: The major focus areas of this review are obstructions of the canaliculi and the NLD, traumatic involvement of the lacrimal drainage and their reconstruction strategies, and dacryoendoscopy-guided recanalization of the NLDs. The review found evidence for lack of uniformity in accurately defining the concepts of lacrimal drainage stenosis, partial or complete obstructions. Canalicular obstructions are difficult to manage and outcomes depend on the location of the obstruction. High success rates were reported in cases of canalicular lacerations managed by repair and silicone intubation. Controversies exists in the recanalization strategies involving the NLD. In the absence of any current regenerative strategies, NLD recanalization appears to be promising, but skepticism is well justified until its long-term effects are well known.Conclusions: Reconstructive strategies in canalicular trauma are highly successful. Recanalization strategies for the lacrimal drainage system are promising and there is a need to explore stem cells and regenerative modalities to take the lacrimal drainage science a step forward.
CRIS-Team Scopus Importer:2020-02-11
Keywords: canaliculi; Lacrimal drainage; nasolacrimal duct; recanalization; reconstruction

Human lacrimal gland cell line: Potential techniques and translational implications - Singh, Swati; Arnold, Philipp; Paulsen, Friedrich (Experimental Eye Research, 2023)
CRIS-Team Scopus Importer:2023-03-10

Human synovia contains trefoil factor family (TFF) peptides 1-3 although synovial membrane only produces TFF3: Implications in osteoarthritis and rheumatoid arthritis - Popp, Judith; Schicht, Martin; Garreis, Fabian; Klinger, Patricia; Gelse, Kolja; Sesselmann, Stefan; Tsokos, Michael; Etzold, Saskia; Stiller, Dankwart; Claassen, Horst; Paulsen, Friedrich (International Journal of Molecular Sciences, 2019)
Objective: Trefoil factor family peptide 3 (TFF3) has been shown to support catabolic functions in cases of osteoarthritis (OA). As in joint physiology and diseases such as OA, the synovial membrane (SM) of the joint capsule also plays a central role. We analyze the ability of SM to produce TFF compare healthy SM and its secretion product synovial fluid (SF) with SM and SF from patients suffering from OA or rheumatoid arthritis (RA). Methods: Real-time PCR and ELISA were used to measure the expression of TFFs in healthy SM and SM from patients suffering from OA or RA. For tissue localization, we investigated TFF1-3 in differently aged human SM of healthy donors by means of immunohistochemistry, real-time PCR and Western blot. Results: Only TFF3 but not TFF1 and -2 was expressed in SM from healthy donors as well as cases of OA or RA on protein and mRNA level. In contrast, all three TFFs were detected in all samples of SF on the protein level. No significant changes were observed for TFF1 at all. TFF2 was significantly upregulated in RA samples in comparison to OA samples. TFF3 protein was significantly downregulated in OA samples in comparison to healthy samples and cases of RA significantly upregulated compared to OA. In contrast, in SM TFF3 protein was not significantly regulated. Conclusion: The data demonstrate the production of TFF3 in SM. Unexpectedly, SF contains all three known TFF peptides. As neither articular cartilage nor SM produce TFF1 and TFF2, we speculate that these originate with high probability from blood serum.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Osteoarthritis (OA); Rheumatoid arthritis (RA); Synovial fluid (SF); Synovial membrane (SM); Trefoil factor family peptides (TFF)

Human wrist anatomy: anatomical features important for treatment of palmar dislocation of the lunate bone - Wozniak, Slawomir; Szpotowicz, Grzegorz; Bienias, Mariusz; Kedzierski, Bartlomiej; Sosnowska, Dorota; Szymocha, Marcin; Wasilewska, Elena; Zazga, Maria; Domagala, Zygmunt; Davies, D. Ceri; Paulsen, Friedrich (JOURNAL OF ANATOMY, 2021)
CRIS-Team WoS Importer:2021-02-12

Hyperelastic parameter identification of human articular cartilage and substitute materials - Weizel, A.; Distler, Thomas; Detsch, Rainer; Boccaccini, Aldo R.; Paulsen, Friedrich; Seitz, H.; Budday, Silvia; Bräuer, Lars (Journal of the Mechanical Behavior of Biomedical Materials, 2022)
Numerical simulations are a valuable tool in the field of tissue engineering for cartilage repair and can help to understand which mechanical properties affect the behavior of chondrocytes and contribute to the success or failure of surrogate materials as implants. However, special attention needs to be paid when identifying corresponding material parameters in order to provide reliable numerical predictions of the material's response. In this study, we identify hyperelastic material parameters for numerical simulations in COMSOL Multiphysics (R) v. 5.6 for human articular cartilage and two surrogate materials, commercially available ChondroFiller(liquid), and oxidized alginate-gelatin (ADA-GEL) hydrogels. We consider several hyperelastic isotropic material models and provide separate parameter sets for the unconditioned and the conditioned material response, respectively, based on previously generated experimental data including both compression and tension experiments. We compare a direct parameter identification approach assuming homogeneous deformation throughout the specimen and an inverse approach, where the experiments are simulated using a finite element model with realistic boundary conditions in COMSOL Multiphysics (R) v. 5.6. We demonstrate that it is important to consider both compression and tension data simultaneously and to use the inverse approach to obtain reliable parameters. The one-term Ogden model best represents the unconditioned response of cartilage, while the conditioned response of cartilage and ADA-GEL is equally well represented by the two-term Ogden and five-term Mooney-Rivlin models. The five-term Mooney-Rivlin model is also most suitable to model the unconditioned response of ADA-GEL. For ChondroFiller(liquid), we suggest using the five-term Mooney-Rivlin or two-term Ogden model for the unconditioned and the two-term Ogden model for the conditioned material response. These results will help to choose appropriate material models and parameters for simulations of whole joints or to advance mechanical-stimulation assisted cartilage tissue engineering in the future.
CRIS-Team WoS Importer:2022-07-01
Keywords: Parameter identification; Finite hyperelasticity; Human articular cartilage; Hydrogels; Tissue engineering

Identifying composition-mechanics relations in human brain tissue based on neural-network-enhanced inverse parameter identification - Hinrichsen, Jan; Feiler, Lea; Reiter, Nina; Bräuer, Lars; Schicht, Martin; Paulsen, Friedrich; Budday, Silvia (Mathematics and Mechanics of Solids, 2024)
The mechanical properties of human brain tissue remain far from being fully understood. One aspect that has gained more attention recently is their regional dependency, as the brain’s microstructure varies significantly from one region to another. Understanding the correlation between tissue components and the mechanical behavior is an important step toward better understanding how human brain tissue properties change in space and time and to develop highly spatially resolved constitutive models for large-scale brain simulations. Here, we analyze the correlation between human brain tissue components quantified through enzyme-linked immunosorbent assays (ELISA) and material parameters obtained through an inverse parameter identification scheme based on a hyperelastic Ogden model and multimodal mechanical testing data for eight regions of the brain. We use neural networks as a metamodel to save computational costs. The networks are trained on finite element simulation outputs and are able to replace the simulations in the initial optimization step. We identified strong dependencies between mechanical properties and Iba1 associated with microglia cells, collagen VI, GFAP associated with astrocytes, and collagen IV. These results advance our understanding of microstructure-mechanics relations in human brain tissue and will contribute to the development of highly spatially resolved microstructure-informed constitutive models.<br

IgA subclasses have different effector functions associated with distinct glycosylation profiles - Steffen, Ulrike; Koeleman, Carolien A.; Sokolova, Maria V.; Bang, Holger; Kleyer, Arnd; Rech, Jürgen; Unterweger, Harald; Schicht, Martin; Garreis, Fabian; Hahn, Jonas; Andes, Fabian T.; Hahn, Madelaine; et al. (Nature Communications, 2020)
Monomeric serum immunoglobulin A (IgA) can contribute to the development of various autoimmune diseases, but the regulation of serum IgA effector functions is not well defined. Here, we show that the two IgA subclasses (IgA1 and IgA2) differ in their effect on immune cells due to distinct binding and signaling properties. Whereas IgA2 acts pro-inflammatory on neutrophils and macrophages, IgA1 does not have pronounced effects. Moreover, IgA1 and IgA2 have different glycosylation profiles, with IgA1 possessing more sialic acid than IgA2. Removal of sialic acid increases the pro-inflammatory capacity of IgA1, making it comparable to IgA2. Of note, disease-specific autoantibodies in patients with rheumatoid arthritis display a shift toward the pro-inflammatory IgA2 subclass, which is associated with higher disease activity. Taken together, these data demonstrate that IgA effector functions depend on subclass and glycosylation, and that disturbances in subclass balance are associated with autoimmune disease.
CRIS-Team Scopus Importer:2020-01-21

IL-21 in Conjunction with Anti-CD40 and IL-4 Constitutes a Potent Polyclonal B Cell Stimulator for Monitoring Antigen-Specific Memory B Cells - Franke, Fridolin; Kirchenbaum, Greg A.; Kürten, Stefanie; Lehmann, Paul V. (Cells, 2020)
Detection of antigen-specific memory B cells for immune monitoring requires their activation, and is commonly accomplished through stimulation with the TLR7/8 agonist R848 and IL-2. To this end, we evaluated whether addition of IL-21 would further enhance this TLR-driven stimulation approach; which it did not. More importantly, as most antigen-specific B cell responses are T cell-driven, we sought to devise a polyclonal B cell stimulation protocol that closely mimics T cell help. Herein, we report that the combination of agonistic anti-CD40, IL-4 and IL-21 affords polyclonal B cell stimulation that was comparable to R848 and IL-2 for detection of influenza-specific memory B cells. An additional advantage of anti-CD40, IL-4 and IL-21 stimulation is the selective activation of IgM(+) memory B cells, as well as the elicitation of IgE(+) ASC, which the former fails to do. Thereby, we introduce a protocol that mimics physiological B cell activation through helper T cells, including induction of all Ig classes, for immune monitoring of antigen-specific B cell memory.
CRIS-Team WoS Importer:2020-04-21

Imaging the Parasinus Region with a Third-Generation Dual-Source CT and the Effect of Tin Filtration on Image Quality and Radiation Dose - Lell, Michael; May, Matthias; Brand, Michael; Eller, A.; Buder, Thomas; Hofmann, Eva Maria; Uder, Michael; Wüst, Wolfgang (American Journal of Neuroradiology, 2015)
CT is the imaging technique of choice in the evaluation of midface trauma or inflammatory disease. We performed a systematic evaluation of scan protocols to optimize image quality and radiation exposure on third-generation dual-source CT.CT protocols with different tube voltage (70-150 kV), current (25-300 reference mAs), prefiltration, pitch value, and rotation time were systematically evaluated. All images were reconstructed with iterative reconstruction (Advanced Modeled Iterative Reconstruction, level 2). To individually compare results with otherwise identical factors, we obtained all scans on a frozen human head. Conebeam CT was performed for image quality and dose comparison with multidetector row CT. Delineation of important anatomic structures and incidental pathologic conditions in the cadaver head was evaluated.One hundred kilovolts with tin prefiltration demonstrated the best compromise between dose and image quality. The most dose-effective combination for trauma imaging was Sn100 kV/250 mAs (volume CT dose index, 2.02 mGy), and for preoperative sinus surgery planning, Sn100 kV/150 mAs (volume CT dose index, 1.22 mGy). "Sn" indicates an additional prefiltration of the x-ray beam with a tin filter to constrict the energy spectrum. Exclusion of sinonasal disease was possible with even a lower dose by using Sn100 kV/25 mAs (volume CT dose index, 0.2 mGy).High image quality at very low dose levels can be achieved by using a Sn100-kV protocol with iterative reconstruction. The effective dose is comparable with that of conventional radiography, and the high image quality at even lower radiation exposure favors multidetector row CT over conebeam CT.
EVALuna2:14481

Immune phenotype of the CD4+ T cells in the aged lymphoid organs and lacrimal glands - Trujillo-Vargas, Claudia M.; Mauk, Kelsey E.; Hernandez, Humberto; de Souza, Rodrigo G.; Yu, Zhiyuan; Galletti, Jeremias G.; Dietrich, Jana; Paulsen, Friedrich; de Paiva, Cintia S. (GeroScience, 2022)
Aging is associated with a massive infiltration of T lymphocytes in the lacrimal gland. Here, we aimed to characterize the immune phenotype of aged CD4+ T cells in this tissue as compared with lymphoid organs. To perform this, we sorted regulatory T cells (Tregs, CD4+CD25+GITR+) and non-Tregs (CD4+CD25negGITRneg) in lymphoid organs from female C57BL/6J mice and subjected these cells to an immunology NanoString® panel. These results were confirmed by flow cytometry, live imaging, and tissue immunostaining in the lacrimal gland. Importantly, effector T helper 1 (Th1) genes were highly upregulated on aged Tregs, including the master regulator Tbx21. Among the non-Tregs, we also found a significant increase in the levels of EOMESmed/high, TbetnegIFN-γ+, and CD62L+CD44negCD4+ T cells with aging, which are associated with cell exhaustion, immunopathology, and the generation of tertiary lymphoid tissue. At the functional level, aged Tregs from lymphoid organs are less able to decrease proliferation and IFN-γ production of T responders at any age. More importantly, human lacrimal glands (age range 55–81 years) also showed the presence of CD4+Foxp3+ cells. Further studies are needed to propose potential molecular targets to avoid immune-mediated lacrimal gland dysfunction with aging.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Aging; CD4; Conventional T cells; Dry eye disease; Lacrimal gland; Lymphoid organs; Regulatory T cells; Sjögren’s syndrome; Transcriptome

Immunohistochemical Analysis of the Lacrimal Sac Mucopeptide Concretions - Mohammad, Javed Ali; Heichel, Jens; Paulsen, Friedrich (Ophthalmic Plastic and Reconstructive Surgery, 2019)
PURPOSE: To investigate the presence and distribution patterns of proteins in the lacrimal sac mucopeptide concretions. METHODS: The study was performed on 10 mucopeptide concretions obtained from the lacrimal sac during an endoscopic dacryocystorhinostomy. Immunohistochemical labeling was performed for assessing the presence and distribution of von Willebrand factor, fibronectin, collagen I, collagen III, human beta-defensin 2, beta-defensin 3, lysozyme, prolactin, cytokeratin (CK)-CK4, CK7, CK18, immunoglobulin M (IgM), immunoglobulin G (IgG), psoriasin (S100-A7), and migration inhibitory factor-related protein (MRP14/S100-A9). The results were then scored as positive or negative and the distribution pattern, if any, within the sectioned concretions was assessed. RESULTS: Immunohistochemical labeling was strongly positive for von Willebrand factor and fibronectin in the core areas of the concretions. Collagen I was widely dispersed both in the peripheral and core areas whereas collagen III was mostly limited to only few areas of the core. Strong immunoreactivity was noted for lysozyme, which was abundantly distributed, whereas prolactin receptors were positive on the surface and also the dispersed cells within the concretion matrices. Very few peripheral areas of concretions showed MRP14 or S100-A9 positivity in a noncontiguous fashion. Immunoreactivity was uniformly negative for CK-18, IgM, IgG, and psoriasin. CONCLUSIONS: The presence of fibronectin and von Willebrand factor in the core of the concretions strengthens the earlier hypothesis that blood components may act as a nidus for subsequent mucopeptide deposition. The study also provides possible clues to the lacrimal defenses mounted during dacryolithiasis.Fibronectin and vWF are present in the core of the dacryoliths. Blood components may act as a nidus in the evolution of lacrimal sac mucopeptide concretions.
CRIS-Team Scopus Importer:2019-11-15

Immunohistochemical characterization of putative primary afferent (sensory) myenteric neurons in human small intestine - Brehmer, Axel; Croner, Roland; Dimmler, Arno; Papadopoulos, Thomas; Schrödl, Falk; Neuhuber, Winfried (Autonomic Neuroscience-Basic & Clinical, 2004)
Pseudouni- or multiaxonal Dogiel type II neurons are the intrinsic primary afferent (sensory) neurons (IPANs) in the guinea pig small intestine. Our aim was to decipher the chemical code of human myenteric type II neurons and to establish their putative vertical projections, i.e., from the myenteric plexus to the submucosa/mucosa. Additionally, we tried to distinguish them chemically from uniaxonal, dendritic type V neurons displaying, at first glance, similar shapes, i.e., smoothly contoured cell bodies with several long processes. Wholemount preparations of the myenteric plexus were immunohistochemically double or triple stained for neurofilaments (NF) and one or two of the following peptides: calbindin, calretinin (CR), calcitonin gene-related peptide (CGRP), somatostatin (SOM) and substance P (SP). In each triple stained wholemount three counts were conducted: (1) NF-positive pseudouni- or multiaxonal (type II) neurons including their reactivities for the above peptides, (2) uniaxonal or NF-negative neurons displaying coreactivities for the above peptides and (3) NF-reactive type V neurons taking into account their reactivities for the above markers. Additionally, type II neurons, which had an axon leading into (disrupted) interconnecting strands towards the submucosa were counted and somal areas of types II and V neurons were measured. The majority of myenteric type II neurons displayed coreactivities for SOM/CR (89.6%), SOM/SP (86.6%) and SP/CR (81.6%), respectively. A minority of type II neurons was positive for CGRP or calbindin. A small population with type III morphology (uniaxonal, long and slender dendrites) displayed the same coreactivities as type II neurons. In contrast, not one single type V neuron was coreactive for SOM/CR, SOM/SP or SP/CR. Out of 627 type II neurons counted in six wholemounts, 84 type II neurons displayed an axon which could be followed into disrupted interconnecting strands indicating a vertical projection pattern. Somal areas of type II neurons were twice as big as those of type V neurons (904±210 versus 449±110 μm). In conclusion, most human myenteric type II neurons contain SOM, SP and CR. We suggest they are the human IPANs. Type V neurons are both morphologically and chemically distinctly different from type II neurons and may represent descending interneurons. Further studies have to decipher the type-specific chemical code of type II neurons distinguishing them also from type III neurons. © 2004 Elsevier B.V. All rights reserved.
Keywords: Enteric nervous system; Gut; Innervation; Morphometry

Immunohistochemical detection of urea transporter-A in the tear- producing part of the lacrimal system - Jäger, Franziska; Paulsen, Friedrich; Bergua, Antonio; Jungbauer, Rebecca; Hammer, Christian (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Objective: Urea constitutes a physiological and presumably well-regulated constituent of tear fluid. Its la-crimal concentration is significantly decreased in dry eye disease. Urea homeostasis within the tear fluid may also depend on the expression of urea transporters. The present study reports on the expression patterns of urea transporter A (UT-A) in the cells and tissues of the ocular surface and the lacrimal glands. Methods: UT-A immunohistochemistry was performed on 5 mu m paraffin sections of paraformaldehyde-fixed human, porcine, and murine corneas, eyelids, and lacrimal glands (n = 5 each). Results: UT-A immunostaining was largely comparable in all three species. UT-A signals were detected in the corneal epithelium and endothelium, in the conjunctival epithelium, in the acinar cells and excretory ducts of the lacrimal gland, Meibomian gland, and in the glands of Moll and Zeis. The Meibomian glands and the glands of Zeis exhibited a marked UT-A-positive staining in the basal cells of the alveolar epithelia and in the ductal epithelia. Conclusion: UT-A shows comparable expression patterns to UT-B (previous study) at the ocular surface and in the lacrimal glands, as determined by immunohistochemistry. The presence of both urea transporters in the lacrimal functional unit suggests that they are essential for the normal function of the lacrimal system and the integrity of the tear film. Potential alterations in urea transporter expression might be associated with the significant reduction of urea found in the tear fluid of dry eye patients. They may thus play an important role in the pathogenesis of dry eye disease. (c) 2022 Elsevier GmbH. All rights reserved.
CRIS-Team WoS Importer:2022-09-16

Immunohistological Study of Palpebral Lobe of the Lacrimal Gland in Severe Dry Eyes Secondary to Stevens–Johnson Syndrome - Singh, Swati; Mohammad, Javed Ali; Mittal, Vikas; Brabletz, Simone; Paulsen, Friedrich (Current Eye Research, 2020)
Purpose: To detect the immunohistochemical changes in the main lacrimal glands of patients suffering from chronic ocular sequelae of Stevens–Johnson syndrome (SJS). Methods: Histological sections of biopsies from the lacrimal gland of three chronic SJS patients (mean age, 33 years; 2 males) with severe dry eye disease (Schirmer = 0 mm) were assessed using double immunofluorescence techniques. Changes in the expression of secretory proteins lactoferrin (Lf), lysozyme (Ly), aquaporin 5 (AQP5), S-100, and early apoptosis marker (Annexin V) were studied. Results: Different morphological expressions of secretory proteins were present in the three samples. One sample had maintained the immunoreactivity for Lf, Ly, S-100, similar to healthy controls. Two samples had significantly reduced immunoreactivity for anti-Lf, anti-Ly, and S-100, the weakest being in the sample with distorted lobular architecture and mild interlobular fibrosis. AQP5 had a distinct vesicular intracytoplasmic immunoreactivity suggesting defective trafficking and integration of the protein to the apical membrane. There was no S-100 immunostaining in the acinar or ductal epithelium, whereas interstitial nerve fibers scattered in the periacinar region showed reduced immunoreactivity for S-100. There was strong Annexin V immunoreactivity in the nuclei of epithelial cells in the majority of acinar and ductal epithelia of all the samples, with distorted nuclear morphology in one sample. Conclusion: Defective trafficking of AQP5 and variable expression of Ly, Lf, S-100 are the notable findings in the lacrimal glands of chronic SJS patients along with signs of early apoptosis. It suggests that the palpebral lobe of the lacrimal gland is involved in the pathological processes occurring in the conjunctiva of SJS patients.
CRIS-Team Scopus Importer:2020-10-30
Keywords: aquaporin 5; aqueous deficient dry eye; dry eye; dry eye disease; Lacrimal gland; SJS; stevens-Johnson syndrome

Immunology of uveitis - Caspi, Rachel R.; Dick, Andrew; Forrester, John; Klein, Reinhild; Niederkorn, Jerry Y.; Paulsen, Friedrich; Rosenbaum, James; Wakefield, Denis; Zierhut, Manfred (Springer Berlin Heidelberg, 2016)
Today we are able to differentiate approximately a hundred entities of intraocular inflammations and group them into anatomical types like anterior, intermediate, posterior, and panuveitis. This book will cover most of the reported entities. A few of these entities have highly typical clinical findings, so that the specialist easily may be able to determine the entity, leading to therapy. But a lot of entities develop similarities in their clinical appearance (similar endothelial precipitates, similar chorioretinal infiltrations, similar retinal necrosis) and also similar complications (elevated intraocular pressure, cataract formation, and macular edema).
CRIS-Team Scopus Importer:2022-08-05

Impact of different cephalometric skeletal configurations on anatomic midface parameters in adults - Willershausen, Ines; Ehrenfried, Amelie; Krautkremer, Franziska; Ströbel, Armin; Seidel, Corinna Lesley; Paulsen, Friedrich; Kopp, Markus; Uder, Michael; Gölz, Lina; May, Matthias (Clinical Oral Investigations, 2024)
Objectives: Skull morphology and growth patterns are essential for orthodontic treatment, impacting clinical decision making. We aimed to determine the association of different cephalometric skeletal configurations on midface parameters as measured in 3D CT datasets. Materials and methods: After sample size calculation, a total of 240 fully dentulous patients between 20 and 79 years of age (mean age: 42 ± 15), who had received a CT of the skull within the scope of trauma diagnosis or intracranial bleeding, were retrospectively selected. On the basis of cephalometric analysis, using MPR reconstructions, patients were subdivided into three different vertical skull configurations (brachyfacial, mesofacial, dolichofacial) and the respective skeletal Class I, II, and III relationships. Anatomic parameters were measured using a three-dimensional post-processing console: the thickness of the maxillary and palatine bones as well as the alveolar crest, maxillary body and sutural length, width and height of the hard palate, maxillary facial wall thickness, and masseter muscle thickness and length. Results: Individuals with brachyfacial configurations had a significantly increased palatal and alveolar ridge thicknesses compared to those with dolichofacial- or mesofacial configurations. Brachyfacial configurations presented a significantly increased length and thickness of the masseter muscle (4.599 cm; 1.526 cm) than mesofacial (4.431 cm; 1.466 cm) and dolichofacial configurations (4.405 cm; 1.397 cm) (p < 0.001). Individuals with a skeletal Class III had a significantly shorter palatal length (5.313 cm) than those with Class I (5.406 cm) and Class II (5.404 cm) (p < 0.01). Sutural length was also significantly shorter in Class III (p < 0.05). Conclusions: Skeletal configurations have an impact on parameters of the bony skull. Also, measurable adaptations of the muscular phenotype could result. Clinical relevance: The association between viscerocranial morphology and midface anatomy might be beneficial for tailoring orthodontic appliances to individual anatomy and planning cortically anchored orthodontic appliances.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Anatomy; Cephalometry; Computed tomography; Midface; Orthodontics; Ultra-high-resolution datasets

Impact of different pretreatments and attachment materials on shear bond strength of indirectly bonded brackets using CAD/CAM transfer trays to monolithic zirconia - Jungbauer, Rebecca; Hammer, Christian; Edelhoff, Daniel; Proff, Peter; Stawarczyk, Bogna (Dental Materials, 2023)
Objective: Investigating the impact of different pretreatment methods, attachment materials and aging regimens on shear bond strength (SBS) between zirconia and indirectly bonded brackets using CAD/CAM transfer trays. Methods: Zirconia substrates were conditioned with silica coated alumina (CoJet) and a) Clearfil Ceramic Primer Plus (CF), b) RelyX Ceramic Primer (RXP), c) Futurabond U (FU). Brackets were virtually placed, transfer tray designed (OnyxCeph) and 3D-printed for indirect bonding with a) Transbond LV (TBL), b) Nexus NX3 (NX3), c) Maximum Cure (MC). SBS testing was performed with a universal testing machine after 24 h, 500 thermal cycles, 90 d. Directly bonded brackets to human enamel using Transbond XT Adhesive served as control. The adhesive remnant index (ARI) was evaluated. Data was analyzed with Shapiro–Wilk, Kruskal–Wallis and Dunn's post-hoc test with Bonferroni correction, Chi2 test (p < 0.05), and the Weibull modulus was calculated. Results: SBS ranged from 0.1 to 15.5 MPa and were influenced mostly by the attachment material. NX3 generally showed the highest values (9.5–15.8 MPa). Initially RXP/TBL and FU/TBL presented the lowest values (4.3/4.8 MPa). Aging regimens reduced SBS of MC irrespective of pretreatment, after 90 d values ranged from 0.1 to 0.9 MPa. ARI 1 was predominant in all MC groups and FU/NX3, 2 and 3 in the other groups. Weibull moduli ranged between 0.15 (MC/RXP/500 TC) and 6.24 (NX3/RXP/500 TC). Significance: MC seems not to be suitable for indirect bonding using CAD/CAM transfer trays to zirconia. NX3 showed similar SBS values compared to the control, TBL lower.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Adult treatment; CAD/CAM; Indirect bonding; Monolithic zirconia; Orthodontics; Shear bond strength

Impact of Glatiramer Acetate on B Cell-Mediated Pathogenesis of Multiple Sclerosis - Kürten, Stefanie; Jackson, Leila J.; Kaye, Joel; Vollmer, Timothy L. (Cns Drugs, 2018)
Growing evidence indicates that B cells play a key role in the pathogenesis of multiple sclerosis (MS). B cells occupy distinct central nervous system (CNS) compartments in MS, including the cerebrospinal fluid and white matter lesions. Also, it is now known that, in addition to entering the CNS, B cells can circulate into the periphery via a functional lymphatic system. Data suggest that the role of B cells in MS mainly involves their in situ activation in demyelinating lesions, leading to altered pro- and anti-inflammatory cytokine secretion, and a highly effective antigen-presenting cell function, resulting in activation of memory or naïve T cells. Clinically, B cell-depleting agents show significant efficacy in MS. In addition, many disease-modifying therapies (DMTs) traditionally understood to target T cells are now known to influence B cell number and function. One of the earliest DMTs to be developed, glatiramer acetate (GA), has been shown to reduce the total frequency of B cells, plasmablasts, and memory B cells. It also appears to promote a shift toward reduced inflammation by increasing anti-inflammatory cytokine release and/or reducing pro-inflammatory cytokine release by B cells. In the authors' opinion, this may be mediated by cross-reactivity of B cell receptors for GA with antigen (possibly myelin basic protein) expressed in the MS lesion. More research is required to further characterize the role of B cells and their bidirectional trafficking in the pathogenesis of MS. This may uncover novel targets for MS treatments and facilitate the development of B cell biomarkers of drug response.
EVALuna2:35207

Impact of plantaris ligamentous tendon - Olewnik, Łukasz; Karauda, Piotr; Gonera, Bartosz; Kurtys, Konrad; Tubbs, R. Shane; Paulsen, Friedrich; Szymański, Rafał; Polguj, Michał (Scientific Reports, 2021)
There are countless morphological variations among the muscles, tendons, ligaments, arteries, veins and nerves of the human body, many of which remain undescribed. Anatomical structures are also subject to evolution, many disappearing and others continually emerging. The main goal of this pilot study was to describe a previously undetected anatomical structure, the plantaris ligamentous tendon, and to determine its frequency and histology. Twenty-two lower limbs from 11 adult cadavers (11 left, and 11 right) fixed in 10% formalin were examined. The mean age of the cadavers at death was 60.1 years (range 38–85). The group comprised six women and five men from a Central European population. All anatomical dissections of the leg and foot area accorded with the pre-established protocol. Among the 22 lower limbs, the PLT was present in 16 (72.7%) and absent in six (27.3%). It originated as a strong fan-shaped ligamentous tendon from the superior part of the plantaris muscle, the posterior surface of the femur and the lateral aspect of the knee joint capsule. It inserted to the ilio-tibial band. Histologically, a tendon and ligament were observed extending parallel to each other. A new anatomical structure has been found, for which the name plantaris ligamentous tendon is proposed. It occurs around the popliteal region between the plantaris muscle, the posterior surface of the femur, and the ilio-tibial band.
CRIS-Team Scopus Importer:2021-03-19

Impact of polishing system on surface roughness of different ceramic surfaces after various pretreatments and bracket debonding - Jungbauer, Rebecca; Liebermann, Anja; Hammer, Christian; Edelhoff, Daniel; Proff, Peter; Stawarczyk, Bogna (Clinical Oral Investigations, 2023)
Objective: Evaluating various polishing methods after bracket debonding and excessive attachment material removal for different ceramics and pretreatments. Material and methods: Zirconia (ZrO2), leucite (LEU) and lithium disilicate (LiSi) specimens were pretreated with a) silica coated alumina particles (CoJet); LEU and LiSi additionally with b) hydrofluoric acid (HF), c) Monobond Etch&Prime (MEP), d) silicium carbide grinder (SiC) before bracket bonding, shearing off, ARI evaluation, excessive attachment material removal and polishing with i) Sof-Lex Discs (Soflex), ii) polishing paste (Paste), iii) polishing set (Set). Before/after polishing surface roughness (Ra) was measured with a profilometer. Martens hardness parameter were also assessed. Results: Irrespective of pretreatment Ra of LEU increased the most, followed by LiSi and ZrO2 (p < 0.001, SiC: p = 0.012), in accordance with the measured Martens hardness parameter. CoJet/SiC caused greater roughness as HF/MEP (p < 0.001). The ZrO2 surface was rougher after polishing with Paste/Set (p < 0.001; p = 0.047). Ra improved in the LEU/CoJet, LEU/SiC and LiSi/SiC groups with Soflex/Set (p < 0.001), in the LiSi/CoJet and LEU/HF groups by Soflex (p = 0.003, p < 0.001) and worsened by Paste (p = 0.017, p < 0.001). Polishing of HF or MEP pretreated LiSi with Set increased Ra (p = 0.001, p < 0.001), so did Paste in the LEU/MEP group (p < 0.001). Conclusions: Paste couldn’t improve the surfaces. Soflex was the only method decreasing Ra on rough surfaces and not causing roughness worsening. Polishing of LEU/LiSi after MEP, LEU after HF pretreatment doesn´t seem to have any benefit. Clinical Relevance: To avoid long-term damage to ceramic restorations, special attention should be paid to the polishing method after orthodontic treatment.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Bracket debonding; Ceramics; Polishing; Pretreatment; Surface roughness

Impact of prolactin and prolactin-inducible protein (PIP) for dry eye disease - Juengert, Katharina; Paulsen, Friedrich; Garreis, Fabian (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Impact of Siponimod on Enteric and Central Nervous System Pathology in Late-Stage Experimental Autoimmune Encephalomyelitis - Weier, Alicia; Enders, Michael; Kirchner, Philipp; Ekici, Arif Bülent; Bigaud, Marc; Kapitza, Christopher; Wörl, Jürgen; Kuerten, Stefanie (International Journal of Molecular Sciences, 2022)
Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS). Although immune modulation and suppression are effective during relapsing-remitting MS, secondary progressive MS (SPMS) requires neuroregenerative therapeutic options that act on the CNS. The sphingosine-1-phosphate receptor modulator siponimod is the only approved drug for SPMS. In the pivotal trial, siponimod reduced disease progression and brain atrophy compared with placebo. The enteric nervous system (ENS) was recently identified as an additional autoimmune target in MS. We investigated the effects of siponimod on the ENS and CNS in the experimental autoimmune encephalomyelitis model of MS. Mice with late-stage disease were treated with siponimod, fingolimod, or sham. The clinical disease was monitored daily, and treatment success was verified using mass spectrometry and flow cytometry, which revealed peripheral lymphopenia in siponimod- and fingolimod-treated mice. We evaluated the mRNA expression, ultrastructure, and histopathology of the ENS and CNS. Single-cell RNA sequencing revealed an upregulation of proinflammatory genes in spinal cord astrocytes and ependymal cells in siponimod-treated mice. However, differences in CNS and ENS histopathology and ultrastructural pathology between the treatment groups were absent. Thus, our data suggest that siponimod and fingolimod act on the peripheral immune system and do not have pronounced direct neuroprotective effects.
CRIS-Team Scopus Importer:2022-12-09
Keywords: central nervous system; enteric nervous system; experimental autoimmune encephalomyelitis; fingolimod; multiple sclerosis; siponimod

Increased expression of the Th17-IL-6R/pSTAT3/BATF/Ror?T-axis in the tumoural region of adenocarcinoma as compared to squamous cell carcinoma of the lung - Balabko, Liubov; Andreev, Katerina; Burmann, Nadine; Schubert, Melanie; Mathews, Martina; Trufa, Denis; Reppert, Sarah; Rau, Tilmann; Schicht, Martin; Sirbu, Horia; Hartmann, Arndt; Finotto, Susetta (Scientific Reports, 2014)
Here we describe increased expression of IL6R in the tumoural region of lung tissue from patients affected by lung adenocarcinoma as compared to squamous cell lung carcinoma. Moreover, here we found increased IL6R in the tumour free part of the lung. By using a murine model of lung adenocarcinoma, we discovered that few lung tumour cells expressed IL-6R and CD4+CD25+Foxp-3+ T regulatory cells down-regulated IL-6R in the tumour bearing lungs. Downstream of IL-6R, the Th17 lineage-specification factors: Signal transducer and activator of transcription 3 (STAT3), Basic leucine zipper transcription factor, BATF and a protein encoded by the RORC in human (RAR-related orphan receptor C) (ROR?T), were also found induced in the tumoural region of lung tissue from patients affected by lung adenocarcinoma as compared to those carrying squamous cell carcinoma. Moreover, pSTAT3 protein was found phosphorylated and auto-phosphorylated in the tumoural region of patients with adeno cell carcinoma of the lung as compared to the tumoural region of patients with squamous cell carcinoma of the lung. Intranasal application of anti-IL-6R antibodies in a murine model of lung adenocarcinoma, induced T regulatory cell markers such as Foxp3, Ctla4, Icos, Il10, Il21, Folr4 and Lag3 and inhibited Rorc in lung adenocarcinoma.
EVALuna2:4416

INCREASE OF CORTICAL MICRO-CHANNELS (COMICS) AS A NEW FEATURE OF STRUCTURAL DAMAGE IN PAIENTS WITH RHEUMATOID ARTHRITIS - Werner, David; Simon, David; Englbrecht, Matthias; Stemmler, F.; Berlin, Andreas; Haschka, J.; Renner, Nina; Buder, Thomas; Rech, Jürgen; Engelke, Klaus; Hueber, Axel; Schett, Georg; et al. (2017)
EVALuna2:34454

Indications and possible limitations using medio-plantar plate systems in tarsometatarsal 1 fusions – A cadaveric study - Winter, Philipp; Klos, Kajetan; Lambert, Laura; Paulsen, Friedrich; Landgraeber, Stefan; Wagener, Joe (Annals of Anatomy-Anatomischer Anzeiger, 2023)
Background: The tarsometatarsal 1 arthrodesis is an adequate treatment for moderate to severe hallux valgus deformity and instability of the first ray. Plantar plating arthrodesis has been shown to provide better mechanical stability and fewer postoperative complications than screw fixation or medial plating. The medio-plantar plate is a new plate design for Lapidus arthrodesis. It could combine the biomechanical advantages of the plantar plate and the anatomical overview of a medial plate. However, the implanted material can cause irritation of the tibialis anterior, which in some cases may require removal of the material. The purpose of this study was to examine the possibility of tendon irritation following medio-plantar first tarsometatarsal joint arthrodesis using cadaveric specimens. Methods: The study involved the simulated surgical procedure of medio-plantar plate arthrodesis on 30 lower extremities. After the plates were fixed, a thorough examination of the feet was conducted to assess any tendon irritation and to determine a recommendation for placement of the medio-plantar plate based on the Olewnik classification. Results: Irritation of the tibialis anterior tendon components with the medio-plantar plate depends mainly on the anatomic norm variant, classified according to Olewnik et al. A medio-plantar plate is particularly recommended in TA tendon Olewnik type 3 and type 5. The positioning of a medio-plantar plate in Olewnik type 1 and type 2 tendons depends on the anatomic fit of the medio-plantar plate and the bony configuration of the TMT 1 joint. A large portion of the TA tendon must be detached, so a different plate design may be preferred in these patients. Conclusions: TMT 1 arthrodesis with medio-plantar plating of the first tarsometatarsal joint should be performed considering the anatomic TA tendon variations. Level of evidence: Level V, Expert Opinion includes Case Reports and Technique Tips.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Hallux valgus; Lapidus; Medio-plantar plate; Plantar plate; Tarsometatarsal arthrodesis; Tendon irritation; Tibialis anterior

INDUCIBLE MMP-3 EXPRESSION IN A STEROID-INDUCED MURINE MODEL OF GLAUCOMA - O'Callaghan, Jeffrey; Cassidy, Paul S.; Reina-Torres, Ester; Sherwood, Joseph; Humphries, Marian M.; Campbell, Matthew; O'Brien, Colm J.; Lütjen-Drecoll, Elke; Stamer, W. Daniel; Overby, Darryl R.; Humphries, Peter (2018)
EVALuna2:35309

Influence of psoriasin on VEGF-mediated corneal neovascularization - Garreis, Fabian; Beckenbauer, Eva; Schulte, Ulrike; Schicht, Martin; Hampel, Ulrike; Paulsen, Friedrich (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

In mammalian skeletal muscle, phosphorylation of TOMM22 by protein kinase CSNK2/CK2 controls mitophagy - Kravic, Bojana; Harbauer, Angelika B.; Romanello, Vanina; Simeone, Luca; Vögtle, F. Nora; Kaiser, Tobias; Straubinger, Marion; Huraskin, Danyil; Böttcher, Martin; Cerqua, Cristina; Martin, Eva Denise; Poveda-Huertes, Daniel; et al. (Autophagy, 2017)
In yeast, Tom22 the central component of the TOMM (translocase of outer mitochondrial membrane) receptor complex is responsible for the recognition and translocation of synthesized mitochondrial precursor proteins, and its protein kinase CK2-dependent phosphorylation is mandatory for TOMM complex biogenesis and proper mitochondrial protein import. In mammals, the biological function of protein kinase CSNK2/CK2 remains vastly elusive and it is unknown whether CSNK2-dependent phosphorylation of TOMM protein subunits has a similar role as that in yeast. To address this issue, we used a skeletal muscle-specific Csnk2b/Ck2?-conditional knockout (cKO) mouse model. Phenotypically, these skeletal muscle Csnk2b cKO mice showed reduced muscle strength and abnormal metabolic activity of mainly oxidative muscle fibers, which point towards mitochondrial dysfunction. Enzymatically, active muscle lysates from skeletal muscle Csnk2b cKO mice phosphorylate murine TOMM22, the mammalian ortholog of yeast Tom22, to a lower extent than lysates prepared from controls. Mechanistically, CSNK2-mediated phosphorylation of TOMM22 changes its binding affinity for mitochondrial precursor proteins. However, in contrast to yeast, mitochondrial protein import seems not to be affected in vitro using mitochondria isolated from muscles of skeletal muscle Csnk2b cKO mice. PINK1, a mitochondrial health sensor that undergoes constitutive import under physiological conditions, accumulates within skeletal muscle Csnk2b cKO fibers and labels abnormal mitochondria for removal by mitophagy as demonstrated by the appearance of mitochondria-containing autophagosomes through electron microscopy. Mitophagy can be normalized by either introduction of a phosphomimetic TOMM22 mutant in cultured myotubes, or by in vivo electroporation of phosphomimetic Tomm22 into muscles of mice. Importantly, transfection of the phosphomimetic Tomm22 mutant in muscle cells with ablated Csnk2b restored their oxygen consumption rate comparable to wild-type levels. In sum, our data show that mammalian CSNK2-dependent phosphorylation of TOMM22 is a critical switch for mitophagy and reveal CSNK2-dependent physiological implications on metabolism, muscle integrity and behavior.
EVALuna2:25775

Innervation of human superficial fascia - Fede, Caterina; Petrelli, Lucia; Pirri, Carmelo; Neuhuber, Winfried; Tiengo, Cesare; Biz, Carlo; De Caro, Raffaele; Schleip, Robert; Stecco, Carla (Frontiers in Neuroanatomy, 2022)
The superficial fascia has only recently been recognized as a specific anatomical structure. Furthermore, whereas it is actually recognized that the innervation of the deep/muscular fascia plays a key role in proprioception and nociception, there are very few studies that have analyzed these characteristics in the superficial fascia. In this work, our group analyzed two different anatomical districts (abdomen and thigh), from volunteer patients, undergoing surgery procedures. Each sample was processed for histological analysis by Hematoxylin&Eosin, and by immunohistochemistry stainings (in 5-micron-paraffin embedded section and in cryosectioned free floating samples), with antibodies specific for nerve fibers: S100 antibody for myelinating and non-myelinating Schwann cells, PGP9.5 antibody as pan-neuronal marker, tyrosine hydroxylase for autonomic innervation. The results revealed a huge innervation: the nervous structures were found above all around blood vessels and close to adipocytes, but they penetrated also in the connective tissue itself and are found in the midst of fibro-adipose tissue. The tissue is pervaded by both thin (mean diameter of 4.8 ± 2.6 μm) and large nerve fiber bundles of greater diameter (21.1 ± 12.2 μm). The ratio S100/TH positivity was equal to 2.96, with a relative percentage of autonomic innervation with of 33.82%. In the light of these findings is evident that the superficial fasciae have a clear and distinct anatomical identity and a specific innervation, which should be considered to better understand their role in thermoregulation, exteroception and pain perception. The knowledge of the superficial fascia may improve grading and developing of different manual approach for treatments of fascial dysfunctions, and the understanding of how some factors like temperature or manual therapies can have an impact on sensitivity of the fascia.
CRIS-Team Scopus Importer:2022-09-30
Keywords: autonomic innervation; hypodermis; innervation; nerve fibers; superficial fascia

Innervation of rat and human dura mater and pericranial tissues in the parieto-temporal region by meningeal afferents - Schüler, Markus; Neuhuber, Winfried; De Col, Roberto; Meßlinger, Karl (Headache, 2014)
To reinvestigate the innervation pattern of the dura mater of rat and human middle cranial fossa, the morpho-functional substrate of headache generation, and adjacent extracranial tissues with neuronal in vitro tracing.This study was initiated by recent structural and functional findings of meningeal afferent fibers which innervate the cranial dura mater and may project to extracranial tissues.Anterograde and retrograde neuronal in vitro tracing was made in formaldehyde fixed hemisected rat and human skulls. The fluorescent tracer DiI was applied to proximally cut meningeal nerves in rat and to distal branches of the spinosus nerve in human calvaria lined by dura mater. After several weeks, the dura mater and deep extracranial tissues were examined with fluorescence microscopy.In addition to a network of meningeal nerve fibers, several fiber bundles were observed, leaving the skull through emissary canals and fissures to innervate the pericranial temporal, parietal, and occipital periosteum. Traced fibers were seen spreading into deep layers of the temporal and upper neck muscles. Retrograde neuronal tracing revealed labeled cell bodies exclusively in the mandibular and maxillary division of the rat trigeminal ganglion, and centrally projecting fibers were identified in the spinal trigeminal tract. Electron microscopy of the cross-sected spinosus nerve showed myelinated and unmyelinated axons with similar numbers in human and rat.We conclude that a proportion of meningeal afferents innervates extracranial tissues like periosteum and pericranial muscles via collaterals projecting through the skull. These afferents may be nociceptive, some may subserve proprioceptive functions. The finding of extracranial projections of meningeal afferents may be important for our understanding of extracranial impacts on headache generation and therapy.
EVALuna2:2445

Innervation pattern of the preocular human central retinal artery - Bergua, Antonio; Kapsreiter, Markus; Neuhuber, Winfried; Reitsamer, Herbert A.; Schroedl, Falk (Experimental Eye Research, 2013)
The central retinal artery (CRA) is the main vessel for inner retinal oxygen and nutrition supply. While the intraocular branches lack autonomic innervation, the innervation pattern of the extra-ocular part of this vessel along its course within the optic nerve is poorly investigated. This part however is essential for maintenance of retinal blood supply, in physiological and pathological conditions. Therefore, the aim of this study was the characterization of the autonomic innervation of the preocular CRA in humans with morphological methods. Meeting the Declaration of Helsinki, eyes of body or cornea donors were processed for single or double immunohistochemistry against tyrosine hydroxilase (TH), dopamine-?-hydroxylase (DBH), choline acetyl-transferase (ChAT), vesicular acetylcholine transporter (VAChT), neuronal nitric oxide synthase (nNOS), calcitonin gene-related peptide (CGRP), substance P (SP), vasoactive intestinal polypeptide (VIP), and cytochemistry for NADPH-diaphorase (NADPH-d). For documentation, light-, fluorescence-, and confocal laser-scanning microscopy were used. TH and DBH immunoreactive nerve fibres were detected in the CRA vessel wall, although a distinct perivascular plexus was missing. Further, nerve fibres immunoreactive for ChAT and VAChT were found, while CGRP, SP, and VIP were not detected. NADPH-d staining revealed scattered nerve fibres in the adventitia of the CRA and in close vicinity; however, nNOS-immunostaining could not confirm this finding. The CRA receives adrenergic and cholinergic innervations, indicating sympathetic and parasympathetic components, respectively. Remarkably, a peptidergic primary afferent innervation was missing. Since clinical results suggest an autoregulation of intraretinal vessels, further studies are needed to clarify the impact of CRA innervation for retinal perfusion.
EVALuna2:4135

Innervation pattern of the unclosed detrusor muscle in classic bladder exstrophy: a study of patients with urothelial overexpression of nerve growth factor - Promm, Martin; Otto, Wolfgang; Götz, Stefanie; Burger, Maximilian; Müller, Karolina; Rubenwolf, Peter; Neuhuber, Winfried; Rösch, Wolfgang H. (Pediatric Surgery International, 2024)
Purpose: An overexpression of nerve growth factor (NGF) in the urothelium is discussed to lead to neuronal hyperinnervation of the bladder detrusor. The aim was to assess the sensory and sympathetic innervation of the detrusor in unclosed exstrophic bladders patients with known overexpression of NGF in the urothelium. Methods: Full-thickness bladder biopsies were prospectively obtained from 34 infants at delayed primary bladder closure between 01/2015 and 04/2020. The bladder biopsies were immunohistochemically stained with antibodies against S100, calcitonin gene-related peptide (anti-CGRP), Neurofilament 200 (anti-NF200), and tyrosine-hydroxylase (anti-TH). Specimens from 6 children with congenital vesicoureterorenal reflux (VUR) served as controls. Results: There was no statistically significant difference in nerve fiber density in any of the immunohistochemical assessments (anti-S100 [p = 0.210], anti-CGRP [p = 0.897], anti-NF200 [p = 0.897]), and anti-TH [p = 0.956]) between patients with BE and patients with VUR. However, we observed a trend toward lower nerve fiber densities in exstrophic detrusor. Conclusion: Overall our results showed an unharmed innervation pattern in this cohort but a lower density of nerve fibers in the detrusor compared to controls. Further studies in patients after successful primary closure are needed to clarify the potential impact of the urothelial overexpression of NGF modulating the innervation pattern in exstrophic bladders.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Bladder exstrophy-epispadias complex; Delayed procedure; Immunohistochemistry; Nerve growth factor; Urothelium

Insights into the Microstructural Origin of Brain Viscoelasticity - Reiter, Nina; Roy, Biswaroop; Paulsen, Friedrich; Budday, Silvia (Journal of Elasticity, 2021)
Mechanical aspects play an important role in brain development, function, and disease. Therefore, continuum-mechanics-based computational models are a valuable tool to advance our understanding of mechanics-related physiological and pathological processes in the brain. Currently, mainly phenomenological material models are used to predict the be- havior of brain tissue numerically. The model parameters often lack physical interpretation and only provide adequate estimates for brain regions which have a similar microstructure and age as those used for calibration. These issues can be overcome by establishing advanced constitutive models that are microstructurally motivated and account for regional heterogeneities through microstructural parameters. In this work, we perform simultaneous compressive mechanical loadings and microstruc- tural analyses of porcine brain tissue to identify the microstructural mechanisms that under- lie the macroscopic nonlinear and time-dependent mechanical response. Based on experimental insights into the link between macroscopic mechanics and cellular rearrangements, we propose a microstructure-informed finite viscoelastic constitutive model for brain tissue. We determine a relaxation time constant from cellular displacement curves and introduce hyperelastic model parameters as linear functions of the cell density, as determined through histological staining of the tested samples. The model is calibrated using a combination of cyclic loadings and stress relaxation experiments in compression. The presented consider- ations constitute an important step towards microstructure-based viscoelastic constitutive models for brain tissue, which may eventually allow us to capture regional material hetero- geneities and predict how microstructural changes during development, aging, and disease affect macroscopic tissue mechanics.
Keywords: Brain tissue; Finite viscoelasticity; Microstructure; Constitutive modeling; Parameter identification

Insulin-like factor 3 promotes wound healing at the ocular surface - Hampel, Ulrike; Klonisch, Thomas; Sel, Saadettin; Schulze, Ute; Paulsen, Friedrich (Endocrinology, 2013)
Tear fluid is known to contain many different hormones with relevance for ocular surface homeostasis. We studied the presence and functional role of insulin-like factor 3 (INSL3) and its cognate receptor RXFP2 (relaxin/insulin-like family peptide receptor 2) at the ocular surface and in tears. Expression of human INSL3 and RXFP2 was determined in tissues of the ocular surface and lacrimal apparatus; in human corneal (HCE), conjunctival (HCjE), and sebaceous (SC) epithelial cell lines; and in human tears by RT-PCR and ELISA. We investigated effects of human recombinant INSL3 (hrINSL3) on cell proliferation and cell migration and the influence of hrINSL3 on the expression of MMP2, -9, and -13 and TIMP1 and -2 was quantified by real-time PCR and ELISA in HCE, HCjE, and SC cells. We used a C57BL/6 mouse corneal defect model to elucidate the effect of topical application of hrINSL3 on corneal wound healing. INSL3 and RXFP2 transcripts and INSL3 protein were detected in all tissues and cell lines investigated. Significantly higher concentrations of INSL3 were detected in tears from male vs. female volunteers. Stimulation of HCE, HCjE, and SC with hrINSL3 significantly increased cell proliferation in HCjE and SC and migration of HCjE. Treatment with hrINSL3 for 24 hours regulated MMP2, TIMP1, and TIMP2 expression. The local application of hrINSL3 onto denuded corneal surface resulted in significantly accelerated corneal wound healing in mice. These findings suggest a novel and gender-specific role for INSL3 and cognate receptor RXFP2 signaling in ocular surface homeostasis and determined a novel role for hrINSL3 in corneal wound healing. Copyright © 2013 by The Endocrine Society.
CRIS-Team Scopus Importer:2022-08-05

Integration of the musculature in the course "functional anatomy of the locomotor system"-Preparing medical students for the dissection course - Hammer, Christian; Paulsen, Friedrich; Burger, Pascal H. M.; Scholz, Michael (Annals of Anatomy-Anatomischer Anzeiger, 2016)
PURPOSE: To enhance the efficacy of the preclinical first-year course for medical and dental students 'functional anatomy of the locomotor system' (demo course) which serves as a preparation for the dissection course at the Friedrich-Alexander University of Erlangen-Nürnberg, Germany. METHODS: The muscular system was integrated into the curriculum of the demo course. Moreover, the number of tutors was increased from around 5 to 15 for approximately 120 students. A detailed course agenda, which had been lacking hitherto, was developed for each course day. Extensive preparation and briefing of course tutors was introduced. Self-prepared questionnaires were applied to compare student attitudes towards the demo course before and after the restructuring process. Surveys were conducted at the end of the unchanged demo course, at the end of the dissection course in the following term (same students) and at the end of the restructured demo course. RESULTS: The mark given for overall course quality improved from 3 ("satisfactory") to 2 ("good"). The students felt significantly better prepared for the dissection course after the restructuring process, although they perceived the work load as more challenging in relation to the limited time available. They assessed the new course as better structured and stated that the muscular system had been important for the functional comprehension of the locomotor system. CONCLUSIONS: According to student opinion, the attempt to improve the demo course quality by providing a detailed course agenda and enhanced tutelage had been successful. As expected, the musculature is critical to functional understanding of the locomotor system.
EVALuna2:35354

Intensity of side effects of topical glaucoma medication and its influence on adherence behavior in patients with glaucoma - Yu, Alice L.; Weise, Stefanie; Welge-Lüssen, Ulrich-Christoph (Clinical Ophthalmology, 2014)
The aim of this study was to investigate the intensity of side effects that patients attribute to their topical glaucoma medication and their relationship to adherence behavior.This was a questionnaire-based study of 123 glaucoma patients at a university eye clinic in Erlangen, Germany. An initial questionnaire asked about patient demographic data, the treatment plan, and intensity of side effects, and included Adherence to Refills and Medication Scale 2 (ARMS2) and visual analog scale (VAS-AD) scores. In a follow-up questionnaire, the treatment plan, intensity of side effects, ARMS2, and VAS-AD were reanalyzed.Most patients reported having few side effects, although only 20% said that they had no symptoms suggestive of side effects at all. The patients showed good adherence behavior on both the ARMS2 and VAS-AD scores, which were stable over time. The intensity of side effects experienced in the previous 7 days did not correlate with adherence scores and had no predictive value for adherence.This study could not detect any significant influence of the subjectively experienced intensity of side effects on patients' adherence behavior. However, we believe that a simple and clear treatment plan with few side effects is still preferred by most patients.
EVALuna2:21198

Interface morphology and gas production by a refractive 347 nm ultraviolet femtosecond laser: Comparison with established laser systems - Hammer, Christian; Kunert, Kathleen S.; Zhang, Yao; Loerner, Johannes; Wuelner, Christian; Rothuber, Elia L.; Paulsen, Friedrich; Seiler, Theo (Journal of Cataract and Refractive Surgery, 2018)
PURPOSE: To evaluate gas production and interface quality after refractive lenticule creation. A new ultraviolet (UV) 347 nm femtosecond laser was compared with the FS200 and the Visumax lasers. SETTING: Department of Anatomy II, University of Erlangen-Nürnberg, Erlangen, Germany. DESIGN: Experimental study. METHODS: Refractive lenticules were created in 52 porcine corneas with the UV laser (n = 20), the Visumax laser (n = 20), and a modified FS200 laser (n = 12). Twelve corneas in each laser group were fixed immediately after lenticule creation to entrap the gas produced. Lenticule extraction was omitted. From 16 other corneas (UV and Visumax lasers; n = 8 each) -5.0 diopter (D) and -10.0 D lenticules were extracted. On lenticule extraction, a flap was created and lifted. In 12 additional corneas, a flap was cut using the FS200 laser and lifted afterward; laser in situ keratomileusis was performed on 8 of these samples. The corneas were processed for light microscopy (gas bubble 2-dimensional morphometry) and scanning electron microscopy (interface quality). RESULTS: The Visumax generated approximately one half as much gas as the FS200. The UV laser undercut the Visumax by another 50%. The interfaces created by the FS200 appeared smooth and without irregularities. The optical zone margin was always conspicuous in the Visumax samples but hardly discernible in the UV specimens. Slight irregularities and very small lenticule pieces were found occasionally in both groups. The UV interfaces appeared slightly rougher than the Visumax interfaces. CONCLUSIONS: Ultraviolet laser lenticule extraction seems promising. The interface quality was similar to that of the clinical Visumax system while gas production was reduced significantly.
EVALuna2:35302

Internal vascular anatomy of the human lacrimal gland: A protocol based on cadaver dissection and three-dimensional micro-computed tomography - Singh, Swati; Chopra, Prakshi; Necker, Fabian; Scholz, Michael; Liphardt, Anna-Maria; Schuster, Louis; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2024)
Purpose: To evaluate the feasibility of studying the vascular supply of the orbital and palpebral lobes of the human lacrimal gland using micro-computed tomography (micro-CT) and microscopic dissection. Methods: The lacrimal gland artery of a fresh parasagittalized cadaver head (male, aged 76 years) was infused with a lead oxide-latex mixture near the occipital pole of the gland. The entire lacrimal gland was imaged using micro-CT and 3D cinematic rendering (CR) and then dissected under a surgical microscope. Results: Micro-CT and CR images showed well-demarcated internal vascular branches of the lacrimal artery and their distribution within the orbital and palpebral lobes. The entire course of the artery and its branches could be visualized by CR and microscopic dissection, with the former showing better spatial orientation and finer branching. The main artery runs along the free edge of the aponeurosis of the levator palpebrae superior muscle and lies in the isthmus portion of the gland (between the orbital and palpebral lobes). The branches of the main lacrimal artery include one branch to the orbital adipose tissue just before entering the gland, two branches to the orbital lobe (medial and lateral), and two branches to the palpebral lobe (medial and lateral). The main artery terminates as palpebral and orbital lobe branches in the lateral half of the lacrimal gland. Conclusion: Latex and contrast-enhanced micro-CT is very well suited to visualize the vascular anatomy of the lacrimal artery within the gland. A large number of lacrimal gland examinations using the method presented here are required to demonstrate and understand the variability of the vascular anatomy of the human lacrimal gland.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Anatomy; CT; Dry eye disease; Lacrimal artery; Lacrimal gland

Interstitial cells of Cajal: Crucial for the development of megacolon in human Chagas' disease? - Jabari, Samir; Da Silveira, Alexandre B.M.; De Oliveira, Enio; Quint, Karl; Wirries, André; Neuhuber, Winfried; Brehmer, Axel (Colorectal Disease, 2013)
Aim: Megacolon, chronic dilation of a colonic segment,is accompanied by extensive myenteric neuron loss. However, this fails to explain unequivocally the formation of megacolon. We aimed to study further enteric structures that are directly or indirectly involved in colonic motility. Method: From surgically removed megacolon segments of seven Chagasic patients, three sets of cryosections from oral, megacolonic and anal zones were immunohistochemically quadruple-stained for smooth-muscle actin (SMA), synaptophysin (SYN, for nerve fibres), S100 (glia) and c-Kit (interstitial cells of Cajal, ICCs). Values of area measurements were related to the appropriate muscle layer areas and these proportions were compared with those of seven non-Chagasic control patients. Results: Whereas nerve and glia profile proportions did not mirror unequivocally the changes of Chagasic colon calibre (nondilation/dilation/nondilation), the proportions of SMA (i.e. muscle tissue density) and c-Kit (i.e. ICC density) did so: they decreased from the oral to the megacolonic segment but increased to the anal zones (muscle tissue density: control 68.3%, oral 54.3%, mega 42.1%, anal 47.6%; ICC-density: control 1.8%, oral 1.1%, mega 0.4, anal 0.8%). Conclusion: Of the parameters evaluated, muscle tissue and ICC densities may be involved in the formation of Chagasic megacolon, although the mechanism of destruction cannot be deduced. © 2013 The Association of Coloproctology of Great Britain and Ireland.
Keywords: Chagasic megacolon; Enteric glia; Enteric nervous system; Interstitial cells of Cajal; Neurodegeneration; Smooth muscle density

INTRAARTICULAR MICRO CHANNELS OF MCP JOINTS INCREASE DURING DEVELOPMENT OF RHEUMATOID ARTHRITIS - Werner, David; Simon, David; Rech, Jürgen; Haschka, J.; Buder, Thomas; Neuhuber, Winfried; Schett, Georg; Hueber, Axel; Kleyer, Arnd (2015)
EVALuna2:34457

Intramuscular innervation of plantaris muscle evaluated using a modified Sihler's staining protocol — Proposal for a new classification - Olewnik, Ł.; Karauda, P.; Gonera, B.; Kurtys, K.; Haładaj, R.; Tubbs, R. Shane; Paulsen, Friedrich; Ramón Sanudo, J.; Polguj, M. (Annals of Anatomy-Anatomischer Anzeiger, 2020)
Purpose: The plantaris muscle is a morphologically variable structure with regard to both its origin and insertion, and the course of the tendon. We here determined the pattern of branching and distribution of intramuscular nerves of the plantaris muscle to determine its usability for autologous transplantation. No information exists on the innervation of the plantaris muscle using Sihler's staining technique, and hence its intramuscular nerves. The main purpose of the work is to determine the pattern of branching and distribution of the intramuscular nerves of the plantaris muscle. Is the plantaris muscle a good transplant candidate? Materials and methods: Eighty lower limbs from cadavers (40 left, 40 right, 40 male, 40 female, age range 41–94 years) were fixed in 10% formalin solution and examined macroscopically as well as morphometrically with regard to the innervation pattern of the respective plantaris muscle. Afterwards Sihler's staining was used in all 80 plantaris muscles to identify the exact distribution of the muscular branch originating from the main nerve trunk in the muscle belly. Results: Two patterns of branching and nerve distribution could be intensified in the plantaris muscle: Type I, with a single pattern entire up to the muscle and then divided into superior and inferior intramuscular branches.; type II with a double innervation pattern (superior and inferior). The superior and inferior pattern were not connected to each other. Conclusion: The plantaris muscle reveals variability with two different innervation patterns. Type II is ideally suited for autologous transplantation. New classifications of innervation are desirable for individual muscles rather than a generalized approach.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Innervation; Nerve; Planteris muscle; Sihler's staining

Intravascular Large B-Cell Lymphoma: A Review with a Focus on the Prognostic Value of Skin Involvement - Breakell, Thomas; Waibel, Heidi; Schliep, Stefan; Ferstl, Barbara; Erdmann, Michael; Berking, Carola; Heppt, Markus (Current Oncology, 2022)
Intravascular large B-cell lymphoma (IVLBCL) is an aggressive Non-Hodgkin lymphoma (NHL) characterised by the presence of neoplastic lymphoid cells within small-and medium-sized blood vessels. According to the clinical presentation, the current WHO classification distinguishes the ‘classic’ (formerly ‘Western’) from a hemophagocytic syndrome-associated (formerly ‘Asian’) variant. A third ‘cutaneous’ variant has been proposed, characterised by a good prognosis and unique clinical features. While laboratory findings can hint at diagnosis, symptoms are rather nonspecific, and deep skin biopsy supported by further measures such as bone marrow aspiration and positron emission tomography-computed tomography scanning is needed to make a definite diagnosis. Treatment is comprised of anthracycline-based chemotherapy supplemented with rituximab and central nervous system prophylaxis. While there are various prognostic models for NHL, only one is specific to IVLBCL, which does not sufficiently represent some patient groups, especially regarding the lack of differentiation within the patient collective with skin involvement. This underlines the necessity for the establishment of further prognostic models in particular for IVLBCL patients with cutaneous manifestations.
CRIS-Team Scopus Importer:2022-05-13
Keywords: dermato-oncology; intravascular large B-cell lymphoma; IVLBCL; prognostic model; R-CHOP; skin cancer

Intrinsic choroidal neurons in the chicken eye: Chemical coding and synaptic input - Stübinger, Karin; Brehmer, Axel; Reitsamer, Herbert; Nickla, Debora; Schrödl, Falk; et al. (Histochemistry and Cell Biology, 2010)
Intrinsic choroidal neurons (ICNs) exist in some primates and bird species. They may act on both vascular and non-vascular smooth muscle cells, potentially influencing choroidal blood flow. Here, we report on the chemical coding of ICNs and eye-related cranial ganglia in the chicken, an important model in myopia research, and further to determine synaptic input onto ICN. Chicken choroid, ciliary, superior cervical, pterygopalatine, and trigeminal ganglia were prepared for double or triple immunohistochemistry of calcitonin gene-related peptide (CGRP), choline acetyltransferase (ChAT), dopamine-β-hydroxylase, galanin (GAL), neuronal nitric oxide synthase (nNOS), somatostatin (SOM), tyrosine hydroxylase (TH), vasoactive intestinal polypeptide (VIP), vesicular monoamine-transporter 2 (VMAT2), and α-smooth muscle actin. For documentation, light, fluorescence, and confocal laser scanning microscopy were used. Chicken ICNs express nNOS/VIP/GAL and do not express ChAT and SOM. ICNs are approached by TH/VMAT2-, CGRP-, and ChAT-positive nerve fibers. About 50% of the pterygopalatine ganglion neurons and about 9% of the superior cervical ganglion neurons share the same chemical code as ICN. SOM-positive neurons in the ciliary ganglion are GAL/NOS negative. CGRP-positive neurons in the trigeminal ganglion lack GAL/SOM. The neurochemical phenotype and synaptic input of ICNs in chicken resemble that of other bird and primate species. Because ICNs lack cholinergic markers, they cannot be readily incorporated into current concepts of the autonomic nervous system. The data obtained provide the basis for the interpretation of future functional experiments to clarify the role of these cells in achieving ocular homeostasis. © Springer-Verlag 2010.
Keywords: Blood flow; Immunohistochemistry; Myopia; Nitric oxide

Intrinsic choroidal neurons in the duck eye receive sympathetic input: Anatomical evidence for adrenergic modulation of nitrergic functions in the choroid - Schrödl, Falk; Tines, Roland; Brehmer, Axel; et al. (Cell and Tissue Research, 2001)
Intrinsic choroidal neurons (ICN) in the duck eye form an intramural ganglionic plexus that may subserve complex integrative functions. A key feature of such ganglia is an innervation by sympathetic postganglionic neurons. The present study was thus aimed at determining the sympathetic postganglionic innervation of ICN. Choroids were processed for double immunofluorescence labelling with the following markers: tyrosine-hydroxylase (TH)/nitric oxide synthase (nNOS), TH/galanin (GAL), dopamine-β-hydroxylase (DBH)/vasoactive intestinal polypeptide (VIP), TH/DBH and DBH/α-smooth-muscle actin (αSMA), and for triple immunofluorescence labelling with VIP/DBH/TH. Epifluorescence and confocal laser scanning microscopy were used for evaluation. Immunoperoxidase staining for TH or DBH in combination with NADPH-diaphorase histochemistry was applied for electron microscopy. ICN spread over the entire choroid but were concentrated in an equatorial zone passing obliquely from naso-cranial to temporocaudal. More than 80% of nNOS-positive ICN showed close appositions of TH/DBH-immunoreactive varicose nerve fibres at the light-microscopic level, as could be confirmed by confocal laser scanning microscopy. Ultrastructurally, these appositions could be defined as both synapses or close contacts without synaptic specialisation. Vascular and non-vascular smooth muscle fibres also received TH/DBH-immunopositive innervation. Our findings suggest that most ICN receive a sympathetic input that might modulate their nitrergic effects upon vascular and non-vascular smooth muscle fibres in the choroid and that they may have more complex functions than merely being a simple parasympathetic relay.
Keywords: Cairina moschata (Aves); Confocal microscopy; Duck; Electron microscopy; Nitric oxide; Parasympathetic nerve; Sympathetic nerve

Intrinsic choroidal neurons in the human eye: Projections, targets, and basic electrophysiological data - Schrödl, Falk; De Laet, Ann; Tassignon, Marie-Jose; Van Bogaert, Pierre-Paul; Brehmer, Axel; Timmermans, Jean-Pierre; et al. (Investigative Ophthalmology & Visual Science, 2003)
PURPOSE. The chemical coding of intrinsic choroidal neurons (ICNs) has features in common with extrinsic fibers (e.g., from the pterygopalatine ganglion) making it impossible to assess whether a neuronal nitric oxide synthase (nNOS)/vasoactive intestinal polypeptide (VIP)-immunoreactive nerve fiber is of intrinsic or extrinsic origin. Neurobiotin injections into single neurons allow the visualization of projections of these cells and the determination of the origin of target innervation. Thus, this technique was used in the present study to help characterize the organization of the ICN in the human eye. METHODS. ICNs were visualized with the fluorescent vital dye 4-Di-2-ASP. Electrophysiological properties were determined by means of intracellular recordings. The impaled neurons were iontophoretically filled with neurobiotin. After fixation, immunohistochemistry for neuronal nitric oxide synthase (nNOS), α-smooth muscle actin, and calcitonin gene-related peptide (CGRP) was conducted. RESULTS. ICN processes were traced over distances of up to 2.612 μm. They were found in the immediate vicinity of other nNOS-positive or -negative ICNs and were also found apposed to smooth muscle fibers (vascular and stromal nonvascular). CGRP-positive fibers forming boutons were observed closely associated with ICNs. Electrophysiological recording showed phasic firing without slow afterhyperpolarization, no spontaneous activity, an input resistance of 136 ± 73 Mω, and a membrane time constant of 7 ± 1 ms. CONCLUSIONS. Apart from the first functional characterization of ICNs, this study provided more precise evidence of reciprocal ICN-to-ICN contacts and innervation of both choroidal nonvascular and vascular smooth muscle. The presented technique offers promising perspectives to further investigate the function of ICNs in ocular homeostasis.

Intrinsic neurons in the duck choroid are contacted by CGRP-immunoreactive nerve fibres: Evidence for a local pre-central reflex arc in the eye - Schrödl, Falk; Schweigert, Matthias; Brehmer, Axel; Neuhuber, Winfried (Experimental Eye Research, 2001)
Intrinsic choroidal neurons represent peripherally displaced autonomic nerve cells supposed to work as a local integrative network similar to the enteric nervous system, to control choroidal vasculature and stromal smooth muscle. A typical feature of such intramural neuronal networks is the innervation by primary afferent collaterals expressing peptides, e.g. CGRP. The present study was aimed at determining primary afferent contacts on nitrergic intrinsic choroidal neurons (ICN) in the duck eye. In addition, a sympathetic innervation of ICN was assessed. Choroids were immunohistochemically processed for the following markers: Neuronal nitric oxide synthase (nNOS), galanin (GAL), calcitonin gene-related peptide (CGRP), and tyrosine hydroxylase (TH). For evaluation, fluorescence as well as confocal laser scanning microscopy were used. For electron microscopy, immunoperoxidase staining for CGRP in combination with NADPH-diaphorase histochemistry was applied. ICN immunoreactive for nNOS or GAL spread over the entire choroid, although they were concentrated in an equatorial zone passing obliquely from naso-cranial to temporo-caudal. About 40% of ICN showed dose relationships with CGRP-immunoreactive nerve fibres, originating most likely in the trigeminal ganglion, as seen in the fluorescence and confocal laserscanning microscope. These appositions could be ultrastructurally defined as both synapses and close contacts without synaptic specialization. Some ICN endowed with CGRP-positive fibres also received TH-immunoreactive boutons. CGRP-immunoreactive profiles were also detected in close relationship to choroidal non-vascular smooth muscle cells and collagen fibres connected to them. In many instances, they were intercalated between smooth muscle cells and processes of ICN forming triads. These results suggest that ICN, similar to other intramural autonomic systems integrate signals from trigeminal primary afferent collaterals. The 'sensory' terminals of these primary afferents may be located in the anterior eye segment but also within the smooth muscle stroma of the choroid itself. Thus, ocular homeostasis may be regulated via intraocular pre-central reflexes which are probably subject to sympathetic modulation. © 2001 Academic Press.
Keywords: Confocal laserscanning microscopy; Electron microscopy; Nitric oxide; Parasympathetic nerve; Sympathetic nerve; Trigeminal primary afferents

Introducing the Foveola lunata, an anatomical landmark of the wrist - Wozniak, Slawomir; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2023)
The lunate foveola is often the starting point of a cystic swelling called a "ganglion". To make the anatomy of this region more relevant to the needs of clinicians and more accessible to students, we propose to introduce the term lunate foveola (Foveola lunata) on the dorsal side of the wrist just distal to the os lunatum. The easily located foveola will help in the examination of the wrist to more easily understand the anatomy of the wrist and facilitate the examination of patients with wrist injuries when an injury to the lunate (Os lunatum) is suspected.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Carpal bones; Lunate foveola; Lunate injury; Perilunate dislocation; Wrist

Inverse identification of region-specific hyperelastic material parameters for human brain tissue - Hinrichsen, Jan; Reiter, Nina; Bräuer, Lars; Paulsen, Friedrich; Käßmair, Stefan; Budday, Silvia (Biomechanics and modeling in mechanobiology, 2023)
The identification of material parameters accurately describing the region-dependent mechanical behavior of human brain tissue is crucial for computational models used to assist, e.g., the development of safety equipment like helmets or the planning and execution of brain surgery. While the division of the human brain into different anatomical regions is well established, knowledge about regions with distinct mechanical properties remains limited. Here, we establish an inverse parameter identification scheme using a hyperelastic Ogden model and experimental data from multi-modal testing of tissue from 19 anatomical human brain regions to identify mechanically distinct regions and provide the corresponding material parameters. We assign the 19 anatomical regions to nine governing regions based on similar parameters and microstructures. Statistical analyses confirm differences between the regions and indicate that at least the corpus callosum and the corona radiata should be assigned different material parameters in computational models of the human brain. We provide a total of four parameter sets based on the two initial Poisson’s ratios of 0.45 and 0.49 as well as the pre- and unconditioned experimental responses, respectively. Our results highlight the close interrelation between the Poisson’s ratio and the remaining model parameters. The identified parameters will contribute to more precise computational models enabling spatially resolved predictions of the stress and strain states in human brains under complex mechanical loading conditions.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Finite element method; Finite hyperelasticity; Human brain tissue; Ogden model; Parameter identification

Inverse identification of region-specific hyperelastic material parameters for human brain tissue - Hinrichsen, Jan; Reiter, Nina; Bräuer, Lars; Paulsen, Friedrich; Käßmair, Stefan; Budday, Silvia (Biomechanics and Modeling in Mechanobiology, 2023)
The identification of material parameters accurately describing the region-dependent mechanical behavior of human brain tissue is crucial for computational models used to assist, e.g., the development of safety equipment like helmets or the planning and execution of brain surgery. While the division of the human brain into different anatomical regions is well established, knowledge about regions with distinct mechanical properties remains limited. Here, we establish an inverse parameter identification scheme using a hyperelastic Ogden model and experimental data from multi-modal testing of tissue from 19 anatomical human brain regions to identify mechanically distinct regions and provide the corresponding material parameters. We assign the 19 anatomical regions to nine governing regions based on similar parameters and microstructures. Statistical analyses confirm differences between the regions and indicate that at least the corpus callosum and the corona radiata should be assigned different material parameters in computational models of the human brain. We provide a total of four parameter sets based on the two initial Poisson’s ratios of 0.45 and 0.49 as well as the pre- and unconditioned experimental responses, respectively. Our results highlight the close interrelation between the Poisson’s ratio and the remaining model parameters. The identified parameters will contribute to more precise computational models enabling spatially resolved predictions of the stress and strain states in human brains under complex mechanical loading conditions.<br

Investigation of general and cytoskeletal markers to estimate numbers and proportions of neurons in the human intestine - Ganns, Daniela; Schrödl, Falk; Brehmer, Axel; et al. (Histology and Histopathology, 2006)
An important requirement in pathological diagnostics in the human enteric nervous system (ENS) is the estimation of the total numbers of neurons and of proportions of distinct subpopulations. In this study, we compared the suitability of two suggested panneuronal markers, cuprolinic blue (CB) and anti-Hu-protein (HU), for staining and counting human myenteric neurons in wholemounts, derived from small and large intestinal samples. Furthermore, the proportional expression of three cytoskeletal intermediate filaments, α-internexin (IN), neurofilament 200 (NF) and peripherin (PE), was correlated with both CB and HU. In 8 CB- and HU-stained wholemounts, 93.3% of all neurons were double labeled, 3.3% of neurons were stained only with CB whereas 3.3% were immuno-stained only for HU. Thus, both markers were comparably reliable in representing the putative total human myenteric neuron population in our material. The wholemounts double stained for IN/CB or IN/HU revealed between 56.2 and 71.5% of neurons to be IN-reactive. Between 42.8 and 50.9% of neurons were immunoreactive for NF whereas 53.9 to 62.4% of neurons were reactive for PE. Although our sample number was too small to allow final conclusions, we suggest that the variations in proportions of intermediate filament expression we observed may be due to individual circumstances rather than to correlation with age or region. The proportions of neurons positive for IN, NF or PE but unstained by CB histochemical or HU immunohistochemical techniques was between 0 and 2.2%. We conclude that both CB and HU techniques are suitable methods for representation of almost all myenteric neurons in the human gut and that the differential expression of the cytoskeletal proteins investigated has to be included in the classification of enteric neurons in pathological diagnostics of human gastrointestinal diseases.
Keywords: Enteric nervous system; Gut; Innervation; Intermediate filaments

Investigation of magnetically driven passage of magnetic nanoparticles through eye tissues for magnetic drug targeting - Zahn, Diana; Klein, Katja; Radon, Patricia; Berkov, Dmitry; Erokhin, Sergey; Nagel, Edgar; Eichhorn, Michael; Wiekhorst, Frank; Dutz, Silvio (Nanotechnology, 2020)
This paper elucidates the feasibility of magnetic drug targeting to the eye by using magnetic nanoparticles (MNPs) to which pharmaceutical drugs can be linked. Numerical simulations revealed that a magnetic field gradient of 20 T m-1 seems to be promising for dragging magnetic multicore nanoparticles of about 50 nm into the eye. Thus, a targeting magnet system made of superconducting magnets with a magnetic field gradient at the eye of about 20 T m-1 was simulated. For the proof-of-concept tissue experiments presented here the required magnetic field gradient of 20 T m-1 was realized by a permanent magnet array. MNPs with an optimized multicore structure were selected for this application by evaluating their stability against agglomeration of MNPs with different coatings in water for injections, physiological sodium chloride solution and biological media such as artificial tear fluid. From these investigations, starch turned out to be the most promising coating material because of its stability in saline fluids due to its steric stabilization mechanism. To evaluate the passage of MNPs through the sclera and cornea of the eye tissues of domestic pigs (Sus scrofa domesticus), a three-dimensionally printed setup consisting of two chambers (reservoir and target chamber) separated by the eye tissue was developed. With the permanent magnet array emulating the magnetic field gradient of the superconducting setup, experiments on magnetically driven transport of the MNPs from the reservoir chamber into the target chamber via the tissue were performed. The resulting concentration of MNPs in the target chamber was determined by means of quantitative magnetic particle spectroscopy. It was found that none of the tested particles passed the cornea, but starch-coated particles could pass the sclera at a rate of about 5 ng mm-2 within 24 h. These results open the door for future magnetic drug targeting to the eye.
CRIS-Team Scopus Importer:2020-10-16
Keywords: magnetic drug targeting; magnetic field gradient; magnetic nanoparticles; magnetic particle spectroscopy

In vitro effects of benzalkonium chloride and prostaglandins on human meibomian gland epithelial cells - Rath, Anca; Eichhorn, Michael; Traeger, Katharina; Paulsen, Friedrich; Hampel, Ulrike (Annals of Anatomy-Anatomischer Anzeiger, 2019)
Purpose: Benzalkonium chloride is the most widely used preservative in ophthalmic topical solutions. The aim of this study was to investigate the influence of BAC as a single substance or as a component of several commercially available ophthalmic solutions on meibomian gland epithelial cells in vitro.
CRIS-Team WoS Importer:2019-04-18

In vitro effects of docosahexaenoic and eicosapentaenoic acid on human meibomian gland epithelial cells - Hampel, Ulrike; Krüger, Magret; Kunnen, Carolina; Garreis, Fabian; Willcox, Mark; Paulsen, Friedrich (Experimental Eye Research, 2015)
To investigate the effect of ?-3 fatty acids on human meibomian gland epithelial cells (HMGECs, cell line) in vitro. HMGECs were stimulated with docosahexaenoic acid (DHA) or combinations with eicosapentaenoic acid (EPA) and acetyl sialic acid (ASA). Sudan III fat staining, viability and proliferation assays, electric cell-substrate impedance sensing, real-time PCR for gene expression of cyclooxygenase-2 and 15-lipoxygenase and ELISAs for resolvin D1 (RvD1), IFN?, TNF? and IL-6 were applied. Lipid droplet accumulation and viability was increased by 100 ?M DHA in the presence or absence of EPA in serum cultured HMGECs. In contrast, HMGECs cultured with DHA and EPA under serum-free conditions showed minimal lipid accumulation, decreased proliferation and viability. Normalized impedance was significantly reduced in serum-free cultured HMGECs when stimulated with DHA and EPA. HMGECs cultured in serum containing medium showed increased normalized impedance under DHA and EPA stimulation compared to DHA or EPA alone or controls. IL-6 and IFN? were downregulated in HMGECs treated for 72 h with DHA and EPA. In general, TNF?, IFN? and IL-6 levels were decreased after 72 h compared to 24 h in serum containing medium with or without DHA or EPA. The concentration of RvD1 was elevated 2-fold after DHA treatment. Cyclooxygenase-2 gene expression decreased compared to controls during DHA stimulation after 72 h. Treatment with DHA and ASA revealed a decreased 15-lipoxygenase gene expression which was reduced after three days of DHA incubation. DHA and EPA supplementation affected HMGECs in vitro and supported anti-inflammatory effects by influencing cytokine levels, decreasing COX-2 expression and increasing the production of RvD1.
EVALuna2:4441

In vitro effects of sex hormones in human meibomian gland epithelial cells - Schröder, Antje; Abrar, Daniel; Hampel, Ulrike; Schicht, Martin; Paulsen, Friedrich; Garreis, Fabian (Experimental Eye Research, 2016)
Meibomian gland dysfunction (MGD) is considered the most common cause of dry eye disease (DED). Sex hormones seem to play a role in the pathogenesis of MGD although their involvement is not completely understood. Therefore, in the present study we evaluated the effect of dihydrotestosteron (DHT) and estradiol (β-Est) on an immortalized human meibomian gland epithelial cell line (HMGEC). Protein expression of sex hormone receptors in HMGEC was investigated by western blot. Ultrastructural morphology, Sudan III lipid staining, cell proliferation as well as vitality assays were performed. Furthermore, expression of MGD-associated markers for keratinization (hornerin, involucrin and CK6), proliferation (CK5 and CK14) and lipid synthesis (fatty acid synthase and stearoyl-CoA desaturase) were analyzed by real time RT-PCR. Western blot revealed presence of androgen receptor (AR), estrogen receptors α and -β (ERα, ERβ) and progesterone receptor (PR) in HMGEC. PR, ERα and ERβ expression was significantly induced under cultivation with serum, whereas sex hormones stimulation showed no further effect on protein expression of PR, ERα and ERβ. Our results showed no impact of MGD-associated sex hormones to cellular morphology and lipid accumulation in HMGEC. Cell proliferation was slightly induced through application of sex hormones and supplementation of calcium. However, both sex hormones and calcium altered gene expression of MGD-associated markers. Especially keratinization genes hornerin (HRNR) and cornulin (COR) were induced after application of sex hormones and calcium in serum-free cultivated HMGEC. This may promote keratinization processes that are associated with MGD. Further investigations are necessary to analyze the (hyper)keratinization processes that occur during MGD and using HMGEC as an in vitro model.
EVALuna2:35345

In-vivo B-cell activity predicts response to treatment with glatiramer acetate and interferons in patients with relapsing-remitting multiple sclerosis (RRMS) - Braune, Stefan; Tacke, Sabine; Ziemssen, Tjalf; Lehmann, Paul; Bergmann, Arnfin; Kürten, Stefanie (NEUROLOGY, 2020)
CRIS-Team WoS Importer:2020-08-21

Involvement of catecholaminergic neurons in motor innervation of striated muscle in the mouse esophagus - van der Keylen, Piet; Garreis, Fabian; Steigleder, Ruth; Sommer, Daniel; Neuhuber, Winfried; Wörl, Jürgen (Histochemistry and Cell Biology, 2016)
Enteric co-innervation is a peculiar innervation pattern of striated esophageal musculature. Both anatomical and functional data on enteric co-innervation related to various transmitters have been collected in different species, although its function remains enigmatic. However, it is unclear whether catecholaminergic components are involved in such a co-innervation. Thus, we examined to identify catecholaminergic neuronal elements and clarify their relationship to other innervation components in the esophagus, using immunohistochemistry with antibodies against tyrosine hydroxylase (TH), vesicular acetylcholine transporter (VAChT), choline acetyltransferase (ChAT) and protein gene product 9.5 (PGP 9.5), α-bungarotoxin (α-BT) and PCR with primers for amplification of cDNA encoding TH and dopamine-β-hydroxylase (DBH). TH-positive nerve fibers were abundant throughout the myenteric plexus and localized on about 14% of α-BT-labelled motor endplates differing from VAChT-positive vagal nerve terminals. TH-positive perikarya represented a subpopulation of only about 2.8% of all PGP 9.5-positive myenteric neurons. Analysis of mRNA showed both TH and DBH transcripts in the mouse esophagus. As ChAT-positive neurons in the compact formation of the nucleus ambiguus were negative for TH, the TH-positive nerve varicosities on motor endplates are presumably of enteric origin, although a sympathetic origin cannot be excluded. In the medulla oblongata, the cholinergic ambiguus neurons were densely supplied with TH-positive varicosities. Thus, catecholamines may modulate vagal motor innervation of esophageal-striated muscles not only at the peripheral level via enteric co-innervation but also at the central level via projections to the nucleus ambiguus. As Parkinson's disease, with a loss of central dopaminergic neurons, also affects the enteric nervous system and dysphagia is prevalent in patients with this disease, investigation of intrinsic catecholamines in the esophagus may be worthwhile to understand such a symptom.
EVALuna2:35349

Involvement of corneal epithelial cells in the Th17 response in an in vitro bacterial inflammation model - Arranz-Valsero, Isabel; Schulze, Ute; Contreras-Ruiz, Laura; García-Posadas, Laura; López-García, Antonio; Paulsen, Friedrich; Diebold, Yolanda (Molecular Vision, 2013)
Purpose: Staphylococcus aureus (SA) and Pseudomonas aeruginosa (PA) are frequent causes of bacterial keratitis, an inflammatory process that can lead to vision loss. We used a human corneal epithelial (HCE) cell line to study the Th17 inflammatory pathway, including interleukin (IL-) 6, IL-17, and associated receptors, in response to stimulation by SA and PA culture supernatants. Methods: Cells of the HCE cell line were exposed to either SA or PA supernatants in dilutions of 1:100 or 1:50, or to human recombinant IL-17A (20 ng/ml). Cell culture supernatants were collected at 6, 24, and 72 h, and protein and RNA were isolated. Expression of cytokine (IL-6, IL-17A), receptor (sIL-6R, IL-17RA), and mediator (soluble glycoprotein [sgp] 130, MIP3α) proteins and mRNAs were determined with enzyme-linked immunosorbent assay, immunohistochemistry, western blotting, and real-time, reverse-transcription quantitative PCR. In addition, IL-17RA was localized by transmission electron microscopy after immunogold labeling. Results: Basal secretion of IL-6 and IL-17A by HCE cells occurred in a time-dependent manner. Expression of IL-6 was significantly enhanced by SA stimulation, but not by PA stimulation. IL-6 mRNA expression was higher in the control and SA-stimulated cells at 6 and 24 h, but not at 72 h. In the PA-stimulated cells, mRNA levels were significantly lower than the controls at 6 and 24 h. Expression of sIL-6R was not altered by SA or PA supernatants, but sgp130 expression was greater than controls at 6 h, less than controls at 24 h, and the same as controls at 72 h. HCE cells secreted IL-17A in a time-dependent manner that was not altered by stimulation; however, the IL-17A mRNA levels were lower than those of the controls at 6 h. With immunohistochemistry, IL-17RA was localized in perinuclear vesicles and in the cytosol and membranes of HCE cells. IL-17RA was also present in the epithelial cells from human ocular surface tissues. As quantified with western blotting, expression of IL-17RA was unchanged in HCE cells stimulated by SA or PA supernatants. Conclusions: HCE cells react to bacterial inflammation by enhancing the secretion of IL-6 and by regulating the proinflammatory response with differential secretion of sgp130. Under normal conditions, HCE cells and ocular surface tissues express IL-17RA. Additionally, HCE cells express IL-17RA after bacterial stimulation. All of these molecules are involved in the Th17 differentiation pathway, suggesting that corneal epithelial cells may act as indirect participants in the Th17 signaling pathway. © 2013 Molecular Vision.
CRIS-Team Scopus Importer:2022-08-05

Isolation and characterization of extracellular vesicles (EVs) from ovarian cancer ascites - a feasibility study - Reinhardt, N.; Lettau, M.; Hugendieck, G.; Neumann, S.; Rogmans, C.; Weimer, J. P.; Floerkemeier,; Arnold, N.; Arnold, Philipp; Janssen, O.; Maass, N.; Bauerschlag, D. O.; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Isolation and Investigation of Presumptive Murine Lacrimal Gland Stem Cells - Ackermann, Philipp; Hetz, Susann; Dieckow, Julia; Schicht, Martin; Richter, Anja; Kruse, Charli; Schroeder, Insa S.; Jung, Matthias; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2015)
Aqueous tear deficiency due to lacrimal gland insufficiency is one of the major causes of dry eye disease. In severe cases, such as Sjogren's syndrome, Stevens-Johnson syndrome, or ocular cicatricial pemphigoid, therapy with artificial tears is often insufficient to relieve severe discomfort, prevent progressive ocular surface disease, or enable visual rehabilitation by corneal transplantation. Cell or organ generation from stem cells, resulting in tear-like secretion, presents an option as a suitable alternative treatment. To obtain deeper insights into lacrimal gland stem cells we analyzed murine lacrimal glands for markers of pluripotency, self-renewal, and differentiation.A special, patented technique with mechanical and enzymatic digestion was used to generate high numbers of cells in vitro from murine lacrimal glands. These presumptive "murine lacrimal gland stem cells" ("mLGSCs") can be propagated as monolayer cultures over multiple passages. By means of RT-PCR, Western blot, and immunohistochemistry, markers of pluripotency and differentiation were demonstrated. Hanging drop culture was used to build organoid bodies from mLGSCs to investigate their spontaneous differentiation in three-dimensional culture with histology, immunohistochemistry, and transmission electron microscopy methods.Isolated mLGSCs were cultured over more than 65 passages. Murine lacrimal gland stem cells expressed markers of pluripotency such as Nanog, Sox2, Kruppel-like factor 4 (Klf4), as well as early-lineage markers of all three germ layers. Three-dimensional culture of these cells revealed their ability to differentiate into various cell types.Our results suggest that mLGSCs were isolated and cultured successfully. These cells have the ability to differentiate into all three germ layers. The results provide further insights into lacrimal gland stem cell physiology for engineering of a lacrimal gland construct to treat severe cases of tear deficiency in the future.
EVALuna2:4443

Is the increased presence of CD8 T-lymphocytes related to serotonin levels in Chagas disease? - de Freitas, Michelle A.R.; De Oliveira, Enio; De Oliveira, F.; Jabari, Samir; Brehmer, Axel; Da Silveira, Alexandre B.M. (Colorectal Disease, 2015)

JoVE Video Dataset - Polykandriotis, Elias; Himmler, Marcus; Mansouri, Shirin; Ruppe, Florian; Grüner, Jasmin; Bräuer, Lars; Schubert, Dirk W.; Horch, Raymund E. (2022)
With the evolution of suture materials, there has been a change in paradigms in primary and secondary tendon repair. Improved mechanical properties allow more aggressive rehabilitation and earlier recovery. However, for the repair to hold against higher mechanical demands, more advanced suturing and knotting techniques must be assessed in combination with those materials. In this protocol, the use of polytetrafluoroethylene (PTFE) as a suture material in combination with different repair techniques was investigated. In the first part of the protocol, both linear tension strength and elongation of knotted against not-knotted strands of three different materials used in flexor tendon repair were evaluated. The three different materials are polypropylene (PPL), ultra-high molecular weight polyethylene with a braided jacket of polyester (UHMWPE), and polytetrafluoroethylene (PTFE). In the next part (ex vivo experiments with cadaveric flexor tendons), the behavior of PTFE using different suture techniques was assessed and compared with PPL and UHMWPE. This experiment is comprised of four steps: harvesting of the flexor tendons from fresh cadaveric hands, transection of the tendons in a standardized manner, tendon repair by four different techniques, mounting, and measurement of the tendon repairs on a standard linear dynamometer. The UHMWPE and PTFE showed comparable mechanical properties and were significantly superior to PPL in terms of linear traction strength. Repairs with four- and six-strand techniques proved stronger than two-strand techniques. Handling and knotting of PTFE are a challenge due to very low surface friction but fastening of the four- or six-strand repair is comparatively easy to achieve. Surgeons routinely use PTFE suture material in cardiovascular surgery and breast surgery. The PTFE strands are suitable for use in tendon surgery, providing a robust tendon repair so that early active motion regimens for rehabilitation can be applie
Keywords: Polytetrafluoroethylene; PTFE; Suture Material; Tendon Surgery; Mechanical Properties; Flexor Tendon Repair; Linear Tension Strength; Cadaveric Upper Limb; Incision; A1 Pulley; Flexor Digitorum Profundus; Tendon Retractor; Traction

Lacrimal and meibomian gland evaluation in dry eye disease: A mini-review - Singh, Swati; Donthineni, Pragnya Rao; Srivastav, Saumya; Jacobi, Christina; Basu, Sayan; Paulsen, Friedrich (Indian Journal of Ophthalmology, 2023)
Lacrimal and meibomian glands contribute to the aqueous and lipid components of tear film, respectively. Their evaluation remains central to diagnosing and managing dry eye disease (DED). The review discusses the differences and reliability of various diagnostic tests and commercially available devices used for DED diagnosis. Slit-lamp-based techniques are direct palpebral lobe and tear flow assessment, Schirmer test, meibum quality and expressibility, and evaluation of tear meniscus height. Non-invasive tear meniscus height (TMH), tear break-up time (TBUT), lipid layer thickness (LLT), and meibography are machine-based diagnostic tests. The structure-function correlation of the tear-producing glands gives more comprehensive details than either information alone. Many devices are available in the market, which make DED diagnosis an easy feat, but the tests should be interpreted keeping in mind the intra-observer and inter-observer repeatability. Also, the tear film displays a huge variability as per the environmental conditions and impact of blinking. Hence, the examiner should be well versed with the techniques and repeat the test two to three times to obtain an average reading, which is more reliable. The recommended sequence of tests for diagnosing DED is a dry eye questionnaire, TMH, LLT, NIBUT (FBUT if non-invasive test is unavailable but should be performed after osmolarity), tear osmolarity, meibography, and ocular surface staining. Invasive tests such as Schirmer should be performed after the non-invasive tear film diagnostic testing.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Dry eye disease; lacrimal gland; lipid layer thickness; meibomian glands; tear break-up time; tear meniscus height

Lacrimal gland activity in lacrimal drainage obstruction: exploring the potential cross-talk between the tear secretion and outflow. - Singh, Swati; Srivastav, Saumya; Bothra, Nandini; Paulsen, Friedrich; Ali, Mohammad Javed (British Journal of Ophthalmology, 2024)
PURPOSE: To investigate the effects of lacrimal drainage obstructions on the lacrimal gland activity and if there exists a potential link between the two. METHODS: Direct assessment of the lacrimal gland activity from the palpebral lobe was performed in consecutive patients diagnosed with unilateral primary acquired nasolacrimal duct obstruction (PANDO), along with Ocular Surface Disease Index (OSDI), non-invasive tear break up time (NIBUT; Oculus K5M), tear meniscus height and Schirmer I. The primary outcome measure was the difference in the tear flow rate between the eye with PANDO and the contralateral uninvolved eye. RESULTS: Thirty patients (median age, 45.5 years; 25 females) with unilateral PANDO had epiphora for a mean duration of 20 months. The mean OSDI score was 6.3. NIBUT (mean 11.56 vs 11.58 s; p=0.49) and Schirmer I values (mean 18.83 vs 19.4 mm; p=0.313) were not significantly different between PANDO and non-PANDO eyes. The morphology of the palpebral lobe (size 29.3 vs 28.6 mm2, p=0.41) and the number of lacrimal ductular openings (median 2 vs 2.5) were similar between the two eyes. The mean tear flow from the lacrimal glands of the PANDO side was significantly reduced compared with the contralateral uninvolved side (0.8 vs 0.99 µL/min; p=0.014)). CONCLUSION: Tear flow rate from palpebral lobes of patients with unilateral lacrimal outflow obstruction shows a significant reduction compared with the contralateral side. The potential ways of communications between the tear drainage and the tear production mechanisms need to be explored further.
EVALuna2:545152

Lacrimal gland targeted therapies for refractory epiphora: quantitative changes in the gland activity - Singh, Swati; Bothra, Nandini; Ali, Mohammad Javed (Orbit, 2023)
Purpose: To investigate the effect of botulinum toxin (BTX) and partial orbital lobe dacryoadenectomy (POLD) on the main lacrimal gland functions using the direct assessment of its secretory activity. Methods: A pilot study involving 14 subjects (mean age, 42.16 years) with proximal bicanalicular block (n = 9) or complete punctal effacement (n = 5) received either intraglandular 2.5 units of BTX (n = 7) or underwent the POLD procedure (n = 7). Dynamic assessment of tear secretion from the palpebral lobes was performed as per standard protocols. The parameters studied included Schirmer I, changes in the glandular outflow, and the neurosensory secretory lag. Results: Schirmer I values showed a mean reduction of 5.25 mm (range, 2–8 mm) following BTX injection, and mean tear flow decreased from 1.46 (Formula presented.) to 1.11 (Formula presented.) (P = 0.15). The POLD group showed a significant mean reduction of 0.45 (Formula presented.) in mean tear flow at 1 month (P = 0.03) and 0.32 (Formula presented.) at 3 months of follow-up (P = 0.20). However, there was no statistically significant change of the Schirmer values in the POLD group at 3 months. Conclusion: Direct assessment of lacrimal gland function can be used to monitor changes following the gland therapies. Although POLD shows a significant reduction in short term, significant surgical improvisation would be needed for it to be effective in long term. A larger study is ongoing to further our understanding.
CRIS-Team Scopus Importer:2023-05-26
Keywords: botulinum toxin; canalicular obstruction; dacryoadenectomy; epiphora; Lacrimal gland

LAP proteins are localized at the post-synaptic membrane of neuromuscular junctions and appear to modulate synaptic morphology and transmission - Kravic, Bojana; Huraskin, Danyil; Frick, Alexander; Jung, Jasmin; Redai, Veronika; Palmisano, Ralf; Marchetto, Sylvie; Borg, Jean-Paul; Mei, Lin; Hashemolhosseini, Said (Journal of Neurochemistry, 2016)
Erbin, Lano, Scribble, and Densin-180 belong to LAP (leucine-rich repeats and PDZ domain) adaptor proteins involved in cell signaling pathways. Previously, we identified Erbin, Lano, and Scribble, but not Densin-180, in muscle cells, where they are involved in regulating the aggregation of nicotinic acetylcholine receptors in vitro. Here, we analyzed their cellular localization at the neuromuscular junction (NMJ) in skeletal muscles of mice. Erbin, Lano, and Scribble were significantly accumulated at NMJs and localized in different synaptic cells. Moreover, we used mouse mutants to analyze the role of Erbin at the NMJ. We used two Erbin mutant mouse strains that either completely lack Erbin protein (Erbin(null/null) ) or express a truncated Erbin mutant where the carboxy-terminal PDZ domain is replaced by ?-galactosidase (Erbin(?C/?C) ) thereby abolishing its interaction with ErbB receptor tyrosine kinases. Neither the lack of the PDZ domain of Erbin, nor its complete absence interfered with the general localization of LAP proteins at NMJs, but Lano and Scribble transcript levels were up-regulated in homozygous Erbin-null muscles. Furthermore, grip strength was reduced and neural transmission impaired in homozygous aged Erbin-null but not Erbin-?C mice. Erbin-null skeletal muscles did not reveal any conspicuous impairment of the muscle fiber. Localization of other NMJ marker proteins was not affected either. Quantitative 3D morphometry showed that NMJs of Erbin-null muscles were significantly smaller and fragmented in the soleus. We speculate that Erbin, Lano, and Scribble act at the post-synaptic membrane of NMJs in a concerted fashion to regulate nicotinic acetylcholine receptors cluster morphology and neural transmission. Cover Image for this issue: doi: 10.1111/jnc.13340.
EVALuna2:4995

Larger Descemetorhexis to Improve Graft Adhesion in Descemet Membrane Endothelial Keratoplasty Does Not Cause Postoperative Peripheral Corneal Edema - Tourtas, Theofilos; Weller, Julia M.; Bachmann, Björn; Kruse, Friedrich (Eye & Contact Lens-Science and Clinical Practice, 2015)
To evaluate the incidence of peripheral corneal edema after Descemet membrane endothelial keratoplasty (DMEK) with respect to the size of the descemetorhexis.A single-center retrospective review of data of 200 consecutive DMEK surgeries for Fuchs endothelial dystrophy was performed. Forty-eight eyes of 47 patients were enrolled in this study based on the presence of a peripheral zone of free denuded stroma between the margin of the graft and the host's Descemet membrane (DM) (group A) or a peripheral overlap between the graft and the host's DM (group B). In group A (n=26 eyes), the diameter of the descemetorhexis was approximately 10 mm, whereas in group B (n=22 eyes), the diameter was approximately 6 mm. Both groups received an 8-mm graft. Main outcome measures included peripheral corneal thickness (PCT) at 4 mm from the center, central corneal thickness (CCT), central-to-peripheral thickness ratio (CPTR), and endothelial cell density (ECD).Mean preoperative PCT±SD in group A was 728±52 ?m and in group B was 708±49 ?m (P=0.192). Four weeks after DMEK, mean PCT±SD was 703±43 ?m in group A and 691±59 ?m in group B (P=0.368). Mean preoperative CCT±SD was 642±53 ?m and 627±58 ?m in groups A and B, respectively (P=0.306). There was no significant difference in CCT between groups A and B 4 weeks after surgery (P=0.268). Mean preoperative CPTR±SD in group A was 0.88±0.05 and in group B was 0.89±0.05 (P=0.934). Four weeks after DMEK, CPTR was not significantly different between groups A and B (P=0.893). There was no significant difference in ECD between groups A and B, before and at 4 weeks after DMEK (P=0.093 and P=0.831, respectively).A larger descemetorhexis in DMEK resulting in a peripheral small zone of denuded stroma does not increase the incidence of peripheral corneal edema as compared with a small descemetorhexis with overlapping DMs.
EVALuna2:21238

Leveraging medical imaging for medical education - A cinematic rendering-featured lecture - Binder, Johannes; Krautz, Christian; Engel, Klaus; Grützmann, Robert; Fellner, Franz A.; Burger, Pascal H.M.; Scholz, Michael (Annals of Anatomy-Anatomischer Anzeiger, 2018)
BACKGROUND: The integration of medical imaging into anatomical education offers advantages in understanding and learning. However, spatial orientation with conventional (2D) imaging data is challenging, and the students' ability to imagine structures in three dimensions is individual. In addition, the quality of current volume rendering methods is limited. OBJECTIVE: We tested Cinematic Rendering (CR), a novel visualization technique that provides photorealistic volume rendering, in the setting of an interactive anatomy lecture with first-year undergraduate medical and dental students. Our goal was to estimate the acceptance and positive effects CR adds to the subjects. METHODS: A total of 120 students were surveyed with specifically designed self-assessment questionnaires on the use of CR as a tool in anatomical education. RESULTS: Of 120 participating students (87 medical and 33 dental) a large majority of 95.9% (Q3) experienced CR as helpful to understand anatomy better. Overall a large majority of the students experienced CR as helpful for learning and understanding, 85% saw an improvement in anatomical education through the integration of CR (Q3-6) and could also imagine using CR as a self-study tool on an electronic device. CONCLUSION: Our undergraduate medical and dental students experienced CR as a beneficial tool for anatomical education in the chosen setting (lecture) and see further opportunities for the sensible use of this technique. Future research on the topic should include other application possibilities as well.
EVALuna2:35343

Localization of receptors for calcitonin-gene-related peptide to intraganglionic laminar endings of the mouse esophagus: peripheral interaction between vagal and spinal afferents? - Horling, Lena; Bunnett, N. W.; Meßlinger, Karl; Neuhuber, Winfried; Raab, Marion (Histochemistry and Cell Biology, 2014)
The calcitonin-gene-related peptide (CGRP) receptor is a heterodimer of calcitonin-receptor-like receptor (CLR) and receptor-activity-modifying protein 1 (RAMP1). Despite the importance of CGRP in regulating gastrointestinal functions, nothing is known about the distribution and function of CLR/RAMP1 in the esophagus, where up to 90 % of spinal afferent neurons contain CGRP. We detected CLR/RAMP1 in the mouse esophagus using immunofluorescence and confocal laser scanning microscopy and examined their relationship with neuronal elements of the myenteric plexus. Immunoreactivity for CLR and RAMP1 colocalized with VGLUT2-positive intraganglionic laminar endings (IGLEs), which were contacted by CGRP-positive varicose axons presumably of spinal afferent origin, typically at sites of CRL/RAMP1 immunoreactivity. This provides an anatomical basis for interaction between spinal afferent fibers and IGLEs. Immunoreactive CLR and RAMP1 also colocalized in myenteric neurons. Thus, CGRP-containing spinal afferents may interact with both vagal IGLEs and myenteric neurons in the mouse esophagus, possibly modulating motility reflexes and inflammatory hypersensitivity.
EVALuna2:2448

Locally renewing resident synovial macrophages provide a protective barrier for the joint - Culemann, Stephan; Grüneboom, Anika; Nicolás-Ávila, José Ángel; Weidner, Daniela; Lämmle, Katrin Franziska; Rothe, Tobias; Quintana, Juan A.; Kirchner, Philipp; Krljanac, Branislav; Eberhardt, Martin; Ferrazzi, Fulvia; Kretzschmar, Elke; et al. (Nature, 2019)
Macrophages are considered to contribute to chronic inflammatory diseases such as rheumatoid arthritis1. However, both the exact origin and the role of macrophages in inflammatory joint disease remain unclear. Here we use fate-mapping approaches in conjunction with three-dimensional light-sheet fluorescence microscopy and single-cell RNA sequencing to perform a comprehensive spatiotemporal analysis of the composition, origin and differentiation of subsets of macrophages within healthy and inflamed joints, and study the roles of these macrophages during arthritis. We find that dynamic membrane-like structures, consisting of a distinct population of CX3CR1+ tissue-resident macrophages, form an internal immunological barrier at the synovial lining and physically seclude the joint. These barrier-forming macrophages display features that are otherwise typical of epithelial cells, and maintain their numbers through a pool of locally proliferating CX3CR1− mononuclear cells that are embedded into the synovial tissue. Unlike recruited monocyte-derived macrophages, which actively contribute to joint inflammation, these epithelial-like CX3CR1+ lining macrophages restrict the inflammatory reaction by providing a tight-junction-mediated shield for intra-articular structures. Our data reveal an unexpected functional diversification among synovial macrophages and have important implications for the general role of macrophages in health and disease.
CRIS-Team Scopus Importer:2019-08-16

Long-Term Endurance Exercise in Humans Stimulates Cell Fusion of Myoblasts along with Fusogenic Endogenous Retroviral Genes In Vivo - Frese, Sebastian; Rübner, Matthias; Suhr, Frank; Konou, Thierry M.; Tappe, Kim A.; Toigo, Marco; Jung, Hans H.; Henke, Christine; Steigleder, Ruth; Strissel, Pamela; Hübner, Hanna; Beckmann, Matthias; et al. (PLoS ONE, 2015)
Myogenesis is defined as growth, differentiation and repair of muscles where cell fusion of myoblasts to multinucleated myofibers is one major characteristic. Other cell fusion events in humans are found with bone resorbing osteoclasts and placental syncytiotrophoblasts. No unifying gene regulation for natural cell fusions has been found. We analyzed skeletal muscle biopsies of competitive cyclists for muscle-specific attributes and expression of human endogenous retrovirus (ERV) envelope genes due to their involvement in cell fusion of osteoclasts and syncytiotrophoblasts. Comparing muscle biopsies from post- with the pre-competitive seasons a significant 2.25-fold increase of myonuclei/mm fiber, a 2.38-fold decrease of fiber area/nucleus and a 3.1-fold decrease of satellite cells (SCs) occurred. We propose that during the pre-competitive season SC proliferation occurred following with increased cell fusion during the competitive season. Expression of twenty-two envelope genes of muscle biopsies demonstrated a significant increase of putative muscle-cell fusogenic genes Syncytin-1 and Syncytin-3, but also for the non-fusogenic erv3. Immunohistochemistry analyses showed that Syncytin-1 mainly localized to the sarcolemma of myofibers positive for myosin heavy-chain isotypes. Cellular receptors SLC1A4 and SLC1A5 of Syncytin-1 showed significant decrease of expression in post-competitive muscles compared with the pre-competitive season, but only SLC1A4 protein expression localized throughout the myofiber. Erv3 protein was strongly expressed throughout the myofiber, whereas envK1-7 localized to SC nuclei and myonuclei. Syncytin-1 transcription factors, PPAR? and RXR?, showed no protein expression in the myofiber, whereas the pCREB-Ser133 activator of Syncytin-1 was enriched to SC nuclei and myonuclei. Syncytin-1, Syncytin-3, SLC1A4 and PAX7 gene regulations along with MyoD1 and myogenin were verified during proliferating or actively-fusing human primary myoblast cell cultures, resembling muscle biopsies of cyclists. Myoblast treatment with anti-Synycytin-1 abrogated cell fusion in vitro. Our findings support functional roles for ERV envelope proteins, especially Syncytin-1, contributing to cell fusion of myotubes.
EVALuna2:17549

Loss of beta ENaC Function in Meibomian Gland Produces Severe Sex-Biased Ocular Surface Diseases in Mice - Yu, Dongfang; Saini, Yogesh; Chen, Gang; Burns, Kimberlie A.; Dang, Hong; Davis, Richard; Randell, Scott H.; Esther, Charles R.; Paulsen, Friedrich; Boucher, Richard C. (2017)
EVALuna2:35333

Loss of CYLD accelerates melanoma development and progression in the Tg(Grm1) melanoma mouse model - de Jel, Miriam Martha; Schott, Mandy; Lamm, Susanne; Neuhuber, Winfried; Kuphal, Silke; Boßerhoff, Anja Katrin (Oncogenesis, 2019)
The deubiquitinase cylindromatosis (CYLD) is a well-known tumor suppressor, found to be down regulated in many cancer types including breast cancer, colon carcinoma and malignant melanoma. CYLD is suppressed in human melanoma cells by the transcriptional repressor SNAIL1 leading to an increase of their proliferative, invasive and migratory potential. To gain additional insights into the distinct function of this tumor suppressor gene a new mouse model Tg(Grm1)Cyld−/− was generated. Herewith, we demonstrate that Cyld-deficiency leads to earlier melanoma onset and accelerated tumor growth and metastasis in the GRM1 melanoma mouse model. First, RNA sequencing data revealed a potential role of CYLD in the regulation of genes involved in proliferation, migration and angiogenesis. Experiments using cell lines generated from both primary and metastatic melanoma tissue of Tg(Grm1) Cyld−/− and Tg(Grm1) Cyld+/+ mice confirmed that loss of CYLD enhances the proliferative and migratory potential, as well as the clonogenicity in vitro. Moreover, we could show that Cyld-knockout leads to increased vasculogenic mimicry and enhanced (lymph-) angiogenesis shown by tube formation assays, immunohistochemistry and mRNA expression analyses. In summary, our findings reveal new functional aspects of CYLD in the process of (lymph-) angiogenesis and demonstrate its importance in the early process of melanoma progression.
CRIS-Team Scopus Importer:2019-10-18

Loss of β Epithelial Sodium Channel Function in Meibomian Glands Produces Pseudohypoaldosteronism 1-Like Ocular Disease in Mice - Yu, Dongfang; Saini, Yogesh; Chen, Gang; Ghio, Andrew J.; Dang, Hong; Burns, Kimberlie A.; Wang, Yang; Davis, Richard M.; Randell, Scott H.; Esther, Charles R.; Paulsen, Friedrich; Boucher, Richard C. (American Journal of Pathology, 2018)
Human subjects with pseudohypoaldosteronism-1 because of loss-of-function mutations in epithelial sodium channel (ENaC) subunits exhibit meibomian gland (MG) dysfunction. A conditional βENaC MG knockout (KO) mouse model was generated to elucidate the pathogenesis of absent ENaC function in the MG and associated ocular surface disease. βENaC MG KO mice exhibited a striking age-dependent, female-predominant MG dysfunction phenotype, with white toothpaste-like secretions observed obstructing MG orifices at 7 weeks of age. There were compensatory increases in tear production but higher tear sodium and indexes of mucin concentration in βENaC MG KO mice. Histologically, MG acinar atrophy was observed with ductal enlargement and ductal epithelial hyperstratification. Inflammatory cell infiltration was observed in both MG and conjunctiva of βENaC MG KO mice. In older βENaC MG KO mice (5 to 11 months), significant ocular surface pathologies were noted, including corneal opacification, ulceration, neovascularization, and ectasia. Inflammation in MG and conjunctiva was confirmed by increased cytokine gene and protein expression and positive Ly-6B.2 immunostaining. Cell proliferation assays revealed lower proliferation rates of MG cells derived from βENaC MG KO than control mice, suggesting that βENaC plays a role in cell renewal of mouse MG. Loss of βENaC function resulted in MG disease and severe ocular surface damage that phenocopied aspects of human pseudohypoaldosteronism-1 MG disease and was sex dependent.
EVALuna2:35322

Low proliferation and differentiation capacities of adult hippocampal stem cells correlate with memory dysfunction in humans - Coras, Roland; Siebzehnrübl, Florian; Pauli, Elisabeth; Huttner, Hagen; Njunting, Marleisje; Kobow, Katja; Villmann, Carmen; Hahnen, Eric; Neuhuber, Winfried; Weigel, Daniel; Buchfelder, Michael; Stefan, Herrmann; et al. (Brain, 2010)
The hippocampal dentate gyrus maintains its capacity to generate new neurons throughout life. In animal models, hippocampal neurogenesis is increased by cognitive tasks, and experimental ablation of neurogenesis disrupts specific modalities of learning and memory. In humans, the impact of neurogenesis on cognition remains unclear. Here, we assessed the neurogenic potential in the human hippocampal dentate gyrus by isolating adult human neural stem cells from 23 surgical en bloc hippocampus resections. After proliferation of the progenitor cell pool in vitro we identified two distinct patterns. Adult human neural stem cells with a high proliferation capacity were obtained in 11 patients. Most of the cells in the high proliferation capacity cultures were capable of neuronal differentiation (53 +/- 13% of in vitro cell population). A low proliferation capacity was observed in 12 specimens, and only few cells differentiated into neurons (4 +/- 2%). This was reflected by reduced numbers of proliferating cells in vivo as well as granule cells immunoreactive for doublecortin, brain-derived neurotrophic factor and cyclin-dependent kinase 5 in the low proliferation capacity group. High and low proliferation capacity groups differed dramatically in declarative memory tasks. Patients with high proliferation capacity stem cells had a normal memory performance prior to epilepsy surgery, while patients with low proliferation capacity stem cells showed severe learning and memory impairment. Histopathological examination revealed a highly significant correlation between granule cell loss in the dentate gyrus and the same patient's regenerative capacity in vitro (r = 0.813; P < 0.001; linear regression: R-adjusted(2) = 0.635), as well as the same patient's ability to store and recall new memories (r = 0.966; P = 0.001; linear regression: R-adjusted(2) = 0.9). Our results suggest that encoding new memories is related to the regenerative capacity of the hippocampus in the human brain.
Keywords: stem cells; neurogenesis; hippocampus; memory; learning; epilepsy; doublecortin

LOXL1 deficiency in the lamina cribrosa as candidate susceptibility factor for a pseudoexfoliation-specific risk of glaucoma - Schlötzer-Schrehardt, Ursula; Hammer, Christian; Krysta, Anita W.; Hofmann-Rummelt, Carmen; Pasutto, Francesca; Sasaki, Takako; Kruse, Friedrich; Zenkel, Matthias (Ophthalmology, 2012)
To test the hypothesis that a primary disturbance in lysyl oxidase-like 1 (LOXL1) and elastin metabolism in the lamina cribrosa of eyes with pseudoexfoliation syndrome constitutes an independent risk factor for glaucoma development and progression.Observational, consecutive case series.Posterior segment tissues obtained from 37 donors with early and late stages of pseudoexfoliation syndrome without glaucoma, 37 normal age-matched control subjects, 5 eyes with pseudoexfoliation-associated open-angle glaucoma, and 5 eyes with primary open-angle glaucoma (POAG).Protein and mRNA expression of major elastic fiber components (elastin, fibrillin-1, fibulin-4), collagens (types I, III, and IV), and lysyl oxidase crosslinking enzymes (LOX, LOXL1, LOXL2) were assessed in situ by quantitative real-time polymerase chain reaction, (immuno)histochemistry, and light and electron microscopy. Lysyl oxidase-dependent elastin fiber assembly was assessed by primary optic nerve head astrocytes in vitro.Expression levels of elastic proteins, collagens, and lysyl oxidases in the lamina cribrosa.Lysyl oxidase-like 1 proved to be the major lysyl oxidase isoform in the normal lamina cribrosa in association with a complex elastic fiber network. Compared with normal and POAG specimens, lamina cribrosa tissues obtained from early and late stages of pseudoexfoliation syndrome without and with glaucoma consistently revealed a significant coordinated downregulation of LOXL1 and elastic fiber constituents on mRNA and protein level. In contrast, expression levels of collagens and other lysyl oxidase isoforms were not affected. Dysregulated expression of LOXL1 and elastic proteins was associated with pronounced (ultra)structural alterations of the elastic fiber network in the laminar beams of pseudoexfoliation syndrome eyes. Inhibition of LOXL1 interfered with elastic fiber assembly by optic nerve head astrocytes in vitro.The findings provide evidence for a pseudoexfoliation-specific elastinopathy of the lamina cribrosa resulting from a primary disturbance in LOXL1 regulation and elastic fiber homeostasis, possibly rendering pseudoexfoliation syndrome eyes more vulnerable to pressure-induced optic nerve damage and glaucoma development and progression.
EVALuna2:1645

Macular pigment optical density measured by heterochromatic modulation photometry - Huchzermeyer, Cord; Schlomberg, Juliane; Welge-Lüssen, Ulrich-Christoph; Berendschot, Tos T. J. M.; Pokorny, Joel; Kremers, Jan (PLoS ONE, 2014)
To psychophysically determine macular pigment optical density (MPOD) employing the heterochromatic modulation photometry (HMP) paradigm by estimating 460 nm absorption at central and peripheral retinal locations.For the HMP measurements, two lights (B: 460 nm and R: 660 nm) were presented in a test field and were modulated in counterphase at medium or high frequencies. The contrasts of the two lights were varied in tandem to determine flicker detection thresholds. Detection thresholds were measured for different R:B modulation ratios. The modulation ratio with minimal sensitivity (maximal threshold) is the point of equiluminance. Measurements were performed in 25 normal subjects (11 male, 14 female; age: 30±11 years, mean ± sd) using an eight channel LED stimulator with Maxwellian view optics. The results were compared with those from two published techniques - one based on heterochromatic flicker photometry (Macular Densitometer) and the other on fundus reflectometry (MPR).We were able to estimate MPOD with HMP using a modified theoretical model that was fitted to the HMP data. The resultant MPODHMP values correlated significantly with the MPODMPR values and with the MPODHFP values obtained at 0.25° and 0.5° retinal eccentricity.HMP is a flicker-based method with measurements taken at a constant mean chromaticity and luminance. The data can be well fit by a model that allows all data points to contribute to the photometric equality estimate. Therefore, we think that HMP may be a useful method for MPOD measurements, in basic and clinical vision experiments.
EVALuna2:21179

Malignancy going viral: ACE2 and TMPRSS2 expression in conjunctival neoplastic diseases - Grajewski, Rafael S.; Rokohl, Alexander C.; Becker, Martina; Paulsen, Friedrich; Heindl, Ludwig M. (Annals of Anatomy-Anatomischer Anzeiger, 2021)
CRIS-Team WoS Importer:2021-03-12

Matrix metalloproteinase-3 (MMP-3)-mediated gene therapy for glaucoma - O'Callaghan, Jeffrey; Delaney, Conor; O'Connor, Merissa; van Batenburg-Sherwood, Joseph; Schicht, Martin; Lütjen-Drecoll, Elke; Hudson, Natalie; Ni Dhubhghaill, Sorcha; Humphries, Peter; Stanley, Chris; Keravala, Annahita; Chalberg, Thomas; et al. (Science Advances, 2023)
Approximately 80 million people globally are affected by glaucoma, with a projected increase to over 110 million by 2040. Substantial issues surrounding patient compliance remain with topical eye drops, and up to 10% of patients become treatment resistant, putting them at risk of permanent vision loss. The major risk factor for glaucoma is elevated intraocular pressure, which is regulated by the balance between the secretion of aqueous humor and the resistance to its flow across the conventional outflow pathway. Here, we show that adeno-associated virus 9 (AAV9)-mediated expression of matrix metalloproteinase-3 (MMP-3) can increase outflow in two murine models of glaucoma and in nonhuman primates. We show that long-term AAV9 transduction of the corneal endothelium in the nonhuman primate is safe and well tolerated. Last, MMP-3 increases outflow in donor human eyes. Collectively, our data suggest that glaucoma can be readily treated with gene therapy-based methods, paving the way for deployment in clinical trials.
CRIS-Team Scopus Importer:2023-04-28

Mechanical characterization of human brain tissue - Budday, Silvia; Sommer, Gerhard; Birkl, Christoph; Langkammer, Christian; Haybaeck, Johannes; Kohnert, Julius; Bauer, Melanie; Paulsen, Friedrich; Steinmann, Paul; Kuhl, Ellen; Holzapfel, Gerhard A. (Acta Biomaterialia, 2017)
Mechanics are increasingly recognized to play an important role in modulating brain form and function. Computational simulations are a powerful tool to predict the mechanical behavior of the human brain in health and disease. The success of these simulations depends critically on the underlying constitutive model and on the reliable identification of its material parameters. Thus, there is an urgent need to thor- oughly characterize the mechanical behavior of brain tissue and to identify mathematical models that cap- ture the tissue response under arbitrary loading conditions. However, most constitutive models have only been calibrated for a single loading mode. Here, we perform a sequence of multiple loading modes on the same human brain specimen – simple shear in two orthogonal directions, compression, and tension – and characterize the loading-mode specific regional and directional behavior. We complement these three indi- vidual tests by combined multiaxial compression/tension-shear tests and discuss effects of conditioning and hysteresis. To explore to which extent the macrostructural response is a result of the underlying microstructural architecture, we supplement our biomechanical tests with diffusion tensor imaging and histology. We show that the heterogeneous microstructure leads to a regional but not directional depen- dence of the mechanical properties. Our experiments confirm that human brain tissue is nonlinear and vis- coelastic, with a pronounced compression-tension asymmetry. Using our measurements, we compare the performance of five common constitutive models, neo-Hookean, Mooney-Rivlin, Demiray, Gent, and Ogden, and show that only the isotropic modified one-term Ogden model is capable of representing the hyperelastic behavior under combined shear, compression, and tension loadings: with a shear modulus of 0.4–1.4 kPa and a negative nonlinearity parameter it captures the compression-tension asymmetry and the increase in shear stress under superimposed compression but not tension. Our results demonstrate that material parameters identified for a single loading mode fail to predict the response under arbitrary loading conditions. Our systematic characterization of human brain tissue will lead to more accurate com- putational simulations, which will allow us to determine criteria for injury, to develop smart protection sys- tems, and to predict brain development and disease progression.
Keywords: Human brain; Mechanical testing; Hyperelastic modeling; Mooney Rivlin model; Ogden model

Mechanisms, clinical profile and role of prostaglandin and prostamide analogues in antiglaucomatous therapy - Yu, A.; Welge-Lüssen, Ulrich-Christoph (Klinische Monatsblätter für Augenheilkunde, 2013)
Prostaglandin and prostamide analogues belong to a new substance group which came into the market in the 1990s. They have revolutionised antiglaucomatous therapy by their once-daily dosing regimen and fewer side effects. Today, prostaglandin and prostamide analogues are approved as first-line therapy for patients with primary open-angle glaucoma and ocular hypertension. They lower the intraocular pressure primarily by increasing the uveoscleral outflow. Recent investigations have shown that they also improve the trabecular outflow facility and thus the conventional outflow pathways. Prostaglandin and prostamide analogues are highly efficient in lowering the intraocular pressure, for which they are superior to other antiglaucomatous substance groups. In particular, they appear to have a good control of 24-hour intraocular pressure fluctuations by primarily improving the outflow pathways. Furthermore, they have less systemic side effects than ?-blockers. However, their use is often associated with higher costs. In case of undesirable events, they mostly present with ocular symptoms. Based on their good clinical profile, prostaglandin and prostamide analogues play an important role in the primary and additive therapy for glaucoma.
EVALuna2:21128

Mechanisms of mechanical load transfer through brain tissue - Reiter, Nina; Paulsen, Friedrich; Budday, Silvia (Scientific Reports, 2023)
Brain injuries are often characterized by diffusely distributed axonal and vascular damage invisible to medical imaging techniques. The spatial distribution of mechanical stresses and strains plays an important role, but is not sufficient to explain the diffuse distribution of brain lesions. It remains unclear how forces are transferred from the organ to the cell scale and why some cells are damaged while neighboring cells remain unaffected. To address this knowledge gap, we subjected histologically stained fresh human and porcine brain tissue specimens to compressive loading and simultaneously tracked cell and blood vessel displacements. Our experiments reveal different mechanisms of load transfer from the organ or tissue scale to single cells, axons, and blood vessels. Our results show that cell displacement fields are inhomogeneous at the interface between gray and white matter and in the vicinity of blood vessels—locally inducing significant deformations of individual cells. These insights have important implications to better understand injury mechanisms and highlight the importance of blood vessels for the local deformation of the brain’s cellular structure during loading.
CRIS-Team Scopus Importer:2023-06-09

Mediastinal anatomical landmarks, their variants and tips for video-assisted thoracoscopic navigation during oesophageal extirpation - Dydykin, Sergey; Paulsen, Friedrich; Khorobykh, Tatyana; Mishchenko, Natalya; Kapitonova, Marina; Gupalo, Sergey; Bogoyavlenskaya, Tatyana; Agadzhanov, Vadim; Salikhov, Pashad (Surgical and Radiologic Anatomy, 2021)
Purpose There is no systematic description of primary anatomical landmarks that allow a surgeon to reliably and safely navigate the superior and posterior mediastinum's fat tissue spaces near large vessels and nerves during video-assisted endothoracoscopic interventions in the prone position of a patient. Our aim was to develop an algorithm of sequential visual navigation during thoracoscopic extirpation of the esophagus and determine the most permanent topographic and anatomical landmarks allowing safe thoracoscopic dissection of the esophagus in the prone position. Methods The anatomical study of the mediastinal structural features was carried out on 30 human cadavers before and after opening the right pleural cavity. Results For thoracoscopic extirpation of the esophagus in the prone position, anatomical landmarks are defined, their variants are assessed, and an algorithm for their selection is developed, allowing their direct visualization before and after opening the mediastinal pleura. Conclusion The proposed algorithm for topographic and anatomical navigation based on the key anatomical landmarks in the posterior mediastinum provides safe performance of the video-assisted thoracoscopic extirpation of the esophagus in the prone position.
CRIS-Team WoS Importer:2021-09-03

Medical hypnosis as an effective intervention against test anxiety in first year medical students - Hammer, Christian; Scholz, Michael; Bischofsberger, Larissa; Paulsen, Friedrich; Burger, Pascal H. M. (PSYCHOTHERAPY AND PSYCHOSOMATICS, 2019)
CRIS-Team WoS Importer:2019-09-27

Messung der Dichte der Langerhans-Zellen als Verlaufsparameter bei Patienten mit Keratoconjunctivitis sicca unter topischer antiinflammatorischer Therapie mit Ciclosporin A 0,05% Augentropfen - Schneider, Eva; Paulsen, Friedrich; Jacobi, Christina (Klinische Monatsblätter für Augenheilkunde, 2020)
Background Keratoconjunctivitis sicca is one of the most common ocular diseases and is associated with a considerable decrease in the quality of life. It is accompanied by symptoms of discomfort, tear film instability, hyperosmolarity of the tear film, inflammation of the ocular surface and neurosensory abnormalities. It is still not clear yet if the density of Langerhans cells in the central cornea can be used for objective evaluation of the inflammation in the tear film and the ocular surface. Patients and Methods 47 patients (age 21â Š-â Š85 years, 13Â male and 34 female patients) with moderate to severe keratoconjunctivitis sicca (according to the DEWS criteria severity level 2â Š-â Š3) were enrolled in this prospective, clinical trial. Patients were treated for 3 months with topical anti-inflammatory therapy with cyclosporine 0,05% eye drops twice daily. The following parameters were examined: OSDI Score, tear break-up time (TBUT), Schirmer test with anaesthesia, lid-parallel conjunctival folds (LIPCOF), in-vivo confocal microscopy with HRT II and RCM for evaluation of Langerhans cell density in the central cornea, visual acuity, tear film osmolarity and Meibomian gland dysfunction (MGD). Results After anti-inflammatory treatment, there was a significant reduction in the density of Langerhans cells (p ≤ 0.001**), an increase in TBUT (p ≤ 0.001**), as well as a significant decrease in tear film osmolarity (p ≤ 0.05*) and OSDI Score (p ≤ 0 001**). Visual acuity, MGD and Schirmer test did not change significantly. Conclusions The results of this clinical trial show that topical anti-inflammatory therapy with cyclosporine A 0.05% eye drops in patients with moderate to severe keratoconjunctivitis sicca is effective in reducing inflammation of the ocular surface and the tear film, as well as in increasing the quality of life in these patients. Evaluation of Langerhans cell density in the central corneal epithelium by in vivo confocal microscopy is an effective objective diagnostic feature in monitoring anti-inflammatory therapy in patients with dry eye disease or other ocular surface pathologies.
CRIS-Team Scopus Importer:2020-06-05
Keywords: anti-inflammatory therapy; chronic inflammation; in-vivo confocal microscopy; Keratoconjunctivitis sicca; Langerhans cells; topical cyclosporine A 0; 05% therapy

Methylglyoxal causes pain and hyperalgesia in human through C-fiber activation - Düll, Miriam; Riegel, Kathrin; Tappenbeck, Julia; Ries, Vivien; Strupf, Marion; Fleming, Thomas; Sauer, Susanne; Namer, Barbara (Pain, 2019)
The endogenous metabolite methylglyoxal (MG) accumulates in diabetic patients with neuropathic pain. Methylglyoxal could be a mediator of diabetes-induced neuropathic pain through TRPA1 activation and sensitization of the voltage-gated sodium channel subtype 1.8. In this study, we tested the algogenic and sensitizing effect of MG in healthy human subjects using intracutaneous microinjections. The involvement of C fibers was assessed through selective A-fiber nerve block, axon-reflex-erythema, and through single nerve fiber recordings in humans (microneurography). Involvement of the transduction channels TRPA1 and TRPV1 in MG-induced pain sensation was investigated with specific ion channel blockers. We showed for the first time in healthy humans that MG induces pain, axon-reflex-erythema, and long-lasting hyperalgesia through the activation of C nociceptors. Predominantly, the subclass of mechano-insensitive C fibers is activated by MG. A fibers contribute only negligibly to the burning pain sensation. Selective pharmacological blockade of TRPA1 or TRPV1 showed that TRPA1 is crucially involved in MG-induced chemical pain sensation and heat hyperalgesia. In conclusion, the actions of MG through TRPA1 activation on predominantly mechano-insensitive C fibers might be involved in spontaneously perceived pain in diabetic neuropathy and hyperalgesia as well as allodynia.
CRIS-Team Scopus Importer:2019-10-25

Methylglyoxal modification of Na v 1.8 facilitates nociceptive neuron firing and causes hyperalgesia in diabetic neuropathy - Bierhaus, Angelika; Fleming, Thomas; Stoyanov, Stoyan; Leffler, Andreas; Babes, Alexandru; Neacsu, Cristian; Sauer, Susanne; Eberhardt, Mirjam; Schnoelzer, Martina; Lasischka, Felix; Neuhuber, Winfried; Kichko, Tetyana; et al. (Nature Medicine, 2012)
This study establishes a mechanism for metabolic hyperalgesia based on the glycolytic metabolite methylglyoxal. We found that concentrations of plasma methylglyoxal above 600 nM discriminate between diabetes-affected individuals with pain and those without pain. Methylglyoxal depolarizes sensory neurons and induces post-translational modifications of the voltage-gated sodium channel Na v 1.8, which are associated with increased electrical excitability and facilitated firing of nociceptive neurons, whereas it promotes the slow inactivation of Na v 1.7. In mice, treatment with methylglyoxal reduces nerve conduction velocity, facilitates neurosecretion of calcitonin gene-related peptide, increases cyclooxygenase-2 (COX-2) expression and evokes thermal and mechanical hyperalgesia. This hyperalgesia is reflected by increased blood flow in brain regions that are involved in pain processing. We also found similar changes in streptozotocin-induced and genetic mouse models of diabetes but not in Na v 1.8 knockout (Scn10 -/-) mice. Several strategies that include a methylglyoxal scavenger are effective in reducing methylglyoxal-and diabetes-induced hyperalgesia. This previously undescribed concept of metabolically driven hyperalgesia provides a new basis for the design of therapeutic interventions for painful diabetic neuropathy. © 2012 Nature America, Inc. All rights reserved.
CRIS-Team Scopus Importer:2022-11-28

Mice Heterozygous for the Sodium Channel Scn8a (Nav1.6) Have Reduced Inflammatory Responses During EAE and Following LPS Challenge - Alrashdi, Barakat; Dawod, Bassel; Tacke, Sabine; Kürten, Stefanie; Cote, Patrice D.; Marshall, Jean S. (Frontiers in Immunology, 2021)
Voltage gated sodium (Nav) channels contribute to axonal damage following demyelination in experimental autoimmune encephalomyelitis (EAE), a rodent model of multiple sclerosis (MS). The Nav1.6 isoform has been implicated as a primary contributor in this process. However, the role of Nav1.6 in immune processes, critical to the pathology of both MS and EAE, has not been extensively studied. EAE was induced with myelin oligodendrocyte (MOG35-55) peptide in Scn8admu/+ mice, which have reduced Nav1.6 levels. Scn8admu/+ mice demonstrated improved motor capacity during the recovery and early chronic phases of EAE relative to wild-type animals. In the optic nerve, myeloid cell infiltration and the effects of EAE on the axonal ultrastructure were also significantly reduced in Scn8admu/+ mice. Analysis of innate immune parameters revealed reduced plasma IL-6 levels and decreased percentages of Gr-1high/CD11b+ and Gr-1int/CD11b+ myeloid cells in the blood during the chronic phase of EAE in Scn8admu/+ mice. Elevated levels of the anti-inflammatory cytokines IL-10, IL-13, and TGF-β1 were also observed in the brains of untreated Scn8admu/+ mice. A lipopolysaccharide (LPS) model was used to further evaluate inflammatory responses. Scn8admu/+ mice displayed reduced inflammation in response to LPS challenge. To further evaluate if this was an immune cell-intrinsic difference or the result of changes in the immune or hormonal environment, mast cells were derived from the bone marrow of Scn8admu/+ mice. These mast cells also produced lower levels of IL-6, in response to LPS, compared with those from wild type mice. Our results demonstrate that in addition to its recognized impact on axonal damage, Nav1.6 impacts multiple aspects of the innate inflammatory response.
CRIS-Team Scopus Importer:2021-04-19
Keywords: experimental autoimmune encephalomyelitis; inflammation; lipopolysaccharide; mast cells; multiple sclerosis; sodium channel

MIGS – eine Off-label-Option für eine therapierefraktäre, steroidinduzierte okuläre Hypertension - Hohberger, Bettina; Haug, Marius; Bergua, Antonio; Lämmer, Robert (Ophthalmologe, 2019)
Steroid-induced ocular hypertension (SIOH), which cannot be regulated by topical antiglaucoma agents, is a rare complication after intravitreal implantation of diverse cortisone derivatives. This case report presents a therapeutic approach for treatment-refractory SIOH after intravitreal implantation of fluocinolone acetonide using various minimally invasive glaucoma surgery (MIGS) techniques.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Glaucoma; iStent inject; MIGS; Ocular hypertension; Xen gel stent

Modeling the finite viscoelasticity of human brain tissue based on microstructural information - Reiter, Nina; Schäfer, Anne-Mareike; Auer, Sophia; Paulsen, Friedrich; Budday, Silvia (Proceedings in Applied Mathematics and Mechanics, 2023)
Continuum-mechanics-based computational models are a valuable tool to advance our understanding of mechanics-related physiological and pathological processes in the brain. Current numerical predictions of brain tissue behavior are mainly based on phenomenological material models. Such models rely on parameters that often lack physical interpretation and only provide adequate estimates for brain regions with a similar microstructure as those used for calibration. These issues can be overcome by establishing advanced constitutive models that are microstructurally motivated and account for regional and temporal changes through microstructural parameters. In a previous study, we have proposed a microstructure-informed finite viscoelastic constitutive model for porcine brain tissue based on experimental insights into the link between macroscopic deformations and cell displacements during compression tests. Here, we test whether the model can be applied to the material response of human brain tissue from different brain regions during compression and tension tests. We calibrate the model using a combination of cyclic loadings in compression and tension as well as stress relaxation experiments in compression. Furthermore, we include cell densities and the percentage area covered by cell nuclei from microstructural analyses of the tested samples into the model. While it was not possible to identify one set of material parameters for all four considered brain regions, we successfully applied the model to tissue from the cerebellar white matter. Our results show that the microstructure-based time constant that we had determined based on experiments on porcine brain tissue is also valid for human tissue. Furthermore, the microstructure-informed material model is capable of capturing the pronounced compression-tension asymmetry of brain tissue.<br

Modulation of Pancreatic Neuroendocrine Neoplastic Cell Fate by Autophagy-Mediated Death - Matrood, Sami; De Prisco, Nicola; Wissniowski, Thaddeus T.; Wiese, Dominik; Jabari, Samir; Griesmann, Heidi; Wanzel, Michael; Stiewe, Thorsten; Neureiter, Daniel; Klieser, Eckhard; Mintziras, Ioannis; Buchholz, Malte; et al. (Neuroendocrinology, 2021)
Introduction: Autophagic cell death in cancer cells can be mediated by inhibition of deacetylases. Although extensive studies have focused on the autophagic process in cancer, little is known about the role of autophagy in degrading cytosolic and nuclear components of pancreatic neuroendocrine neoplastic (pNEN) cells leading to cell death, thus improving the therapy of patients affected by pNEN. Methods: 2D and 3D human pNEN and pancreatic stellate cells were treated with panobinostat and bafilomycin. Autophagy markers were detected by RT-qPCR, immunofluorescence, and Western blot. Autophagosomes were detected by electron microscopy and their maturation by real-time fluorescence of LC3B stable transfected cells. ChIP was performed at the cAMP responsive element. Immunofluorescence was performed in murine pancreatic tissue. Results: We observed that pan-deacetylase inhibitor panobinostat treatment causes autophagic cell death in pNEN cells. We also found that although AMPK-alpha phosphorylation is counterbalanced by phosphorylated AKT, it is not capable to inhibiting autophagic cell death. However, the binding activity of the cAMP responsive element is prompted by panobinostat. Although autophagy inhibition prevented autophagosome synthesis, maturation, and cell death, panobinostat treatment induced the accumulation of mature autophagosomes in the cytosol and the nucleus, leading to disruption of the organelles, cellular digestion, and decay. Observation of autophagosome membrane proteins Beclin1 and LC3B aggregation in murine pancreatic islets indicates that autophagy restoration may also lead to autophagosome aggregation in murine insulinoma cells. A basal low expression of autophagy markers was detectable in patients affected by pNEN, and, interestingly, the expression of these markers was significantly lower in metastatic pNEN. Discussion/Conclusion: Our study highlights that the autophagy functional restoration and prolongation of this catabolic process, mediated by inhibition of deacetylase, is responsible for the reduction of pNEN cells. Prompting of autophagy cell death could be a promising strategy for the therapy of pNEN.
CRIS-Team WoS Importer:2021-09-24

Molecular dynamics simulations of the delta and omicron SARS-CoV-2 spike – ACE2 complexes reveal distinct changes between both variants - Socher, Eileen; Heger, Lukas; Paulsen, Friedrich; Zunke, Friederike; Arnold, Philipp (Computational and Structural Biotechnology Journal, 2022)
SARS-CoV-2, the virus causing the COVID-19 pandemic, changes frequently through the appearance of mutations constantly leading to new variants. However, only few variants evolve as dominating and will be considered as “Variants of Concern” (VOCs) by the world health organization (WHO). At the end of 2020 the alpha (B.1.1.7) variant appeared in the United Kingdom and dominated the pandemic situation until mid of 2021 when it was substituted by the delta variant (B.1.617.2) that first appeared in India as predominant. At the end of 2021, SARS-CoV-2 omicron (B.1.1.529) evolved as the dominating variant. Here, we use in silico modeling and molecular dynamics (MD) simulations of the receptor-binding domain of the viral spike protein and the host cell surface receptor ACE2 to analyze and compare the interaction pattern between the wild type, delta and omicron variants. We identified residue 493 in delta (glutamine) and omicron (arginine) with altered binding properties towards ACE2.<br
Keywords: COVID-19; SARS-CoV-2; B.1.427/B.1.429; B.1.617.2; B.1.617.1; B.1.1.529; Epsilon variant; Delta variant; Kappa variant; Omicron variant; VOC; Spike protein; Receptor-binding domain; ACE2; Receptor interface; Molecular dynamics simulations

Monoamines in the enteric nervous system - Neuhuber, Winfried; Wörl, Jürgen (Histochemistry and Cell Biology, 2018)
Recent advances in neurogastroenterology have extended and refined our knowledge on the roles monoamines play in physiology and pathophysiology of the gastrointestinal tract. The catecholamine noradrenaline, as the primary transmitter of postganglionic sympathetic neurons, orchestrates motility and secretory reflexes and controls arterial perfusion as well as immune functions. The catecholamine dopamine is produced by a subpopulation of enteric neurons which possibly use it as transmitter. Serotonin, largely produced by enterochromaffin cells and to a small extent by enteric neurons profoundly affects gut motility, enteric neuron development and is also involved in immunomodulation. However, its mode of action and the relative contribution of non-neuronal versus neuronal serotonin was recently subject to debate again. Histamine, although entirely of non-neuronal origin, is pivotal for gastrointestinal neuroimmunomodulation besides its paracrine effect in gastric HCl production.
EVALuna2:35201

Morphological alterations within the peripheral fixation of the iris dilator muscle in eyes with pigmentary glaucoma - Flügel-Koch, Cassandra; Tektas, Ozan Yüksel; Kaufman, Paul L.; Paulsen, Friedrich; Lütjen-Drecoll, Elke (Investigative Ophthalmology & Visual Science, 2014)
To analyze the peripheral fixation of the iris dilator muscle in normal eyes and in eyes with pigmentary glaucoma (PG).Using 63 control eyes (age 18 months-99 years), the peripheral iris dilator was investigated by light microscopy, immunohistochemistry, and electron microscopy. Development was studied using 18 differently aged fetal eyes stained immunohistochemically against ?-smooth muscle (SM) actin. The peripheral iris dilator muscle in PG was analyzed using semithin and ultrathin sections of six glutaraldehyde-fixed eyes from three donors aged 38, 62, and 74 years.In normal eyes, the peripheral end of the iris dilator muscle is arranged in a sphincter-like manner. Arcade-shaped tendinous connections associated with myofibroblasts (iridial strands) anchor the iris dilator within the elastic-fibromuscular ciliary meshwork that also serves as fixation area for the elastic tendons of the inner ciliary muscle portions. The iridial strands are innervated and can adapt their length during accommodation. The PG eyes show incomplete circular bundles and iridial strands that are mainly anchored to the iris stroma and the flexible uveal parts of the trabecular meshwork.The normal anchorage of the peripheral iris dilator and its presumably neuronally regulated length adaptation stabilize the peripheral iris during accommodation. Insufficient fixation in PG could promote posterior bowing of the iris with rubbing against the zonular fibers and pigment liberation from the iris pigmented epithelium.
EVALuna2:4417

Morphological and Immunohistochemical Characterization of Human Intrinsic Gastric Neurons - Anetsberger, Daniel; Kürten, Stefanie; Jabari, Samir; Brehmer, Axel (Cells Tissues Organs, 2019)
Our knowledge about human gastric enteric neuron types is even more limited than that of human intestinal types. Here, we immunohistochemically stained wholemounts and sections of gastric specimens obtained from 18 tumor-resected patients. Myenteric wholemounts were labeled for choline acetyl transferase (ChAT), neuronal nitric oxide synthase (NOS), and the human neuronal protein HuC/D (as pan-neuronal marker for quantitative analysis) or alternatively for neurofilament (for morphological evaluation). ChAT-positive neurons outnumbered NOS-positive neurons (56 vs. 27%), and neurons negative for both markers accounted for 17%. Two larger groups of neurons (each between 12 and 14%) costained for ChAT and vasoactive intestinal peptide (VIP) or for NOS and VIP, respectively. Clear morphochemical correlation was found for uniaxonal stubby type I neurons (ChAT+; putative excitatory inter- or motor neurons), for uniaxonal spiny type I neurons (NOS+/VIP+; putative inhibitory motor or interneurons), and for multiaxonal type II neurons (ChAT+; putative afferent neurons; immunostaining of additional wholemounts revealed their coreactivity for somatostatin). Whereas these latter neuron types were already known from the human intestine, the morphology of gastric myenteric neurons coreactive for ChAT and VIP was newly described: they had numerous short, extremely thin dendrites and resembled, together with their cell bodies, a "hairy" head. In our sections, nerve fibers coreactive for ChAT and VIP were commonly found only in the mucosa. We suggest these myenteric ChAT+/VIP+/hairy neurons to be mucosal effector neurons. In contrast to myenteric neurons, the much less common submucosal neurons were not embedded in a continuous plexus and did not display any clear morphochemical phenotypes.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Chemical coding; Enteric nervous system; Innervation; Morphology; Neurons; Stomach

Morphological classification of NADPHd-positive and -negative myenteric neurons in the porcine small intestine - Brehmer, Axel; Stach, Werner (Cell and Tissue Research, 1997)
In this study, the neuronal nitric oxide synthase (nNOS)-related NADPHd reaction was combined with a silver impregnation method to visualize the morphology of nitrergic and non-nitrergic enteric neurons in the pig. Based on colour combination, NADPHd-positive and impregnated, NADPHd-negative but impregnated and NADPHd-positive but non-impregnated groups of nerve cells could be distinguished in whole-mounts of the small intestine. Neurons of the first two groups could be classified morphologically. NADPHd-positive and impregnated cells showed type III and type VI morphology, the first being located preferably in the upper, the latter in the lower small intestine. Both project largely in an aboral direction. NADPHd-negative but silver impregnated are the orally projecting type I, the adendritic, mostly circumferentially projecting type II, the vertically - to the submucous plexuses - projecting type IV and the aborally projecting type V neurons. Given that NADP-PHd and nNOS are identical, we conclude that type III and type VI neurons are nitrergic and type I, II, IV and V neurons are non-nitrergic. A considerable number of mostly smaller NADPHd-positive but non-impregnated neurons could not be classified.
Keywords: Axonal projection; Enteric nervous system; NADPH diaphorase; Neuron type; Nitric oxide synthase; Pig; Silver impregnation

Morphological classifications of enteric neurons - 100 years after Dogiel - Brehmer, Axel; Schrödl, Falk; et al. (Anatomy and Embryology, 1999)
The first differentiation of enteric neurons into three morphological types was done by the russian histologist A. S. Dogiel on the basis of the different shapes and lengths of their dendrites. Although a number of authors considered his results during the following decades, only a division into two types withstood time: type I neurons had one long and several short processes, whereas type II neurons were characterized by several long processes. Some further structural features were discussed but substantial progress was not made until the late 1970s. This stagnation was due to some inaccuracies in Dogiel's descriptions, to the fact that most histologists in this field followed the reticular concept of the nervous system, to the idea that enteric neurons represent no more than a vegetative, postganglionic relay station between the central nervous system and the periphery, and to methodological difficulties. With the application of modern neuroanatomical techniques it was realized that the enteric nervous system contains a considerable number of neuronal subpopulations. The search for morphological correlates of the chemical diversity of enteric neurons was done mainly in the pig and the guinea-pig. In the pig, additional structural features such as axonal projection, distribution of neurons within ganglia, within different plexuses and along the length of the gut, blood supply etc. were included as criteria for further refining neuronal classification. Most of our knowledge about functional features of enteric neurons, e.g. chemical coding, neuronal connectivity, electrophysiological behaviour, was derived from studies in the guinea-pig small intestine. In light of interspecies differences, comparison of findings from different species is mandatory. The search for morphological and functional peculiarities of human enteric neuronal circuitry has to consider all methodological and conceptual advances made within the past 100 years since the pioneering work of Dogiel.
Keywords: Enteric nervous system; Innervation; Intestine; Morphology; Neuron

Morphological Features of the Porcine Lacrimal Gland and Its Compatibility for Human Lacrimal Gland Xenografting - Henker, Robert; Scholz, Michael; Gaffling, Simone; Nagayoshi, Asano; Hampel, Ulrike; Garreis, Fabian; Hornegger, Joachim; Paulsen, Friedrich (PLoS ONE, 2013)

Morphological phenotyping of enteric neurons using neurofilament immunohistochemistry renders chemical phenotyping more precise in porcine ileum - Brehmer, Axel; Schrödl, Falk; Neuhuber, Winfried (Histochemistry and Cell Biology, 2002)
The aim of the study was: (1) to test the suitability of neurofilament (NF) immunohistochemistry for representing the shapes of morphologically defined neuron types in the pig ileum myenteric plexus, (2) to estimate the proportions of these neuron types as related to the whole myenteric neuron population and (3) to demonstrate the usefulness of a refined morphological classification of enteric neurons on the paradigm of calcitonin gene-related peptide (CGRP)-immunoreactive neurons. So far, immunoreactivity for this peptide was supposed to be present in the pig enteric nervous system only in type II neurons. Ileal whole mounts of two pigs were stained with the cuprolinic blue (CB) method and, thereafter, incubated with an antibody pool against NF proteins (70, 160 and 210 kDa), visualised with a fluorochrome-tagged secondary antibody. The structural representation of morphologically defined myenteric neuron types typical for pig ileum (Stach I, II, IV, V and VI) was equivalent to their silver impregnated image, as demonstrated in previous studies. Counts of CB-stained neurons revealed between 2,526 and 2,662 neurons per square centimetre in one pig and between 2,027 and 2,763 in the other. As related to these total neuron numbers, the proportions of type I neurons were 1.7% and 1.5%, of type II neurons 7.2% and 7.9%, of type IV neurons 1.9% and 2.4%, of type V neurons 1.1% and 1.5%, and of type VI neurons 1.3% each. These values are generally comparable with those estimated earlier on silver impregnated material. Double labelling for NF and CGRP indicated that CGRP-immunoreactive smooth contoured neurons with long processes could be subdivided into two distinct morphological neuron types, i.e. type II and type V. We conclude that NF immunohistochemistry is an appropriate tool for representation of morphologically defined enteric neuron types in the pig. Combination of this technique with immunohistochemistry for neuroactive substances may be useful for making both morphological and chemical classification schemes mutually more precise.
Keywords: CGRP; Cuprolinic blue; Enteric nervous system; Innervation; Intestine

Morphological variability of the fibularis brevis tendon in human fetuses - Olewnik, Łukasz; Zielinska, Nicol; Ruzik, Kacper; Podgórski, Michał; Kiciński, Przemysław; Diogo, Rui; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2024)
Introduction: The morphological variability of the fibularis brevis tendon in adults is well known. However, studies on its classification in the human fetus do not exist. The aim of this study was to provide the first comprehensive classification of the fibularis brevis tendon based on its insertion in human fetuses. The second aim of the study is to evaluate the prevalence of fibularis digiti quinti. Material and Methods: Forty-three spontaneously aborted human fetuses were studied (21 male, 22 female, 86 lower limbs). All were from a Central European population), aged 18–38 weeks of gestation at the time of death. Results: Three main types of fibularis brevis tendon were distinguished. The most common was Type I (77%), characterized by a single distal attachment. The tendon was attached to the tuberosity at the base of the fifth metatarsal, on the lateral side. The second most common was Type II (19%) - a bifurcated distal attachment. The main tendon was attached to the tuberosity at the base of the fifth metatarsal on the lateral side. Based on the attachment site of the accessory tendon, four subtypes were determined: Type IIA - the accessory tendon attached to the dorsal surface of the base of the fifth metatarsal. At the side of attachment, the fibularis brevis tendon was connected with a portion of the fibularis tertius tendon. Type IIB - the accessory tendon attached to the proximal part of the shaft of the fifth metatarsal. Type IIC - the accessory tendon was attached to the fascia covering the fourth interosseous space. Type IID - the accessory tendon was fused with fibularis longus tendon. Type III is the rarest (4%) - triple branched distal attachment. The main tendon was attached to the tuberosity at the base of the fifth metatarsal. The first accessory tendon was attached to the proximal part of the shaft of the fifth metatarsal, and the second accessory tendon was attached to the fascia covering the fourth interosseous space. The fibularis digiti quinti was present in 24 feet (28%) of the 86 lower limbs dissected. Conclusion: The fibularis brevis is characterized by high morphological variability. The proposed classification consists of three main Types (I-III), with Type II divided into subtypes (A-D). The fibularis digiti quinti is not closely related to the type of fibularis brevis tendon.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Anatomical variations; Fibularis brevis muscle; Fibularis brevis tendon; Foetuses

Morphological variability of the fibularis longus tendon in human fetuses - Olewnik, Lukasz; Zielinska, Nicol; Ruzik, Kacper; Podgorski, Michal; Paulsen, Friedrich; Diogo, Rui; Polguj, Michal (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Introduction: The morphological variability of the fibularis longus tendon (FLT) in adults is well understood. However, no comprehensive classification exists in human fetuses. The goal of this study was to prepare the first comprehensive classification of the fibularis longus tendon based on its insertion in human fetuses. Material and methods: Forty-seven spontaneously-aborted human fetuses were examined: 38 male, 56 female, a total of 94 lower limbs (Central European population). Age ranged from18-38 weeks of gestation at death. Results: The classification comprised three types of FLT. The most common type was Type I (49%), characterized by the single distal attachment. This type was divided into two subtypes (A-B): A - the tendon inserts to the lateral tubercle of the base of the 1st metatarsal bone, B - the tendon inserts to the head of the 1st metatarsal bone. The second most type was Type II, characterized by a bifurcated distal attachment (24.5%). This type was divided into three subtypes (A-C): A - the main tendon inserts to the lateral tubercle of the base of the 1st metatarsal bone and the accessory band inserts to the medial cuneiform bone; B - the strong, main tendon inserts to both the base of the 1st metatarsal bone and medial cuneiform bone, including the first metatarsal-cuneiform joint, and the accessory bands inserts to the fourth interosseus dorsalis muscle; C - the main tendon inserts to the lateral tubercle of the base of the 1st metatarsal bone and the accessory band inserts to the first interosseus dorsalis muscle. The rarest type was Type III, characterized by a trifurcated distal attachment: the main tendon inserts to the lateral tubercle of the base of the 1st metatarsal bone and the first accessory band inserts to the medial cuneiform bone and the second accessory bands inserts to the first interosseus dorsalis muscle. The anterior frenular ligament was observed in 16% of all cases, and posterior frenular ligament in 6.4%. Conclusion: The FLT displays high morphological variability. The proposed classification consists of three main types, with Type I and Type II divided into sub-types; it also provides additional data regarding its accessory tendon bands. (c) 2021 The Authors. Published by Elsevier GmbH. CC_BY_NC_ND_4.0
CRIS-Team WoS Importer:2021-12-03

Morphological variability of the fibularis tertius tendon in human foetuses. - Karauda, Piotr; Paulsen, Friedrich; Polguj, Michal; Diogo, R.; Olewnik, L. (Folia Morphologica, 2022)
BACKGROUND: In adults, the fibularis tertius (FT) demonstrates great morphological variation. The present study classifies the types of FT insertion in human foetuses and compares their prevalence to the prevailing classification among adults. MATERIALS AND METHODS: Fifty spontaneously-aborted human foetuses (19 male, 31 female, 100 upper limbs in total) aged 18-38 weeks of gestation at death were examined. The foetuses were obtained from spontaneous abortion after parental consent. The study was performed in accordance with the legal procedures in force in Poland and with the Body Donation Programme for both adults and foetuses. RESULTS: The most common type of FT found was type VI (32%), characterised by a bifurcated distal attachment: a main tendon inserting onto the base of the fourth metatarsal bone, and accessory bands inserting onto the fourth interosseous space. Five other types were observed: type IV (20%), with a single tendon inserting distally to the fascia covering the fourth interosseous space; type I (18%), with a single tendon inserting distally onto the shaft of the fifth metatarsal bone; type V (14%), with a bifurcated arrangement comprising a main tendon characterised by a very wide insertion onto the base of the fifth metatarsal bone and an accessory band inserting onto the base of the fourth metatarsal bone; and type III (12%) with a single tendon inserting distally onto the shaft of the fourth metatarsal bone and fascia covering the fourth interosseous space. Finally, type II (4%) was characterised by a single tendon inserting onto the base of the fifth metatarsal bone via a very wide distal insertion. CONCLUSIONS: The FT demonstrates high morphological variability, with the most common configuration found in adults - a single insertion onto metatarsal 5 - being actually uncommonly found in foetuses.
EVALuna2:515787

Morphological variability of the plantaris tendon in the human fetus - Waśniewska-Włodarczyk, Anna; Paulsen, Friedrich; Olewnik, Łukasz; Polguj, Michał (Scientific Reports, 2021)
Muscular anatomy often differs between species and individuals. In particular, the plantaris muscle (PM) demonstrates great morphological variability in its course and its proximal and distal attachments. The aim of this study was to investigate the morphological variation of the PM tendon in human fetuses. Forty-six spontaneously aborted human fetuses (23 male, 23 female) aged 18–38 weeks of gestation were studied. Morphology of the attachment of the PM was assessed in both lower extremities (n = 92). The PM was present in 72 lower limbs (78.26%) and absent in 20 (21.74%). Eight types of PM distal attachment were identified. We propose an eight-fold classification of PM insertion in fetuses. Leg length, length of tendon, extension point (ExP) from the calcaneus, and ExP thickness differed significantly among types of PM insertion.
CRIS-Team Scopus Importer:2021-08-27

Morphology and morphometry of lacrimal drainage system in relation to bony landmarks in Caucasian adults: a cadaveric study - Ali, Mohammad Javed; Schicht, Martin; Paulsen, Friedrich (International Ophthalmology, 2018)
PURPOSE: The objective of this study is to examine the morphometry of the lacrimal drainage system with reference to bony landmarks in the vicinity. METHODS: Twenty midsaggitalized heads obtained from sixteen preserved cadavers were studied. Measurements involved detailed morphometry of anterior and posterior lacrimal crests, bony lacrimal sac fossa, entrance and length of the bony nasolacrimal duct (NLD), attachment of Horner's muscle, and characteristics of the inferior meatal opening of the NLD. RESULTS: The mean lengths of anterior and posterior lacrimal crests were 16.3 and 12.5 mm, respectively. At the midpoint of the posterior lacrimal crest, Horner's muscle was found to be attached at a mean of 1.3 mm posterior to the crest. The mean dimensions of the bony lacrimal sac fossa at superior, mid and inferior levels were 6.5, 8.7, and 5.9 mm, respectively. The mean contribution of the lacrimal bone to the lacrimal sac fossa was 56.2%. The mean anteroposterior and transverse diameters of the entrance of the bony NLD were 5.7 and 4.7 mm, respectively. The most common type of NLD opening in the inferior meatus was that of "vertical sulcus" (70%, 14/20). The mean distance of the NLD opening from the anterior nasal spine and Limen nasi were 22.2 and 18.9 mm, respectively. CONCLUSION: This study provides useful anatomical and positional relationship of bony lacrimal landmarks and nasolacrimal duct in Caucasian adults.
EVALuna2:35298

Morphology of enkephalin-immunoreactive myenteric neurons in the human gut - Brehmer, Axel; Lindig, Tobias; Schrödl, Falk; Neuhuber, Winfried; Ditterich, Daniel; Rexer, Martin; Rupprecht, Holger (Histochemistry and Cell Biology, 2005)
The aim of this study was the morphological and further chemical characterisation of neurons immunoreactive for leu-enkephalin (leuENK). Ten wholemounts of small and large intestinal segments from nine patients were immunohistochemically triple-stained for leuENK/neurofilament 200 (NF)/substance P (SP). Based on their simultaneous NF-reactivity and 3D reconstruction of single NF-reactive cells, 97.5% of leuENK-positive neurons displayed the appearance of stubby neurons: small somata; short, stubby dendrites and one axon. Of these leuENK-reactive stubby neurons, 91.3% did not display co-reactivity for SP whereas 8.7% were SP-co-reactive. As to their axonal projection pattern, 50.4% of the recorded leuENK stubby neurons had axons running orally whereas in 29.4% they ran anally; the directions of the remaining 20.2% could not be determined. No axons were seen to enter into secondary strands of the myenteric plexus. Somal area measurements revealed clearly smaller somata of leuENK-reactive stubby neurons (between 259±47 μm and 487±113 μm) than those of putative sensory type II neurons (between 700±217 μm and 1,164±396 μm). The ratio dendritic field area per somal area of leuENK-reactive stubby neurons was between 2.0 and 2.8 reflecting their short dendrites. Additionally, we estimated the proportion of leuENK-positive neurons in comparison to the putative whole myenteric neuron population in four leuENK/anti-Hu doublestained wholemounts. This proportion ranged between 5.9% and 8.3%. We suggest leuENK-reactive stubby neurons to be muscle motor neurons and/or ascending interneurons. Furthermore, we explain why we do not use the term "Dogiel type I neurons" for this population. © Springer-Verlag 2005.
Keywords: 3D reconstruction; Enteric nervous system; Innervation; Intestine; Opioids

Morphology of VIP/nNOS-immunoreactive myenteric neurons in the human gut - Brehmer, Axel; Schrödl, Falk; et al. (Histochemistry and Cell Biology, 2006)
In this study, we characterized human myenteric neurons co-immunoreactive for neuronal nitric oxide synthase (nNOS) and vasoactive intestinal peptide (VIP) by their morphology and their proportion as related to the putative entire myenteric neuronal population. Nine wholemounts (small and large intestinal samples) from nine patients were triple-stained for VIP, neurofilaments (NF) and nNOS. Most neurons immunoreactive for all three markers displayed radially emanating, partly branching dendrites with spiny endings. These neurons were called spiny neurons. The spiny character of their dendrites was more pronounced in the small intestinal specimens and differed markedly from enkephalinergic stubby neurons described earlier. Exclusively in the duodenum, some neurons displayed prominent main dendrites with spiny side branches. Of the axons which could be followed from the ganglion of origin within primary strands of the myenteric plexus beyond the next ganglion (70 out of 140 traced neurons), 94.3% run anally and 5.7% orally. Very few neurons reactive for both VIP and nNOS could not be morphologically classified due to weak or absent NF-immunoreactivity. Another six wholemounts were triple-stained for VIP, nNOS and Hu proteins (HU). The proportion of VIP/nNOS-coreactive neurons in relation to the number of HU-reactive neurons was between 5.8 and 11.5% in the small and between 10.6 and 17.5% in the large intestinal specimens. We conclude that human myenteric spiny neurons co-immunoreactive for VIP and nNOS represent either inhibitory motor or descending interneurons. © Springer-Verlag 2005.
Keywords: Colon; Dogiel classification; Enteric nervous system; Innervation; Neuron type

Mosaic trisomy of chromosome 1q in human brain tissue associates with unilateral polymicrogyria, very early-onset focal epilepsy, and severe developmental delay - Kobow, Katja; Jabari, Samir; Pieper, Tom; Kudernatsch, Manfred; Polster, Tilman; Woermann, Friedrich G.; Kalbhenn, Thilo; Hamer, Hajo; Roessler, Karl; Muhlebner, Angelika; Spliet, Wim G. M.; Feucht, Martha; et al. (Acta Neuropathologica, 2020)
Polymicrogyria (PMG) is a developmental cortical malformation characterized by an excess of small and frustrane gyration and abnormal cortical lamination. PMG frequently associates with seizures. The molecular pathomechanisms underlying PMG development are not yet understood. About 40 genes have been associated with PMG, and small copy number variations have also been described in selected patients. We recently provided evidence that epilepsy-associated structural brain lesions can be classified based on genomic DNA methylation patterns. Here, we analyzed 26 PMG patients employing array-based DNA methylation profiling on formalin-fixed paraffin-embedded material. A series of 62 well-characterized non-PMG cortical malformations (focal cortical dysplasia type 2a/b and hemimegalencephaly), temporal lobe epilepsy, and non-epilepsy autopsy controls was used as reference cohort. Unsupervised dimensionality reduction and hierarchical cluster analysis of DNA methylation profiles showed that PMG formed a distinct DNA methylation class. Copy number profiling from DNA methylation data identified a uniform duplication spanning the entire long arm of chromosome 1 in 7 out of 26 PMG patients, which was verified by additional fluorescence in situ hybridization analysis. In respective cases, about 50% of nuclei in the center of the PMG lesion were 1q triploid. No chromosomal imbalance was seen in adjacent, architecturally normal-appearing tissue indicating mosaicism. Clinically, PMG 1q patients presented with a unilateral frontal or hemispheric PMG without hemimegalencephaly, a severe form of intractable epilepsy with seizure onset in the first months of life, and severe developmental delay. Our results show that PMG can be classified among other structural brain lesions according to their DNA methylation profile. One subset of PMG with distinct clinical features exhibits a duplication of chromosomal arm 1q.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Brain development; Chromosome 1; Copy number variation; Cortical malformation; ID; Seizures

Mucosal innervation of the pig small intestine. A preliminary report. - Brehmer, Axel; Schrödl, Falk; Neuhuber, Winfried (Biogenic Amines, 1997)
The carbocyanine tracer DiI was applied into single villi of the fixed small intestine of pigs. After incubation of several months, labelled nervous elements were found in the plexus mucosus and the plexus muscularis mucosae as well as in the ganglionated nerve networks: the inner and outer submucous and the myenteric plexus. Both dendritic and adendritic neurons could be identified. The results indicate that neurons of all three ganglionated plexuses of the pig small intestine are integrated in mucosal function and, that their axons travel through non-ganglionated plexuses before reaching the mucosa.
Keywords: DiI; Enteric nervous system; Mucosal plexus; Neuron; Plexus muscularis mucosae

Mucosal layers and related nerve fibres in non-chagasic and chagasic human colon—a quantitative immunohistochemical study - Jabari, Samir; Da Silveira, Alexandre B.M.; De Oliveira, Enio; Quint, Karl; Wirries, André; Neuhuber, Winfried; Brehmer, Axel (Cell and Tissue Research, 2014)
Chagasic megacolon is accompanied by extensive myenteric and, simultaneously, moderate submucosal neuron loss. Here, we examined changes of the innervation pattern of the lamina propria (LP) and muscularis mucosae (MM). Two alternating sets of cryosections were taken from seven non-chagasic colonic and seven chagasic megacolonic specimens (the latter included both the dilated megacolonic and the non-dilated transitional oral and anal zones) and were immunohistochemically triple-stained for smooth-muscle actin (SMA), synaptophysin (SYN) and glial acid protein S100 and, alternatively, for SMA, vasoactive intestinal peptide (VIP) and somatostatin (SOM). Subsequent image analysis and statistical evaluation of nervous tissue profile areas revealed that, in LP, the most extreme differences (i.e. increase in thickness or decrease in nerve, glia and muscle tissue profile area, respectively) compared with control values occurred in the dilated megacolonic zone itself. In contrast, the most extreme differences in the MM were in the anal-to-megacolonic zone (except the profile area of muscle tissue, which was lowest in the megacolonic zone). This parallels our previous results in the external muscle coat. A partial and selective survival of VIP-immunoreactive in contrast to SOM-immunoreactive nerve fibres was observed in both mucosal layers investigated. Thus, VIPergic nerve elements might be crucial for the maintenance of the mucosal barrier. The differential changes of neural tissue parameters in LP and MM might reflect a multifactorial rather than a pure neurogenic development of megacolon in chronic Chagas’ disease.
Keywords: Chagas’ disease; Enteric nervous system; Innervation; Megacolon; Mucosa; Muscularis mucosae

Mucosal projections of enteric neurons in the porcine small intestine - Hens, Jurgen; Schrödl, Falk; Brehmer, Axel; Adriaensen, Dirk; Neuhuber, Winfried; Scheuermann, Dietrich W.; Schemann, Michael; Timmermans, Jean-Pierre (Journal of Comparative Neurology, 2000)
In the present study, a combination of immunohistochemistry and retrograde 1,1'-didodecyl-3,3,3',3'-tetramethylindocarbocyanine perchlorate (DiI) tracing was used to unravel the morphology, distribution, and neurochemical coding of submucous and myenteric neurons with axonal projections to the mucosa of the porcine small intestine. The majority of traced neurons was located in the inner submucous plexus (ISP; 78%), whereas the remaining part was distributed between the outer submucous plexus (OSP; 10%) and myenteric plexus (MP; 12%). Among these traced neurons, some distinct neuronal populations could be distinguished according to their morphologic and neurochemical properties. In the ISP, several types of traced neurons were detected: 1) morphologic type II neurons expressing choline acetyltransferase (ChAT) immunoreactivity, calcitonin gene-related peptide (CGRP) immunoreactivity, and substance P (SP) immunoreactivity; 2) ChAT/SP- immunoreactive (-IR) small neurons; 3) vasoactive intestinal polypeptide (VIP) -IR small neurons; and 4) multidendritic ChAT/somatostatin (SOM) -IR neurons. The traced neuronal populations of the OSP and MP were similar to each other. In both plexuses, the following DiI-labelled neurons were found: 1) ChAT/CGRP/(SP)-IR type II neurons; 2) multidendritic ChAT/SP-IR neurons; and 3) multidendritic ChAT/SOM-IR neurons. Comparison of the present findings with previously obtained data concerning the mucosal innervation pattern of the intestine of small mammals, revealed significant species differences with respect to the morphologic and neurochemical features of the involved enteric neuronal classes. Although not identical, a closer resemblance between pig and human enteric nervous system seems to be at hand, as far as the anatomic organization and the presence of neurochemically identified neuronal subtypes within the enteric nervous system are concerned. (C) 2000 Wiley-Liss, Inc.
Keywords: DiI-tracing; Enteric nervous system; Immunohistochemistry; Neuropeptides; Organotypic culture

Multilobar unilateral hypoplasia with emphasis on the posterior quadrant and severe epilepsy in children with FCD ILAE Type 1A - Holthausen, Hans; Coras, Roland; Tang, Yingying; Bai, Lily; Wang, Irene; Pieper, Tom; Kudernatsch, Manfred; Hartlieb, Till; Staudt, Martin; Winkler, Peter; Hofer, Wiebke; Jabari, Samir; et al. (Epilepsia, 2021)
Objective: Focal cortical dysplasia (FCD) Type 1 and its three subtypes have yet not been fully characterized at the clinical, anatomopathological, and molecular level (International League Against Epilepsy [ILAE] FCD classification from 2011). We aimed to describe the clinical phenotype of patients with histopathologically confirmed FCD1A obtained from a single epilepsy center between 2002 and 2016. Methods: Medical records were retrieved from the hospital's archive. Results from electroencephalography (EEG) video recordings, neuroimaging, and histopathology were reevaluated. Magnetic resonance imaging (MRI) post-processing was retrospectively performed in nine patients. DNA methylation studies were carried out from archival surgical brain tissue in 11 patients. Results: Nineteen children with a histopathological diagnosis of FCD1A were included. The average onset of epilepsy was 0.9 years (range 0.2–10 years). All children had severe cognitive impairment and one third had mild motor deficits, yet fine finger movements were preserved in all patients. All patients had daily seizures, being drug resistant from disease onset. Interictal electroencephalography revealed bilateral multi-regional epileptiform discharges. Interictal status epilepticus was observed in 8 and countless subclinical seizures in 11 patients. Regional continuous irregular slow waves were of higher lateralizing and localizing yield than spikes. Posterior background rhythms were normal in 16 of 19 children. Neuroimaging showed unilateral multilobar hypoplasia and increased T2-FLAIR signals of the white matter in 18 of 19 patients. All children underwent tailored multilobar resections, with seizure freedom achieved in 47% (Engel class I). There was no case with frontal involvement without involvement of the posterior quadrant by MRI and histopathology. DNA methylation profiling distinguished FCD1A samples from all other epilepsy specimens and controls. Significance: We identified a cohort of young children with drug resistance from seizure onset, bad EEG with posterior emphasis, lack of any focal neurological deficits but severe cognitive impairment, subtle hypoplasia of the epileptogenic area on MRI, and histopathologically defined and molecularly confirmed by DNA methylation analysis as FCD ILAE Type 1A.
CRIS-Team Scopus Importer:2021-11-12
Keywords: brain; neuroimaging; neuropathology; neurophysiology; seizure

Multimodal control of neck muscles for vestibular mediated head oscillation damping during walking: a pilot study - Hölzl, Matthias; Neuhuber, Winfried; Ueberschär, Olaf; Schleichardt, Axel; Stamm, Natalie; Arens, Christoph; Biesdorf, Andreas; Goessler, Ulrich; Hülse, Roland (European Archives of Oto-Rhino-Laryngology, 2020)
Purpose: It is still in question whether head oscillation damping during walking forms a part of the vestibular function. The anatomical pathway from the vestibular system to the neck muscles via the medial vestibulospinal tract (MVST) is well known but there is a lack of knowledge of the exact influence and modulation of each other in daily life activities. Methods: (I) We fixed a head–neck unit of a human cadaver specimen in a steal frame to determine the required pitch-torque for a horizontal head position. The mean value of the acquired pitch-torque was 0.54 Nm. (II) On a motorized treadmill we acquired kinematic data of the head, the sternum and both feet by wireless 3D IMUs for seven asymptomatic volunteers. Subsequently three randomized task conditions were performed. Condition 1 was walking without any irritation. Condition 2 imitated a sacculus irritation using a standardized cVEMP signal. The third condition used an electric neck muscle-irritation (TENS). The data were analyzed by the simulation environment software OpenSim 4.0. Results: 8 neck muscle pairs were identified. By performing three different conditions we observed some highly significant deviations of the neck muscle peak torques. Analysing Euler angles, we found during walking a LARP and RALP head pendulum, which also was strongly perturbated. Conclusion: Particularly the pitch-down head oscillation damping is the most challenging one for neck muscles, especially under biomechanical concerns. Mainly via MVST motor activity of neck muscles might be modulated by vestibular motor signals. Two simultaneous proprioceptor effects might optimize head oscillation damping. One might be a proprioceptive feedback loop to the vestibular nucleus. Another might trigger the cervicocollic reflex (CCR).
CRIS-Team Scopus Importer:2020-12-25
Keywords: Cervical vestibular-evoked myogenic potential (cVEMP); Head stabilization; Medial vestibulospinal tract (MVST); Neck muscles; Vestibulocollic reflex (VCR)/cervicocollic reflex (CCR)

Murine esophagus expresses glial‐derived central nervous system antigens - Kapitza, Christopher; Chunder, Rittika; Scheller, Anja; Given, Katherine S.; Macklin, Wendy B.; Enders, Michael; Kürten, Stefanie; Neuhuber, Winfried; Wörl, Jürgen (International Journal of Molecular Sciences, 2021)
Multiple sclerosis (MS) has been considered to specifically affect the central nervous system (CNS) for a long time. As autonomic dysfunction including dysphagia can occur as accompanying phenomena in patients, the enteric nervous system has been attracting increasing attention over the past years. The aim of this study was to identify glial and myelin markers as potential target structures for autoimmune processes in the esophagus. RT‐PCR analysis revealed glial fibrillary acidic protein (GFAP), proteolipid protein (PLP), and myelin basic protein (MBP) expression, but an absence of myelin oligodendrocyte glycoprotein (MOG) in the murine esophagus. Selected immunohistochemistry for GFAP, PLP, and MBP including transgenic mice with cell‐type specific expression of PLP and GFAP supported these results by detection of (1) GFAP, PLP, and MBP in Schwann cells in skeletal muscle and esophagus; (2) GFAP, PLP, but no MBP in perisynaptic Schwann cells of skeletal and esophageal motor endplates; (3) GFAP and PLP, but no MBP in glial cells surrounding esophageal myenteric neurons; and (4) PLP, but no GFAP and MBP in enteric glial cells forming a network in the esophagus. Our results pave the way for further investigations regarding the involvement of esophageal glial cells in the pathogenesis of dysphagia in MS.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Autoantibodies; Dysphagia; Enteric glia; Enteric nervous system; Esophagus; Glial fibrillary acidic protein; Motor endplate; Multiple sclerosis; Myelin basic protein; Proteolipid protein

Mutations in the B.1.1.7 SARS-CoV-2 Spike Protein Reduce Receptor-Binding Affinity and Induce a Flexible Link to the Fusion Peptide - Socher, Eileen; Conrad, Marcus; Heger, Lukas; Paulsen, Friedrich; Sticht, Heinrich; Zunke, Friederike; Arnold, Philipp (Biomedicines, 2021)
The B.1.1.7 variant of the SARS-CoV-2 virus shows enhanced infectiousness over the wild type virus, leading to increasing patient numbers in affected areas. Amino acid exchanges within the SARS-CoV-2 spike protein variant of B.1.1.7 affect inter-monomeric contact sites within the trimer (A570D and D614G) as well as the ACE2-receptor interface region (N501Y), which comprises the receptor-binding domain (RBD) of the spike protein. However, the molecular consequences of mutations within B.1.1.7 on spike protein dynamics and stability or ACE2 binding are largely unknown. Here, molecular dynamics simulations comparing SARS-CoV-2 wild type with the B.1.1.7 variant revealed inter-trimeric contact rearrangements, altering the structural flexibility within the spike protein trimer. Furthermore, we found increased flexibility in direct spatial proximity of the fusion peptide due to salt bridge rearrangements induced by the D614G mutation in B.1.1.7. This study also implies a reduced binding affinity for B.1.1.7 with ACE2, as the N501Y mutation restructures the RBD-ACE2 interface, significantly decreasing the linear interaction energy between the RBD and ACE2. Our results demonstrate how mutations found within B.1.1.7 enlarge the flexibility around the fusion peptide and change the RBD-ACE2 interface. We anticipate our findings to be starting points for in depth biochemical and cell biological analyses of B.1.1.7.
CRIS-Team WoS Importer:2021-06-04
Keywords: COVID-19; SARS-CoV-2; B.1.1.7; molecular dynamics simulation; ACE2; receptor binding

Myelinated Axons in the Auricular Branch of the Human Vagus Nerve - Safi, Sami Alexander; Ellrich, Jens; Neuhuber, Winfried (Anatomical Record-Advances in Integrative Anatomy and Evolutionary Biology, 2016)
Transcutaneous stimulation of the auricular branch of the vagus nerve (ABVN) resulted in deactivation of temporal lobe structures, similar to invasive cervical vagus nerve (CVN) stimulation. Presumably, both methods stimulated myelinated afferent beta axons mediating anti-convulsive effects. How numbers of A beta axons in the human ABVN compare to those of the CVN is unknown. The ABVN, CVN, recurrent laryngeal nerve (RLN) and thoracic vagus nerve (TVN) were dissected from embalmed bodies. Numbers and calibers of myelinated axons were analyzed in semithin sections. Myelinated axons in the left and right ABVN averaged to 385 and 363, respectively. Numbers of A beta axons measuring 7 mu m averaged to 64 and 78 on the left and right, respectively. Numbers of A beta axons in CVN were estimated by subtracting myelinated presumed motor axons in RLN from the total count of CVN. This resulted in 280 and 504 A beta axons on the left and right, respectively, concurring well with the thick myelinated axon count of the ipsilateral TVN (255 and 466, respectively). Thus, the ratio of A beta axons in the ABVN and CVN was approximate to 1:5 and 1:6 on the left and right side, respectively. These results indicate that transcutaneous ABVN stimulation might be a promising alternative to invasive CVN stimulation. Anat Rec, 299:1184-1191, 2016. (c) 2016 Wiley Periodicals, Inc.
EVALuna2:184250
Keywords: axon caliber; transcutaneous stimulation; vagal afferents; external ear; man

Myenteric neurons with different projections have different dendritic tree patterns: A morphometric study in the pig ileum - Brehmer, Axel; Beleites, Bernhard (Journal of the Autonomic Nervous System, 1996)
Morphometric analysis was performed of two types of myenteric neurons with, at first glance, very similar morphology, but different projections in the pig ileum. 50 type IV cells projecting vertically to the outer submucosal plexus, and 50 solitary type V neurons projecting aborally, within the myenteric plexus, were evaluated. Using a computer-aided morphometric device, the following parameters were recorded: somal area, longest somal diameter, number of primary dendrites, dendritic length, number of dendritic branching points and number of terminal segments. In addition to other significant differences, the most prominent discriminating parameter between the two populations of nerve cells estimated in this study was the length of the longest dendrite of each cell type. The longest dendrite of an individual type V neuron is a manifold longer than the corresponding somal diameter, in contrast to type IV neurons where it is at most twice the somal diameter. In addition, all type IV and type V single dendritic lengths were arranged in histograms, where the type V dendrites showed two frequency peaks. Thus, we assume that solitary type V neurons can develop two populations of dendrites: a short and a long one. These results demonstrate that myenteric neurons with different projections (and hence different functions) display strikingly different dendritic morphology.
Keywords: Autonomic nervous system; Dendrite; Enteric nervous system; Morphometry; Neuron types; Silver impregnation; Small intestine

MyoBio: An automated bioreactor system technology for standardized perfusion-decellularization of whole skeletal muscle - Ritter, Paul; Cai, Aijia; Reischl, Barbara; Fiedler, Maren; Prölß, Gerhard; Frie, Benjamin; Kretzschmar, Elke; Michael, Mena; Hartmann, Kristin; Lesko, Christian; Salti, Hatiham; Arkudas, Andreas; et al. (IEEE transactions on bio-medical engineering, 2022)
Objective: Decellularizing solid organs is a promising top-down process to produce acellular bio-scaffolds for 'de novo' regrowth or application as tissue 'patches' that compensate, e.g., large volumetric muscle loss in reconstructive surgery. Therefore, generating standardized acellular muscle scaffolds marks a pressing area of need. Although animal muscle decellularization protocols were established, those are mostly manually performed and lack defined bioreactor environments and metrologies to assess decellularization quality in real-time. To close this gap, we engineered an automated bioreactor system to provide chemical decellularization solutions to immersed whole rat gastrocnemius medialis muscle through perfusion of the main feeding arteries. Results: Perfusion control is adjustable according to decellularization quality feedback. This was assessed both from (i) ex situ assessment of sarcomeres/nuclei through multiphoton fluorescence and label-free Second Harmonic Generation microscopy and DNA quantification, along with (ii) in situ assessment of the samples passive mechanical elasticity. Conclusion: We find DNA and sarcomere-free constructs after 72 h of 0.1% SDS perfusion-decellularization. Furthermore, passive elasticity can be implemented as additional online decellularization quality measure, noting a threefold elasticity decrease in acellular constructs. Significance: Our MyoBio represents a novel and useful automated bioreactor environment for standardized and controlled generation of acellular whole muscle scaffolds as a valuable source for regenerative medicine.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Biological systems; Biomechatronics; bioreactors; Biotechnology; decellularization; Inductors; Muscles; Plastics; skeletal muscle; Surgery; Tendons; tissue engineering

Myoepithelial cell-driven acini contraction in response to oxytocin receptor stimulation is impaired in lacrimal glands of Sjögren's syndrome animal models - Hawley, Dillon; Tang, Xin; Zyrianova, Tatiana; Shah, Mihir; Janga, Srikanth; Letourneau, Alexandra; Schicht, Martin; Paulsen, Friedrich; Hamm-Alvarez, Sarah; Makarenkova, Helen P.; Zoukhri, Driss (Scientific Reports, 2018)
The purpose of the present studies was to investigate the impact of chronic inflammation of the lacrimal gland, as occurs in Sjögren's syndrome, on the morphology and function of myoepithelial cells (MECs). In spite of the importance of MECs for lacrimal gland function, the effect of inflammation on MECs has not been well defined. We studied changes in MEC structure and function in two animal models of aqueous deficient dry eye, NOD and MRL/lpr mice. We found a statistically significant reduction in the size of MECs in diseased compared to control lacrimal glands. We also found that oxytocin receptor was highly expressed in MECs of mouse and human lacrimal glands and that its expression was strongly reduced in diseased glands. Furthermore, we found a significant decrease in the amount of two MEC contractile proteins, α-smooth muscle actin (SMA) and calponin. Finally, oxytocin-mediated contraction was impaired in lacrimal gland acini from diseased glands. We conclude that chronic inflammation of the lacrimal gland leads to a substantial thinning of MECs, down-regulation of contractile proteins and oxytocin receptor expression, and therefore impaired acini contraction. This is the first study highlighting the role of oxytocin mediated MEC contraction on lacrimal gland function.
EVALuna2:35307

Nano- and microplastics: a comprehensive review on their exposure routes, translocation, and fate in humans - Ramsperger, Anja F.R.M.; Bergamaschi, Enrico; Panizzolo, Marco; Fenoglio, Ivana; Barbero, Francesco; Peters, Ruud; Undas, Anna; Purker, Sebastian; Giese, Bernd; Lalyer, Carina R.; Tamargo, Alba; Moreno-Arribas, M. Victoria; et al. (NanoImpact, 2023)
Contamination of the environment with nano-and microplastic particles (NMPs) and its putative adverse effects on organisms, ecosystems, and human health is gaining increasing scientific and public attention. Various studies show that NMPs occur abundantly within the environment, leading to a high likelihood of human exposure to NMPs. Here, different exposure scenarios can occur. The most notable exposure routes of NMPs into the human body are via the airways and gastrointestinal tract (GIT) through inhalation or ingestion, but also via the skin due to the use of personal care products (PCPs) containing NMPs. Once NMPs have entered the human body, it is possible that they are translocated from the exposed organ to other body compartments. In our review article, we combine the current knowledge on the (1) exposure routes of NMPs to humans with the basic understanding of the potential (2) translocation mechanisms into human tissues and, consequently, their (3) fate within the human body. Regarding the (1) exposure routes, we reviewed the current knowledge on the occurrence of NMPs in food, beverages, personal care products and the air (focusing on indoors and workplaces) and found that the studies suggest an abundant presence of MPs within the exposure scenarios. The overall abundance of MPs in exposure matrices relevant to humans highlights the importance of understanding whether NMPs have the potential for tissue translocation. Therefore, we describe the current knowledge on the potential (2) translocation pathways of NMPs from the skin, GIT and respiratory systems to other body compartments. Here, particular attention was paid to how likely NMPs can translocate from the primary exposed organs to secondary organs due to naturally occurring defence mechanisms against tissue translocation. Based on the current understanding, we conclude that a dermal translocation of NMPs is rather unlikely. In contrast, small MPs and NPs can generally translocate from the GIT and respiratory system to other tissues. Thus, we reviewed the existing literature on the (3) fate of NMPs within the human body. Based on the current knowledge of the contamination of human exposure routes and the potential translocation mechanisms, we critically discuss the size of the detected particles reported in the fate studies. In some cases, the particles detected in human tissue samples exceed the size of a particle to overcome biological barriers allowing particle translocation into tissues. Therefore, we emphasize the importance of critically reading and discussing the presented results of NMP in human tissue samples.
CRIS-Team Scopus Importer:2022-12-16
Keywords: effects; human exposure; Microplastic; Nanoplastic; translocation

Nav1.6 promotes inflammation and neuronal degeneration in a mouse model of multiple sclerosis - Alrashdi, Barakat; Dawod, Bassel; Schampel, Andrea; Tacke, Sabine; Kürten, Stefanie; Marshall, Jean S.; Côté, Patrice D. (Journal of Neuroinflammation, 2019)
BACKGROUND: In multiple sclerosis (MS) and in the experimental autoimmune encephalomyelitis (EAE) model of MS, the Nav1.6 voltage-gated sodium (Nav) channel isoform has been implicated as a primary contributor to axonal degeneration. Following demyelination Nav1.6, which is normally co-localized with the Na+/Ca2+ exchanger (NCX) at the nodes of Ranvier, associates with β-APP, a marker of neural injury. The persistent influx of sodium through Nav1.6 is believed to reverse the function of NCX, resulting in an increased influx of damaging Ca2+ ions. However, direct evidence for the role of Nav1.6 in axonal degeneration is lacking. METHODS: In mice floxed for Scn8a, the gene that encodes the α subunit of Nav1.6, subjected to EAE we examined the effect of eliminating Nav1.6 from retinal ganglion cells (RGC) in one eye using an AAV vector harboring Cre and GFP, while using the contralateral either injected with AAV vector harboring GFP alone or non-targeted eye as control. RESULTS: In retinas, the expression of Rbpms, a marker for retinal ganglion cells, was found to be inversely correlated to the expression of Scn8a. Furthermore, the gene expression of the pro-inflammatory cytokines Il6 (IL-6) and Ifng (IFN-γ), and of the reactive gliosis marker Gfap (GFAP) were found to be reduced in targeted retinas. Optic nerves from targeted eyes were shown to have reduced macrophage infiltration and improved axonal health. CONCLUSION: Taken together, our results are consistent with Nav1.6 promoting inflammation and contributing to axonal degeneration following demyelination.
CRIS-Team Scopus Importer:2019-11-22
Keywords: Adeno-associated virus; Conditional knockout; Experimental autoimmune encephalitis; Inflammation; Multiple sclerosis; Nav1.6; Optic nerve; Optic neuritis; Retinal ganglion cells; Scn8a; Sodium channel

Neurochemical classification of serotonin-immunoreactive neurons co-innervating motor endplates in the mouse esophagus - Zinsser-Krys, Jillena; Kapitza, Christopher; Böhnke, Lena; van der Keylen, Piet; Neuhuber, Winfried; Wörl, Jürgen (Anatomical Record, 2022)
Serotonin immunoreactivity was previously found in myenteric neurons co-innervating motor endplates in the mouse esophagus striated muscle and an involvement in motility control was suggested. However, it is not known if other neuroactive substances are present in these neurons and to what extent they co-localize. First, vasoactive intestinal peptide (VIP) was established as a bona fide marker for putative inhibitory myenteric neurons by evaluating co-localization with neuronal nitric oxide synthase (nNOS) and neuropeptide Y (NPY). Then, co-localization of serotonin and VIP was tested in co-innervating axons on motor endplates, which were visualized with α-bungarotoxin (α-BT) by multilabel immunofluorescence. Myenteric ganglia were also surveyed for co-localization in neuronal perikarya and varicosities. nNOS, NPY, and VIP were completely co-localized in enteric co-innervating nerve terminals on motor endplates. After co-staining with VIP, we found (a) serotonin (5-HT)-positive nerve endings without VIP (44% of 5-HT-positively innervated endplates), (b) 5-HT- and VIP-positive endings without co-localization (35%), and (c) 5-HT- and VIP-positive endings with co-localization (21%). About one-fifth of nerve terminals on motor endplates containing 5-HT originate from putative inhibitory peptidegic nitrergic neurons. However, the majority represents a different population presumably subserving different functions.
CRIS-Team Scopus Importer:2022-07-22
Keywords: 5-hydroxytryptamine; enteric co-innervation; neuromuscular junction; neuronal nitric oxide synthase; neuropeptide Y; vasoactive intestinal peptide

Neurocritical care complications and interventions influence the outcome in aneurysmal subarachnoid hemorrhage - Hammer, Alexander; Erbguth, Frank; Hohenhaus, Matthias; Hammer, Christian; Lücking, Hannes; Gesslein, Markus; Killer-Oberpfalzer, Monika; Steiner, Hans Herbert; Janssen, Hendrik (BMC Neurology, 2021)
Background: This observational study was performed to show the impact of complications and interventions during neurocritical care on the outcome after aneurysmal subarachnoid hemorrhage (SAH). Methods: We analyzed 203 cases treated for ruptured intracranial aneurysms, which were classified regarding clinical outcome after one year according to the modified Rankin Scale (mRS). We reviewed the data with reference to the occurrence of typical complications and interventions in neurocritical care units. Results: Decompressive craniectomy (odds ratio 21.77 / 6.17 ; p < 0.0001 / p = 0.013), sepsis (odds ratio 14.67 / 6.08 ; p = 0.037 / 0.033) and hydrocephalus (odds ratio 3.71 / 6.46 ; p = 0.010 / 0.00095) were significant predictors for poor outcome and death after one year beside “World Federation of Neurosurgical Societies” (WFNS) grade (odds ratio 3.86 / 4.67 ; p < 0.0001 / p < 0.0001) and age (odds ratio 1.06 / 1.10 ; p = 0.0030 / p < 0.0001) in our multivariate analysis (binary logistic regression model). Conclusions: In summary, decompressive craniectomy, sepsis and hydrocephalus significantly influence the outcome and occurrence of death after aneurysmal SAH.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Decompressive craniectomy; Intracranial aneurysm; Neurocritical care; Outcome; Subarachnoid hemorrhage; Vascular disorders

Neurokinin-1 Receptor Antagonists Protect Mice from CD95- and Tumor Necrosis Factor-α-Mediated Apoptotic Liver Damage - Bang, Renate; Biburger, Markus; Neuhuber, Winfried; Tiegs, Gisa (Journal of Pharmacology and Experimental Therapeutics, 2004)
Previously, we have shown that primary afferent neurons are necessary for disease activity in immune-mediated liver injury in mice. These nerve fibers are detectable by substance P (SP) immunocytochemistry in the portal tract of rodent liver. Antagonists of the neurokinin-1 receptor (NK-1R), which is the prime receptor of SP, prevented liver damage by suppressing the synthesis of proinflammatory cytokines. Here, we investigated the influence of primary afferent nerve fibers, SP, and NK-1 receptor antagonists on hepatocyte apoptosis in vivo induced by administration of activating anti-CD95 monoclonal antibody (mAb) to mice. Depletion of primary afferent nerve fibers by neonatal capsaicin treatment prevented CD95-mediated activation of caspase-3, measured as enzymatic activity in liver homogenates or by demonstration of hepatocellular immunoreactivity for active caspase-3 in liver slices, and liver damage. This effect was reversed by administration of SP to anti-CD95 mAb-treated mice depleted from primary afferent neurons. The presence of the NK-1 R on mouse hepatocytes was demonstrated by immunocytochemistry and flow cytometry. Intraperitoneal pretreatment with the NK-1 receptor antagonists (2S,3S)-cis-2-(diphenylmethyl)-N-([2-methoxyphenyl]-methyl)-1-azabicyclo(2.2.2.) -octan-3-amine (CP-96,345) or (2S,3S)3-([3,5-bis(trifluoromethyl)phenyl]methoxy)-2-phenylpiperadine (L-733,060) dose dependently protected mice from CD95-mediated liver injury. Similar results were obtained when apoptotic liver damage was induced by administration of tumor necrosis factor-α to D-galactosamine-sensitized mice. In conclusion, SP, probably by binding to its receptor on hepatocytes, might aggravate apoptotic signals in these cells. Because NK-1 receptor antagonists not only suppress the proinflammatory cytokine response in the liver but also prevent liver cell apoptosis in vivo, they might be suitable drugs for treatment of immune-mediated liver disease.

Neutrophil Extracellular Traps Drive Dacryolithiasis - Zlatar, Leticija; Timm, Thomas; Lochnit, Günter; Bilyy, Rostyslav; Bäuerle, Tobias; Munoz Becerra, Marco; Schett, Georg; Knopf, Jasmin; Heichel, Jens; Ali, Mohammad Javed; Schapher, Mirco; Paulsen, Friedrich; et al. (Cells, 2023)
Mucopeptide concretions, previously called dacryoliths, are macroscopic stones that commonly obstruct the lacrimal sac. The mechanism behind dacryolithiasis remains unclear; however, the involvement of various immune cells, including neutrophils, has been confirmed. These findings remain limited, and no information on neutrophil extracellular traps (NETs), essentially involved in the pathogenesis of other lithiases, is available yet. Here, we employ microcomputed tomography, magnetic resonance tomography, histochemistry, mass spectrometry, and enzyme activity analyses to investigate the role of neutrophils and NETs in dacryolithiasis. We classify mucopeptide concretions into three types, with respect to the quantity of cellular and acellular material, polysaccharides, and mucosubstances. We propose the role of neutrophils and NETs within the existing model of gradual formation and growth of mucopeptide concretions, with neutrophils contributing to the initial stages of dacryolithiasis, as they localized on the inner (older) parts of the tissue. As NETs localized on the outer (newer) parts of the tissue, we link their role to the late stages of dacryolithiasis, presumably maintaining the proinflammatory environment and preventing efficient clearance. An abundance of IgG on the surface indicates the involvement of the adaptive immune system later as well. These findings bring new perspectives on dacryolithiasis, in which the innate and adaptive immune system are essentially involved.
CRIS-Team Scopus Importer:2023-08-11
Keywords: dacryolithiasis; dacryoliths; lacrimal sac; mucopeptide concretions; neutrophil extracellular traps; neutrophils

New anatomy-related ratios describing the risk of incomplete colonoscopy in human patients - Wozniak, Slawomir; Kempinski, Radoslaw; Pytrus, Tomasz; Zazga, Maria; Szymocha, Marcin; Domagala, Zygmunt; Davies, D. Ceri; Paulsen, Friedrich (JOURNAL OF ANATOMY, 2021)
CRIS-Team WoS Importer:2021-02-12

New insight into tear transport through the upper and lower canaliculi of the nasolacrimal ducts - Paulsen, Friedrich; Zetzsche, Maximilian; Mohammad, Javed Ali; Heichel, Jens; Scholz, Michael; Hammer, Christian (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

New insights into lacrimal gland anatomy using 7T MRI and electron microscopy: Relevance for lacrimal gland targeted therapies and bioengineering - Singh, Swati; Winter, Zoltan; Necker, Fabian; Bäuerle, Tobias; Scholz, Michael; Bräuer, Lars; Paulsen, Friedrich (Ocular Surface, 2023)
Purpose: To study the tissue architecture, isthmus (connection between two lobes) of the lacrimal gland using preclinical 7T MRI in combination with histology and electron microscopy. Methods: Ten lacrimal glands from Caucasian body donors (mean age 78.7 years) were studied using 7T-MRI (N = 5; scanned at 75-μm intervals), histology, and electron microscopy (N = 5) and 3D cinematic rendering (CR) techniques. Results: 3D CR images showed uniform-sized lobules (widest lobule diameter, 1.68 ± 0.19 mm in orbital lobe, 1.68 ± 0.17 mm in palpebral lobe) in both lobes, separated by septae (size, 0.29 ± 0.09 mm). The internal framework of the gland resembled a honeycoomb pattern. In CR and histology, the isthmus contained glandular acini, large blood vessels, nerves, and no more than two ducts having a tortuous course towards the conjunctival surface. On assigning a color display to the rendered lacrimal gland, all glands showed a blood vessel originating from the main lacrimal artery just 5 mm beyond the hilum and making it course to the palpebral lobe via isthmus. The distance between the conjunctiva and the central substance of the orbital and palpebral lobe was 9.4 ± 0.2 mm and 2.8 ± 0.7 mm, respectively. Electron microscopy of the palpebral lobe revealed compact subepithelial layer in the overlying conjunctiva, followed by loosely scattered collagen bundles that contained the gland lobules. Conclusion: 3D-CR can be used to study the lacrimal gland microstructure, help fabricate a 3D scaffold for lacrimal gland bioprinting, and serve as guide for transconjunctival lacrimal gland targeted therapies i.e., 2.9 & 9 mm long needle to reach the orbital and palpebral lobe center, respectively in normal-size glands.
CRIS-Team Scopus Importer:2023-10-13
Keywords: 3D printing; 7T MRI; Cinematic rendering; Dry eye disease; Lacrimal gland; Palpebral lobe

New Insights Into the Anatomy of the Eyelashes With Regard to Ethnic Differences Against a Clinical Background. - Singh, Swati; Hammer, Christian; Paulsen, Friedrich (Ophthalmic Plastic and Reconstructive Surgery, 2024)
BACKGROUND: To investigate the root depth, root angle, and light and scanning electron microscopical anatomy of human eyelashes relevant to eyelash ablation. METHODS: Eyelash root depth, the angle between eyelash root and skin epithelium, spatial relationship, and scanning electron microscopical features of the eyelashes were studied on 4 upper and 4 lower eyelids of Caucasian (n = 4) and Indian (n = 4) cadaver heads according to a set protocol. RESULTS: There were significant differences in the mean eyelash root depth between Indians (2.3 ± 0.38 mm) and Caucasians (1.9 ± 0.26 mm; p = 0.007), as well as between upper eyelids and lower eyelids (1.9 ± 0.2 mm vs. 1.8 ± 0.1 mm). The mean angle between the lash follicle root and the skin epithelium was 75 ± 11 degrees and similar in both ethnic groups. The eyelash bulb was located close to the tarsal plate and meibomian glands and formed an angle of less than 15 degrees with the eyelash root. Scanning electron microscopy studies revealed that the eyelash bulb was 202 ± 12 μm wide in Indians and 170.6 ± 16.8 μm wide in Caucasian eyelids ( p = 0.08). The eyelashes were placed more closely in Indian eyelids than in Caucasian eyelids ( p = 0.03). The width of the cuticle layer varied between the hair shaft and the inner eyelid segment. CONCLUSIONS: There are differences in eyelash root depth, inter-eyelash distance, and cuticle thickness between Indian and Caucasian eyelids. The oblique orientation of the eyelash root and close proximity of the eyelash bulb to the tarsal plate should be kept in mind while doing the electroepilation procedure.
EVALuna2:545156

New insights into the lacrimal pump - Ali, Mohammad Javed; Zetzsche, Maximilian; Scholz, Michael; Hahn, Dieter; Gaffling, Simone; Heichel, Jens; Hammer, Christian; Bräuer, Lars; Paulsen, Friedrich (Ocular Surface, 2020)
Purpose: To date, there are many theories about tear transport through the canaliculi of the draining lacrimal system into the lacrimal sac but only few with supportive data. It is certain that the function of the lacrimal part of orbicularis oculi muscle (Horner-Duverney's muscle) is indispensable for the transport of “used” tears. However, the muscle's exact structure and the mechanisms of its functions are as yet unclear. To obtain deeper insights we undertook the present study. Methods: Upper and lower canaliculi (including the entrance into the lacrimal sac) from donor cadavers were dissected. Some of the specimens were prepared for scanning electron microscopy (SEM) to analyze the course of muscle fibers surrounding the canaliculi. Others were sectioned for enzyme- (EHC) and immunohistochemistry (IHC) to learn about the distribution of slow and fast reacting muscle fibers in Horner-Duverney's muscle as well as to analyze the distribution of different neurotransmitters to learn more about the innervation of Horner-Duverney's muscle. Four tear duct systems taken from body donors were cut out en bloc after formalin fixation, serially sectioned and reconstructed using a newly developed technology for 3D reconstruction of histological serial sections named HiD® (Chimaera GmbH, Germany). Patients that had undergone dacryocystorhinostomy (DCR) were video-analyzed endonasally during active blinking, focusing on viewing the temporal wall of the lacrimal sac movement where the canaliculi penetrated the lacrimal sac. Results: SEM revealed that muscle fibers of Horner-Duverney's muscle surround the vertical parts of the upper and lower canaliculus in a scissor like pattern whereas they ran in parallel to the first two thirds of the horizontal parts surrounding the respective canaliculus. Here, the muscle fibers were embedded in dense connective tissue forming a unique network. At the nasal third, muscle fibers left the canaliculi and ran to the posterior part of the fascia of the lacrimal sac and the lacrimal bone. EHC revealed that Horner-Duverney's muscle contained nearly an equal distribution of type I and type IIb muscle fibers compared to the superior rectus muscle which contains more type I and the masseter and iliopsoas muscles with more type IIb muscle fibers. IHC indicated presence of trigeminal, catecholaminergic and cholinergic nerve endings. 3D reconstructions supported the SEM data. Endonasal video analysis of patients after DCR with a nasally open lacrimal sac revealed bulging of the temporal wall of the lacrimal sac during blinking. On the basis of these findings, a modified lacrimal pump theory is proposed. Conclusion: The results support the hypothesis that contraction of Horner-Duverney's muscle leads to closure of the canaliculi in their first two thirds based on the special arrangement of muscle fibers and connective tissue fibers. This causes the tear fluid in the canaliculi to be pressed/transported towards the lacrimal sac. The medial third of the vertical portions of the canaliculi, the canaliculus communis and the intrasaccal portion of the canaliculus are compressed by the shortening and thickening of the Horner-Duverney muscle from dorsal, which leads to a compression of the canaliculi lumens in this part of the system, thereby pushing the lacrimal fluid further towards the lacrimal sac. The mix of fast contracting and fatigue resistant muscle fibers is ideally suited for the blink mechanism that is complexly regulated by the nervous system.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Canaliculus; Efferent tear ducts; Horner's muscle; Lacrimal pump; Nasolacrimal ducts; Orbicularis oculi; Tear drainage; Tear flow

Nimodipine Exerts Beneficial Effects on the Rat Oligodendrocyte Cell Line OLN-93 - Boltz, Felix; Enders, Michael; Feigenspan, Andreas; Kirchner, Philipp; Ekici, Arif Bülent; Kürten, Stefanie (Brain Sciences, 2022)
Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS). Therapy is currently limited to drugs that interfere with the immune system; treatment options that primarily mediate neuroprotection and prevent neurodegeneration are not available. Here, we studied the effects of nimodipine on the rat cell line OLN-93, which resembles young mature oligodendrocytes. Nimodipine is a dihydropyridine that blocks the voltage-gated L-type calcium channel family members Cav1.2 and Cav1.3. Our data show that the treatment of OLN-93 cells with nimodipine induced the upregulation of myelin genes, in particular of proteolipid protein 1 (Plp1), which was confirmed by a significantly greater expression of PLP1 in immunofluorescence analysis and the presence of myelin structures in the cytoplasm at the ultrastructural level. Whole-genome RNA sequencing additionally revealed the upregulation of genes that are involved in neuroprotection, remyelination, and antioxidation pathways. Interestingly, the observed effects were independent of Cav1.2 and Cav1.3 because OLN-93 cells do not express these channels, and there was no measurable response pattern in patch-clamp analysis. Taking into consideration previous studies that demonstrated a beneficial effect of nimodipine on microglia, our data support the notion that nimodipine is an interesting drug candidate for the treatment of MS and other demyelinating diseases.
CRIS-Team Scopus Importer:2022-05-06
Keywords: dihydropyridines; MS; myelination; neuroprotection; nimodipine; OLN-93

Norepinephrine stimulates the epithelial Na+ channel in cortical collecting duct cells via ?2-adrenoceptors - Mansley, Morag; Neuhuber, Winfried; Korbmacher, Christoph; Bertog, Marko (American Journal of Physiology-Renal Physiology, 2015)
There is good evidence for a causal link between excessive sympathetic drive to the kidney and hypertension. We hypothesized that sympathetic regulation of tubular Na(+) absorption may occur in the aldosterone-sensitive distal nephron, where the fine tuning of renal Na(+) excretion takes place. Here, the appropriate regulation of transepithelial Na(+) transport, mediated by the amiloride-sensitive epithelial Na(+) channel (ENaC), is critical for blood pressure control. To explore a possible effect of the sympathetic transmitter norepinephrine on ENaC-mediated Na(+) transport, we performed short-circuit current (Isc) measurements on confluent mCCDcl1 murine cortical collecting duct cells. Norepinephrine caused a complex Isc response with a sustained increase of amiloride-sensitive Isc by 44%. This effect was concentration dependent and mediated via basolateral ?2-adrenoceptors. In cells pretreated with aldosterone, the stimulatory effect of norepinephrine was reduced. Finally, we demonstrated that noradrenergic nerve fibers are present in close proximity to ENaC-expressing cells in murine kidney slices. We conclude that the sustained stimulatory effect of locally elevated norepinephrine on ENaC-mediated Na(+) absorption may contribute to the hypertensive effect of increased renal sympathetic activity.
EVALuna2:4150

Novel collagen membranes for the reconstruction of the corneal surface - Petsch, Corinna; Schlötzer-Schrehardt, Ursula; Meyer-Blazejewska, Ewa; Frey, Markus; Kruse, Friedrich; Bachmann, Björn (Tissue Engineering: Parts A, B, and C, 2014)
No standardized biomaterial exists for the surgical treatment of persistent corneal erosions and ulcerations. We analyzed the suitability and biocompatibility of defined noncross-linked and UV/riboflavin cross-linked equine type I collagen membranes for the reconstruction of the corneal surface. Isolated human oral mucosa epithelial cells, a cell type in clinical use for the treatment of ocular surface diseases, were subcultivated on both types of membranes and examined concerning cell adhesion, proliferation, and differentiation. Biocompatibility was evaluated following superficial and intrastromal corneal transplantation in New Zealand white rabbits. In cell cultures all collagen membranes supported adhesion of oral mucosa epithelial cells leading to the formation of multilayered epithelial cell sheets. After intrastromal corneal implantation clinical signs of degradation were seen in all variants of collagen membranes, which was fastest in noncross-linked variants. The histological and ultrastructural level invasion of keratocytes and production of new collagen fibers inside the collagen membranes could be detected in noncross-linked variants. After superficial corneal implantation covering of the membranes by corneal epithelium over time was visible. Ultrastructural analysis showed a slower rate of degradation and less invading keratocytes in cross-linked variants compared with noncross-linked collagen membranes. Cross-linked and noncross-linked variants of the collagen membrane proofed to be suitable to serve as a carrier for epithelial stem cells in vitro and showed a high biocompatibility in vivo. These results indicate that the tested collagen membranes might be suitable for the reconstruction of the corneal surface in patients with nonhealing ulcerations. Whether membranes with faster or slower degradation properties are preferable for the treatment of persistent corneal ulcerations might depend on the underlying corneal pathology and the degree of concomitant inflammation.
EVALuna2:21203

Novel Homozygous FA2H Variant Causing the Full Spectrum of Fatty Acid Hydroxylase-Associated Neurodegeneration (SPG35) - German, Alexander; Jukic, Jelena; Laner, Andreas; Arnold, Philipp; Socher, Eileen; Mennecke, Angelika; Schmidt, Manuel; Winkler, Jürgen; Abicht, Angela; Regensburger, Martin (Genes, 2023)
Fatty acid hydroxylase-associated neurodegeneration (FAHN/SPG35) is caused by pathogenic variants in FA2H and has been linked to a continuum of specific motor and non-motor neurological symptoms, leading to progressive disability. As an ultra-rare disease, its mutational spectrum has not been fully elucidated. Here, we present the prototypical workup of a novel FA2H variant, including clinical and in silico validation. An 18-year-old male patient presented with a history of childhood-onset progressive cognitive impairment, as well as progressive gait disturbance and lower extremity muscle cramps from the age of 15. Additional symptoms included exotropia, dystonia, and limb ataxia. Trio exome sequencing revealed a novel homozygous c.75C>G (p.Cys25Trp) missense variant in the FA2H gene, which was located in the cytochrome b5 heme-binding domain. Evolutionary conservation, prediction models, and structural protein modeling indicated a pathogenic loss of function. Brain imaging showed characteristic features, thus fulfilling the complete multisystem neurodegenerative phenotype of FAHN/SPG35. In summary, we here present a novel FA2H variant and provide prototypical clinical findings and structural analyses underpinning its pathogenicity.<br
Keywords: hereditary spastic paraplegia; SPG35; FA2H; FAHN; genetic variant modeling

Nutritional reconstruction in an early modern population: Searching for a relationship between dental microwear and bone element composition - Dąbrowski, Paweł; Kulus, Michał Jerzy; Grzelak, Joanna; Olchowy, Cyprian; Staniowski, Tomasz; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Background: Observing the microwear patterns of the dental crowns enamel surface can provide information on the ingredients and structure of the food consumed, but also on eating habits and lifestyle. Major role in reconstructing the diet and lifestyle of past populations is played by the analysis of alkaline earth metals, such as strontium, barium, zinc and calcium. Ba and Sr are indicators of the consumption of vegetables, plants (cereals and legumes) and marine organisms. This study aims to assess dietary diversity and identify its components based on microscopic techniques and chemical analyses of material from early modern archaeological sites in Wrocław, Poland. Methods: The material consisted of 36 permanent molars and the intrasternal parts of 122 first ribs, collected from 6 Wroclaw early modern cemeteries. Tooth microwear was evaluated on Scanning electron microscopy images, with Microwear 4.02 software. Bone chemical composition (Ca, P, Ba, Sr content) was evaluated with mass spectrometry. Results: Most lines were present on the teeth from St. Mary Magdalene Cemetery, with the lowest average number of lines observed on the teeth from St. Barbara Cemetery. The Ca/P ratios calculated for different sites formed two clusters that allows to distinguish two groups of archaeological sites with different bone preservation status. Number of differences in Ba/Sr, Sr/Ca, Ba/Ca ratios was found between disctinct archaeological sites. A number of correlations were found between the concentration of the chemical elements, but no statistically significant correlation was found between the microwear characteristics and the proportion of the elements studied. Some strong correlations were found between microwear features and the Ca/P ratio. Conclusions: the different values of Sr/Ca, Ba/Ca and Ba/Sr ratios indicate different diets in the different communities. The data obtained indicate a mixed diet, with a relatively high proportion of animal products throughout Wrocław. Conclusions should be treated with caution due to secondary diagenesis. The lack of interdependence between microwear and chemical composition characteristics suggests that the two methods should be considered complementary and not overlapping, as they provide different insights into the diets of past populations. The comparison of microwear between different sites should always take into account secondary diagenesis and the burial environment, as these influence the characteristics of microwear.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Bones; Dental microwear; Diagenesis; Diet reconstruction

Obinutuzumab-induced b cell depletion reduces spinal cord pathology in a cd20 double transgenic mouse model of multiple sclerosis - Breakell, Thomas; Tacke, Sabine; Schropp, Verena; Zetterberg, Henrik; Blennow, Kaj; Urich, Eduard; Kürten, Stefanie (International Journal of Molecular Sciences, 2020)
B cell-depleting therapies have recently proven to be clinically highly successful in the treatment of multiple sclerosis (MS). This study aimed to determine the effects of the novel type II anti-human CD20 (huCD20) monoclonal antibody (mAb) obinutuzumab (OBZ) on spinal cord degeneration in a B cell-dependent mouse model of MS. Double transgenic huCD20xHIGR3 (CD20dbtg) mice, which express human CD20, were immunised with the myelin fusion protein MP4 to induce experimental autoimmune encephalomyelitis (EAE). Both light and electron microscopy were used to assess myelination and axonal pathology in mice treated with OBZ during chronic EAE. Furthermore, the effects of the already established murine anti-CD20 antibody 18B12 were assessed in C57BL/6 wild-type (wt) mice. In both models (18B12/wt and OBZ/CD20dbtg) anti-CD20 treatment significantly diminished the extent of spinal cord pathology. While 18B12 treatment mainly reduced the extent of axonal pathology, a significant decrease in demyelination and increase in remyelination were additionally observed in OBZ-treated mice. Hence, the data suggest that OBZ could have neuroprotective effects on the CNS, setting the drug apart from the currently available type I anti-CD20 antibodies.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Anti-CD20; B cells; EAE; MAb; Multiple sclerosis; Neurodegeneration; Obinutuzumab

Obligation, capacity, skills and stamina - Development of a site-adapted competence profile for medical students in Germany - Scholz, Michael; Paulsen, Friedrich; Ropohl, Axel; Burger, Pascal H. M. (Annals of Anatomy-Anatomischer Anzeiger, 2018)
In order to get admission to study medicine at a German university, the most important criterion is the proof of an excellent final college prep school examination (Abitur) in order to get an adequate study place without time loss. For the purpose of a suitable selection for admission of candidates, however, the best qualified and suitable applicants should be found to be distributed to the limited available university places for medicine. The final examination mark alone can represent such a suitability - if at all - only to a very limited extent. In order to figure out which skills and competences characterize a potential medical student and after studies a well-practicing and resilient later physician, we sought for initial steps to apply competence profiling as a predictor matching suitable prerequisites to a subsequent successful outcome. In order to meet these demands, we founded a project called ComMedMent at the Friedrich Alexander University of Erlangen-Nürnberg (FAU), where we defined competences for successfully becoming a medical expert while studying the medical curriculum. Here we present a comprehensive catalogue of 16 standards and meaningful key competencies for potentially successful medical students at the FAU. In collaboration with the Center for Competence Balancing - CeKom SÜD - (Pforzheim; Germany) and a local competence team comprising institute management, lecturers and students of different educational backgrounds, a target profile for the "ideally equipped students and later successful practitioners" was established. The identification of a site-specific and/or general requirement profile for medical students could open up new perspectives for the selection process and show the opportunities for helping students along the path to becoming medical experts.
EVALuna2:35319

Obstructive sleep apnea and rhonchopathy are associated with downregulation of trefoil factor family peptide 3 (TFF3)-Implications of changes in oral mucus composition - Siber-Hoogeboom, Regina; Schicht, Martin; Hoogeboom, Sebastian; Paulsen, Friedrich; Traxdorf, Maximilian (PLoS ONE, 2017)
STUDY OBJECTIVES: Trefoil factor family (TFF) peptides belong to the family of mucin-associated peptides and are expressed in most mucosal surfaces. TFF peptides carry out functions such as proliferation and migration enhancement, anti-apoptosis, and wound healing. Moreover, TFFs are associated with mucins and interact with them as "linker peptides", thereby influencing mucus viscosity. To test the hypothesis that in rhonchopathy and obstructive sleep apnea (OSA) changes occur in the expression of TFF3 and -2 that could contribute to changes in mucus viscosity, leading to an increase in upper airway resistance during breathing. METHODS: RT-PCR, Western-blot, immunohistochemistry and ELISA were performed to detect and quantify TFF3 and -2 in uvula samples. In addition, 99 saliva samples from patients with mild, moderate or severe OSA, as well as samples from rhonchopathy patients and from healthy volunteers, were analyzed by ELISA. RESULTS: TFF3 was detected in all uvula samples. Immunohistochemistry revealed a subjectively decreasing antibody reactivity of the uvula epithelia with increasing disease severity. ELISA demonstrated significantly higher TFF3 saliva protein concentrations in the healthy control group compared to cases with rhonchopathy and OSA. Predisposing factors of OSA such as BMI or age showed no correlation with TFF3. No significant changes were observed with regard to TFF2. CONCLUSIONS: The results suggest the involvement of TFF3 in the pathogenesis of rhonchopathy and OSA and lead to the hypothesis that reduction of TFF3 production by the epithelium and subepithelial mucous glands of the uvula contribute to an increase in breathing resistance due to a change in mucus organization.
EVALuna2:35325

OCT-Angiography: agonistic beta 2-adrenergic receptor autoantibodies and FAZ-to-FAZ-ratio in glaucoma patients - Mardin, Christian Y.; Hosari, Sami; Wallukat, Gerd; Kunze, Rudolf; Herrmann, Martin; Lämmer, Robert; Hohberger, Bettina (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

OCT-Angiography: Mydriatic phenylephrine and tropicamide do not influence retinal microvasculature in macula and peripapillary region - Hohberger, Bettina; Müller, Manuela; Hosari, Sami; Mardin, Christian Y. (PLoS ONE, 2019)
PURPOSE: Optical coherence tomography angiography (OCT-A) enables visualization of retinal microcirculation. As a potential influence of mydriatic eye drops on retinal vessel density (VD) was proposed, the purpose of the present study was to investigate an influence of 5% phenylephrine and 0.5% tropicamide on macula and peripapillary VD. METHODS: 30 eyes of 30 healthy persons were measured by en face OCT-A (Spectralis OCT II, Heidelberg Engineering, Heidelberg). Scans of the macula (12 sectors, region of interest, ROI: 6.10 mm2) and peripapillary region (4 sectors, ROI: 2.67 mm2) were performed before (-) and 30 minutes after application of phenylephrine 5% and tropicamide 0.5% (+) eye drops (scan size was 8.41 mm2). Macula microcirculation was quantified in 3 retinal layers (superficial vascular plexus (SVP), deep capillary plexus (DCP), intermediate capillary plexus (ICP)). Data analysis was performed with the Erlangen-Angio-Tool. RESULTS: (I) Mean VD was 33.03±2.3 (SVP), 23.53±2.9 (ICP) and 25.48±4.2 (DCP) before and 33.12±2.4 (SVP), 23.74±2.9 (ICP) and 25.82±4.0 (DCP) with mydriasis respectively. (II) Sectorial analysis: 30.63±2.9-34.45±2.9 (-) and 31.04±2.9-34.34±2.7 (+) in SVP; 22.61±2.9-24.93±3.2 (-) and 22.75±2.5-25.20±3.0 (+) in ICP; 24.56±4.7-26.45±3.4 (-) and 25.00±4.1-27.07±3.5 (+) in DCP. (III) Peripapillary region showed a mean VD of 31.82±3.8 before and 31.59±4.3 after mydriasis. Sectorial analysis of VD yielded a range of 31.04±4.1-32.65±3.8 (-) and 30.98±4.4-31.89±4.1 (+). (IV) Macula and peripapillary VD were not different before and after mydriasis (p>0.05). CONCLUSION: Pharmacologic mydriasis did not influence retinal microcirculation in macula and peripapillary region enabling OCT-A scans with enhanced imaging process and scan quality.
CRIS-Team Scopus Importer:2019-10-25

Ocular Phenotype of Relaxin Gene Knockout (Rln-/-) Mice - Hampel, Ulrike; Chinnery, Holly R.; Garreis, Fabian; Paulsen, Friedrich; de Iongh, Robb; Bui, Bang V.; Nguyen, Christine; Parry, Laura; Chen, Huei Leo (Current Eye Research, 2020)
Purpose: To test if relaxin deficiency affects ocular structure and function we investigated expression of relaxin (Rln) and RXFP receptors (Rxfp1, Rxfp2), and compared ocular phenotypes in relaxin gene knockout (Rln−/−) and wild type (Rln+/+) mice. Materials and Methods: Rln, Rxfp1 and Rxfp2 mRNA expression was detected in ocular tissues of Rln+/+ mice using RT-PCR. The eyes of 11 Rln−/− and 5 Rln+/+ male mice were investigated. Corneal and retinal thickness was assessed using optical coherence tomography. Intraocular pressure was measured using a rebound tonometer. Retinal, choroidal and sclera morphology and thickness were evaluated histologically. Eyes were collected and fixed for immunofluorescence staining or used for RNA extraction to evaluate mRNA expression using real-time PCR. Results: Rln mRNA was expressed only in the retina, whereas Rxfp1 transcripts were detected in the retina, cornea and sclera/choroid. Rxfp2 was only present in the cornea. None of these genes were expressed in the lacrimal gland, eyelid or lens. Intraocular pressure was higher and central cornea of Rln−/− mice was significantly thicker and had significantly larger endothelial cells and a lower endothelial cell density than Rln+/+ mice. Immunohistochemistry demonstrated no significant difference in AQP3 and AQP5 staining in the cornea or other regions between wildtype and Rln−/− mice. mRNA expression of Aqp4 was significantly higher in Rln−/− than in Rln+/+ corneas, whereas Col1a2, Mmp9, Timp1 and Timp2 were significantly decreased. Expression of Aqp1, Aqp4, Aqp5, Vim and Tjp1 was significantly decreased in Rln−/− compared to Rln+/+ uvea. No significant differences in these genes were detected in the retina. Retinal, choroidal and scleral thicknesses were not different and morphology appeared normal. Conclusion: The findings indicate that loss of Rln affects expression of several genes in the uvea and cornea and results in thicker corneas with altered endothelial cells. Many of the gene changes suggest alterations in extracellular matrix and fluid transport between cells.
CRIS-Team Scopus Importer:2020-03-27
Keywords: corneal thickness; phenotype eye; Relaxin knockout

Ocular surface changes in mice with streptozotocin-induced diabetes and diabetic polyneuropathy - Schicht, Martin; Farger, Jessica; Wedel, Saskia; Sisignano, Marco; Scholich, Klaus; Geisslinger, Gerd; Perumal, Natarajan; Grus, Franz H.; Singh, Swati; Sahin, Afsun; Paulsen, Friedrich; Lütjen-Drecoll, Elke (Ocular Surface, 2024)
Purpose: Diabetes mellitus (DM) is a leading risk factor for corneal neuropathy and dry eye disease (DED). Another common consequence of DM is diabetic peripheral polyneuropathy (DPN). Both complications affect around 50 % of the DM patients but the relationship between DM, DED and DPN remains unclear. Methods: In this study, we examined mice with early onset of DM and PN after streptozotocin (STZ)-induced diabetes (DPN). We compared the early morphological changes of the sciatic nerve, dorsal root and trigeminal ganglia with the changes in the ocular surface, including tear proteomic and we also investigated respective changes in the gene expressions and morphological alterations in the eye tissues involved in tear production. Results: The lacrimal gland, conjunctival goblet cells and cornea showed morphological changes along with alterations in tear proteins without any obvious signs of ocular surface inflammation. The gene expression for respectively altered tear proteins i.e., of Clusterin in cornea, Car6, Adh3a1, and Eef1a1 in eyelids, and Pigr in the lacrimal gland also showed significant changes compared to control mice. In the trigeminal ganglia like in the dorsal root ganglia neuronal cells showed swollen mitochondria and, in the latter, there was a significant increase of NADPH oxidases and MMP9 suggestive of oxidative and neuronal stress. In the dorsal root ganglia and the sciatic nerve, there was an upregulation of a number of pro-inflammatory cytokines and pain-mediating chemokines. Conclusion: The early ocular changes in DM Mice only affect the lacrimal gland. Which, is reflected in the tear film composition of DPN mice. Due to the high protein concentration in tear fluid in humans, proteomic analysis in addition to noninvasive investigation of goblet cells and cornea can serve as a tools for the early diagnosis of DPN, DED in clinical practice. Early treatment could delay or even prevent the ocular complications of DM such as DED and PN.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Diabetes mellitus (DM); Dry eye disease (DED); Ocular surface; Polyneuropathies (PN); Tear film

Oligophrenin-1 (Ophn1) is expressed in mouse retinal vessels - Sel, Saadettin; Kaiser, Maja; Nass, Norbert; Trau, Stefanie; Roepke, Albrecht; Storsberg, Joachim; Hampel, Ulrike; Paulsen, Friedrich; Kalinski, Thomas (Gene Expression Patterns, 2012)
The Rho GTPase activating protein (RhoGAP) Oligophrenin 1 (Ophn1) regulates numerous members of the Rho family that are involved in neuronal morphogenesis of the central and peripheral nervous system. In the present study we investigated the spatial and temporal expression of Ophn1 in the mouse eye. The expression of Ophn1 was analysed on both mRNA and protein level. To identify the Ophn1 transcripts, adult retina and cerebrum (positive control) of postnatal day (P) 158 was subjected to reverse transcription polymerase chain reaction (RT-PCR) and sequencing of the amplified cDNA. The Ophn1 protein was analyzed in adult retina by Western blotting and in developing eyes at embryonic day (E) 12, E14, E16, E18, P0, P3, P7, P14 and P158 by immunohistochemistry. Ophn1 transcripts were detected in adult retina by RT-PCR and confirmed by sequencing. Western blot analysis revealed the expression of Ophn1 protein in the adult retina. Immunohistochemical examination of developing eyes localized the protein to retinal vasculature with an onset of Ophn1 expression from P14 onwards. The specific expression pattern suggests that Ophn1 could have a physiological role in the retinal vasculatures. At P14, the vessel development in the retina is widely completed, implying that Ophn1 has either a function during adulthood or for the generation of the intermediate plexus during the late vessel development of the retina.
EVALuna2:4385

Optical imaging techniques in engineering thermodynamics - Bräuer, Lars; Zigan, Lars; Fröba, Andreas Paul; Wensing, Michael; Leipertz, Alfred; Will, Stefan (Kick-off Symposium Optical Imaging Center Erlangen, 2013)

Optimization of polycaprolactone‑ based nanofiber matrices for the cultivation of corneal endothelial cells - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas A. (Nature Medicine, 2021)
Posterior lamellar transplantation of the eye’ s cornea (DSAEK, DMEK) currently is the gold standard for treating patients with corneal endothelial cell and back surface pathologies resulting in functional impairment. An artificial biomimetic graft carrying human corneal endothelium could minimize the dependency on human donor corneas giving access to this vision‑restoring surgery to large numbers of patients, thus reducing current long waiting lists. In this study, four groups of electrospun nanofibrous scaffolds were compared: polycaprolactone (PCL), PCL/collagen, PCL/gelatin and PCL/chitosan. Each of the scaffolds were tissue‑engineered with human corneal endothelial cells (HCEC‑B4G12) and analyzed with regard to their potential application as artificial posterior lamellar grafts. Staining with ZO‑1 and Na+/K+‑ATPase antibodies revealed intact cell functionalities. It could be shown, that blending leads to decreasing contact angle, whereby a heterogeneous blend morphology could be revealed. Scaffold cytocompatibility could be confirmed for all groups via live/dead staining, whereby a significant higher cell viability could be observed for the collagen and gelatine blended matrices with 97 ± 3% and 98 ± 2% living cells respectively. TEM images show the superficial anchoring of the HCECs onto the scaffolds. This work emphasizes the benefit of blended PCL nanofibrous scaffolds for corneal endothelial keratoplast

Optimization of polycaprolactone - based nanofiber matrices for the cultivation of corneal endothelial cells - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas A. (Scientific Reports, 2021)

Organization of sympathetic innervation of interscapular brown adipose tissue in the mouse - Huesing, Clara; Zhang, Rui; Gummadi, Sanjeev; Lee, Nathan; Qualls-Creekmore, Emily; Yu, Sangho; Morrison, Christopher D.; Burk, David; Berthoud, Hans Rudolf; Neuhuber, Winfried; Munzberg, Heike (Journal of Comparative Neurology, 2021)
The interscapular brown adipose tissue (iBAT) is under sympathetic control, and recent studies emphasized the importance of efferent sympathetic and afferent sensory or humoral feedback systems to regulate adipose tissue function and overall metabolic health. However, functional studies of the sympathetic nervous system in the mouse are limited, because details of anatomy and fine structure are lacking. Here, we used reporter mice for tyrosine hydroxylase expressing neurons (TH:tomato mice), iDISCO tissue clearance, confocal, lightsheet, and electron microscopy to clarify that (a) iBAT receives sympathetic input via dorsal rami (instead of often cited intercostal nerves); (b) dorsal rami T1-T5 correspond to the postganglionic input from sympathetic chain ganglia (stellate/T1-T5); (c) dorsal rami serve as conduits for sympathetic axons that branch off in finer nerve bundles to enter iBAT; (d) axonal varicosities show strong differential innervation of brown (dense innervation) versus white (sparse innervation) adipocytes, that surround the core iBAT in the mouse and are intermingled in human adipose tissues, (e) axonal varicosities can form neuro-adipocyte junctions with brown adipocytes. Taken together, we demonstrate that sympathetic iBAT innervation is organized by specific nerves and terminal structures that can be surgically and genetically accessed for neuromodulatory purposes.
CRIS-Team WoS Importer:2021-12-24

Orthodontic bonding to silicate ceramics: impact of different pretreatment methods on shear bond strength between ceramic restorations and ceramic brackets - Jungbauer, Rebecca; Kirschneck, Christian; Hammer, Christian; Proff, Peter; Edelhoff, Daniel; Stawarczyk, Bogna (Clinical Oral Investigations, 2021)
Objective: The study aims to investigate the shear bond strength (SBS) between silicate ceramic restorations and ceramic brackets after different pretreatments and aging methods. Material and methods: Leucite (LEU) and lithium disilicate (LiSi) specimens were pretreated with (i) 4% hydrofluoric acid + silane (HF), (ii) Monobond Etch&Prime (MEP), (iii) silicatization + silane (CoJet), and (iv) SiC grinder + silane (SiC). Molars etched (phosphoric acid) and conditioned acted as comparison group. SBS was measured after 24 h (distilled water, 37 °C), 500 × thermocycling (5/55 °C), and 90 days (distilled water, 37 °C). Data was analyzed using Shapiro–Wilk, Kruskal–Wallis with Dunn’s post hoc test and Bonferroni correction, Mann–Whitney U, and Chi2 test (p < 0.05). The adhesive remnant index (ARI) was determined. Results: LEU pretreated with MEP showed lower SBS than pretreated with HF, CoJet, or SiC. LiSi pretreated with MEP resulted in lower initial SBS than pretreated with HF or SiC. After thermocycling, pretreatment using MEP led to lower SBS than with CoJet. Within LiSi group, after 90 days, the pretreatment using SiC resulted in lowest SBS values. After HF and MEP pretreatment, LEU showed lower initial SBS than LiSi. After 90 days of water storage, within specimens pretreated using CoJet or SiC showed LEU higher SBS than LiSi. Enamel presented higher or comparable SBS values to LEU and LiSi. With exception of MEP pretreatment, ARI 3 was predominantly observed, regardless the substrate, pretreatment, and aging level. Conclusions: MEP pretreatment presented the lowest SBS values, regardless the silicate ceramic and aging level. Further research is necessary. Clinical relevance: There is no need for intraoral application of HF for orthodontic treatment.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Ceramic bracket; Orthodontic bonding; Pretreatment; Shear bond strength; Silicate ceramic

Osteopontin is induced by TGF-?2 and regulates metabolic cell activity in cultured human optic nerve head astrocytes - Neumann, Carolin; Garreis, Fabian; Paulsen, Friedrich; Hammer, Christian; Birke, Marco T.; Scholz, Michael (PLoS ONE, 2014)
The aqueous humor (AH) component transforming growth factor (TGF)-?2 is strongly correlated to primary open-angle glaucoma (POAG), and was shown to up-regulate glaucoma-associated extracellular matrix (ECM) components, members of the ECM degradation system and heat shock proteins (HSP) in primary ocular cells. Here we present osteopontin (OPN) as a new TGF-?2 responsive factor in cultured human optic nerve head (ONH) astrocytes. Activation was initially demonstrated by Oligo GEArray microarray and confirmed by semiquantitative (sq) RT-PCR, realtime RT-PCR and western blot. Expressions of most prevalent OPN receptors CD44 and integrin receptor subunits ?V, ?4, ? 5, ?6, ?9, ?1, ?3 and ?5 by ONH astrocytes were shown by sqRT-PCR and immunofluorescence labeling. TGF-?2 treatment did not affect their expression levels. OPN did not regulate gene expression of described TGF-?2 targets shown by sqRT-PCR. In MTS-assays, OPN had a time- and dose-dependent stimulating effect on the metabolic activity of ONH astrocytes, whereas TGF-?2 significantly reduced metabolism. OPN signaling via CD44 mediated a repressive outcome on metabolic activity, whereas signaling via integrin receptors resulted in a pro-metabolic effect. In summary, our findings characterize OPN as a TGF-?2 responsive factor that is not involved in TGF-?2 mediated ECM and HSP modulation, but affects the metabolic activity of astrocytes. A potential involvement in a protective response to TGF-?2 triggered damage is indicated, but requires further investigation.
EVALuna2:4415

Oxidized Hyaluronic Acid-Gelatin-Based Hydrogels for Tissue Engineering and Soft Tissue Mimicking - Kuth, Sonja; Karakaya, Emine; Reiter, Nina; Schmidt, Lorenz-Peter; Paulsen, Friedrich; Tessmar, Jorg; Budday, Silvia; Boccaccini, Aldo R. (Tissue Engineering - Part C: Methods, 2022)
Hydrogels are ideal materials for mimicking and engineering soft tissue. Hyaluronic acid is a linear polysaccharide native to the human extracellular matrix. In this study, we first develop and characterize two hydrogel compositions built from oxidized HA and gelatin with and without alginate-di-aldehyde (ADA) crosslinked by ionic and enzymatic agents with potential applications in soft tissue engineering and tissue mimicking structures. The stability under incubation conditions was improved by adjusting crosslinking times. Through large-strain mechanical measurements, the hydrogels' properties were compared to human brain tissue and the samples containing ADA revealed similar mechanical properties to the native tissue specimens in cyclic compression-tension. In vitro characterization demonstrated a high viability of encapsulated mouse embryonic fibroblasts and a spreading of the cells in case of ADA-free samples.
CRIS-Team WoS Importer:2022-05-20

Oxidized silicon nanoparticles and iron oxide nanoparticles for radiation therapy - Klein, Stefanie; Kizaloglu, Melek; Dell'Acriprete, M. L.; Neuhuber, Winfried; Distel, Luitpold; Gonzales, M. C.; Kryschi, Carola (2016)
EVALuna2:33050

Oxidized silicon nanoparticles for radiosensitization of cancer and tissue cells - Klein, Stefanie; Dell'Arciprete, Maria L.; Wegmann, Marc; Distel, Luitpold; Neuhuber, Winfried; Gonzalez, Monica C.; Kryschi, Carola (Biochemical and Biophysical Research Communications, 2013)
The applicability of ultrasmall uncapped and aminosilanized oxidized silicon nanoparticles (SiNPs and NH-SiNPs) as radiosensitizer was studied by internalizing these nanoparticles into human breast cancer (MCF-7) and mouse fibroblast cells (3T3) that were exposed to X-rays at a single dose of 3Gy. While SiNPs did not increase the production of reactive oxygen species (ROS) in X-ray treated cells, the NH-SiNPs significantly enhanced the ROS formation. This is due to the amino functionality as providing positive surface charges in aqueous environment. The NH-SiNPs were observed to penetrate into the mitochondrial membrane, wherein these nanoparticles provoked oxidative stress. The NH-SiNPs induced mitochondrial ROS production was confirmed by the determination of an increased malondialdehyde level as representing a gauge for the extent of membrane lipid peroxidation. X-ray exposure of NH-SiNPs incubated MCF-7 and 3T3 cells increased the ROS concentration for 180%, and 120%, respectively. Complementary cytotoxicity studies demonstrate that these silicon nanoparticles are more cytotoxic for MCF-7 than for 3T3 cells. © 2013 Elsevier Inc.

Pain-induced skin autoimmunity - Odoardi, Francesca; Neuhuber, Winfried; Fluegel, Alexander (Cell Research, 2014)
A recent paper published in Nature reports sensory nerve fibers in the skin that give local immune cells important instructions for the organization of an immune response; in this particular case the cooperation between the nervous and immune systems had disastrous consequences, namely an auto-destruction of the skin.
EVALuna2:4145

Palate Lung Nasal Clone (PLUNC), a Novel Protein of the Tear Film: Three-Dimensional Structure, Immune Activation, and Involvement in Dry Eye Disease (DED) - Schicht, Martin; Rausch, Felix; Beron, Martin; Jacobi, Christina; Garreis, Fabian; Hartjen, Nadine; Beileke, Stephanie; Kruse, Friedrich; Bräuer, Lars; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2015)
Palate Lung Nasal Clone (PLUNC) is a hydrophobic protein belonging to the family of surfactant proteins that is involved in fluid balance regulation of the lung. Moreover, it is known to directly act against gram-negative bacteria. The purpose of this study was to investigate the possible expression and antimicrobial role of PLUNC at the healthy ocular surface and in tears of patients suffering from dry eye disease (DED).Bioinformatics and biochemical and immunologic methods were combined to elucidate the structure and function of PLUNC at the ocular surface. Tissue-specific localization was performed by using immunohistochemistry. The PLUNC levels in tear samples from non-Sjögren's DED patients with moderate dry eye suffering either from hyperevaporation or tear deficiency were analyzed by ELISA and compared with tears from healthy volunteers.Palate Lung Nasal Clone is expressed under healthy conditions at the ocular surface and secreted into the tear film. Protein modeling studies and molecular dynamics simulations performed indicated surface activity of PLUNC. In vitro experiments revealed that proinflammatory cytokines and bacterial supernatants have only a slight effect on the expression of PLUNC in HCE and HCjE cell lines. In tears from DED patients, the PLUNC concentration is significantly increased (7-fold in evaporative dry eye tears and 17-fold in tears from patients with tear deficiency) compared with healthy subjects.The results show that PLUNC is a protein of the tear film and suggest that it plays a role in fluid balance and surface tension regulation at the ocular surface.
EVALuna2:4442

Pancreas morphogenesis and homeostasis depends on tightly regulated Zeb1 levels in epithelial cells - Losada, Maria Lasierra; Pauler, Melissa; Vandamme, Niels; Goossens, Steven; Berx, Geert; Leppkes, Moritz; Schuhwerk, Harald; Brabletz, Simone; Brabletz, Thomas; Stemmler, Marc (Cell Death Discovery, 2021)
The pancreas is comprised of exocrine and endocrine compartments releasing digestive enzymes into the duodenum and regulating blood glucose levels by insulin and glucagon release. Tissue homeostasis is depending on transcription factor networks, involving Ptf1α, Ngn3, Nkx6.1, and Sox9, which are already activated during organogenesis. However, proper organ function is challenged by diets of high sugar and fat content, increasing the risk of type 2 diabetes and other disorders. A detailed understanding of processes that are important for homeostasis and are impaired during type 2 diabetes is lacking. Here, we show that Zeb1—a transcription factor known for its pivotal role in epithelial-mesenchymal transition, cell plasticity, and metastasis in cancer—is expressed at low levels in epithelial cells of the pancreas and is crucial for organogenesis and pancreas function. Loss of Zeb1 in these cells result in an increase of islet mass, impaired glucose tolerance, and sensitizes to develop liver and pancreas steatosis during diabetes and obesity. Interestingly, moderate overexpression of Zeb1 results in severe pancreas agenesis and lethality after birth, due to islet insufficiency and lack of acinar structures. We show that Zeb1 induction interferes with proper differentiation, cell survival, and proliferation during pancreas formation, due to deregulated expression of endocrine-specific transcription factors. In summary, our analysis suggests a novel role of Zeb1 for homeostasis in epithelial cells that is indispensable for pancreas morphogenesis and proper organ function involving a tight regulation of Zeb1 expression.
CRIS-Team Scopus Importer:2021-06-18

Partial, selective survival of nitrergic neurons in chagasic megacolon - Jabari, Samir; Da Silveira, Alexandre B.M.; De Oliveira, Enio; Neto, Salustiano D.; Quint, Karl; Neuhuber, Winfried; Brehmer, Axel (Histochemistry and Cell Biology, 2011)
One frequent chronic syndrome of Chagas' disease is megacolon, an irreversible dilation of a colonic segment. Extensive enteric neuron loss in the affected segment is regarded as key factor for deficient motility. Here, we assessed the quantitative balance between cholinergic and nitrergic neurons representing the main limbs of excitatory and inhibitory colonic motor innervation, respectively. From surgically removed megacolonic segments of four patients, each three myenteric wholemounts (from non-dilated oral, megacolonic and non-dilated anal parts) was immunohistochemically triple-stained for choline acetyltransferase, neuronal nitric oxide synthase (NOS) and the panneuronal human neuronal protein Hu C/D. Degenerative changes were most pronounced in the megacolonic and anal regions, e.g. bulked, honeycomb-like ganglia with few neurons which were partly enlarged or atrophic or vacuolated. Neuron counts from each 15 ganglia of 12 megacolonic wholemounts were compared with those of 12 age- and region-matched controls. Extensive neuron loss, mainly in megacolonic and anal wholemounts, was obvious. In all three regions derived from megacolonic samples, the proportion of NOS-positive neurons (control: 55%) was significantly increased: in non-dilated oral parts to 61% (p = 0.003), in megacolonic regions to 72% (p < 0.001) and in non-dilated anal regions to 78% (p < 0.001). We suggest the chronic dilation of megacolonic specimens to be due to the preponderance of the nitrergic, inhibitory input to the intestinal muscle. However, the observed neuronal imbalance was not restricted to the dilated regions: the non-dilated anal parts may be innervated by ascending, cholinergic axons emerging from less affected, more anally located regions. © 2010 The Author(s).
Keywords: Acquired hypoganglionosis; Enteric nervous system; Myenteric plexus; Neurodegeneration

Pathogenesis and Diagnosis of Proximal Hamstring Tendinopathies. - Schroeter, Sarah; Heiß, Rafael; Hammer, Christian; Best, Raymond; Brucker, Peter; Hinterwimmer, Stefan; Grim, Casper; Engelhardt, Martin; Hotfiel, Thilo (Sportverletzung-Sportschaden, 2024)
The proximal hamstring complex is a highly vulnerable area that is especially prone to injury. Proximal hamstring tendinopathies (PHTs) remain challenging in diagnosis, treatment, rehabilitation, and prevention due to a large variety of different injuries, slow healing response, persistent symptoms, and functional impairments. PHTs are often misdiagnosed or underdiagnosed, leading to delayed treatment and therapy failure. In addition, many athletes are at a high risk of PHT recurrence, a leading cause of prolonged rehabilitation and impaired individual performance. Until now, there have been no clear criteria for the diagnosis and classification of PHT. Tendinopathies can be graded based on their symptoms and onset. Additionally, radiological characteristics exist that describe the severity of tendinopathies. The diagnosis usually includes a battery of pain provocation tests, functional tests, and imaging to ensure a proper classification. Understanding the specific tasks in the pathogenesis and diagnostic process of PHT requires knowledge of functional anatomy, injury pattern and pathophysiological mechanisms as well as examination and imaging techniques. This work provides a structured overview of the pathogenesis and diagnostic work-up of PHT, emphasizing structured examination and imaging to enable a reliable diagnosis and rapid treatment decisions.
EVALuna2:547142

Pathophysiology of Meibomian Glands - An Overview - Dietrich, Jana; Garreis, Fabian; Paulsen, Friedrich (Ocular Immunology and Inflammation, 2021)
Purpose: The meibomian glands are located in the tarsal plate of the upper and lower eyelid and are responsible for the production of a lipid-rich secretion, the meibum, which forms the outer component of the tear film. Meibomian gland dysfunction results in excessive evaporation of the tear film and is the leading cause of dry eye disease (DED). Despite the high prevalence of DED, the etiology of meibomian gland dysfunction is only basically understood. In addition, the molecular mechanisms of meibomian gland maturation and physiological function are currently the focus of research. Methods: A systematic literature search was performed using the main scientific databases, including all relevant published articles up to September 2020. Results: This article provides an overview of the current state of knowledge about meibomian gland stem cells, cell surface marker expression and PPAR gamma signaling, as well as the pathological causes of meibomian gland dysfunction. Conclusion: Androgen deficiency, hyperkeratinization, PPAR gamma signaling and inflammatory reactions including neutrophil extracellular traps (NETs) seem to be key factors within the pathological processes of the meibomian gland.
CRIS-Team WoS Importer:2021-05-28

Pattern of lipofuscin pigmentation in nitrergic and non-nitrergjc, neurofilament immunoreactive myenteric neuron types of human small intestine - Brehmer, Axel; Blaser, Barbara; Seitz, Gerhard; Schrödl, Falk; et al. (Histochemistry and Cell Biology, 2004)
Lipofuscin, an autofluorescent age pigment, occurs in enteric neurons. Due to its broad excitation and emission spectra, it overlaps with commonly used fluorophores in immunohistochemistry. We investigated the pattern of lipofuscin pigmentation in neurofilament (NF)-reactive nitrergic and non-nitrergic human myenteric neuron types. Subsequently, we tested two methods for reduction of lipofuscin-like autofluorescence. Myenteric plexus/longitudinal muscle wholemounts of small intestines of five patients undergoing surgery for carcinoma (aged between 18 and 69 years) were double stained for NF and neuronal nitric oxide synthase (nNOS). Lipofuscin pigmentation patterns were semiquantitatively evaluated by using confocal laser scanning microscopy with three different excitation wave lengths (one for undisturbed lipofuscin autofluorescence and two for specific labellings). Two pigmentation patterns could be detected in the five NF-reactive neuron types investigated. In nitrergic/spiny as well as in non-nitrergic/stubby neurons, coarse, intensely autofluorescent pigment granules were prominent. In non-nitrergic type II, III and V neurons, a fine granular, diffusely distributed and less intensely autofluorescent pigment was obvious. After incubation of wholemounts in either CuSO or Sudan black B solutions, unspecific autofluorescence could be substantially reduced whereas specific NF and nNOS fluorescence remained largely unaffected. We conclude that NF immunohistochemistry is useful for morphological representation of subpopulations of human myenteric neurons. The lipofuscin pigmentation in human myenteric neurons reveals at least two different patterns which can be related to distinct neuron types. Incubations of multiply stained whole mounts in both CuSO or Sudan black B are suitable methods for reducing autofluorescence thus facilitating discrimination between specific (immunohistochemical) and non-specific (lipofuscin) fluorescence.
Keywords: Age; Autofluorescence; Gut; Innervation

Performance control after arthroscopic arthrolysis with capsulectomy in fresh-frozen elbow joints - Nietschke, R.; Schneider, M. M.; Hollinger, B.; Buder, Thomas; Zimmerer, A.; Zimmermann, F.; Burkhart, K. J. (Unfallchirurg, 2019)
Background and objective Posttraumatic or postoperative movement restrictions in elbow joints can often occur (including capsular contracture) and can generate everyday limitations. In persistent elbow stiffness, arthroscopic arthrolysis with removal of the dorsal and ventral capsule portions can be carried out. The purpose of this study was to assess the efficacy of arthroscopic capsulectomy by means of an in vitro anatomical study. Methods A standardized elbow arthroscopy with ventral and dorsal capsulectomy was performed and image-documented in five fresh-frozen elbow specimens. Subsequently, open dissection of the elbow joint was performed to analyze the amount of residual capsule by means of photodocumentation of the specimens. Results Regardless of the surgeon and surgical experience, anterior and posterior remnants of the capsule remained in all specimens. Dorsal capsule strands around the standard arthroscopy portals were noticed particularly more often in the area of the high dorsolateral camera portal. An incomplete capsulectomy was seen on the ulnar side at the level of the posterior medial ligament (PML) in the immediate vicinity of the ulnar nerve. Ventrally, a capsulectomy was performed from the radial side and also the ulnar side until the brachialis muscle and additionally a complete capsulectomy as far as the anterior medial ligament (AML) and radial collateral ligament (RCL) was achieved. The capsule was completely resected in a proximal direction. Distally, irrelevant capsular remnants were found in the region of the annular ligament and distal of the tip of the coronoid process. Conclusion Arthroscopic arthrolysis can be performed with a high degree of radicality. The radicality must be self-critically taken into account in one's own action. The radicality of the portal change may even be higher ventrally than with an isolated column procedure. On the other hand, it must be critically considered that posteriorly, the PML cannot be adequately addressed by means of arthroscopy due to the risk of ulnar nerve injury. Portal changes might help to enable a more complete visualization of the joint capsule and may avoid leaving possibly relevant remnants of the capsule. If a release of the PML is required, this may have to be carried out in combination with an ulnar nerve release in a mini-open technique.
CRIS-Team WoS Importer:2019-10-18

Perioperative and postoperative risk factors for corneal graft failure - Yu, Alice L.; Kaiser, Michaela; Schaumberger, Markus; Messmer, Elisabeth; Kook, Daniel; Welge-Lüssen, Ulrich-Christoph (Clinical Ophthalmology, 2014)
In this study, we assessed the outcome of penetrating keratoplasties using organ-cultured corneal tissues at the University Eye Hospital, Ludwig-Maximilians-University, Munich, Germany. The goal was to identify perioperative and postoperative risk factors that may affect graft survival.The medical records of 377 patients who underwent a penetrating keratoplasty between 2001 and 2011 were reviewed. Organ-cultured corneal tissue was obtained from the eye bank of Ludwig-Maximilians-University. Perioperative and postoperative risk factors for graft failure were evaluated by univariate and multivariate analyses.The 5-year overall survival rate of penetrating keratoplasties was 68%. Graft failure occurred in 26% of patients. High-risk keratoplasties, such as repeat penetrating keratoplasties and emergency penetrating keratoplasties, as well as postoperative conditions, such as glaucoma, retinal surgery, suture problems, persistent epithelial defect, infectious keratitis, and graft rejection, were significantly associated with graft failure in the multivariate analyses.This study showed a similar graft-survival rate as demonstrated in previous studies. In addition, a number of perioperative and postoperative risk factors were identified in this specific patient population.
EVALuna2:21200

Personalized Chest Computed Tomography: Minimum Diagnostic Radiation Dose Levels for the Detection of Fibrosis, Nodules, and Pneumonia - May, Matthias; Heiß, Rafael; Köhnen, Julia; Wetzl, Matthias; Wiesmüller, Marco; Treutlein, Christoph; Uder, Michael; Kopp, Markus; Bräuer, Lars (Investigative Radiology, 2022)
OBJECTIVES: The purpose of this study was to evaluate the minimum diagnostic radiation dose level for the detection of high-resolution (HR) lung structures, pulmonary nodules (PNs), and infectious diseases (IDs). MATERIALS AND METHODS: A preclinical chest computed tomography (CT) trial was performed with a human cadaver without known lung disease with incremental radiation dose using tin filter-based spectral shaping protocols. A subset of protocols for full diagnostic evaluation of HR, PN, and ID structures was translated to clinical routine. Also, a minimum diagnostic radiation dose protocol was defined (MIN). These protocols were prospectively applied over 5 months in the clinical routine under consideration of the individual clinical indication. We compared radiation dose parameters, objective and subjective image quality (IQ). RESULTS: The HR protocol was performed in 38 patients (43%), PN in 21 patients (24%), ID in 20 patients (23%), and MIN in 9 patients (10%). Radiation dose differed significantly among HR, PN, and ID (5.4, 1.2, and 0.6 mGy, respectively; P < 0.001). Differences between ID and MIN (0.2 mGy) were not significant (P = 0.262). Dose-normalized contrast-to-noise ratio was comparable among all groups (P = 0.087). Overall IQ was perfect for the HR protocol (median, 5.0) and decreased for PN (4.5), ID-CT (4.3), and MIN-CT (2.5). The delineation of disease-specific findings was high in all dedicated protocols (HR, 5.0; PN, 5.0; ID, 4.5). The MIN protocol had borderline IQ for PN and ID lesions but was insufficient for HR structures. The dose reductions were 78% (PN), 89% (ID), and 97% (MIN) compared with the HR protocols. CONCLUSIONS: Personalized chest CT tailored to the clinical indications leads to substantial dose reduction without reducing interpretability. More than 50% of patients can benefit from such individual adaptation in a clinical routine setting. Personalized radiation dose adjustments with validated diagnostic IQ are especially preferable for evaluating ID and PN lesions.
CRIS-Team Scopus Importer:2022-02-25

Pharmacologic stabilization of hypoxia-inducible transcription factors protects developing mouse brain from hypoxia-induced apoptotic cell death - Trollmann, Regina; Richter, Markus; Jung, Susan; Walkinshaw, G.; Brackmann, Florian (Neuroscience, 2014)
Accumulation of hypoxia-inducible transcription factors (HIFs) by prolyl-4-hydroxylase inhibitors (PHI) has been suggested to induce neuroprotection in the ischemic rodent brain. We aimed to investigate in vivo effects of a novel PHI on HIF-regulated neurotrophic and pro-apoptotic factors in the developing normoxic and hypoxic mouse brain.Neonatal mice (P7) were treated with PHI FG-4497 (30-100mg/kg, i.p.) followed by exposure to systemic hypoxia (8% O2, 6h) 4h later. Cerebral expression of HIF?-subunits, specific neurotrophic and vasoactive target genes (vascular endothelial growth factor (VEGF), adrenomedullin (ADM), erythropoietin (EPO), inducible nitric oxide synthase (iNOS)) as well as pro-apoptotic (BCL2/adenovirus E1B 19-kDa protein-interacting protein 3 gene (BNIP3), immediate early response 3 (IER3)) and migratory factors (chemokine receptor 4 (CXCR4), stromal cell-derived factor 1 (SDF-1)) was determined (quantitative real-time (RT)., Western blot analysis) in comparison to controls. Apoptotic cell death was analyzed by terminal desoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL) and cleaved caspase 3 (CC3) staining.Under normoxic conditions, FG-4497 treatment significantly induced the accumulation of both HIF-1? and HIF-2? isoforms in developing mouse brain. In addition, there was a significant up-regulation of HIF target genes (VEGF, ADM, EPO, CXCR4, p<0.01) with FG-4497 treatment compared to controls supporting functional activation of the HIF proteins. Under hypoxia, differential target gene activation was observed in the developing brain including additive effects of FG-4497 and hypoxia on mRNA expression of VEGF and ADM as well as a dose-dependent down-regulation of iNOS. BNIP3 but not IER3 mRNA levels significantly increased in hypoxic brains pre-treated with high-dose FG-4497 compared to controls. Of special interest, FG-4497 treatment significantly diminished apoptotic cell death, quantified by TUNEL and CC3-positive cells, in hypoxic developing brains compared to controls.PHI treatment modulates neurotrophic factors known to be crucially involved in hypoxia-induced cerebral adaptive mechanisms as well as early brain maturation. Pre-treatment with FG-4497 seems to protect the developing brain from hypoxia-induced apoptosis. Present observations provide basic information for further evaluation of neuroprotective properties of PHI treatment in hypoxic injury of the developing brain. However, potential effects on maturational processes need special attention in experimental research targeting HIF-dependent neuroprotective interventions during the very early stage of brain development.
EVALuna2:18900

Plasma gelsolin promotes re-epithelialization - Wittmann, Johannes; Dieckow, J.; Schröder, Henrik; Hampel, Ulrike; Garreis, Fabian; Jacobi, Christina; Milczarek, Aleksandra; Hsieh, K. L.; Pulli, Benjamin; Chen, J. W.; Hoogeboom, S.; Bräuer, Lars; et al. (Scientific Reports, 2018)
Woundhealing disorders characterized by impaired or delayed re-epithelialization are a serious medical problem that is painful and difficult to treat. Gelsolin (GSN), a known actin modulator, supports epithelial cell regeneration and apoptosis. The aim of this study was to estimate the potential of recombinant gelsolin (rhu-pGSN) for ocular surface regeneration to establish a novel therapy for delayed or complicated wound healing. We analyzed the influence of gelsolin on cell proliferation and wound healing in vitro, in vivo/ex vivo and by gene knockdown. Gelsolin is expressed in all tested tissues of the ocular system as shown by molecular analysis. The concentration of GSN is significantly increased in tear fluid samples of patients with dry eye disease. rhu-pGSN induces cell proliferation and faster wound healing in vitro as well as in vivo/ex vivo. TGF-β dependent transcription of SMA is significantly decreased after GSN gene knockdown. Gelsolin is an inherent protein of the ocular system and is secreted into the tear fluid. Our results show a positive effect on corneal cell proliferation and wound healing. Furthermore, GSN regulates the synthesis of SMA in myofibroblasts, which establishes GSN as a key protein of TGF-β dependent cell differentiation.
EVALuna2:35306

Podocytes Produce and Secrete Functional Complement C3 and Complement Factor H - Mühlig, Anne K.; Keir, Lindsay S.; Abt, Jana C.; Heidelbach, Hannah S.; Horton, Rachel; Welsh, Gavin I.; Meyer-Schwesinger, Catherine; Licht, Christoph; Coward, Richard J.; Fester, Lars; Saleem, Moin A.; Oh, Jun (Frontiers in Immunology, 2020)
Podocytes are an important part of the glomerular filtration barrier and the key player in the development of proteinuria, which is an early feature of complement mediated renal diseases. Complement factors are mainly liver-born and present in circulation. Nevertheless, there is a growing body of evidence for additional sites of complement protein synthesis, including various cell types in the kidney. We hypothesized that podocytes are able to produce complement components and contribute to the local balance of complement activation and regulation. To investigate the relevant balance between inhibiting and activating sides, our studies focused on complement factor H (CFH), an important complement regulator, and on C3, the early key component for complement activation. We characterized human cultured podocytes for the expression and secretion of activating and regulating complement factors, and analyzed the secretion pathway and functional activity. We studied glomerular CFH and C3 expression in puromycin aminonucleoside (PAN) -treated rats, a model for proteinuria, and the physiological mRNA-expression of both factors in murine kidneys. We found, that C3 and CFH were expressed in cultured podocytes and expression levels differed from those in cultivated glomerular endothelial cells. The process of secretion in podocytes was stimulated with interferon gamma and located in the Golgi apparatus. Cultured podocytes could initiate the complement cascade by the splitting of C3, which can be shown by the generation of C3a, a functional C3 split product. C3 contributed to external complement activation. Podocyte-secreted CFH, in conjunction with factor I, was able to split C3b. Podocytes derived from a patient with a CFH mutation displayed impaired cell surface complement regulation. CFH and C3 were synthesized in podocytes of healthy C57Bl/6-mice and were upregulated in podocytes of PAN treated rats. These data show that podocytes produce functionally active complement components, and could therefore influence the local glomerular complement activation and regulation. This modulating effect should therefore be considered in all diseases where glomerular complement activation occurs. Furthermore, our data indicate a potential novel role of podocytes in the innate immune system.
CRIS-Team Scopus Importer:2020-09-11
Keywords: complement secretion; glomerulus; kidney; local regulation; proteinuria

Polytetrafluoroethylene (PTFE) as a Suture Material in Tendon Surgery - Polykandriotis, Elias; Himmler, Marcus; Mansouri, Shirin; Ruppe, Florian; Grüner, Jasmin; Bräuer, Lars; Schubert, Dirk W.; Horch, Raymund E. (Journal of Visualized Experiments, 2022)
With the evolution of suture materials, there has been a change in paradigms in primary and secondary tendon repair. Improved mechanical properties allow more aggressive rehabilitation and earlier recovery. However, for the repair to hold against higher mechanical demands, more advanced suturing and knotting techniques must be assessed in combination with those materials. In this protocol, the use of polytetrafluoroethylene (PTFE) as a suture material in combination with different repair techniques was investigated. In the first part of the protocol, both linear tension strength and elongation of knotted against not-knotted strands of three different materials used in flexor tendon repair were evaluated. The three different materials are polypropylene (PPL), ultra-high molecular weight polyethylene with a braided jacket of polyester (UHMWPE), and polytetrafluoroethylene (PTFE). In the next part (ex vivo experiments with cadaveric flexor tendons), the behavior of PTFE using different suture techniques was assessed and compared with PPL and UHMWPE. This experiment is comprised of four steps: harvesting of the flexor tendons from fresh cadaveric hands, transection of the tendons in a standardized manner, tendon repair by four different techniques, mounting, and measurement of the tendon repairs on a standard linear dynamometer. The UHMWPE and PTFE showed comparable mechanical properties and were significantly superior to PPL in terms of linear traction strength. Repairs with four- and six-strand techniques proved stronger than two-strand techniques. Handling and knotting of PTFE are a challenge due to very low surface friction but fastening of the four- or six-strand repair is comparatively easy to achieve. Surgeons routinely use PTFE suture material in cardiovascular surgery and breast surgery. The PTFE strands are suitable for use in tendon surgery, providing a robust tendon repair so that early active motion regimens for rehabilitation can be applied.
CRIS-Team Scopus Importer:2022-11-18

Polytetrafluoroethylene (PTFE) suture vs fiberwire and polypropylene in flexor tendon repair - Polykandriotis, Elias; Ruppe, Florian; Niederkorn, Miriam; Polykandriotis, Ektor; Bräuer, Lars; Horch, Raymund E.; Arkudas, Andreas; Grüner, Johanna (Archives of Orthopaedic and Trauma Surgery, 2021)
Background In this study, we evaluate the value of novel suture material based on monofilamentous-extruded polyfluoroethylene (PTFE) compared to polypropylene (PPL) and Fiberwire (FW). Materials and methods 60 flexor tendons were harvested from fresh cadaveric upper extremities. 4-0 sutures strands were used in the PPL, FW and PTFE group. Knotting properties and mechanical characteristics of the suture materials were evaluated. A 4-strand locked cruciate (Adelaide) or a 6-strand (M-Tang) suture technique was applied as core sutures for a tendon repair. Two-way ANOVA tests were performed with the Bonferroni correction. Results Stable knotting was achieved with 5 throws with the PPL material, 7 throws for FW and 9 throws for PTFE. In the PPL group, linear tensile strength was 45.92 +/- 12.53 N, in the FW group 80.11 +/- 18.34 N and in the PTFE group 76.16 +/- 29.10 N. FW and PTFE are significantly stronger than PPL but show no significant difference among each other. Similar results were obtained in the subgroup comparisons for different repair techniques. The Adelaide and the M-Tang knotting technique showed no significant difference. Conclusion Fiberwire showed superior handling and knotting properties in comparison to PTFE. However, PTFE allows easier approximation of the stumps. In both, M-Tang and Adelaide repairs, PTFE was equal to FW in terms of repair strength. Both PTFE and FW provide for a robust tendon repair so that early active motion regimens for rehabilitation can be applied.
CRIS-Team WoS Importer:2021-05-07

Population-based study of the durability of humoral immunity after SARS-CoV-2 infection - Peterhoff, David; Wiegrebe, Simon; Einhauser, Sebastian; Patt, Arisha J.; Beileke, Stephanie; Günther, Felix; Steininger, Philipp; Niller, Hans H.; Burkhardt, Ralph; Küchenhoff, Helmut; Gefeller, Olaf; Überla, Klaus; et al. (Frontiers in Immunology, 2023)
SARS-CoV-2 antibody quantity and quality are key markers of humoral immunity. However, there is substantial uncertainty about their durability. We investigated levels and temporal change of SARS-CoV-2 antibody quantity and quality. We analyzed sera (8 binding, 4 avidity assays for spike-(S-)protein and nucleocapsid-(N-)protein; neutralization) from 211 seropositive unvaccinated participants, from the population-based longitudinal TiKoCo study, at three time points within one year after infection with the ancestral SARS-CoV-2 virus. We found a significant decline of neutralization titers and binding antibody levels in most assays (linear mixed regression model, p<0.01). S-specific serum avidity increased markedly over time, in contrast to N-specific. Binding antibody levels were higher in older versus younger participants – a difference that disappeared for the asymptomatic-infected. We found stronger antibody decline in men versus women and lower binding and avidity levels in current versus never-smokers. Our comprehensive longitudinal analyses across 13 antibody assays suggest decreased neutralization-based protection and prolonged affinity maturation within one year after infection.
CRIS-Team Scopus Importer:2023-11-03
Keywords: antibody; avidity; COVID-19; durability; longitudinal; neutralization; population-based; SARS-CoV-2

Poro-Viscoelastic Effects During Biomechanical Testing of Human Brain Tissue - Greiner, Alexander; Reiter, Nina; Paulsen, Friedrich; Holzapfel, Gerhard A.; Steinmann, Paul; Comellas Sanfeliu, Ester; Budday, Silvia (Frontiers in Mechanical Engineering, 2021)
Brain tissue is one of the softest tissues in the human body and the quantification of its mechanical properties has challenged scientists over the past decades. Associated experimental results in the literature have been contradictory as characterizing the mechanical response of brain tissue not only requires well-designed experimental setups that can record the ultrasoft response, but also appropriate approaches to analyze the corresponding data. Due to the extreme complexity of brain tissue behavior, nonlinear continuum mechanics has proven an expedient tool to analyze testing data and predict the mechanical response using a combination of hyper-, visco-, or poro-elastic models. Such models can not only allow for personalized predictions through finite element simulations, but also help to comprehensively understand the physical mechanisms underlying the tissue response. Here, we use a nonlinear poro-viscoelastic computational model to evaluate the effect of different intrinsic material properties (permeability, shear moduli, nonlinearity, viscosity) on the tissue response during different quasi-static biomechanical measurements, i.e., large-strain compression and tension as well as indentation experiments. We show that not only the permeability but also the properties of the viscoelastic solid largely control the fluid flow within and out of the sample. This reveals the close coupling between viscous and porous effects in brain tissue behavior. Strikingly, our simulations can explain why indentation experiments yield that white matter tissue in the human brain is stiffer than gray matter, while large-strain compression experiments show the opposite trend. These observations can be attributed to different experimental loading and boundary conditions as well as assumptions made during data analysis. The present study provides an important step to better understand experimental data previously published in the literature and can help to improve experimental setups and data analysis for biomechanical testing of brain tissue in the future.
Keywords: human brain; viscoelasticity; poroelasticity; constitutive modeling; mechanical properties; biomechanical testing; indentation; finite element analysis

Potential compression of the musculocutaneous, median and ulnar nerves by a very rare variant of the coracobrachialis longus muscle - Olewnik, L.; Paulsen, Friedrich; Tubbs, R. Shane; Zielinska, N.; Szewczyk, B.; Karauda, Piotr; Polguj, Michal (Folia Morphologica, 2021)
The coracobrachialis longus muscle (CBL) is an extremely rare variant of the coracobrachialis muscle (CRM). The CBL originates from the apex of the coracoid process together with the short head of the biceps brachii and inserts on the olecranon of the ulna. The CBL consists of three parts: A superior part (classical CRM - length 137.88 mm), a middle fibrous layer (23.41 mm), and an inferior part (185.37 mm). A rare relationship between the CBL and median, musculocutaneous and ulnar nerves was observed with potential compression at these three parts. In addition, this case report describes a connection between CBL and the medial head of the triceps brachii, as well as a third head of the biceps brachii, which originate from the fibrous layer. This case report highlights the relationships between the CBL and the median, ulnar and musculocutaneous nerves.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Anatomical variations; Coracobrachialis longus muscle; Median nerve; Musculocutaneous nerve; Ulnar nerve

Practical postgraduate teaching in Human Anatomy: A review - Sañudo, José R.; Vázquez, Teresa; Talarico, Ernest F.; Duparc, Fabrice; Paulsen, Friedrich; Macchi, Veronica; Feigl, George; Elizondo-Omaña, Rodrigo; De Caro, Raffaele; Aragonés, P.; McHanwell, Stephen; Moriggl, Bernhard; et al. (European Journal of Anatomy, 2021)
Anatomy is a fundamental subject for both medical and surgical training. Anatomy departments might collaborate with clinicians organizing continuing medical education (CME) and other professional development courses. The courses should have a large practical component (in content and organization) but also should provide the latest scientifically based theoretical knowledge, respecting the learning of anatomy as well as aiming at performing different techniques. Anatomy departments should support these courses by establishing hands-on practical training courses and components.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Applied anatomy; Clinical anatomy; Continuing medical education; Education; Surgical anatomy; Teaching

Predictors for Recurrence of Chronic Subdural Hematoma - Hammer, Alexander; Tregubow, Alexander; Kerry, Ghassan; Schrey, Michael; Hammer, Christian; Steiner, Hans-Herbert (Turkish Neurosurgery, 2017)
AIM: This prospective study was designed to analyze the dependence of different factors on the recurrence rate of chronic subdural hematoma (cSDH) after surgical treatment. MATERIAL AND METHODS: Seventy-three consecutive patients, who were surgically treated at our department due to cSDH between 2009 and 2012, were included. The following parameters were analyzed: patient age and gender, occurrence of trauma, time between trauma and admission, neurological symptoms, presence of minor diseases, intake of anticoagulation medication. We classified the results of diagnostic imaging and determined the space-consuming effect via the cerebral midline shift. In addition, we scrutinized intraoperative findings and the dependence of the position of subdural drainage on the recurrence rate of cSDH. RESULTS: In our patient group, cSDH recurrence was significantly associated with aphasia (p=0.008). Moreover an increased cSDH recurrence rate was observed in the patient group that had a separated manifestation of the cSDH in the preoperative diagnostic imaging (p=0.048) and received no drainage implant (p=0.016). Homogeneous isodense cSDH was associated with no apparent recurrence (p=0.037). CONCLUSION: Within the scope of this study, we detected aphasia and separated cSDH as predictors of cSDH recurrence. Homogeneous isodense cSDH seems to be a good prognostic sign regarding the risk of recurrence development. Furthermore, our data clearly emphasize the importance of surgically applied drainage implants to prevent a recurrence of cSDH.
EVALuna2:35329

Preponderance of inhibitory versus excitatory intramuscular nerve fibres in human chagasic megacolon - Jabari, Samir; Da Silveira, Alexandre B.M.; De Oliveira, Enio; Quint, Karl; Neuhuber, Winfried; Brehmer, Axel (International Journal of Colorectal Disease, 2012)
Introduction: Megacolon, chronic dilation of a colonic segment, is a frequent sign of Chagas disease. It is accompanied by an extensive neuron loss which, as shown recently, results in a partial, selective survival of nitrergic myenteric neurons. Here, we focused on the balance of intramuscular excitatory (choline acetyltransferase [ChAT]-immunoreactive) and inhibitory (neuronal nitric oxide synthase [NOS]- as well as vasoactive intestinal peptide [VIP]-immunoreactive) nerve fibres. Materials and methods: From surgically removed megacolonic segments of seven patients, three sets of cryosections (from non-dilated oral, megacolonic and non-dilated anal parts) were immunhistochemically triple-stained for ChAT, NOS and VIP. Separate area measurements of nerve profiles within the circular and longitudinal muscle layers, respectively, were compared with those of seven non-chagasic control patients. Additionally, wholemounts from the same regions were stained for NOS, VIP and neurofilaments (NF). Results: The intramuscular nerve fibre density was significantly reduced in all three chagasic segments. The proportions of inhibitory (NOS only, VIP only, or NOS/VIPcoimmunoreactive) intramuscular nerves were 68 %/58 % (circular/longitudinal muscle, respectively) in the controls and increased to 75 %/69 % (oral parts), 84 %/76 % (megacolonic) and 87 %/94 % (anal) in chagasic specimens. In the myenteric plexus, NF-positive neurons co-staining for NOS and VIP also increased proportionally. The almost complete lack of dendritic structures in ganglia of chagasic specimens hampered morphological identification. Discussion and conclusion: We suggest that preponderance of inhibitory, intramuscular nerve fibres may be one factor explaining the chronic dilation. Since the nerve fibre imbalance is most pronounced in the anal, non-dilated segment, other components of the motor apparatus (musculature, interstitial cells, submucosal neurons) have to be considered. © Springer-Verlag 2012.
Keywords: Chagasic megacolon; Enteric nervous system; Neurodegeneration; Neuronal nitric oxide synthase; Vasoactive intestinal peptide

Prevalence and characteristics of test anxiety in first year anatomy students - Bischofsberger, Larissa; Burger, Pascal H.M.; Hammer, Alexander; Paulsen, Friedrich; Scholz, Michael; Hammer, Christian (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Background: Test anxiety is a common phenomenon at universities with the potential to impair academic performance and student well-being. This study was conducted to investigate prevalence, characteristics, and development of the test anxiety categories “emotionality”, “worry”, “interference”, and “lack of confidence” among first year medical students. Methods: Overall, 625 freshman medical students were enrolled. They were recruited from the participants of a first semester anatomy course. The participants were assessed four times with a validated psychological test anxiety questionnaire (Prüfungsangstfragebogen, PAF). The first assessment was conducted at the commencement of the first semester. All further assessments were performed two days prior to each of three mandatory oral anatomy tests in the course of one half year. Prevalence rates as well as mean global and subscale scores of the test anxiety dimensions “emotionality”, “worry”, “interference” and “lack of confidence” were determined and compared between assessments. Results: Approximately 50% of the study participants showed pronounced test anxiety in at least one dimension over the observation period. Only about 10% were considered test anxiety-positive according to the global PAF scale. Worry showed the highest (up to 48%) and interference the lowest (≈5%) prevalence rates. Emotionality had a stable prevalence of approximately 17%, whereas lack of confidence showed a rising trend over the observation period from 15.2% up to 24.0%. Conclusion: Test anxiety is substantially more prevalent among medical students as commonly reported and deserves more detailed, dimension-specific exploration in future. Especially worry and lack of confidence give reason for concern, demanding further investigation.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Examination anxiety; Medical education; Stress relaxation; Test anxiety

Preventive effects of omega-3 and omega-6 Fatty acids on peroxide mediated oxidative stress responses in primary human trabecular meshwork cells - Tourtas, Theofilos; Birke, Marco; Kruse, Friedrich; Welge-Lüssen, Ulrich-Christoph; Birke, Kerstin (PLoS ONE, 2012)
Pathologic processes in glaucoma include increased apoptosis, accumulation of extracellular material in the trabecular meshwork and optic nerve, condensations of the cytoskeleton and precocious cellular senescence. Oxidative stress was shown to generate these alterations in primary ocular cells. Fatty acids omega-3 and -6 are alleged to constitute a prophylaxis against these deleterious effects. Here, we tested actual preventive effects omega-3 and -6 against peroxide induced stress responses in primary human trabecular meshwork cells. Changes of mitochondrial activity, proliferation, heat shock proteins, extracellular matrix components, and inflammatory markers were evaluated. Alterations of the cytoskeleton were evaluated by phalloidin labeling. Here we report a repressive effect of omega-6 on metabolic activity and proliferation, which was not detected for omega-3. Both agents were able to prevent the anti-proliferative effect of H?O?, but only omega-3 prevented metabolic repression. Expression of heat shock protein 27 was unaltered by both fatty acids, whereas heat shock protein 90 was significantly induced by both. Omega-6 increased fibronectin and connective tissue growth factor synthesis, as well as the amount of secreted fibronectin. Omega-3, instead, induced plasminogen activator inhibitor 1 synthesis. H?O? further increased fibronectin production in omega-6 supplemented cells, which was not the case in omega-3 treated cells. H?O? stimulation of plasminogen activator inhibitor 1 and connective tissue growth factor was repressed by both fatty acids. Both fatty acids appeared to abolish H?O? mediated stimulation of nuclear factor ?B and IL-6, but not IL-1? and IL-8. H?O? induced formation of cross-linked actin networks and stress fibers, which was reduced by preemptive application of omega-3. Omega-6, in contrast, had no protective effect on that, and even seemed to promote condensation. Based on the observed side effects of omega-6, omega-3 appears to be the more beneficial fatty acid in respect of prophylactic intake for prevention of a glaucomatous disease.
EVALuna2:21079

Production and Secretion of Gelsolin by Both Human Macrophage- and Fibroblast-like Synoviocytes and GSN Modulation in the Synovial Fluid of Patients with Various Forms of Arthritis - Feldt, Jessica; Schicht, Martin; Welss, Jessica; Gelse, Kolja; Sesselmann, Stefan; Tsokos, Michael; Socher, Eileen; Garreis, Fabian; Mueller, Thomas; Paulsen, Friedrich (Biomedicines, 2022)
Gelsolin (GSN) is an actin-binding protein involved in cell formation, metabolism and wound closure processes. Since this protein is known to play a role in arthritis, here we investigate how the synovial membrane with its specific synoviocytes contributes to the expression of GSN and how the amount of GSN expressed is modulated by different types of arthritis. Synovial membranes from adult healthy subjects and patients with rheumatoid arthritis (RA) and osteoarthritis (OA) are analyzed by immunofluorescence, Western blot and ELISA. Macrophage-like synoviocytes (MLS) and fibroblast-like synoviocytes (FLS) were isolated, cultured and analyzed for their potential to produce and secrete GSN. In addition, the GSN concentrations in the synovial fluid of various forms of arthritis are determined by ELISA. GSN is produced by the healthy and arthritic synovial membranes. Both forms of synoviocytes (MLS and FLS) release GSN. The results show that there is a significant reduction in GSN in the synovial fluid in adult patients with OA. This reduction is also detectable in adult patients with RA but is not as evident. In juvenile arthritis, there is a slight increase in GSN concentration in the synovial fluid. This study shows that primary MLS and FLS express GSN and that these cells, in addition to articular chondrocytes, contribute to GSN levels in synovial fluid. Furthermore, GSN concentrations are modulated in different types of arthritis. Further studies are needed to fully understand how GSN is involved in joint homeostasis.<br
Keywords: arthritis; gelsolin; synovial fluid; synoviocytes

Prolactin and Prolactin-inducible protein (PIP) in the pathogenesis of primary acquired nasolacrimal duct obstruction (PANDO) - Mohammad, Javed Ali; Paulsen, Friedrich (Medical Hypotheses, 2019)
Primary acquired nasolacrimal duct obstruction (PANDO) is a syndrome of unknown etiology, predominantly affecting post-menopausal females, characterized by progressive inflammation, fibrosis and subsequent obstruction of the nasolacrimal duct. Numerous factors have been proposed as possible etiologic factors and include anatomical configuration, ocular and nasal infections, peri-lacrimal vascular disorders, hormonal influence, lacrimal drainage lymphoid tissue, gastroesophageal reflux disease, topical medications, swimming pool exposure, smoking, genetic factors, autonomic and lysosomal dysregulation. The authors hypothesize Prolactin (PRL) and Prolactin-inducible protein (PIP) play a role in the etiopathogenesis of primary acquired nasolacrimal duct obstruction.
CRIS-Team WoS Importer:2019-04-18

Prolactin Inducible Protein, but Not Prolactin, Is Present in Human Tears, Is Involved in Tear Film Quality, and Influences Evaporative Dry Eye Disease - Jüngert, Katharina; Paulsen, Friedrich; Jacobi, Christina; Horwath-Winter, Jutta; Garreis, Fabian (Frontiers in Medicine, 2022)
PurposeDecreased production of the aqueous component of the tear film is an important cause of the development of dry eye disease (DED). Tear production is influenced by hormones and hormone-like factors. Prolactin (PLR), a multifunctional pituitary gland hormone, is regularly present in the lacrimal gland of rats and rabbits. In humans, serum PLR concentration correlates with tear quality. To gain deeper insights of possible effects of PRL, prolactin receptor (PRLR) and prolactin inducible protein (PIP), we analyzed the three proteins in the human lacrimal apparatus and in reflex tears of healthy volunteers as well as patients suffering from DED. MethodsGene expression of PRLR and PIP was analyzed by RT-PCR in cadaveric human lacrimal gland and ocular surface tissues, immortalized human corneal epithelial cells (HCE and hTEPI) and human Meibomian gland epithelial cells (HMGECs). At the protein level, the expression and localization of PRL, PRLR and PIP in formalin-fixed paraffin sections of the lacrimal apparatus were studied by immunohistochemistry. In addition, tear fluid from DED patients and healthy volunteers was analyzed by ELISA to determine the concentration of PRL and PIP. ResultsRT-PCR analyses revealed gene expression of PRLR and PIP in human tissue samples of cornea, lacrimal glands, and eyelids, whereas only PIP, but not PRLR, was detectable in immortalized corneal epithelial cells. Immunohistochemistry revealed for the first time the expression and localization of PRL, PRLR, and PIP in human tissues of the lacrimal apparatus and at the ocular surface. PRL and PRLR were detectable in corneal epithelium, lacrimal glands, and Meibomian glands. Reflex tears from DED patients revealed significantly increased PIP concentrations, whereas PRL was undetectable in tears of DED patients and healthy volunteers. ConclusionPRL, PRLR, and PIP are found in the lacrimal apparatus and on the ocular surface. PIP, but not PRL, is present in human tears and appears to be involved in the physiology of tear film quality. Our clinical data revealed that PIP may affect tear quality, but further functional analyses are needed to fully elucidate the effects of PRL and PIP-associated factors in tear secretion as well as in the connection of DED.
CRIS-Team WoS Importer:2022-07-29

Protein kinase CK2 interacts at the neuromuscular synapse with Rapsyn, Rac1, 14-3-3?, and Dok-7 proteins and phosphorylates the latter two - Herrmann, Dustin; Straubinger, Marion; Hashemolhosseini, Said (Journal of Biological Chemistry, 2015)
Previously, we demonstrated that the protein kinase CK2 associates with and phosphorylates the receptor tyrosine kinase MuSK (muscle specific receptor tyrosine kinase) at the neuromuscular junction (NMJ), thereby preventing fragmentation of the NMJs (Cheusova, T., Khan, M. A., Schubert, S. W., Gavin, A. C., Buchou, T., Jacob, G., Sticht, H., Allende, J., Boldyreff, B., Brenner, H. R., and Hashemolhosseini, S. (2006) Genes Dev. 20, 1800-1816). Here, we asked whether CK2 interacts with other proteins involved in processes at the NMJ, which would be consistent with the previous observation that CK2 appears enriched at the NMJ. We identified the following proteins to interact with protein kinase CK2: (a) the ? and ? subunits of the nicotinic acetylcholine receptors with weak interaction, (b) dishevelled (Dsh), and (c) another four proteins, Rapsyn, Rac1, 14-3-3?, and Dok-7, with strong interaction. CK2 phosphorylated 14-3-3? at serine residue 235 and Dok-7 at several serine residues but does not phosphorylate Rapsyn or Rac1. Furthermore, phosphomimetic Dok-7 mutants aggregated nicotinic acetylcholine receptors in C2C12 myotubes with significantly higher frequency than wild type Dok-7. Additionally, we mapped the interacting epitopes of all four binding partners to CK2 and thereby gained insights into the potential role of the CK2/Rapsyn interaction.
EVALuna2:4975

Protein modeling and molecular dynamics simulation of the two novel surfactant proteins SP-G and SP-H - Rausch, Felix; Schicht, Martin; Bräuer, Lars; Paulsen, Friedrich; Brandt, Wolfgang (Journal of Molecular Modeling, 2014)
Surfactant proteins are well known from the human lung where they are responsible for the stability and flexibility of the pulmonary surfactant system. They are able to influence the surface tension of the gas-liquid interface specifically by directly interacting with single lipids. This work describes the generation of reliable protein structure models to support the experimental characterization of two novel putative surfactant proteins called SP-G and SP-H. The obtained protein models were complemented by predicted posttranslational modifications and placed in a lipid model system mimicking the pulmonary surface. Molecular dynamics simulations of these protein-lipid systems showed the stability of the protein models and the formation of interactions between protein surface and lipid head groups on an atomic scale. Thereby, interaction interface and strength seem to be dependent on orientation and posttranslational modification of the protein. The here presented modeling was fundamental for experimental localization studies and the simulations showed that SP-G and SP-H are theoretically able to interact with lipid systems and thus are members of the surfactant protein family.
EVALuna2:4436

Proteolysis of CD44 at the cell surface controls a downstream protease network - Woehner, Birte; Li, Wenjia; Hey, Sven; Drobny, Alice; Werny, Ludwig; Becker-Pauly, Christoph; Lucius, Ralph; Zunke, Friederike; Linder, Stefan; Arnold, Philipp (Frontiers in Molecular Biosciences, 2023)
The cell surface receptor cluster of differentiation 44 (CD44) is the main hyaluronan receptor of the human body. At the cell surface, it can be proteolytically processed by different proteases and was shown to interact with different matrix metalloproteinases. Upon proteolytic processing of CD44 and generation of a C-terminal fragment (CTF), an intracellular domain (ICD) is released after intramembranous cleavage by the γ-secretase complex. This intracellular domain then translocates to the nucleus and induces transcriptional activation of target genes. In the past CD44 was identified as a risk gene for different tumor entities and a switch in CD44 isoform expression towards isoform CD44s associates with epithelial to mesenchymal transition (EMT) and cancer cell invasion. Here, we introduce meprin β as a new sheddase of CD44 and use a CRISPR/Cas9 approach to deplete CD44 and its sheddases ADAM10 and MMP14 in HeLa cells. We here identify a regulatory loop at the transcriptional level between ADAM10, CD44, MMP14 and MMP2. We show that this interplay is not only present in our cell model, but also across different human tissues as deduced from GTEx (Gene Tissue Expression) data. Furthermore, we identify a close relation between CD44 and MMP14 that is also reflected in functional assays for cell proliferation, spheroid formation, migration and adhesion.
CRIS-Team Scopus Importer:2023-03-24
Keywords: ADAM10; CD44; cell adhesion; meprin β; MMP14; MMP2; shedding; tumor spheroid

Pt-Fe3O4, Pd-Fe3O4, and Au-Fe3O4Nanoheterodimers and Their Efficacy as Radiosensitizers in Cancer Therapy - Klein, Stefanie; Otto, Julia; Harreiß, Christina; Distel, Luitpold; Leistner, Angelika; Neuhuber, Winfried; Spiecker, Erdmann; Kryschi, Carola (ACS Applied Bio Materials, 2021)
The X-radiation enhancing effect of caffeic acid-functionalized Au-Fe3O4, Pt-Fe3O4, and Pd-Fe3O4 nanoheterodimers (NHDs) on 2D and 3D breast tumor (MCF-7) and healthy breast epithelial (MCF-10A) cells was comprehensively examined by performing cell viability, reactive oxygen species (ROS) detection, enzyme activity, and clonogenic assays. Intracellular NHDs were observed to cause DNA fragmentation and to enhance superoxide and hydroxyl radical formation in MCF-7 cells when exposed to a single dose of 1 Gy. MCF-7-derived multicellular tumor spheroids (MCF-7 MCTS) and MCF-10A-derived multicellular spheroids (MCF-10A MCS) were incubated with the NHDs and irradiated with five daily doses of 2 Gy. The Au-Fe3O4 and Pt-Fe3O4 NHD-loaded MCF-7 MCTS significantly decreased in volume after being exposed to fractionated irradiation, whereas intracellular Au-Fe3O4 and Pt-Fe3O4 NHDs promoted the growth of the irradiated MCF-10A MCS. Moreover, Au-Fe3O4 and Pt-Fe3O4 NHDs were shown to impede ROS formation and inhibit DNA strand breakage in the noncancerous MCF-10A cells. On the other hand, the Pd-Fe3O4 NHDs boosted X-radiation-induced damage of MCF-10 A cells, which was ascribed to impairment of the ROS scavenging enzyme activities. In summary, caffeic acid-functionalized Au-Fe3O4 and Pt-Fe3O4 NHDs performed as excellent X-radiation enhancing agents in breast tumor cells, while they protect healthy breast epithelial cells against X-radiation.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Au-Fe; caffeic acid; MCF-10A; MCF-7; multicellular tumor spheroids; Pd-Fe; Pt-Fe; radiotherapy

Qualitative Hormonal Profiling of the Lacrimal Drainage System: Potential Insights into the Etiopathogenesis of Primary Acquired Nasolacrimal Duct Obstruction - Ali, Mohammad Javed; Schicht, Martin; Paulsen, Friedrich (Ophthalmic Plastic and Reconstructive Surgery, 2017)
PURPOSE: To investigate the presence and distribution patterns of hormone receptors in the lacrimal drainage system in normal and diseased states. METHODS: The study was performed on cadaveric and clinical samples of the lacrimal drainage system. Immunohistochemical labeling was performed for assessing the presence and distribution of receptors of estrogen alpha, estrogen beta, aromatase (CYP19), testosterone, progesterone, oxytocin, prolactin, and somatostatins 1 to 5 (SSTR1, SSTR2, SSTR3, SSTR4, and SSTR5). The immunohistochemistry stains were scored as positive or negative, and the distribution patterns in the canaliculus, lacrimal sac, and nasolacrimal duct were assessed. RESULTS: There was a strong expression of estrogen alpha, estrogen beta, and oxytocin, but this showed variations in distribution patterns. Testosterone and progesterone expressions were more localized to the basement membrane of the epithelium in postmenopausal females. While SSTR2 and SSTR4 expressed only on the villus surfaces of superficial epithelial cells; oxytocin, aromatase, and prolactin additionally expressed in the subepithelial lamina propria and submucosal glands. Diseased samples from primary acquired nasolacrimal duct obstruction showed dramatic reduction or absence of the receptor expression patterns of all the hormones with the exception of epithelial immunoreactivity with prolactin. CONCLUSIONS: This study provides a proof of principle for the presence of multiple hormone receptors and hypothesizes their possible links in the etiopathogenesis of primary acquired nasolacrimal duct obstructions.
EVALuna2:35328

Quantifiable Contrast-Enhanced Ultrasound Explores the Role of Protection, Rest, Ice (Cryotherapy), Compression and Elevation (PRICE) Therapy on Microvascular Blood Flow - Hotfiel, Thilo; Hoppe, Matthias Wilhelm; Heiß, Rafael; Lutter, Christoph; Tischer, Thomas; Forst, Raimund; Hammer, Christian; Freiwald, Jürgen; Engelhardt, Martin; Grim, Casper (Ultrasound in Medicine and Biology, 2021)
The aim of this randomized controlled laboratory study was to evaluate the role of standardized protection, rest, ice (cryotherapy), compression and elevation (PRICE) therapy on microvascular blood flow in human skeletal muscle. Quantifiable contrast-enhanced ultrasound was used to analyze intramuscular tissue perfusion (ITP) of the rectus femoris (RF) and vastus intermedius (VI) muscles in 20 healthy athletes who were randomly assigned to PRICE or control groups. Baseline perfusion measurements (resting conditions, T0) were compared with cycling exercise (T1), intervention (PRICE or control, T2) and follow-up at 60 min post-intervention (T3). The 20 min PRICE intervention included rest, cryotherapy (3°C), compression (35 mm Hg) and elevation. After intervention, PRICE demonstrated a decrease of ITP in VI (–47%, p = 0.01) and RF (–50%, p = 0.037) muscles. At T3, an ongoing decreased ITP for the RF (p = 0.003) and no significant changes for the VI were observed. In contrast, the control group showed an increased ITP at T2 and no significant differences at T3. PRICE applied after exercise led to a down-regulation of ITP, and the termination of PRICE does not appear to be associated with a reactive hyperemia for at least 60 min after treatment.
CRIS-Team Scopus Importer:2021-02-12
Keywords: CEUS; Compression; Cryotherapy; ICE; Muscle injuries; Muscle metabolism; RICE; Sports injuries; Ultrasound

Quantification of surfactant proteins in tears of patients suffering from dry eye disease compared to healthy subjects - Posa, Andreas; Paulsen, Friedrich; Dietz, Richard; Garreis, Fabian; Sander, Ralph; Schicht, Martin; Sel, Saadettin; Scholz, Michael; Hammer, Christian; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2018)
PURPOSE: To quantify and compare the amounts of surfactant proteins SP-A, SP-B, SP-C and SP-D in the tear fluid collected from patients with dry eye syndrome and from individuals with a healthy ocular surface. METHODS: Schirmer strips were used to collect tear fluid from both eyes of 241 volunteers (99 men, 142 women; age range: 18-87 years). Dry eye syndrome was diagnosed by ophthalmologists in 125 patients, whereas the healthy control group comprised 116 individuals. The total protein concentration was determined via Bradford assay. The relative concentration of surfactant proteins SP-A through -D was measured by enzyme-linked immuno-sorbent assay (ELISA). RESULTS: The mean relative concentrations of SP-A, SP-C and SP-D were significantly higher in the dry eye group as compared to the healthy controls (p<0.05, one-way ANOVA). SP-B was also detected at a higher concentration in the dry eye group, but the difference to the control group was not statistically significant. CONCLUSIONS: The upregulation of SP-A and SP-D in the dry eye group is probably related to these proteins' known antimicrobial and immunomodulatory effects at the ocular surface. It may represent a pathophysiological response to the inflammatory condition of the ocular surface in dry eye. The upregulation of SP-B and SP-C may represent an effort of the lacrimal system to reduce surface tension and thus to counteract the increased tendency of the tear film to tear in dry eye.
EVALuna2:35321

Quantitative estimation and chemical coding of spiny type I neurons in human intestines - Schuy, Julia; Schlabrakowski, Anne; Neuhuber, Winfried; Brehmer, Axel (Cells Tissues Organs, 2011)
Previous studies have shown that most human myenteric neurons co-staining for vasoactive intestinal peptide (VIP), neuronal nitric oxide synthase (nNOS) and neurofilaments (NF) display the morphology of spiny type I neurons displaying a descending projection pattern. Here, we estimated the proportions of spiny neurons in human intestines, the amount of congruence of VIP/nNOS-immunoreactive with spiny neurons and whether galanin (GAL) is co-localized with VIP. Three sets of colchicine-pretreated and fixed whole mounts of 21 patients or body donors (median age 65 years; 10 female, 11 male) were stained for VIP, nNOS and NF, for VIP, nNOS and the human neuronal protein Hu C/D (HU) as well as for VIP, nNOS and GAL. The majority of VIP/nNOS-co-reactive neurons were spiny neurons (79/80% in small/large intestine, respectively) and the majority of spiny neurons co-stained for VIP and nNOS (82/69%). Neurons co-immunoreactive for VIP/nNOS/HU amounted to 7 and 4%, respectively. GAL/VIP-co-immunoreactivity was demonstrated in 69 and 27% of spiny neurons, respectively. We conclude that the number of neurons displaying co-reactivity for VIP and nNOS is a quantitative indicator of spiny neurons in both small and large intestine and that the proportion of spiny neurons is about 7% in small and 4% in large intestines. Since nerve fibres co-staining for NF/VIP/nNOS were found mainly in the circular muscle layer but not the surrounding perikarya of spiny neurons, we suggest that they may represent inhibitory motor neurons rather than descending interneurons. Copyright © 2010 S. Karger AG, Basel.
Keywords: Enteric nervous system; Galanin; Myenteric plexus; Neuronal nitric oxide synthase; Vasoactive intestinal peptide

Quantitative estimation of putative primary afferent neurons in the myenteric plexus of human small intestine - Weidmann, Simone; Schrödl, Falk; Neuhuber, Winfried; Brehmer, Axel (Histochemistry and Cell Biology, 2007)
This study aimed at estimating the proportion of human myenteric Dogiel type II neurons, putative intrinsic primary afferent neurons (IPANs), in relation to the entire myenteric neuron population. Since, at present, there is no known single marker, which specifically labels these neurons, we tried to identify the most appropriate marker combination based on the results of an earlier study. For this purpose, 10 wholemounts derived from human small intestinal segments were immunohistochemically triple-stained for calretinin (CALR), somatostatin (SOM) and neurofilaments (NF) and 9 were stained for substance P (SP), SOM and NF. In each wholemount, 15 ganglia selected randomly were evaluated. On the basis of their NF-reactivity, neurons reactive for one or co-reative for both of the other two markers, respectively, were morphologically classified as type II or non-type II neurons. We found that the majorities of neurons co-reactive for CALR/SOM and SP/SOM, respectively, were type II neurons whereas this was not the case for neurons, which were reactive for only one of the two markers. One of the statistical parameters estimated was the positive predictive value, the probability that a neuron displaying CALR/SOM- or SP/SOM-co-reactivity, respectively, is a type II neuron. This value was 97% in case of CALR/SOM- and 95% in case of SP/SOM-co-staining. Although the difference of the statistical parameters between the two stainings was not significant, CALR and SOM were used to estimate indirectly the proportion of type II neurons, in wholemounts co-stained with the pan-neuronal marker neuronal protein HuC/HuD (HU). In these wholemounts, altogether 9.1% of neurons were coreactive for CALR/SOM. We suggest that the proportion of myenteric type II neurons in the human small intestine is related to the proportion of CALR/SOM-co-reactive neurons and may be near to one tenth of the total myenteric neuronal population. © 2007 Springer-Verlag.
Keywords: Chemical code; Enteric nervous system; Human gut; Intrinsic innervation; IPAN

Quantitative evaluation of neurons in the mucosal plexus of adult human intestines - Kramer, Kerstin; Da Silveira, Alexandre B.M.; Jabari, Samir; Kressel, Michael; Raab, Marion; Brehmer, Axel (Histochemistry and Cell Biology, 2011)
The consequence of presence versus absence of mucosal neurons is not consistently assessed. Here, we addressed two questions. First, based on resected gut specimens of 65 patients/body donors suffering from different diseases, counts of mucosal neurons per mm were analysed with respect to age, gender and region. Second, we evaluated resected megacolonic specimens of four patients suffering from chronic Chagas' disease. Mucosal wholemounts were triple-stained for calretinin (CALR), peripherin (PER) and human neuronal protein Hu C/D (HU). Counts revealed no clear correlation between the presence of mucosal neurons and age, gender or region. Mucosal neurons were present in 30 of 36 specimens derived from males (83%) and in 20 of 29 from females (69%). The numbers per mm increased from duodenum to ileum (1.7-10.8) and from ascending to sigmoid colon (3.2-9.9). Out of 149 small intestinal mucosal neurons, 47% were co-reactive for CALR, PER and HU (large intestine: 76% of 300 neurons) and 48% for PER and HU only (large intestine: 23%). In 12 megacolonic specimens (each 3 from 4 patients), all 23 mucosal neurons found (1.9 per mm) displayed co-reactivity for CALR, PER and HU. We suggest that the presence or the absence of mucosal neurons is variable, ongoing studies will address our assumption that they correspond in their morphochemical characteristics to submucosal neurons. Furthermore, both the architecture and neuron number of the megacolonic mucosal plexus displayed no dramatic changes indicating that mucosal nerves might be less involved in chagasic/megacolonic neurodegeneration as known from the myenteric plexus. © 2011 Springer-Verlag.
Keywords: Calretinin; Chagas disease; Enteric nervous system; Megacolon; Mucosal plexus; Peripherin

Randomized comparison of topical prednisolone acetate 1% versus fluorometholone 0.1% in the first year after descemet membrane endothelial keratoplasty - Price, Marianne O.; Price, Francis W.; Kruse, Friedrich; Bachmann, Björn; Tourtas, Theofilos (Cornea, 2014)
The aim of this study was to compare the efficacy and side effects of prednisolone acetate 1% versus fluorometholone 0.1% after Descemet membrane endothelial keratoplasty (DMEK).DMEK recipients used prednisolone acetate 1% for 1 month, and they were randomized to either prednisolone or fluorometholone for months 2 through 12. Dosing was 4 times daily in months 1 to 3, thrice daily in month 4, twice daily in month 5, and once daily in months 6 to 12. The main outcomes were immunologic rejection episodes and intraocular pressure (IOP) elevation (defined as >=24 mm Hg or >=10 mm Hg increase over the preoperative baseline level), assessed by the Kaplan-Meier survival analysis.The study included 325 eyes (99% were white, 96% had Fuchs dystrophy, and 9% had a previous glaucoma diagnosis). No eyes (0%) assigned to prednisolone versus 2 eyes (1.4%) assigned to fluorometholone experienced a possible (n = 1) or probable (n = 1) rejection episode (P = 0.17). Both rejection episodes resolved successfully with increased topical steroids. In the prednisolone arm, a significantly higher proportion exceeded the defined IOP elevation threshold (22% vs. 6%, P = 0.0005), and glaucoma medications were initiated or increased more often (17% vs. 5%, P = 0.0003). The most frequent reasons for discontinuing the assigned intervention were IOP management (n = 13 eyes assigned to prednisolone) or inflammation management (n = 3 eyes assigned to fluorometholone). One-year endothelial cell loss was comparable in both arms (30% vs. 31%, P = 0.50).DMEK has a remarkably low rejection episode rate (<1% through 1 year), as confirmed in this prospective randomized study. This provides a unique opportunity to reduce postoperative topical corticosteroid strength and thereby reduce the risk of steroid-associated complications.
EVALuna2:21205

Reclassification of the Sacral Autonomic Outflow to Pelvic Organs as the Caudal Outpost of the Sympathetic System Is Misleading - Jaenig, Wilfrid; Neuhuber, Winfried (The Journal of the American Osteopathic Association, 2017)
EVALuna2:35223

Recombinant expression of surfactant protein H (SFTA3) in Escherichia coli - Schröder, Henrik; Sollfrank, L.; Paulsen, Friedrich; Bräuer, Lars; Schicht, Martin (Annals of Anatomy-Anatomischer Anzeiger, 2016)
Surfactant proteins are broadly understood to be an important structural and functional part of the lung surfactant system. These proteins influence the intra-alveolar surface tension and contribute to innate immunity of the lung. Beside the four already known surfactant proteins SP-A, SP-B, SP-C and SP-D, two novel SPs (SP-G/SFTA2 and SP-H/SFTA3) have recently been described. These show no sequential or structural similarity with the already known SPs. However, bioinformatic prediction tools suggest physicochemical properties, which have already been described for other surfactant proteins. Although it is known that SFTA2 and SFTA3 are expressed in different human tissues, their distinct functional properties remain unclear. Here, we describe the establishment of a stable expression system for recombinant SFTA3 protein synthesis in Escherichia coli. This gives rise to future experiments with the overall aim to further examine and characterize this novel protein in more detail.
EVALuna2:34493

Recombinant human gelsolin promotes the migration of human articular cartilage chondrocytes by regulating gene expression in vitro. - Feldt, Jessica; Welss, Jessica; Schropp, Verena; Gelse, Kolja; Tsokos, Michael; Paulsen, Friedrich (Osteoarthritis and Cartilage Open, 2020)
OBJECTIVE: It is known that recombinant human gelsolin (rhuGSN) supports wound closure and migration processes in avascular tissue. Since articular cartilage degradation plays an important role in osteoarthritis (OA), we are investigating how rhuGSN affects regeneration processes in human articular cartilage and represents a promising new therapeutic approach for the treatment of OA. METHODS: Primary human chondrocytes (phCs) from articular knee cartilage were cultured with different concentrations of rhuGSN to analyse its direct effect in vitro. In addition, phCs were stimulated with 10 ng/mL IL-1β or TNF-α to simulate osteoarthritis in vitro and treated with different concentrations of rhuGSN to investigate the beneficial effect in disease treatment. Cytokine secretion and gene expression as well as wound assays were performed. RESULTS: GSN significantly promotes wound closure in phCs after 60 h compared to untreated cells. After 24 h treatment with 30 μg/mL rhuGSN, TGF-β secretion increases significantly in the in vitro osteoarthritis model. Gene expression of MMP1 as well as SPARC is reduced in chondrocytes due to treatment with GSN in the OA model. At the same time, CXCR4 expression increases significantly after 24 h treatment with 3 μg/mL GSN. CONCLUSION: In the in vitro model of osteoarthritis, rhuGSN promotes wound closure of chondrocytes by a supported migration as well as expression of reconstructive and down regulated expression of deconstructive genes concentration dependently. Further experiments are needed to fully understand the beneficial effect of gelsolin on human chondrocytes and to verify this promising approach for a pharmacological treatment of osteoarthritis.
EVALuna2:515804

Recombinant pro-CTSD (cathepsin D) enhances SNCA/α-Synuclein degradation in α-Synucleinopathy models. - Huarcaya, Alice Prieto; Drobny, Susy; Marques, Andre R. A.; Di Spiezio, Alessandro; Dobert, Jan; Balta, Denise; Werner, Christian; Rizo Garza, Tania; Gallwitz, Lisa; Bub, Simon; Stojkovska, Iva; Belur, Nandkishore R.; et al. (Autophagy, 2022)
Parkinson disease (PD) is a neurodegenerative disorder characterized by the abnormal intracellular accumulation of SNCA/α-synuclein. While the exact mechanisms underlying SNCA pathology are not fully understood, increasing evidence suggests the involvement of autophagy as well as lysosomal deficiencies. Because CTSD (cathepsin D) has been proposed to be the major lysosomal protease involved in SNCA degradation, its deficiency has been linked to the presence of insoluble SNCA conformers in the brain of mice and humans as well as to the transcellular transmission of SNCA aggregates. We here postulate that SNCA degradation can be enhanced by the application of the recombinant human proform of CTSD (rHsCTSD). Our results reveal that rHsCTSD is efficiently endocytosed by neuronal cells, correctly targeted to lysosomes and matured to an enzymatically active protease. In dopaminergic neurons derived from induced pluripotent stem cells (iPSC) of PD patients harboring the A53T mutation within the SNCA gene, we confirm the reduction of insoluble SNCA after treatment with rHsCTSD. Moreover, we demonstrate a decrease of pathological SNCA conformers in the brain and within primary neurons of a ctsd-deficient mouse model after dosing with rHsCTSD. Boosting lysosomal CTSD activity not only enhanced SNCA clearance in human and murine neurons as well as tissue, but also restored endo-lysosome and autophagy function. Our findings indicate that CTSD is critical for SNCA clearance and function. Thus, enzyme replacement strategies utilizing CTSD may also be of therapeutic interest for the treatment of PD and other synucleinopathies aiming to decrease the SNCA burden.Abbreviations: aa: amino acid; SNCA/α-synuclein: synuclein alpha; APP: amyloid beta precursor protein; BBB: blood brain barrier; BF: basal forebrain; CBB: Coomassie Brilliant Blue; CLN: neuronal ceroid lipofuscinosis; CNL10: neuronal ceroid lipofuscinosis type 10; Corr.: corrected; CTSD: cathepsin D; CTSB: cathepsin B; DA: dopaminergic; DA-iPSn: induced pluripotent stem cell-derived dopaminergic neurons; dox: doxycycline; ERT: enzyme replacement therapy; Fx: fornix, GBA/β-glucocerebrosidase: glucosylceramidase beta; h: hour; HC: hippocampus; HT: hypothalamus; i.c.: intracranially; IF: immunofluorescence; iPSC: induced pluripotent stem cell; KO: knockout; LAMP1: lysosomal associated membrane protein 1; LSDs: lysosomal storage disorders; MAPT: microtubule associated protein tau; M6P: mannose-6-phosphate; M6PR: mannose-6-phosphate receptor; MB: midbrain; mCTSD: mature form of CTSD; neurofil.: neurofilament; PD: Parkinson disease; proCTSD: proform of CTSD; PRNP: prion protein; RFU: relative fluorescence units; rHsCTSD: recombinant human proCTSD; SAPC: Saposin C; SIM: structured illumination microscopy; T-insol: Triton-insoluble; T-sol: Triton-soluble; TEM: transmission electron microscopy, TH: tyrosine hydroxylase; Thal: thalamus.
Keywords: alpha-synuclein; cathepsin D; lysosomal degradation; lysosomal storage disorders; parkinson disease; synucleinopathies

Recommendations of the working group of the Anatomische Gesellschaft on reduction of formaldehyde exposure in anatomical curricula and institutes - Waschke, Jens; Bergmann, Martin; Bräuer, Lars; Brenner, Erich; Buchhorn, Andreas; Deutsch, Arlette; Dokter, Martin; Egu, Desalegn Tadesse; Erguen, Suelleyman; Fassnacht, Ulrich; Fietz, Daniela; Gundlach, Stefanie; et al. (Annals of Anatomy-Anatomischer Anzeiger, 2019)
The practice of human and veterinary medicine is based on the science of anatomy and dissection courses are still irreplaceable in the teaching of anatomy. Embalming is required to preserve body donors, for which process formaldehyde (FA) is the most frequently used and well characterized biocidal substance. Since January 2016, a new occupational exposure limit (OEL) for FA of 0.37 mg/m(3) issued by the European Committee on Hazardous Substances is obligatory since FA has been classified as a human 1B carcinogen. The anatomical institutes in the German-speaking region are called upon to consolidate efforts to reduce use of FA in anatomical curricula and body donations. As a result, the Anatomische Gesellschaft (AG) has formed a "Working Group for Reduction of Formaldehyde Exposure in Dissection Courses" tasked with discussion and recommendation of measures to reduce FA. Based on the assessment of the Working Group, the AG has issued an official opinion to the effect that, at this point in time, embalming of body donors without FA completely is not feasible. Therefore, a combination of approaches are to be used to reduce FA exposure, including technical and structural (architectural) adaptations, modification of protocols for fixation and preservation as well as organizational measures. One structural measure considered unavoidable is the integration of air supply and exhaust of individual dissecting tables into the ventilation system of the anatomy building. To embalm human body donors, intra-arterial perfusion fixation with up to 4% FA and a total fluid volume of 150 mL/kg body weight will suffice. For animals where body weights and biology of bodies vary widely (i.e. special needs of fixation for ruminants, large animals as horses) perfusion fixation with up to 4% FA and a quantity of fixative solution of 10-15% of the body weight may be required. Preservation of body donors in storage (immersion) can be done with 40% ethanol or in a full bath preservation containing up to 2% FA. Corpse humidification in the dissecting room is possible with 2% phenoxyethanol, in each case without FA. In veterinary anatomy, microbiological burden is often higher and therefore might lead to a need of FA in long-time storage. Compliance with the current OEL in all institutes would appear to be feasible in combination with various organizational measures. (C) 2018 Elsevier GmbH. All rights reserved.
CRIS-Team WoS Importer:2019-03-01

Reduced invasive and muscle-sparing operative approaches to the posterolateral chest wall provide an excellent accessibility for the operative stabilization! : Minimized approaches to the posterolateral chest wall - Langenbach, A.; Oppel, Pascal; Grupp, Sina; Krinner, Sebastian; Pachowsky, Milena; Buder, Thomas; Schulz-Drost, Melanie; Hennig, Friedrich; Schulz-Drost, Stefan (European Journal of Trauma and Emergency Surgery, 2017)
Stabilizing techniques for flail chest injuries are described through wide surgical approaches to the chest wall, especially in the most affected posterior and lateral regions. Severe morbidity due to these invasive approaches needs to be considered due to dissection of the scapular guiding muscles and the risk of injuries to neurovascular bundles. This study discusses possibilities for minimized approaches to the posterior and lateral regions.Ten fresh-frozen cadavers in lateral decubitus position were observed on both sides. Each surgical arm was kept mobile during the procedure. Approaches were performed following a standard protocol with muscle-sparing incisions starting with 5 cm in length and extending to 10 and 15 cm. The accessible surface comparing the extensions was measured. Visible ribs were counted. In a next step, MatrixRib® Plates were fixed to those ribs to prove the feasibility of rib stabilization through limited approaches.Combinations of the posterior and lateral minimized approaches allow surgical fixation of 6-9 and 7-11 ribs through 5 and 10 cm incisions, respectively. In the case of an extreme expansion of a rib fracture series, an access extension can be made to 15 cm to be able to adequately supply the entire hemithorax using two approaches.Extensive invasive surgical approaches to the thoracic wall can be replaced by reduced invasive and muscle-sparing access combinations. A free-moving positioning of the arm and an accurate preoperative plan for minimizing approaches are essential. Minimally invasive plate techniques are very helpful adjuncts.
EVALuna2:15855

Reduction of NT-3 or TrkC results in fewer putative vagal mechanoreceptors in the mouse esophagus - Raab, Marion; Wörl, Jürgen; Brehmer, Axel; Neuhuber, Winfried (Autonomic Neuroscience-Basic & Clinical, 2003)
Intraganglionic laminar endings (IGLEs) represent major vagal afferent structures throughout the gastrointestinal tract. Both morphological and functional data suggested a mechanosensory role. Elucidation of their functional significance in a particular organ would be facilitated by the availability of animal models with significantly altered numbers of IGLEs. The present study was aimed at searching for mouse strains fulfilling this criterion in the esophagus. Anterograde wheat germ agglutinin-horseradish peroxidase tracing (WGA-HRP) from nodose ganglion was used in order to label esophageal IGLEs in mice deficient for neurotrophin-3 (NT-3) or tyrosine kinase C-receptor (TrkC) and in control littermates. This approach was feasible only in heterozygous mutants which are viable. IGLEs were counted in tetramethylbenzidine (TMB) processed wholemounts using a standardised protocol. Quantification of myenteric neurons was done in cuprolinic blue-stained specimens. Nodose neuron counts were performed in cryostat sections stained with cresyl violet. Numbers of IGLEs in the esophagus were significantly reduced in both heterozygous NT-3 (NT-3+/-) and heterozygous TrkC (TrkC+/-) mutants (65% and 40% reduction, respectively). Numbers of nodose neurons were also significantly reduced in NT-3+/- mice (48% reduction), while their reduction in TrkC+/- mutants was insignificant (11% reduction). There was no reduction of myenteric neurons in the esophagus of either mutant strain. The numeric deficiency of IGLEs was unlikely to be secondary to reduction of myenteric neurons. Although only heterozygous mutants could be studied, these results suggest that esophageal IGLEs share neurotrophin dependence on NT-3/ TrkC with spinal proprioceptors and some cutaneous mechanosensors. This concurs with their proposed function as vagal mechanosensors crucial for reflex peristalsis. © 2003 Elsevier B.V. All rights reserved.
Keywords: IGLEs; Myenteric ganglia; Neurotrophins; Nodose ganglion; Visceral afferents

Regenerative process evaluation of neuronal subclasses in chagasic patients with megacolon - Moreira, Milena D.; Brehmer, Axel; De Oliveira, Enio; Neto, Salustiano D.; Luquetti, Alejandro O.; Bueno, Lilian L.; Fujiwara, Ricardo T.; de Freitas, Michelle A.R.; Da Silveira, Alexandre B.M. (Human Immunology, 2013)
Chagas' disease is one of the most serious parasitic diseases of Latin America, with a social and economic impact far outweighing the combined effects of other parasitic diseases such as malaria, leishmaniasis and schistosomiasis. In the chronic phase of this disease, the destruction of enteric nervous system (ENS) components leads to megacolon development. Previous data presented that the regeneration tax in the ENS neurons is augmented in chagasic patients. Although, there are several neuronal types with different functions in the intestine a detailed study about the regeneration of every neuronal type was never performed before. Therefore, the aim of this study was to evaluate the regeneration tax of every neuronal cell type in the ENS from chagasic patients with megacolon and non-infected individuals. A neuronal regeneration marker (GAP-43) was used in combination with a pan-neuronal marker (Peripherin) and several neuropeptides markers (cChat, Substance P, NPY, VIP and NOS), and it was considered as positive just with the combination of these markers. Our results demonstrated that the regeneration levels of cChat, Substance P, and NPY were similar in chagasic patients and non-infected individuals. However, levels of VIP and NOS neuropeptides were increased in chagasic patients when compared with non-infected individuals. We believe that the augment in the regeneration occur due to an increased destruction of selective neuronal types. These results corroborates with previous studies that pointed out to selective destruction of VIP and NOS neurons in chagasic patients. © 2012 American Society for Histocompatibility and Immunogenetics.

Regional structural differences in the neuronal composition of myenteric ganglia along the pig small intestine - Brehmer, Axel; Stach, Werner (Anatomical Record, 1998)
Background: Data on structural variations in the neuronal composition of myenteric ganglia along the small intestine of various species are scarcely available. The aim of this study was to compare morphologically the ganglia and neurons of different parts of this organ in the pig. Methods: Wholemounts from jejunum and ileum of two 14-week-old pigs were silver impregnated. The number of morphologically defined neuron types I-VI were counted per cm. To relate these numbers to the putative whole neuron population, all impregnated neuronal nucleoli were counted in the same areas. Results: Morphologically classifiable, impregnated neurons ranged between 17.9 and 23.1% of the putative whole population as determined by neuronal nucleoli counting. The proportions of type I neurons (jejunum, 22-25%; ileum, 19%) and type II neurons (jejunum, 30%; ileum, 37%) were considerable in both segments. The proportion of type III neurons was about 30% in jejunum and 2% in ileum whereas the percentages of type IV (jejunum, 10%; ileum, 18%), type V (jejunum, 2%; ileum, 12%) and type VI neurons (jejunum, 3%; ileum, 11%) were higher in the ileum. All differences between jejunal and ileal percentages were significant as determined by chi square test. Conclusions: Ganglia from the upper jejunum and the lower ileum reveal distinct differences in terms of neuron type composition. We suggest that these morphological differences reflect well known functional differences, e.g. in terms of motility, between different parts of the small intestine.
Keywords: Enteric nervous system; Gradient; Morphology; Myenteric plexus; Neuron number; Neuron type; Silver impregnation

Region‐ and loading‐specific finite viscoelasticity of human brain tissue - Budday, Silvia; Sommer, Gerhard; Paulsen, Friedrich; Holzapfel, Gerhard A.; Steinmann, Paul; Kuhl, Ellen (Proceedings in Applied Mathematics and Mechanics, 2018)
Computational simulations are a powerful tool to understand the mechanical behavior of our brain in health and disease, with the ultimate goal to prevent pathological conditions. Accurate numerical predictions, however, require the development of appropriate constitutive models and, equally important, the careful calibration of the corresponding constitutive parameters. This has been exceptionally challenging due to the ultrasoft and heterogeneous nature of brain tissue, resulting in a distinctly nonlinear, rate‐dependent, compression‐tension asymmetric, and region‐dependent behavior. Previous constitutive models have been deduced from a single loading mode, but fail to predict the behavior under various loading conditions. Here, we developed a large strain, nonlinear, viscoelastic constitutive model for brain tissue on the basis of cyclic and relaxation experiments under multiple loading modes, simple shear, compression, and tension. We carefully calibrated individual parameter sets for four different regions of the human brain, the cortex, the basal ganglia, the corona radiata, and the corpus callosum. The model captures effects such as nonlinearity and compression‐tension asymmetry, but also time‐dependent effects with substantial pre‐conditionning during the first loading cycle, only minor conditioning effects during subsequent cycles, and successive softening when the applied strain is stepwise increased. With close consideration of the underlying microstructure, we evaluate the physical meaning of viscoelastic material parameters with rate‐dependent regional trends. Our results help to improve the accuracy of human brain simulations during development and disease or to predict outcomes of neurosurgical procedure

Relaxin 2 augments tissue growth factor beta effects on keratocytes - Hampel, Ulrike; Holland, Detlev; Paulsen, Friedrich (2016)
EVALuna2:35346

Relaxin 2 is functional at the ocular surface and promotes corneal wound healing - Hampel, Ulrike; Klonisch, Thomas; Sel, Saadettin; Schulze, Ute; Garreis, Fabian; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2012)
We aimed to determine if the insulin-like peptide hormone relaxin 2 (RLN2) is expressed at the ocular surface and in tears and if RLN2 influences wound healing at the ocular surface, which is associated with extracellular matrix (ECM) remodeling.We analyzed transcript levels of human RLN2 and its cognate relaxin-like receptors RXFP1 and RXFP2 in tissues of the ocular surface, lacrimal apparatus, and human corneal (HCE), conjunctival (HCjE) and sebaceous (SC) cell lines. We analyzed effects of human RLN2 on cell proliferation and migration and quantified mRNA expression of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) in HCE, HCjE, and SC. Using an alkali-induced corneal wounding model, we analyzed the wound healing rate in C57BL/6 mice eyes after topically applied RLN2.The presence of RLN2, RXFP1, and RXFP2 transcripts was detected in lacrimal gland, eyelid, conjunctiva, cornea, primary corneal fibroblasts, nasolacrimal ducts, and all three cell lines. ELISA revealed RLN2 protein in all ocular surface tissues analyzed and in human tears. Stimulation of HCE, HCjE, and SC with RLN2 significantly increased cell proliferation and migration. Relative mRNA expression levels of MMP2, MMP9, TIMP1, and TIMP2 were significantly influenced by RLN2 in all three cell lines at different time points studied. The local application of RLN2 onto denuded corneal surface resulted in significantly elevated corneal wound healing.Our data support a novel role for the RLN2 ligand-receptor system at the ocular surface and in the lacrimal apparatus as a potential future therapeutic during wound healing at the ocular surface.
EVALuna2:4369

Reliability of clinical techniques for evaluating alveolar bone quality and primary implant stability - Karl, Matthias; Buder, Thomas; Krafft, Tim; Grobecker-Karl, Tanja (Quintessence International, 2019)
Objective: A novel device for intraoperative compressive testing of alveolar bone during implant surgery has been introduced. It was the goal of this study to compare the performance of this device with traditional methods used for determining alveolar bone quality and primary implant stability. Method and materials: Implant surgery in human cadaver bone was performed by two implantologists differing in experience. Bone quality was rated radiographically, based on tactile sensation during drilling and using intraoperative compressive tests. Implant stability was evaluated using insertion torque measurements and resonance frequency analysis. Statistical analysis was based on two way ANOVA followed by Tukey multiple comparisons and Pearson's product moment correlation. The level of significance was set at alpha = .05. Results: Human cadaver bone was ranked according to implant insertion torque. Radiographic assessment, tactile sensation during drilling, and implant stability measurements did not allow differentiating bone types in all instances. Cortical BoneProbe measurements showed a significant trend towards higher measurement values in greater bone quality types (P < .01); in trabecular bone this trend was also present but was not statistically significant. Significant correlations existed between Bone Probe measurements and most other parameters evaluated. Conclusion: Despite the limited number of measurements performed, intraoperative compressive testing of bone may be an option for objectively classifying alveolar bone quality.
CRIS-Team WoS Importer:2019-05-24

Renaming all spinal autonomic outflows as sympathetic is a mistake - Jaenig, Wilfrid; Keast, Janet R.; Mclachlan, Elspeth M.; Neuhuber, Winfried; Southard-Smith, Michelle (Autonomic Neuroscience-Basic & Clinical, 2017)
EVALuna2:35222

Reply: vascularization of the dorsal base of the second metacarpal bone: implications for a reverse second metacarpal dorsal artery flap - Saalabian, Ali A.; Horch, Raymund E.; Bermel, Christina; Arkudas, Andreas; Kneser, Ulrich (Plastic and Reconstructive Surgery, 2015)
EVALuna2:15584

Reproducibility of graft preparations in Descemet's membrane endothelial keratoplasty - Schlötzer-Schrehardt, Ursula; Bachmann, Björn; Tourtas, Theofilos; Cursiefen, Claus; Zenkel, Matthias; Roessler, Kathrin; Kruse, Friedrich (Ophthalmology, 2013)
To assess the reproducibility of manual graft preparation and evaluate the incidence rate and nature of structural anomalies of Descemet's membrane (DM) preventing successful graft preparation in DM endothelial keratoplasty (DMEK).Prospective, single-center, nonrandomized, consecutive case series.We analyzed 350 corneoscleral buttons from donors aged 18-95 years stored in Optisol-GS or Dulbecco's modified Eagle's medium and used for DMEK surgery in 343 consecutive patients with Fuchs' endothelial dystrophy or pseudophakic bullous keratopathy.Residual endothelial cell-DM complexes obtained after successful DM stripping for DMEK and whole donor corneas obtained after unsuccessful DM stripping were examined by transmission electron microscopy and immunohistochemistry.Accuracy of the cleavage plane between DM and corneal stroma and structural abnormalities of the DM-stroma interface.Uneventful manual separation without any disruption of DM was achieved in 335 of 350 donor corneas (95.7%) by use of a previously established bimanual submerged preparation technique. Correspondingly, the peeled DM specimens revealed a regular and smooth cleavage plane exposing the amorphous interfacial matrix on their anterior surface. Although 8 of 350 donor corneas (2.3%) showed focal adhesions of DM to the corneal stroma and developed isolated tears during stripping, preparation of the graft could be successfully completed. However, 7 of the 350 donor corneas (2.0%) showed extremely strong adhesion and multiple tears of DM, preventing successful preparation of the graft. These specimens revealed either ultrastructural (peg-like interlockings) or biochemical abnormalities (increased staining intensities for adhesive glycoproteins) along the DM-stroma interface.Using an appropriate technique, manual preparation of grafts for DMEK with reproducible tissue qualities is possible in the vast majority (98%) of donor corneas. Although a relatively rare phenomenon, interindividual variations in DM structure and composition may be responsible for failure of graft preparation in about 2% of donor corneas.The authors have no proprietary or commercial interest in any of the materials discussed in this article.
EVALuna2:21132

Resilience and sense of coherence in first year medical students - a cross-sectional study - Luibl, Lena; Traversari, Julia; Paulsen, Friedrich; Scholz, Michael; Burger, Pascal (Bmc Medical Education, 2021)
Background: A broad range of studies show that medical students often have a significantly deteriorated mental health status. Although starting medical school with values comparable to the population average, only a few semesters later, medical undergraduates show increased rates of psychological risk states and some manifest mental illnesses, such as burnout and depression. In our survey we intentionally assessed mental health parameters from a salutogenetic, i.e. resource-oriented point of view. Methods: We examined first-year medical students in a cross-sectional study and assessed sense of coherence (SOC) and resilience as parameters from the salutogenesis model by Antonovsky in a structured way using validated, self-administered questionnaires. In total, we examined 236 students of human medicine, dentistry and molecular medicine at the Friedrich-Alexander-University Erlangen-Nürnberg (FAU). Results: Our analyses showed significantly higher values of resilience among male students compared to female students (p < 0.01). In contrast, even though a significant correlation between resilience and SOC was observed, only a non-significantly lower value of SOC was found in female students. Compared to the reference sample our medical students in their first year of study showed significantly lower values for resilience (p < 0.01) and SOC (p < 0.01). Conclusion: Resilience and SOC are known to correlate with psychological stress (burnout parameters) and depression. In order to keep protective factors like SOC and resilience in medical students at a good and healthy level we see the necessity to address that problem proactively and educationally. Integrating training focused on the preservation of the students´ own mental health into the medical curriculum from the beginning of university courses, and throughout the whole medical study course, is essential and should be an obligatory training goal. Based on our study results, we also deem it necessary to think about ways to adapt the measures for the gender-specific needs of our students, e.g. dependent on their biological gender.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Medical education; Mental health status; Resilience; Salutogenesis; Sense of coherence; Undergraduate medical students

Rheumatoid arthritis is characterized by early changes of the cortical micro-channel (CoMiC) system in the bare area of the joints - Werner, David; Simon, David; Englbrecht, Matthias; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Haschka, Judith; Renner, Nina; Buder, Thomas; Engelke, Klaus; Hueber, Axel; Rech, Jürgen; et al. (Arthritis and Rheumatology, 2017)
To characterize the specific structural properties of the erosion-prone bare area of the human joint and to search for early microstructural changes in this region during rheumatoid arthritis Methods: An initial cadaveric study was used for exact localization of the bare area of the metacarpal heads, detection of cortical micro-channels (CoMiCs) in this region by high-resolution peripheral computed tomography (HR-pQCT) and, after anatomical dissection, their validation by micro-computed tomography (?CT). In the second part, number and distribution of CoMiCs were analyzed in 105 healthy individuals and 107 RA patients with similar sex and age distribution.HR-pQCT investigation combined with adaptive thresholding allowed detection of CoMiCs in the bare area of cadaveric joints. Their existence in the bare area was additionally validated by ?CT. In healthy individuals, the number of CoMiCs increased with age. RA patients showed significantly (p<0.001) more CoMiCs (112.9±54.7/joint) than healthy individuals (75.2±41.9/joint) with 20-49 years old RA patients exhibiting similar CoMiC numbers as observed in over 65 year old healthy individuals. Importantly, CoMiCs were found in RA patients already very early in their disease course with enrichment in the erosion-prone radial side of the joint.CoMiCs represent a new form of structural change in the joints of patients with RA. While CoMiCs increase with age, RA patients develop such changes much earlier in life and already at the onset of the disease. CoMiCs therefore represent an interesting new opportunity to assess structural changes in RA. This article is protected by copyright. All rights reserved.
EVALuna2:13409

Risk factors for mental disorders develop early in German students of dentistry - Scholz, Michael; Neumann, Carolin; Ropohl, A.; Paulsen, Friedrich; Burger, P. H. M. (Annals of Anatomy-Anatomischer Anzeiger, 2016)
PURPOSE: We investigated mental risk factors such as symptoms of burnout and sense of coherence in students of dental medicine at the University of Erlangen in the context of a learning type survey. Our aim was to assess the presence of analogies to the results we had previously determined for students of human medicine. METHODS: We surveyed a total of 163 dentistry students during the first 2.5 years, up to the first state examination. To ensure comparability, the data were collected from all students at the beginning of each semester. Standardized, validated questionnaires on burnout symptoms (Burnout Screening Scales; BOSS-II), sense of coherence (Sense of Coherence Scale; SOC-L9) and learning type according to Kolb were used in the survey. RESULTS: A total of about 90% of the students provided responses to the voluntary survey. The extent and manifest dynamics of the stress levels observed can be characterized as dramatic. Having started out at cognitive and emotional stress levels typical of the normal populace, a massive deterioration of these parameters was observed in the students by the time they were facing their first state examination in the 5th semester. At the same time, their sense of coherence also suffered a pronounced drop-off. No significant learning type-correlated differences were determined in a mean comparison of the measured parameters. CONCLUSION: Based on the results obtained, we see a need for preventive course offerings to students of dentistry to reduce the prevalence of mental disorders in this group. We discern additional potential for enhancement of mental health with courses more specifically geared to the different learning styles among the students.
EVALuna2:35353

Rod photoreceptor ribbon synapses in DBA/2J mice show progressive age-related structural changes. - Fuchs, Michaela; Scholz, Michael; Sendelbeck, Anna; Atorf, Jenny; Schlegel, Christine Julie; Enz, Ralf; Brandstätter, Johann Helmut (PLoS ONE, 2012)
The DBA/2J mouse is a commonly used animal model in glaucoma research. The eyes of DBA/2J mice show severe age-related changes that finally lead to the degeneration of retinal ganglion cells and the optic nerve. Recent electroretinogram studies identified functional deficits, which suggest that also photoreceptor cells are involved in the pathological processes occurring in the DBA/2J mouse retina. In a comparative study, we examined anatomical and molecular changes in the retinae of DBA/2J and C57BL/6 control mice with light and electron microscopy and with PCR analyses. In the retina of the DBA/2J mouse, we found a thinning of the outer plexiform layer, the first synaptic layer in the transfer of visual signals, and age-dependent and progressive degenerative structural changes at rod photoreceptor ribbon synapses. The structural ribbon changes represent a photoreceptor synaptic phenotype that has not yet been described in this animal model of secondary angle-closure glaucoma. Furthermore, genes of the classical complement cascade were upregulated in the photoreceptor cells of aging DBA/2J mice, suggesting a putative link between ribbon synapse degradation and the innate immune system. © 2012 Fuchs et al.
UnivIS-Import:2015-04-14:Pub.2012.med.IB.profes_1.rodpho

Same same but different: A Web-based deep learning application revealed classifying features for the histopathologic distinction of cortical malformations - Kubach, Joshua; Muhlebner-Fahrngruber, Angelika; Soylemezoglu, Figen; Miyata, Hajime; Niehusmann, Pitt; Honavar, Mrinalini; Rogerio, Fabio; Kim, Se-Hoon; Aronica, Eleonora; Garbelli, Rita; Vilz, Samuel; Popp, Alexander; et al. (Epilepsia, 2020)
Objective: The microscopic review of hematoxylin-eosin–stained images of focal cortical dysplasia type IIb and cortical tuber of tuberous sclerosis complex remains challenging. Both entities are distinct subtypes of human malformations of cortical development that share histopathological features consisting of neuronal dyslamination with dysmorphic neurons and balloon cells. We trained a convolutional neural network (CNN) to classify both entities and visualize the results. Additionally, we propose a new Web-based deep learning application as proof of concept of how deep learning could enter the pathologic routine. Methods: A digital processing pipeline was developed for a series of 56 cases of focal cortical dysplasia type IIb and cortical tuber of tuberous sclerosis complex to obtain 4000 regions of interest and 200 000 subsamples with different zoom and rotation angles to train a neural network. Guided gradient-weighted class activation maps (Guided Grad-CAMs) were generated to visualize morphological features used by the CNN to distinguish both entities. Results: Our best-performing network achieved 91% accuracy and 0.88 area under the receiver operating characteristic curve at the tile level for an unseen test set. Novel histopathologic patterns were found through the visualized Guided Grad-CAMs. These patterns were assembled into a classification score to augment decision-making in routine histopathology workup. This score was successfully validated by 11 expert neuropathologists and 12 nonexperts, boosting nonexperts to expert level performance. Significance: Our newly developed Web application combines the visualization of whole slide images with the possibility of deep learning–aided classification between focal cortical dysplasia IIb and tuberous sclerosis complex. This approach will help to introduce deep learning applications and visualization for the histopathologic diagnosis of rare and difficult-to-classify brain lesions.
CRIS-Team Scopus Importer:2020-03-06
Keywords: brain; convolutional neural network; cortical malformations; deep learning; digital pathology; epilepsy

Scavenging of bacteria or bacterial products by magnetic particles functionalized with a broad-spectrum pathogen recognition receptor motif offers diagnostic and therapeutic applications - Friedrich, Bernhard; Lyer, Stefan; Janko, Christina; Unterweger, Harald; Brox, Regine; Cunningham, Sarah; Dutz, Silvio; Taccardi, Nicola; Bikker, Floris J.; Hurle, Katrin; Sebald, Heidi; Lenz, Malte; et al. (Acta Biomaterialia, 2022)
Sepsis is a dysregulated host response of severe bloodstream infections, and given its frequency of occurrence and high mortality rate, therapeutic improvements are imperative. A reliable biomimetic strategy for the targeting and separation of bacterial pathogens in bloodstream infections involves the use of the broad-spectrum binding motif of human GP-340, a pattern-recognition receptor of the scavenger receptor cysteine rich (SRCR) superfamily that is expressed on epithelial surfaces but not found in blood. Here we show that these peptides, when conjugated to superparamagnetic iron oxide nanoparticles (SPIONs), can separate various bacterial endotoxins and intact microbes (E. coli, S. aureus, P. aeruginosa and S. marcescens) with high efficiency, especially at low and thus clinically relevant concentrations. This is accompanied by a subsequent strong depletion in cytokine release (TNF, IL-6, IL-1β, Il-10 and IFN-γ), which could have a direct therapeutic impact since escalating immune responses complicates severe bloodstream infections and sepsis courses. SPIONs are coated with aminoalkylsilane and capture peptides are orthogonally ligated to this surface. The particles behave fully cyto- and hemocompatible and do not interfere with host structures. Thus, this approach additionally aims to dramatically reduce diagnostic times for patients with suspected bloodstream infections and accelerate targeted antibiotic therapy. Statement of significance: Sepsis is often associated with excessive release of cytokines. This aspect and slow diagnostic procedures are the major therapeutic obstacles. The use of magnetic particles conjugated with small peptides derived from the binding motif of a broad-spectrum mucosal pathogen recognition protein GP-340 provides a highly efficient scavenging platform. These peptides are not found in blood and therefore are not subject to inhibitory mechanisms like in other concepts (mannose binding lectine, aptamers, antibodies). In this work, data are shown on the broad bacterial binding spectrum, highly efficient toxin depletion, which directly reduces the release of cytokines. Host cells are not affected and antibiotics not adsorbed. The particle bound microbes can be recultured without restriction and thus be used directly for diagnostics.
CRIS-Team Scopus Importer:2022-03-11
Keywords: GP-340; Magnetic nanoparticles; Pathogen binding; Sepsis; SRCR domain

Schirmer strip vs. capillary tube method: Non-invasive methods of obtaining proteins from tear fluid - Posa, Andreas; Braeuer, Lars; Schicht, Martin; Garreis, Fabian; Beileke, Stephanie; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2013)
Human tear fluid is a complex mixture containing over 500 solute proteins, lipids, electrolytes, mucins, metabolites, hormones and desquamated epithelial cells as well as foreign substances from the ambient air. Little is known to date about the function of most tear components. The efficient and gentle collection of tear fluid facilitates closer investigation of these matters. The objective of the present paper was to compare two commonly used methods of obtaining tear fluid, the capillary tube and Schirmer strip methods, in terms of usefulness in molecular biological investigation of tear film. The comparative protein identification methods Bradford and Western Blot were used in the analyses to this end. The surfactant proteins (SP) A-D recently described as present on the eye surface were selected as the model proteins. Both methods feature sufficient uptake efficiency for proteins in or extraction from the sampling means used (capillary tube/Schirmer strip). The total protein concentration can be determined and the proteins in the tears can be detected - besides the hydrophilic SP-A and D also the non-water-soluble proteins of smaller size such as SP-B and C. Thus both methods afford a suitable basis for comparative analysis of the physiological processes in the tear fluid of healthy and diseased subjects. On the whole, the Schirmer strip has several advantages over the capillary tube. © 2012 Elsevier GmbH.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Capillary tube method; Dry eye; Proteomics; Schirmer strip; Surfactant proteins; Tear fluid

Selection of medical students: Should, can - and endure Sollen, können-und aushalten - Scholz, Michael; Burger, Pascal; Paulsen, Friedrich (Deutsches Ärzteblatt international, 2018)
CRIS-Team Scopus Importer:2022-08-05

Selective retina therapy and thermal stimulation of the retina: different regenerative properties-implications for AMD therapy - Richert, Elisabeth; Papenkort, Julia; Von Der Burchard, Claus; Klettner, Alexa; Arnold, Philipp; Lucius, Ralph; Brinkmann, Ralf; Framme, Carsten; Roider, Johann; Tode, Jan (Bmc Ophthalmology, 2021)
Background Selective Retina Therapy (SRT), a photodisruptive micropulsed laser modality that selectively destroys RPE cells followed by regeneration, and Thermal Stimulation of the Retina (TSR), a stimulative photothermal continuous wave laser modality that leads to an instant sublethal temperature increase in RPE cells, have shown therapeutic effects on Age-related Macular Degeneration (AMD) in mice. We investigate the differences between both laser modalities concerning RPE regeneration. Methods For PCR array, 6 eyes of murine AMD models, apolipoprotein E and nuclear factor erythroid-derived 2- like 2 knock out mice respectively, were treated by neuroretina-sparing TSR or SRT. Untreated litter mates were controls. Eyes were enucleated either 1 or 7 days after laser treatment. For morphological analysis, porcine RPE/choroid organ cultures underwent the same laser treatment and were examined by calcein vitality staining 1 h and 1, 3 or 5 days after irradiation. Results TSR did not induce the expression of cell-mediators connected to cell death. SRT induced necrosis associated cytokines as well as inflammation 1 but not 7 days after treatment. Morphologically, 1 h after TSR, there was no cell damage. One and 3 days after TSR, dense chromatin and cell destruction of single cells was seen. Five days after TSR, there were signs of migration and proliferation. In contrast, 1 h after SRT a defined necrotic area within the laser spot was seen. This lesion was closed over days by migration and proliferation of adjacent cells. Conclusions SRT induces RPE cell death, followed by regeneration within a few days. It is accompanied by necrosis induced inflammation, RPE proliferation and migration. TSR does not induce immediate RPE cell death; however, migration and mitosis can be seen a few days after laser irradiation, not accompanied by necrosis-associated inflammation. Both might be a therapeutic option for the treatment of AMD.
CRIS-Team WoS Importer:2021-12-10

Selective survival of calretinin and vasoactive-intestinalpeptide- containing nerve elements in human chagasic submucosa and mucosa - Jabari, Samir; Da Silveira, Alexandre B.M.; De Oliveira, Enio; Neto, Salustiano D.; Quint, Karl; Neuhuber, Winfried; Brehmer, Axel (Cell and Tissue Research, 2012)
Chronic Chagas' disease is frequently characterized by massive myenteric neuron loss resulting in megacolon with severely and irreversibly disturbed motility. Here, we focused on two submucosal neuron populations, immunoreactive for calretinin (CALR) or somatostatin (SOM), and their respective mucosal nerve fibres in chagasic megacolon. Surgically removed megacolonic segments of seven chagasic patients were compared with seven ageand region-matched non-chagasic control segments. Evaluation included immunohistochemical triple-staining of cryosections for CALR, SOM and peripherin or for CALR and vasoactive intestinal peptide (VIP) and of submucosal whole-mounts for CALR, SOMand the pan-neuronal marker anti-HuC/D. Submucosal neuron counts in chagasic tissue revealed neuron numbers reduced to 51.2 % of control values. In cryosections, nerve fibre area measurements revealed 8.6 % nerve fibre per mucosal area in control segments, but this value decreased to 1.5 % in megacolonic segments. In both evaluations, a disproportionate decrease of SOM-reactive nerve elements was observed. The proportions of SOM-positive neurons related to the total neuron number declined to 2 % (control 10 %) and the proportion of SOM-reactive mucosal nerve fibres related to the whole mucosal area to 0.014 % (control 1.8 %)in chagasic tissue. The second set of cryosections revealed extensive colocalization of CALR with VIP in both surviving submucosal perikarya and mucosal nerve fibres. We suggest that VIP, a neuroprotective and neuroeffectory peptide typically contained in submucosal neurons, allows both the VIP-containing neurons to endure and the patients to survive by maintaining their mucosal barrier, despite the almost complete loss of colonic motility for decades. © Springer-Verlag 2012.
Keywords: Chagasic megacolon; Enteric nervous system; Human; Mucosa; Submucosal plexus; Vasoactive intestinal peptide

Sensory spinal interoceptive pathways and energy balance regulation - Münzberg, Heike; Berthoud, Hans Rudolf; Neuhuber, Winfried (Molecular Metabolism, 2023)
Interoception plays an important role in homeostatic regulation of energy intake and metabolism. Major interoceptive pathways include gut-to-brain and adipose tissue-to brain signaling via vagal sensory nerves and hormones, such as leptin. However, signaling via spinal sensory neurons is rapidly emerging as an additional important signaling pathway. Here we provide an in-depth review of the known anatomy and functions of spinal sensory pathways and discuss potential mechanisms relevant for energy balance homeostasis in health and disease. Because sensory innervation by dorsal root ganglia (DRG) neurons goes far beyond vagally innervated viscera and includes adipose tissue, skeletal muscle, and skin, it is in a position to provide much more complete metabolic information to the brain. Molecular and anatomical identification of function specific DRG neurons will be important steps in designing pharmacological and neuromodulation approaches to affect energy balance regulation in disease states such as obesity, diabetes, and cancer.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Diabetes; Energy expenditure; Food intake; Gut-brain communication; Interoception; Interorgan communication; Obesity; Sensory nerves; Spinal cord

Serum-induced keratinization processes in an immortalized human meibomian gland epithelial cell line - Hampel, Ulrike; Schröder, Antje; Mitchell, Todd; Brown, Simon; Snikeris, Peta; Garreis, Fabian; Kunnen, Carolina; Willcox, Mark; Paulsen, Friedrich (PLoS ONE, 2015)
The aim of this study was to evaluate a human meibomian gland epithelial cell line (HMGEC) as a model for meibomian gland (patho)physiology in vitro.HMGEC were cultured in the absence or presence of serum. Sudan III lipid staining, ultrastructural analysis and lipidomic analyses were performed. Impedance sensing, desmoplakin 1/2 mRNA and cytokeratin (CK) 1, 5, 6, 14 levels were evaluated. Serum containing medium supplemented with higher serum, glucose, an omega-3 lipid cocktail, eicosapentaenoic acid or sebomed medium were investigated for lipid accumulation and ultrastructural morphology.Lipid droplet accumulation in HMGEC was induced by serum containing media after 1 day, but decreased over time. Cultivation in serum induced desmosome and cytokeratin filament formation. Desmoplakin 1/2 gene levels were significantly upregulated after 1d of serum treatment. Furthermore, the normalized impedance increased significantly. Lipidome analysis revealed high levels of phospholipids (over 50%), but very low levels of wax ester and cholesteryl esters (under 1%). Stimulation with eicosapentaenoic acid increased lipid accumulation after one day.Serum treatment of HMGEC caused lipid droplet formation to some extent but also induced keratinization. The cells did not produce typical meibum lipids under these growth conditions. HMGEC are well suited to study (hyper)keratinization processes of meibomian gland epithelial cells in vitro.
EVALuna2:4445

Severe bornavirus-encephalitis presenting as Guillain–Barré-syndrome - Coras, Roland; Korn, Klaus; Kürten, Stefanie; Huttner, Hagen; Enßer, Armin (Acta Neuropathologica, 2019)
CRIS-Team Scopus Importer:2019-06-04

Sex neurosteroids: Hormones made by the brain for the brain - Fester, Lars; Rune, Gabriele M. (Neuroscience Letters, 2021)
In general, hippocampal neurons are capable of synthesizing sex steroids de novo from cholesterol, since the brain is equipped with all the enzymes required for the synthesis of estradiol and testosterone, the end products of sex steroidogenesis. Regarding estradiol, its synthesis in hippocampal neurons is homeostatically controlled by Ca2+ transients and is regulated by GnRH. Locally synthesized estradiol and testosterone maintain synaptic transmission and synaptic connectivity. Remarkably, the neurosteroid estradiol is effective in females, but not in males, and vice versa dihydrotestosterone (DHT) is effective in males, but not in females. Experimentally induced inhibition of estradiol synthesis in females and DHT synthesis in males resp. results in synapse loss, impaired LTP, and downregulation of synaptic proteins. GnRH-induced increase in estradiol synthesis appears to provide a link between the hypothalamus and the hippocampus, which may underlie estrous cyclicity of spine density in the female hippocampus. Hippocampal neurons are sex-dependently differentiated with respect to the responsiveness of hippocampal neurons to sex neurosteroids.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Hippocampus; LTP; Sex steroids; Sex-specificity; Synaptic plasticity

Sex-specific features of spine densities in the hippocampus - Brandt, Nicola; Löffler, Tobias; Fester, Lars; Rune, Gabriele M. (Scientific Reports, 2020)
Previously, we found that in dissociated hippocampal cultures the proportion of large spines (head diameter ≥ 0.6 μm) was larger in cultures from female than from male animals. In order to rule out that this result is an in vitro phenomenon, we analyzed the density of large spines in fixed hippocampal vibratome sections of Thy1-GFP mice, in which GFP is expressed only in subpopulations of neurons. We compared spine numbers of the four estrus cycle stages in females with those of male mice. Remarkably, total spine numbers did not vary during the estrus cycle, while estrus cyclicity was evident regarding the number of large spines and was highest during diestrus, when estradiol levels start to rise. The average total spine number in females was identical with the spine number in male animals. The density of large spines, however, was significantly lower in male than in female animals in each stage of the estrus cycle. Interestingly, the number of spine apparatuses, a typical feature of large spines, did not differ between the sexes. Accordingly, NMDA-R1 and NMDA-R2A/B expression were lower in the hippocampus and in postsynaptic density fractions of adult male animals than in those of female animals. This difference could already be observed at birth for NMDA-R1, but not for NMDA-R2A/B expression. In dissociated embryonic hippocampal cultures, no difference was seen after 21 days in culture, while the difference was evident in postnatal cultures. Our data indicate that hippocampal neurons are differentiated in a sex-dependent manner, this differentiation being likely to develop during the perinatal period.
CRIS-Team Scopus Importer:2020-07-24

Sexual dimorphism among quantitative parameters of the muscles of mastication and skull of the rabbit - Brehmer, Axel; Beleites, Bernhard (Anatomischer Anzeiger, 1988)
The dry weight of the muscles of mastication and the size of the skull in the rabbit were studied from the 45th to the 225th d of life. Sexual dimorphism in the dry weight of the muscles of mastication appeared after the 100th d, the weight being higher in the case of the males. Sexual dimorphism of the skull affected only the zygomatic arch, the dimensions of the zygomatic arch in the male being greater than in the female from the 120th d on. The 2 differences are considered in relation to each other.

SFTA3, a novel protein of the lung: three-dimensional structure, characterisation and immune activation - Schicht, Martin; Rausch, Felix; Finotto, Susetta; Mathews, Martina; Mattil, Anja; Schubert, Melanie; Koch, Beate; Traxdorf, Maximilian; Bohr, Christopher; Worlitzsch, Dieter; Brandt, Wolfgang; Garreis, Fabian; et al. (European Respiratory Journal, 2014)
The lung constantly interacts with numerous pathogens. Thus, complex local immune defence mechanisms are essential to recognise and dispose of these intruders. This work describes the detection, characterisation and three-dimensional structure of a novel protein of the lung (surfactant-associated protein 3 (SFTA3/SP-H)) with putative immunological features. Bioinformatics, biochemical and immunological methods were combined to elucidate the structure and function of SFTA3. The tissue-specific detection and characterisation was performed by using electron microscopy as well as fluorescence imaging. Three-dimensional structure generation and analysis led to the development of specific antibodies and, as a consequence, to the localisation of a novel protein in human lung under consideration of cystic fibrosis, asthma and sepsis. In vitro experiments revealed that lipopolysaccharide induces expression of SFTA3 in the human lung alveolar type II cell line A549. By contrast, the inflammatory cytokines interleukin (IL)-1? and IL-23 inhibit expression of SFTA3 in A549. Sequence- and structure-based prediction analysis indicated that the novel protein is likely to belong to the family of lung surfactant proteins. The results suggest that SFTA3 is an immunoregulatory protein of the lung with relevant protective functions during inflammation at the mucosal sites.
EVALuna2:4400

SFTA3 - a novel surfactant protein of the ocular surface and its role in corneal wound healing and tear film surface tension - Schicht, Martin; Garreis, Fabian; Hartjen, Nadine; Beileke, Stephanie; Jacobi, Christina; Sahin, Afsun; Holland, Detlef; Schröder, Henrik; Hammer, Christian; Paulsen, Friedrich; Bräuer, Lars (Scientific Reports, 2018)
The study aimed to characterize the expression and function of SFTA3 at the ocular surface and in tears. Ocular tissues, conjunctival (HCjE) and human corneal (HCE) epithelial cell lines as well as tearfilm of patients suffering from different forms of dry eye disease (DED) were analyzed by means of RT-PCR, western blot, immunohistochemistry, and ELISA. A possible role of recombinant SFTA3 in corneal wound healing was investigated performing in vitro scratch assays. Tear film regulatory properties were analyzed with the spinning drop method and the regulation of SFTA3 transcripts was studied in HCE and HCjE after incubation with proinflammatory cytokines as well as typical ocular pathogens by real-time RT-PCR and ELISA. The results reveal that human ocular tissue as well as tears of healthy volunteers express SFTA3 whereas tears from patients with DED showed significantly increased SFTA3 levels. In vitro wounding of HCE cell cultures that had been treated with recombinant SFTA3 demonstrated a significantly increased wound closure rate and rSFTA3 reduced the surface tension of tear fluid. The results indicate that SFTA3 at the ocular surface seemed to be involved in wound healing and the reduction of surface tension.
EVALuna2:35316

Silk fiber-reinforced hyaluronic acid-based hydrogel for cartilage tissue engineering - Weitkamp, Jan Tobias; Wöltje, Michael; Nußpickel, Bastian; Schmidt, Felix N.; Aibibu, Dilbar; Bayer, Andreas; Eglin, David; Armiento, Angela R.; Arnold, Philipp; Cherif, Chokri; Lucius, Ralph; Smeets, Ralf; et al. (International Journal of Molecular Sciences, 2021)
A continuing challenge in cartilage tissue engineering for cartilage regeneration is the creation of a suitable synthetic microenvironment for chondrocytes and tissue regeneration. The aim of this study was to develop a highly tunable hybrid scaffold based on a silk fibroin matrix (SM) and a hyaluronic acid (HA) hydrogel. Human articular chondrocytes were embedded in a porous 3-dimensional SM, before infiltration with tyramine modified HA hydrogel. Scaffolds were cultured in chondropermissive medium with and without TGF-β1. Cell viability and cell distribution were assessed using CellTiter-Blue assay and Live/Dead staining. Chondrogenic marker expression was detected using qPCR. Biosynthesis of matrix compounds was analyzed by dimethylmethylene blue assay and immuno-histology. Differences in biomaterial stiffness and stress relaxation were characterized using a one-step unconfined compression test. Cell morphology was investigated by scanning electron microscopy. Hybrid scaffold revealed superior chondro-inductive and biomechanical properties compared to sole SM. The presence of HA and TGF-β1 increased chondrogenic marker gene expression and matrix deposition. Hybrid scaffolds offer cytocompatible and highly tunable properties as cell-carrier systems, as well as favorable biomechanical properties.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Autologous chondrocyte implanta-tion; Biomaterials; Cartilage; Chondrocytes; Hyaluronic acid; Silk fibroin; TGF-β1

Skully - An Educational Web Application for the Human Skull - Bertelshofer, Franziska; Brehm, Oliver; Fitzner, Paul; Lammert, Jacqueline; Janka, Rolf Matthias; Paulsen, Friedrich; Greiner, Günther (Bildverarbeitung für die Medizin 2016, 2016)
One fundamental topic in anatomy is the structure of the human skull. Common sources for studying are books, atlases and other two dimensional material which makes it hard to optimally locate the separate parts of the human skull in three dimensional space and understand the relations between them. We developed a browser application visualizing three dimensional models of the human skull. The user can interact with those models, e.g. move them freely to gain insight in the three dimensional structure and position of the single bones, highlight separate bones or groups of them and view textual annotations. In a developer mode those annotations can be edited easily by anatomy experts or course tutors to contain all relevant information. Furthermore the application is platform independent, it can used on e.g. computers with different operating systems, tablets and mobile phones.

Smart Shell-by-Shell Nanoparticles with Tunable Perylene Fluorescence in the Organic Interlayer - Stiegler, Lisa; Klein, Stefanie; Kryschi, Carola; Neuhuber, Winfried; Hirsch, Andreas (Chemistry - A European Journal, 2021)
A new series of shell-by-shell (SbS)-functionalized Al2O3 nanoparticles (NPs) containing a perylene core in the organic interlayer as a fluorescence marker is introduced. Initially, the NPs were functionalized with both, a fluorescent perylene phosphonic acid derivative, together with the lipophilic hexadecylphosphonic acid or the fluorophilic (1 H,1 H,2 H,2H-perfluorodecyl)phosphonic acid. The lipophilic first-shell functionalized NPs were further implemented with amphiphiles built of aliphatic chains and polar head-groups. However, the fluorophilic NPs were combined with amphiphiles consisting of fluorocarbon tails and polar head-groups. Depending on the nature of the combined phosphonic acids and the amphiphiles, tuning of the perylene fluorescence can be accomplished due variations of supramolecular organization with the shell interface. Because the SbS-functionalized NPs dispose excellent dispersibility in water and in biological media, two sorts of NPs with different surface properties were tested with respect to biological fluorescent imaging applications. Depending on the agglomeration of the NPs, the cellular uptake differs. The uptake of larger agglomerates is facilitated by endocytosis, whereas individualized NPs cross directly the cellular membrane. Also, the larger agglomerates were preferentially incorporated by all tested cells.
CRIS-Team Scopus Importer:2020-12-11
Keywords: amphiphiles; fluorescent imaging; hydro-; lipo-; fluoro-philic/phobic; perylene chromophore; shell-by-shell (SbS)-functionalization

Sobetirome rescues α-synuclein-mediated demyelination in an in vitro model of multiple system atrophy - Meszaros, Lisa; Himmler, Marcus; Schneider, Yanni; Arnold, Philipp; Dörje, Frank; Schubert, Dirk W.; Winkler, Jürgen (European Journal of Neuroscience, 2023)
Multiple system atrophy (MSA) is a rare and rapidly progressive atypical parkinsonian disorder characterized by oligodendroglial cytoplasmic inclusions containing α-synuclein (α-syn), demyelination, inflammation and neuronal loss. To date, no disease-modifying therapy is available. Targeting α-syn-driven oligodendroglial dysfunction and demyelination presents a potential therapeutic approach for restricting axonal dysfunction, neuronal loss and disease progression. The present study investigated the promyelinogenic potential of sobetirome, a blood–brain barrier permeable and central nervous system selective thyromimetic in the context of an in vitro MSA model. Oligodendrocyte precursor cells (OPCs) were obtained from transgenic mice overexpressing human α-syn specifically in oligodendrocytes (MBP29 mouse line), a well-described MSA model, and non-transgenic littermates. mRNA and protein expression analyses revealed a substantial rescue effect of sobetirome on myelin-specific proteins in control and α-syn overexpressing oligodendrocytes. Furthermore, myelination analysis using nanofibres confirmed that sobetirome increases both the length and number of myelinated segments per oligodendrocyte in primary murine α-syn overexpressing oligodendrocytes and their respective control. These results suggest that sobetirome may be a promising thyromimetic compound targeting an important neuropathological hallmark of MSA.
CRIS-Team Scopus Importer:2023-12-22
Keywords: MSA; myelin; oligodendrocytes; sobetirome; thyromimetics; α-synuclein

Somatostatin immunoreactivity in quail pterygopalatine ganglion - Schrödl, Falk; De Stefano, M. Egle; Minvielle, Francis; Brehmer, Axel; Neuhuber, Winfried (Journal of Anatomy, 2005)
In the ciliary ganglion of the chicken and quail, somatostatin (SOM) is an exclusive marker for parasympathetic postganglionic neurons innervating the choroid. A second parasympathetic pathway projecting to the choroid originates from the pterygopalatine ganglion. The aim of this study was to investigate SOM immunoreactivity in the pterygopalatine ganglion of the Japanese quail (Coturnix coturnix japonica) and on neurons within the choroid, the intrinsic choroidal neurons (ICN). We did so using immunohistochemistry and subsequent light, electron and confocal laser scanning microscopy. Pterygopalatine neurons were characterized by nNOS-immunohistochemistry or NADPH-diaphorase cytochemistry. SOM immunoreactivity was absent in the perikarya, but neurons were densely surrounded by SOM-positive nerve fibres. Electron microscopy revealed that these fibres formed contacts with and without membrane specializations on pterygopalatine neurons. In the choroid, neuronal nitric-oxide synthase (nNOS)-immunoreactive ICN were likewise closely apposed by SOM-immunoreactive nerve fibres, as revealed by confocal microscopy. There was no detectable co-localization of the markers. In the absence of tracing studies, it is open to speculation whether SOM immunoreactivity originates from preganglionic fibres of the superior salivatory nucleus, postganglionic fibres of the ciliary ganglion or fibres of the brainstern via as yet unknown pathways. SOM may regulate the production of NO in pterygopalatine neurons and ICN, respectively, and is therefore involved in neuronal circuits regulating ocular homeostasis. © Anatomical Society of Great Britain and Ireland 2005.
Keywords: Autonomic innervation of the eye; Blood flow; Intrinsic choroidal neurons; NADPH-d; nNOS

Somatostatin supports corneal wound healing in vivo - Hampel, Ulrike; Frömmling, Paul; Bräuer, Lars; Schaefer, Ivonne; Sel, Saadettin; Holland, Detlev; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2016)
PURPOSE: To evaluate the influence of somatostatin (SST) and its analog octreotid (Oct) on corneal wound healing processes. METHODS: The wound healing rate in C57BL/6 mice eyes under SST and Oct treatment was analyzed using an alkali-induced corneal wounding model. Effects of SST and Oct on cell proliferation, migration and quantified protein expression of vascular endothelial growth factor (VEGF) on human corneal epithelial cells (HCE, cell line) were evaluated by means of electric cell-substrate impedance sensing, scratch migration assays and ELISA. ERK1/2 and p38 phosphorylation was investigated by semi-quantitative western blot analysis. RESULTS: Ten nanograms per microliters of SST significantly accelerated the wound closure rate of corneal defects in vivo. SST and Oct had no influence on HCE cell proliferation and migration and did not activate ERK1/2 or p38 signaling in HCE cells. However, there was increased VEGF protein expression in cytosolic proteins and medium supernatants of HCE upon Oct stimulation for 24h. One and 10ng/ml Oct led to a 2.5-fold and 100ng/ml Oct to a 4-fold upregulation of VEGF protein expression. CONCLUSION: The data implicate that SST promotes corneal wound healing in a mouse model. However, using a HCE cell line in vitro, the wound healing mechanism does not seem to be supported by proliferation and migration processes or by activation of ERK1/2 and p38 signaling pathways. Other possible mechanisms could be the activation of other pathways and the induction of growth factors such as VEGF that modulate the observed corneal wound healing process.
EVALuna2:34494

Spatiotemporal Pattern of Human Cortical and Subcortical Activity during Early-Stage Odor Processing - Stadlbauer, Andreas; Kaltenhauser, Martin; Buchfelder, Michael; Brandner, Sebastian; Neuhuber, Winfried; Renner, Bertold (Chemical Senses, 2016)
The dynamics of early-stage cortical and subcortical responses in the human brain to odor stimulation are currently unknown. The objective of the present study was to analyze spatiotemporal patterns of human brain activity during odor perception using magnetoencephalography (MEG). In 12 normosmic healthy subjects, we investigated the onset of brain activity in relation to ipsilateral and contralateral stimulation with 2 odorants. Olfactory stimuli (200ms duration) were applied using an olfactometer, and brain activity was recorded with a 248-magnetometer whole-head MEG system. Olfactory responses were identified shortly (within 150ms) after stimulus onset in both hemispheres. Stimulation on the ipsilateral side yielded signals earlier (starting at 90ms) compared with contralateral stimulation in the primary olfactory cortex, hippocampus, parahippocampal gyrus, amygdala, and orbitofrontal cortex (P < 0.001). The duration and peak amplitude of olfactory evoked magnetic fields were found to increase with increasing poststimulus time in the majority of the investigated cortical structures (P ≤ 0.019 and P ≤ 0.021). The study showed the locations of early olfactory brain activity in humans within 150ms after the onset of stimuli. Olfactory activation is processed on the ipsilateral side of stimulation in early stages. After a short delay of 34ms a corresponding pattern of activation was also seen in the contralateral hemisphere, indicating the functional connectivity between the 2 hemispheres in the anterior commissure.
EVALuna2:32855

Special obligation to Exercise Diligence in sensitive Topics - Schicht, Martin (Monatsschrift Kinderheilkunde, 2020)
CRIS-Team WoS Importer:2020-04-14

Special pattern of endochondral ossification in human laryngeal cartilages: X-ray and light-microscopic studies on thyroid cartilage - Claassen, Horst; Schicht, Martin; Sel, Saadettin; Paulsen, Friedrich (Clinical Anatomy, 2014)
Endochondral ossification is a process that also occurs in the skeleton of the larynx. Differences in the ossification mechanism in comparison to growth plates are not understood until now. To get deeper insights into this process, human thyroid cartilage was investigated by the use of X-rays and a series of light-microscopic stainings. A statistical analysis of mineralization was done by scanning areas of mineralized cartilage and of ossification. We detected a special mode of endochondral ossification which differs from the processes in growth plates. Thyroid cartilage ossifies very slowly and in a gender-specific manner. Compared with age-matched women, bone formation in thyroid cartilage of men is significantly higher in the age group 41-60 years. Endochondral ossification is prepared by internal changes of extracellular matrix leading to areas of asbestoid fibers with ingrowing cartilage canals. In contrast to growth plates, bone is deposited on large areas of mineralized cartilage, which appear at the rims of cartilage canals. Furthermore, primary parallel fibered bone was observed which was deposited on woven bone. The predominant bone type is cancellous bone with trabeculae, whereas compact bone with Haversian systems was seldom found. Trabeculae contain a great number of reversal and arresting lines meaning that the former were often reconstructed and that bone formation was arrested and resumed again with advancing age. It is hypothesized that throughout life trabeculae of ossified thyroid cartilage undergo adaptation to different loads due to the use of voice.
EVALuna2:4424

Spectrum bias and individual strengths of SARS-CoV-2 serological tests–A population-based evaluation - Einhauser, Sebastian; Peterhoff, David; Niller, Hans Helmut; Beileke, Stephanie; Günther, Felix; Steininger, Philipp; Burkhardt, Ralph; Heid, Iris M.; Pfahlberg, Annette Bettina; Überla, Klaus; Gefeller, Olaf; Wagner, Ralf (Diagnostics, 2021)
Antibody testing for determining the SARS-CoV-2 serostatus was rapidly introduced in early 2020 and since then has been gaining special emphasis regarding correlates of protection. With limited access to representative samples with known SARS-CoV-2 infection status during the initial period of test development and validation, spectrum bias has to be considered when moving from a “test establishment setting” to population-based settings, in which antibody testing is currently implemented. To provide insights into the presence and magnitude of spectrum bias and to estimate performance measures of antibody testing in a population-based environment, we compared SARS-CoV-2 neutralization to a battery of serological tests and latent class analyses (LCA) in a subgroup (n = 856) of the larger population based TiKoCo-19 cohort (n = 4185). Regarding spectrum bias, we could proof notable differences in test sensitivities and specificities when moving to a population-based setting, with larger effects visible in earlier registered tests. While in the population-based setting the two Roche ELECSYS anti-SARS-CoV-2 tests outperformed every other test and even LCA regarding sensitivity and specificity in dichotomous testing, they didn’t provide satisfying quantitative correlation with neutralization capacity. In contrast, our in-house anti SARS-CoV-2-Spike receptor binding domain (RBD) IgG-ELISA (enzyme-linked-immunosorbant assay) though inferior in dichotomous testing, provided satisfactory quantitative correlation and may thus represent a better correlate of protection. In summary, all tests, led by the two Roche tests, provided sufficient accuracy for dichotomous identification of neutralizing sera, with increasing spectrum bias visible in earlier registered tests, while the majority of tests, except the RBD-ELISA, didn’t provide satisfactory quantitative correlations.
CRIS-Team Scopus Importer:2021-10-29
Keywords: ECLIA; ELISA; Neutralization; SARS-CoV-2; Sensitivity; Serology; Specificity; Spectrum bias; Test accuracy

SP-G, a novel surfactant protein of the ocular surface that regulates surface tension of tears and might play a role in dry eye disease - Bräuer, Lars; Schicht, Martin; Paulsen, Friedrich (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

"SP-G", a Putative New Surfactant Protein - Tissue Localization and 3D Structure - Rausch, Felix; Schicht, Martin; Paulsen, Friedrich; Ngueya, Ivan; Bräuer, Lars; Brandt, Wolfgang (PLoS ONE, 2012)
Surfactant proteins (SP) are well known from human lung. These proteins assist the formation of a monolayer of surface-active phospholipids at the liquid-air interface of the alveolar lining, play a major role in lowering the surface tension of interfaces, and have functions in innate and adaptive immune defense. During recent years it became obvious that SPs are also part of other tissues and fluids such as tear fluid, gingiva, saliva, the nasolacrimal system, and kidney. Recently, a putative new surfactant protein (SFTA2 or SP-G) was identified, which has no sequence or structural identity to the already know surfactant proteins. In this work, computational chemistry and molecular-biological methods were combined to localize and characterize SP-G. With the help of a protein structure model, specific antibodies were obtained which allowed the detection of SP-G not only on mRNA but also on protein level. The localization of this protein in different human tissues, sequence based prediction tools for posttranslational modifications and molecular dynamic simulations reveal that SP-G has physicochemical properties similar to the already known surfactant proteins B and C. This includes also the possibility of interactions with lipid systems and with that, a potential surface-regulatory feature of SP-G. In conclusion, the results indicate SP-G as a new surfactant protein which represents an until now unknown surfactant protein class. © 2012 Rausch et al.
CRIS-Team Scopus Importer:2022-08-05

Spiny versus stubby: 3D reconstruction of human myenteric (type I) neurons - Brehmer, Axel; Lindig, Tobias; Kumar, Vinod; Kikins, Ron; Pieper, Steve; Schrödl, Falk; Neuhuber, Winfried (Intensive Care Medicine, 2008)
We have compared the three-dimensional (3D) morphology of stubby and spiny neurons derived from the human small intestine. After immunohistochemical triple staining for leu-enkephalin (ENK), vasoactive intestinal peptide (VIP) and neuro filament (NF), neurons were selected and scanned based on their immunoreactivity, whether ENK (stubby) or VIP (spiny). For the 3D reconstruction, we focused on confocal data pre-processing with intensity drop correction, non-blind deconvolution, an additional compression procedure in z-direction, and optimizing segmentation reliability. 3D Slicer software enabled a semi-automated segmentation based on an objective threshold (interrater and intrarater reliability, both 0.99). We found that most dendrites of stubby neurons emerged only from the somal circumference, whereas in spiny neurons, they also emerged from the luminal somal surface. In most neurons, the nucleus was positioned abluminally in its soma. The volumes of spiny neurons were significantly larger than those of stubby neurons (total mean of stubbies 806 ± 128 μm, of spinies 2,316 ± 545 μm ), and spiny neurons had more dendrites (26.3 vs. 11.3). The ratios of somal versus dendritic volumes were 1:1.2 in spiny and 1:0.3 in stubby neurons. In conclusion, 3D reconstruction revealed new differences between stubby and spiny neurons and allowed estimations of volumetric data of these neuron populations. © Springer-Verlag 2008.
Keywords: Confocal microscopy; Enteric nervous system; Gut; Innervation; Neuron type

Spiny versus stubby: 3D reconstruction of human myenteric (type I) neurons - Lindig, Tobias; Kumar, Vinod; Kikins, Ron; Pieper, Steve; Schrödl, Falk; Neuhuber, Winfried; Brehmer, Axel (Histochemistry and Cell Biology, 2009)
We have compared the three-dimensional (3D) morphology of stubby and spiny neurons derived from the human small intestine. After immunohistochemical triple staining for leu-enkephalin (ENK), vasoactive intestinal peptide (VIP) and neurofilament (NF), neurons were selected and scanned based on their immunoreactivity, whether ENK (stubby) or VIP (spiny). For the 3D reconstruction, we focused on confocal data pre-processing with intensity drop correction, non-blind deconvolution, an additional compression procedure in z-direction, and optimizing segmentation reliability. 3D Slicer software enabled a semi-automated segmentation based on an objective threshold (interrater and intrarater reliability, both 0.99). We found that most dendrites of stubby neurons emerged only from the somal circumference, whereas in spiny neurons, they also emerged from the luminal somal surface. In most neurons, the nucleus was positioned abluminally in its soma. The volumes of spiny neurons were significantly larger than those of stubby neurons (total mean of stubbies 806 ± 128 μm, of spinies 2,316 ±; 545 μm ), and spiny neurons had more dendrites (26.3 vs. 11.3). The ratios of somal versus dendritic volumes were 1:1.2 in spiny and 1:0.3 in stubby neurons. In conclusion, 3D reconstruction revealed new differences between stubby and spiny neurons and allowed estimations of volumetric data of these neuron populations. © Springer-Verlag 2008.
Keywords: Confocal microscopy; Enteric nervous system; Gut; Innervation; Neuron type

Splitting the "Unsplittable": Dissecting Resident and Infiltrating Macrophages in Experimental Autoimmune Encephalomyelitis - Koeniger, Tobias; Kürten, Stefanie (International Journal of Molecular Sciences, 2017)
Macrophages predominate the inflammatory landscape within multiple sclerosis (MS) lesions, not only regarding cellularity but also with respect to the diverse functions this cell fraction provides during disease progression and remission. Researchers have been well aware of the fact that the macrophage pool during central nervous system (CNS) autoimmunity consists of a mixture of myeloid cells. Yet, separating these populations to define their unique contribution to disease pathology has long been challenging due to their similar marker expression. Sophisticated lineage tracing approaches as well as comprehensive transcriptome analysis have elevated our insight into macrophage biology to a new level enabling scientists to dissect the roles of resident (microglia and non-parenchymal macrophages) and infiltrating macrophages with unprecedented precision. To do so in an accurate way, researchers have to know their toolbox, which has been filled with diverse, discriminating approaches from decades of studying neuroinflammation in animal models. Every method has its own strengths and weaknesses, which will be addressed in this review. The focus will be on tools to manipulate and/or identify different macrophage subgroups within the injured murine CNS.
EVALuna2:35217

Standardized statement for the ethical use of human cadaveric tissues in anatomy research papers: Recommendations from Anatomical Journal Editors-in-Chief - Iwanaga, Joe; Singh, Vishram; Takeda, Sen; Ogeng'O, Julius; Kim, Hee-Jin; Morys, Janusz; Ravi, Kumar Satish; Ribatti, Domenico; Trainor, Paul A.; Sanudo, Jose Ramon; Apaydin, Nihal; Sharma, Anu; et al. (Clinical Anatomy, 2022)
Human cadaveric donors are essential for research in the anatomical sciences. However, many research papers in the anatomical sciences often omit a statement regarding the ethical use of the donor cadavers or, as no current standardized versions exist, use language that is extremely varied. To rectify this issue, 22 editors-in-chief of anatomical journals, representing 17 different countries, developed standardized and simplified language that can be used by authors of studies that use human cadaveric tissues. The goal of these editor recommendations is to standardize the writing approach by which the ethical use of cadaveric donors is acknowledged in anatomical studies that use donor human cadavers. Such sections in anatomical papers will help elevate our discipline and promote standardized language use in others non anatomy journals and also other media outlets that use cadaveric tissues.
CRIS-Team Scopus Importer:2022-03-18
Keywords: anatomy; cadavers; dissection; medical ethics; guideline; recommendation; research

Staphylococcus aureus and Pseudomonas aeruginosa Express and Secrete Human Surfactant Proteins - Schicht, Martin; Worlitzsch, Dieter; Bensel, Tobias; Sawers, R. Gary; Paulsen, Friedrich; Bräuer, Lars (PLoS ONE, 2013)
Surfactant proteins (SP), originally known from human lung surfactant, are essential to proper respiratory function in that they lower the surface tension of the alveoli. They are also important components of the innate immune system. The functional significance of these proteins is currently reflected by a very large and growing number of publications. The objective goal of this study was to elucidate whether Staphylococcus aureus and Pseudomonas aeruginosa is able to express surfactant proteins. 10 different strains of S. aureus and P. aeruginosa were analyzed by means of RT-PCR, Western blot analysis, ELISA, immunofluorescence microscopy and immunoelectron microscopy. The unexpected and surprising finding revealed in this study is that different strains of S. aureus and P. aeruginosa express and secrete proteins that react with currently commercially available antibodies to known human surfactant proteins. Our results strongly suggest that the bacteria are either able to express 'human-like' surfactant proteins on their own or that commercially available primers and antibodies to human surfactant proteins detect identical bacterial proteins and genes. The results may reflect the existence of a new group of bacterial surfactant proteins and DNA currently lacking in the relevant sequence and structure databases. At any rate, our knowledge of human surfactant proteins obtained from immunological and molecular biological studies may have been falsified by the presence of bacterial proteins and DNA and therefore requires critical reassessment. © 2013 Bräuer et al.
CRIS-Team Scopus Importer:2022-08-05

Steady-State Visually Evoked Potentials Elicited by Multifrequency Pattern-Reversal Stimulation - Hohberger, Bettina; Kremers, Jan; Horn, Folkert (Translational Vision Science & Technology, 2019)
Purpose: It has been shown that multifrequency stimulation with multifocal electroretinography can reduce recording time without a loss in signal-to-noise ratio. Here, we studied the applicability of multifrequency stimulations for steady-state visually evoked potential (VEP) recordings.
CRIS-Team WoS Importer:2019-03-15
Keywords: Objective visual field test; Multifocal VEP; Signal-to-noise ratio; Pattern reversal; Steady-state

Store-operated calcium entry is reduced in spastin-linked hereditary spastic paraplegia - Winner, Beate; Rizo Garza, Tania; Gebhardt, Lisa; Riedlberger, Julia; Eberhardt, Esther; Fester, Lars; Alansary, Dalia; Winkler, Jürgen; Turan, Sören; Arnold, Philipp; Niemeyer, Barbara; Fischer, Michael (2022)
Pathogenic variants in SPAST, the gene coding for spastin, are the single most common cause of hereditary spastic paraplegia, a progressive motor neuron disease. Spastin regulates key cellular functions, including microtubule-severing and endoplasmic reticulum-morphogenesis. However, it remains unclear how alterations in these cellular functions due to SPAST pathogenic variants result in motor neuron dysfunction. Since spastin influences both microtubule network and endoplasmic reticulum structure, we hypothesized that spastin is necessary for the regulation of Ca2+ homeostasis via store-operated calcium entry. Here, we show that the lack of spastin enlarges the endoplasmic reticulum and reduces store-operated calcium entry. In addition, elevated levels of different spastin variants induced clustering of STIM1 within the endoplasmic reticulum, altered the transport of STIM1 to the plasma membrane and reduced store-operated calcium entry, which could be rescued by exogenous expression of STIM1. Importantly, store-operated calcium entry was strongly reduced in induced pluripotent stem cell-derived neurons from hereditary spastic paraplegia patients with pathogenic variants in SPAST resulting in spastin haploinsufficiency. These neurons developed axonal swellings in response to lack of spastin. We were able to rescue both store-operated calcium entry and axonal swellings in SPAST patient neurons by restoring spastin levels, using CRISPR/Cas9 to correct the pathogenic variants in SPAST. These findings demonstrate that proper amounts of spastin are a key regulatory component for store-operated calcium entry mediated Ca2+ homeostasis and suggest store-operated calcium entry as a disease relevant mechanism of spastin-linked motor neuron disease.Rizo et al. use iPSC-derived neurons from patients to investigate how pathogenic variants in SPAST give rise to hereditary spastic paraplegia. They show that dysregulation of spastin, a microtubule- and ER-remodelling protein encoded by SPAST, alters the dynamics of the ER, resulting in aberrant Ca2+ regulation.
Keywords: spastin; STIM1; microtubules; endoplasmic reticulum; store-operated calcium entry

Strategies against Burnout and Anxiety in Medical Education - Implementation and Evaluation of a New Course on Relaxation Techniques (Relacs) for Medical Students - Wild, Katharina; Scholz, Michael; Ropohl, Axel; Bräuer, Lars; Paulsen, Friedrich; Burger, Pascal H. M. (PLoS ONE, 2014)
Burnout and stress-related mental disorders (depression, anxiety) occur in medical students and physicians with a significantly higher prevalence than in the general population. At the same time, the learning of coping mechanisms against stress is still not an integral part of medical education. In this pilot study we developed an elective course for learning relaxation techniques and examined the condition of the students before and after the course. 42 students participated in the semester courses in 2012 and 2013 as well as in a survey at the start and end of each course. The students were instructed in autogenic training (AT) and progressive muscle relaxation according to Jacobsen (PMR) with the goal of independent and regular exercising. At the beginning and the end of the semester/course the students were interviewed using standardized, validated questionnaires on burnout (BOSS-II) and anxiety (STAI-G), depression (BDI), quality of life (SF-12) and sense of coherence (SOC-L9). We compared the results of our students participating in Relacs with results from eight semester medical students (n = 88), assessed with the same questionnaires at similar points of time within their semester. Participating students showed a significant decline in cognitive and emotional burnout stress and in trait anxiety. Furthermore, they showed a reduction in state anxiety and a conspicuous decrease in mean depression. The sense of coherence increased at the same time. A comparative cohort of medical students of 8th semester students, showed lower values for the specified measurement parameters at the beginning, but showed no progressive changes. Our course introducing AT and PMR led to a significant reduction of burnout and anxiety within the participating group of medical students. Even the course attendance for just one semester resulted in significant improvements in the evaluated parameters in contrast to those students who did not attend the course.
EVALuna2:4405

Strategies for neuroprotection in multiple sclerosis and the role of calcium - Enders, Michael; Heider, Thorsten; Ludwig, Andreas; Kürten, Stefanie (International Journal of Molecular Sciences, 2020)
Calcium ions are vital for maintaining the physiological and biochemical processes inside cells. The central nervous system (CNS) is particularly dependent on calcium homeostasis and its dysregulation has been associated with several neurodegenerative disorders including Parkinson’s disease (PD), Alzheimer’s disease (AD) and Huntington’s disease (HD), as well as with multiple sclerosis (MS). Hence, the modulation of calcium influx into the cells and the targeting of calcium-mediated signaling pathways may present a promising therapeutic approach for these diseases. This review provides an overview on calcium channels in neurons and glial cells. Special emphasis is put on MS, a chronic autoimmune disease of the CNS. While the initial relapsing-remitting stage of MS can be treated effectively with immune modulatory and immunosuppressive drugs, the subsequent progressive stage has remained largely untreatable. Here we summarize several approaches that have been and are currently being tested for their neuroprotective capacities in MS and we discuss which role calcium could play in this regard.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Calcium channels; Calcium homeostasis; Dihydropyridines; Multiple sclerosis; Neurodegeneration; Neuroprotection; Nimodipine; Remyelination

Structural and functional properties of meprin β metalloproteinase with regard to cell signaling - Li, Wenjia; Lueckstaedt, Wiebke; Wöhner, Birte; Bub, Simon; Schulz, Antonia; Socher, Eileen; Arnold, Philipp (Biochimica Et Biophysica Acta-Molecular Cell Research, 2021)
The metalloproteinase meprin β plays an important role during collagen I deposition in the skin, mucus detachment in the small intestine and also regulates the abundance of different cell surface proteins such as the interleukin-6 receptor (IL-6R), the triggering receptor expressed on myeloid cells 2 (TREM2), the cluster of differentiation 99 (CD99), the amyloid precursor protein (APP) and the cluster of differentiation 109 (CD109). With that, regulatory mechanisms that control meprin β activity and regulate its release from the cell surface to enable access to distant substrates are increasingly important. Here, we will summarize factors that alternate meprin β activity and thereby regulate its proteolytic activity on the cell surface or in the supernatant. We will also discuss cleavage of the IL-6R and TREM2 on the cell surface and compare it to CD109. CD109, as a substrate of meprin β, is cleaved within the protein core thereby releasing defined fragments from the cell surface. At last, we will also summarize the role of proteases in general and meprin β in particular in substrate release on extracellular vesicles.
Keywords: meprin β; CD109; proteolysis; metalloproteases; substrates; extracellular vesicles

Structural features of the anterior region of the mandible - Vasil'ev, Yuriy; Paulsen, Friedrich; Dydykin, Sergey; Bogoyavlenskaya, Tatyana; Kashtanov, Artem (Annals of Anatomy-Anatomischer Anzeiger, 2020)
The research aims were to find out further intraosseous mandible organization indications and to structure it systematically. Material and methods: : in our research 400 mandibles were used: for the intraosseous examinations in total 300 mandibles of persons aged 20–65 were used. For all corpses cephalic index was measured. Segmentation of the mandibles were made by Jigley saw between medial root of the first molar at one side and central and second incisor of the opposite one. After that segments were stained with Schiff's reagent with following preparation. Dry preparations (n = 100) were used in exploration of mental foramen macroanatomy. Results: : mental foramen cavity depth was divided into three types: low, n = 33 (depth 269 ± 081 mm), medium, n = 36 (depth 358 ± 092 mm) and deep, n = 31 (depth 417 ± 036 mm); transverse size of the cavity is 3109 ± 041 mm and longitudinal size is 397 ± 055 mm. According to the mandible anterior intraosseous organization research it is possible to make a mental nerve intraosseous canal types systematization: semi-oval; straight; s-shaped type, formed by two opposite and transient bends. The S-shaped type (49%) is more common in persons with a dolichocephalic skull type, especially (57.55%) in mesocephalic type and semi-oval (66.36%) in brachycephalic type. Conclusion: : nerve in the eponymous mental foramen, (which we would like to call a cavity), is branched into two large branches: the extraosseous branch, which innervates the soft tissues (such as Rr. mentales, Rr. labiales and Rr. gingivales), and the intraosseous branch, which runs from the mental foramen to the symphysis, from the latter branch to the first premolar, to the canine and to the incisors.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Bone; Inferior alveolar nerve; Mandible; Mental foramen; Mental nerve; Terminology

Structure, Function and Insertion of the Human Vocal Folds - Paulsen, Friedrich; Tillmann, Bernhard (Advances in Oto-Rhino-Laryngology, 2020)
We here summarize the structures of the laryngeal vocal fold as well as its insertion structures at the anterior commissure and at the area of the vocal process and place these findings within the context of biomechanical, functional, and clinical implications.
CRIS-Team Scopus Importer:2020-11-20

Structure of enteric neurons. - Brehmer, Axel (Advances in Anatomy Embryology and Cell Biology, 2006)
The ENS contains numerous different neuron populations which belong to three main groups, primary afferent neurons, interneurons and effector neurons. The most extensive knowledge on the different enteric neuron types is derived from studies in the guinea pig. A significant obstacle for the transfer of this knowledge to putative equivalent enteric neurons of other species, including human, is species differences as to their morphological, chemical, physiological etc. phenotypes. Modern morphological classifications are based on the work of the Russian histologist Dogiel. Since the late 1970s, refined morphological classifications of enteric neurons beyond Dogiel have been attempted mainly in two species, the pig and the guinea pig. These reflect the immunohistochemical diversity of enteric neurons more precisely but are far from being complete. In this paper, we follow two aims. First, we have presented an overview on the chemical coding of the morphological neuron types described by Stach in the pig intestine. In doing so, we have pointed out the difference between the definitions of type I neurons given by Dogiel and Stach. Second, we have attempted to provide a basis for the morpho-chemical classification of human enteric neurons as revealed by their immunoreactivity for NFs and several neuroactive substances or related markers. According to results from guinea pig, where there is functional evidence, human morphological type II neurons (non-dendritic, multiaxonal; co-reactive for NF, CAR, SOM, SP) seem to be the intrinsic primary afferent neurons. This conclusion is based primarily on structural equivalence. Human ENK-positive, stubby (type I) neurons maybe ascending interor motorneurons. In contrast, nitrergic, VIP-reactive spiny (type I) neurons maybe descending inter- or motor neurons. Further, morphologically defined human neuron types, i.e. type III, type V and dendritic type II neurons, are non-nitrergic but could not be chemically defined as yet. Future investigations of morpho-chemical characteristics of human enteric neurons including also other cytoskeletal markers will provide a broader basis for neurohistopathological diagnostics of gut diseases.

Structure, regulation and related diseases of the actin-binding protein gelsolin - Feldt, Jessica; Schicht, Martin; Garreis, Fabian; Welss, Jessica; Schneider, Ulrich W.; Paulsen, Friedrich (Expert Reviews in Molecular Medicine, 2019)
Gelsolin (GSN), one of the most abundant actin-binding proteins, is involved in cell motility, shape and metabolism. As a member of the GSN superfamily, GSN is a highly structured protein in eukaryotic cells that can be regulated by calcium concentration, intracellular pH, temperature and phosphatidylinositol-4,5-bisphosphate. GSN plays an important role in cellular mechanisms as well as in different cellular interactions. Because of its participation in immunologic processes and its interaction with different cells of the immune system, GSN is a potential candidate for various therapeutic applications. In this review, we summarise the structure of GSN as well as its regulating and functional roles, focusing on distinct diseases such as Alzheimer's disease, rheumatoid arthritis and cancer. A short overview of GSN as a therapeutic target in today's medicine is also provided.
CRIS-Team WoS Importer:2019-02-27

Substance P- and choline acetyltransferase immunoreactivities in somatostatin-containing, human submucosal neurons - Beyer, Jakob; Jabari, Samir; Rau, Tilman T.; Neuhuber, Winfried; Brehmer, Axel (Histochemistry and Cell Biology, 2013)
The submucous layers of human small and large intestines contain at least two separate neuron populations. Besides morphological features, they differ in their immunoreactivities for calretinin (CALR) and somatostatin (SOM), respectively. In this study, submucosal wholemounts of 23 patients or body donors (including all segments of small intestine and colon) were immunohistochemically quadruple stained for CALR and SOM as well as for substance P (SP) and choline acetyltransferase (ChAT). We found that all SOM-positive neurons co-stained for ChAT and the majority for SP [between 50 % in the small intestinal external submucosal plexus (ESP) and 75 % in the colonic ESP]. In contrast, a majority of CALR-neurons contained ChAT (between 77 % in the small intestinal ESP and 92 % in the large intestinal ESP) whereas less than 4 % of CALR-neurons were co-immunoreactive for SP. Another set of wholemounts was co-stained for peripherin, a marker enabling morphological analysis. Where identifiable, both SOM alone- and SOM/SP-neurons displayed a uniaxonal (supposed pseudouniaxonal) morphology. We suggest that the chemical code of SOM-immunoreactive, human submucosal neurons may be "ChAT+/SOM+/ SP±". In additional sections double stained for SOM and SP, we regularly found double-labelled nerve fibres only in the mucosa. In contrast, around submucosal arteries mostly SOM alone- fibres were found and the muscularis propria contained numerous SP-alone fibres. We conclude that the main target of submucosal SOM(/SP)-neurons may be the mucosa. Due to their morpho-chemical similarity to human myenteric type II neurons, we further suggest that one function of human submucosal SOM-neurons may be a primary afferent one. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Enteric nervous system; Gut; Innervation; Mucosa; Submucosal plexus

Superparamagnetic iron oxide nanoparticles as novel x-ray enhancer for low-dose radiation therapy - Klein, Stefanie; Sommer, Anja; Distel, Luitpold; Hazemann, Jean-Louis; Kroener, Wolfgang; Neuhuber, Winfried; Müller, Paul; Proux, Olivier; Kryschi, Carola (Journal of Physical Chemistry B, 2014)
Superparamagnetic iron oxide nanoparticles (SPIONs) with a mixed phase composition (γ-FeO)(Fe O)and sizes between 9 and 20 nm were synthesized via coprecipitation and were either left uncoated or subsequently surface-stabilized with citrate or malate anions. The sizes, morphology, surface chemistry, and magnetic properties of the nanoparticles were characterized using transmission electron microscopy (TEM), Fourier transform infrared spectroscopy, and superconducting quantum interference device measurements, respectively. Cellular uptake and intracellular distribution in normal tissue and tumor cells were verified by TEM images. X-ray-induced changes of the oxidation state and site geometries of surface iron ions of uncoated and citrate-coated SPIONs were explored by collecting Fe K-edge X-ray absorption spectroscopy data. The potential applicability of citrate- and malate-coated SPIONs as an X-ray enhancer for radiation cancer therapy was substantiated by their drastic enhancement of the concentration of reactive oxygen species (ROS) in X-ray irradiated tumor cells. © 2014 American Chemical Society.

Superparamagnetic iron oxide nanoparticles as radiosensitizer via enhanced reactive oxygen species formation - Klein, Stefanie; Sommer, Anja; Distel, Luitpold; Neuhuber, Winfried; Kryschi, Carola (Biochemical and Biophysical Research Communications, 2012)
Internalization of citrate-coated and uncoated superparamagnetic iron oxide nanoparticles by human breast cancer (MCF-7) cells was verified by transmission electron microscopy imaging. Cytotoxicity studies employing metabolic and trypan blue assays manifested their excellent biocompatibility. The production of reactive oxygen species in iron oxide nanoparticle loaded MCF-7 cells was explained to originate from both, the release of iron ions and their catalytically active surfaces. Both initiate the Fenton and Haber-Weiss reaction. Additional oxidative stress caused by X-ray irradiation of MCF-7 cells was attributed to the increase of catalytically active iron oxide nanoparticle surfaces. © 2012 Elsevier Inc.

Surfactant protein H is part of the tear film, lowers surface tension, is increased in dry eye disease and accelerates corneal wound healing - Paulsen, Friedrich; Hartjen, Nadine; Beilicke, Stephanie; Garreis, Fabian; Jacobi, Christina; Sahin, Afsun; Holland, Detlev; Bräuer, Lars; Schicht, Martin (2018)
EVALuna2:35310

Surfactant proteins of the human larynx - Sheats, Michelle; Schröder, Henrik; Rauscha, F.; Bohr, Christopher; Kißlinger, Franziska; De Tristan, J.; Iro, Heinrich; Garreis, Fabian; Paulsen, Friedrich; Schicht, Martin; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2016)
PURPOSE: Surfactant proteins (SPs) originally identified in lung tissue are important players in the innate immune system. Beyond this, they contribute to stability and rheology of gaseous or aqueous interphases. In the present study, we determined the expression and presence of SPs (A, B, C and D) in different areas of the human larynx. METHODS: mRNA expression of SP-A, -B, -C and -D was analyzed by means of RT-PCR in healthy samples of epiglottis, vocal and vestibular folds, subglottis and trachea. Distribution and localization of all four SPs were analyzed by Western blot and immunohistochemistry in healthy human tissue samples. RESULTS: All four SPs were detected at the mRNA- and protein level in the human larynx as well as by means of immunohistochemistry in the different tissue samples of the human larynx. CONCLUSION: The results reveal that all four SPs are produced with different expression patterns within the human larynx. Based on the known functions, our results suggest that SPs might be involved in maintaining mucus rheology and subsequently they could be essential components for proper phonation. Moreover, the proteins seem to play a role in immune defense of the larynx.
EVALuna2:33358

Surfactant proteins: Role in lacrimal drainage disorders - Mohammad, Javed Ali; Paulsen, Friedrich (Medical Hypotheses, 2019)
Surfactants are complex mixtures of phospholipids and proteins produced by type II alveolar cells of the lungs and play a crucial role in pulmonary physiology. Six types of surfactant proteins (SP) are known; SP-A, SP-B, SP-C, SP-D, SP-G and SP-H. The major role of SP is in reducing surface tension and various immunological functions. SP-A, SP-B, SP-C and SP-D have been demonstrated in the tear film and the epithelium of the lacrimal sac (LS) and nasolacrimal ducts (NLD). All surfactant proteins except SP-G were also isolated from the canalicular tissues. The authors hypothesize that surfactant proteins play a significant role in the pathogenesis of lacrimal drainage disorders; functional nasolacrimal duct obstruction (FNLDO) and infective dacryocystitis.
CRIS-Team WoS Importer:2019-03-29

Surgical fixation of sternal fractures: preoperative planning and a safe surgical technique using locked titanium plates and depth limited drilling - Schulz-Drost, Stefan; Oppel, Pascal; Grupp, Sina; Schmitt, Sonja; Carbon, Roman Th.; Mauerer, Andreas; Hennig, Friedrich; Buder, Thomas (Journal of Visualized Experiments, 2015)
Different ways to stabilize a sternal fracture are described in literature. Respecting different mechanisms of trauma such as the direct impact to the anterior chest wall or the flexion-compression injury of the trunk, there is a need to retain each sternal fragment in the correct position while neutralizing shearing forces to the sternum. Anterior sternal plating provides the best stability and is therefore increasingly used in most cases. However, many surgeons are reluctant to perform sternal osteosynthesis due to possible complications such as difficulties in preoperative planning, severe injuries to mediastinal organs, or failure of the performed method. This manuscript describes one possible safe way to stabilize different types of sternal fractures in a step by step guidance for anterior sternal plating using low profile locking titanium plates. Before surgical treatment, a detailed survey of the patient and a three dimensional reconstructed computed tomography is taken out to get detailed information of the fracture's morphology. The surgical approach is usually a midline incision. Its position can be described by measuring the distance from upper sternal edge to the fracture and its length can be approximated by the summation of 60 mm for the basis incision, the thickness of presternal soft tissue and the greatest distance between the fragments in case of multiple fractures. Performing subperiosteal dissection along the sternum while reducing the fracture, using depth limited drilling, and fixing the plates prevents injuries to mediastinal organs and vessels. Transverse fractures and oblique fractures at the corpus sterni are plated longitudinally, whereas oblique fractures of manubrium, sternocostal separation and any longitudinally fracture needs to be stabilized by a transverse plate from rib to sternum to rib. Usually the high convenience of a patient is seen during follow up as well as a precise reconstruction of the sternal morphology.
EVALuna2:15820

Sympathetic innervation of inguinal white adipose tissue in the mouse - Huesing, Clara; Qualls-Creekmore, Emily; Lee, Nathan; François, Marie; Torres, Hayden; Zhang, Rui; Burk, David H.; Yu, Sangho; Morrison, Christopher D.; Berthoud, Hans Rudolf; Neuhuber, Winfried; Münzberg, Heike (Journal of Comparative Neurology, 2020)
Adipose tissue plays an important role in metabolic homeostasis and its prominent role as endocrine organ is now well recognized. Adipose tissue is controlled via the sympathetic nervous system (SNS). New viral, molecular-genetic tools will soon allow a more detailed study of adipose tissue innervation in metabolic function, yet, the precise anatomical extent of preganglionic and postganglionic inputs to the inguinal white adipose tissue (iWAT) is limited. Furthermore, several viral, molecular-genetic tools will require the use of cre/loxP mouse models, while the available studies on sympathetic iWAT innervation were established in larger species. In this study, we generated a detailed map for the sympathetic innervation of iWAT in male and female mice. We adapted iDISCO tissue clearing to process large, whole-body specimens for an unprecedented view of the natural abdominal SNS. Combined with pseudorabies virus retrograde tracing from the iWAT, we defined the preganglionic and postganglionic sympathetic input to iWAT. We used fluorescence-guided anatomical dissections of sympathetic nerves in reporter mice to further clarify that postganglionic axons connect to iWAT via lateral cutaneous rami (dorsolumbar iWAT portion) and the lumbar plexus (inguinal iWAT portion). Importantly, these rami carry axons that branch to iWAT, as well as axons that travel further to innervate the skin and vasculature, and their functional impact will require consideration in denervation studies. Our study may serve as a comprehensive map for future experiments that employ virally driven neuromodulation techniques to predict anatomy-based viral labeling.
CRIS-Team Scopus Importer:2020-10-09
Keywords: iDISCO; imaging; pseudorabies virus; sympathetic chain ganglia; tissue clearing; transsynaptic retrograde tracing

Sympathetic innervation of the mouse kidney and liver arising from prevertebral ganglia - Torres, Hayden; Huesing, Clara; Burk, David H.; Molinas, Adrien J.R.; Neuhuber, Winfried; Berthoud, Hans Rudolf; Münzberg, Heike; Derbenev, Andrei V.; Zsombok, Andrea (American Journal of Physiology-Regulatory Integrative and Comparative Physiology, 2021)
The sympathetic nervous system (SNS) plays a crucial role in the regulation of renal and hepatic functions. Although sympathetic nerves to the kidney and liver have been identified in many species, specific details are lacking in the mouse. In the absence of detailed information of sympathetic prevertebral innervation of specific organs, selective manipulation of a specific function will remain challenging. Despite providing major postganglionic inputs to abdominal organs, limited data are available about the mouse celiac-superior mesenteric complex. We used tyrosine hydroxylase (TH) and dopamine β-hydroxylase (DbH) reporter mice to visualize abdominal prevertebral ganglia. We found that both the TH and DbH reporter mice are useful models for identification of ganglia and nerve bundles. We further tested if the celiac-superior mesenteric complex provides differential inputs to the mouse kidney and liver. The retrograde viral tracer, pseudorabies virus (PRV)-152 was injected into the cortex of the left kidney or the main lobe of the liver to identify kidney-projecting and liver-projecting neurons in the celiac-superior mesenteric complex. iDISCO immunostaining and tissue clearing were used to visualize unprecedented anatomical detail of kidney-related and liverrelated postganglionic neurons in the celiac-superior mesenteric complex and aorticorenal and suprarenal ganglia compared with TH-positive neurons. Kidney-projecting neurons were restricted to the suprarenal and aorticorenal ganglia, whereas only sparse labeling was observed in the celiac-superior mesenteric complex. In contrast, liver-projecting postganglionic neurons were observed in the celiac-superior mesenteric complex and aorticorenal and suprarenal ganglia, suggesting spatial separation between the sympathetic innervation of the mouse kidney and liver.
CRIS-Team Scopus Importer:2021-09-10
Keywords: iDISCO; Kidney; Liver; Retrograde tracing; Sympathetic nervous system

Syndromic and Nonsyndromic Systemic Associations of Congenital Lacrimal Drainage Anomalies: A Major Review - Ali, Mohammad Javed; Paulsen, Friedrich (Ophthalmic Plastic and Reconstructive Surgery, 2017)
PURPOSE: To review and summarize the syndromic, nonsyndromic, and systemic associations of congenital lacrimal drainage anomalies. METHODS: The authors performed a PubMed search of all articles published in English on congenital lacrimal anomalies (1933-2016). Patients of these articles were reviewed along with the literature of direct references to syndromes and other systemic associations. Data reviewed included syndromic descriptions, systemic details, demographics, lacrimal presentations, management, and outcomes. RESULTS: Syndromic and systemic associations with congenital lacrimal drainage disorders are not known to be common. Although familial presentations have been reported, the inheritance patterns are unclear for most anomalies. There is an increasingly growing evidence of a genetic basis to many lacrimal anomalies. However, few syndromes have either widespread or are frequently associated with lacrimal anomalies. Few sequences of distinct lacrimal presentations and intraoperative findings are seen. Surgical challenges in these patients are distinct and a thorough pre and intraoperative anatomical assessment, detailed imaging when indicated, and assessment and correction of associated periocular and facial abnormalities may facilitate good outcomes. CONCLUSIONS: Lacrimal drainage anomalies associated with syndromic and nonsyndromic systemic conditions have certain unique features of their own and their surgical and anesthesia challenges are distinct. Diagnosis of congenital lacrimal drainage anomalies should prompt consideration of the possible presence of associated systemic abnormalities.
EVALuna2:35324

Systemic PPAR gamma Antagonism Reduces Metastatic Tumor Progression in Adipocyte-Rich Bone in Excess Weight Male Rodents - Gaculenko, Anastasia; Gregoric, Gasper; Popp, Vanessa; Seyler, Lisa; Ringer, Mark; Kachler, Katerina; Wu, Zhengquan; Kisel, Wadim; Hofbauer, Christine; Hofbauer, Lorenz C.; Uder, Michael; Schett, Georg; et al. (Journal of Bone and Mineral Research, 2021)
Primary tumors are widely associated with an excess in body fat. The role of adipose tissue on tumor cell homing to bone is yet poorly defined. In this study, we aimed to assess whether bone colonization by tumor cells is favored by an adipocyte-rich bone marrow. We delineated the accompanying alterations of the bone microenvironment and established a treatment approach that interferes with high fat diet (HFD)-induced bone metastasis formation. We were able to show that adipocytes affect skeletal tumor growth in a metastatic model of breast cancer in male rats and melanoma in male mice as well as in human breast cancer bone biopsies. Indeed, HFD-induced bone marrow adiposity was accompanied by accelerated tumor progression and increased osteolytic lesions. In human bone metastases, bone marrow adiposity correlated with tumor cell proliferation. By antagonization of the adipocyte differentiation and storage pathway linked to the peroxisome proliferator-activated receptor gamma (PPAR gamma) with bisphenol-A-diglycidylether (BADGE), we were able to decelerate tumor progression and subsequent osteolytic damage in the bones of two distinct metastatic animal models exposed to HFD. Overall these data show that adipose tissue is a critical factor in bone metastases and cancer-induced bone loss. 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).
CRIS-Team WoS Importer:2021-09-03

Teaching anatomy under COVID-19 conditions at German universities: recommendations of the teaching commission of the anatomical society - Böckers, Anja; Claassen, Horst; Haastert-Talini, Kirsten; Westermann, Jürgen (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Background: In this viewpoint representatives of the Teaching Commission of the Anatomical Society summarize their teaching experiences gained during the COVID-19 pandemic in the summer term of 2020 and derive first recommendations concerning face-to-face and remote teaching of anatomy for the future. Methods: Representatives of the Teaching Commission of the Anatomical Society met virtually, exchanged experiences and summarized them in writing and answered a short questionnaire. Results: The required transition to remote learning during summer term of 2020 was possible, but revealed technical shortcomings and major deficits concerning practical hands-on teaching. Conclusion: The Teaching Commission of the Anatomical Society recommends that universities should follow the idea of as much face-to-face teaching as possible and as much online teaching as necessary for future terms.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Anatomy teaching; COVID-19 pandemic; Face-to face-learning; Remote learning

Teaching to Relax: Development of a Program to Potentiate Stress—Results of a Feasibility Study with Medical Undergraduate Students - Scholz, Michael; Neumann, Carolin; Wild, Katharina; Garreis, Fabian; Hammer, Christian; Ropohl, Axel; Paulsen, Friedrich; Burger, Pascal H. M. (Applied Psychophysiology and Biofeedback, 2016)
Medical students are a population at risk for the development of stress-related risk states (e.g. burnout) and manifest mental disorders (e.g. depression). Still the learning of coping mechanisms against stress is not an integral part of the medical curriculum. In a pilot study we developed an elective course for learning relaxation techniques (Relacs) which was geared to the clinical practice of autogenic training (AT) with psychiatric patients. The course focussed on an innovative and mostly communicative transfer of knowledge about AT, progressive muscle relaxation and medical hypnosis and stressed the principle of repeated and supervised exercises in small student groups alongside self-administered exercise. 42 students took part in this course and showed a very high acceptance for the topic and positive evaluation. Moreover, we found a distinct improvement of the participants’ mental parameters (burnout, anxiety) and a good knowledge about the course’s contents within the final exams at the end of the semester. The structure and realisation of the course is easily adaptable and very effective regarding the improvement of the students’ mental health. Due to our results and the commonly known prevalence of stress-related disorders in medical students we postulate the integration of courses on relaxation strategies in the medical curriculum.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Autogenic training; Burnout; Medical education; Medical hypnosis; Progressive muscle relaxation

Temporal and spatial expression pattern of Nnat during mouse eye development - Sel, Saadettin; Patzel, Eva; Poggi, Lucia; Kaiser, Delia; Kalinski, Thomas; Schicht, Martin; Paulsen, Friedrich; Nass, Norbert (Gene Expression Patterns, 2017)
BACKGROUND: Neuronatin (Nnat) was initially identified as a highly expressed gene in neonatal mammalian brain. In this study, we analyze the spatial and temporal expression pattern of Nnat during mouse eye development as well as in the adult. METHODS: The expression of Nnat was analyzed on mRNA as well as protein level. The presence of Nnat transcripts in the adult retina was examined using reverse transcription-polymerase chain reaction (RT-PCR). Nnat protein expression was evaluated by Western blot and immunohistochemistry during eye development at embryonic day (E) 12, 15, 16 and postnatal day (P) 7, 14, 30 and 175 (adult). RESULTS: Immunohistochemical studies of the developing mouse eye revealed Nnat expression in embryonic and adult neuroretina as well as in corneal epithelial, stromal, endothelial cells and in lens epithelium. Expression of Nnat was detected from E12 onwards and was also present in adult eyes. CONCLUSIONS: The expression pattern suggests that Nnat may play an important role during eye development and in the maintenance of mature eye.
EVALuna2:35340

Test anxiety among German medical students and its impact on lifestyle and substance abuse - Tektas, Ozan Yüksel; Paulsen, Friedrich; Sel, Saadetin (Medical Teacher, 2013)
CRIS-Team Scopus Importer:2022-08-05

Tff3 Deficiency Protects against Hepatic Fat Accumulation after Prolonged High-Fat Diet - Seselja, Kate; Bazina, Iva; Vrecl, Milka; Welss, Jessica; Schicht, Martin; Mihalj, Martina; Kopacin, Vjekoslav; Paulsen, Friedrich; Pirman, Tatjana; Loncar, Mirela Baus (Life, 2022)
Trefoil factor 3 (Tff3) protein is a small secretory protein expressed on various mucosal surfaces and is involved in proper mucosal function and recovery via various mechanisms, including immune response. However, Tff3 is also found in the bloodstream and in various other tissues, including the liver. Its complete attenuation was observed as the most prominent event in the early phase of diabetes in the polygenic Tally Ho mouse model of diabesity. Since then, its role in metabolic processes has emerged. To elucidate the complex role of Tff3, we used a new Tff3-deficient mouse model without additional metabolically relevant mutations (Tff3-/-/C57BL/6NCrl) and exposed it to a high-fat diet (HFD) for a prolonged period (8 months). The effect was observed in male and female mice compared to wild-type (WT) counter groups (n = 10 animals per group). We monitored the animals' general metabolic parameters, liver morphology, ultrastructure and molecular genes in relevant lipid and inflammatory pathways. Tff3-deficient male mice had reduced body weight and better glucose utilization after 17 weeks of HFD, but longer HFD exposure (32 weeks) resulted in no such change. We found a strong reduction in lipid accumulation in male Tff3-/-/C57BL/6NCrl mice and a less prominent reduction in female mice. This was associated with downregulated peroxisome proliferator-activated receptor gamma (Ppar gamma) and upregulated interleukin-6 (Il-6) gene expression, although protein level difference did not reach statistical significance due to higher individual variations. Tff3-/-/C57Bl6N mice of both sex had reduced liver steatosis, without major fatty acid content perturbations. Our research shows that Tff3 protein is clearly involved in complex metabolic pathways. Tff3 deficiency in C57Bl6N genetic background caused reduced lipid accumulation in the liver; further research is needed to elucidate its precise role in metabolism-related events.
CRIS-Team WoS Importer:2022-09-09

TGF-β2- and H2O2-Induced Biological Changes in Optic Nerve Head Astrocytes Are Reduced by the Antioxidant Alpha-Lipoic Acid - Yu, Alice L.; Moriniere, Jerome; Welge-Lüssen, Ulrich-Christoph (Ophthalmic Research, 2012)
Background/Aims: The goal of the present study was to determine whether transforming growth factor-?(2) (TGF-?(2))- and oxidative stress-induced cellular changes in cultured human optic nerve head (ONH) astrocytes could be reduced by pretreatment with the antioxidant ?-lipoic acid (LA). Methods: Cultured ONH astrocytes were treated with 1.0 ng/ml TGF-?(2) for 24 h or 200 µM hydrogen peroxide (H(2)O(2)) for 1 h. Lipid peroxidation was measured by a decrease in cis-parinaric acid fluorescence. Additionally, cells were pretreated with different concentrations of LA before TGF-?(2) or H(2)O(2) exposure. Expressions of the heat shock protein (Hsp) ?B-crystallin and Hsp27, the extracellular matrix (ECM) component fibronectin and the ECM-modulating protein connective tissue growth factor (CTGF) were examined with immunohistochemistry and real-time PCR analysis. Results: Both TGF-?(2) and H(2)O(2) increased lipid peroxidation. Treatment of astrocytes with TGF-?(2) and H(2)O(2) upregulated the expression of ?B-crystallin, Hsp27, fibronectin and CTGF. Pretreatment with different concentrations of LA reduced the TGF-?(2)- and H(2)O(2)-stimulated gene expressions. Conclusion: We showed that TGF-?(2)- and H(2)O(2)-stimulated gene expressions could be prevented by pretreatment with the antioxidant LA in cultured human ONH astrocytes. Therefore, it is tempting to speculate that the use of antioxidants could have protective effects in glaucomatous optic neuropathy.
EVALuna2:21103

The accessory heads of the quadriceps femoris muscle may affect the layering of the quadriceps tendon and potential graft harvest lengths - Olewnik, Łukasz; Zielinska, Nicol; Aragones, Paloma; Ruzik, Kacper; Paulsen, Friedrich; Borowski, Andrzej; LaPrade, Robert F. (Knee Surgery Sports Traumatology Arthroscopy, 2023)
Purpose: The aim of the study was to assess the quadriceps femoris system for the presence of additional layers. Methods: One hundred and twenty-eight lower limbs fixed in 10% formalin were examined. Results: Five types of quadriceps tendon layering were found based on the accessory heads of the quadriceps muscle. Type I (55%)—represented by four heads and four layers, and it was something new because standard orthopaedic textbooks described quadriceps tendon as a structure composed of only three layers. Type II (27.4%)—the first four layers were the same as in Type 1, but the accessory tendon of the fifth head of the quadriceps femoris muscle had the deepest attachments. Type III (10.9%)—this type included 6 heads of quadriceps femoris. It consisted of five layers. Type IV (3.1%)—this type included 7 quadriceps femoris heads. This type consisted of only four layers. Type V (3.1%)—this type included 8 heads of the quadriceps femoris heads. This type consist of 5 layers. Conclusion: The findings of this study provide a detailed anatomy of the quadriceps tendon including the accessory tendons of the accessory heads of the quadriceps tendon. The accessory heads of the quadriceps femoris muscle contribute to the layering of the quadriceps tendon. The second conclusion of this study is the development of safe distances depending on the types. Not all types are perfect for harvesting—Type IV seems to be the safest type, in turn Type V the most dangerous.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Accessory heads; Harvest; Quadriceps femoris; Quadriceps tendon; Sport; Surgery

The anatomy of the anterolateral structures of the knee — A histologic and macroscopic approach - Brockmeyer, Matthias; Orth, Patrick; Höfer, Denis; Seil, Romain; Paulsen, Friedrich; Menger, Michael D.; Kohn, Dieter; Tschernig, Thomas (Knee, 2019)
Background: The anatomy of the anterolateral structures of the knee is complex and still controversial. The aim of our study was to analyze this anatomy by histologic and macroscopic evaluation, with a particular emphasis on the anterolateral ligament (ALL). Material and methods: Twenty-three cadaveric knee joints were dissected followed by a qualitative and quantitative anatomic analysis of the anterolateral knee structures. Histology and comparison of different anterolateral structures was performed in addition. Results: The ALL was identified in all of the dissected cadaveric knee specimens. It runs in an oblique course from its proximo-dorsal insertion at the distal femur into a ventro-distal direction to the anterolateral tibia. The femoral insertion site was found to be posterior and slightly proximal to the lateral femoral epicondyle and the femoral attachment of the lateral collateral ligament (LCL). The femoral insertion of the ALL overlapped the LCL in all dissected knees. The tibial insertion site was midway between Gerdy's tubercle (GT) and the tip of the fibular head (FH). In 15 of the dissected 23 knee joints, thin attachments to the lateral meniscus were observed. Histology confirmed differences in the composition of the anterolateral knee joint capsule, the ALL and the iliotibial band (ITB). Conclusions: The ALL occurs as a regular separate anterolateral ligamentous structure. It is distinguishable from the ITB and the anterolateral joint capsule in both embalmed and non-embalmed specimens. Histology of the ALL indicates typical ligamentous tissue which clearly differs from the anterolateral knee joint capsule and the thicker ITB. Level of evidence: Level II, descriptive anatomic study.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Anatomy; Anterior cruciate ligament (ACL); Anterolateral instability; Anterolateral knee structures; Anterolateral ligament (ALL); Histology

The anterolateral ligament (ALL) of the knee-Part of the iliotibial tract or a truly separate structure? - Brockmeyer, Matthias; Hoefer, Denis; Schaefer, Katja; Seil, Romain; Becker, Kurt; Paulsen, Friedrich; Kohn, Dieter; Tschernig, Thomas (Annals of Anatomy-Anatomischer Anzeiger, 2017)
In this Short Communication, the issue is discussed whether the recently reported anterolateral ligament of the knee is a unique structure or just part of the iliotibial tract. The presented findings from investigations in body donors support the view of a unique structure.
EVALuna2:35339

The Attitudes of European Medical Students towards the Clinical Importance of Neuroanatomy - Moxham, Bernard John; Brenner, Erich; Plaisant, Odile; Pais, Diogo; Stabile, Isabel; Scholz, Michael; Paulsen, Friedrich; Bueno-Lopez, Jose Luis; Reblet, Concepcion; Arraez-Aybar, Luis-Alfonso; Sotgiu, Maria Alessandra; Arsic, Stojanka; et al. (Annals of Anatomy-Anatomischer Anzeiger, 2022)
The attitudes of medical students towards the clinical importance of neuroanatomy have been little studied. Because it has been reported that medical students find neuroanatomy difficult and can have 'neurophobia', here we test the hypothesis that early-stage medical students across Europe have a low regard for neuroanatomy's clinical relevance. The work was conducted under the auspices of the Trans-European Pedagogic Research Group (TEPARG), with just over 1,500 students from 12 European medical schools providing responses to a survey (52% response rate) that assessed their attitudes using Thurstone and Chave methodologies. Regardless of the university surveyed, and of the teaching methods employed for neuroanatomy, our findings were not consistent with our hypothesis. However, the students had a less favourable opinion of neuroanatomy's importance compared to gross anatomy; although their attitudes were more positive than previously reported for histology and embryology. The extent to which neuroanatomy plays a significant role in the early years of medical education is moot. Nevertheless, we conclude that in addition to newly recruited medical students being informed of the subject's role in a healthcare profession, we advocate the use of modern imaging technologies to enhance student understanding and motivation and cognisance of the core syllabus for the subject being developed by the International Federation of Associations of Anatomists (IFAA).
CRIS-Team WoS Importer:2021-10-29

The attitudes of medical students in Europe toward the clinical importance of histology - Moxham, Bernard John; Emmanouil-Nikoloussi, Elpida; Brenner, Erich; Plaisant, Odile; Brichova, Hana; Kucera, Tomas; Pais, Diogo; Stabile, Isobel; Borg, Jordy; Scholz, Michael; Paulsen, Friedrich; Luis Bueno-Lopez, Jose; et al. (Clinical Anatomy, 2017)
Many studies have been undertaken to assess the attitudes of medical students to the clinical importance of gross anatomy. However, much less is known about their attitudes toward the clinical importance of histology. Using Thurstone and Chave methods to assess attitudes, over 2,000 early stage medical students across Europe provided responses to a survey that tested the hypothesis that the students have a high regard for histology's clinical relevance. Regardless of the university and country surveyed, and of the teaching methods employed for histology, our findings were not consistent with our hypotheses, students providing a more moderate assessment of histology's importance compared to gross anatomy but more positive than their attitudes toward embryology. Histology should play a significant role in medical education in terms of appreciating not just normal structure and function but also pathology. We conclude that teachers of histology should pay special attention to informing newly-recruited medical students of the significant role played by histology in attaining clinical competence and in underpinning their status as being learned members of a healthcare profession. This work was conducted under the auspices of the Trans-European Pedagogic Research Group (TEPARG). Clin. Anat. 30:635-643, 2017. © 2017 Wiley Periodicals, Inc.
EVALuna2:35330

The autonomic facial nerve pathway in birds: A tracing study in chickens - Schrödl, Falk; Brehmer, Axel; Neuhuber, Winfried; Nickla, Debora (Investigative Ophthalmology & Visual Science, 2006)
PURPOSE. In birds, the parasympathetic innervation of the choroid is via the ciliary (cranial nerve III) and pterygopalatine (cranial nerve VII) ganglia, the latter consisting of a chain of microganglia within the orbit. Because of the scattered nature of these microganglia, lesions of this nerve pathway in birds have not been attempted, making interpretation of the functional contribution of this parasympathetic input to the avian eye uncertain. The purpose of this study was to find an extraorbital approach to the preganglionic part of cranial nerve VII and to reveal its peripheral terminals and its site of origin in the brain stem. METHODS. The radix autonomica cranial nerve VII was accessed via the tympanic cavity and injected with dextran coupled to Texas red (DTxR). Orbital structures and the brain stem were prepared for tracer detection and immunohistochemistry for neuronal nitric oxide synthase (nNOS), choline acetyl transferase (ChAT), vasoactive intestinal polypeptide (VIP), calcitonin gene-related peptide (CGRP), galanin (GAL), and somatostatin (SOM). For documentation, fluorescence and confocal laser scanning microscopy were used. RESULTS. Anterogradely labeled DTxR-positive nerve fibers were detected within the orbital pterygopalatine microganglionic chain, forming boutons closely associated with nNOS-positive neurons. Retrogradely labeled DTxR-positive neurons with cell diameters of approximately 20 μm were found in the brain stem. These were positive for ChAT, but negative for nNOS, VIP, SOM, GAL, and CGRP. They most likely represent the preganglionic neurons of the superior salivatory nucleus. In close proximity, there were larger (40 μm) unlabeled neurons that were positive for ChAT and CGRP, but negative for GAL. These most likely represent motoneurons of the facial nerve. CONCLUSIONS. This surgical approach offers excellent opportunities for lesioning experiments for the study of the autonomic facial nerve pathway in birds in terms of both its anatomic organization and its function. Copyright © Association for Research in Vision and Ophthalmology.

The beta(4)-Subunit of the Large-Conductance Potassium Ion Channel K(Ca)1.1 Regulates Outflow Facility in Mice - Bertrand, Jacques A.; Schicht, Martin; Stamer, W. Daniel; Baker, David; Sherwood, Joseph M.; Luetjen-Drecoll, Elke; Selwood, David L.; Overby, Darryl R. (Investigative Ophthalmology & Visual Science, 2020)
PURPOSE. The large-conductance calcium-activated potassium channel K(Ca)1.1 (BKCa, maxi-K) influences aqueous humor outflow facility, but the contribution of auxiliary beta-subunits to K(Ca)1.1 activity in the outflow pathway is unknown.
CRIS-Team WoS Importer:2020-04-21

The Cerebral Surfactant System and Its Alteration in Hydrocephalic Conditions - Schob, Stefan; Lobsien, Donald; Friedrich, Benjamin; Bernhard, Matthias K.; Gebauer, Corinna; Dieckow, Julia; Gawlitza, Matthias; Pirlich, Mandy; Saur, Dorothee; Bräuer, Lars; Bechmann, Ingo; Hoffmann, Karl-Titus; et al. (PLoS ONE, 2016)
INTRODUCTION: Pulmonary Surfactant reduces surface tension in the terminal airways thus facilitating breathing and contributes to host's innate immunity. Surfactant Proteins (SP) A, B, C and D were recently identified as inherent proteins of the CNS. Aim of the study was to investigate cerebrospinal fluid (CSF) SP levels in hydrocephalus patients compared to normal subjects. PATIENTS AND METHODS: CSF SP A-D levels were quantified using commercially available ELISA kits in 126 patients (0-84 years, mean 39 years). 60 patients without CNS pathologies served as a control group. Hydrocephalus patients were separated in aqueductal stenosis (AQS, n = 24), acute hydrocephalus without aqueductal stenosis (acute HC w/o AQS, n = 16) and idiopathic normal pressure hydrocephalus (NPH, n = 20). Furthermore, six patients with pseudotumor cerebri were investigated. RESULTS: SP A-D are present under physiological conditions in human CSF. SP-A is elevated in diseases accompanied by ventricular enlargement (AQS, acute HC w/o AQS) in a significant manner (0.67, 1.21 vs 0.38 ng/ml in control, p<0.001). SP-C is also elevated in hydrocephalic conditions (AQS, acute HC w/o AQS; 0.87, 1.71 vs. 0.48 ng/ml in controls, p<0.001) and in Pseudotumor cerebri (1.26 vs. 0.48 ng/ml in controls, p<0.01). SP-B and SP-D did not show significant alterations. CONCLUSION: The present study confirms the presence of SPs in human CSF. There are significant changes of SP-A and SP-C levels in diseases affecting brain water circulation and elevation of intracranial pressure. Cause of the alterations, underlying regulatory mechanisms, as well as diagnostic and therapeutic consequences of cerebral SP's requires further thorough investigations.
EVALuna2:34490

The chemicals between us—First results of the cluster analyses on anatomy embalming procedures in the German-speaking countries - Kerner, Alexander Michael; Biedermann, Uta; Bräuer, Lars; Caspers, Svenja; Doll, Sara; Engelhardt, Maren; Filler, Timm J.; Ghebremedhin, Estifanos; Gundlach, Stefanie; Hayn-Leichsenring, Gregor U.; Heermann, Stephan; Hettwer-Steeger, Ingrid; et al. (Anatomical Sciences Education, 2023)
Hands-on courses utilizing preserved human tissues for educational training offer an important pathway to acquire basic anatomical knowledge. Owing to the reevaluation of formaldehyde limits by the European Commission, a joint approach was chosen by the German-speaking anatomies in Europe (Germany, Austria, Switzerland) to find commonalities among embalming protocols and infrastructure. A survey comprising 537 items was circulated to all anatomies in German-speaking Europe. Clusters were established for “ethanol”-, formaldehyde-based (“FA”), and “other” embalming procedures, depending on the chemicals considered the most relevant for each protocol. The logistical framework, volumes of chemicals, and infrastructure were found to be highly diverse between the groups and protocols. Formaldehyde quantities deployed per annum were three-fold higher in the “FA” (223 L/a) compared to the “ethanol” (71.0 L/a) group, but not for “other” (97.8 L/a), though the volumes injected per body were similar. “FA” was strongly related to table-borne air ventilation and total fixative volumes ≤1000 L. “Ethanol” was strongly related to total fixative volumes >1000 L, ceiling- and floor-borne air ventilation, and explosion-proof facilities. Air ventilation was found to be installed symmetrically in the mortuary and dissection facilities. Certain predictors exist for the interplay between the embalming used in a given infrastructure and technical measures. The here-established cluster analysis may serve as decision supportive tool when considering altering embalming protocols or establishing joint protocols between institutions, following a best practice approach to cater toward best-suited tissue characteristics for educational purposes, while simultaneously addressing future demands on exposure limits.
CRIS-Team Scopus Importer:2023-05-26
Keywords: body donor; cadaver; conservation; embalming; fixation; formaldehyde; human tissue; occupational exposure limit the value

The communication between ocular surface and nasal epithelia in 3d cell culture technology for translational research: A narrative review - Aydin, Malik; Dietrich, Jana; Witt, Joana; Finkbeiner, Maximiliane S.C.; Park, Jonas J.H.; Wirth, Stefan; Engeland, Christine E.; Paulsen, Friedrich; Ehrhardt, Anja (International Journal of Molecular Sciences, 2021)
There is a lack of knowledge regarding the connection between the ocular and nasal epithelia. This narrative review focuses on conjunctival, corneal, ultrastructural corneal stroma, and nasal epithelia as well as an introduction into their interconnections. We describe in detail the morphology and physiology of the ocular surface, the nasolacrimal ducts, and the nasal cavity. This knowledge provides a basis for functional studies and the development of relevant cell culture models that can be used to investigate the pathogenesis of diseases related to these complex structures. Moreover, we also provide a state‐of‐the‐art overview regarding the development of 3D culture models, which allow for addressing research questions in models resembling the in vivo situation. In particular, we give an overview of the current developments of corneal 3D and organoid models, as well as 3D cell culture models of epithelia with goblet cells (conjunctiva and nasal cavity). The benefits and shortcomings of these cell culture models are discussed. As examples for pathogens related to ocular and nasal epithelia, we discuss infections caused by adenovirus and measles virus. In addition to pathogens, also external triggers such as allergens can cause rhinoconjunctivitis. These diseases exemplify the interconnections between the ocular surface and nasal epithelia in a molecular and clinical context. With a final translational section on optical coherence tomography (OCT), we provide an overview about the applicability of this technique in basic research and clinical ophthalmology. The techniques presented herein will be instrumental in further elucidating the functional interrelations and crosstalk between ocular and nasal epithelia.
CRIS-Team Scopus Importer:2021-12-10
Keywords: 3D cell culture; Goblet cells; Infection; Nasal epithelium; Ocular surface epithelium

The comparison of the morphology of the mid-palatal suture between edentulous individuals and dentate jaws shows morphological differences - Willershausen, Ines; Krautkremer, Franziska; Hilbert, Tobias; Seidel, Corinna Lesley; Geppert, Carol-Immanuel; Ghanaati, Shahram; Necker, Fabian; Paulsen, Friedrich; Gölz, Lina; Scholz, Michael (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Background: A profound understanding of the evolution and anatomy of the viscero- and neurocranium is quintessentially important for orthodontists. This particularly alludes to structures, which are directly targeted by orthodontic therapy such as the maxilla and the mid-palatal suture. The anatomy of the mid-palatal suture of toothed individuals is well described, whereas little is known about sutures’ morphological changes after tooth loss. Therefore, the aim of this study was to evaluate the edentulous mid-palatal suture by means of histologic and histomorphometric analysis. Methods: Ten mid-palatal sutures of edentulous donors as well as six age- and sex matched dentulous controls were examined. For the histological and histomorphometric analysis (sutural width, obliteration, vascularization and interdigitation) conventional staining protocols (HE, Movat-Pentachrome, Sirius Red) and immunofluorescence (vWF, TRAP) were performed. Histomorphometric analysis was carried out using NIS-elements imaging software. Results: When compared to dentulous controls, the edentulous investigation group showed a decreased vascularization and sutural width as well as an increased sutural obliteration. Notably, a high variability and inhomogeneity within regard the histomorphometric parameters was seen in edentulous samples. Conclusions: The mid-palatal suture of edentulous individuals showed significant morphological differences compared to individuals with toothed jaws. The loss of teeth and thereby functional loading seems to have a considerable impact on sutures’ morphology.
CRIS-Team Scopus Importer:2022-06-17
Keywords: Atrophy; Edentulous jaw; Histomorphometry; Mid-palatal suture

The Detection of Surfactant Proteins A, B, C and D in the Human Brain and Their Regulation in Cerebral Infarction, Autoimmune Conditions and Infections of the CNS - Schob, Stefan; Schicht, Martin; Sel, Saadettin; Stiller, Dankwart; Kekule, Alexander; Paulsen, Friedrich; Maronde, Erik; Bräuer, Lars (PLoS ONE, 2013)
Surfactant proteins (SP) have been studied intensively in the respiratory system. Surfactant protein A and surfactant protein D are proteins belonging to the family of collectins each playing a major role in the innate immune system. The ability of surfactant protein A and surfactant protein D to bind various pathogens and facilitate their elimination has been described in a vast number of studies. Surfactant proteins are very important in modulating the host's inflammatory response and participate in the clearance of apoptotic cells. Surfactant protein B and surfactant protein C are proteins responsible for lowering the surface tension in the lungs. The aim of this study was an investigation of expression of surfactant proteins in the central nervous system to assess their specific distribution patterns. The second aim was to quantify surfactant proteins in cerebrospinal fluid of healthy subjects compared to patients suffering from different neuropathologies. The expression of mRNA for the surfactant proteins was analyzed with RT-PCR done with samples from different parts of the human brain. The production of the surfactant proteins in the brain was verified using immunohistochemistry and Western blot. The concentrations of the surfactant proteins in cerebrospinal fluid from healthy subjects and patients suffering from neuropathologic conditions were quantified using ELISA. Our results revealed that surfactant proteins are present in the central nervous system and that the concentrations of one or more surfactant proteins in healthy subjects differed significantly from those of patients affected by central autoimmune processes, CNS infections or cerebral infarction. Based on the localization of the surfactant proteins in the brain, their different levels in normal versus pathologic samples of cerebrospinal fluid and their well-known functions in the lungs, it appears that the surfactant proteins may play roles in host defense of the brain, facilitation of cerebrospinal fluid secretion and maintenance of the latter's rheological properties. © 2013 Schob et al.
CRIS-Team Scopus Importer:2022-08-05

The distribution of conjunctival goblet cells in mice - Welss, Jessica; Punchago, Nichapa; Feldt, Jessica; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Purpose: To evaluate the density and distribution of conjunctival goblet cells in mice without clinical evidence of ocular surface diseases. Methods: Immediately after euthanasia of C57BL/6 wild-type mice, the eyes including eyelids were removed and fixed in paraformaldehyde. Entire eyeballs and eyelids were cut in series along the sagittal axis from nasal to temporal on a microtome and then stained with Periodic Acid-Schiff acid to visualize the goblet cells. At each section stained in this way, the conjunctival goblet cells of the entire upper and lower lid conjunctiva were counted by light microscopy. Additional (transmission electron microscopy) (TEM)-Analysis on ultrathin sections was performed to evaluate morphological differences. Results: The total number of conjunctival goblet cells differs markedly between individual animals. Categorisation into upper eyelid (UL) and lower eyelid (LL) and into regions (nasal, middle, temporal) revealed a significant increase of goblet cells from nasal to temporal in the UL and a significant decrease in the LL. Conclusion: The distribution of conjunctival goblet cells in mice differs considerably from humans and between individual animals. Therefore, precise selection of sampling and methods are needed to obtain comparable data. We recommend to use the middle region of the conjunctiva of UL/LL for goblet cell studies in mice. These findings are of particular interest for dry eye mouse models as well as pharmacological studies on mice with influence on their goblet cells.
CRIS-Team Scopus Importer:2021-01-22
Keywords: conjunctiva; Dry eye mouse model; Goblet cell; Lacrimal apparatus; Mucin; Ocular surface

The distribution of human surfactant proteins within the oral cavity and their role during infectious diseases of the gingiva - Schicht, Martin; Stengl, Christina; Sel, Sadettin; Heinemann, Friedhelm; Goetz, Werner; Petschelt, Anselm; Pelka, Matthias; Scholz, Michael; Rausch, Felix; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2015)
The oral cavity with the teeth and the surrounding gingival epithelium, the periodontium, the salivary glands and other structures are open to the oral environment and thus exposed to multiple microbiological and pathogenic influences. To prevent permanent inflammatory processes such as gingivitis or periodontitis an efficient defense system is essential to ensure healthy and physiological function of the oral cavity and other interacting organic systems. Surfactant proteins (SPs), originally found in pulmonary tissue are important factors of the immune system and beyond this, support the stability and rheology of gas or fluid interfaces. This study aimed to analyze the distribution of surfactant proteins by means of Western blot and immunohistochemistry in salivary glands as well as in healthy and pathological saliva. The different expression patterns of SP-A, -B, -C and -D in healthy and pathological (periodontitis) saliva were determined using ELISA quantification. One further objective of the study was the first detection of two recent discovered proteins belonging to the surfactant protein family within human salivary glands and saliva. The results of the study reveal differences in protein expression of SP-A, -B, -C and -D within healthy and pathologic saliva. The concentration of the surfactant proteins SP-A, SP-C and SP-D is increased in saliva of people suffering from periodontal diseases, whereas by contrast, SP-B shows an opposite expression pattern. Furthermore, the results evidence the presence of SP-G and SP-H within saliva and salivary glands for the first time.
EVALuna2:4399

The Effect of Androgens on Proinflammatory Cytokine Secretion from Human Ocular Surface Epithelial Cells - Marangoz, Deniz; Oner, Cagri; Schicht, Martin; Turgut Cosan, Didem; Paulsen, Friedrich; Yildiz, Erdost; Zibandeh, Noushin; Sahin, Afsun (Ocular Immunology and Inflammation, 2019)
Purpose: The purpose of this study is to explore the effects of dihydrotestosterone (DHT) on lipopolysaccharide (LPS)-induced proinflammatory cytokine release in human ocular surface epithelial cells exposed to LPS and LPS-binding protein (LBP). Methods: Immortalized human corneal, conjunctival, and meibomian gland epithelial cells were cultured in keratinocyte-free medium. After confluency, they were exposed to a stratification medium Dulbecco's modified Eagle medium (DMEM)/F12 in the presence of fetal bovine serum and were exposed to vehicle, LPS + LBP, or DHT. Culture media were processed for multiplex-bead analysis of specific proinflammatory cytokines including interferon (IFN)-γ, tumor necrosis factor (TNF)-α, interleukin (IL)-2, IL-4, IL-8, IL-6, IL-10, IL-1β, vascular endothelial growth factor (VEGF)-A. Cytokine concentrations were compared by analysis of variance with Tukey post hoc testing. p < 0.05 was considered statistically significant. Results: The results are LPS + LBP-induced the secretion of IFN-γ, IL-6, IL-10, IL-1β, VEGF-A cytokines in corneal epithelial cells; TNF-α, IL-2, IL-8, IL-6, IL-1β, VEGF-A cytokines in conjunctival epithelial cells; and IL-8, IL-6, IL-1β, VEGF-A cytokines in meibomian gland epithelial cells. When these LPS + LBP-stimulated cells were exposed to DHT for 2 days, it was found that DHT suppressed the secretion of IL-6, IL-10, IL-1β, VEGF-A cytokines in corneal epithelial cells; TNF-α, IL-6, IL-1β, VEGF-A cytokines in conjunctival epithelial cells; and IL-6, IL-1β, VEGF-A cytokines in meibomian gland epithelial cells. Conclusion: LPS + LBP is shown to induce the secretion of certain proinflammatory cytokines from ocular surface and adnexal epithelial cells. DHT showed anti-inflammatory activity by suppressing some of those cytokines in these cell lines.
CRIS-Team Scopus Importer:2019-11-26
Keywords: cell culture; Dihydrotestosterone; lipopolysaccharide; ocular surface epithelium; proinflammatory cytokine

The enteric nervous system is a potential autoimmune target in multiple sclerosis - Wunsch, Marie; Jabari, Samir; Voussen, Barbara; Enders, Michael; Srinivasan, Shanthi; Cossais, Francois; Wedel, Thilo; Boettner, Martina; Schwarz, Anna; Weyer, Linda; Goecer, Oktay; Schroeter, Michael; et al. (Acta Neuropathologica, 2017)
Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS) in young adults that has serious negative socioeconomic effects. In addition to symptoms caused by CNS pathology, the majority of MS patients frequently exhibit gastrointestinal dysfunction, which was previously either explained by the presence of spinal cord lesions or not directly linked to the autoimmune etiology of the disease. Here, we studied the enteric nervous system (ENS) in a B cell- and antibody-dependent mouse model of MS by immunohistochemistry and electron microscopy at different stages of the disease. ENS degeneration was evident prior to the development of CNS lesions and the onset of neurological deficits in mice. The pathology was antibody mediated and caused a significant decrease in gastrointestinal motility, which was associated with ENS gliosis and neuronal loss. We identified autoantibodies against four potential target antigens derived from enteric glia and/or neurons by immunoprecipitation and mass spectrometry. Antibodies against three of the target antigens were also present in the plasma of MS patients as confirmed by ELISA. The analysis of human colon resectates provided evidence of gliosis and ENS degeneration in MS patients compared to non-MS controls. For the first time, this study establishes a pathomechanistic link between the well-established autoimmune attack on the CNS and ENS pathology in MS, which might provide a paradigm shift in our current understanding of the immunopathogenesis of the disease with broad diagnostic and therapeutic implications.
EVALuna2:35218

The environmental needs of clinician-scientists in ophthalmology - Ali, Mohammad Javed; Paulsen, Friedrich (Saudi Journal of Ophthalmology, 2017)
CRIS-Team Scopus Importer:2022-08-05

The human meibomian gland epithelial cell line as a model to study meibomian gland dysfunction - Hampel, Ulrike; Garreis, Fabian (Experimental Eye Research, 2017)
The meibomian gland dysfunction (MGD) is the leading cause of dry eye disease (DED) throughout the world. The investigation of MGD lacks suitable in vivo and in vitro models. In 2010 a human meibomian gland epithelial cell line (HMGEC) was established, so far the only available meibomian gland cell line. The characterization of HMGEC is of major importance to clarify its suitability for studying the meibomian gland (patho)physiology in vitro. The current culture protocol and new concepts of HMGEC culture will be compared. Hormones are believed to be a key factor in meibomian gland dysfunction thus HMGEC responsiveness to hormone stimulation is crucial to elucidate the hormonal influence on the meibomian gland. This review will summarize current findings about HMGEC and discuss its role in the meibomian gland dysfunction research.
EVALuna2:35327

The impact of different cone beam computed tomography and multi-slice computed tomography scan parameters on virtual three-dimensional model accuracy using a highly precise ex vivo evaluation method - Matta, Ragai-Edward; von Wilmowsky, Cornelius; Neuhuber, Winfried; Lell, Michael; Neukam, Friedrich Wilhelm; Adler, Werner; Wichmann, Manfred; Bergauer, Bastian (Journal of Cranio-Maxillofacial Surgery, 2016)
Multi-slice computed tomography (MSCT) and cone beam computed tomography (CBCT) are indispensable imaging techniques in advanced medicine. The possibility of creating virtual and corporal three-dimensional (3D) models enables detailed planning in craniofacial and oral surgery. The objective of this study was to evaluate the impact of different scan protocols for CBCT and MSCT on virtual 3D model accuracy using a software-based evaluation method that excludes human measurement errors.MSCT and CBCT scans with different manufacturers' predefined scan protocols were obtained from a human lower jaw and were superimposed with a master model generated by an optical scan of an industrial noncontact scanner. To determine the accuracy, the mean and standard deviations were calculated, and t-tests were used for comparisons between the different settings.Averaged over 10 repeated X-ray scans per method and 19 measurement points per scan (n = 190), it was found that the MSCT scan protocol 140 kV delivered the most accurate virtual 3D model, with a mean deviation of 0.106 mm compared to the master model. Only the CBCT scans with 0.2-voxel resolution delivered a similar accurate 3D model (mean deviation 0.119 mm).Within the limitations of this study, it was demonstrated that the accuracy of a 3D model of the lower jaw depends on the protocol used for MSCT and CBCT scans.
EVALuna2:5540

The importance of surfactant proteins-New aspects on macrophage phagocytosis - Tschernig, Thomas; Veith, Nils T.; Diler, Ebru; Bischoff, Markus; Meier, Carola; Schicht, Martin (Annals of Anatomy-Anatomischer Anzeiger, 2016)
Surfactant and its components have multiple functions. The so called collectins are surfactant proteins which opsonize bacteria and improve pulmonary host defense via the phagocytosis and clearance of microorganisms and particles. In this special issue of the Annals of Anatomy a new surfactant protein, Surfactant Associated 3, is highlighted. As outlined in this mini review Surfactant Associated 3 is regarded as an enhancer of phagocytosis. In addition, the role played by SP-A is updated and open research questions raised.
EVALuna2:35351

The influence of a modified blood supply on craniofacial growth in the rabbit. 1. Vascular casts - Brehmer, Axel; Beleites, Bernhard (Anatomischer Anzeiger, 1989)
This series describes changes in the arteries of the head and neck and the growth of the muscles of mastication, the skull and lower jaw after unilateral ligation of the common carotid artery. 1st Report: Kallocryl casts of the arterial system of the head and neck in rabbits aged about 8 months were made. The casts from ligated animals were compared with those from control animals. The description deals with the arrangement and number of anastomoses.

The influence of a modified blood supply on craniofacial growth in the rabbit. 3. Skull and lower jaw: General development in size - Brehmer, Axel; Beleites, Bernhard (Anatomischer Anzeiger, 1989)
This report deals with the growth of the skull and lower jaw after unilateral ligation on the common carotid artery in juvenile rabbits. No differences that could be attributed to the operation were found between the animals with ligated carotids and the control animals.

The influence of a modified blood supply on craniofacial growth in the rabbit. 4. Skull and lower jaw: Asymmetry - Beleites, Bernhard; Brehmer, Axel (Anatomischer Anzeiger, 1989)
Using a microscopic measuring method we wee able to detect minor regions of asymmetry in the zygomatic arches of rabbits in which the common carotid artery had been ligated. These are considered in connection with the (also slight) asymmetric gains in the dry weight of the muscles of mastication in the ligated animals (see 2nd Bulletin).

The influence of modified blood supply on craniofacial growth in the rabbit. 2. Muscles of mastication - Beleites, Bernhard; Brehmer, Axel (Anatomischer Anzeiger, 1989)
After ligation of the right common carotid artery, the dry weight of the muscles of mastication on the ligated side did not differ from that of the control animals between the 45th and 225th d of life. On the opposite side, however, the muscles were in some cases significantly heavier than those of the control animals, particularly in male rabbits with ligated common carotid arteries. The methodical application of these results is proposed.

The large intestine from fetal period to adulthood and its impact on the course of colonoscopy - Wozniak, Slawomir; Pytrus, Tomasz; Kobierzycki, Christopher; Grabowski, Krzysztof; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2019)
The human large intestine in the living adult has a total length of about 1300 mm, ranging from 1100 to 2108 mm. The development of the gut continues after birth, up to the age 4–5. The large intestine ascends at the beginning in the right abdominal quadrant, then it traverses the abdominal cavity, and finally it descends to the anus. The left and right colic flexures are the basic flexions between the transverse, ascending and descending colon, respectively. Additionally, there are secondary bendings between intestinal segments. The angles between the neighbouring parts can vary between examined subjects. Most of the angulations can be found in the transverse (range 2–9) and sigmoid colon (range 1–9), making them the most troublesome parts to pass with a colonoscope. Colonoscopy (usually performed in the left lateral or supine position) is one of the most important examination of the large intestine mucus membrane. During this procedure the endoscope is passed through the colon into the cecum or terminal ilium. The individual anatomical features (tortuosity, supernumerary loops and elongation) may slow down or interfere with the progress of the scope. We summarize current knowledge on the human large intestine from the fetal period to adulthood and carve out some aspects that are currently less known to colonoscopists.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Colon morphology; Colonoscopy; Human large intestine

The learning type makes the difference - the interrelation of Kolb's learning styles and psychological status of preclinical medical students at the University of Erlangen - Burger, Pascal H.; Scholz, Michael (GMS Zeitschrift für Medizinische Ausbildung, 2014)
Theories on learning styles and types have been integral to discussions on the basics of teaching for nearly 40 years. The learning style typology of Kolb divides learners into four groups (Diverger, Assimilator, Converger and Accomodator), which differ both in terms of their learning behaviour as well as personality and preferences. We studied the sense of coherence and burnout symptoms in medical students of the preclinical semesters (1(st) to 4(th) semester) at the Friedrich-Alexander University of Erlangen within the context of the observed learning styles. A total of 530 students were interviewed in winter semester 2012/13 using standardized psychometric questionnaires. Our students showed a significant correlation between the respective learning styles and expression of a sense of coherence, as well as cognitive and emotional burnout symptoms. The learning styles of the students differed significantly within these same parameters. We also demonstrated that learning styles and types not only influence study performance, but that there are also relationships to sense of coherence and psychological ailments. A more forward-looking integration of the theory of learning types in the medical education curriculum could positively influence both the performance and psychological well-being of the students.
EVALuna2:4433

The legal and ethical framework governing Body Donation in Europe - 1st update on current practice - Riederer, Beat M.; Bolt, S.; Brenner, Eric; Bueno-López, José L.; Circulescu, A. R.M.; Davies, D. C.; De Caro, Raffaele; Gerrits, P. O.; McHanwell, Stephen; Pais, Diogo; Paulsen, Friedrich; Plaisant, Odile; et al. (European Journal of Anatomy, 2012)
Previously, we have reported on the legal and ethical aspects and current practice of body donation in several European countries, reflecting cultural and religious variations as well as different legal and constitutional frameworks. We have also established good practice in body donation. Here we shall further extend the legal and ethical frameworks in place and also focus on novelties in the law and different directives. Of particular interest are points that address the commercialization of human bodies and body parts and weaknesses in the legal directives. Therefore, it is important to define what is ethical and what needs to be considered unethical in body donation and the subsequent utilisation of human bodies for teaching and research.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Body donation; European community; Legal and ethical aspects

The legal and ethical framework governing body donation in Europe – 2nd update on current practice - Brenner, Erich; Bleys, Ronald L.A.W.; de Caro, Raffaele; Catereniuc, Ilia; Chirculescu, Andy R.M.; Destrieux, Christophe; Eppler, Elisabeth; Filgueira, Luis; Kachlik, David; Kiss, Péter; Lee, Clive; Matveeva, Niki; et al. (Annals of Anatomy-Anatomischer Anzeiger, 2024)
Background: In 2008, members of the TEPARG provided first insights into the legal and ethical framework governing body donation in Europe. In 2012, a first update followed. This paper is now the second update on this topic and tries to extend the available information to many more European countries. Methods: For this second update, we have asked authors from all European countries to contribute their national perspectives. By this enquiry, we got many contributions compiled in this paper. When we did not get a personal contribution, one of us (EB) searched the internet for relevant information. Results: Perspectives on the legal and ethical framework governing body donation in Europe. Conclusions: We still see that a clear and rigorous legal framework is still unavailable in several countries. We found national regulations in 18 out of 39 countries; two others have at least federal laws. Several countries accept not only donated bodies but also utilise unclaimed bodies. These findings can guide policymakers in reviewing and updating existing laws and regulations related to body donation and anatomical studies.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Anatomical research; Body donation; Body procurement; Teaching of anatomy

The morphological variability of fibularis tertius origin in human foetuses - Ruzik, K.; Westrych, K.; Zielinska, N.; Podgórski, M.; Karauda, P.; Diogo, R.; Paulsen, Friedrich; Polguj, M.; Olewnik, (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Background: The purpose of this study was to characterize the morphology of the fibularis tertius (FT) in human fetuses, and to provide a classification based on its modes of origin in human fetuses. Methods: The material comprised 100extremities from 50 spontaneously aborted human fetuses (19 male, 31 female, 100 lowerlimbs in total), aged 18–38 weeks of gestation. These were dissected and the presence or absence of the FT muscle as well as the type of its proximal attachment were determined, and the FT was measured morphometrically. Results: The FT was present in 50% of fetuses. Four types of FT muscle origin were identified. The most common was Type 2, characterized by an origin on the middle third of the fibula and the intermuscular septum. Three other types were observed: Type 1 with an origin located on proximal third of the fibula and to the intermuscular septum, Type 3 characterized by an absent muscle belly, and an independent tendon originating from the that of the extensor digitorum longus, and Type 4 with an origin located on the distal third of the fibula and the intermuscular septum. Conclusions: The fibularis tertius demonstrates high morphological variability, with the most common origin located on third of the fibula and to the intermuscular septum.
CRIS-Team Scopus Importer:2022-04-08
Keywords: Anatomical variations; Development; Fibularis tertius; Fibularis tertius origin; Foetuses; New classification; Variations

The morphology of the circulus arteriosus cerebri of the rabbit and its changes following unilateral ligation of the common carotid artery - Brehmer, Axel; Beleites, Bernhard (Anatomischer Anzeiger, 1988)
Kallocryl casts showed in all cases that the circulus arteriosus is closed in the rabbit. This refutes claims to the contrary in the literature. Attention is drawn to contradictions in the nomenclature denoting the parts of the circulus. According to our observations, in the rabbit only the caudal part of the circulus, mainly the caudal communicans artery, is implicated in the compensation of unilateral ligature of the common carotid artery.

The mystery behind the nostrils – technical clues for successful nasal epithelial cell cultivation - Aydin, Malik; Naumova, Ella A.; Bellm, Aliyah; Behrendt, Ann Kathrin; Giachero, Federica; Bahlmann, Nora; Zhang, Wenli; Wirth, Stefan; Ehrhardt, Anja; Arnold, Wolfgang H.; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Objectives: Research involving the nose reveals important information regarding the morphology and physiology of the epithelium and its molecular response to agents. The role of nasal epithelial cells and other cell subsets within the nasal epithelium play an interesting translational split between experimental and clinical research studying respiratory disorders or pathogen reactions. With an additional technical manuscript including a detailed description of important technical aspects, tips, tricks, and nuances for a successful culturing of primary, human nasal epithelial cells (NAEPCs), we here aim to improve the process of communication between experimentalists and physicians, supporting the purpose of a fruitful work for future translational projects. Methods: Based on previous work on various complex culture models of subject-derived NAEPCs, this additional manuscript harmonizes previously published facts combined with own experiences for a trouble-free implementation in laboratories. Results: A well-designed experimental question is essential prior to the establishment of different NAEPCs culture models. The correct method of cell extraction from the nasal cavity is essential and represent an important basis for successful culture work. Prior enzymatic processing of biopsy specimens, cell culture materials, collagenization procedure, culture conditions, and choice of culture medium are some important practical notes that increase the quality of the culture. Moreover, protocols on imaging techniques including histologic and electron microscopy must be adapted for NAEPC culture. Adapted flow cytometric protocols and transepithelial electrical resistance measurements can add valuable information. Outlook: A successful culturing of NAEPCs can provide an important basis for genetic studies and the implementation of omics-science, which is increasingly receiving broad attention in the scientific community. The common aim of in vitro ‘mini-noses’ will be a breakthrough in laboratories aiming to perform research under in vivo conditions. Here, organoid models are interesting models presenting a basis for translational studies.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Cell culture; Culture models; Modeling; Nasal epithelial cells; Nasal epithelium; Nose

The neuropeptide calcitonin gene-related peptide (CGRP) prevents inflammatory liver injury in mice - Kroeger, Irena; Erhardt, Annette; Abt, Dominik; Fischer, Michael; Biburger, Markus; Rau, Thomas; Neuhuber, Winfried; Tiegs, Gisa (Journal of Hepatology, 2009)
Background/Aims: Calcitonin gene-related peptide (CGRP) is a potent vasodilator and supposed to be responsible for neurogenic inflammation involved in migraine. Its role in inflammatory diseases of other organs is controversial and poorly investigated regarding liver inflammation, although the organ is innervated by CGRP containing primary sensory nerve fibers. Methods: Male Balb/c and IL-10 mice were pretreated with either αCGRP or the CGRP receptor antagonists CGRP or BIBN4096BS. Immune-mediated liver injury was induced by administration of lipopolysaccharide (LPS) or tumor necrosis factor-α (TNFα) to galactosamine (GalN)-sensitized mice and evaluated by serum transaminase activities and cytokine levels. Furthermore, intrahepatic CGRP receptor expression and hepatic CGRP concentrations were examined. Results: CGRP receptor 1 was expressed by immune cells and hepatocytes in human and murine liver. During liver injury CGRP receptor expression was increased whereas hepatic CGRP concentrations concomitantly decreased. While CGRP receptor antagonists failed to affect liver damage, pretreatment with αCGRP protected mice from GalN/LPS-induced liver injury by suppression of the pro-inflammatory cytokine response independently from IL-10 but related to the induction of the transcriptional repressor inducible cAMP early repressor (ICER). In contrast, αCGRP failed to protect against GalN/TNFα-induced liver failure. Conclusion: In the liver, CGRP exerts anti-inflammatory properties, which are characterized by a reduced production of pro-inflammatory cytokines. © 2009 European Association for the Study of the Liver.
Keywords: Calcitonin gene-related peptide; Inducible cAMP early repressor; Interleukin-10; Liver inflammation; TNFα

The normal human choroid is endowed with a significant number of lymphatic vessel endothelial hyaluronate receptor 1 (LYVE-1) - Positive macrophages - Schrödl, Falk; Brehmer, Axel; Neuhuber, Winfried; Kruse, Friedrich; May, Christian Albrecht; Cursiefen, Claus (Investigative Ophthalmology & Visual Science, 2008)
PURPOSE. Lymphatic vessel endothelial hyaluronic acid receptor (LYVE-1) is a newly discovered lymphatic endothelium-specific marker that is also expressed by a subpopulation of macrophages. To date, there is no report on its expression in the posterior human uvea. The purpose of this study was to investigate the expression of LYVE-1 in normal human choroids. METHODS. Eyes of body/cornea donors (55-89 years of age; 4-9 hours postmortem) were obtained. Choroids were dissected and prepared for cryosections followed by immunohistochemistry with anti-human LYVE-1 antiserum and immunogold labeling. In addition, anti-human antibodies against macrophage markers (CD68, MHC class II) and lymphatic (podoplanin) and blood vascular endothelium (CD31, vWF) were used. For documentation, light-, fluorescence-, confocal laser scanning-, and electron-microscopy were used. RESULTS. The normal human choroidal stroma contained 27 ± 86 LYVE-1 positive cells/mm2. The cells displayed irregular shapes with a relatively uniform diameter of 32 μm. Costaining with CD68 and negativity for CD31, podoplanin, and melan-A/HMB45, as well as electron microscopic features, suggest these LYVE-1 cells to be macrophages. Besides that, no classic LYVE-1/podoplanin lymphatic vessels were detected within the normal adult human choroid. CONCLUSIONS. The normal adult human choroid does not contain typical lymph vessels, but is endowed with a significant number of LYVE-1 positive macrophages. These cells may be involved in choroidal hyaluronic acid metabolism or contribute to temporary formation of lymphatic channels under inflammatory conditions. Copyright © Association for Research in Vision and Ophthalmology.

The novel surfactant protein SP-H enhances the phagocytosis efficiency of macrophage-like cell lines U937 and MH-S - Diler, Ebru; Schicht, Martin; Rabung, Andrea; Tschernig, Thomas; Meier, Carola; Rausch, Felix; Garreis, Fabian; Bräuer, Lars; Paulsen, Friedrich (BMC Research Notes, 2014)
Surfactant proteins (SP) secreted by alveolar type 2 cells, play an essential role in maintaining the air-liquid barrier of the lung and are also involved in the opsonisation and clearance of bacteria by phagocytes. We have recently described a novel surfactant protein, SP-H (SFTA3). Expression of SP-H was earlier demonstrated to be upregulated by LPS and negatively regulated by IL-1? and IL-23 in vitro. The influence of SP-H on phagocytosis was measured using a murine and a human phagocytic cell line and fluorescent latex beads.SP-H markedly increases phagocytosis in vitro in the murine-derived alveolar macrophage cell lines MH-S and in human-derived differentiated U937 cells.It can be assumed that SP-H is involved in regulating phagocytic activity of macrophages. SP-H is a new player in pulmonary host defence.
EVALuna2:4439

The plantaris muscle – Anatomical curiosity or a structure with important clinical value? – A comprehensive review of the current literature - Gonera, B.; Kurtys, K.; Paulsen, Friedrich; Polguj, Michał; LaPrade, Robert F.; Grzelecki, Dariusz; Karauda, Piotr; Olewnik, Łukasz (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Purpose: Although the plantaris muscle is vestigial in humans, it is far too important to remain omitted. The aim of this study is to provide a comprehensive review of the existing literature focused on plantaris muscle clinical value, grafting usefulness and its morphological variations. Hopefully this study will be of great use for every medical practitioner due to its clarity and conciseness despite such broaden scope of this article. Material and Methods: The article is written based on 100 studies published since 1868 until 2020. During careful selection process 12 papers were dismissed due to their insufficient sample size, wrong methods used or results that were previously discovered. Results: Many aspects concerning the plantaris muscle are already well examined, summarized and described. However this study has shown how much we still do not know and which fields require further investigations. Conclusion: The anatomical variations of plantaris muscle morphology may cause mid-portion Achilles tendinopathy, tennis leg syndrome or increase the risk of failure while harvesting the tendons.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Achilles mid-portion tendinopathy; Autologous graft; Plantaris muscle; Popliteal region; Tennis leg

The Potential Role of SP-G as Surface Tension Regulator in Tear Film: From Molecular Simulations to Experimental Observations - Schicht, Martin; Riedlova, Kamila; Kukulka, Mercedes; Li, Wenyue; Scheer, Aurelius; Garreis, Fabian; Jacobi, Christina; Paulsen, Friedrich; Cwiklik, Lukasz; Bräuer, Lars (International Journal of Molecular Sciences, 2022)
The ocular surface is in constant interaction with the environment and with numerous pathogens. Therefore, complex mechanisms such as a stable tear film and local immune defense mechanisms are required to protect the eye. This study describes the detection, characterization, and putative role of surfactant protein G (SP-G/SFTA2) with respect to wound healing and surface activity. Bioinformatic, biochemical, and immunological methods were combined to elucidate the role of SP-G in tear film. The results show the presence of SP-G in ocular surface tissues and tear film (TF). Increased expression of SP-G was demonstrated in TF of patients with dry eye disease (DED). Addition of recombinant SP-G in combination with lipids led to an accelerated wound healing of human corneal cells as well as to a reduction of TF surface tension. Molecular modeling of TF suggest that SP-G may regulate tear film surface tension and improve its stability through specific interactions with lipids components of the tear film. In conclusion, SP-G is an ocular surface protein with putative wound healing properties that can also reduce the surface tension of the tear film.
CRIS-Team WoS Importer:2022-06-10

The presence of cerebellar B cell aggregates is associated with a specific chemokine profile in the cerebrospinal fluid in a mouse model of multiple sclerosis - Schropp, Verena; Chunder, Rittika; Dietel, Barbara; Tacke, Sabine; Kuerten, Stefanie (Journal of Neuroinflammation, 2023)
Background: The presence of meningeal ectopic lymphoid structures (ELS) in a subgroup of patients diagnosed with secondary progressive multiple sclerosis (SPMS) corresponds to a pronounced cortical inflammation and an aggravated disease course. In MP4-induced experimental autoimmune encephalomyelitis (EAE), a mouse model of multiple sclerosis (MS), B cell aggregates develop in the central nervous system (CNS) in the chronic stage of the disease. Therefore, the model is suitable for studying key molecules of ELS development and maintenance. Here, we investigated whether there is a specific cytokine and chemokine signature in paired cerebrospinal fluid (CSF) and serum samples associated with the presence of cerebellar B cell and T cell pathology and B cell aggregates of MP4-immunized mice. Methods: Paired CSF and serum samples were collected from the cisterna magna and periphery of MP4-immunized mice at the chronic stage of disease. A control group with mice immunized only with the adjuvant (vehicle) was included in the study. A selected panel of 34 cytokines and chemokines were measured by MAGPIX® for both cohorts. For the assessment of B cell and T cell infiltration, immunohistochemical staining was performed and analyzed using light microscopy. To detect specific chemokine receptors additional staining was conducted. Results: While we detected several upregulated cytokines and chemokines in the CSF of MP4-immunized mice independent of the extent of B cell and T cell pathology compared to vehicle-immunized mice, C-C motif chemokine ligand (CCL)-1 was associated with high B cell and T cell infiltration. Furthermore, the level of certain chemokines, including CCL1, CCL5, CCL7, CCL12, CCL22 and C-X-C motif chemokine ligand (CXCL)-13, was significantly increased (p < 0.05) in MP4-immunized mice showing a high number of B cell aggregates. While C-C motif chemokine receptor (CCR)5 had a ubiquitous expression independent of the extent of B cell and T cell pathology, C-X-C motif chemokine receptor (CXCR)-5 and CXCR6 expression was specifically associated with high B cell and T cell pathology. Conclusion: Our data suggest that multiple cytokines and chemokines are involved in the pathophysiology of MP4-induced EAE. Furthermore, the presence of B cell aggregates was associated with a specific chemokine profile in the CSF, which might be useful for predicting the presence of these aggregates without the necessity to histologically screen the CNS tissue.
CRIS-Team Scopus Importer:2023-02-10
Keywords: B cell aggregates; Chemokines; CSF; EAE; MP4

Therapeutic potential of AAV-mediated MMP-3 secretion from corneal endothelium in treating glaucoma - O'Callaghan, Jeffrey; Crosbie, Darragh. E.; Cassidy, Paul. S.; Sherwood, Joseph M.; Flügel-Koch, Cassandra; Lütjen-Drecoll, Elke; Humphries, Marian M.; Reina-Torres, Ester; Wallace, Deborah; Kiang, Anna-Sophia; Campbell, Matthew; Stamer, W. Daniel; et al. (Human Molecular Genetics, 2017)
Intraocular pressure (IOP) is maintained as a result of the balance between production of aqueous humour (AH) by the ciliary processes and hydrodynamic resistance to its outflow through the conventional outflow pathway comprising the trabecular meshwork (TM) and Schlemm's canal (SC). Elevated IOP, which can be caused by increased resistance to AH outflow, is a major risk factor for open-angle glaucoma. Matrix metalloproteinases (MMPs) contribute to conventional aqueous outflow homeostasis in their capacity to remodel extracellular matrices, which has a direct impact on aqueous outflow resistance and IOP. We observed decreased MMP-3 activity in human glaucomatous AH compared to age-matched normotensive control AH. Treatment with glaucomatous AH resulted in significantly increased transendothelial resistance of SC endothelial and TM cell monolayers and reduced monolayer permeability when compared to control AH, or supplemented treatment with exogenous MMP-3.Intracameral inoculation of AAV-2/9 containing a CMV-driven MMP-3 gene (AAV-MMP-3) into wild type mice resulted in efficient transduction of corneal endothelium and an increase in aqueous concentration and activity of MMP-3. Most importantly, AAV-mediated expression of MMP-3 increased outflow facility and decreased IOP, and controlled expression using an inducible promoter activated by topical administration of doxycycline achieved the same effect. Ultrastructural analysis of MMP-3 treated matrices by transmission electron microscopy revealed remodelling and degradation of core extracellular matrix components. These results indicate that periodic induction, via use of an eye drop, of AAV-mediated secretion of MMP-3 into AH could have therapeutic potential for those cases of glaucoma that are sub-optimally responsive to conventional pressure-reducing medications.
EVALuna2:35335

The receptor for advanced glycation end products RAGE is involved in corneal healing - Nass, Norbert; Trau, Stefanie; Paulsen, Friedrich; Kaiser, Delia; Kalinski, Thomas; Sel, Saadettin (Annals of Anatomy-Anatomischer Anzeiger, 2017)
Impaired corneal healing is still a major cause of blindness. As RAGE (receptor for advanced glycation endproducts) is involved in inflammation and wound healing in other tissues, we here investigated its relevance for corneal wound healing. Corneal re-epithelialization after alkaline injury was analysed in an ex-vivo approach with cultured, enucleated eyes from mice either of the C57Bl/6 NChR genotype (RAGE+/+) and mice of the same strain lacking the RAGE gene (RAGE-/-). The wound area was determined time dependently by fluorescence imaging using fluorescein staining. The eyes of RAGE-/- mice showed a significantly slower re-epithelialization than eyes of the RAGE+/- and the RAGE+/+ genotype. In immunohistochemistry, RAGE expression was increased in wounded corneas whereas the abundance of the RAGE ligand HMGB1 was unaffected, but an increase in S100b-like proteins was revealed upon injury. However, neither the addition of the RAGE agonist HMGB1 or an HMGB1 antagonising antibody nor bovine S100b protein to the culture medium of the wounded eyes had an effect on corneal wound closure in ex-vivo. Further gene expression analysis by RT-PCR demonstrated an increase in RAGE expression on the mRNA level, no significant regulation of HMGB1 and a differential regulation of the S100 gene family after alkaline burn of the cornea. In conclusion, RAGE is clearly involved in corneal re-epithelialization most probably mediated by signalling via S100 proteins.
EVALuna2:35341

The Relevance of the Bacterial Microbiome, Archaeome and Mycobiome in Pediatric Asthma and Respiratory Disorders - Baehren, Carolin; Buedding, Eleni; Bellm, Aliyah; Schult, Frank; Pembaur, Anton; Wirth, Stefan; Ehrhardt, Anja; Paulsen, Friedrich; Postberg, Jan; Aydin, Malik (Cells, 2022)
Bacteria, as well as eukaryotes, principally fungi, of the upper respiratory tract play key roles in the etiopathogenesis of respiratory diseases, whereas the potential role of archaea remains poorly understood. In this review, we discuss the contribution of all three domains of cellular life to human naso-and oropharyngeal microbiomes, i.e., bacterial microbiota, eukaryotes (mostly fungi), as well as the archaeome and their relation to respiratory and atopic disorders in infancy and adolescence. With this review, we aim to summarize state-of-the-art contributions to the field published in the last decade. In particular, we intend to build bridges between basic and clinical science.
CRIS-Team Scopus Importer:2022-04-29
Keywords: allergy; archaea; asthma; fungi; microbiome; nasopharynx; oropharynx; respiratory tract infections

Thermosensitive TRP Channels Are Functionally Expressed and Influence the Lipogenesis in Human Meibomian Gland Cells - Keller, Melina; Mergler, Stefan; Li, Aruna; Zahn, Ingrid; Paulsen, Friedrich; Garreis, Fabian (International Journal of Molecular Sciences, 2024)
While the involvement of thermosensitive transient receptor potential channels (TRPs) in dry eye disease (DED) has been known for years, their expression in the meibomian gland (MG) has never been investigated. This study aims to show their expression and involvement in the lipogenesis of the MG, providing a possible new drug target in the treatment of DED. Our RT-PCR, Western blot and immunofluorescence analysis showed the expression of TRPV1, TRPV3, TRPV4 and TRPM8 in the MG at the gene and the protein level. RT-PCR also showed gene expression of TRPV2 but not TRPA1. Calcium imaging and planar patch-clamping performed on an immortalized human meibomian gland epithelial cell line (hMGECs) demonstrated increasing whole-cell currents after the application of capsaicin (TRPV1) or icilin (TRPM8). Decreasing whole-cell currents could be registered after the application of AMG9810 (TRPV1) or AMTB (TRPM8). Oil red O staining on hMGECs showed an increase in lipid expression after TRPV1 activation and a decrease after TRPM8 activation. We conclude that thermo-TRPs are expressed at the gene and the protein level in MGs. Moreover, TRPV1 and TRPM8’s functional expression and their contribution to their lipid expression could be demonstrated. Therefore, TRPs are potential drug targets and their clinical relevance in the therapy of meibomian gland dysfunction requires further investigation.
CRIS-Team Scopus Importer:2024-04-26
Keywords: dry eye disease; meibomian gland; meibomian gland dysfunction; tear film; thermo-TRPs; TRP channels

The role of triggering receptor expressed on myeloid cells 2 in Parkinson's disease and other neurodegenerative disorders - Schwarz, Hannah; Bässler, Sarah; Balta, Denise; Socher, Eileen; Zunke, Friederike; Arnold, Philipp (Behavioural Brain Research, 2022)
Parkinson's disease (PD) is a progressive neurological disorder marked by cardinal clinical symptoms such as rigor, tremor, and akinesia. Albeit a loss of dopaminergic neurons from the substantia nigra pars compacta is causative for the movement impairments found in patients, molecular reasoning for this loss is still incomplete. In recent years, triggering factor expressed on myeloid cells (TREM2) gained attention in the field of neurodegeneration as it could be associated with different neurodegenerative disorders. Primarily identified as a risk factor in Alzheimer's disease, variants in TREM2 were linked to PD and multiple sclerosis, too. Expressed on phagocytic cells, such as macrophages and microglia, TREM2 puts the focus on inflammation associated conditions in PD and provides a molecular target that could at least partly explain the role of immune cells in PD. Here, we summarize expression patterns and molecular functions of TREM2, recapitulate on its role in inflammation, phagocytosis and cell survival, before turning to neurodegenerative disorders with an emphasis on PD.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Cell signaling; DAP12; Inflammation; Neurodegeneration; Parkinson's disease; TREM2

The roles of TRPV1, TRPA1 and TRPM8 channels in chemical and thermal sensitivity of the mouse oral mucosa - Kichko, Tetyana; Neuhuber, Winfried; Kobal, Gerd; Reeh, Peter (European Journal of Neuroscience, 2018)
Spices in food and beverages and compounds in tobacco smoke interact with sensory irritant receptors of the transient receptor potential (TRP) cation channel family. TRPV1 (vanilloid type 1), TRPA1 (ankyrin 1) and TRPM8 (melastatin 8) not only elicit action potential signaling through trigeminal nerves, eventually evoking pungent or cooling sensations, but by their calcium conductance they also stimulate the release of calcitonin gene-related peptide (CGRP). This is measured as an index of neuronal activation to elucidate the chemo- and thermosensory transduction in the isolated mouse buccal mucosa of wild types and pertinent knockouts. We found that the lipophilic capsaicin, mustard oil and menthol effectively get access to the nerve endings below the multilayered squamous epithelium, while cigarette smoke and its gaseous phase were weakly effective releasing CGRP. The hydrophilic nicotine was ineffective unless applied unprotonated in alkaline (pH9) solution, activating TRPA1 and TRPV1. Also, mustard oil activated both these irritant receptors in millimolar but only TRPA1 in micromolar concentrations; in combination (1 mm) with heat (45 °C), it showed supraadditive, that is heat sensitizing, effects in TRPV1 and TRPA1 knockouts, suggesting action on an unknown heat-activated channel and mustard oil receptor. Menthol caused little CGRP release by itself, but in subliminal concentration (2 mm), it enabled a robust cold response that was absent in TRPM8-/- but retained in TRPA1-/- and strongly reduced by TRPM8 inhibitors. In conclusion, all three relevant irritant receptors are functionally expressed in the oral mucosa and play their specific roles in inducing neurogenic inflammation and sensitization to heat and cold.
EVALuna2:35205

The sacral autonomic outflow: against premature oversimplification - Jaenig, Wilfrid; Mclachlan, Elspeth M.; Neuhuber, Winfried (Clinical Autonomic Research, 2018)
EVALuna2:35204

The Sacral Autonomic Outflow Is Spinal, but Not "Sympathetic" - Neuhuber, Winfried; Mclachlan, Elspeth; Jaenig, Wilfrid (Anatomical Record-Advances in Integrative Anatomy and Evolutionary Biology, 2017)
A recent article published in a high-profile journal proposed to reclassify the sacral autonomic outflow as being part of the sympathetic system. In this commentary, arguments against this erroneous proposal are provided. Anat Rec, 300:1369-1370, 2017. © 2017 Wiley Periodicals, Inc.
EVALuna2:35221

The structure of the trabecular meshwork, its connections to the ciliary muscle, and the effect of pilocarpine on outflow facility in mice - Overby, Darryl R.; Bertrand, Jacques; Schicht, Martin; Paulsen, Friedrich; Stamer, W. Daniel; Lütjen-Drecoll, Elke (Investigative Ophthalmology & Visual Science, 2014)
To determine the connections between the ciliary muscle (CM), trabecular meshwork (TM), and Schlemm's canal (SC) and their innervations that allows CM contraction (by pilocarpine) to influence conventional outflow in mice.Sequential sections and whole mounts of murine corneoscleral angles were stained for elastin, ?-smooth muscle actin (?SMA), vesicular acetylcholine transporter (VAChT), neuronal nitric oxide synthase (nNOS), vasoactive intestinal peptide (VIP), and tyrosine hydroxylase (TH). Elastic (EL) fibers between the CM, TM, and SC were examined in ultrathin, sequential sections from different planes. The effect of pilocarpine (100 ?M) on conventional outflow facility was measured by perfusion of enucleated mouse eyes.The mouse TM contains a three-dimensional (3D) net of EL fibers connecting the inner wall of SC to the cornea anteriorly, the ciliary body (CB) internally and the choroid and CM posteriorly. The CM bifurcates near the posterior TM, extending outer tendons to the juxtacanalicular tissue and inner wall of SC and internal connections to the lamellated TM and CB. Ciliary muscle and lamellated TM cells stain with ?SMA and are innervated by VAChT-containing nerve fibers, without TH, VIP, or nNOS. Pilocarpine doubled outflow facility.Mouse eyes resemble primate eyes not only by their well developed SC and TM, but also by their 3D EL net tethering together the TM and SC inner wall and by the tendinous insertion of the CM into this net. The increase in outflow facility following cholinergic stimulation in mice, as in primates, supports using mice for studies of aqueous humor dynamics and glaucoma.
EVALuna2:4410

The tendon of the fibularis brevis muscle – Systematic overview and new classification system - Zielinska, Nicol; Tubbs, R. Shane; Gonera, Bartosz; Georgiev, Georgi P.; Paulsen, Friedrich; Olewnik, Łukasz (Annals of Anatomy-Anatomischer Anzeiger, 2024)
The fibularis brevis muscle belongs to the lateral compartment of the leg. It originates from the lower two-thirds of the lateral surface of the fibula bone and it also is attached to the anterior intermuscular septum. Its insertion is normally located on the tuberosity at the base of the fifth metatarsal bone, on its lateral side. However, distal attachment of this muscle is morphologically variable. Different variations have been identified and some classification systems have been created for both adults and foetuses. Based on various literature references, we have created a new classification system and compared the frequency of each type. The main aim of this review is to present morphological variations of the fibularis brevis tendon with their clinical significance, especially in autografting in case of surgical treatment of fibularis brevis tendon rupture. The clinical aspect of this pathology and some medical cases will also be presented.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Adults; Clinical significance; Comprehensive review; Fetuses; Fibularis brevis muscle; Fibularis brevis tendon; New classification

The toxic effect of air on primary human retinal pigment epithelium cells - Kopsachilis, Nikolaos; Carifi, Gianluca; Tsatsos, Michael; Welge-Lüssen, Ulrich-Christoph (Current Eye Research, 2015)
To investigate the toxic effect of air on primary human retinal pigment epithelium cells (RPE) over time.RPE cultures were retrieved from six donor eyes and cultivated at 37 °C in 5% CO(2) and 95% humidified air. The RPE were divided in six groups with each group containing four samples. Six groups of RPE cultures were set up and four samples were enclosed in each group: group 1 consisted of samples in which RPE were exposed to air for 1 hour. Group 2 consisted of RPE exposed to air for 3 hours, group 3 for 6 hours group 4 for 12 hours group 5 for 24 hours and group 6 for 36 hours respectively.Six hours after exposure, the morphology of the cells was still intact. At 12 hours few cells appeared enlarged. 24 hours after exposure to air the cells started losing their typical morphology and appeared deformed. Viability was higher than 95% in groups 1-3 while for groups 4-6 was 75.5%, 15.5% and 7.3%, respectively.The toxic effect of air for the studied in vitro model of RPE is not significant for the first 6 hours. The morphology of the cells progressively changed after 12 hours of exposure and almost all cells appeared apoptotic at 36 hours.
EVALuna2:21246

The transcription factor Foxk1 is expressed in developing and adult mouse neuroretina - Sel, Saadettin; Muenzenberg, Christoph; Nass, Norbert; Kalinski, Thomas; Datan, Maja; Auffarth, Gerd U.; Toeteberg-Harms, Marc; Zenkel, Matthias; Kruse, Friedrich; Paulsen, Friedrich; Schicht, Martin (Gene Expression Patterns, 2013)
The forkhead transcription factor Foxk1 is an important regulator of myogenic progenitor cells. Since our previous data from mouse retina revealed that Foxk1 is upregulated in Ptf1a-deficient mice we investigated the spatial and temporal expression of Foxk1 during development of mouse retina. Expression of Foxk1 was analyzed on both mRNA and protein level. To identify Foxk1 transcripts, retina and cerebrum (positive control) of adult animals (postnatal day 90 (P90)) was subjected to reverse transcription polymerase chain reaction (RT-PCR) and sequencing of the amplified cDNA. The Foxk1 protein was analyzed in adult retina by Western blotting and in developing eyes at embryonic day (E) 13, 15, E17, P0, P4, P7, P10 and P90 by immunohistochemistry. Localization of Foxk1 expression was determined using cell-specific markers by double labelling. Foxk1 transcripts were detected in adult retina by RT-PCR and confirmed by sequencing. Western blot analysis confirmed the expression of Foxk1 protein in the adult retina. Immunohistochemical examination of developing eyes localized the protein to bipolar, amacrine and ganglion cells with an onset of Foxk1 expression from E15 onwards. The expression pattern during development suggests that Foxk1 may have an important role in retinal cells. © 2013 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Foxk1; Retinal development; Retinogenesis; Transcription factor

The Translational Role of MUC8 in Salivary Glands: A Potential Biomarker for Salivary Stone Disease? - Schicht, Martin; Reichle, Adrian; Schapher, Mirco; Garreis, Fabian; Kleinsasser, Benedikt; Aydin, Malik; Sahin, Afsun; Iro, Heinrich; Paulsen, Friedrich (Diagnostics, 2021)
Mucin (MUC) 8 has been shown to play an important role in respiratory disease and inflammatory responses. In the present study, we investigated the question of whether MUC8 is also produced and secreted by salivary glands and whether it may also play a role in the oral cavity in the context of inflammatory processes or in the context of salivary stone formation. Tissue samples from parotid and submandibular glands of body donors (n = 6, age range 63-88 years), as well as surgically removed salivary stones from patients (n = 38, age range 48-72 years) with parotid and submandibular stone disease were immunohistochemically analyzed targeting MUC8 and TNF alpha. The presence of MUC8 in salivary stones was additionally analyzed by dot blot analyses. Moreover, saliva samples from patients (n = 10, age range 51-72 years), who had a salivary stone of the submandibular gland on one side were compared with saliva samples from the other "healthy " side, which did not have a salivary stone, by ELISA. Positive MUC8 was detectable in the inter- and intralobular excretory ducts of both glands (parotid and submandibular). The glandular acini showed no reactivity. TNF alpha revealed comparable reactivity to MUC8 in the glandular excretory ducts and also did not react in glandular acini. Salivary stones demonstrated a characteristic distribution pattern of MUC8 that differed between parotid and submandibular salivary stones. The mean MUC8 concentration was 71.06 ng/mL in female and 33.21 ng/mL in male subjects (p = 0.156). Saliva from the side with salivary calculi contained significantly (15-fold) higher MUC8 concentration levels than saliva from the healthy side (p = 0.0005). MUC8 concentration in salivary stones varied from 4.59 ng/mL to 202.83 ng/mL. In females, the MUC8 concentration in salivary stones was significantly (2.3-fold) higher, with an average of 82.84 ng/mL compared to 25.27 ng/mL in male patients (p = 0.034). MUC8 is secreted in the excretory duct system of salivary glands and released into saliva. Importantly, MUC8 salivary concentrations vary greatly between individuals. In addition, the MUC8 concentration is gender-dependent (& FEMALE; > & MALE;). In the context of salivary stone diseases, MUC8 is highly secreted in saliva. The findings support a role for MUC8 in the context of inflammatory events and salivary stone formation. The findings allow conclusions on a gender-dependent component of MUC8.
CRIS-Team WoS Importer:2022-01-14

Tiefes periokuläres Trauma mit Tränenwegsbeteiligung durch Kaiserschnittentbindung - Heichel, Jens; Struck, Hans Gert; Paulsen, Friedrich; Javed Ali, Mohammad; Viestenz, Arne (HNO, 2021)
Periocular injuries during a caesarean section are extremely rare. The case report of a five hour old newborn addresses the trauma management concerning diagnostics, therapy, and post-operative care of a deep periocular soft tissue injury. The pattern of injury consisted of full thickness wounds of the medial and lateral lid margins, opening of the superior conjunctival fornix, and penetration of Tenon’s capsule. The reconstruction was performed layer by layer while an autostable monocanaliculonasal lacrimal intubation was inserted.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Calamari ring sign; Eyelids; Lacrimal intubation; Orbit; Pediatric ophthalmology

TILGen: A Program to Investigate Immune Targets in Breast Cancer Patients - First Results on the Influence of Tumor-Infiltrating Lymphocytes - Würfel, Franziska; Erber, Ramona; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Kremer, Anita; Kranich, Hannah; Mackensen, Andreas; Häberle, Lothar; Hack, Carolin; Rauh, Claudia; et al. (Breast Care, 2018)
Background: Despite advancements in the treatment of primary and metastatic breast cancer, many patients lack a durable response to these treatments. Patients with triple-negative breast cancer (TNBC) and human epidermal growth factor receptor 2(HER2)-positive breast cancer who do not have a pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) have a very poor prognosis. Tumor-infiltrating lymphocytes (TILs) have been identified as a predictive marker for pCR after NACT in TNBC and HER2-positive breast cancer. These patient populations could also be suitable for novel treatment strategies including neoepitope-based therapies. This work analyses the effect of TILs on the pCR in neoadjuvantly treated patients in the TILGen study and presents the procedures aimed at establishing neoepitope-based therapies in this study. Methods: Neoadjuvantly treated HER2-positive and TNBC patients were eligible for the presented analysis concerning the association between TILs and pCR. A total of 146 patients could be identified within the TILGen study. TILs were evaluated as percentage of stromal tumor tissue in core biopsies at primary diagnosis. The phenotype ‘lymphocyte-predominant breast cancer' (LPBC) was associated with pCR by logistic regression adjusted for estrogen receptor status, progesterone receptor status, HER2 status, age at diagnosis, and grading. Results: LPBC was seen in 24 (16.4%) patients. In this patient group, 66.7% achieved a pCR, while the pCR rate was 32.8% in patients with a low TIL count. The adjusted odds ratio was 6.60 (95% confidence interval 2.02-21.56; p < 0.01). Conclusion: TILs are a strong predictor of pCR in TNBC and HER2-positive breast cancer patients. Implications for the use of this information including the effect on prognosis might help to identify patients most likely to benefit from a neoepitope-based therapy approach.<br

Time Trend in SARS-CoV-2 Seropositivity, Surveillance Detection- and Infection Fatality Ratio until Spring 2021 in the Tirschenreuth County—Results from a Population-Based Longitudinal Study in Germany - Einhauser, Sebastian; Peterhoff, David; Beileke, Stephanie; Günther, Felix; Niller, Hans Helmut; Steininger, Philipp; Knöll, Antje; Korn, Klaus; Berr, Melanie; Schütz, Anja; Wiegrebe, Simon; Stark, Klaus J.; et al. (Viruses, 2022)
Herein, we provide results from a prospective population-based longitudinal follow-up (FU) SARS-CoV-2 serosurveillance study in Tirschenreuth, the county which was hit hardest in Germany in spring 2020 and early 2021. Of 4203 individuals aged 14 years or older enrolled at baseline (BL, June 2020), 3546 participated at FU1 (November 2020) and 3391 at FU2 (April 2021). Key metrics comprising standardized seroprevalence, surveillance detection ratio (SDR), infection fatality ratio (IFR) and success of the vaccination campaign were derived using the Roche N-and S-Elecsys anti-SARS-CoV-2 test together with a self-administered questionnaire. N-seropositivity at BL was 9.2% (1st wave). While we observed a low new seropositivity between BL and FU1 (0.9%), the combined 2nd and 3rd wave accounted for 6.1% new N-seropositives between FU1 and FU2 (ever seropositives at FU2: 15.4%). The SDR decreased from 5.4 (BL) to 1.1 (FU2) highlighting the success of massively increased testing in the population. The IFR based on a combination of serology and registration data resulted in 3.3% between November 2020 and April 2021 compared to 2.3% until June 2020. Although IFRs were consistently higher at FU2 compared to BL across age-groups, highest among individuals aged 70+ (18.3% versus 10.7%, respectively), observed differences were within statistical uncertainty bounds. While municipalities with senior care homes showed a higher IFR at BL (3.0% with senior care home vs. 0.7% w/o), this effect diminished at FU2 (3.4% vs. 2.9%). In April 2021 (FU2), vaccination rate in the elderly was high (>77.4%, age-group 80+).
CRIS-Team Scopus Importer:2022-06-17
Keywords: case fatality ratio; elderly; infection fatality ratio; longitudinal; population-based; SARS-CoV-2; senior care homes; seroprevalence; surveillance detection ratio; vaccination

Tonic Investigation Concept of Cervico-vestibular Muscle Afferents - Dorn, Linda Josephine; Lappat, Annabelle; Neuhuber, Winfried; Scherer, Hans; Olze, Heidi; Hoelzl, Matthias (International Archives of Otorhinolaryngology, 2017)
Introduction Interdisciplinary research has contributed greatly to an improved understanding of the vestibular system. To date, however, very little research has focused on the vestibular system's somatosensory afferents. To ensure the diagnostic quality of vestibular somatosensory afferent data, especially the extra cranial afferents, stimulation of the vestibular balance system has to be precluded. Objective Sophisticated movements require intra- and extra cranial vestibular receptors. The study's objective is to evaluate an investigation concept for cervico-vestibular afferents with respect to clinical feasibility. Methods A dedicated chair was constructed, permitting three-dimensional trunk excursions, during which the volunteer's head remains fixed. Whether or not a cervicotonic provocation nystagmus (c-PN) can be induced with static trunk excursion is to be evaluated and if this can be influenced by cervical monophasic transcutaneous electrical nerve stimulation (c-TENS) with a randomized test group. 3D-video-oculography (VOG) was used to record any change in cervico-ocular examination parameters. The occurring nystagmuses were evaluated visually due to the small caliber of nystagmus amplitudes in healthy volunteers. Results The results demonstrate: no influence of placebo-controlled c-TENS on the spontaneous nystagmus; a significant increase of the vertical nystagmus on the 3D-trunk-excursion chair in static trunk flexion with cervical provocation in all young healthy volunteers (n = 49); and a significant difference between vertical and horizontal nystagmuses during static trunk excursion after placebo-controlled c-TENS, except for the horizontal nystagmus during trunk torsion. Conclusion We hope this cervicotonic investigation concept on the 3D trunk-excursion chair will contribute to new diagnostic and therapeutic perspectives on cervical pathologies in vestibular head-to-trunk alignment.
EVALuna2:35220

Towards microstructure-informed material models for human brain tissue - Budday, Silvia; Sarem, Melika; Starck, Laurent; Sommer, Gerhard; Pfefferle, Jule; Phunchago, Nichapa; Kuhl, Ellen; Paulsen, Friedrich; Steinmann, Paul; Shastri, V. Prasad; Holzapfel, Gerhard A. (Acta Biomaterialia, 2020)
Emerging evidence suggests that the mechanical behavior of the brain plays a critical role in development, disease, and aging. Recent studies have begun to characterize the mechanical behavior of gray and white matter tissue and to identify sets of material models that best reproduce the stress-strain behavior of different brain regions. Yet, these models are mainly phenomenological in nature, their parameters often lack clear physical interpretation, and they fail to correlate the mechanical behavior to the underlying microstructural composition. Here we make a first attempt towards identifying general relations between microstructure and mechanics with the ultimate goal to develop microstructurally motivated constitutive equations for human brain tissue. Using histological staining, we analyze the microstructure of brain specimens from different anatomical regions, the cortex, basal ganglia, corona radiata, and corpus callosum, and identify the regional stiffness and viscosity under multiple loading conditions, simple shear, compression, and tension. Strikingly, our study reveals a negative correlation between cell count and stiffness, a positive cor- relation between myelin content and stiffness, and a negative correlation between proteoglycan content and stiffness. Additionally, our analysis shows a positive correlation between lipid and proteoglycan content and viscosity. We demonstrate how understanding the microstructural origin of the macroscopic behavior of the brain can help us design microstructure-informed material models for human brain tissue that inherently capture regional heterogeneities. This study represents an important step towards using brain tissue stiffness and viscosity as early diagnostic markers for clinical conditions including chronic traumatic encephalopathy, Alzheimer’s and Parkinson’s disease, or multiple sclerosis.
Keywords: material modeling; biomechanical testing; hyperelasticity; Ogden model; human brain tissue; microstructure

Transcutaneous (External) Dacryocystorhinostomy with Reconstruction of the Ductus nasolacrimalis. - Heichel, Jens; Dettmer, Wiebke; Paulsen, Friedrich; Ali, Mohammad Javed; Schmidt-Pokrzywniak, Andrea; Viestenz, Arne; Hammer, Thomas; Struck, Hans Gert (Klinische Monatsblätter für Augenheilkunde, 2024)
BACKGROUND: Dacryocystorhinostomy (DCR) is regarded as the gold standard for the treatment of chronic dacryocystitis (CDC). Different modifications of the surgical procedure have been developed over the years. METHODS: Patients with CDC due to postsaccal lacrimal stenosis and under treatment with DCR have been included in this retrospective study. Two groups of different surgical procedures were analysed: firstly DCR without reconstruction of the ductus nasolacrimalis (DNL, group 1) and secondly patients with reopening the DNL (group 2). Criteria for success were absence of permanent epiphora, absence of inflammation of the lacrimal sac (functional success), and no recurrent surgery with free patency of the lacrimal duct (anatomical success). This was obtained by questionnaire after a follow-up of at least 12 months. The impact of gender, ectasia of the lacrimal sac, dacryoliths, and prior lacrimal surgeries was analysed. RESULTS: Overall, 248 surgeries were enrolled in this trial. Mean age in group 1 was 68 years (range: 22 to 92 years) and gender ratio was 3.2 to 1 (female : male). In that group, 68 operations could be followed up. In group 2, 62 operations on patients of a mean age of 63 years (range: 24 to 89 years) and a gender ratio of 2.9 to 1 (female : male) were observed. Complete success occurred in 75.0% in group 1 and 75.8% in group 2. Recurrent operations were necessary in one case of group 2 (1.6%) and 4 cases of group 1 (5.9%). Gender (group 1 p = 1; group 2 p = 0.115; between groups p = 0.511), ectasia of the lacrimal sac (group 1 p = 0.877; group 2 p = 0.674; between groups p = 0.878), dacryolith (group 1 p = 1; group 2 p = 0.465; between groups p = 1), and prior lacrimal surgery (group 1 p = 0.092; group 2 p = 0.051; between groups p = 0.520) did not influence the success rates in each group or between groups. Significantly more dacryoliths were found during operations of group 2 (p = 0.010). CONCLUSION: Reconstruction of the DNL during DCR is a possible and easy modification, with a slightly better success rate in curing CDC. Intraoperatively, dacryoliths might not be apparent remain in the deeper parts of the lacrimal ducts. Therefore, these segments should be inspected during surgery.
EVALuna2:545159

Trauma of periorbital soft tissue. Reconstruction with regard to functional and aesthetic aspects - Reich, W.; Sel, Saadettin; Holbach, L.; Paulsen, Friedrich; Scheller, K. (Ophthalmologe, 2013)
Complex midfacial trauma requires interdisciplinary management. A wide range of reconstructive procedures are needed and if necessary secondary and even tertiary interventions should be performed at the appropriate time. We present the case of a 45-year-old man who was involved in a car accident and presented with severe injuries to the periorbital soft tissue. The focus was on the reconstruction of this sensitive region with regard to functional and aesthetic aspects. In view of the severity of the injuries the final clinical status is considered to be very important. Special issues and pitfalls in the reconstruction of trauma cases and potential management are discussed.
EVALuna2:21119

Treatment-resistant nodular scleritis Therapieresistente noduläre Skleritis - Hübner, L.; Mardin, Christian; Held, Jürgen; Tappe, D.; Hammer, Christian; Bergua, Antonio (Ophthalmologe, 2022)
CRIS-Team Scopus Importer:2022-03-18

Trefoil factor 3 (TFF3) is involved in cell migration for skeletal repair - Krüger, Katharina; Schmidt, Sebastian; Paulsen, Friedrich; Ignatius, Anita; Klinger, Patricia; Hotfiel, Thilo; Swoboda, Bernd; Gelse, Kolja (International Journal of Molecular Sciences, 2019)
The aim of the study was to explore the possible role of Trefoil Factor Family peptide 3 (TFF3) for skeletal repair. The expression of TFF3 was analyzed in human joint tissues as well as in a murine bone fracture model. Serum levels of TFF3 following a defined skeletal trauma in humans were determined by ELISA. The mRNA expression of TFF3 was analyzed under normoxia and hypoxia. Expression analysis after stimulation of human mesenchymal progenitor cells (MPCs) with TFF3 was performed by RT2 Profiler PCR Array. The effect of recombinant human (rh)TFF3 on MPCs was analysed by different migration and chemotaxis assays. The effect on cell motility was also visualized by fluorescence staining of F-Actin. TFF3 was absent in human articular cartilage, but strongly expressed in the subchondral bone and periosteum of adult joints. Strong TFF3 immunoreactivity was also detected in murine fracture callus. Serum levels of TFF3 were significantly increased after skeletal trauma in humans. Expression analysis demonstrated that rhTFF3 significantly decreased mRNA of ROCK1. Wound healing assays showed increased cell migration of MPCs by rhTFF3. The F-Actin cytoskeleton was markedly influenced by rhTFF3. Cell proliferation was not increased by rhTFF3. The data demonstrate elevated expression of TFF3 after skeletal trauma. The stimulatory effects on cell motility and migration of MPCs suggest a role of TFF3 in skeletal repair.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Cell migration; Chemotaxis; Fracture healing; Mesenchymal progenitor cells; TFF3

Trefoil factor family peptide 3 (TFF3) is upregulated under experimental conditions similar to dry eye disease and supports corneal wound healing effects in vitro - Schulze, Ute; Hampel, Ulrike; Sel, Saadettin; Contreras-Ruiz, Laura; Schicht, Martin; Dieckow, Julia; Diebold, Yolanda; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2014)
To elucidate the role of trefoil family peptide (TFF) 3 at the ocular surface under conditions similar to dry eye disease (DED) and in tears of patients suffering from DED.Trefoil family peptide 3 levels in tear samples from non-Sjögren's DED patients with moderate dry eye were analyzed by ELISA and compared with tears from healthy volunteers. A human corneal epithelial (HCE) cell line was treated with proinflammatory cytokines IL-1? and TNF-?, hyperosmolar medium, or scratching for up to 24 hours. Trefoil family peptide 3 gene expression and protein biosynthesis were analyzed by RT-PCR, immunofluorescence, and ELISA. Migration and proliferation of HCE cells under recombinant (r) human (h) trefoil factor family peptide 3 (TFF3) stimulation were investigated by scratching and bromodeoxyuridine (BrdU) proliferation assays.Tears of patients suffering from DED contained significantly higher TFF3 levels than tears from healthy volunteers. Stimulation of HCE cells with proinflammatory cytokines, culture under hyperosmolar conditions, or scratching resulted, with the exception of hyperosmolar conditions, in an increase in TFF3 expression and elevated secretion level of TFF3. Cell proliferation decreased and cell migration increased after 24-hours stimulation with rhTFF3.These results suggest that inflammatory factors or ocular surface damage as they occur in DED, lead to an increase of TFF3 tear film concentration, whereas hyperosmolarity does not. Our data underline a potential role for TFF3 as a candidate therapeutic for the ocular surface damage observed in DED.
EVALuna2:4420

TRPA1 and substance P mediate colitis in mice - Engel, Matthias; Leffler, Andreas; Niedermirtl, Florian; Babes, Alexandru; Zimmermann, Katharina; Filipovic, Milos; Izydorczyk, Iwona; Eberhardt, Mirjam; Kichko, Tetyana; Müller-Tribbensee, Sonja; Khalil, Mohammad; Siklosi, Norbert; et al. (Gastroenterology, 2011)

TRPC Channels in the Physiology and Pathophysiology of the Renal Tubular System: What Do We Know? - Englisch, Colya N.; Paulsen, Friedrich; Tschernig, Thomas (International Journal of Molecular Sciences, 2023)
The study of transient receptor potential (TRP) channels has dramatically increased during the past few years. TRP channels function as sensors and effectors in the cellular adaptation to environmental changes. Here, we review literature investigating the physiological and pathophysiological roles of TRPC channels in the renal tubular system with a focus on TRPC3 and TRPC6. TRPC3 plays a key role in Ca2+ homeostasis and is involved in transcellular Ca2+ reabsorption in the proximal tubule and the collecting duct. TRPC3 also conveys the osmosensitivity of principal cells of the collecting duct and is implicated in vasopressin-induced membrane translocation of AQP-2. Autosomal dominant polycystic kidney disease (ADPKD) can often be attributed to mutations of the PKD2 gene. TRPC3 is supposed to have a detrimental role in ADPKD-like conditions. The tubule-specific physiological functions of TRPC6 have not yet been entirely elucidated. Its pathophysiological role in ischemia-reperfusion injuries is a subject of debate. However, TRPC6 seems to be involved in tumorigenesis of renal cell carcinoma. In summary, TRPC channels are relevant in multiples conditions of the renal tubular system. There is a need to further elucidate their pathophysiology to better understand certain renal disorders and ultimately create new therapeutic targets to improve patient care.
CRIS-Team Scopus Importer:2023-01-20
Keywords: autosomal dominant polycystic kidney disease; ischemic injury; kidney; renal carcinoma; renal tubular system; transient receptor potential; TRPC3; TRPC6

Two-photon fluorescence lifetime imaging monitors metabolic changes during wound healing of corneal epithelial cells in vitro - Gehlsen, Uta; Oetke, Andrea; Szaszak, Marta; Koop, Norbert; Paulsen, Friedrich; Gebert, Andreas; Huettmann, Gereon; Steven, Philipp (Graefes Archive For Clinical and Experimental Ophthalmology, 2012)
Background Early and correct diagnosis of delayed or absent corneal epithelial wound healing is a key factor in the prevention of infection and consecutive destruction of the corneal stroma with impending irreversible visual loss. Two-photon microscopy (TPM) is a novel technology that has potential to depict epithelial cells and to evaluate cellular function by measuring autofluorescence properties such as fluorescence intensity and fluorescence lifetimes of metabolic co-factors such as NAD(P)H. Methods Using non-invasive TPM in a tissue-culture scratch model and an organ-culture erosion model, fluorescence intensity and fluorescence lifetimes of NAD(P)H were measured before and during closure of the epithelial wounds. Influence of temperature and selective inhibition of metabolism on intensity and lifetimes were tested additionally. Results Decrease of temperature resulted in significant increase of fluorescence lifetimes and decrease of the relative amount of free NAD(P)H due to decreased global metabolism. Increase in temperature and upregulation of glycolysis through blocking the mitochondrial electron transport chain by rotenone resulted in increased intensity, decreased lifetimes and increase in the relative amount of free NAD(P)H. Changes of lifetimes and free:protein-bound NAD(P)H ratios were similar to changes measured during wound healing in both scratch and erosion models. Conclusions Fluorescence lifetime measurements (FLIM) detected enhancement of cellular metabolism following epithelial damage in both models. The prospective detection of cellular autofluorescence in vivo, in particular FLIM of metabolic cofactor NAD(P)H, has the potential to become an indispensible tool in clinical use to differentiate healing from non-healing epithelial cells and to evaluate effects of newly developed substances on cellular metabolism in preclinical and clinical trials. © Springer-Verlag 2012.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Corneal epithelium; Metabolism; Two-photon microscopy; Wound healing

Two submucosal nerve plexus in human intestines - Brehmer, Axel; Rupprecht, Holger; Neuhuber, Winfried (Histochemistry and Cell Biology, 2010)
We examined the architecture of human submucosal nerve networks of gut segments derived from 12 individuals (each six from small and large intestines). Twelve undivided submucosal wholemounts were prepared and immunohistochemically stained for peripherin (nerve elements) and for α-smooth muscle actin (remnants of attached muscle bundles). We found two ganglionic nerve networks. The plexus submucosus externus was generally monolayered and located under the outermost surface of the submucosal wholemounts. Its nerve fibre strands frequently joined each other in acute or obtuse angles, the meshes of the network were relatively wide and frequently polyangular shaped. The plexus submucosus internus was generally multi-(mostly two-or three-)layered and occupied at least the inner half of the thickness of the wholemount, sometimes extending abluminally beyond the great submucosal vessels. Its meshes were irregular. The shapes of ganglia of the two plexus were generally different, those of the internal plexus were frequently grape-like whereas the neurons of external ganglia were mostly embedded in the contoures of the joining nerve fibres. Both plexus were intensely connected via coiled interconnecting strands, either with or without intercalated ganglia. For use of eponyms for two different submucosal plexus, the names of Meissner (inner) and Schabadasch (outer) are historically justified. © Springer-Verlag 2009.
Keywords: External; Henle; Intermediate; Internal; Meissner; Schabadasch

Ultrastructural changes associated with dexamethasone-induced ocular hypertension in mice - Overby, Darryl R.; Bertrand, Jacques; Tektas, Ozan Yüksel; Boussommier-Calleja, Alexandra; Schicht, Martin; Ethier, C. Ross; Woodward, David F.; Stamer, W. Daniel; Lütjen-Drecoll, Elke (Investigative Ophthalmology & Visual Science, 2014)
To determine whether dexamethasone (DEX)-induced ocular hypertension (OHT) in mice mimics the hallmarks of steroid-induced glaucoma (SIG) in humans, including reduced conventional outflow facility (C), increased extracellular matrix (ECM), and myofibroblasts within the outflow pathway.Osmotic mini-pumps were implanted subcutaneously into C57BL/6J mice for systemic delivery of DEX (3-4 mg/kg/d, n = 31 mice) or vehicle (n = 28). IOP was measured weekly by rebound tonometry. After 3 to 4 weeks, mice were euthanized and eyes enucleated for ex vivo perfusion to measure C, for electron microscopy to examine the trabecular meshwork (TM) and Schlemm's canal (SC), or for immunohistochemistry to examine type IV collagen and ?-smooth muscle actin. The length of basement membrane material (BMM) was measured along the anterior-posterior extent of SC by electron microscopy. Ultrastructural changes in BMM of DEX-treated mice were compared against archived human SIG specimens.Dexamethasone increased IOP by 2.6 ± 1.6 mm Hg (mean ± SD) over 3 to 4 weeks and decreased C by 52% ± 17% versus controls. Intraocular pressure elevation correlated with decreased C. Dexamethasone treatment led to increased fibrillar material in the TM, plaque-like sheath material surrounding elastic fibers, and myofibroblasts along SC outer wall. The length of BMM underlying SC was significantly increased in mice with DEX and in humans with SIG, and in mice decreased C correlated with increased BMM.Dexamethasone-induced OHT in mice mimics hallmarks of human SIG within 4 weeks of DEX treatment. The correlation between reduced C and newly formed ECM motivates further study using DEX-treated mice to investigate the pathogenesis of conventional outflow obstruction in glaucoma.
EVALuna2:4421

Ultrastructure of the lacrimal drainage system in health and disease: A major review - Ali, Mohammad Javed; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2019)
Purpose: To provide a systematic review of the literature on the ultrastructural findings of the lacrimal drainage system in healthy state and in few of the disorders studied so far. Methods: The authors performed a PubMed search of all articles published with reference to electron microscopic features of the lacrimal drainage pathways. Data captured include demographics, study techniques, scanning or transmission electron microscopic features, presumed or confirmed interpretations and their implications. Specific emphasis was laid on addressing the lacunae and potential directions for future research. Results: Ultrastructural studies have led to better understanding of the lacrimal drainage anatomy-physiology correlations. Cellular interactions between fibroblasts and lymphocytes could form a basis for pathogenesis of punctal stenosis. Ultrastructural characterization of peri-lacrimal cavernous bodies and changes in primary acquired nasolacrimal duct obstruction (PANDO) led to them being partly implicated in its etiopathogenesis. Electron microscopic characterization of the dacryolith core promises insights into their evolution. Ultrastructural tissue effects of mitomycin-C during a DCR surgery has provided potential evidence of its role in cases with high-risk of failure. Lacrimal stent biofilms are common but their clinical implications are currently uncertain. Conclusion: Ultrastructural exploration of lacrimal drainage system so far has been limited and sparsely explored. The list of unexplored areas is exhaustive. There is a need for the lacrimal Clinician-Scientist to make themselves familiar with techniques and interpretation of electron microscopy to advance the ultrastructural frontier of this science.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Lacrimal drainage; Lacrimal sac; Nasolacrimal duct; Scanning electron microscopy; SEM; Transmission electron microscopy; Ultrastructure

Understanding the Implications of Medicaid Expansion for Cancer Care in the US: A Review - Ermer, Theresa; Walters, Samantha L.; Canavan, Maureen E.; Salazar, Michelle C.; Li, Andrew X.; Doonan, Michael; Boffa, Daniel J. (JAMA Oncology, 2021)
Importance: Insurance status has been linked to important differences in cancer treatment and outcomes in the US. With more than 15 million individuals gaining health insurance through Medicaid expansion, there is an increasing need to understand the implications of this policy within the US cancer population. This review provides an overview of the fundamental principles and nuances of Medicaid expansion, as well as the implications for cancer care. Observations: The Patient Protection and Affordable Care Act presented states with an option to expand Medicaid coverage by broadening the eligibility criteria (eg, raising the eligible income level). During the past 10 years, Medicaid expansion has been credited with a 30% reduction in the population of uninsured individuals in the US. Such a significant change in the insurance profile could have important implications for the 1.7 million patients diagnosed with cancer each year, the oncology teams that care for them, and policy makers. However, several factors may complicate efforts to characterize the effect of Medicaid expansion on the US cancer population. Most notably, there is considerable variation among states in terms of whether Medicaid expansion took place, when expansion occurred, eligibility criteria for Medicaid, and coverage types that Medicaid provides. In addition, economic and health policy factors may be intertwined with factors associated with Medicaid expansion. Finally, variability in the manner in which cancer care has been captured and depicted in large databases could affect the interpretation of findings associated with expansion. Conclusions and Relevance: The expansion of Medicaid was a historic public policy initiative. To fully leverage this policy to improve oncological care and to maximize learning for subsequent policies, it is critical to understand the effect of Medicaid expansion. This review aims to better prepare investigators and their audiences to fully understand the implications of this important health policy initiative..
CRIS-Team Scopus Importer:2021-11-26

Unraveling the Local Relation Between Tissue Composition and Human Brain Mechanics Through Machine Learning - Linka, Kevin; Reiter, Nina; Würges, Jasmin; Schicht, Martin; Cyron, Christian J.; Paulsen, Friedrich; Budday, Silvia; Bräuer, Lars (Frontiers in Bioengineering and Biotechnology, 2021)
The regional mechanical properties of brain tissue are not only key in the context of brain injury and its vulnerability towards mechanical loads, but also affect the behavior and functionality of brain cells. Due to the extremely soft nature of brain tissue, its mechanical characterization is challenging. The response to loading depends on length and time scales and is characterized by nonlinearity, compression-tension asymmetry, conditioning, and stress relaxation. In addition, the regional heterogeneity–both in mechanics and microstructure–complicates the comprehensive understanding of local tissue properties and its relation to the underlying microstructure. Here, we combine large-strain biomechanical tests with enzyme-linked immunosorbent assays (ELISA) and develop an extended type of constitutive artificial neural networks (CANNs) that can account for viscoelastic effects. We show that our viscoelastic constitutive artificial neural network is able to describe the tissue response in different brain regions and quantify the relevance of different cellular and extracellular components for time-independent (nonlinearity, compression-tension-asymmetry) and time-dependent (hysteresis, conditioning, stress relaxation) tissue mechanics, respectively. Our results suggest that the content of the extracellular matrix protein fibronectin is highly relevant for both the quasi-elastic behavior and viscoelastic effects of brain tissue. While the quasi-elastic response seems to be largely controlled by extracellular matrix proteins from the basement membrane, cellular components have a higher relevance for the viscoelastic response. Our findings advance our understanding of microstructure - mechanics relations in human brain tissue and are valuable to further advance predictive material models for finite element simulations or to design biomaterials for tissue engineering and 3D printing applications.
Keywords: human brain; viscoelasticity; constitutive modeling; microstructure; mechanical properties; artificial neural network; extracellular matrix

Updated incidence of dry eye syndrome in Germany - Posa, A.; Sel, S.; Dietz, R.; Sander, R.; Bräuer, Lars; Paulsen, Friedrich (Klinische Monatsblätter für Augenheilkunde, 2014)
Dry eye is one of the most common eye surface disorders. Patients suffer in particular from annoying subjective symptoms that compromise quality of life. The aim of the study was to find out when patients consult ophthalmologists in Germany and what symptoms they present.170 patients treated at ophthalmological practices in Bavaria, Saxony and Saxony-Anhalt with dry eye were surveyed regarding their symptoms.The majority of those questioned were 40 years of age or older (88 %) (average: 60), female (59 %) and described a variety of subjective symptoms (65 %). More than five different concurrent symptoms were named. There is a recognisable increase in cases - by more than 3.5 times - at the age of forty (in women) and fifty (in men).We hope to contribute with the data obtained to a more complete understanding of this highly complex pathological process. A further aim is to facilitate recognition of this mostly chronic condition in its early stages when the symptoms are still poorly defined. The data on the German population obtained here should become part of a comparative analysis within the international context. Despite considerable scientific effort, dry eye remains a difficult challenge for both patients and attending physicians.
EVALuna2:4437

Upregulation of Transient Receptor Potential Vanilloid Type-1 Channel Activity and Ca2+ Influx Dysfunction in Human Pterygial Cells - Garreis, Fabian; Schröder, Antje; Reinach, Peter S.; Zoll, Stefanie; Khajavi, Noushafarin; Dhandapani, Priyavathi; Lucius, Alexander; Pleyer, Uwe; Paulsen, Friedrich; Mergler, Stefan (Investigative Ophthalmology & Visual Science, 2016)
PURPOSE: The heat-sensitive transient receptor potential vanilloid type-1 (TRPV1) channel (i.e., capsaicin [CAP] receptor) is upregulated in numerous cancers. This study determined if this response occurs in fresh and cultured hyperplastic human pterygial epithelial tissues. METHODS: Reverse transcriptase PCR and quantitative real-time PCR, along with immunohistochemistry and Western blotting, characterized TRPV1 expression patterns in pterygial and healthy conjunctival tissue, primary and immortalized pterygial cells (hPtEC), and primary and immortalized conjunctival epithelial cells (HCjEC). Imaging of Ca2+ and planar whole-cell patch-clamping evaluated TRP channel activity. An MTS assay measured cell metabolic activity and a cell growth assay monitored proliferation. RESULTS: Capsaicin (20 μM) and elevating bath temperature above 43°C activated Ca2+ transients more in hPtEC than HCjEC. Capsaicin induced corresponding changes in inward currents that were inhibited by 20 μM capsazepine (CPZ). Vascular endothelial growth factor (VEGF) also increased Ca2+-influx and induced corresponding inward currents more in hPtEC than in HCjEC, whereas CPZ (20 μM), BCTC (20 μM), or La3+ (500 μM) reduced these responses, respectively. Whereas epidermal growth factor (EGF) increased proliferation more in hPtEC than in HCjEC, VEGF had no effect on this response. Capsazepine suppressed hPtEC proliferation induced by EGF and VEGF, whereas it was cytotoxic to HCjEC. CONCLUSIONS: Mitogenic responses to EGF and VEGF are mediated through TRPV1 transactivation. Only in hPtEC do the increases in proliferation induced by EGF exceed those in HCjEC. Therefore, TRPV1 is a potential drug target whose clinical relevance in treating pterygium warrants further assessment.
EVALuna2:35348

Urea and ocular surface: Synthesis, secretion and its role in tear film homeostasis - Singh, Swati; Hammer, Christian; Paulsen, Friedrich (Ocular Surface, 2023)
Urea has been detected in the tear film, aqueous humor, and vitreous of the eye. While most of the urea in the aqueous humor and vitreous is considered to be an ultrafiltrate from the blood vessels, the presence of urea transporters and urea-synthesizing enzymes in the lacrimal gland, meibomian glands, conjunctiva, and cornea suggests ureagenesis occurring at the ocular surface. This review summarizes the distribution and function of urea transporters, urea and its synthesizing enzymes at the ocular surface to analyze their role in the tear film homeostasis. Urea transporters (UT)-A- and UT-B-as well as the enzymes arginase I, II, and agmatinase are located at the ocular surface. Urea concentration on the ocular surface is influenced by blood urea concentration, the amount of urea released by the tear fluid, tear evaporation, and arginase concentration in the tears. There are conflicting reports on the relationship between tear and plasma urea levels though a linear correlation exists between their levels. Urea protects the ocular surface from osmotic stress and is thought to maintain a lipid-water interface in the lamellar phase of the tear film. The reduction of urea levels in the tears of patients with evaporative dry eye suggests its possible role in tear film stability. Other than mitigating osmotic stress, urea has hydrating properties as well. Animal studies have demonstrated the healing effects of urea on the corneal epithelium. Future studies examining the variations in urea content in tears from different ocular surfaces, at different times of day, and under different environmental conditions would further solidify the role of urea in tear film stability.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Dry eye disease; Ocular surface; Tear film; Urea; Urea transporters

Urea transporter-B expression on the ocular surface and in the lacrimal glands - Jäger, Franziska; Paulsen, Friedrich; Bergua, Antonio; Jungbauer, Rebecca; Hammer, Christian (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Objective: Urea is a component of tear fluid showing a significantly decreased concentration in dry eye disease. The urea content of tear fluid may depend on urea transporters. The purpose of this study was to examine the expression of urea transporter B (UT-B) at the ocular surface and in the lacrimal glands. Methods: UT-B protein and mRNA expression was investigated in human, porcine, and murine samples. Immunohistochemical staining for UT-B was performed on paraffin sections of human, porcine, and murine corneas, eyelids, and lacrimal glands (n = 5 each). Reverse transcriptase polymerase chain reaction was conducted to detect UT-B mRNA in human and murine cornea, conjunctiva, Meibomian gland, and lacrimal gland (n = 5 each). Results: UT-B protein expression was comparable in all three species. It was found in the corneal epithelium and endothelium, in the conjunctival epithelium, in the end pieces and excretory ducts of the lacrimal gland, Meibomian gland, and in the glands of Moll and Zeis. The glands of Zeis and the Meibomian glands showed intense UT-B signals in the basal layers of the alveolar epithelia and in the cells of the ductal epithelia. UT-B mRNA was detected in all samples analyzed. Conclusion: UT-B is expressed by the cells and tissues of the ocular surface and in the lacrimal glands. Potential changes in urea transporter expression might have implications for the pathogenesis of dry eye disease. Since comparable results were obtained for all species investigated, the presented findings may open the door for DED-relevant experimentation on porcine and murine model systems.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Dry eye disease; Dry eye syndrome; Lacrimal apparatus; Lacrimal functional unit; Meibomian gland dysfunction; Ocular surface; Tear film; Urea transporter

Usability of abattoir-acquired pig eyes for refractive excimer laser research - Topka, Marius; Zhang, Yao; Bock, Antonia; Riedel, Peter; Lörner, Johannes; Hammer, Alexander; Maier, Eva; Paulsen, Friedrich; Hammer, Christian (Scientific Reports, 2021)
The purpose of this study was to elucidate, under which conditions abattoir-acquired pig eyes are suitable for refractive excimer laser experiments. Porcine eyes from tunnel-scalded (n = 5) and tank-scalded (n = 10) pigs were compared to unscalded eyes (n = 5) and to eyes scalded in the laboratory (n = 5). The corneal epithelium was removed before an excimer laser was used to perform a − 8.0 D photoablation. Corneal thickness was measured by optical coherence topography before and after photoablation. The ablation depth was determined with a contour measuring station, the morphology of the ablated areas was characterized by scanning electron microscopy and white-light profilometry. The scalded eyes showed an increase in corneal swelling which gained statistical significance in tank-scalded eyes showing a wedge-shaped opaque stromal lesion in the nasal corneal quadrant. A measurable deterioration of photoablation was only found in tank-scalded eyes that exhibited the opaque lesion. Ablated area morphology was smooth and regular in the unscalded and tunnel-scalded eyes. The tank-scalded eyes showed conspicuous wrinkles. While unscalded eyes should always be preferred for excimer laser laboratory experiments, the data suggest that the use of tunnel-scalded eyes may also be acceptable and should be chosen over tank-scalded eyes.
CRIS-Team Scopus Importer:2021-10-08

Vagal mechanisms as neuromodulatory targets for the treatment of metabolic disease - Berthoud, Hans Rudolf; Neuhuber, Winfried (Annals of the New York Academy of Sciences, 2019)
With few effective treatments available, the global rise of metabolic diseases, including obesity, type 2 diabetes mellitus, and cardiovascular disease, seems unstoppable. Likely caused by an obesogenic environment interacting with genetic susceptibility, the pathophysiology of obesity and metabolic diseases is highly complex and involves crosstalk between many organs and systems, including the brain. The vagus nerve is in a key position to bidirectionally link several peripheral metabolic organs with the brain and is increasingly targeted for neuromodulation therapy to treat metabolic disease. Here, we review the basics of vagal functional anatomy and its implications for vagal neuromodulation therapies. We find that most existing vagal neuromodulation techniques either ignore or misinterpret the rich functional specificity of both vagal efferents and afferents as demonstrated by a large body of literature. This lack of specificity of manipulating vagal fibers is likely the reason for the relatively poor beneficial long-term effects of such therapies. For these therapies to become more effective, rigorous validation of all physiological endpoints and optimization of stimulation parameters as well as electrode placements will be necessary. However, given the large number of function-specific fibers in any vagal branch, genetically guided neuromodulation techniques are more likely to succeed.
CRIS-Team Scopus Importer:2019-07-16
Keywords: anti-inflammatory pathways; diabetes; electrical stimulation; genetically guided; gut–brain communication; neuromodulation; obesity; vagotomy

Valvular system of the lacrimal drainage pathway and the valve of Rosenmüller - Gaca, Piotr J.; Heindl, Ludwig M.; Paulsen, Friedrich; Ali, Mohammad Javed (Annals of Anatomy-Anatomischer Anzeiger, 2023)
The valves of the lacrimal drainage system are an enigma with a rich eponymous history. The unidirectional flow of tears along with the ultrastructural demonstration of distinctive mucosal folds on the luminal surface has rekindled an interest in them. The first in vivo direct demonstration of the valve of Rosenmüller and its functions has laid to rest some of the controversies of its existence and that of the valve of Huschke. The dynamic assessment of the valve of Rosenmüller has shown a well-defined functional role in the facilitation of unidirectional tear flow. The present mini review describes the embryological aspects, brief overview of the eponymous valves, techniques for their identification along with recent structural and functional aspects of the valve of Rosenmüller.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Embryology; Hasner; Lacrimal; Nasolacrimal duct; Rosenmüller; Valve

Vascular Endothelial Growth Factor (VEGF) Induced Downstream Responses to Transient Receptor Potential Vanilloid 1 (TRPV1) and 3-Iodothyronamine (3-T1AM) in Human Corneal Keratocytes - Tuerker, Ersal; Garreis, Fabian; Khajavi, Noushafarin; Reinach, Peter S.; Joshi, Pooja; Brockmann, Tobias; Lucius, Alexander; Ljubojevic, Nina; Turan, Elizabeth; Cooper, Drew; Schick, Felix; Reinholz, Rob; et al. (Frontiers in Endocrinology, 2018)
This study was undertaken to determine if crosstalk among the transient receptor potential (TRP) melastatin 8 (TRPM8), TRP vanilloid 1 (TRPV1), and vascular endothelial growth factor (VEGF) receptor triad modulates VEGF-induced Ca2+ signaling in human corneal keratocytes. Using RT-PCR, qPCR and immunohistochemistry, we determined TRPV1 and TRPM8 gene and protein coexpression in a human corneal keratocyte cell line (HCK) and human corneal cross sections. Fluorescence Ca2+ imaging using both a photomultiplier and a single cell digital imaging system as well as planar patch-clamping measured relative intracellular Ca2+ levels and underlying whole-cell currents. The TRPV1 agonist capsaicin increased both intracellular Ca2+ levels and whole-cell currents, while the antagonist capsazepine (CPZ) inhibited them. VEGF-induced Ca2+ transients and rises in whole-cell currents were suppressed by CPZ, whereas a selective TRPM8 antagonist, AMTB, increased VEGF signaling. In contrast, an endogenous thyroid hormone-derived metabolite 3-Iodothyronamine (3-T1AM) suppressed increases in the VEGF-induced current. The TRPM8 agonist menthol increased the currents, while AMTB suppressed this response. The VEGF-induced increases in Ca2+ influx and their underlying ionic currents stem from crosstalk between VEGFR and TRPV1, which can be impeded by 3-T1AM-induced TRPM8 activation. Such suppression in turn blocks VEGF-induced TRPV1 activation. Therefore, crosstalk between TRPM8 and TRPV1 inhibits VEGFR-induced activation of TRPV1.
EVALuna2:35299

Vascularization of the dorsal base of the second metacarpal bone: an anatomical study using C-arm cone beam computed tomography - Bermel, Christina; Saalabian, Ali A.; Horch, Raymund E.; Dörfler, Arnd; Alexiou, Christoph; Lyer, Stefan; Neuhuber, Winfried; Arkudas, Andreas; Kneser, Ulrich (Plastic and Reconstructive Surgery, 2014)
Vascularized bone grafts of the hand are a promising option for treatment of hand abnormalities. Therefore, the purpose of this study was to analyze the arterial anatomy of the dorsal aspect of the second metacarpal base to further investigate this possible donor site for bone grafts.The authors examined 16 fresh frozen cadaveric hands by using a C-arm cone beam computed tomography scanner and depicted the three-dimensional course of the second dorsal metacarpal artery and measured the diameter, length, and arc of rotation of this nutritive vessel. In addition, the authors dissected six of the hands under a dissecting microscope and, after selective injection of gelatin dye solution, the authors analyzed the vessel entrances into the bones histologically.In all examined hands, the second dorsal metacarpal artery was a nutritive vessel to the dorsal base of the second metacarpal. The average diameter was 1.3±0.4 mm and the average length of the vascular pedicle was approximately 3.3±0.3 cm. In 14 of 16 cases, the arc of rotation was sufficient to reach the lunate without difficulty. Histologic analysis showed an intrinsic blood supply in the donor region with a vessel diameter of approximately 58 ?m. A clinical case with application in Kienböck disease is presented.Pedicled vascularized bone grafts from this area are suitable for clinical application to treat Kienböck disease if standard donor sites are unavailable.
EVALuna2:4144

VIP changes during daytime in chicken intrinsic choroidal neurons - Hohberger, Bettina; Jeßberger, Carmen; Hermann, Franz; Zenkel, Matthias; Kaser-Eichberger, Alexandra; Bergua, Antonio; Juenemann, Anselm G.; Schrödl, Falk; Neuhuber, Winfried (Experimental Eye Research, 2018)
PURPOSE: Ocular autonomic control is mediated by sympathetic and parasympathetic nerve fibres. Their interactions are complemented by primary afferent nerve fibers of and intrinsic choroidal neurons (ICN). As the vasodilatative neuropeptide, vasoactive intestinal peptide (VIP), is expressed in extrinsic and intrinsic ocular neurons, it is of special interest in ophthalmic research. Since circadian changes of ocular blood flow are known in humans and birds, this study aimed at investigating VIP expression at different daytimes in chicken choroid, the preferred model species in ICN research. METHODS: 12 eyes of 12 chickens were retrieved, slaughtered at 8.00-9.30 a.m. (n = 6) and 8.00 p.m. (n = 6), respectively, and choroidal wholemounts were prepared for immunofluorescence of VIP. VIP-positive ICN of both groups were quantified and density of VIP-positive axons assessed semi-quantitatively. In 28 additional eyes retrieved in the morning (n = 14) and evening (n = 14), choroidal VIP content was determined by ELISA. Morning and evening data were analyzed statistically. NADPH-diaphorase (NADPH-d, ICN cell marker) was done at additional 12 whole mount choroids of 12 chicken, retrieved in the morning (n = 6) and evening (n = 6). RESULTS: (1) Numbers of VIP positive neurons differed significantly between morning: (239.17 ± 113.9) and evening: (550.83 ± 245.7; p = 0.018). (2) Numbers of VIP-positive perikarya were significantly more accumulated in the temporal part of the choroid in the evening than in the morning (p = 0.026). (3) VIP positive axon density was found to be similar throughout the choroid in the morning and evening. (4) Number of NADPH-d positive neurons was not significantly different between morning (848.8 ± 399.5) and evening (945.8 ± 622.1, p > 0.05). (5) ELISA demonstrated a significant difference of VIP content (p = 0.012) in tissues harvested in the morning (145.41 ± 43.3 pg/ml) compared to evening (221.44 ± 106.3 pg/ml). CONCLUSIONS: As VIP positive axon density was similar in the morning and the evening throughout the choroid, PPG and ICN seemed to contribute equally to the axon network. Yet, changes in the total choroidal VIP content, the numbers of VIP positive perikarya, reflecting the intracellular VIP content, and their topographical distribution at two different days-times argue for a different status of activation of both neuronal sources in contrast to the equal amount of NADPHD-d positive neurons. The higher VIP content in the evening, compared to the morning, correlates with a known circadian rhythm of a lower IOP and a higher choroidal thickness at night. Thus, these changes may argue for a potential role of ICN in the regulation of ocular homeostasis and integrity.
EVALuna2:34748

Vulnerable in the end – Longitudinal study among medical students on mental health and personal and work-related resources over a 5.5-year-period - Schneider, Kurt; Breuer, G.; Luibl, Lena; Paulsen, F.; Scholz, Michael; Burger, P. H.M. (Annals of Anatomy-Anatomischer Anzeiger, 2023)
Background: Mental health problems are common in medical professionals and their development already starts at the undergraduate level. Studies on medical students can replicate higher prevalence for depression and burnout in this group, but they normally compare semester cohorts in an anonymized, cross-sectional approach and without a preventive perspective. Methods: We surveyed medical students at the beginning and end of their medical curriculum and collected data on burnout, depressivity, work related experience and salutogenesis parameters with validated self-administered questionnaires. Most remarkably we obtained the data from the same 58 individuals after 5.5 years, representing data of the highest quality in order to compare the mental health status at the beginning and the end of our students´ medical curriculum. Results: Our results not only show a severe exacerbation of physical, mental and emotional burnout in the participants at the end of their studies. The students also do not seem to have sufficient personal (resilience) or social resources (e.g. experience of social support) for coping with their mental health problems around the time of their graduation. Conclusions: Our participants reflect a development of mental health during their medical studies at university that is paving the way to the devastating prevalence of mental disorders and suicide in health professionals. From our results we derive an urgent need to integrate self-care and active coping in the learning goals of medical curricula.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Burnout; Healthcare Professional; Mental Health; Resilience

What drives Meibomian gland disease? - Paulsen, Friedrich; Garreis, Fabian (Archivos de la Sociedad Española de Oftalmología, 2014)
EVALuna2:4435

What neurons hide behind calretinin immunoreactivity in the human gut? - Beuscher, Nicholas; Jabari, Samir; Strehl, Johanna; Neuhuber, Winfried; Brehmer, Axel (Histochemistry and Cell Biology, 2014)
Calretinin (CALR) is often used as an immunohistochemical marker for the histopathological diagnosis of human intestinal neuropathies. However, little is known about its distribution pattern with respect to specific human enteric neuron types. Prior studies revealed CALR in both myenteric and submucosal neurons, most of which colabel with choline acetyl transferase (ChAT). Here, we specified the chemical code of CALR-positive neurons in small and large intestinal wholemounts in a series of 28 patients. Besides other markers, we evaluated the labeling pattern of CALR in combination with vasoactive intestinal peptide (VIP). In colonic submucosa, CALR and VIP were almost completely colocalized in about three-quarters of all submucosal neurons. In the small intestinal submucosa, both the colocalization rate of CALR and VIP as well as the proportion of these neurons were lower (about one-third). In the myenteric plexus of both small intestine and colon, CALR amounted to 11 and 10 %, respectively, whereas VIP to 5 and 4 % of the whole neuron population, respectively. Colocalization of both markers was found in only 2 and 3 % of myenteric neurons, respectively. In section specimens, nerve fibers coreactive for CALR and VIP were found in the mucosa but not in the muscle coat. Summarizing the present and earlier results, CALR was found in at least one submucosal and two myenteric neuron populations. Submucosal CALR+/VIP+/ ChAT± neurons innervate mucosal structures. Furthermore, CALR immunoreactivity in the myenteric plexus was observed in morphological type II (supposed primary afferent) and spiny type I (supposed inter- or motor-) neurons. © 2013 Springer-Verlag.
Keywords: Calcium-binding protein; Enteric nervous system; Neuron type; nNOS; Somatostatin

Wound healing in rabbit corneas after flapless refractive lenticule extraction with a 345 nm ultraviolet femtosecond laser - Hammer, Christian M.; Petsch, Corinna; Klenke, Joerg; Skerl, Katrin; Wuellner, Christian; Donitzky, Christof; Paulsen, Friedrich; Scholz, Michael; Seiler, Theo; Kruse, Friedrich; Menzel-Severing, Johannes (Journal of Cataract and Refractive Surgery, 2017)
PURPOSE: To characterize corneal wound healing in a rabbit model after flapless refractive lenticule extraction with a 345 nm ultraviolet femtosecond laser. SETTING: Departments of Ophthalmology and Anatomy II, University of Erlangen-Nürnberg and Wavelight GmbH, Erlangen, Germany. DESIGN: Experimental study. METHODS: Flapless refractive lenticule extraction was performed in 1 eye each of 20 New Zealand white rabbits (-5.0 diopters). Groups of 4 animals were euthanized after 48 hours, 1 week, 2 weeks, 4 weeks, and 3 months, respectively. Corneal samples were prepared for histology and fluorescence microscopy. To assess corneal cell death, proliferation, and myofibroblastic transdifferentiation, terminal uridine deoxynucleotidyl nick end-labeling (TUNEL) assay as well as immunostaining for Ki67 and α-smooth muscle actin (αSMA) were performed on sagittal cryosections. RESULTS: Histology revealed a zone of keratocyte depletion with a thickness of approximately 50 μm around the extraction site. At 48 hours, pronounced TUNEL staining of keratocytes was detected around the interface (159.9 cells/mm ± 18.4 [SD]), which steadily decreased to 74.9 ± 19.8 cells/mm at 1 week and 5.7 ± 4.8 cells/mm at 2 weeks. Ki67 staining of keratocytes was evident at 48 hours (10.0 ± 3.8 cells/mm), which then decreased at 1 week (5.2 ± 1.7 cells/mm) and 2 weeks (0.4 ± 0.5 cells/mm). From 4 weeks onward, no TUNEL or Ki67 staining was detected. The corneal stroma was αSMA-negative at all timepoints. CONCLUSION: Application of the 345 nm laser showed no signs of problematic repair processes in the cornea, which supports the initiation of the clinical phase.
EVALuna2:35326

XCR1 expression distinguishes human conventional dendritic cell type 1 with full effector functions from their immediate precursors - Heger, Lukas; Hatscher, Lukas; Liang, Chunguang; Lehmann, Christian; Amon, Lukas; Lühr, Jennifer J.; Kaszubowski, Tomasz; Nzirorera, Rayk; Schaft, Niels; Dörrie, Jan; Irrgang, Pascal; Tenbusch, Matthias; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Dendritic cells (DCs) are major regulators of innate and adaptive immune responses. DCs can be classified into plasmacytoid DCs and conventional DCs (cDCs) type 1 and 2. Murine and human cDC1 share the mRNA expression of XCR1. Murine studies indicated a specific role of the XCR1-XCL1 axis in the induction of immune responses. Here, we describe that human cDC1 can be distinguished into XCR1- and XCR1+ cDC1 in lymphoid as well as nonlymphoid tissues. Steady-state XCR1+ cDC1 display a preactivated phenotype compared to XCR1- cDC1. Upon stimulation, XCR1+ cDC1, but not XCR1- cDC1, secreted high levels of inflammatory cytokines as well as chemokines. This was associated with enhanced activation of NK cells mediated by XCR1+ cDC1. Moreover, XCR1+ cDC1 excelled in inhibiting replication of Influenza A virus. Further, under DC differentiation conditions, XCR1- cDC1 developed into XCR1+ cDC1. After acquisition of XCR1 expression, XCR1- cDC1 secreted comparable level of inflammatory cytokines. Thus, XCR1 is a marker of terminally differentiated cDC1 that licenses the antiviral effector functions of human cDC1, while XCR1- cDC1 seem to represent a late immediate precursor of cDC1.
CRIS-Team Scopus Importer:2023-08-25
Keywords: antiviral immunity; cDC1; DC differentiation; IL-12; XCR1

X-ray dose-enhancing impact of functionalized Au-Fe3O4nanoheterodimers on MCF-7 and A549 multicellular tumor spheroids - Klein, Stefanie; Distel, Luitpold; Neuhuber, Winfried (ACS Applied Bio Materials, 2021)
The efficiency of nanoparticle-enhanced radiotherapy was studied by loading MCF-7 and A549 multicellular tumor spheroids (MCTSs) with caffeic acid- and nitrosoniumfunctionalized Au-Fe3O4 nanoheterodimers (Au-Fe3O4 NHDs). Transmission electron microscope images of MCTS crosssectional sections visualized the invasion and distribution of the nitrosonium- and caffeic acid-functionalized Au-Fe3O4 NHDs (NO- and CA-NHDs) in the A549 and MCF-7 MCTSs, whereas the iron content of the MCTSs were quantified using the ferrozine assay. The synergistic impact of intracellular NO- and CA-NHDs and X-ray irradiation on the growth dynamics of the A549 and MCF-7 MCTSs was surveyed by monitoring their temporal evolution under a light microscope over a period of 14 days. The emergence of hypoxia during the spheroid growth was followed by detecting the lactate efflux of MCTSs without and with NO- and CA-NHDs. The performance of the NO- and CA-NHDs as X-ray dose-enhancing agents in the A549 and MCF-7 MCTSs was clarified by performing clonogenic cell survival assays and determining the respective dose-modifying factors for X-ray doses of 0, 2, 4, and 6 Gy. The NO- and CA-NHDs were shown to perform as potent X-ray dose-enhancing agents in A549 and MCF-7 MCTSs. Moreover, the CA-NHDs boosted their radio-sensitizing efficacy by inhibiting the lactate efflux as impairing metabolic reprogramming. A synergistic effect on the MCTS destruction was observed for the combination of both NHDs since the surfactants differ in their antitumor effect.
CRIS-Team Scopus Importer:2021-04-16
Keywords: A549 cells; Au-Fe; MCF-7 cells; Multicellular tumor spheroids; X-ray dose enhancement

Osteopathic treatment approach to psychoemotional trauma by means of bifocal integration - Liem, Torsten; Neuhuber, Winfried (The Journal of the American Osteopathic Association, 2020)
Traumatic psychoemotional experiences often manifest in hypersympathetic states of excitement or in immobilization and withdrawal behaviors. A person with this kind of traumatic background may present with an autonomic response consistently maintained in the defensive state, which over time becomes a stressor. In this article, the authors discuss an osteopathic approach to psychoemotional trauma by means of bifocal integration, with an emphasis on promoting a relaxed body and mind by actively involving the patient in the healing process. They briefly discuss the role of mind-body therapies in treatment, considering the popular polyvagal theory and other neuropsychophysiological frameworks. The authors also focus on clinical practice, introducing the reader to the different elements of the osteopathic treatment, including the acknowledgement and integration of top-down and bottom-up dynamics in diagnosis and therapy.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Emotional integration; Mind-body therapy; Psychoemotional trauma; Trauma